AAV-induced re-expression of Dp71 in retinal Muller glial cells recovers electroretinographic responses in Dp71-null mice - Salgueiro Barboni, Mirella Telles; Vaillend, Cyrille; Joachimsthaler, Anneka; Liber, Andre; Khabou, Hanen; Roux, Michel J.; Vignaud, Lucile; Dalkara, Deniz; Guillonneau, Xavier; Ventura, Dora; Rendon, Alvaro; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Absence of ocular interaction in flicker ERG responses reflecting cone opponent and luminance signals - Salgueiro Barboni, Mirella Telles; Ventura, Dora Fix; Kremers, Jan (Documenta Ophthalmologica, 2010)
The aim of the study was to investigate whether there is an ocular interaction in the flicker ERG responses reflecting luminance and cone opponency in normal human subjects. Flicker ERGs were recorded from one dilated eye of 10 healthy volunteers. Each subject was tested twice: once with and once without occluding the opposite eye. Red and green LEDs were modulated in counterphase in a Ganzfeld stimulator. ERG responses were recorded for different ratios of the modulation in the red and green LEDs and at 12 and 36 Hz. The amplitudes and phases of the fundamental components were compared between the conditions with and without occlusion. The 12-Hz flicker ERGs reflected activity of the cone opponent channel, whereas the 36-Hz data reflected luminance activity. There were no significant differences between the conditions with and without occluding the opposite eye for any of the stimulus protocols. Ocular interaction is absent in flicker ERGs reflecting cone opponent and luminance activity.
Keywords: Ocular interaction; Electroretinogram; Luminance; Cone opponency

Accumulation of T-cell-suppressive PD-L1 high extracellular vesicles is associated with GvHD and might impact GvL efficacy - Baur, Rebecca; Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Völkl, Simon; Gießl, Andreas; Flamann, Cindy; Bruns, Heiko; Schlötzer-Schrehardt, Ursula; Böttcher, Martin; Schewe, Denis M.; Fischer, Thomas; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents the only curative treatment option for a number of hemato-oncological disorders. In fact, allo-HSCT is considered as one of the most successful immunotherapies as its clinical efficacy is based on the donor T-cells' capacity to control residual disease. This process is known as the graft-versus-leukemia (GvL) reaction. However, alloreactive T-cells can also recognize the host as foreign and trigger a systemic potentially life-threatening inflammatory disorder termed graft-versus-host disease (GvHD). A better understanding of the underlying mechanisms that lead to GvHD or disease relapse could help us to improve efficacy and safety of allo-HSCT. In recent years, extracellular vesicles (EVs) have emerged as critical components of intercellular crosstalk. Cancer-associated EVs that express the immune checkpoint molecule programmed death-ligand 1 (PD-L1) can suppress T-cell responses and thus contribute to immune escape. At the same time, it has been observed that inflammation triggers PD-L1 expression as part of a negative feedback network. Here, we investigated whether circulating EVs following allo-HSCT express PD-L1 and tested their efficacy to suppress the ability of (autologous) T-cells to effectively target AML blasts. Finally, we assessed the link between PD-L1 levels on EVs to (T-)cell reconstitution, GvHD, and disease relapse. We were able to detect PD-L1 + EVs that reached a peak PD-L1 expression at 6 weeks post allo-HSCT. Development of acute GvHD was linked to the emergence of PD-L1 high EVs following allo-HSCT. Moreover, PD-L1 levels correlated positively with GvHD grade and declined (only) on successful therapeutic intervention. T-cell-inhibitory capacity was higher in PD-L1 high EVs as compared with their PD-L1 low counterparts and could be antagonized using PD-L1/PD-1 blocking antibodies. Abundance of T-cell-suppressive PD-L1 high EVs appears to also impact GvL efficacy as patients were at higher risk for relapse. Finally, patients of PD-L1 high cohort displayed a reduced overall survival.Taken together, we show that PD-L1-expressing EVs are present following allo-HSCT. PD-L1 levels on EVs correlate with their ability to suppress T-cells and the occurrence of GvHD. The latter observation may indicate a negative feedback mechanism to control inflammatory (GvHD) activity. This intrinsic immunosuppression could subsequently promote disease relapse.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Immune Evation; T-Lymphocytes; Transplantation Immunology

A Close Look at the Clinical Efficacy of Rho-Associated Protein Kinase Inhibitor Eye Drops for Fuchs Endothelial Corneal Dystrophy - Kinoshita, Shigeru; Colby, Kathryn A.; Kruse, Friedrich (Cornea, 2021)
ABSTRACT: The current understanding on the clinical efficacy of Rho-associated protein kinase (ROCK) inhibitor for treating Fuchs endothelial corneal dystrophy is summarized to clarify whether the "off-label" ROCK-inhibitor eye-drop application are appropriate. ROCK-inhibitor eye drops may eventually be deemed a cutting-edge therapy for Fuchs endothelial corneal dystrophy patients with acute corneal endothelial defect.
CRIS-Team Scopus Importer:2021-10-08

A common variant mapping to CACNA1A is associated with susceptibility to exfoliation syndrome - Aung, Tin; Ozaki, Mineo; Mizoguchi, Takanori; Allingham, R. Rand; Li, Zheng; Haripriya, Aravind; Nakano, Satoko; Uebe, Steffen; Harder, Jeffrey M.; Chan, Anita S. Y.; Lee, Mei Chin; Burdon, Kathryn P.; et al. (Nature Genetics, 2015)
Exfoliation syndrome (XFS) is the most common recognizable cause of open-angle glaucoma worldwide. To better understand the etiology of XFS, we conducted a genome-wide association study (GWAS) of 1,484 cases and 1,188 controls from Japan and followed up the most significant findings in a further 6,901 cases and 20,727 controls from 17 countries across 6 continents. We discovered a genome-wide significant association between a new locus (CACNA1A rs4926244) and increased susceptibility to XFS (odds ratio (OR) = 1.16, P = 3.36 × 10(-11)). Although we also confirmed overwhelming association at the LOXL1 locus, the key SNP marker (LOXL1 rs4886776) demonstrated allelic reversal depending on the ancestry group (Japanese: OR(A allele) = 9.87, P = 2.13 × 10(-217); non-Japanese: OR(A allele) = 0.49, P = 2.35 × 10(-31)). Our findings represent the first genetic locus outside of LOXL1 surpassing genome-wide significance for XFS and provide insight into the biology and pathogenesis of the disease.
EVALuna2:9286

A comparison of the suitability of cathode ray tube (CRT) and liquid crystal display (LCD) monitors as visual stimulators in mfERG diagnostics - Kaltwasser, Christoph; Horn, Folkert; Kremers, Jan; Jünemann, Anselm (Documenta Ophthalmologica, 2009)
The aim of this study was to determine up to which extent the specific characteristics of cathode ray tube (CRT) and liquid crystal display (LCD) monitors influence the retinal biosignal when used as stimulators in ocular electrophysiology. In a conventional CRT monitor, each pixel lights up only for a duration of a few milliseconds during each frame. In contrast, liquid crystal displays are quasi-static, i.e. each pixel has a constant luminance during the whole length of the frame, but lights up only with a certain delay after the trigger. These different display characteristics may affect the mfERG signal. The temporal and spatial luminance distributions of a CRT and an LCD monitor were measured in white flashes. The total amount of emitted light was calculated by integration of the intensity versus time curves. By means of an mfERG recording system (RETIsystem, Roland Consult, Brandenburg, Germany) first-order kernel (FOK) mfERG signals were computed and then analysed using customized MATLAB (TheMathWorks, Natick, MA, USA) software. With the two stimulator monitors, differences in the mfERG signal were observed. The latencies of mfERG responses recorded with the LCD monitor were significantly increased by 7.1 ms for N1 and 9.5 ms for P1 compared to the CRT. Due to a higher luminance, the N1 amplitude was significantly higher by approx. 2 dB in measurements with the LCD monitor while no significant difference could be detected with regard to the more contrast sensitive P1 amplitude. When using LCD monitors as stimulators the increase in latencies and differences in the luminance versus time profile must be taken into account. Prior to clinical application, the establishment of guidelines for the use of LCD monitors is recommended.
Keywords: CRT; LCD; Multifocal ERG; Stimulus delivery

A coorelation study between the novel stereo vision perception test (StereoViPer Test) and the frisby test for measuring distance stereopsis - Schmidt, Michael; Lochmann, Matthias; Eskofier, Björn; Michelson, Georg; Paulus, Jan; Tong, Jie (Investigative Ophthalmology & Visual Science, 2014)

Activation of TGF-β signaling induces cell death via the unfolded protein response in Fuchs endothelial corneal dystrophy - Okumura, Naoki; Hashimoto, Keisuke; Kitahara, Miu; Okuda, Hirokazu; Ueda, Emi; Watanabe, Kyoko; Nakahara, Makiko; Sato, Takahiko; Kinoshita, Shigeru; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; et al. (Scientific Reports, 2017)
Fuchs endothelial corneal dystrophy (FECD) is a slowly progressive bilateral disease of corneal endothelium in which accumulation of extracellular matrix (ECM) and loss of corneal endothelial cells (CECs) are phenotypic features. The corneal endothelium maintains corneal transparency by regulating water hydration; consequently, corneal endothelial dysfunction causes serious vision loss. The only therapy for corneal haziness due to corneal endothelial diseases, including FECD, is corneal transplantation using donor corneas, and no pharmaceutical treatment is available. We provide evidence that the expression levels of transforming growth factor-? (TGF-?) isoforms and TGF-? receptors are high in the corneal endothelium of patients with FECD. A cell model based on patients with FECD shows that TGF-? signaling induced a chronic overload of ECM proteins to the endoplasmic reticulum (ER), thereby enhancing the formation of unfolded protein and triggering the intrinsic apoptotic pathway through the unfolded protein response (UPR). We propose that inhibition of TGF-? signaling may represent a novel therapeutic target that suppresses cell loss as well as the accumulation of ECM in FECD.
EVALuna2:21350

Addition of liraglutide in patients with Type 2 diabetes well controlled on metformin monotherapy improves several markers of vascular function - Forst, T.; Michelson, Georg; Ratter, F.; Weber, M. M.; Anders, S.; Mitry, M.; Wilhelm, B.; Pfuetzner, A. (Diabetic Medicine, 2012)
The aim of this study was to investigate the vascular effects of liraglutide in patients well controlled on metformin monotherapy.Forty-four patients with Type 2 diabetes were included in the study. Main inclusion criteria were: pretreatment with metformin on a stable dosage, HbA(1c) < 53 mmol/mol (7.0%), age 30-65 years. Patients were randomized to receive additional liraglutide or to remain on metformin monotherapy. After 6 weeks (1.2 mg) and after 12 weeks (1.8 mg), venous blood was taken for the measurement of several laboratory markers characterizing vascular and endothelial function. In addition, retinal microvascular endothelial function and arterial stiffness were measured.HbA(1c) levels declined from 45 ± 4 mmol/mol (6.3 ± 0.4%; mean ± SD) to 40 ± 3 mmol/mol (5.8 ± 0.3%) during liraglutide treatment. Asymmetric dimethylarginin was reduced by liraglutide treatment from 0.39 ± 0.08 to 0.35 ± 0.06 ?mol/l, E-selectin from 43.6 ± 15.4 to 40.8 ± 15.1 ng/ml, plasminogen activator inhibitor 1 from 861.6 ± 584.3 to 666.1 ± 499.4 ng/ml and intact proinsulin from 9.0 ± 7.2 to 7.0 ± 4.8 pmol/l at 12 weeks of treatment. The microvascular response to flicker light increased from 7.0 ± 15.1 to 15.4 ± 11.5% after 6 weeks and to 11.1 ± 9.9% after 12 weeks. No change could be observed for high-sensitivity C-reactive protein, monocyte chemotactic protein 1, vascular cell adhesion molecule or arterial stiffness parameters.In patients with Type 2 diabetes, well controlled with metformin monotherapy, addition of liraglutide improves several cardiovascular risk markers beyond glycaemic control.
EVALuna2:21069

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Advances in Materials Science and Engineering, 2017)

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices. - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
In this work, polycaprolactone (PCL) was used as a basic polymer for electrospinning of random and aligned nanofiber matrices. Our aim was to develop a biocompatible substrate for ophthalmological application to improve wound closure in defects of the cornea as replacement for human amniotic membrane. We investigated whether blending the hydrophobic PCL with poly (glycerol sebacate) (PGS) or chitosan (CHI) improves the biocompatibility of the matrices for cell expansion. Human corneal epithelial cells (HCEp) and human corneal keratocytes (HCK) were used for in vitro biocompatibility studies. After optimization of the electrospinning parameters for all blends, scanning electron microscopy (SEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and water contact angle were used to characterize the different matrices. Fluorescence staining of the F-actin cytoskeleton of the cells was performed to analyze the adherence of the cells to the different matrices. Metabolic activity of the cells was measured by cell counting kit-8 (CCK-8) for 20days to compare the biocompatibility of the materials. Our results show the feasibility of producing uniform nanofiber matrices with and without orientation for the used blends. All materials support adherence and proliferation of human corneal cell lines with oriented growth on aligned matrices. Although hydrophobicity of the materials was lowered by blending PCL, no increase in biocompatibility or proliferation, as was expected, could be measured. All tested matrices supported the expansion of human corneal cells, confirming their potential as substrates for biomedical applications.

A dim view of M-cone onsets - Parry, Neil R. A.; Mckeefry, Declan J.; Kremers, Jan; Murray, Ian J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We investigated the brightness (i.e., perceived luminance) of isolated L- and M-cone pulses to seek a perceptual correlate of our previous reports that M-on electroretinograms resemble L-off responses, implying the operation of post-receptoral opponent processing. Using triple silent substitutions, cone increments were generated in a 4-primary ganzfeld, masked by random positive or negative luminance bias. The results show that M-cone increments decrease in brightness, while L-cone increments increase. These differences became smaller as field size reduced; this was not eccentricity or area dependent. We speculate about early retinal input into brightness perception.
EVALuna2:21291

A framework for voxel-based morphometric analysis of the optic radiation using diffusion tensor imaging in glaucoma - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Magnetic Resonance Imaging, 2011)
EVALuna2:21060

Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion

Agonistic autoantibodies against ß2-adrenergic receptor influence retinal microcirculation in glaucoma suspects and patients - Hohberger, Bettina; Hosari, Sami; Wallukat, Gerd; Kunze, Rudolf; Krebs, Johann Ferdinand; Müller, Magdalena; Hennig, Till; Lämmer, Robert; Horn, Folkert; Garcia Munoz, Luis Enrique; Herrmann, Martin; Mardin, Christian (PLoS ONE, 2021)
PURPOSE: Agonistic β2-adrenergic receptor autoantibodies (β2-agAAb) have been observed in sera of patients with ocular hypertension and open-angle glaucoma (OAG). They target the β2-receptors on trabecular meshwork, ciliary body and pericytes (Junemann et al. 2018; Hohberger et al. 2019). In addition to their influence on the intraocular pressure, an association to retinal microcirculation is discussed. This study aimed to investigate foveal avascular zone (FAZ) characteristics by en face OCT angiography (OCT-A) in glaucoma suspects and its relationship to β2-agAAb status in patients with OAG. MATERIAL AND METHODS: Thirty-four patients (28 OAG, 6 glaucoma suspects) underwent standardized, clinical examination including sensory testing as white-on-white perimetry (Octopus G1, mean defect, MD) and structural measures as retinal nerve fibre layer (RNFL) thickness, neuroretinal rim width (BMO-MRW), retinal ganglion cell layer (RGCL) thickness, and inner nuclear layer (INL) thickness with high-resolution OCT. FAZ characteristics were measured by OCT-A scans of superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). FAZ-R was calculated (area FAZ (SVP)/area FAZ (ICP)). Using cardiomyocyte bioassays we analysed serum samples for the presence of β2-agAAb. RESULTS: (I) Total mean FAZ area [mm2]: 0.34±0.16 (SVP), 0.24±0.12 (ICP), and 0.49±0.24 (DCP); mean FAZ-R 1.58±0.94. No correlation was seen for FAZ-R with MD, RNFL, BMO-MRW, RGCL thickness and INL thickness (p>0.05). (II) ß2-agAAb have been observed in 91% patients and showed no correlation with MD, RNFL, BMO-MRW, RGCL thickness and INL thickness (p>0.05). (III) FAZ-R correlated significantly with the β2-agAAb-induced increase of the beat rate of cardiomyocyte (p = 0.028). CONCLUSION: FAZ characteristics did not correlate with any glaucoma associated functional and morphometric follow-up parameter in the present cohort. However, level of β2-agAAb showed a significantly correlation with FAZ-ratio. We conclude that β2-agAAb might be a novel biomarker in glaucoma pathogenesis showing association to FAZ-ratio with OCT-A.
CRIS-Team Scopus Importer:2021-05-21

Agonistic Autoantibodies to the β2-Adrenergic Receptor Involved in the Pathogenesis of Open-Angle Glaucoma - Juenemann, Anselm; Hohberger, Bettina; Rech, Jürgen; Sheriff, Ahmed; Fu, Qin; Schlötzer-Schrehardt, Ursula; Voll, Reinhard Edmund; Bartel, Sabine; Kalbacher, Hubert; Hoebeke, Johan; Rejdak, Robert; Horn, Folkert; et al. (Frontiers in Immunology, 2018)
Glaucoma is a frequent ocular disease that may lead to blindness. Primary open-angle glaucoma (POAG) and ocular hypertension (OHT) are common diseases with increased intraocular pressure (IOP), which are mainly responsible for these disorders. Their pathogenesis is widely unknown. We screened the sera of patients with POAG and OHT for the prevalence of autoantibodies (AAb) against G protein-coupled receptors (GPCRs) in comparison to controls. Employing frequency modulation of spontaneously contracting neonatal rat cardiomyocytes in vitro, agonistic GPCR AAb were to be detected in roughly 75% of the patients with POAG and OHT, however, not in controls. Using inhibitory peptides the AAb' target was identified as β2 adrenergic receptor (β2AR). The AAb interact with the second extracellular loop of β2AR. The peptides 181-187 and 186-192 were identified as binding sites of the AAb within the extracellular loop II. The binding of the AAb to β2ARs was verified by surface-plasmon-resonance analysis. The isotype of the AAb was (immunoglobulin) IgG3. In an additional pilot principal-of-proof study, including four patients with POAG, the removal of the AAb against the β2AR and other immunoglobulins G by immunoadsorption resulted in a transient reduction of IOP. These findings might indicate a possible role of agonistic AAb directed against β2ARs in the dynamics of aqueous humor and might support a contribution of adaptive autoimmunity in the etiopathogenesis of POAG and OHT.
EVALuna2:33846

Agonistic beta2-adrenergic autoantibodies in glaucoma - Hohberger, Bettina (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Agonistic beta 2-adrenergic receptor autoantibodies characterize the aqueous humor of patients with primary and secondary open-angle glaucoma - Hohberger, Bettina; Woern, Max; Lämmer, Robert; Herrmann, Martin; Mardin, Christian; Kruse, Friedrich; Kunze, Rudolf; Wallukat, Gerd (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Agonistic beta 2-Adrenergic Receptor Autoantibodies Characterize the Aqueous Humor of Patients With Primary and Secondary Open-Angle Glaucoma - Hohberger, Bettina; Worn, Max; Lämmer, Robert; Mahajan, Aparna; Mardin, Christian; Schlötzer-Schrehardt, Ursula; Kunze, Rudolph; Herrmann, Martin; Wallukat, Gerd (Frontiers in Immunology, 2021)
Purpose
CRIS-Team WoS Importer:2021-05-28

Agonistic beta 2-Adrenergic Receptor Autoantibodies: Longitudinal analysis of the efficacy of beta-adrenoceptor antagonist on intraocular pressure - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Lämmer, Robert (2018)
EVALuna2:34742

Air Versus Sulfur Hexafluoride Gas Tamponade in Descemet Membrane Endothelial Keratoplasty: A Fellow Eye Comparison - von Marchtaler, Philipp; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2017)
To perform a fellow eye comparison of outcomes and complications when using air or sulfur hexafluoride (SF6) gas as a tamponade in Descemet membrane endothelial keratoplasty (DMEK).One hundred thirty-six eyes of 68 consecutive patients who underwent uneventful DMEK in both eyes for Fuchs endothelial corneal dystrophy were included in this retrospective study. Inclusion criteria were air tamponade (80% of the anterior chamber volume) in the first eye and 20% SF6 gas tamponade (80% of the anterior chamber volume) in the second eye; and same donor tissue culture condition in both eyes. All eyes received laser iridotomy on the day before DMEK. Main outcome measures included preoperative and postoperative best-corrected visual acuity, endothelial cell density, corneal volume, rebubbling rate, and rate of postoperative pupillary block caused by the air/gas bubble.Thirteen of 68 eyes (19.1%) with an air tamponade needed rebubbling compared with 4 of 68 eyes (5.9%) with an SF6 gas tamponade (P = 0.036). Postoperative pupillary block necessitating partial release of air/gas occurred in 1 eye (1.5%) with an air tamponade and 3 eyes (4.4%) with an SF6 gas tamponade (P = 0.301). There were no significant differences in preoperative and postoperative best-corrected visual acuity, endothelial cell density, and corneal volume within 3-month follow-up.Our results confirm the previously reported better graft adhesion when using an SF6 gas tamponade in DMEK without increased endothelial cell toxicity. The rate of pupillary block in eyes with an SF6 gas tamponade was comparable to that with an air tamponade. As a consequence, we recommend using SF6 gas as the tamponade in DMEK.
EVALuna2:21352

A Keypoint Detection and Description Network Based on the Vessel Structure for Multi-modal Retinal Image Registration - Sindel, Aline; Hohberger, Bettina; Fassihi Dehcordi, Sebastian; Mardin, Christian Y.; Lämmer, Robert; Maier, Andreas; Christlein, Vincent (Bildverarbeitung für die Medizin 2022, 2022)
Ophthalmological imaging utilizes different imaging systems, such as color fundus, infrared, fluorescein angiography, optical coherence tomography (OCT) or OCT angiography. Multiple images with different modalities or acquisition times are often analyzed for the diagnosis of retinal diseases. Automatically aligning the vessel structures in the images by means of multi-modal registration can support the ophthalmologists in their work. Our method uses a convolutional neural network to extract features of the vessel structure in multi-modal retinal images. We jointly train a keypoint detection and description network on small patches using a classification and a cross-modal descriptor loss function and apply the network to the full image size in the test phase. Our method demonstrates the best registration performance on our and a public multi-modal dataset in comparison to competing method

Akute unilaterale Sehstörung nach COVID-Impfung - Bachmann, P.; Mardin, Christian Y.; Bartsch, A. J.; Weller, Julia (Ophthalmologe, 2021)
CRIS-Team Scopus Importer:2021-10-01

Alouatta trichromatic color vision: cone spectra and physiological responses studied with microspectrophotometry and single unit retinal electrophysiology - Silveira, Luiz Carlos L.; Saito, Cezar A.; Da Silva Filho, Manoel; Kremers, Jan; Bowmaker, James K.; Lee, Barry B. (PLoS ONE, 2014)
The howler monkeys (Alouatta sp.) are the only New World primates to exhibit routine trichromacy. Both males and females have three cone photopigments. However, in contrast to Old World monkeys, Alouatta has a locus control region upstream of each opsin gene on the X-chromosome and this might influence the retinal organization underlying its color vision. Post-mortem microspectrophotometry (MSP) was performed on the retinae of two male Alouatta to obtain rod and cone spectral sensitivities. The MSP data were consistent with only a single opsin being expressed in each cone and electrophysiological data were consistent with this primate expressing full trichromacy. To study the physiological organization of the retina underlying Alouatta trichromacy, we recorded from retinal ganglion cells of the same animals used for MSP measurements with a variety of achromatic and chromatic stimulus protocols. We found MC cells and PC cells in the Alouatta retina with similar properties to those previously found in the retina of other trichromatic primates. MC cells showed strong phasic responses to luminance changes and little response to chromatic pulses. PC cells showed strong tonic response to chromatic changes and small tonic response to luminance changes. Responses to other stimulus protocols (flicker photometry; changing the relative phase of red and green modulated lights; temporal modulation transfer functions) were also similar to those recorded in other trichromatic primates. MC cells also showed a pronounced frequency double response to chromatic modulation, and with luminance modulation response saturation accompanied by a phase advance between 10-20 Hz, characteristic of a contrast gain mechanism. This indicates a very similar retinal organization to Old-World monkeys. Cone-specific opsin expression in the presence of a locus control region for each opsin may call into question the hypothesis that this region exclusively controls opsin expression.
EVALuna2:21215

Altered visual processing in the mdx52 mouse model of Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Liber, André Maurício Passos; Joachimsthaler, Anneka; Saoudi, Amel; Goyenvalle, Aurélie; Rendon, Alvaro; Roger, Jérome E.; Ventura, Dora Fix; Kremers, Jan; Vaillend, Cyrille (Neurobiology of Disease, 2021)
The mdx52 mouse model of Duchenne muscular dystrophy (DMD) is lacking exon 52 of the DMD gene that is located in a hotspot mutation region causing cognitive deficits and retinal anomalies in DMD patients. This deletion leads to the loss of the dystrophin proteins, Dp427, Dp260 and Dp140, while Dp71 is preserved. The flash electroretinogram (ERG) in mdx52 mice was previously characterized by delayed dark-adapted b-waves. A detailed description of functional ERG changes and visual performances in mdx52 mice is, however, lacking. Here an extensive full-field ERG repertoire was applied in mdx52 mice and WT littermates to analyze retinal physiology in scotopic, mesopic and photopic conditions in response to flash, sawtooth and/or sinusoidal stimuli. Behavioral contrast sensitivity was assessed using quantitative optomotor response (OMR) to sinusoidally modulated luminance gratings at 100% or 50% contrast. The mdx52 mice exhibited reduced amplitudes and delayed implicit times in dark-adapted ERG flash responses, particularly in their b-wave and oscillatory potentials, and diminished amplitudes of light-adapted flash ERGs. ERG responses to sawtooth stimuli were also diminished and delayed for both mesopic and photopic conditions in mdx52 mice and the first harmonic amplitudes to photopic sine-wave stimuli were smaller at all temporal frequencies. OMR indices were comparable between genotypes at 100% contrast but significantly reduced in mdx52 mice at 50% contrast. The complex ERG alterations and disturbed contrast vision in mdx52 mice include features observed in DMD patients and suggest altered photoreceptor-to-bipolar cell transmission possibly affecting contrast sensitivity. The mdx52 mouse is a relevant model to appraise the roles of retinal dystrophins and for preclinical studies related to DMD.
CRIS-Team Scopus Importer:2021-02-26
Keywords: B-wave; Dp140; Dp260; Dp427; Duchenne muscular dystrophy; Dystrophin; Electroretinogram; Mouse model; Photoreceptors; Retina

Alternative splicing and nonsense-mediated mRNA decay contribute to regulation of LOXL1 expression in response to cellular stress in pseudoexfoliation - Berner, Daniel; Zenkel, Matthias; Pasutto, Francesca; Schoedel, Johannes; Reis, André; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (2017)
EVALuna2:34538

A method for estimating intrinsic noise in electroretinographic (ERG) signals - Zele, Andrew J.; Feigl, Beatrix; Kambhampati, Pradeep K.; Hathibelagal, Amithavikram R.; Kremers, Jan (Documenta Ophthalmologica, 2015)
To develop a signal processing paradigm for extracting ERG responses to temporal sinusoidal modulation with contrasts ranging from below perceptual threshold to suprathreshold contrasts and estimate the magnitude of intrinsic noise in ERG signals at different stimulus contrasts.Photopic test stimuli were generated using a 4-primary Maxwellian view optical system. The 4-primary lights were sinusoidally temporally modulated in-phase (36 Hz; 2.5-50 % Michelson contrast). The stimuli were presented in 1-s epochs separated by a 1-ms blank interval and repeated 160 times (160.160-s duration) during the recording of the continuous flicker ERG from the right eye using DTL fibre electrodes. After artefact rejection, the ERG signal was extracted using Fourier transforms in each of the 1-s epochs where a stimulus was presented. The signal processing allows for computation of the intrinsic noise distribution in addition to the signal-to-noise (SNR) ratio.We provide the initial report that the ERG intrinsic noise distribution is independent of stimulus contrast, whereas SNR decreases linearly with decreasing contrast until the noise limit at 2.5 %. The 1-ms blank intervals between epochs de-correlated the ERG signal at the line frequency (50 Hz) and thus increased the SNR of the averaged response. We confirm that response amplitude increases linearly with stimulus contrast. The phase response shows a shallow positive relationship with stimulus contrast.This new technique will enable recording of intrinsic noise in ERG signals above and below perceptual visual threshold and is suitable for measurement of continuous rod and cone ERGs across a range of temporal frequencies, and post-receptoral processing in the primary retinogeniculate pathways at low stimulus contrasts. The intrinsic noise distribution may have application as a biomarker for detecting changes in disease progression or treatment efficacy.
EVALuna2:21230

A modified silent substitution electroretinography protocol to separate photoreceptor subclass function in lightly sedated dogs - Wise, E. N.; Foster, M. L.; Kremers, Jan; Mowat, F. M. (Veterinary Ophthalmology, 2020)
Objective: A previously published study successfully isolated photoreceptor responses from canine rods, long/medium-wavelength (L/M) cones, and short-wavelength (S) cones using silent substitution electroretinography (ERG) performed under general anesthesia. We hypothesized that responses would be similar in dogs under sedation and that a curtailed protocol suitable for use in clinical patients could effectively isolate responses from all three photoreceptor subtypes. Animals studied: Three normal adult purpose-bred beagles (2 females and 1 male). Methods: Dogs were dark-adapted for 1 hour. Sine wave color stimuli were delivered using LEDs in a Ganzfeld dome. The ERG protocol under anesthesia was performed as previously published; sedated ERG protocols were performed after a 3-day washout period. Intravenous sedation (dexmedetomidine 1.25 mcg/kg, butorphanol 0.1 mg/kg) was administered for sedation. Statistical analysis was performed using two-way repeated-measures ANOVA and linear regression. Results: In both anesthetized and sedated animals, rod-derived responses peaked at low frequency (4-12 Hz), L/M-cone responses peaked at high frequency (32-38 Hz), and S-cone responses peaked at low frequency (4-12 Hz). The frequencies eliciting maximal responses were similar in sedated and anesthetized protocols, although rod amplitudes were significantly higher in the sedated protocols compared with anesthetized (P <.001). Conclusion: We present a clinically applicable method to consistently isolate rod and cone subclass function in sedated dogs. This may allow detailed evaluation of photoreceptor function in clinical patients with rod or cone subclass deficits without the need for general anesthesia or protracted adaptation times.
CRIS-Team Scopus Importer:2020-12-04
Keywords: electroretinography; L/M-cone; photoreceptor; rod; S-cone; silent substitution

A multi-color video-ophthalmoscopes allows to measure the spectral distribution of light absorption of blood in the human retina - Tornow, Ralf-Peter; Odstrcilik, Jan; Kolar, Radim (Frontiers in Medicine, 2023)
Based on our previously developed mono-color video-ophthalmoscope a multi-color video-ophthalmoscope was developed. Using narrow band transmission filters, this instrument allows to measure the pulsatile cardiac cycle induced blood volume changes in the human retina for any wavelength in the sensitivity range of the used CMOS-camera. In this key experiment, video sequences (8 s, 25 fps, 200 frames) of the optic nerve head (ONH) were acquire for seven wavelengths between 475 nm and 677 nm one after the other. After image registration of all frames of each video sequence (to compensate for eye movements) and trend correction (to compensate for slow intensity changes), the amplitude of the cardiac cycle induced light intensity changes (pulsatile absorption amplitude PAA) can be calculated for all seven wavelengths. The results confirmed that the spectral distribution of PAA (λ) follows the distribution of the light absorption of blood. The measured values correspond to the absorption of a thin blood layer of about 0.5 μm thickness.
CRIS-Team Scopus Importer:2023-04-28
Keywords: blood light absorption; multi-color imaging; photoplethysmography; retina; retinal imaging; video ophthalmoscopy

A Multiple Piccolino-RIBEYE Interaction Supports Plate-Shaped Synaptic Ribbons in Retinal Neurons - Müller, Tanja; Gierke, Kaspar; Joachimsthaler, Anneka; Sticht, Heinrich; Izsvak, Zsuzsanna; Hamra, F. Kent; Fejtová, Anna; Ackermann, Frauke; Garner, Craig C.; Kremers, Jan; Brandstätter, Johann Helmut; Regus-Leidig, Hanna (Journal of Neuroscience, 2019)
Active zones at chemical synapses are highly specialized sites for the regulated release of neurotransmitters. Despite a high degree of active zone protein conservation in vertebrates, every type of chemical synapse expresses a given set of protein isoforms and splice variants adapted to the demands on neurotransmitter release. So far, we know little about how specific active zone proteins contribute to the structural and functional diversity of active zones. In this study, we explored the nanodomain organization of ribbon-type active zones by addressing the significance of Piccolino, the ribbon synapse-specific splice variant of Piccolo, for shaping the ribbon structure. We followed up on previous results, which indicated that rod photoreceptor synaptic ribbons lose their structural integrity in a knockdown of Piccolino. Here, we demonstrate an interaction between Piccolino and the major ribbon component RIBEYE that supports plate-shaped synaptic ribbons in retinal neurons. In a detailed ultrastructural analysis of three different types of retinal ribbon synapses in Piccolo/Piccolino-deficient male and female rats, we show that the absence of Piccolino destabilizes the superstructure of plate-shaped synaptic ribbons, although with variable manifestation in the cell types examined. Our analysis illustrates how the expression of a specific active zone protein splice variant (e.g., Piccolino) contributes to structural diversity of vertebrate active zones.
CRIS-Team WoS Importer:2019-04-12

Analysis of genetically determined gene expression suggest role of inflammatory processes in etiology of exfoliation syndrome - Hirbo, Jibril; Pasutto, Francesca; Sealock, Julia; Evans, Patrick; Pawar, Priyanka; Tao, Ran; Straub, Peter; Breyer, Max; Berner, Daniel; Reis, André; Schlötzer-Schrehardt, Ursula; Khor, C. C.; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-10-16

Analysis of genetically determined gene expression suggests role of inflammatory processes in exfoliation syndrome - Hirbo, Jibril B.; Pasutto, Francesca; Gamazon, Eric R.; Evans, Patrick; Pawar, Priyanka; Berner, Daniel; Sealock, Julia; Tao, Ran; Straub, Peter S.; Konkashbaev, Anuar I.; Breyer, Max A.; Schlötzer-Schrehardt, Ursula; et al. (BMC Genomics, 2023)
Background: Exfoliation syndrome (XFS) is an age-related systemic disorder characterized by excessive production and progressive accumulation of abnormal extracellular material, with pathognomonic ocular manifestations. It is the most common cause of secondary glaucoma, resulting in widespread global blindness. The largest global meta-analysis of XFS in 123,457 multi-ethnic individuals from 24 countries identified seven loci with the strongest association signal in chr15q22–25 region near LOXL1. Expression analysis have so far correlated coding and a few non-coding variants in the region with LOXL1 expression levels, but functional effects of these variants is unclear. We hypothesize that analysis of the contribution of the genetically determined component of gene expression to XFS risk can provide a powerful method to elucidate potential roles of additional genes and clarify biology that underlie XFS. Results: Transcriptomic Wide Association Studies (TWAS) using PrediXcan models trained in 48 GTEx tissues leveraging on results from the multi-ethnic and European ancestry GWAS were performed. To eliminate the possibility of false-positive results due to Linkage Disequilibrium (LD) contamination, we i) performed PrediXcan analysis in reduced models removing variants in LD with LOXL1 missense variants associated with XFS, and variants in LOXL1 models in both multiethnic and European ancestry individuals, ii) conducted conditional analysis of the significant signals in European ancestry individuals, and iii) filtered signals based on correlated gene expression, LD and shared eQTLs, iv) conducted expression validation analysis in human iris tissues. We observed twenty-eight genes in chr15q22–25 region that showed statistically significant associations, which were whittled down to ten genes after statistical validations. In experimental analysis, mRNA transcript levels for ARID3B, CD276, LOXL1, NEO1, SCAMP2, and UBL7 were significantly decreased in iris tissues from XFS patients compared to control samples. TWAS genes for XFS were significantly enriched for genes associated with inflammatory conditions. We also observed a higher incidence of XFS comorbidity with inflammatory and connective tissue diseases. Conclusion: Our results implicate a role for connective tissues and inflammation pathways in the etiology of XFS. Targeting the inflammatory pathway may be a potential therapeutic option to reduce progression in XFS.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Exfoliation syndrome; GTEx; GWAS; predicted expressions; transcriptomics; TWAS

Analysis of RIM Expression and Function at Mouse Photoreceptor Ribbon Synapses - Löhner, Martina; Babai, Norbert; Müller, Tanja; Gierke, Kaspar; Atorf, Jenny; Joachimsthaler, Anneka; Peukert, Angela; Martens, Henrik; Feigenspan, Andreas; Kremers, Jan; Schoch, Susanne; Brandstätter, Johann Helmut; et al. (The Journal of Neuroscience, 2017)
RAB3A-interacting molecule (RIM) proteins are important regulators of transmitter release from active zones. At conventional chemical synapses, RIMs contribute substantially to vesicle priming and docking and their loss reduces the readily releasable pool of synaptic vesicles by up to 75%. The priming function of RIMs is mediated via the formation of a tripartite complex with Munc13 and RAB3A, which brings synaptic vesicles in close proximity to Ca(2+) channels and the fusion site and activates Munc13. We reported previously that, at mouse photoreceptor ribbon synapses, vesicle priming is Munc13 independent. In this study, we examined RIM expression, distribution, and function at male and female mouse photoreceptor ribbon synapses. We provide evidence that RIM1? and RIM1? are highly likely absent from mouse photoreceptors and that RIM2? is the major large RIM isoform present at photoreceptor ribbon synapses. We show that mouse photoreceptors predominantly express RIM2 variants that lack the interaction domain for Munc13. Loss of full-length RIM2? in a RIM2? mutant mouse only marginally perturbs photoreceptor synaptic transmission. Our findings therefore strongly argue for a priming mechanism at the photoreceptor ribbon synapse that is independent of the formation of a RIM-Munc13-RAB3A complex and thus provide further evidence for a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses in synaptic vesicle exocytosis.SIGNIFICANCE STATEMENT RAB3A-interacting molecules 1 and 2 (RIM1/2) are essential regulators of exocytosis. At conventional chemical synapses, their function involves Ca(2+) channel clustering and synaptic vesicle priming and docking through interactions with Munc13 and RAB3A, respectively. Examining wild-type and RIM2 mutant mice, we show here that the sensory photoreceptor ribbon synapses most likely lack RIM1 and predominantly express RIM2 variants that lack the interaction domain for Munc13. Our findings demonstrate that the photoreceptor-specific RIM variants are not essential for synaptic vesicle priming at photoreceptor ribbon synapses, which represents a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses with respect to synaptic vesicle priming mechanisms.
EVALuna2:21339

Analysis of visual appearance of retinal nerve fibers in high resolution fundus images: a study on normal subjects - Kolar, Radim; Tornow, Ralf-Peter; Lämmer, Robert; Odstrcilik, Jan; Mayer, Markus Anton; Gazarek, Jiri; Jan, Jiri; Kubena, Tomas; Cernosek, Pavel (Computational and Mathematical Methods in Medicine, 2013)
The retinal ganglion axons are an important part of the visual system, which can be directly observed by fundus camera. The layer they form together inside the retina is the retinal nerve fiber layer (RNFL). This paper describes results of a texture RNFL analysis in color fundus photographs and compares these results with quantitative measurement of RNFL thickness obtained from optical coherence tomography on normal subjects. It is shown that local mean value, standard deviation, and Shannon entropy extracted from the green and blue channel of fundus images are correlated with corresponding RNFL thickness. The linear correlation coefficients achieved values 0.694, 0.547, and 0.512 for respective features measured on 439 retinal positions in the peripapillary area from 23 eyes of 15 different normal subjects.
EVALuna2:21171

Analyzing the transmission of visible light through electrospun nanofibrous PCL scaffolds - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Helsinki (Finland), 2021, 2021)

An evaluation system for stereopsis of beach volleyball players measuring perception time as a function of disparity within a virtual environment - Paulus, Jan; Hornegger, Joachim; Schmidt, Michael; Eskofier, Björn; Michelson, Georg (Journal of Vision, 2013)

A new interpretation of components in the ERG signals to sine wave luminance stimuli at different temporal frequencies and contrasts - Pangeni, Gobinda; Horn, Folkert; Kremers, Jan (Visual Neuroscience, 2010)
Full-field electroretinograms were recorded from five normal human subjects using white light (mean luminance: 250 cd/m(2)) sine wave stimuli at different frequencies and contrasts. In agreement with previous studies, we found that the amplitude of the fundamental component displayed a dip at about 12 Hz, coinciding with a maximum in the second harmonic component, indicating frequency doubling of the responses. By including measurements at different contrasts, we were able to recognize two (sine-like and transient) response components. We found that the waveform of the transient response was relatively frequency independent. An algorithm to separate the two components was developed. The interaction between these two components can explain the frequency-doubled responses around 12 Hz. The sine-like component is more linear and prominent in the low-frequency region, whereas the transient seems to be more nonlinear and prominent in the high-frequency region.
Keywords: Electroretinogram; Sine wave stimuli; Component analysis; Temporal modulation; Luminance contrast

A New Interpretation of Components in the Erg Signals to Sine Wave Luminance Stimuli at Different Temporal Frequencies and Contrasts - Pangeni, G.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: non-clinical; retina: distal (photoreceptors; horizontal cells; bipolar cells); retina: proximal (bipolar; amacrine; and ganglion cells)

A new method to measure electroretinograms (ERGs) elicited by temporal white noise - Kremers, Jan; Feigl, Beatrix K.; Aher, Avinash; Mckeefry, Declan J.; Parry, Neil Robert Alan; Maguire, John; Murray, Ian J.; Zele, Andrew J. (Investigative Ophthalmology & Visual Science, 2017)

Angioregressive pretreatment of mature corneal blood vessels before keratoplasty: fine-needle vessel coagulation combined with anti-VEGFs - Koenig, Yanyan; Bock, Felix; Kruse, Friedrich; Stock, Klaus-Peter; Cursiefen, Claus (Cornea, 2012)
To evaluate the efficacy and safety of combined feeder vessel coagulation and topical antiangiogenic therapy using bevacizumab in the treatment of mature corneal blood vessels.Sixteen eyes of 16 patients with mature corneal neovascularization (NV) due to different underlying corneal diseases underwent fine-needle feeder vessel coagulation by diathermy and were treated postoperatively for up to 4 weeks with topical bevacizumab eye drops (containing 5 mg/mL bevacizumab) 5 times a day. Nine patients received an additional subconjunctival bevacizumab injection at the time of cautery.The mean duration of follow-up was 276 ± 147.3 days (range, 29-464 days). Regression of the feeder vessel was observed in 14 eyes. The vascularized area was reduced significantly (P < 0.05). Combined subconjunctival and eye drop antivascular endothelial growth factor treatment was significantly more effective in reducing the vascularized area compared with antivascular endothelial growth factor eye drop therapy alone (P < 0.05). Five patients (5 eyes) needed a second treatment. Thirteen patients (13 eyes) receiving topical bevacizumab treatment combined with feeder vessel coagulation showed stable visual acuity. Two patients had improved visual acuity. One patient had enlarged area of lipid keratopathy despite successful treatment of corneal NV and thus decreased visual acuity. Overall, there was a nonsignificant improvement of best-corrected visual acuity (P > 0.05).In this pilot study, fine-needle feeder vessel coagulation combined with topical bevacizumab application for treatment of mature corneal NV seemed to be a well-tolerated new treatment option to regress corneal NV. This may not only improve corneal transparency but also "preconditions" such a cornea for future keratoplasty.
EVALuna2:21110

An Image-Based Method for Measuring Strabismus in Virtual Reality - Mehringer, Wolfgang; Wirth, Markus; Gradl, Stefan; Durner, Luis; Ring, Matthias; Laudanski, Annemarie F.; Eskofier, Björn; Michelson, Georg (2020 IEEE International Symposium on Mixed and Augmented Reality Adjunct (ISMAR-Adjunct), 2020)
Strabismus is a visual disorder characterized by eye misalignment. The effect of Panum’s Fusional Area (PFA) compensates for small misalignments. However, prominent misalignments affect binocular vision and when present in childhood it may lead to amblyopia, a developmental disorder of the visual system. With the advent of Virtual Reality (VR) technology, possibilities for novel binocular treatments to amblyopia arise in which the measurement of strabismus is crucial to correctly compensate for it. Thus, VR yields great potential due to the ability of displaying content to each eye independently. Major research in VR addresses this topic using eye-tracking while there is a paucity of research on image-based assessment methods. In this work, we propose a VR application for measuring strabismus in nine lines of sight. We conducted a study with 14 healthy participants to evaluate the system under two conditions: no strabismus and an artificial deviation induced by prism lenses. Further, we evaluated the effect of PFA on the system by measuring its extent in horizontal and vertical lines of sight. Results show significant difference between the expected deviation induced by prism lenses and the measured deviation. The existing difference within the measurements can be explained with the recorded extent of the PFA.<br
Keywords: Visualization; Vision defects; Virtual Reality; Human-centered computing; Strabismus

A novel approach to analyze white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

A novel ELISA-based crossmatch procedure to detect donor-specific anti-HLA antibodies responsible for corneal allograft rejections - Sel, Saadettin; Schlaf, Gerald; Schurat, Oliver; Altermann, Wolfgang W. (Journal of Immunological Methods, 2012)
Previous studies had shown that donor-specific anti-HLA antibodies may highly influence the survival rate of corneal allografts, although the anterior chamber generally represents an immune-privileged compartment of the eye. We postulated that the introduction of a novel crossmatch procedure for the detection of donor-specific anti-HLA antibodies in recipients awaiting a corneal graft would be adequate to investigate their influence on the outcome of the graft survival. The Antibody Monitoring System (AMS) HLA class I & II crossmatch ELISA was adapted for the use of material from the outer scleral rim instead of blood lymphocytes to isolate the donors' HLA molecules. In case of detectable donor-specific anti-HLA class I and/or class II antibodies (DSA) this result was confirmed using an identification ELISA to specify the detectable recipient's anti-HLA antibodies. PCR-based genetic tissue typing of the donors was performed also using their outer scleral rims. 45 recipients of corneal grafts were analyzed for DSA prior to or after grafting, respectively. 75% of the recipients with preformed DSA exhibited immunological complications up to the complete graft loss in four cases during the first two months. In contrast 77% of the recipients without DSA did not show any complications during the follow up period of averagely 18months. Only two cases of graft loss were observed in this group after 17 and 23months, respectively. The results demonstrate the impact of preventing donor-specific anti-HLA antibodies which are for the first time reliably detectable in any laboratory's daily work using the adapted AMS-ELISA.
EVALuna2:21105

A novel mechanism of UV-A and riboflavin-mediated corneal cross-linking through induction of tissue transglutaminases - Kopsachilis, Nikolaos; Tsaousis, Konstantinos T.; Tsinopoulos, Ioannis T.; Kruse, Friedrich; Welge-Luessen, Ulrich (Cornea, 2013)
Collagen cross-linking using UV-A irradiation combined with the photosensitizer riboflavin is a new technique for treating progressive keratoconus. The purposes of this study were to examine whether primary human corneal keratocytes (HCKs) are capable of expressing and secreting fibronectin and tissue transglutaminase (tTgase), an enzyme cross-linking extracellular matrix protein, and to examine whether fibronectin and tTgase are increased after the treatment of HCK cells with UV-A irradiation combined with riboflavin (RFUV-A), thus providing another possible physiological mechanism of the cross-linking pathway.Cell cultures established from HCKs were treated with 0.025% riboflavin solution and UV-A (370 nm) irradiance 3 mW/cm2 for 30 minutes. Induction of fibronectin and tTgase was investigated by immunohistochemistry, real-time polymerase chain reaction, and Western blot analysis. Cell viability was quantified by a microscopic live-dead assay. External tTgase activity was measured by the ability to form polymerized fibronectin and the incorporation of biotinylated cadaverine into fibronectin.Treatment of cultured HCK cells with RFUV-A increased the fibronectin and tTgase messenger RNA and protein levels. This effect was not observed in cells treated with riboflavin or UV-A radiation alone. Incorporation of biotinylated cadaverine was significantly increased when HCK cells were treated with RFUV-A.The enzymes tTgase and fibronectin are expressed by RFUV-A treatment in cultured HCK cells. This mechanism provides more information about the physiology of corneal cross-linking.
EVALuna2:21144

A novel suture retention test for scaffold strength characterization in ophthalmology. - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2016)
Sutures are a common way to attach scaffolds in patients. For tubular cardiac scaffolds, the 'suture retention strength' is commonly used to evaluate the resistance of a scaffold against the pull-out of a suture. In order to make this quantity accessible for ophthalmological scaffolds the test procedure has been modified in a novel way. Polycaprolactone (PCL) films of different thicknesses and an amniotic membrane (AM) were used for the experiments. Circular samples with a radius of 7mm were taken and a suture was passed through each sample and tied to a loop. The sample was clamped in a tensile tester and a bolt was passed through the loop. The suture was then pulled with a constant deformation rate until pull-out occurred. The suture retention strength, the deformation at the suture retention strength, and the deformation at rupture were determined for each sample. The presented modified suture retention test allows to measure the relevant parameters of samples on the scale of ophthalmological scaffolds in a reproducible way. A comparison between the first data on PCL and AM has been made.

Anterior Chamber Air Bubble to Achieve Graft Attachment After DMEK: Is Bigger Always Better? - Cirkovic, Aleksandar; Beck, Christina; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2016)
To analyze the influence of the size of the air bubble subsequent to Descemet membrane endothelial keratoplasty (DMEK) surgery on the rate of graft detachment and need for rebubbling, the incidence of pupillary block, and the observed endothelial cell loss.This is a single-center, retrospective, consecutive case series of 74 cases undergoing DMEK and fulfilling the inclusion criteria concerning the size of the air bubble at the end of surgery. Based on the medical records, patients were divided into 2 groups (n = 37, respectively). The first group had an air bubble with a volume of approximately 50% and the second group of approximately 80% of the anterior chamber (AC) volume, respectively. Patients who did not comply with instructions to remain in the supine position until complete resorption of AC air or cases in which difficulties in graft preparation (eg, radial breaks) occurred were excluded from data analysis. The central corneal thickness and endothelial cell density were measured 6 months after surgery.Ten of 37 patients (27.0%) in the 50% air bubble group and 3 of 37 patients (8.1%) in the 80% air bubble group needed 1 rebubbling procedure (P = 0.032). There was no difference between the groups after 6 months regarding endothelial cell density and central corneal thickness. No pupillary block was observed.Larger air bubbles of 80% anterior chamber volume decrease the risk of graft detachment after DMEK with no detrimental effect on the outcome and risk for pupillary block.
EVALuna2:21286

Anterior Scleral Canal Opening (ASCO) offset relative to Bruch's Membrane Opening (BMO) influences the Angular Location of Peak Retinal Nerve Fiber Layer Thickness (RNFLT) in Healthy Human Eyes - Hong, Seung Woo; Yang, Hongli; Gardiner, Stuart Keith; Luo, Haomin; Hardin, Christy A.; Sharpe, Glen; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Liebmann, Jeffrey M.; Mardin, Christian Y.; Quigley, Harry A.; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Antiangiogenic therapy at the ocular surface: when, what and why? - Bock, F.; Regenfuss, B.; Cursiefen, Claus (Ophthalmologe, 2011)
There are numerous indications for local antiangiogenic therapy at the ocular surface. These include vision-limiting corneal neovascularization, corneal blood and lymphatic vessels endangering corneal graft survival and tumor-associated lymphangiogenesis. A literature review in PubMed and own clinical and experimental data form the basis for a discussion of the indications, current therapeutic options and potential side-effects of local antiangiogenic therapy at the ocular surface.
EVALuna2:21057

A potential role for impaired retinoic acid signaling in the pathophysiology of pseudoexfoliation syndrome/glaucoma - Zenkel, Matthias; Berner, Daniel; Hoja, Ursula; Pasutto, Francesca; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Appearance-based Approach to Extract an Age-related Biomarkers from Retinal Images - Bock, Rüdiger; Meier, Jörg; Nyul, Laszlo Gabor; Wärntges, Simone; Michelson, Georg; Hornegger, Joachim (3rd Russian-Bavarian Conference on Biomedical Engineering, 2007)

Application of morphological operators for optic nerve head segmentation in optical coherence tomography images - Moupagiatzis, Ioannis; Mayer, Markus Anton; Hornegger, Joachim; Tornow, Ralf-Peter; Mardin, Christian Y. (2012 19th International Conference on Systems, Signals and Image Processing, IWSSIP 2012, 2012)
Optical Coherence Tomography (OCT) is an imaging modality that has several advantages (e.g. high resolution and three dimensional imaging) in comparison with other ophthalmic imaging methods. Retinal structures, such as the optic nerve head (ONH), can be examined in detail. The geometry of the ONH can offer valuable information for the detection of glaucoma, because it is affected by this disease. However, manual examinations are highly subjective. In this study we present an approach using morphological operators for the completely automated segmentation of the ONH region, which is crucial for the further examination of the geometrical parameters that indicate the presence of glaucoma. The method was applied to OCT volumes of 10 individuals (7 glaucoma patients, 3 normal subjects). The automatically extracted results were evaluated both qualitatively and quantitatively, and yielded a sensitivity of 0.89±0.09 and a specificity of 0.98±0.01. © 2012 Institute of Telecommunica.

Applications of Artificial Intelligence in Optical Coherence Tomography Angiography Imaging - Schottenhamml, Julia; Hohberger, Bettina; Mardin, Christian Y. (Klinische Monatsblätter für Augenheilkunde, 2022)
Optical coherence tomography angiography (OCTA) and artificial intelligence (AI) are two emerging fields that complement each other. OCTA enables the noninvasive, in vivo, 3D visualization of retinal blood flow with a micrometer resolution, which has been impossible with other imaging modalities. As it does not need dye-based injections, it is also a safer procedure for patients. AI has excited great interest in many fields of daily life, by enabling automatic processing of huge amounts of data with a performance that greatly surpasses previous algorithms. It has been used in many breakthrough studies in recent years, such as the finding that AlphaGo can beat humans in the strategic board game of Go. This paper will give a short introduction into both fields and will then explore the manifold applications of AI in OCTA imaging that have been presented in the recent years. These range from signal generation over signal enhancement to interpretation tasks like segmentation and classification. In all these areas, AI-based algorithms have achieved state-of-The-Art performance that has the potential to improve standard care in ophthalmology when integrated into the daily clinical routine.
CRIS-Team Scopus Importer:2022-12-23
Keywords: artificial intelligence; deep learning; machine learning; OCTA

Applying nnU-Net to the segmentation of microaneurysms in OCTA data in patients with non-proliferative diabetic retinopathy - Husvogt, Lennart; Abu-Qamar, Omar; Levine, Emily; Schottenhamml, Julia; Ploner, Stefan; Breininger, Katharina; Moult, Eric; Waheed, Nadia K.; Fujimoto, James G.; Maier, Andreas (ARVO Annual Meeting 2021, 2021)

APSified OCT-angiography analysis: Macula vessel density in healthy eyes during office hours - Müller, Meike; Schottenhamml, Julia; Hosari, Sami; Hohberger, Bettina; Mardin, Christian Y. (PLoS ONE, 2023)
Purpose Optical coherence tomography angiography (OCT-A) can visualize retinal capillary microcirculation non-invasively. In order to investigate potential factors influencing OCT-A diagnostics, the aim of the present study was to determine circadian changes in macular vessel density (VD) in healthy adults during office hours, considering axial length (AL) and subfoveal choroidal thickness (CT). Methods In the prospective study 30 eyes of 30 healthy subjects (mean age 28.7 ± 11.8, range 19–60 years) were recruited who underwent repeated measurements of AL, subfoveal CT and three-layer macula VD (superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP)) on a single day at three predetermined timepoints (9 AM, 3 PM, and 9 PM). For better intra- and interindividual scan comparability, the new Anatomic Positioning System function (APS, part of Glaucoma Module Premium Edition [GMPE], Heidelberg Engineering, Germany) allowing analysis of identical retinal areas, was used for quantitative OCT-A analysis. Results Overall mean macula VD was unchanged during office hours in SVP, ICP and DCP, respectively (p>0.05). In addition, AL and CT showed no statistically significant changes over time (p>0.05). Rather, a large interindividual variance of VD with different peak time was observed. Contrary to the overall data, sectorial VD changed in dependency of office hours in all layers with an increase of VD in SVP between 9 AM and 9 PM (p = 0.003), in ICP between 3 PM and 9 PM (p = 0.000), in DCP between 9 AM and 9 PM (p = 0.048), and 3 PM and 9 PM (p = 0.000), respectively. Conclusion Overall mean macula VD, subfoveal CT and AL tended not to show statistically significant changes over time in this cohort, whereas a regional analysis of VD did. Therefore, a circadian influence on capillary microcirculation should be kept in mind. Moreover, the results highlight the importance of a more detailed analysis of VD in different sectors and different vascular layers. In addition, the pattern of diurnal variation could vary inter-individually, thus a patient-specific fluctuation pattern would need to be considered when evaluating these parameters in clinical practice.
CRIS-Team Scopus Importer:2023-03-24

'APSifyed' Bruch's membrane opening (BMO) based peripapillary OCT-A analysis - Mardin, Christian Y.; Schottenhamml, Julia; Dehcordi, Sebastian Fassihi; Müller, Meike; Maier, Andreas; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-01

Are agonistic beta 2-adrenergic receptor autoantibodies present in normal tension glaucoma and secondary open-angle glaucoma? - Hohberger, Bettina; Mardin, Christian Y.; Hosari, Sami; Lämmer, Robert; Kunze, Rudolf; Juenemann, Anselm; Schlötzer-Schrehardt, Ursula; Wallukat, Gerd; Herrmann, Martin (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Argon Cold Plasma–A Novel Tool to Treat Therapy-resistant Corneal Infections - Reitberger, Helena; Czugala, Marta; Chow, Catherine; Mohr, Andreas; Burkovski, Andreas; Gruenert, Anja K.; Schoenebeck, Renate; Fuchsluger, Thomas (American Journal of Ophthalmology, 2018)

A Spatiotemporal Illumination Model for 3d Image Fusion in Optical Coherence Tomography - Ploner, Stefan; Won, Jungeun; Schottenhamml, Julia; Girgis, Jessica; Lam, Kenneth; Waheed, Nadia; Fujimoto, James; Maier, Andreas (2023 IEEE 20th International Symposium on Biomedical Imaging, 2023)
Optical coherence tomography (OCT) is a non-invasive, micrometer-scale imaging modality that has become a clinical standard in ophthalmology. By raster-scanning the retina, sequential cross-sectional image slices are acquired to generate volumetric data. In-vivo imaging suffers from discontinuities between slices that show up as motion and illumination artifacts. We present a new illumination model that exploits continuity in orthogonally raster-scanned volume data. Our novel spatiotemporal parametrization adheres to illumination continuity both temporally, along the imaged slices, as well as spatially, in the transverse directions. Yet, our formulation does not make inter-slice assumptions, which could have discontinuities. This is the first optimization of a 3D inverse model in an image reconstruction context in OCT. Evaluation in 68 volumes from eyes with pathology showed reduction of illumination artifacts in 88% of the data, and only 6% showed moderate residual illumination artifacts. The method enables the use of forward-warped motion corrected data, which is more accurate, and enables supersampling and advanced 3D image reconstruction in OCT.<br

Assessment of retinal vein pulsation through video-ophthalmoscopy and simultaneous biosignals acquisition - Kolar, Radim; Vicar, Tomas; Chmelik, Jiri; Jakubicek, Roman; Odstrcilik, Jan; Valterova, Eva; Nohel, Michal; Skorkovska, Karolina; Tornow, Ralf-Peter (Biomedical Optics Express, 2023)
The phenomenon of retinal vein pulsation is still not a deeply understood topic in retinal hemodynamics. In this paper, we present a novel hardware solution for recording retinal video sequences and physiological signals using synchronized acquisition, we apply the photoplethysmographic principle for the semi-automatic processing of retinal video sequences and we analyse the timing of the vein collapse within the cardiac cycle using of an electrocardiographic signal (ECG). We measured the left eyes of healthy subjects and determined the phases of vein collapse within the cardiac cycle using a principle of photoplethysmography and a semi-automatic image processing approach. We found that the time to vein collapse (Tvc) is between 60 ms and 220 ms after the R-wave of the ECG signal, which corresponds to 6% to 28% of the cardiac cycle. We found no correlation between Tvc and the duration of the cardiac cycle and only a weak correlation between Tvc and age (0.37, p = 0.20), and Tvc and systolic blood pressure (-0.33, p = 0.25). The Tvc values are comparable to those of previously published papers and can contribute to the studies that analyze vein pulsations.
CRIS-Team Scopus Importer:2023-06-30

Association between axial length and horizontal and vertical globe diameters - Jonas, Jost B.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To assess relationships between axial length and the horizontal and vertical globe diameters.The study consisted of enucleated human eyes. The horizontal, vertical, and sagittal diameters were measured.The study included 135 globes removed because of malignant uveal melanoma (111 globes) or end-stage painful glaucoma (n = 24 eyes). Mean axial, horizontal, and vertical diameters were 24.6 ± 2.6 mm (range: 20-35 mm), 23.7 ± 1.4 mm (range: 21-29 mm) and 23.7 ± 1.4 mm (range: 20-29 mm) respectively. The horizontal diameter and vertical diameter did not differ significantly (P = 0.92), while both were significantly (P < 0.001) shorter than the axial diameter. The horizontal diameter was significantly and linearly correlated with the vertical globe diameter (P < 0.001; regression line: vertical globe diameter = 0.84 × horizontal globe diameter + 3.69). The axial diameter was significantly (P < 0.001) associated with the horizontal diameter and vertical diameters in a bipartite manner. In eyes with an axial length <=24 mm, horizontal and vertical diameters increased by 0.44 and 0.51 mm, respectively, for each mm increase in axial diameter, while in eyes with an axial length >24 mm, the horizontal and vertical globe diameter increased by a lower amount of 0.19 and 0.21 mm, respectively, for each mm increase in axial diameter.Myopic enlargement of the globe beyond an axial length of 24 mm takes place predominantly in the sagittal axis, leading to a change in the globe form from a sphere to an elongated form. It fits with the notion that myopic elongation may occur by an elongation of the eye walls in regions close to the globe's equator.
EVALuna2:21312

Association of Rare CYP39A1 Variants with Exfoliation Syndrome Involving the Anterior Chamber of the Eye - Li, Zheng; Wang, Zhenxun; Lee, Mei Chin; Zenkel, Matthias; Peh, Esther; Ozaki, Mineo; Topouzis, Fotis; Nakano, Satoko; Chan, Anita; Chen, Shuwen; Williams, Susan E.I.; Orr, Andrew; et al. (Journal of the American Medical Association, 2021)
Importance: Exfoliation syndrome is a systemic disorder characterized by progressive accumulation of abnormal fibrillar protein aggregates manifesting clinically in the anterior chamber of the eye. This disorder is the most commonly known cause of glaucoma and a major cause of irreversible blindness. Objective: To determine if exfoliation syndrome is associated with rare, protein-changing variants predicted to impair protein function. Design, Setting, and Participants: A 2-stage, case-control, whole-exome sequencing association study with a discovery cohort and 2 independently ascertained validation cohorts. Study participants from 14 countries were enrolled between February 1999 and December 2019. The date of last clinical follow-up was December 2019. Affected individuals had exfoliation material on anterior segment structures of at least 1 eye as visualized by slit lamp examination. Unaffected individuals had no signs of exfoliation syndrome. Exposures: Rare, coding-sequence genetic variants predicted to be damaging by bioinformatic algorithms trained to recognize alterations that impair protein function. Main Outcomes and Measures: The primary outcome was the presence of exfoliation syndrome. Exome-wide significance for detected variants was defined as P < 2.5 × 10-6. The secondary outcomes included biochemical enzymatic assays and gene expression analyses. Results: The discovery cohort included 4028 participants with exfoliation syndrome (median age, 78 years [interquartile range, 73-83 years]; 2377 [59.0%] women) and 5638 participants without exfoliation syndrome (median age, 72 years [interquartile range, 65-78 years]; 3159 [56.0%] women). In the discovery cohort, persons with exfoliation syndrome, compared with those without exfoliation syndrome, were significantly more likely to carry damaging CYP39A1 variants (1.3% vs 0.30%, respectively; odds ratio, 3.55 [95% CI, 2.07-6.10]; P = 6.1 × 10-7). This outcome was validated in 2 independent cohorts. The first validation cohort included 2337 individuals with exfoliation syndrome (median age, 74 years; 1132 women; n = 1934 with demographic data) and 2813 individuals without exfoliation syndrome (median age, 72 years; 1287 women; n = 2421 with demographic data). The second validation cohort included 1663 individuals with exfoliation syndrome (median age, 75 years; 587 women; n = 1064 with demographic data) and 3962 individuals without exfoliation syndrome (median age, 74 years; 951 women; n = 1555 with demographic data). Of the individuals from both validation cohorts, 5.2% with exfoliation syndrome carried CYP39A1 damaging alleles vs 3.1% without exfoliation syndrome (odds ratio, 1.82 [95% CI, 1.47-2.26]; P <.001). Biochemical assays classified 34 of 42 damaging CYP39A1 alleles as functionally deficient (median reduction in enzymatic activity compared with wild-type CYP39A1, 94.4% [interquartile range, 78.7%-98.2%] for the 34 deficient variants). CYP39A1 transcript expression was 47% lower (95% CI, 30%-64% lower; P <.001) in ciliary body tissues from individuals with exfoliation syndrome compared with individuals without exfoliation syndrome. Conclusions and Relevance: In this whole-exome sequencing case-control study, presence of exfoliation syndrome was significantly associated with carriage of functionally deficient CYP39A1 sequence variants. Further research is needed to understand the clinical implications of these findings.
CRIS-Team Scopus Importer:2021-03-05

Association of rs613872 and trinucleotide repeat expansion in the TCF4 gene in Fuchs endothelial corneal dystrophy in Germany - Komori, Yuya; Okumura, Naoki; Hayashi, Ryosuke; Nakano, Masakazu; Tashiro, Kei; Yoshii, Kengo; Aleff, Ross; Butz, Malinda; Highsmith, Edward W.; Wieben, Eric; Fautsch, Michael P.; Baratz, Keith H.; et al. (2018)
EVALuna2:34743

Association of rs613872 and Trinucleotide Repeat Expansion in the TCF4 Gene of German Patients With Fuchs Endothelial Corneal Dystrophy - Okumura, Naoki; Hayashi, Ryousuke; Nakano, Masakazu; Tashiro, Kei; Yoshii, Kengo; Aleff, Ross; Butz, Malinda; Highsmith, Edward W.; Wieben, Eric D.; Fautsch, Michael P.; Baratz, Keith H.; Komori, Yuya; et al. (Cornea, 2019)
PURPOSE: To investigate single nucleotide polymorphisms (SNPs) and trinucleotide repeat (TNR) expansion in the transcription factor 4 (TCF4) gene in a large cohort of German patients with Fuchs endothelial corneal dystrophy (FECD). METHODS: Genomic DNA was obtained from 398 patients with FECD and from 58 non-FECD controls. Thirty-seven previously reported SNPs were evaluated by genotyping. The 398 FECD samples were analyzed for TNR expansions by short tandem repeat assays and Southern blotting. The possible associations between the TNR length and clinical parameters (age, sex, visual acuity, and central corneal thickness) were analyzed in 132 patients. RESULTS: The SNPs in COL8A2, TCF8, LOXHD1, and AGBL1 showed no heterogeneity in 36 cases, although SLCA411 showed 3 nonsense mutations. SNPs were detected for TCF4 (rs613872, rs2123392, rs17089887, rs1452787, and rs1348047), but only rs613872 showed a significant association with FECD (P = 9.93 × 10). Overall, 315/398 (79%) patients harbored TNR lengths >50, whereas no non-FECD controls harbored TNR lengths >50. The TCF4 SNP rs613872 genotype was TT: 39 (67%), TG: 18 (31%), and GG: 1 (2%) in non-FECD controls; TT: 39 (47%), TG: 38 (46%), and GG: 6 (7%) in FECD cases harboring TNR <50; and TT: 23 (8%), TG: 224 (79%), and GG: 38 (13%) in FECD cases harboring TNR >50 (P = 2.93 × 10). No significant association was detected between the TNR length and clinical parameters. CONCLUSIONS: Our large German cohort demonstrated a significant association between the risk allele G in rs613872 and FECD, irrespective of TNR expansion, although this risk allele was more frequent in FECD cases with TNR expansion than without.
CRIS-Team Scopus Importer:2019-06-25

Association of the retinal vasculature and disease course in patients with relapsing remitting multiple sclerosis - Noll, C.; Aly, L.; Wicklein, R.; Berthele, A.; Mardin, Christian Y.; Korn, T.; Hemmer, B.; Knier, B. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Association of the retinal vasculature and intrathecal immunity during relapsing remitting multiple sclerosis - Noll, C.; Aly, L.; Hiltensperger, M.; Wicklein, R.; Mitsdorffer, M.; Herrmann, D.; Gasperi, C.; Herrmann, D.; Gasperi, C.; Berthele, A.; Hosari, Sami; Mardin, Christian Y.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03

A stepwise approach to donor preparation and insertion increases safety and outcome of Descemet membrane endothelial keratoplasty - Kruse, Friedrich; Laaser, Kathrin; Cursiefen, Claus; Heindl, Ludwig M.; Schlötzer-Schrehardt, Ursula; Riss, Stephan; Bachmann, Bjoern O. (Cornea, 2011)
Lamellar techniques for selective replacement of diseased corneal structures have recently been improved. Descemet membrane endothelial keratoplasty (DMEK) allows the sole replacement of the endothelium–Descemet membrane layer (EDM). However, wide-spread use of DMEK is currently limited because of problems with donor preparation namely the tearing of the Descemet membrane and the difficulty to unfold the EDM graft in the anterior chamber (AC).A standardized DMEK procedure that allows safe preparation of EDM, atraumatic introduction of EDM into the AC, reliable orientation of EDM during surgery, and stepwise unfolding within the AC is described in 80 patients. Visual acuity and corneal endothelial cell density were assessed.A stepwise approach using a novel bimanual underwater technique to harvest EDM from donor corneal buttons allows reproducible generation of grafts without tearing the Descemet membrane. Injection of the EDM roll into the AC is achieved by use of a standard injector cartridge, whereas the depth of AC is maintained by an irrigation handpiece. Marks at the margin of EDM allow orientation. Finally, unfolding EDM in the AC is achieved by sequential use of water jets and air bubbles. In the early phase of the learning curve, 4 patients were regrafted because of graft failure. Endothelial cell density decreased from 2600 6 252 to 1526 6 341 cells per square millimeter 1 month after DMEK.A novel technique for graft preparation and EDM injection results in improved safety with a high rate of successful DMEK
EVALuna2:21013

Asymmetrical Functional Deficits of ON and OFF Retinal Processing in the mdx3Cv Mouse Model of Duchenne Muscular Dystrophy - Tsai, Tina I.; Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Roux, Michel J.; Rendon, Alvaro; Ventura, Dora Fix; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)
The dystrophin mouse mutant mdx3Cv exhibits scotopic electroretinograpic (ERG) abnormalities, which resemble clinical changes observed in Duchenne muscular dystrophy (DMD) patients. In the present study, ERGs obtained from mdx3Cv and their wild-type littermates under scotopic, mesopic, and photopic conditions were analyzed to provide further insight on the affected retinal pathways, and to compare them with human data.Electroretinograms of mdx3Cv (n = 9) and age-matched C57BL/6J mice (n = 10) included the scotopic full-field flash (for outer retinal deficits in rod pathway), scotopic threshold response (for inner retinal integrity), photopic flash, sinusoidal flicker (for outer retinal deficits in cone pathway), mesopic rapid-on/-off sawtooth flicker, and photopic long-duration flash measurements (for separate ON-/OFF-responses under different conditions).The mdx3Cv mice exhibited diminished and delayed scotopic and photopic ERGs, particularly in their b-wave and oscillatory potentials. Interestingly, homologues to the a- and b-wave of the mesopic ON-response were affected in their peak/trough times but not in their amplitude, whereas changes to both features were uncovered for photopic ON-response and sinusoidal flicker. Mesopic and photopic OFF-components were within the norm.Abnormal scotopic and photopic flash ERGs were observed in mdx3Cv, which corroborate with deficits that are likely restricted to the level of photoreceptor-to-bipolar cell transmission. Further overlaps between mdx3Cv mice and DMD patients exist, including asymmetrical ON versus OFF ERG alterations under mesopic versus photopic vision. In mice, ON-pathway function is compromised, whereas the OFF-pathway is spared.
EVALuna2:21316
Keywords: Duchenne muscular dystrophy; dystrophin; electrophysiology; mouse model

Asymmetrical ON/OFF retinal dysfunction in the mdx(Cv3) mouse model of Duchenne muscular dystrophy - Tsai, Tina I.; Barboni, Mirella Telles Salgueiro; Nagy, Balazs Vince; Roux, Michel J.; Rendon, Alvaro; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

Asymmetries in the contributions of on- and off-mechanisms to the ERG signal - Kremers, Jan (Psychology & Neuroscience, 2013)
Keywords: Asymmetries; L- and M-cones; Electroretinograms; On- and off-responses

Asymmetry of Peripapillary Retinal Blood Vessel and Retinal Nerve Fiber Layer Thickness Between Healthy Right and Left Eyes - Quach, Jack; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Scheuerle, Alexander F.; Burgoyne, Claude F.; Chauhan, Balwantray C.; Vianna, Jayme R. (Investigative Ophthalmology & Visual Science, 2023)
Purpose: The purpose of this study was to determine if there is asymmetry in retinal blood vessel (RBV) position and thickness between right and left eyes (R-L) and evaluate whether R-L asymmetry in RBV thickness is related to R-L asymmetry of retinal nerve fiber layer thickness (RNFLT). Methods: We analyzed peripapillary circle scan optical coherence tomography (OCT) examinations from healthy White subjects to measure RNFLT and RBV thickness and position relative to the fovea to Bruch's membrane opening axis, for all visible RBV. The R-L asymmetries of RNFLT and RBV thickness were computed for each A-scan. Four major vessels (superior temporal artery [STA] and superior temporal vein [STV], inferior temporal artery [ITA], and vein [ITV]) were identified using infrared images. Results: We included 219 individuals. The mean (standard deviation) number of RBV measured per eye was 15.0 (SD = 2.2). The position of the STV and STA was more superior in left eyes than in right eyes, by 2.4 degrees and 3.7 degrees, respectively (P < 0.01). There was no region with significant R-L asymmetry in RBV thickness. RNFLT was thicker in right eyes in the temporal superior region and thicker in left eyes in the superior and nasal superior regions, with the asymmetry profile resembling in a "W" shape. This shape was also present in post hoc analyses in two different populations. The R-L asymmetries of RBV and RNFLT at each A-scan were not significantly associated (P = 0.37). Conclusions: There is little R-L asymmetry in RBV, and it is not related to RNFLT asymmetry. This study suggests that R-L RNFLT asymmetry is due to factors other than RBV.
CRIS-Team Scopus Importer:2023-03-03

A Temporal White Noise Analysis for Extracting the Impulse Response Function of the Human Electroretinogram - Zele, Andrew J.; Feigl, Beatrix; Kambhampati, Pradeep K.; Aher, Avinash; Mckeefry, Declan; Parry, Neil; Maguire, John; Murray, Ian; Kremers, Jan (Translational Vision Science & Technology, 2017)
Purpose: We introduce a method for determining the impulse response function (IRF) of the ERG derived from responses to temporal white noise (TWN) stimuli.Methods: This white noise ERG (wnERG) was recorded in participants with normal trichromatic vision to full-field (Ganzfeld) and 39.3 degrees diameter focal stimuli at mesopic and photopic mean luminances and at different TWN contrasts. The IRF was obtained by cross-correlating the TWN stimulus with the wnERG.Results: We show that wnERG recordings are highly repeatable, with good signal-tonoise ratio, and do not lead to blink artifacts. The wnERG resembles a flash ERG waveform with an initial negativity (N1) followed by a positivity (P1), with amplitudes that are linearly related to stimulus contrast. These N1 and N1-P1 components showed commonalties in implicit times with the a-and b-waves of flash ERGs. There was a clear transition from rod-to cone-driven wnERGs at similar to 1 photopic cd.m(-2). We infer that oscillatory potentials found with the flash ERG, but not the wnERG, may reflect retinal nonlinearities due to the compression of energy into a short time period during a stimulus flash.Conclusion: The wnERG provides a new approach to study the physiology of the retina using a stimulation method with adaptation and contrast conditions similar to natural scenes to allow for independent variation of stimulus strength and mean luminance, which is not possible with the conventional flash ERG.
Keywords: electroretinogram (ERG); temporal white noise; impulse response function

Author Correction: Virtual reality for assessing stereopsis performance and eye characteristics in Post-COVID (Scientific Reports, (2023), 13, 1, (13167), 10.1038/s41598-023-40263-w) - Mehringer, Wolfgang; Stöve, Maike; Krauß, Daniel; Ring, Matthias; Steussloff, Fritz; Güttes, Moritz; Zott, Julia; Hohberger, Bettina; Michelson, Georg; Eskofier, Björn (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 13 August 2023 In the original version of this Article, Bettina Hohberger, Georg Michelson and Bjoern Eskofier were omitted as equally contributing authors. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-10-13

Autoantibodies Activating the β2-Adrenergic Receptor Characterize Patients With Primary and Secondary Glaucoma - Hohberger, Bettina; Kunze, Rudolf; Wallukat, Gerd; Kara, Katja; Mardin, Christian Y.; Lämmer, Robert; Schlötzer-Schrehardt, Ursula; Hosari, Sami; Horn, Folkert; Munoz Becerra, Luis; Herrmann, Martin (Frontiers in Immunology, 2019)
Recently, agonistic autoantibodies (agAAb) activating the β2-adrenergic receptor were detected in primary open-angle glaucoma (POAG) or ocular hypertension (OHT) patients and were linked to intraocular pressure (IOP) (1). The aim of the present study was to quantify β2-agAAb in the sera of glaucoma suspects and patients with primary and secondary glaucoma. Patients with OHT (n = 33), pre-perimetric POAG (pre-POAG; n = 11), POAG (n = 28), and 11 secondary OAG (SOAG) underwent ophthalmological examinations including examinations with Octopus G1 perimetry and morphometry. Twenty-five healthy individuals served as controls. Serum-derived IgG samples were analyzed for β2-agAAb using a functional bioassay. The beat-rate-increase of spontaneously beating cultured neonatal rat cardiomyocytes was monitored with 1.6 beats/15 s as cut-off. None of the sera of normal subjects showed β2-agAAb. In POAG or OHT patients increased beating rates of 4.1 ± 2.2 beats/15 s, and 3.7 ± 2.8 beats/15 s were detected (p > 0.05). Glaucoma patients with (POAG) and without perimetric (pre-POAG) defects did not differ (pre-POAG 4.4 ± 2.6 beats/15 s, POAG 4.1 ± 2.0 beats/15 s, p > 0.05). Patients with SOAG yielded mean beating rates of 4.7 ± 1.7 beats/15 s (p > 0.05). β2-agAAb were seen in 73% of OHT, 82% of pre-POAG, 82% of POAG, and 91% SOAG patients (p < 0.001). Clinical data did not correlate with beating rate (p > 0.05). The robust β2-agAAb seropositivity in patients with OHT, pre-POAG, POAG, and SOAG suggest a primary common role for β2-agAAb starting early in glaucoma pathophysiology and turned out to be a novel marker identifying all patients with increased IOP independent of glaucoma stage and entity.
CRIS-Team Scopus Importer:2019-10-29
Keywords: autoantibodies; glaucoma; ocular hypertension; primary open-angle glaucoma; secondary open-angle glaucoma; β2-adrenergic receptor

Autoantibodies targeting G protein-coupled receptors: An evolving history in autoimmunity. Report of the 4th international symposium - Cabral-Marques, Otávio; Moll, Guido; Catar, Rusan; Preuß, Beate; Bankamp, Lukas; Pecher, Ann Christin; Henes, Joerg; Klein, Reinhild; Kamalanathan, A. S.; Akbarzadeh, Reza; van Oostveen, Wieke; Hohberger, Bettina; et al. (Autoimmunity Reviews, 2023)
G protein-coupled receptors (GPCR) are involved in various physiological and pathophysiological processes. Functional autoantibodies targeting GPCRs have been associated with multiple disease manifestations in this context. Here we summarize and discuss the relevant findings and concepts presented in the biennial International Meeting on autoantibodies targeting GPCRs (the 4th Symposium), held in Lübeck, Germany, 15–16 September 2022. The symposium focused on the current knowledge of these autoantibodies' role in various diseases, such as cardiovascular, renal, infectious (COVID-19), and autoimmune diseases (e.g., systemic sclerosis and systemic lupus erythematosus). Beyond their association with disease phenotypes, intense research related to the mechanistic action of these autoantibodies on immune regulation and pathogenesis has been developed, underscoring the role of autoantibodies targeting GPCRs on disease outcomes and etiopathogenesis. The observation repeatedly highlighted that autoantibodies targeting GPCRs could also be present in healthy individuals, suggesting that anti-GPCR autoantibodies play a physiologic role in modeling the course of diseases. Since numerous therapies targeting GPCRs have been developed, including small molecules and monoclonal antibodies designed for treating cancer, infections, metabolic disorders, or inflammatory conditions, anti-GPCR autoantibodies themselves can serve as therapeutic targets to reduce patients' morbidity and mortality, representing a new area for the development of novel therapeutic interventions.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Anti-GPCR autoantibodies; Autoimmune diseases; COVID-19; Post-COVID; Rheumatic diseases

Automated quality assessment of retinal fundus photos - Paulus, Jan; Meier, Jörg; Bock, Rüdiger; Hornegger, Joachim; Michelson, Georg (International Journal of Computer Assisted Radiology and Surgery, 2010)
Objective: Automated, objective and fast measurement of the image quality of single retinal fundus photos to allow a stable and reliable medical evaluation. Methods: The proposed technique maps diagnosis-relevant criteria inspired by diagnosis procedures based on the advise of an eye expert to quantitative and objective features related to image quality. Independent from segmentation methods it combines global clustering with local sharpness and texture features for classification. Results: On a test dataset of 301 retinal fundus images we evaluated our method on a given gold standard by human observers and compared it to a state of the art approach. An area under the ROC curve of 95.3% compared to 87.2% outperformed the state of the art approach. A significant p-value of 0.019 emphasizes the statistical difference of both approaches. Conclusions: The combination of local and global image statistics models the defined quality criteria and automatically produces reliable and objective results in determining the image quality of retinal fundus photos. © 2010 CARS.

Automatic No-Reference Quality Assessment for Retinal Fundus Images Using Vessel Segmentation - Köhler, Thomas; Budai, Attila; Kraus, Martin; Odstrcilik, Jan; Michelson, Georg; Hornegger, Joachim (2013 26th IEEE International Symposium on Computer-Based Medical Systems (CBMS), 2013)

Automatic Segmentation of the Optic Radiation using DTI in Glaucoma Patients - El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Engelhorn, Tobias; Dörfler, Arnd; Wärntges, Simone; Michelson, Georg (Computational Vision and Medical Image Processing - VipIMAGE 2009, 2009)

Automatic Segmentation of the Optic Radiation Using DTI in Healthy Subjects and Patients with Glaucoma - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Computational Vision and Medical Image Processing, 2011)

Automatische Qualitätsmessung von Retina-Fundusbildern - Paulus, Jan; Bock, Rüdiger; Meier, Jörg; Michelson, Georg; Hornegger, Joachim (Bildverarbeitung für die Medizin 2009 - Algorithmen, Systeme, Anwendungen, 2009)

A Very Rare and Easily Missed Macular Disease - Huchzermeyer, Cord; Bergua, A. (Klinische Monatsblätter für Augenheilkunde, 2015)
EVALuna2:21231

A Virtual Environment Based Evaluating System for Goalkeepers Stereopsis Performance in Soccer - Paulus, Jan; Hornegger, Joachim; Schmidt, Michael; Eskofier, Björn; Michelson, Georg (Sportinformatik 2012, 2012)

Basal nitric oxide activity is an independent determinant of arteriolar structure in the human retinal circulation - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Schneider, Markus; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2011)
Experimental data indicate that nitric oxide might play a role in structure and remodeling of peripheral small arteries and arterioles. We hypothesized that retinal arteriolar structure is modulated by basal nitric oxide activity.The study cohort comprised 97 male untreated patients with normal and elevated blood pressure but without clinical evidence for cardiovascular disease. The changes of retinal capillary blood flow (RCF) to nitric oxide synthase inhibitor N-monomethyl-L-arginine (L-NMMA), that reflects basal nitric oxide activity of retinal vasculature, and to flicker light, that in part nitric oxide dependently provokes retinal vasodilatation, and parameters of retinal arteriolar structure, for example wall-to-lumen ratio (WLR), were assessed noninvasively and in vivo by scanning laser Doppler flowmetry.Participants were stratified according to the median WLR of retinal arterioles into two groups. In the group with WLR above the median RCF in response to infusion of L-NMMA decreased to a smaller extent (-3.82 ± 26 vs. -26.0 ± 45 arbitrary units and -0.83 ± 8.4 vs. -5.88 ± 11%, P = 0.004 and P = 0.015; respectively), whereas RCF in response to flicker light did not differ significantly compared to the counter group (22.2 ± 56 vs. 39.8 ± 51 arbitrary units and 7.42 ± 15 vs. 11.9 ± 14%, P = 0.112 and P = 0.149). In the whole study cohort WLR of retinal arterioles was related with the decrease of RCF to L-NMMA infusion [when expressed in absolute terms (r = 0.252, P = 0.013) and in percentage change (r = 0.213, P = 0.036)] and inversely related with the change of RCF to flicker light [when expressed in absolute terms (r = -0.203, P = 0.048) but not clearly when expressed in percentage change (r = -0.161, P = 0.120)]. Adjustment for major cardiovascular risk factors and changes of systemic hemodynamics in response to L-NMMA infusion revealed an independent relationship between WLR of retinal arterioles and percentage change of RCF to L-NMMA infusion (ß = 0.300, P = 0.007).Basal nitric oxide activity emerged as an independent determinant of arteriolar remodeling in the human retinal circulation in vivo.
EVALuna2:3475

Baseline magnetic resonance imaging of the optic nerve provides limited predictive information on short-term recovery after acute optic neuritis - Berg, Sebastian; Kaschka, Iris; Utz, Kathrin S.; Huhn, Konstantin; Laemmer, Alexandra; Lämmer, Robert; Waschbisch, Anne; Kloska, Stephan; Lee, De-Hyung; Dörfler, Arnd; Linker, Ralf (PLoS ONE, 2015)
In acute optic neuritis, magnetic resonance imaging (MRI) may help to confirm the diagnosis as well as to exclude alternative diagnoses. Yet, little is known on the value of optic nerve imaging for predicting clinical symptoms or therapeutic outcome.To evaluate the benefit of optic nerve MRI for predicting response to appropriate therapy and recovery of visual acuity.Clinical data as well as visual evoked potentials (VEP) and MRI results of 104 patients, who were treated at the Department of Neurology with clinically definite optic neuritis between December 2010 and September 2012 were retrospectively reviewed including a follow up within 14 days.Both length of the Gd enhancing lesion (r = -0.38; p = 0.001) and the T2 lesion (r = -0.25; p = 0.03) of the optic nerve in acute optic neuritis showed a medium correlation with visual acuity after treatment. Although visual acuity pre-treatment was little but nonsignificantly lower if Gd enhancement of the optic nerve was detected via orbital MRI, improvement of visual acuity after adequate therapy was significantly better (0.40 vs. 0.24; p = 0.04). Intraorbitally located Gd enhancing lesions were associated with worse visual improvement compared to canalicular, intracranial and chiasmal lesions (0.35 vs. 0.54; p = 0.02).Orbital MRI is a broadly available, valuable tool for predicting the improvement of visual function. While the accurate individual prediction of long-term outcomes after appropriate therapy still remains difficult, lesion length of Gd enhancement and T2 lesion contribute to its prediction and a better short-term visual outcome may be associated with detection and localization of Gd enhancement along the optic nerve.
EVALuna2:21236

Bias associated with the use of maximum, minimum, or range of a number of intraocular pressure measurements - Huchzermeyer, Cord; Horn, Folkert; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2011)
EVALuna2:21008

Bilateral Acute Macular Neuroretinopathy (AMN) after COVID-19 and its Clinical Course - Bartsch, Alexander; Skornia, Adam; Mardin, Christian Y.; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2023)
Acute macular neuroretinopathy (AMN) is a rare disease entity. It is mainly observed in young women with a history of influenza-like infection or who have been taking oral contraceptives for several years. Patients typically describe subjective visual deterioration and mono- or bilateral paracentral relative scotomas. In some cases, funduscopic ophthalmic examination may reveal subtle sharply demarcated flat lesions of reddish-brown or orange colour in the macular region. Diagnosis is usually made by near-infrared fundus imaging which shows hyporeflective areas, and SD-OCT imaging which manifests changes in the outer retinal layers. In the following, three patient cases with bilateral AMN are described which occurred in direct temporal relationship to a recent SARS-CoV-2 infection.
CRIS-Team WoS Importer:2023-06-02
Keywords: akute makuläre; Neuroretinopathie; SD-OCT; Retina; COVID-19; SARS-CoV-2

Bilateral Orbital IgG4-Related Disease with Systemic and Corneal Involvement Showing an Excellent Response to Steroid and Rituximab Therapy: Report of a Case with 11 Years Follow-Up - Berta, Agnes I.; Agaimy, Abbas; Braun, Joachim M.; Manger, Bernhard; Kruse, Friedrich Eduard; Holbach, Leonard (Orbit, 2015)
IgG4-related disease is a newly recognized fibro-inflammatory condition. The purpose of this report is to present a patient with 11 years of follow-up, who revealed characteristic features of IgG4-related disease with systemic, orbital and corneal involvement and showed a favorable response to steroids and rituximab treatment.
EVALuna2:6708

Bilateral posterior persistent hyperplastic primary vitreous - Hohberger, B.; Knorr, H. L.J.; Mardin, Christian Y.; Trollmann, Regina; von Marchtaler, Philipp; Gusek-Schneider, G. ‑C (Ophthalmologe, 2017)
Bilateral persistent hyperplastic primary vitreous (PHPV) represents a rare entity of a congential malformation. This casuistic presents for the first time in the German literature the case of a 4-month-old child with bilateral posterior PHPV.
EVALuna2:21353

Bilateral vision loss in a patient with weight loss and neurologic symptoms - La Mancusa, Antonia; Rech, J.; Harrer, Thomas; Knorr, H.; Bergua, A. (Klinische Monatsblätter für Augenheilkunde, 2011)
EVALuna2:12701

Binocular vision training for professional athletes - Kutzner, Benedikt; Ring, Matthias; Michelson, Georg (Ophthalmologe, 2022)
Background Optimal visual abilities including stereo acuity seem to be an important issue in sports. There is increasing evidence that stereo acuity can be sustainably improved by digital vision training even for people with good stereo acuity. Study design and test methods In this study 31 male and female tennis players (professionals, young professionals, coaches and former professionals) completed at least 6 training units each with 192 dynamic stereoscopic tasks (N = 1152) within 6 weeks including a 4-option test with different levels of difficulty on a 3D screen at a distance of 5 m. The parameter reaction time and correctness at 15-300 arcseconds was determined. For a more precise representation of the reaction time improvement as a function of the difficulty level, the parameter reaction time increase per stereo disparity reduction (ReST) was defined. Results Reaction time to 15 arcsecond stimuli significantly decreased from 3.9 s to 1.6 s (59%) as a result of digital vision training. The correctness at 30 arcsecond stimuli significantly increased by 23%. Discussion The observed improvement in reaction time during vision training did not result in decreasing correctness when answering the visual questions. This represents an overall improvement in stereo vision. Conclusion Dynamic visual training over 6 weeks improves stereoscopic performance including stereo acuity, response time and correctness.
CRIS-Team WoS Importer:2022-02-11

Biomaterialien als DMEK-& Amnionmembranersatz - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (2. Baltic Sea Eye Conference, Rostock (Deutschland), 2020, 2020)

Biomechanical assessment of healthy and keratoconic corneas (with/without crosslinking) using dynamic ultrahigh-speed Scheimpflug technology and the relevance of the parameter (A1L-A2L) - Fuchsluger, Thomas; Brettl, Susanne; Geerling, Gerd; Kaisers, Wolfgang; Zeitz, Philipp Franko (British Journal of Ophthalmology, 2019)
Aims To examine corneal biomechanics in healthy and keratoconic eyes, with or without crosslinking obtained by ultrahigh-speed Scheimpflug measurements (Corvis ST).
CRIS-Team WoS Importer:2019-07-02

Blind Source Separation of Different Retinal Pulsatile Patterns from Simultaneous Long-term Binocular Ophthalmoscopic Video-records - Labounkova, Ivana; Labounek, Rene; Odstrcilik, Jan; Hracho, Michal; Nestrasil, Igor; Tornow, Ralf-Peter; Kolar, Radim (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2019)
Optical imaging of retinal hemodynamic function is an important part of ophthalmologic research. Development and inventing of imaging devices and data analysis methods are both just in progress. The current study innovatively implements two blind source separation (BSS) techniques (i.e. spatial Principal Component Analysis - sPCA; and spatial Independent Component Analysis - sICA) in application of an automatic detection and segmentation of a distinct Optic Disc (OD) areas with different hemodynamic properties from a simultaneous binocular video-ophthalmoscopic records. Both methods detected 3 different spatial patterns mostly symmetric over both eyes stable and reproducible over investigated participants, i.e. central Spontaneous Vessel Pulsations (SVPs), inner OD intensity pulsations and other OD pulsations. Dynamics of all mentioned patterns has a periodic character with similar main frequency (possibly corresponding to subject-specific heart rate) but shifted phase decreasing patterns' mutual high cross-correlations. The sICA estimates a higher rate of phase shifts than sPCA.
CRIS-Team Scopus Importer:2020-02-21

Blind Source Separation of Retinal Pulsatile Patterns in Optic Nerve Head Video-Recordings - Labounkova, Ivana; Labounek, Rene; Nestrasil, Igor; Odstrcilik, Jan; Tornow, Ralf-Peter; Kolar, Radim (IEEE Transactions on Medical Imaging, 2020)
Dynamic optical imaging of retinal hemodynamics is a rapidly evolving technique in vision and eye-disease research. Video-recording, which may be readily accessible and affordable, captures several distinct functional phenomena such as the spontaneous venous pulsations (SVP) of central vein or local arterial blood supply etc. These phenomena display specific dynamic patterns that have been detected using manual or semiautomated methods. We propose a pioneering concept in retina video-imaging using blind source separation (BSS) serving as an automated localizer of distinct areas with temporally synchronized hemodynamics. The feasibility of BSS techniques (such as spatial principal component analysis and spatial independent component analysis) and K-means based post-processing method were successfully tested on the monocular and binocular video-ophthalmoscopic (VO) recordings of optic nerve head (ONH) in healthy subjects. BSSs automatically detected three spatially distinct reproducible areas, i.e. SVP, optic cup pulsations (OCP) that included areas of larger vessels in the nasal part of ONH, and “other” pulsations (OP). The K-means post-processing reduced a spike noise from the patterns’ dynamics while high linear dependence between the non-filtered and post-processed signals was preserved. Although the dynamics of all patterns were heart rate related, the morphology analysis demonstrated significant phase shifts between SVP and OCP, and between SVP and OP. In addition, we detected low frequency oscillations that may represent respiratory-induced effects in time-courses of the VO recordings.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Blind Source Separation; ICA; Independent Component Analysis; Optic Nerve Head; PCA; Principal Component Analysis; Retina; Spontaneous Venous Pulsations; Video-ophthalmoscopy

Blockade of CCR7 leads to decreased dendritic cell migration to draining lymph nodes and promotes graft survival in low-risk corneal transplantation - Hos, D.; Dörrie, Jan; Schaft, Niels; Bock, F.; Notara, M.; Kruse, Friedrich; Krautwald, S.; Cursiefen, C.; Bachmann, B. O. (Experimental Eye Research, 2016)
The chemokine receptor CCR7 is essential for migration of mature dendritic cells (DCs) to the regional lymph nodes, and it has been shown that blocking of CCR7 improves graft survival after high-risk corneal transplantation in vascularized recipient corneas. However, it is so far unknown whether blocking of CCR7 reduces migration of DCs from the avascular cornea to the draining lymph nodes and whether this leads to improved graft survival also in the low-risk setting of corneal transplantation, which accounts for the majority of perforating transplantations performed. Therefore, in this study, pellets containing Freund's adjuvant and bovine serum albumin (BSA) conjugated to Alexa488 fluorescent dye were implanted into the corneal stroma of BALB/c mice to analyze antigen uptake by corneal DCs and their migration to the regional lymph nodes. After pellet implantation, mice were either treated by local administration of a CCR7 blocking fusion protein that consisted of CCL19 fused to the Fc part of human IgG1 or a control-IgG. In vivo fluorescence microscopy showed uptake of Alexa488-conjugated BSA by corneal DCs within 8 h. Furthermore, analysis of single cell suspensions of draining lymph nodes prepared after 48 h revealed that 2.1 ± 0.3% of CD11c(+) cells were also Alexa488(+). Importantly, DC migration was significantly reduced after topical administration of CCL19-IgG (1.2 ± 0.2%; p < 0.05). To test the effect of CCR7 blockade on graft rejection after allogeneic low-risk keratoplasty, corneal transplantations were performed using C57BL/6-mice as donors and BALB/c-mice as recipients. Treatment mice received two intraperitoneal loading doses of CCL19-IgG prior to transplantation, followed by local treatment with CCL19-IgG containing eye drops for the first two weeks after transplantation. Control mice received same amounts of control-IgG. Kaplan-Meier survival analysis showed that in the CCL19-IgG treated group, 76% of the grafts survived through the end of the 8 week observation period, whereas 38% of the grafts survived in the control group (p < 0.05). Taken together, our study shows that blockade of CCR7 reduces the migration of mature corneal DCs to the draining lymph nodes and leads to improved graft survival in low-risk corneal transplantation.
EVALuna2:19600

Blockade of insulin receptor substrate-1 inhibits corneal lymphangiogenesis - Hos, Deniz; Regenfuss, Birgit; Bock, Felix; Onderka, Jasmine; Cursiefen, Claus (Investigative Ophthalmology & Visual Science, 2011)
To analyze whether insulin receptor substrate (IRS-1) is involved in lymphatic vessel development and whether IRS-1 blockade can inhibit lymphangiogenesis in vivo.The impact of IRS-1 blockade by GS-101 (Aganirsen), an antisense oligonucleotide against IRS-1, on lymphatic endothelial cell (LEC) proliferation was assessed by ELISA. Furthermore, the effect of IRS-1 blockade on prolymphangiogenic growth factor expression by LECs and macrophages (peritoneal exudate cells) was tested by real-time PCR. The mouse model of inflammatory corneal neovascularization was used to analyze the effect of IRS-1 blockade in vivo: after corneal suture placement, mice were treated with GS-101 eye drops (twice daily afterwards for 1 week, 5 ?L per drop; 50, 100, or 200 ?M). Afterward, corneal wholemounts were prepared and stained for blood and lymphatic vessels.Blockade of IRS-1 by GS-101 inhibited LEC proliferation dose dependently. GS-101 led to decreased VEGF-A expression levels in LECs, whereas VEGF-C, VEGF-D, and VEGFR3 showed no significant change. In macrophages, VEGF-A expression levels were also inhibited by IRS-1 blockade. Additionally, GS-101 strongly inhibited macrophage-derived VEGF-C, VEGF-D, and VEGFR3 expression. In vivo, corneal hemangiogenesis was significantly inhibited when used at a concentration of 200 ?M (by 17%; P < 0.01). Corneal lymphangiogenesis was significantly inhibited when used at a dose of 100 ?M (by 21%; P < 0.01), and the highest used dose (200 ?M) showed an even stronger inhibition (by 28%; P < 0.001).Blockade of IRS-1 inhibits not only hemangiogenesis but also lymphangiogenesis. To the authors' knowledge, this is the first evidence that IRS-1 is involved in the molecular pathway leading to lymphangiogenesis.
EVALuna2:21053

Blue-Yellow VEP with Projector-Stimulation in Glaucoma - Dussan Molinos, Laura; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2021)
Background and aim In the past, increased latencies of the blue-on-yellow pattern visually evoked potentials (BY-VEP), which predominantly originate in the koniocellular pathway, have proven to be a sensitive biomarker for early glaucoma. However, a complex experimental setup based on an optical bench was necessary to obtain these measurements because computer screens lack sufficient temporal, spatial, spectral, and luminance resolution. Here, we evaluated the diagnostic value of a novel setup based on a commercially available video projector.
CRIS-Team WoS Importer:2021-12-03

Bone marrow cells and CD117-positive haematopoietic stem cells promote corneal wound healing - Sel, Saadettin; Schilling, Ulf M.; Nass, Norbert; Simm, Andreas; Garreis, Fabian; Knak, Matthias; Storsberg, Joachim; Kaiser, Maja; Kalinski, Thomas; Ehrich, Dirk; Bredehorn-Mayr, Timm; Paulsen, Friedrich (Acta Ophthalmologica, 2012)
Purpose: The present study was conducted to evaluate the therapeutic effects of topically applied bone marrow (BM) cells and CD117-positive haematopoietic stem (CD117(+)) cells on alkali-induced corneal ulcers. Methods: Bone marrow cells and CD117(+) cells were isolated from syngenic mice and labelled with an intracellular cell tracer. Defined corneal wounds were produced in 89 eyes of syngenic mice and allowed to partially heal in vivo for 6 hr. The alkali-burned eyes were enucleated 6 hr postinjury and randomly divided into three groups. Control group (33 eyes) was incubated with medium only. The treatment groups received either BM cells (30 eyes) or CD117(+) cells (26 eyes) suspended in medium. Re-epithelialization process of corneal defects was qualitatively and quantitatively assessed and statistically analysed. The corneas were examined by histological and immunohistochemical methods. Results: We found that the re-epithelialization of corneal wounds in both treatment groups was significantly accelerated as compared to the control group. During the follow-up period (85 hr), the corneal transparency was comparable in all groups. Morphological investigations of corneas from control and treatment group showed no evident differences in the phenotype of the regenerated epithelium. Additionally, corneas in the treatment groups were devoid of donor-derived BM cells and CD117(+) cells, respectively. Conclusions: This study provides evidence that topical application of BM cells or CD117(+) cells can be used to reconstruct corneal surfaces. Because neither BM cells nor CD117(+) cells were integrated into the corneal epithelium, we suggest that soluble factors could be responsible for the positive effect of BM cells and CD117(+) cells on corneal wound healing.
EVALuna2:4383

Brittle-Cornea-Syndrom Typ 1 durch Compound-Heterozygotie zweier Mutationen im ZNF469-Gen - Menzel-Severing, Johannes; Meiller, Ralph; Kraus, Cornelia; Trollmann, Regina; Atalay, Deniz (Ophthalmologe, 2019)
We report the case of a 3-year-old boy presenting with bilateral keratoglobus and blue sclera in addition to hallux valgus, arachnodactyly, small joint hypermobility, mitral valve dysfunction and a history of generalized muscular hypotonia in early infancy. Molecular genetics provided evidence of two pathogenic mutations in the ZNF469 gene (compound heterozygosity) leading to the diagnosis of brittle cornea syndrome type 1. In addition to neuropediatric care, spectacles were prescribed to correct refractive error and for ocular protection. Owing to the thin cornea and sclera, eye injuries are the main cause for irreversible visual loss in this disease.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Blue sclera; Connective tissue disease; Hereditary eye disease; Keratoglobus; Pediatric ophthalmology

Bruch's Membrane Opening Minimum Rim Width and Retinal Nerve Fiber Layer Thickness in a Normal White Population: A Multicenter Study - Chauhan, Balwantray C.; Danthurebandara, Vishva M.; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Scheuerle, Alexander F.; Burgoyne, Claude F. (Ophthalmology, 2015)
Conventional optic disc margin-based neuroretinal rim measurements lack a solid anatomic and geometrical basis. An optical coherence tomography (OCT) index, Bruch's membrane opening minimum rim width (BMO-MRW), addresses these deficiencies and has higher diagnostic accuracy for glaucoma. We characterized BMO-MRW and peripapillary retinal nerve fiber layer thickness (RNFLT) in a normal population.Multicenter cross-sectional study.Normal white subjects.An approximately equal number of subjects in each decade group (20-90 years of age) was enrolled in 5 centers. Subjects had normal ocular and visual field examination results. We obtained OCT images of the optic nerve head (24 radial scans) and peripapillary retina (1 circular scan). The angle between the fovea and BMO center (FoBMO angle), relative to the horizontal axis of the image frame, was first determined and all scans were acquired and analyzed relative to this eye-specific FoBMO axis. Variation in BMO-MRW and RNFLT was analyzed with respect to age, sector, and BMO shape.Age-related decline and between-subject variability in BMO-MRW and RNFLT.There were 246 eyes of 246 subjects with a median age of 52.9 years (range, 19.8-87.3 years). The median FoBMO angle was -6.7° (range, 2.5° to -17.5°). The BMO was predominantly vertically oval with a median area of 1.74 mm(2) (range, 1.05-3.40 mm(2)). Neither FoBMO angle nor BMO area was associated with age or axial length. Both global mean BMO-MRW and RNFLT declined with age at a rate of -1.34 ?m/year and -0.21 ?m/year, equivalent to 4.0% and 2.1% loss per decade of life, respectively. Sectorially, the most rapid decrease occurred inferiorly and the least temporally; however, the age association was always stronger with BMO-MRW than with RNFLT. There was a modest relationship between mean global BMO-MRW and RNFLT (r = 0.35), whereas sectorially the relationship ranged from moderate (r = 0.45, inferotemporal) to nonexistent (r = 0.01, temporal).There was significant age-related loss of BMO-MRW in healthy subjects and notable differences between BMO-MRW and RNFLT in their relationship with age and between each other. Adjusting BMO-MRW and RNFLT for age and sector is important in ensuring optimal diagnostics for glaucoma.
EVALuna2:21224

Bruch's membrane thickness in high myopia - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2014)
To measure the thickness of Bruch's membrane (BM) and assess its associations with axial length.Using a light microscope, we measured the thickness of Bruch's membrane, choroid and sclera on horizontal anterior-posterior histological sections of enucleated human globes.The study included 54 eyes (42 with glaucomatous optic nerve damage; 23 globes with axial length >=26.5 mm) with a mean axial length of 26.6 ± 3.3 mm (range: 21.0-34.0 mm). In the non-highly myopic eyes, BM was significantly thicker at the pars plana region (6.6 ± 1.1 ?m) than at the equator (4.1 ± 1.5 ?m; p < 0.001), the midpoint between equator and posterior pole (4.1 ± 1.5 ?m; p < 0.001), the parapapillary region (4.5 ± 1.0 ?m; p = 0.006) or the posterior pole (4.4 ± 1.7 ?m; p = 0.001). At any measurement location at or behind the ora serrata, BM thickness did not differ significantly (all p >= 0.40) between the non-glaucomatous non-highly myopic group and the glaucomatous non-highly myopic group, or between the non-highly myopic group and the highly myopic group. BM thickness at any location was not significantly (all p > 0.45) related to axial length. The ratio of scleral thickness to BM thickness and the ratio of choroidal thickness to BM thickness significantly decreased with longer axial length for measurements taken behind the equator.BM is physiologically thickest in the pars plana, with no major thickness differences between locations at or behind the ora serrata. In contrast to choroidal and scleral thickness, BM thickness is not significantly related to axial length. Axially elongated eyes have a normal BM thickness, despite a thinned choroid and sclera.
EVALuna2:21191

"Bubble-in-the-Roll" Technique Using the Endoject DMEK Injector: Influence of the Air Bubble on Endothelial Cell Loss - Akbaba, Yasemin; Weller, Julia M.; Rössler, Kathrin; Armitage, W. John; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2017)
To evaluate the impact of the air bubble on endothelial cell loss using the "bubble-in-the-roll" technique during Descemet membrane endothelial keratoplasty (DMEK).Twenty DMEK grafts not suitable for transplantation were manually prepared from organ-cultured corneoscleral discs and injected into culture media using the Endoject DMEK injector (Medicel AG, Wolfhalden, Switzerland). Based on the injection method, the grafts were divided into 2 groups: In group A (n = 10), a small air bubble was placed inside the graft roll while it was in the injector. In group B (n = 10), the grafts were injected without an air bubble inside the graft roll. Main outcome measures included endothelial cell density (ECD) after graft stripping and graft injection.There were no statistically significant differences between groups A and B in donor age, storage duration, and donor ECD. ECD decreased from 1929 ± 145 cells/mm to 1796 ± 303 cells/mm after graft stripping in group A and from 1801 ± 226 cells/mm to 1709 ± 290 cells/mm in group B. ECD after graft injection further decreased to 1683 ± 291 cells/mm in group A and to 1651 ± 292 cells/mm in group B. Endothelial cell loss after graft stripping and graft injection was not statistically significant between groups A and B (P = 0.29 and P = 1, respectively).The bubble-in-the-roll technique for injection and unfolding of the graft is a safe method for graft delivery into the anterior chamber guaranteeing orientation of the graft without harming the endothelium.
EVALuna2:21346

Canine multifocal retinopathy in the Australian Shepherd: a case report - Hoffmann, Ingo; Guziewicz, Karina E.; Zangerl, Barbara; Aguirre, Gustavo D.; Mardin, Christian Y. (Veterinary Ophthalmology, 2012)
A 1-year-old Australian Shepherd (AS) was presented for a routine hereditary eye examination. During the examination multiple raised, brown to orange lesions were noted in the fundus, which could not be attributed to a known retinal disease in this breed. As they clinically most closely resembled canine multifocal retinopathy (cmr) and no indication of an acquired condition was found, genetic tests for BEST1 gene mutations were performed. These showed the dog to be homozygous for the cmr1 (C73T/R25X) gene defect. Furthermore, ultrasound (US), electroretinography (ERG), and optical coherence tomography were performed, confirming changes typical for cmr. Subsequently, the AS pedigree members were genetically and clinically tested, demonstrating autosomal recessive inheritance with no clinical symptoms in carrier animals, as was previously described for cmr. To our knowledge, this is the first reported case of canine multifocal retinopathy in the AS breed. Further investigations are under way.
EVALuna2:21067

Can we optimize the refractive target in triple Descemet membrane endothelial keratoplasty in the fellow eye after urgery in the first eye? - Augustin, Victor A.; Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (2018)
EVALuna2:34740

Can we predict the refractive outcome after triple Descemet membrane endothelial keratoplasty? - Augustin, Victor A.; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (European Journal of Ophthalmology, 2019)
Purpose: To analyze and correlate corneal parameters with refractive shift after Descemet membrane endothelial keratoplasty combined with cataract surgery (triple Descemet membrane endothelial keratoplasty). Methods: This single-center retrospective observational case series included 152 eyes of 152 consecutive patients undergoing triple Descemet membrane endothelial keratoplasty in the first eye for Fuchs endothelial corneal dystrophy. Patients were examined preoperatively, as well as at 3, 6, and 12 months after surgery. The main outcome measures were: refractive shift (predicted refractive outcome based on intraocular lens calculation compared to actual postoperative refractive outcome), central corneal thickness, corneal volume, anterior and posterior corneal curvature, and corneal densitometry. These parameters were analyzed and correlated with the refractive shift after surgery. Results: After 3 months from surgery, a mean refractive shift of +1.12 +/- 1.10 D was observed and remained stable until the last follow-up at 12 months (+1.24 +/- 1.07 D). Correlation analysis showed a weak but significant positive correlation between refractive shift and preoperative posterior curvature (rho = 0.314; p = 0.002) or preoperative posterior densitometry (rho = 0.227; p = 0.008). No correlation was found between refractive shift and preoperative central corneal thickness, corneal volume, anterior curvature, or anterior/mid-cornea densitometry. Conclusion: Changes of the posterior cornea may have an influence on the refractive shift. Patients with flatter posterior corneal curvature or higher posterior corneal density seem to exhibit a higher hyperopic shift. The weak correlations indicate a poor predictive value of any preoperative parameter used in our study.
CRIS-Team WoS Importer:2019-04-09

Case Report: Neutralization of Autoantibodies Targeting G-Protein-Coupled Receptors Improves Capillary Impairment and Fatigue Symptoms After COVID-19 Infection - Hohberger, Bettina; Harrer, Thomas; Mardin, Christian; Kruse, Friedrich; Hoffmanns, Jakob; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; Szewczykowski, Charlotte; Schottenhamml, Julia; Kräter, Martin; Bergua, Antonio; et al. (Frontiers in Medicine, 2021)
Clinical features of Coronavirus disease 2019 (COVID-19) are caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Acute infection management is a substantial healthcare issue, and the development of long-Covid syndrome (LCS) is extremely challenging for patients and physicians. It is associated with a variety of characteristics as impaired capillary microcirculation, chronic fatigue syndrome (CFS), proinflammatory cytokines, and functional autoantibodies targeting G-protein-coupled receptors (GPCR-AAbs). Here, we present a case report of successful healing of LCS with BC 007 (Berlin Cures, Berlin, Germany), a DNA aptamer drug with a high affinity to GPCR-AAbs that neutralizes these AAbs. A patient with a documented history of glaucoma, recovered from mild COVID-19, but still suffered from CFS, loss of taste, and impaired capillary microcirculation in the macula and peripapillary region. He was positively tested for various targeting GPCR-AAbs. Within 48 h after a single BC 007 treatment, GPCR-AAbs were functionally inactivated and remained inactive during the observation period of 4 weeks. This observation was accompanied by constant improvement of the fatigue symptoms of the patient, taste, and retinal capillary microcirculation. Therefore, the removal of GPCR-AAb might ameliorate the characteristics of the LCD, such as capillary impairment, loss of taste, and CFS.
CRIS-Team Scopus Importer:2021-12-17
Keywords: BC 007; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; glaucoma; long-COVID syndrome; OCT angiography

Cavernous sinus thrombosis as a rare cause of exophthalmos in childhood : A case report - Kamawal, A.; Schmidt, M. A.; Rompel, O.; Gusek-Schneider, G. C.; Mardin, C. Y.; Trollmann, Regina (Ophthalmologe, 2016)
Complications of acute bacterial sinusitis mostly occur in children and adolescents. In particular, intracranial spread of the infection can lead to severe even fatal courses of the disease. This article is a case report about a 13-year-old boy suffering from left-sided headache, meningismus and exophthalmos as presenting symptoms. Cranial magnetic resonance imaging (MRI) showed merely right-sided sphenoid sinusitis; however, the diffusion-weighted MRI sequence indicated a left-sided cavernous sinus thrombosis, which could be confirmed by computed tomography (CT) angiography. Cerebrospinal fluid diagnostics showed significant leukocytosis confirming secondary meningitis. Finally, exophthalmos was explained by parainfectious cavernous sinus thrombosis and periorbital edema. This case report highlights the importance of extended and specific diagnostic imaging in cases of clinically suspected complications in children and adolescents with sinusitis and the diagnostic significance of diffusion-weighted MRI.
EVALuna2:21321

Ccdc66 null mutation causes retinal degeneration and dysfunction - Gerding, Wanda M.; Schreiber, Sabrina; Schulte-Middelmann, Tobias; Marques, Andreia De Castro; Atorf, Jenny; Akkad, Denis A.; Dekomien, Gabriele; Kremers, Jan; Dermietzel, Rolf; Gal, Andreas; Ruelicke, Thomas; Ibrahim, Saleh; et al. (Human Molecular Genetics, 2011)
Retinitis pigmentosa (RP) is a group of human retinal disorders, with more than 100 genes involved in retinal degeneration. Canine and murine models are useful for investigating human RP based on known, naturally occurring mutations. In Schapendoes dogs, for example, a mutation in the CCDC66 gene has been shown to cause autosomal recessively inherited, generalized progressive retinal atrophy (gPRA), the canine counterpart to RP. Here, a novel mouse model with a disrupted Ccdc66 gene was investigated to reveal the function of protein CCDC66 and the pathogenesis of this form of gPRA. Homozygous Ccdc66 mutant mice lack retinal Ccdc66 RNA and protein expression. Light and electron microscopy reveal an initial degeneration of photoreceptors already at 13 days of age, followed by a slow, progressive retinal degeneration over months. Retinal dysfunction causes reduced scotopic a-wave amplitudes, declining from 1 to 7 months of age as well as an early reduction of the photopic b-wave at 1 month, improving slightly at 7 months, as evidenced by electroretinography. In the retina of the wild-type (WT) mouse, protein CCDC66 is present at highest levels after birth, followed by a decline until adulthood, suggesting a crucial role in early development. Protein CCDC66 is expressed predominantly in the developing rod outer segments as confirmed by subcellular analyses. These findings illustrate that the lack of protein CCDC66 causes early, slow progressive rod-cone dysplasia in the novel Ccdc66 mutant mouse model, thus providing a sound foundation for the development of therapeutic strategies.
EVALuna2:21029

Cell Adhesion Molecules and Stem Cell-Niche-Interactions in the Limbal Stem Cell Niche - Polisetti, Naresh; Zenkel, Matthias; Menzel-Severing, Johannes; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Stem Cells, 2016)
Interactions between stem cells and their microenvironment are critical for regulation and maintenance of stem cell function. To elucidate the molecular interactions within the human limbal epithelial stem/progenitor cell (LEPC) niche, which is essential for maintaining corneal transparency and vision, we performed a comprehensive expression analysis of cell adhesion molecules (CAMs) using custom-made quantitative real-time polymerase chain reaction (qRT-PCR) arrays and laser capture-microdissected LEPC clusters, comprising LEPCs, melanocytes, mesenchymal cells, and transmigrating immune cells. We show that LEPCs are anchored to their supporting basement membrane by the laminin receptors ?3?1 and ?6?4 integrin and the dystroglycan complex, while intercellular contacts between LEPCs and melanocytes are mediated by N-, P-, and E-cadherin together with L1-CAM, a member of the immunoglobulin superfamily (Ig)CAMs. In addition to the LEPC-associated heparan sulfate proteoglycans syndecan-2, glypican-3, and glypican-4, the IgCAM members ICAM-1 and VCAM-1 were found to be variably expressed on LEPCs and associated niche cells and to be dynamically regulated in response to chemokines such as interferon-? to enhance interactions with immune cells. Moreover, junctional adhesion molecule JAM-C accumulating in the subepithelial limbal matrix, appeared to be involved in recruitment of immune cells, while mesenchymal stromal cells appeared to use the nephronectin receptor integrin ?8 for approaching the limbal basement membrane. In summary, we identified a novel combination of cell surface receptors that may regulate both stable and dynamic cell-matrix and cell-cell interactions within the limbal niche. The findings provide a solid foundation for further functional studies and for advancement of our current therapeutic strategies for ocular surface reconstruction. Stem Cells 2016;34:203-219.
EVALuna2:21232

Cell types and synapses expressing the snare complex regulating proteins complexin 1 and complexin 2 in mammalian retina - Lux, Uwe; Ehrenberg, Johanna; Joachimsthaler, Anneka; Atorf, Jenny; Pircher, Bianca; Reim, Kerstin; Kremers, Jan; Gießl, Andreas; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2021)
Complexins (Cplxs) 1 to 4 are components of the presynaptic compartment of chemical synapses where they regulate important steps in synaptic vesicle exocytosis. In the retina, all four Cplxs are present, and while we know a lot about Cplxs 3 and 4, little is known about Cplxs 1 and 2. Here, we performed in situ hybridization experiments and bioinformatics and exploited Cplx 1 and Cplx 2 single-knockout mice combined with immunocytochemistry and light microscopy to characterize in detail the cell type and synapse-specific distribution of Cplx 1 and Cplx 2. We found that Cplx 2 and not Cplx 1 is the main isoform expressed in normal and displaced amacrine cells and ganglion cells in mouse retinae and that amacrine cells seem to operate with a single Cplx isoform at their conventional chemical synapses. Surprising was the finding that retinal function, determined with electroretinographic recordings, was altered in Cplx 1 but not Cplx 2 single-knockout mice. In summary, the results provide an important basis for future studies on the function of Cplxs 1 and 2 in the processing of visual signals in the mammalian retina.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Amacrine cells; Complexin 1; Complexin 2; Conventional chemical synapses; Ganglion cells; Horizontal cells; Retina

Center-Surround Interactions in Flicker Perception of Glaucoma Patients - Teixeira, C. E.; Silveira, L. C. L.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual impairment: neuro-ophthalmological disease; visual fields; temporal vision

Central pulse pressure is an independent determinant of vascular remodeling in the retinal circulation - Ott, Christian; Raff, Ulrike; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Hypertension, 2013)
Pulse pressure has been recognized as a risk factor for stroke. Moreover, it was shown that central pulse pressure relates more strongly to vascular disease and outcome than (peripheral) brachial pulse pressure. Because vascular remodeling in the retinal circulation mirrors the 1 in the cerebral circulation and represents an easy, noninvasive possibility to assess microvascular changes in humans, we analyzed the impact of central pulse pressure on retinal vascular structure in humans. The study cohort comprised 135 nondiabetic patients across a wide range of blood pressure values. Parameter of retinal arteriolar remodeling (wall-to-lumen ratio) was assessed noninvasively and in vivo by scanning laser Doppler flowmetry. Central pulse pressure and augmentation index normalized to a heart rate of 75 beats per minute were assessed by pulse wave analysis. Central pulse pressure correlated with wall-to-lumen ratio (r=0.302; P<0.001), central augmentation index normalized to a heart rate of 75 beats per minute correlated with wall-to-lumen ratio (r=0.190; P=0.028), and in accordance pulse pressure amplification (peripheral pulse pressure/central pulse pressure) was negatively correlated with wall-to-lumen ratio (r=-0.223; P=0.009). In contrast, central mean arterial pressure was not correlated with wall-to-lumen ratio (r=0.110; P=0.203). Multiple regression analysis revealed an independent relationship between wall-to-lumen ratio and central pulse pressure (?=0.277; P=0.009), but not with other classical cardiovascular risk factors. Thus, central pulse pressure, indicative of changes in large conduit arteries is an independent determinant of vascular remodeling in small retinal arterioles. Such a relationship indicates a coupling and crosstalk between the microvascular and macrovascular changes attributable to hypertension.
EVALuna2:3610

Cereblon is expressed in the retina and binds to voltage-gated chloride channels. - Hohberger, Bettina; Enz, Ralf (FEBS letters, 2009)
UnivIS-Import:2018-09-11:Pub.2009.med.IB.profes_1.cerebl
Keywords: Cereblon; CIC-1; CIC-2; CRBN; Protein interaction; Retina

Cerebral Microinfarcts in Primary Open-Angle Glaucoma Correlated With DTI-Derived Integrity of Optic Radiation - Schoemann, Johannes; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; El-Rafei, Ahmed Mohamed Ibrahim; Michelson, Georg (Investigative Ophthalmology & Visual Science, 2014)
To evaluate the correlation between the extent of cerebral white matter lesions (WMLs) and the integrity of the visual pathway represented by fractional anisotropy (FA) in patients with primary open-angle glaucoma (POAG).This case-control study included a total of 61 German patients (39 POAG patients, 22 controls) matched for age and sex. Fractional anisotropy of the optic radiation was determined by 3-Tesla diffusion tensor imaging. White matter lesions and brain volumes were manually measured by using a T2-weighted, 3-D fluid-attenuated inversion recovery sequence.In POAG patients WML volumes were significantly (P = 0.04) increased in the subcortical area. This applied for both absolute and relative units to the specific patient's brain volume, compared to controls. The WML volumes were significantly (P = 0.003) greater in middle-aged (40-59 years) POAG patients than control patients. In controls there was a significant age correlation of WML volumes in the total brain, subcortical, and optic radiation regions of interest. There was a significant correlation between FA and WML in POAG regarding the total brain, the periventricular region, and the optic radiation in both hemispheres. In POAG, FA left and right optic radiation correlated significantly with age (P = 0.002).We were able to demonstrate that (1) POAG patients aged 40 to 60 years had higher volumes of cerebral microinfarcts and (2) POAG patients showed a significant correlation between cerebral microinfarcts and degeneration of the optic radiation. This indicates that cerebral microinfarcts might be an intracerebral risk factor for glaucomatous optic nerve atrophy.
EVALuna2:21212

Changes in perceived temporal variation due to context: contributions from two distinct neural mechanisms - D'Antona, Anthony D.; Kremers, Jan; Shevell, Steven K. (Vision research, 2011)
The percept of a time-varying light depends on the temporal properties of light within the surrounding area. The locus of the neural mechanism mediating this lateral interaction is controversial; neural mechanisms have been posited at the LGN (Kremers et al., 2004) or cortical level (D'Antona & Shevell, 2007). To determine the neural locus, changes in perceived temporal variation were compared with ipsilateral versus contralateral surrounding context. In both cases, a temporally varying central field was viewed within a temporally varying surround; relative phase between center and surround was varied. Perceived modulation depth in the central field depended strongly on the relative phase between center and surround, in both the ipsilateral and contralateral conditions. The results revealed lateral interactions arising from both a weak monocular (plausibly LGN) and a stronger central (cortical) mechanism. The monocular contribution was similar over the range of temporal frequencies tested (approx. 3-12Hz), while the central component showed low-pass temporal-frequency selectivity.
EVALuna2:21031

Changes of Osteopontin in the Aqueous Humor of the DBA2/J Glaucoma Model Correlated with Optic Nerve and RGC Degenerations - Birke, Marco; Neumann, Carolin; Birke, Kerstin; Kremers, Jan; Scholz, Michael (Investigative Ophthalmology & Visual Science, 2010)
PURPOSE. To identify age-dependent regulated aqueous humor (AH) factors in DBA2/J (D2J) mice and to correlate them with optic nerve degeneration and intraocular pressure (IOP) by population and individual analysis.METHODS. AH samples of D2J mice aged 2 (n = 3), 7 (n = 5), and 10 months (n = 14) were analyzed by mouse cytokine antibody array. Ten-month samples were classified into eyes with (D2J+) or without (D2J-) optic neuropathy. Ten-month-old C57/B16 (B6; n = 13) and DBA2/Rj (D2Rj; n = 15) mice served as controls. IOP was recorded from 2 to 10 months. Individual AH osteopontin (OPN) was determined in 31 D2J eyes (10 months) and was correlated with optic neuropathy and IOP. OPN mRNA was detected by in situ hybridization. OPN blood plasma content of D2J and B6 was monitored from 8 to 10 months. Effect of OPN on cell survival in the ganglion cell layer (GCL) or metabolism was tested in ex vivo-cultured D2Rj eyes and murine neuronal precursors.RESULTS. In array analysis, OPN was detected in 10-month-old D2J mice only. They significantly differed between D2J- and D2J+ (P = 0.006). By Western blot analysis, a sevenfold OPN increase in D2J+ was determined compared with B6. Individual analysis confirmed the positive correlation of OPN with optic neuropathy. IOP was not correlated with OPN. OPN blood plasma contents steadily increased with age in D2J. OPN+ cells were detected within the ciliary body of D2J, and OPN+ RGCs were approximate to 30% reduced. OPN treatment inhibited cell degeneration within the GCL in ex vivo-cultured D2Rj eyes and increased the metabolic activity of neuronal precursor cells.CONCLUSIONS. OPN is an age-dependent increased AH factor associated with degeneration of the optic nerve in D2J mice. By modulating the metabolism of neuronal cells, deregulated levels of OPN could be involved in degenerative processes affecting RGCs or optic nerve axons in the D2J model. (Invest Ophthalmol Vis Sci. 2010; 51:5759-5767) DOI:10.1167/iovs.105558

Characterisation of ectasia after penetrating keratoplasty in keratoconus eyes using anterior segment optical coherence tomography - Weller, Julia; Hübner, Lisa; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2023)
Background/aims: Ectasia of the cornea can occur decades after penetrating keratoplasty (PK), especially in keratoconus eyes. The purpose of this study was to characterise ectasia after PK by morphological findings in anterior segment optical coherence tomography (AS-OCT). Methods: In this retrospective, single-centre case series, 50 eyes of 32 patients with a history of PK at an average of 25±10 years earlier were included. The eyes were classified either as ectatic (n=35) or as non-ectatic (n=15). The main parameters included central corneal thickness (CCT), lowest corneal thickness at the interface (LCTI), anterior chamber depth, graft-host interface angle at the thinnest point and host cornea-iris angle. Furthermore, steep and flat keratometry readings obtained by AS-OCT (CASIA-2, Tomey) and Scheimpflug tomography (Pentacam, Oculus) were assessed. OCT findings were correlated with clinical grading of ectasia. Results: There was a highly significant difference in LCTI, graft-host interface angle and anterior chamber depth (in pseudophakic eyes) between the groups. The ratio calculated by the quotient of LCTI divided by CCT was significantly lower in ectatic than non-ectatic eyes (p<0.001). In eyes with an LCTI/CCT ratio of ≤0.7, the OR for the occurrence of a clinical detectable ectasia was 2.4 (CI 1.5 to 3.7). Steep keratometry values were significantly higher in ectatic eyes. Conclusion: AS-OCT is a helpful tool to recognise and quantify ectasia in post-PK eyes objectively.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Cornea; Imaging; Treatment Surgery

Characterization of the cleavage plane in DESCemet's membrane endothelial keratoplasty - Schlötzer-Schrehardt, Ursula; Bachmann, Bjoern O.; Laaser, Kathrin; Cursiefen, Claus; Kruse, Friedrich (Ophthalmology, 2011)
To define the cleavage plane between Descemet's membrane (DM) and posterior corneal stroma in Descemet's membrane endothelial keratoplasty (DMEK) concerning its ultrastructural and immunohistochemical characteristics.Observational, consecutive case series.Fifteen corneoscleral buttons from donors 71.5±4.3 years of age stored in Optisol-GS and used for DMEK surgery in 15 consecutive patients.Endothelial cell-DM complexes (EDMs) and corresponding corneoscleral rims were investigated by transmission electron microscopy and immunohistochemistry using a panel of antibodies against adhesive matrix proteins.Ultrastructural and immunohistochemical characteristics of interface and cleavage plane between DM and posterior stroma.Connection between DM and corneal stroma was mediated predominantly by amorphous material of the interfacial matrix and projecting stromal collagen fibers. After DM stripping, the cleavage plane was located consistently between interfacial matrix and posterior stromal collagen lamellae, providing a largely smooth anterior EDM surface exposing the interfacial zone. Interindividual variations in amount and composition of the interfacial matrix resulted in variable degrees of EDM surface irregularities and variable staining patterns for adhesive matrix proteins such as fibronectin, vitronectin, amyloid P, osteonectin/secreted protein acidic and rich in cysteine (SPARC), fibulin-1, fibulin-2, fibulin-3, fibrillin-1, and keratoepithelin.The findings provide evidence for the existence of a physiologic cleavage plane between the interfacial matrix, the anteriormost adhesive zone of DM, and the corneal stroma, suggesting a relatively weak attachment that can be disconnected by mechanical forces. Interindividual variations in structure and composition of the interfacial matrix may provide an explanation for the variable attachment of EDM grafts to the recipients' corneal stroma and thus may affect the postoperative clinical outcome.The author(s) have no proprietary or commercial interest in any materials discussed in this article.
EVALuna2:21042

Cherry-red spot in a 13-month-old child - Hohberger, B.; Stenger, Nico; Trollmann, Regina; Mardin, C. Y.; Gusek-Schneider, G-C. (Ophthalmologe, 2016)
EVALuna2:21322

Choriocapillaris thickness and density in axially elongated eyes - Panda-Jonas, Songhomitra; Holbach, Leonard; Jonas, Jost B. (Acta Ophthalmologica, 2020)
PURPOSE: Axial myopia is characterized by a thinning of the choroid. We examined whether the myopic choroidal thinning also includes a thinning of the choriocapillaris. METHODS: Using light microscopy, we measured thickness and density of the choriocapillaris at the posterior pole, posterior pole-equator midpoint (PPEMP), equator and close to the ora serrata on histological sections of 58 enucleated human globes (mean age: 62.4 ± 17.8 years; range: 24-88 years; mean axial length: 27.8 ± 4.0 mm; range: 22.0-37.0 mm). RESULTS: Choriocapillaris thickness decreased (p < 0.001) from the posterior pole (median: 3.9 µm; interquartile range (IQR): 3.3-6.0) to the equator (median: 2.7 µm; IQR: 1.5, 4.2). It was not significantly associated with axial length, neither at the posterior pole (p = 0.25), the PPEMP (p = 0.81), equator (p = 0.80) or ora serrata (p = 0.50). Mean choriocapillaris density decreased from the posterior pole to the equator (198 µm/300 µm; IQR: 152/300, 246/300 versus 156 µm/300 µm; IQR: 72/300, 216/300; p < 0.001). Choriocapillaris density was not significantly associated with axial length (posterior pole: p = 0.07; PPEMP: p = 0.33; equator: p = 0.22; ora serrata: p = 0.36). CONCLUSIONS: The choriocapillaris thickness and density, decreasing from the posterior pole to the fundus periphery, were not significantly associated with axial length. These findings may be of interest for the understanding of high myopia and pathologic myopia.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Bruch’s membrane; choriocapillaris; myopia; myopic maculopathy; Scleral staphyloma

Choriocapillaris thickness and density in high myopia - Holbach, Leonard; Jonas, Jost; Panda-Jonas, Songhomitra (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Chromatic discrimination measures in mature observers depend on the response window - Fars, Julien; Fernandes, Thiago P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (Scientific Reports, 2022)
Our past anecdotal evidence prompted that a longer response window (RW) in the Trivector test (Cambridge Colour Test) improved mature observers' estimates of chromatic discrimination. Here, we systematically explored whether RW variation affects chromatic discrimination thresholds measured by the length of Protan, Deutan and Tritan vectors. We employed the Trivector test with three RWs: 3 s, 5 s, and 8 s. Data of 30 healthy normal trichromats were stratified as age groups: 'young' (20-29 years), 'middle-aged' (31-48 years), and 'mature' (57-64 years). We found that for the 'young' and 'middle-aged', the thresholds were comparable at all tested RWs. However, the RW effect was apparent for the 'mature' observers: their Protan and Tritan thresholds decreased at 8-s RW compared to 3-s RW; moreover, their Tritan threshold decreased at 5-s RW compared to 3-s RW. Elevated discrimination thresholds at shorter RWs imply that for accurate performance, older observers require longer stimulus exposure and are indicative of ageing effects manifested by an increase in critical processing duration. Acknowledging low numbers in our 'middle-aged' and 'mature' samples, we consider our study as pilot. Nonetheless, our findings encourage us to advocate a RW extension in the Trivector protocol for testing mature observers, to ensure veridical measures of their chromatic discrimination by disentangling these from other ageing effects-slowing down of both motor responses and visual processing.
CRIS-Team WoS Importer:2022-06-17

Chromatic discrimination: The response window does matter for veridical measurement in mature observers - Fars, Julien; Fernandes, Thiago M. P.; Huchzermeyer, Cord; Kremers, Jan; Paramei, Galina V. (PERCEPTION, 2021)
CRIS-Team WoS Importer:2022-01-21

Chromatische Pupillometrie – ein neuer Weg zur funktionellen Glaukomdiagnostik? - Huchzermeyer, Cord (Klinische Monatsblätter für Augenheilkunde, 2023)
Chromatic pupillometry allows quantification of photoreceptor-driven (extrinsic) and melanopsin-driven (intrinsic) responses of the intrinsic-photosensitive retinal ganglion cells (ipRGCs). This small subpopulation of retinal ganglion cells is also affected by glaucoma, making chromatic pupillometry a potential diagnostic tool. Studies show reduced phasic and tonic responses in glaucoma patients. The diagnostic value in earlier studies depended on the technical details and the study design. The purpose of this article is to give an introduction into the principles of chromatic pupillometry and to discuss the potential applications in the management of glaucoma.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Glaukom; Neuroophthalmologie; Pupillometrie; retinale Ganglienzellen

Circadian Rhythm of VIP in Chicken Intrinsic Choroidal Neurons - Hohberger, Bettina; Lessberger, Carmen; Hermann, Franz; Zenkel, Matthias; Bergua, Antonio; Neuhuber, Winfried (2016)
EVALuna2:184249

Classifying glaucoma with image-based features from fundus photographs - Bock, Rüdiger; Meier, Jörg; Michelson, Georg; Nyul, Laszlo Gabor; Hornegger, Joachim (Springer-verlag, 2007)
Glaucoma is one of the most common causes of blindness and it is becoming even more important considering the ageing society. Because healing of died retinal nerve fibers is not possible early detection and prevention is essential. Robust, automated mass-screening will help to extend the symptom-free life of affected patients. We devised a novel, automated, appearance based glaucoma classification system that does not depend on segmentation based measurements. Our purely data-driven approach is applicable in large-scale screening examinations. It applies a standard pattern recognition pipeline with a 2-stage classification step. Several types of image-based features were analyzed and are combined to capture glaucomatous structures. Certain disease independent variations such as illumination inhomogeneities, size differences, and vessel structures are eliminated in the preprocessing phase. The "vesselfree" images and intermediate results of the methods are novel representations of the data for the physicians that may provide new insight into and help to better understand glaucoma. Our system achieves 86 % success rate on a data set containing a mixture of 200 real images of healthy and glaucomatous eyes. The performance of the system is comparable to human medical experts in detecting glaucomatous retina fundus images. © Springer-Verlag Berlin Heidelberg 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD5.classi

Clinical and Ultrastructural Characteristics of Graft Failure in DMEK: 1-Year Results After Repeat DMEK - Cirkovic, Aleksandar; Schlötzer-Schrehardt, Ursula; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2015)
To evaluate the role of preexisting corneal pathology on the outcome of Descemet membrane endothelial keratoplasty (DMEK), and also to evaluate the long-term outcome of repeat DMEK for graft failure after primary DMEK.Eighteen patients undergoing repeat DMEK after failed DMEK were enrolled; 9 of 18 patients had successful primary DMEK on the fellow eye. Evaluations included preoperative anterior chamber depth, intraoperative degree of difficulty, transmission electron microscopy images (n = 14), best-corrected visual acuity (BCVA), endothelial cell density, central corneal thickness, corneal volume, and patient satisfaction.Surgeries that led to graft failure had a higher intraoperative degree of difficulty compared with successful surgeries (P = 0.002). Eight of 14 failed grafts showed ultrastructural abnormalities, that is, inclusions or deposits of abnormal fibrillar material in Descemet membrane, indicating endothelial dysfunction before transplantation. BCVA on day 10 after surgery was worse in eyes with graft failure compared with successful DMEK (P = 0.008). Median BCVA (logarithm of the minimum angle of resolution) improved from 0.5 before DMEK and 1.9 before repeat DMEK to 0.3 at 1-year follow-up (P = 0.011). One year after repeat DMEK, endothelial cell density (cells/mm) of donor corneas decreased from 2501 ± 264 to 1373 ± 270 (P < 0.001), central corneal thickness (µm) decreased from 807 ± 160 to 576 ± 178 (P = 0.002), and corneal volume (mm) decreased from 84.1 ± 13.0 to 64.4 ± 12.5 (P = 0.002). Patient satisfaction showed no difference between primary and repeat DMEK.A preexisting subclinical corneal endothelial dysfunction may contribute to primary DMEK failure. Repeat DMEK can be performed safely with good long-term outcome.
EVALuna2:21222

Clinical determinants of long-term survival in metastatic uveal melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Erdmann, Michael; Heinzerling, Lucie; Hohberger, Bettina; Knorr, Harald; Leiter, Ulrike; Meier, Friedegund; Mohr, Peter; Rahimi, Farnaz; et al. (Cancer Immunology, Immunotherapy, 2021)
This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified factors were subsequently validated after the population was divided into two cohorts of short-term survival (< 2 years OS, cohort A, n = 50) and long-term survival (> 2 years OS, cohort B, n = 44). A poor ECOG performance status (hazard ratio [HR] 2.0, 95% confidence interval [CI] 1.0–3.9) and elevated serum LDH (HR 2.0, 95% CI 1.0–3.8) were associated with a poor OS, whereas a good response to immune checkpoint blockade (ICB, p < 0.001), radiation therapy (p < 0.001), or liver-directed treatments (p = 0.01) were associated with a prolonged OS. Long-term survivors (cohort B) showed a higher median number of organs affected by metastasis (p < 0.001), while patients with liver metastases only were more common in cohort A (40% vs. 9%; p = 0.002). A partial response to ICB was observed in 16% (12/73), being 21% (8/38) for combined ICB, 17% (1/6) for single CTLA4 inhibition, and 10% (3/29) for single PD1 inhibition. One complete response occurred in cohort B with combined ICB. We conclude that the response to ICB and the presence of extrahepatic disease were favorable prognostic factors for long-term survival.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immune checkpoint blockade; Liver metastases; Liver-directed treatment; Long-term survival; Registry; Uveal melanoma

Clinical Prognostic Factors in metastatic Choroidal Melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, E.; Erdmann, Michael; Heinzerling, L.; Hohberger, Bettina; Knorr, H.; Leiter-Stoppke, U.; Meier, F.; Mohr, P.; Rahimi, F.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

CLL-Derived Extracellular Vesicles Impair T-Cell Activation and Foster T-Cell Exhaustion via Multiple Immunological Checkpoints - Boettcher, Martin; Boettcher-Loschinski, Romy; Kahlfuss, Sascha; Aigner, Michael; Gießl, Andreas; Mackensen, Andreas; Schlötzer-Schrehardt, Ursula; Tueting, Thomas; Bruns, Heiko; Mougiakakos, Dimitrios (Cells, 2022)
Background: Chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of malignant B-cells and multiple immune defects. This leads, among others, to severe infectious complications and inefficient immune surveillance. T-cell deficiencies in CLL include enhanced immune(-metabolic) exhaustion, impaired activation and cytokine production, and immunological synapse malformation. Several studies have meanwhile reported CLL-cell-T-cell interactions that culminate in T-cell dysfunction. However, the complex entirety of their interplay is incompletely understood. Here, we focused on the impact of CLL cell-derived vesicles (EVs), which are known to exert immunoregulatory effects, on T-cell function. Methods: We characterized EVs secreted by CLL-cells and determined their influence on T-cells in terms of survival, activation, (metabolic) fitness, and function. Results: We found that CLL-EVs hamper T-cell viability, proliferation, activation, and metabolism while fostering their exhaustion and formation of regulatory T-cell subsets. A detailed analysis of the CLL-EV cargo revealed an abundance of immunological checkpoints (ICs) that could explain the detected T-cell dysregulations. Conclusions: The identification of a variety of ICs loaded on CLL-EVs may account for T-cell defects in CLL patients and could represent a barrier for immunotherapies such as IC blockade or adoptive T-cell transfer. Our findings could pave way for improving antitumor immunity by simultaneously targeting EV formation or multiple ICs.
CRIS-Team Scopus Importer:2022-08-12
Keywords: cellular therapy; chronic lymphocytic leukemia; extracellular vesicles; immune checkpoints; immune evasion; T-cells

Cluster Analysis of Glaucoma Patients Using the Retinal Nerve Fiber Layer Thickness of the Optic Nerve and DTI Parameters of the Optic Radiation - Michelson, Georg; Wärntges, Simone; Engelhorn, Tobias; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Clinical and Experimental Ophthalmology, 2011)

Color Vision 2018: Introduction by the feature editors - Buck, Steven L.; Baraas, Rigmor; Kremers, Jan; Lindsey, Delwin T.; Nascimento, Sergio M. C.; Webster, Michael A.; Werner, John S. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
This feature issue of the Journal of the Optical Society of America A (JOSA A) reflects the basic and applied research interests of members of the color vision community. Most of the articles stem from presentations at the 24th Biennial Symposium of the International Colour Vision Society (ICVS).
EVALuna2:34925

Combined central retinal vein occlusion and branch retinal artery occlusion treated with intravitreal dexamethasone implant: A case report - Arrigo, Alessandro; Knutsson, Karl Anders; Rajabjan, Firuzeh; Augustin, Victor A.; Bandello, Francesco; Parodi, Maurizio Battaglia (European Journal of Ophthalmology, 2020)
Purpose:
CRIS-Team WoS Importer:2020-03-13

Combined evaluation of frequency doubling technology perimetry and scanning laser ophthalmoscopy for glaucoma detection using automated classification - Horn, Folkert; Lämmer, Robert; Mardin, Christian Y.; Jünemann, Anselm; Michelson, Georg; Lausen, Berthold; Adler, Werner (Journal of Glaucoma, 2012)
To develop a diagnostic setup with classification rules for combined analysis of morphology [Heidelberg Retina Tomograph (HRT)] and function [frequency doubling technology (FDT) perimetry] measurements.We used 2 independent case-control studies from the Erlangen eye department as learning and test data for automated classification using random forests. One eye of 334 open angle glaucoma patients and 254 controls entered the study. All individuals underwent HRT scanning tomography of the optic disc, FDT screening, conventional perimetry, and evaluation of fundus photographs. Random forests were learned on individuals of the Erlangen glaucoma registry (102 preperimetric patients, 130 perimetric patients, 161 controls). The classification performances of random forests and built-in classifiers were examined by receiver operator characteristic analysis on an independent second cohort of individuals (47 preperimetric patients, 55 perimetric patients, 93 controls).HRT measurements had a higher diagnostic power for early glaucomas and FDT perimetry for glaucoma patients with visual field loss. A combination of all parameters using automated classification was superior to single tests in comparison to the diagnostic instrument with the higher diagnostic power in the respective group. Highest sensitivities at a fixed specificity (95%) in the patients of the present test population were: HRT=32%, FDT=19%, combined analysis=47% in preperimetric patients and HRT=76%, FDT=89%, combined analysis=96% in perimetric patients.The feasibility of machine learning for medical diagnostic assistance could be demonstrated in patients from 2 independent study populations. A predictive model using automated classification is able to combine the advantages of morphology and function, resulting in a higher diagnostic power for glaucoma detection.
EVALuna2:5313

Combining L- and M-cone-isolating stimuli to measure parvo- and magnocellular function in normal subjects and glaucoma patients - Huchzermeyer, Cord; Mardin, Christian Y.; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Combining temporal white noise stimulation and silent substitution technique: wnERGs driven by single photoreceptor types in LIAIS mice - Joachimsthaler, Anneka; Stallwitz, Nina; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Comment on: Long-Term Outcome After Superficial Keratectomy of the Abnormal Epithelium for Partial Limbal Stem Cell Deficiency - Bonnet, Clémence; Tseng, Chi Hong; Kruse, Friedrich; Deng, Sophie X. (American Journal of Ophthalmology, 2022)
CRIS-Team Scopus Importer:2022-06-03

Common genetic determinants of intraocular pressure and primary open-angle glaucoma - Van Koolwijk, Leonieke M. E.; Ramdas, Wishal D.; Ikram, M. Kamran; Jansonius, Nomdo M.; Pasutto, Francesca; Hysi, Pirro G.; Macgregor, Stuart; Janssen, Sarah F.; Hewitt, Alex W.; Viswanathan, Ananth C.; Ten Brink, Jacoline B.; Hosseini, S. Mohsen; et al. (PLoS Genetics, 2012)
Intraocular pressure (IOP) is a highly heritable risk factor for primary open-angle glaucoma and is the only target for current glaucoma therapy. The genetic factors which determine IOP are largely unknown. We performed a genome-wide association study for IOP in 11,972 participants from 4 independent population-based studies in The Netherlands. We replicated our findings in 7,482 participants from 4 additional cohorts from the UK, Australia, Canada, and the Wellcome Trust Case-Control Consortium 2/Blue Mountains Eye Study. IOP was significantly associated with rs11656696, located in GAS7 at 17p13.1 (p=1.4×10(-8)), and with rs7555523, located in TMCO1 at 1q24.1 (p=1.6×10(-8)). In a meta-analysis of 4 case-control studies (total N = 1,432 glaucoma cases), both variants also showed evidence for association with glaucoma (p=2.4×10(-2) for rs11656696 and p=9.1×10(-4) for rs7555523). GAS7 and TMCO1 are highly expressed in the ciliary body and trabecular meshwork as well as in the lamina cribrosa, optic nerve, and retina. Both genes functionally interact with known glaucoma disease genes. These data suggest that we have identified two clinically relevant genes involved in IOP regulation.
EVALuna2:9127

Common genetic variants associated with open-angle glaucoma - Ramdas, Wishal D.; Van Koolwijk, Leonieke M. E.; Lemij, Hans G.; Pasutto, Francesca; Cree, Angela J.; Thorleifsson, Gudmar; Janssen, Sarah F.; Jacoline, Ten Brink; Amin, Najaf; Rivadeneira, Fernando; Wolfs, Roger C. W.; Walters, G. Bragi; et al. (Human Molecular Genetics, 2011)
Open-angle glaucoma (glaucoma) is a major eye disorder characterized by optic disc pathology. Recent genome-wide association studies identified new loci associated with clinically relevant optic disc parameters, such as the optic disc area and vertical cup-disc ratio (VCDR). We examined to what extent these loci are involved in glaucoma. The loci studied include ATOH7, CDC7/TGFBR3 and SALL1 for optic disc area, and CDKN2B, SIX1, SCYL1/LTBP3, CHEK2, ATOH7 and DCLK1 for VCDR. We performed a meta-analysis using data from six independent studies including: the Rotterdam Study (n= 5736), Genetic Research in Isolated Populations combined with Erasmus Rucphen Family study (n= 1750), Amsterdam Glaucoma Study (n= 296) and cohorts from Erlangen and Tübingen (n= 1363), Southampton (n= 702) and deCODE (n= 36 151) resulting in a total of 3161 glaucoma cases and 42 837 controls. Of the eight loci, we found significant evidence (P= 1.41 × 10(-8)) for the association of CDKN2B with glaucoma [odds ratio (OR) for those homozygous for the risk allele: 0.76; 95% confidence interval (CI): 0.70-0.84], for the role of ATOH7 (OR: 1.28; 95% CI: 1.12-1.47) and for SIX1 (OR: 1.20; 95% CI: 1.10-1.31) when adjusting for the number of tested loci. Furthermore, there was a borderline significant association of CDC7/TGFBR3 and SALL1 (both P= 0.04) with glaucoma. In conclusion, we found consistent evidence for three common variants (CDKN2B, ATOH7 and SIX1) significantly associated with glaucoma. These findings may shed new light on the pathophysiological protein pathways leading to glaucoma, and point to pathways involved in the growth and development of the optic nerve.
EVALuna2:9086

Common RUNX3 missense variant contributes to psoriatic arthritis by modifying differentiation of CD8(+) T-cells - Kerker, Iris; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Vasileiou, Georgia; Bowes, John; Kirchner, Philipp; Becker, Ina; Giardina, Emiliano; Korendowych, Eleanor; Ekici, Arif Bülent; Ho, Pauline; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Comparative analysis of retinal photoplethysmographic spatial maps and thickness of retinal nerve fiber layer - Odstrcilik, Jan; Kolar, Radim; Horn, Folkert; Tornow, Ralf-Peter (PLoS ONE, 2023)
The paper presents a comparative study of the pulsatile attenuation amplitude (PAA) within the optic nerve head (ONH) at four different areas calculated from retinal video sequences and its relevance to the retinal nerve fiber layer thickness (RNFL) changes in normal subjects and patients with different stages of glaucoma. The proposed methodology utilizes processing of retinal video sequences acquired by a novel video ophthalmoscope. The PAA parameter measures the amplitude of heartbeat-modulated light attenuation in retinal tissue. Correlation analysis between PAA and RNFL is performed in vessel-free locations of the peripapillary region with the proposed evaluating patterns: 360° circular area, temporal semi-circle, nasal semi-circle. For comparison, the full ONH area is also included. Various positions and sizes of evaluating patterns in peripapillary region were tested which resulted in different outputs of correlation analysis. The results show significant correlation between PAA and RNFL thickness calculated in proposed areas. The highest correlation coefficient Rtemp = 0.557 (p<0.001) reflects the highest PAA-RNFL correspondence in the temporal semi-circular area, compared to the lowest value in the nasal semi-circular area (Rnasal = 0.332, p<0.001). Furthermore, the results indicate the most relevant approach to calculate PAA from the acquired video sequences is using a thin annulus near the ONH center. Finally, the paper shows the proposed photoplethysmographic principle based on innovative video ophthalmoscope can be used to analyze changes in retinal perfusion in peripapillary area and can be potentially used to assess progression of the RNFL deterioration.
CRIS-Team Scopus Importer:2023-06-30

Comparative analysis of the basement membrane composition of the human limbus epithelium and amniotic membrane epithelium - Dietrich-Ntoukas, Tina; Hofmann-Rummelt, Carmen; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Cornea, 2012)
: Human amniotic membrane has been widely used as substrate for ex vivo expansion and transplantation of limbal epithelial cells. To further clarify its suitability as a surrogate niche for limbal stem cells and progenitor cells, we analyzed the composition of the amniotic epithelial basement membrane, with special focus on the expression of limbus-specific matrix components.: Cryosections of corneoscleral specimens obtained from 10 human donor eyes and of 6 amniotic membrane specimens obtained at cesarean section were stained by indirect immunofluorescence using a broad panel of antibodies against basement membrane components.: Both amniotic and limbal epithelial basement membranes showed positive immunoreactivity for collagen type IV ?1, ?2, ?5, and ?6 chains; collagens type VII, XV, XVI, XVII, and XVIII; laminin ?3, ?1, ?2, ?3, ?1, and ?2 chains; laminin-111 and laminin-332; nidogen-1 and nidogen-2; fibronectin; fibulin-2; fibrillin-2; perlecan; and agrin. Both types of basement membrane were negative for collagen type IV ?3 and ?4 chains, collagen type V, and laminin ?4 chain. Limbal basement membrane components, which were not detected in amniotic membrane, included laminin ?1, ?2, ?5, and ?3 chains; BM40/SPARC; tenascin-C; matrilin-2; endostatin; and collagen type XVIII.: Despite extensive similarities in basement membrane composition between amniotic and corneolimbal epithelia, the lack of limbus-specific environmental factors argues against the potential of denuded amniotic membrane as a surrogate niche for limbal stem cells but supports its suitability as a substrate to promote the formation of a well-differentiated stratified corneal epithelial equivalent for tissue engineering strategies.
EVALuna2:21080

Comparing functional defects measured by mfERG and standard automated perimetry in patients under (hydroxy-)chloroquine therapy - Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Comparing Transient and Steady-State Multifocal-VEP (mfVEP) using Dartboard Stimulation as Possible Tool for Objective Perimetry - Horn, Folkert; Selle, Franziska; Hohberger, Bettina; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2015)

Comparison of Bruch's Membrane Opening Minimum Rim Width and Peripapillary Retinal Nerve Fiber Layer Thickness in Early Glaucoma Assessment - Gmeiner, Jonas M. D.; Schrems, Wolfgang; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Schrems-Hösl, Laura-Maria (Investigative Ophthalmology & Visual Science, 2016)
To compare the diagnostic value of Bruch's membrane opening minimum rim width (BMO-MRW) and retinal nerve fiber layer thickness (RNFLT) in patients with ocular hypertension, preperimetric, and perimetric glaucoma.One hundred eighty-one eyes consisting of 40 healthy controls, 41 ocular hypertensive subjects, 50 subjects with preperimetric glaucoma and 50 with perimetric glaucoma were included. One randomly selected eye was included. All patients underwent slit-lamp examination, funduscopy, achromatic perimetry, and 24-hour IOP profile. Bruch's membrane opening-MRW and RNFLT (3 peripapillary circle scans, 12°/14°/16°) data were obtained using spectral domain optical coherence tomography. Areas under the receiver operating characteristics curves (AUROC) as well as sensitivity at fixed specificity were computed globally and for six vertical split sectors. Venn diagrams were plotted to identify patients that were diagnosed by one of the two parameters only.For RNFLT the smallest circle diameter showed highest diagnostic accuracy and was used for comparison with BMO-MRW. Distinguishing perimetric glaucoma, RNFLT and BMO-MRW showed comparable AUROCs in global (AUROC, 95% confidence interval: 0.954, 0.911-0.996 and 0.929, 0.872-0.986) and sectoral (0.929, 0.877-0.981 and 0.946, 0.904-0.996) analysis. For preperimetric glaucoma BMO-MRW and RNFLT also demonstrated comparable performance in global (0.839, 0.757-0.921 and 0.821, 0.731-0.912) and sectoral (0.860, 0.782-0.938 and 0.835, 0.750-0.920) analysis. When identifying ocular hypertensive eyes AUROCs were lower for global RNFLT and BMO-MRW (0.493, 0.365-0.621 and 0.562, 0.433-0.691). A combined parameter showed an AUROC of 0.959, 0.921 to 0.996 for perimetric and 0.849, 0.770 to 0.929 for preperimetric glaucoma.Bruch's membrane opening-MRW and RNFLT are comparably useful parameters for discrimination of preperimetric and perimetric glaucomatous eyes and show potential to assist each other in glaucoma diagnosis. (www.ClinicalTrials.gov number, NTC00494923; Erlangen Glaucoma Registry.).
EVALuna2:21294

Comparison of Early Retinal Microvascular Changes and Microalbuminuria as Indicators for Increased Cardioascular Risk - Huchzermeyer, Cord; Schaller, Barbara; Schmid, Kathrin; Schmieder, Roland; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2011)
Prevention of cardiovascular disease is an important goal in clinical medicine and public health. In the process, the diagnosis of early end-organ damage is a priority beside the treatment of classic cardiovascular risk factors. To achieve this, the ophthalmoscopic examination of the retinal vessels plays a prominent role. Alternatively, the quantification of low quantities of albumin in the urine (microalbuminuria) allows the detection of early vascular damage in the kidney. The question is addressed as to whether these two methods are interchangeable or are rather complementary.We examined 226 members of the staff of the University Hospital Erlangen who volunteered to participate in a preventive campaign. A comprehensive history was taken, and height, weight and blood pressure were measured. Analysis of serum lipids and determination of the urinary albumin/creatinine ratio were performed. Fotos of the central fundus were taken with a non-mydriatic camera and analysed by an experienced ophthalmologist in a standardised fashion. The risk for cardiovascular mortality within the next ten years was estimated from age, sex, blood pressure and serum cholesterol using the euroSCORE tables for Germany.There was no signficant correlation between the arteriovenous ratio of the retinal vessels and the urinary albumin/creatinine ratio. Neither parameter correlated with the euroSCORE Germany. Arteriovenous crossings and focal narrowing of the retinal vessels were associated signficantly with an elevated euroSCORE risk.In large population-based studies, the arteriovenous ratio and the urinary albumin/creatinine ratio have been confirmed as markers of cardiovascular risk. In our study, there was no correlation between these two parameters. Thus, they seem to present independent risk markers. The presence of arteriovenous crossings and focal narrowing seems to be linked more closely to the classic cardiovascular risk factors from which the euroSCORE is calculated. The ophathlmolscopic examination of retinal vessels and the analysis of urinary albumin/creatinine ratio seem to complement rather than replace each other.
EVALuna2:3434

Comparison of frequency doubling and flicker defined form perimetry in early glaucoma - Horn, Folkert; Scharch, Vicki; Mardin, Christian Y.; Lämmer, Robert; Kremers, Jan (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To compare perimetric data based on the second-generation frequency doubling technology (FDT) and on flicker defined form (FDF) stimulation in early glaucoma patients.Seventy-two experienced glaucoma patients and 50 healthy subjects of the Erlangen Glaucoma Registry participated in the study. The definition of glaucoma was solely based on optic disc appearance. All patients underwent FDF perimetry (HEP), FDT perimetry (Matrix), standard automated perimetry (SAP, Octopus), and peripapillar measurements of the RNFL thickness (Spectralis OCT). Exclusion criteria were: mean defect (MD) in SAP > 6 dB, eye diseases other than glaucoma, or non-reliable FDF or FDT measurements. Statistical analyses included comparison of the standard indices and correlations between methods. Venn-diagrams show the number of patients with abnormal results in HEP, Matrix, SAP, and mean RNFL thickness.Mean defect data from FDT and FDF perimetry were strongly correlated (R = -0.85, P <0.001). In this cohort of early glaucoma patients, the MD values were 6.1 ± 5.0 dB (FDF) and 4.5 ± 4.1 dB (FDT). Sensitivity in this patient group was 65 % for FDF-MD, 60 % for FDT-MD, and 60 % for RNFL-thickness, all at a specificity of 95 %. The correlation analysis between local RNFL thickness and corresponding visual defects revealed significant Spearman correlation coefficients for the arcuate bundles of the visual field (FDF-inferior: R = -0.65, FDF-superior: R = -0.74, FDT-inferior: R = -0.55, FDT-superior: R = -0.72).FDF and FDT stimulations can be used to detect patients with early glaucoma. Combined consideration of RNFL thickness and results from one of these perimetric tests can increase the total number of detected patients.
EVALuna2:21278

Comparison of macaque and human L- and M-cone driven electroretinograms - Kremers, Jan; Aher, Avinash; Parry, Neil R.A.; Patel, Nimesh B.; Frishman, Laura J. (Experimental Eye Research, 2021)
Purpose: The macaque retina is often used as a model for the human retina. However, there are only a handful of direct in vivo comparisons of the retinal physiology in humans and macaques. In the current study, ERG responses to luminance, L-cone isolating and M-cone isolating stimuli with sinusoidal, sawtooth and square wave temporal profiles were measured. The results were compared with those obtained from human observers. Methods: The responses from five anesthetized adult macaques were measured. Full field stimuli were created. L- and M-cone isolating stimuli were based on the triple silent substitution technique. Sinusoidal stimuli had temporal frequencies between 4 and 56 Hz in 4 Hz steps. Sawtooth stimuli with rapid-on ramp-off and with rapid-off ramp-on excitation profiles had a frequency of 4 Hz. Square stimuli were presented at 2 Hz. Results: Macaque and human ERGs in response to L- and M-cone isolating stimuli reflect L/M opponency and luminance activity. In responses to sine waves, cone opponency dominates at low temporal frequencies (4–12 Hz); luminance dominates at high temporal frequencies. The responses to sawtooth and square wave stimuli reflect a mixture of chromatic and luminance activity. L:M response ratios vary between individuals both in macaques and humans. Macaques show more complex responses, including greater second harmonic contributions than those in humans. Conclusions: Macaque and human ERGs share basic underlying mechanisms reflecting L/M opponency and luminance activity. There may be quantitative differences possibly reflecting differences in contributions of inner retinal mechanisms to the ERGs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Cone opponency; Electroretinogram; Human; L-cones; Luminance; M-cones; Macaque

Complementarity of sensitivity and just noticeable difference in the study of Retinitis Pigmentosa and Stargardt disease - Fars, Julien; Kremers, Jan; Huchzermeyer, Cord (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Computer-Aided Diagnostics and Pattern Recognition: Automated Glaucoma Detection - Köhler, Thomas; Bock, Rüdiger; Hornegger, Joachim; Michelson, Georg (Teleophthalmology in Preventive Medicine, 2015)
Glaucoma is one of the major causes for blindness with a high rate of unreported cases. To reduce this number, screening programs are performed. However, these are characterized by a high workload for manual and cost-intensive assessment. Computer-aided diagnostics (CAD) to perform an automated pre-exclusion of normals might help to improve program's efficiency. This chapter reviews and discusses recent advances in the development of pattern recognition algorithms for automated glaucoma detection based on structural retinal image data. Two main methodologies for glaucoma detection are introduced: (i) structure-driven approaches that mainly rely on the automated extraction of specific medically relevant indicators and (ii) data-driven techniques that perform a generic machine learning approach on entire image data blobs. Both approaches show a reasonable and comparable performance although they rely on different basic assumptions. A combination of these might further improve CAD for a more efficient and cost-sensitive workflow as a major proportion of normals will be excluded from unnecessary detailed investigations.
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD5.comput

Confocal Laser Scanning Tomography to Predict Visual Field Conversion in Patients With Ocular Hypertension and Early Glaucoma - Schrems-Hösl, Laura-Maria; Schrems, Wolfgang; Lämmer, Robert; Horn, Folkert; Jünemann, Anselm; Kruse, Friedrich; Mardin, Christian Y. (Journal of Glaucoma, 2016)
To compare Moorfields regression analysis (MRA), Glaucoma probability score (GPS), and different discriminant functions to predict future visual field conversion of patients with ocular hypertension and early glaucoma.The study included 120 eyes of patients with ocular hypertension and 110 eyes of patients with early glaucoma from the Erlangen glaucoma registry. Annually, all patients underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, and HRT (Heidelberg Retina Tomograph I-III; Heidelberg Engineering) measurements. The cohort was divided into 2 groups based on the development of repeatable glaucomatous visual fields. Positive predictive values and negative predictive values were compared for MRA, GPS, and the classification of Bathija, Iester, Mardin, and Mikelberg at baseline. Kaplan-Meier Survival curves and Logrank tests were used to evaluate equality of survival distributions for different test results.Median follow-up was 9.04 years. 26 eyes (11.3%) demonstrated glaucomatous visual field loss in the follow-up. MRA temporal-superior and temporal-inferior outside normal limits were predictive of future visual field loss with positive predictive values of 33.3% and 28.6%. Normal GPS Temporal Sector demonstrated a negative predictive value of 96.4% and normal results in discriminant functions between 94.7% and 95.5%.Confocal scanning laser tomography is a useful imaging modality to predict future visual field conversion. Development of visual field defects in 10 years is highly unlikely, if GPS classification and/or classification of discriminant analysis at baseline are normal. MRA temporal-superior and temporal-inferior outside normal limits are associated with future VF conversion (ClinicalTrials.gov number, NTC00494923).
EVALuna2:21172

Constitutive expression of HCA(2) in human retina and primary human retinal pigment epithelial cells - Yu, Alice L.; Birke, Kerstin; Lorenz, Reinhard L.; Welge-Lüssen, Ulrich-Christoph (Current Eye Research, 2014)
HCA2, a receptor of ?-hydroxybutyrate and niacin, has recently been described in mouse retina and immortalized human retinal pigment epithelial (RPE) cell lines. As HCA2 might be a pharmacologic target, e.g. in diabetic retinopathy, we studied its expression in human retina and primary human RPE cells.Paraffin sections of human retina and primary human RPE cells were obtained from human donor eyes. Expression of HCA2 in human retina was investigated by immunohistochemistry of paraffin sections and by RT-PCR. HCA2 expression in primary human RPE cells was examined by immunocytochemistry and by Western-blot analysis.Positive immunohistochemical staining for HCA2 was found in paraffin sections of human retina, and positive immunocytochemical staining for HCA2 in primary human RPE cells. RT-PCR analysis detected mRNA expression of HCA2 in human retina. The expression of HCA2 protein was found in primary human RPE cells.Based on these results, HCA2 appears to be constitutively expressed in human retina and in primary human RPE cells. Although its functional role is still unknown, HCA2 may be potentially involved in the pathogenesis of various retinopathies and may offer a new therapeutic target.
EVALuna2:21027

Contact lens-associated superficial stromal keratitis caused by Paecilomyces lilacinus - Huebner, L.; Tourtas, T.; Weller, J. (Ophthalmologe, 2020)
This article presents two cases of contact lens wearers with keratitis caused by Paecilomyces lilacinus. The special feature of these cases was the superficial manifestation of the infection in the upper stromal layer without infiltration into deeper layers. The pathogen was identified following epithelial debridement and corneal scraping. In both cases the fungal keratitis could be successfully managed by intensive topical treatment with voriconazole. Except for an epithelial debridement with EDTA chelation and an amniotic membrane transplantation in one case, no further surgical interventions were necessary.
CRIS-Team WoS Importer:2020-04-10

Cornea: endothelial dystrophies and degenerations - Fuchsluger, Thomas; Lisch, W; Geerling, G; Seitz, B (Klinische Monatsblätter für Augenheilkunde, 2015)
EVALuna2:21220

Corneal endothelium can be protected against cell by anti-Bax siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth; Schubert, Dirk W. (The Association for Research in Vision and Ophthalmology (ARVO), 2018)
Keywords: corneal; ani-Bak

Corneal endothelium can be protected against cell death by anti-Bax and anti-Bak siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth (2018)
EVALuna2:34735

Corneal Higher-Order Aberrations after Descemet's Membrane Endothelial Keratoplasty - Rudolph, Michael; Laaser, Kathrin; Bachmann, Bjoern O.; Cursiefen, Claus; Epstein, Daniel; Kruse, Friedrich (Ophthalmology, 2012)
We compared corneal higher-order aberrations (HOAs) in eyes after Descemet's membrane endothelial keratoplasty (DMEK), Descemet's stripping automated endothelial keratoplasty (DSAEK), and penetrating keratoplasty (PK), and in a control group that had not undergone surgery.Retrospective analysis of clinical data.Thirty eyes of 30 patients who had undergone standard DMEK, 20 eyes of 20 patients after DSAEK, 20 eyes of 20 patients after PK, and 20 eyes of 20 controls were analyzed.In addition to standard postoperative examinations, each participant was analyzed with the Pentacam high-resolution rotating Scheimpflug imaging system (Pentacam HR, Oculus, Wetzlar, Germany). Data were compared between groups.Visual acuity and HOAs.The mean follow-up was 6.5±1.2 months after DMEK, 22.6±11.8 months after DSAEK, and 103.1±74.2 months after PK. There were no statistically significant differences for the anterior 4.0-mm zones between the DMEK group and the controls or between the DMEK and DSAEK groups. The DMEK procedure compared with PK showed statistically significant differences in all terms for the 4.0-mm zones. All combined Zernike terms for mean posterior aberrations of the central 4.0-mm zones showed statistically significant higher aberrations for DMEK compared with controls. The DMEK procedure compared with DSAEK showed statistically significant lower mean values for all combined Zernike terms, except for coma and coma-like terms in the central 4.0-mm zones of the posterior corneal surface. Compared with PK, DMEK showed statistically significant lower mean values for all combined Zernike terms for the central 4.0-mm zones of the posterior corneal surface, except for spherical aberration (SA) and SA-like terms. Best spectacle-corrected visual acuity (BSCVA) after DMEK was statistically significantly better than after DSAEK (P=0.001) and PK (P=0.005). There was no statistically significant difference when BSCVA was compared with controls (P=0.998).Both DSAEK and PK exhibit increased posterior corneal HOAs even years after surgery. Patients receiving DMEK display only slight changes in posterior corneal HOAs.Proprietary or commercial disclosure may be found after the references.
EVALuna2:21073

Corneal tissue interactions of a new 345 nm ultraviolet femtosecond laser - Hammer, Christian M.; Petsch, Corinna; Klenke, Joerg; Skerl, Katrin; Paulsen, Friedrich; Kruse, Friedrich; Seiler, Theo; Menzel-Severing, Johannes (Journal of Cataract and Refractive Surgery, 2015)
To assess the suitability of a new 345 nm ultraviolet (UV) femtosecond laser for refractive surgery.Department of Ophthalmology, University of Erlangen-Nürnberg, Erlangen, Germany.Experimental study.Twenty-five porcine corneas were used for stromal flap or lamellar bed creation (stromal depth, 150 ?m) and 15 rabbit corneas for lamellar bed creation near the endothelium. Ultraviolet femtosecond laser cutting-line morphology, gas formation, and keratocyte death rate were evaluated using light and electron microscopy and compared with a standard infrared (IR) femtosecond laser. Endothelial cell survival was examined after application of a laser cut near the endothelium.Flaps created by the UV laser were lifted easily. Gas formation was reduced 4.2-fold compared with the IR laser (P = .001). The keratocyte death rate near the interface was almost doubled; however, the death zone was confined to a region within 38 ?m ± 10 (SD) along the cutting line. Histologically and ultrastructurally, a distinct and continuous cutting line was not found after UV femtosecond laser application if flap lifting was omitted and standard energy parameters were used. Instead, a regular pattern of vertical striations, presumably representing self-focusing induced regions of optical tissue breakdown, were identified. Lamellar bed creation with standard energy parameters 50 ?m from the endothelium rendered the endothelial cells intact and viable.The new 345 nm femtosecond laser is a candidate for pending in vivo trials and future high-precision flap creation, intrastromal lenticule extraction, and ultrathin Descemet-stripping endothelial keratoplasty.Mr. Klenke and Ms. Skerl were paid employees of Wavelight GmbH when the study was performed. Dr. Seiler is a scientific consultant to Wavelight GmbH. No other author has a financial or proprietary interest in any material or method mentioned.
EVALuna2:21240

Correlated and uncorrelated invisible temporal white noise alters mesopic rod signaling - Hathibelagal, Amithavikram R.; Feigl, Beatrix; Kremers, Jan; Zele, Andrew J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We determined how rod signaling at mesopic light levels is altered by extrinsic temporal white noise that is correlated or uncorrelated with the activity of one (magnocellular, parvocellular, or koniocellular) postreceptoral pathway. Rod and cone photoreceptor excitations were independently controlled using a four-primary photostimulator. Psychometric (Weibull) functions were measured for incremental rod pulses (50 to 250 ms) in the presence (or absence; control) of perceptually invisible subthreshold extrinsic noise. Uncorrelated (rod) noise facilitates rod detection. Correlated postreceptoral pathway noise produces differential changes in rod detection thresholds and decreases the slope of the psychometric functions. We demonstrate that invisible extrinsic noise changes rod-signaling characteristics within the three retinogeniculate pathways at mesopic illumination depending on the temporal profile of the rod stimulus and the extrinsic noise type.
EVALuna2:21298

Correlation between Loss of the Retinal Nerve Fiber Layer Thickness and Local Visual Field Defects measured with FDF-Perimetry - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 642 perimetry; 610 nerve fiber layer; 758 visual fields

Correlation of retinal vascular characteristics with laboratory and ocular findings in Fabry disease: exploring ocular diagnostic biomarkers - Lindziute, Migle; Kaufeld, Jessica; Hufendiek, Karsten; Volkmann, Ingo; Brockmann, Dorothee; Hosari, Sami; Hohberger, Bettina; Christian, Mirko; Framme, Carsten; Jan, Tode; Hufendiek, Katerina (Orphanet Journal of Rare Diseases, 2023)
Background: The goal of this study was to evaluate macular microvascular changes in patients with Fabry disease (FD) using optical coherence tomography angiography (OCTA) and to explore their correlation with laboratory and ocular findings. Methods: A total of 76 eyes (38 patients) and 48 eyes of 24 healthy controls were enrolled in this prospective study. Vessel Area Density (VAD) and Foveal Avascular Zone (FAZ) area were calculated on 2.9 × 2.9 mm OCTA images scanned with the Heidelberg Spectralis II (Heidelberg, Germany). VAD was measured in three layers: Superficial Vascular Plexus (SVP), Intermediate Capillary Plexus (ICP), and Deep Capillary Plexus (DCP). All scans were analyzed with the EA-Tool (Version 1.0), which was coded in MATLAB (The MathWorks Inc, R2017b). FAZ area was manually measured in full-thickness, SVP, ICP and DCP scans. Results: Average VAD in SVP, ICP and DCP was higher in Fabry disease patients than in controls (49.4 ± 11.0 vs. 26.5 ± 6.2, 29.6 ± 7.4 vs. 20.2 ± 4.4, 32.3 ± 8.8 vs. 21.7 ± 5.1 respectively, p < 0.001). Patients with cornea verticillata (CV) had a higher VAD in ICP and DCP compared to patients without CV (p < 0.01). Patients with increased lysoGb3 concentration had a higher VAD in DCP when compared to patients with normal lysoGb3 concentration (p < 0.04). There was no difference in VAD in patients with and without vascular tortuosity. However, a significantly higher VAD was observed in patients with vascular tortuosity compared to controls (p < 0.03). Conclusions: Increased lysoGb3 and VAD in DCP could be reliable biomarkers of disease activity. Cornea verticillata could be adopted as a predictive biomarker for VAD changes and disease progression. The combination of cornea verticillata and increased VAD may serve as a diagnostic biomarker for Fabry disease, however due to the discrepancies in VAD values in various studies, further research has to be done to address this claim.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Biomarkers; Fabry disease; OCT angiography; Vascular remodelling; Vessel area density

Correlations between dark-adapted rod threshold elevations and erg response deficits in duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Dias, Sarah Leonardo; Silva, Leonardo Aparecido; Damico, Francisco Max; Vidal, Kallene Summer; Costa, Marcelo Fernandes; Nagy, Balázs Vince; Kremers, Jan; Ventura, Dora Fix (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. The purpose of this study was to characterize changes in the full-field flash electroretinogram (ERG) in association with psychophysical dark-adapted visual thresholds in patients with genetically characterized Duchenne muscular dystrophy (DMD) either lacking Dp427 (Up 30) or at least Dp260 in addition to Dp427 (Down 30). METHODS. Twenty-one patients with DMD and 27 age-similar controls participated in this study. Dark-adapted (0.01, 3.0, and 10 cd.s/m2 flashes) and light-adapted (3.0 cd.s/m2 flash) ERGs were recorded following International Society for Clinical Electrophysiology of Vision (ISCEV) standard protocols. Visual detection thresholds to 625-nm (cone function) and 527-nm (rod function) light-emitting diode (LED) flashes (2 degree diameter) were measured during a dark adaptation period after a 1-minute exposure to a bleaching light (3000 cd/m2). Initially, 8 minutes of interleaved 625-nm and 527-nm thresholds were measured. After an additional 5 minutes of dark-adaptation, a second set of threshold measurements to 527-nm stimuli was performed during the subsequent 6 minutes. RESULTS. Dark-adapted b-wave amplitude was significantly reduced to all strengths of flash and a-wave in response to the strong flash stimulus was delayed (15.6 vs. 14.7 ms, P < 0.05) in patients with Down 30 compared with controls. Dark-adapted cone thresholds did not differ among the groups (−2.0, −1.8, and −1.7 log cd/m2 for Down 30, Up 30, and controls, respectively, P = 0.21). In contrast, dark-adapted rod thresholds were elevated (F(2,36) = 8.537, P = 0.001) in patients with Down 30 (mean = −3.2 ± 1.1 log cd/m2) relative to controls (mean = −4.2 ± 0.3 log cd/m2). Dark-adapted b-wave amplitudes were correlated with dark-adapted rod sensitivity in patients with DMD (Spearman Rho = 0.943, P = 0.005). The changes were much smaller or absent in patients with intact Dp260. CONCLUSIONS. Dp260 is particularly required for normal rod-system function in dark adaptation.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Cone; Dark-adaptation; Duchenne muscular dystrophy (DMD); Dystrophin protein; Electroretinogram (ERG); Human vision; Retina; Rod

Corrugated Bruch's membrane in high myopia - Jonas, Jost B.; Jonas, Rahul A.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2018)
PURPOSE: To assess the appearance of Bruch's membrane (BM) in axially elongated eyes. METHODS: The light-microscopical investigation included histological anterior-posterior sections of human eyes. Using a light microscope, we assessed whether BM in the posterior segment was straight or locally corrugated. Corrugation of BM was defined as an elevation of BM with a height >20 μm over a basis of 50 μm without collateral proliferations of retinal pigment epithelium or choroidal swelling. RESULTS: The investigation included 85 eyes (age: 62.0 ± 14.1 years; axial length: 26.7 ± 3.5 mm). In multivariate analysis, the presence of a corrugated BM, detected in eight eyes (9.4%), was strongly associated with the presence of macular BM defects [p = 0.001; odds ratio (OR): 418; 95% confidence interval (CI): 1 215 000], but not with axial length (p = 0.54). Bruch's membrane (BM) corrugation was detected in seven (54%) of 13 eyes with macular BM defects. The single eye with BM corrugation and without macular BM defect showed the corrugated BM located in the parapapillary region at the peripheral end of a large parapapillary gamma zone. CONCLUSION: Bruch's membrane (BM) corrugation can be present in the vicinity of macular BM defects in highly myopic eyes, perhaps due to differences in the tension within BM in various regions at the margin of the BM defect. Bruch's membrane (BM) corrugation may also develop at the papillary end of BM in eyes with a large parapapillary gamma zone, potentially due to a disinsertion of BM at the end of the peripapillary choroidal border tissue of Jacoby. The observation of BM corrugation may help elucidating the aetiology of axial myopia.
EVALuna2:34755

Critical endothelial procedures during posterior lamellar graft preparation and transplantation - Fuchsluger, Thomas; Kruse, Friedrich Eduard; Geerling, G. (Ophthalmologe, 2017)
In view of the very low proliferation rate and functional importance of the corneal endothelium in maintaining corneal transparency, safeguarding the integrity of this monolayer plays a central role in posterior lamellar corneal transplantation. Several critical endothelial procedural stages are necessary to carry out such a transplantation.This article presents various preparatory and operative approaches for carrying out the necessary and critical stages within the framework of posterior lamellar corneal transplantation and concentrates on the question of optimization.A review of our own studies and studies of other groups is presented.For the performance of critical endothelial procedural steps, a variety of approaches are available. These range from preparation and insertion of the transplant, through the manipulation during centralization up to the effects of postoperative air or gas bubble tamponade.Because endothelial damage can permanently impair the integrity of lamellar transplants, a minimal handling and no touch policy should be strived for in all critical procedures. Long-term data on the follow-up course will show which of the procedures favored by various authors lead to the best postoperative results.
EVALuna2:21276

Crossing-preserving multi-scale vesselness - Hannink, Julius; Duits, Remco; Bekkers, Erik (Lecture Notes in Computer Science, 2014)
The multi–scale Frangi vesselness filter is an established tool in (retinal) vascular imaging. However, it cannot properly cope with crossings or bifurcations since it only looks for elongated structures. Therefore, we disentangle crossings/bifurcations via (multiple scale) in- vertible orientation scores and apply vesselness filters in this domain. This new method via scale–orientation scores performs considerably bet- ter at enhancing vessels throughout crossings and bifurcations than the Frangi version. Both methods are evaluated on a public dataset. Per- formance is measured by comparing ground truth data to the segmenta- tion results obtained by basic thresholding and morphological component analysis of the filtered images.
Keywords: Multi-scale vesselness filters; continuous wavelet transforms; line detection; gauge frames; retinal imaging

Cross-linking in an artificial human cornea via induction of tissue transglutaminases - Kopsachilis, N.; Tsinopoulos, I.; Tsaousis, Konstantinos; Meiller, R.; Dimitrakos, S. A.; Kruse, Friedrich; Luessen, U. W. (Ophthalmologe, 2012)
In recent years many three-dimensional cornea models have been developed. However, they show poor collagen stability in the stroma. Transglutaminases (Tgases) are calcium-dependent proteins which play an important role in cross-linking of the corneal stroma. The purpose of this study was to find out whether it is possible to induce in vitro cross-linking of the stroma in an artificial hemicornea model with the help of Tgases.For the construction of the hemicornea, human SV40 adenovector corneal epithelial cells (HCE) and human SV40 adenovector corneal keratocytes (HCK) were cultivated. Confluent HCK cells were treated for 24 h with transforming growth factor beta (TGFb) 1, 2 and 3 at different concentrations as well as with other growth factors and the treated cells were compared to untreated cultivated cells. The quantification of the expression of the Tgases by HCKs was examined with the use of real time PCR, Western blot imaging and immunochemistry.All concentrations of TGFbs used resulted in a significant increase of Tgase-mRNA, Tgase protein level and Tgase activity. The Tgases remained unaffected after treatment with other growth factors in comparison to untreated control cells. Treatment of the hemicornea with TGFb2 showed a very strong contraction and haze in comparison to the untreated hemicornea.It has been shown for the first time that TGFb induces a strong expression of Tgases in HCK cells. This effect caused an undesired contraction and haze of the human hemicornea model. Further research is necessary in order to find out whether the induction of Tgases in the HCK cells can be regulated without losing stability of the constructed hemicornea.
EVALuna2:21093

Cultivation and characterisation of primary retinal pigment epithelium cells on nanofibre scaffolds - Heiduschka, Peter; Zimmermann, Julian Alexander; Plagemann, Tanja; Stafiej, Piotr; Himmler, Marcus; Fuchsluger, Thomas Armin; Eter, Nicole (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

CXCL12 promotes glycolytic reprogramming in acute myeloid leukemia cells via the CXCR4/mTOR axis - Braun, Michael; Qorraj, M.; Büttner, Maike; Klein, F. A.; Saul, D.; Aigner, M.; Huber, W.; Mackensen, Andreas; Jitschin, R.; Mougiakakos, Dimitrios (Leukemia, 2016)
EVALuna2:25512

Cytokine-dependent ELAM-1 induction and concomitant intraocular pressure regulation in porcine anterior eye perfusion culture - Birke, Marco; Birke, Kerstin; Lütjen-Drecoll, Elke; Schlötzer-Schrehardt, Ursula; Hammer, Christian (Investigative Ophthalmology & Visual Science, 2011)
To demonstrate the capacity of interleukin (IL)-1 to simultaneously lower intraocular pressure (IOP) and induce trabecular ELAM-1 expression in one experiment and to test for IL-6 accordingly and evaluate the role of transforming growth factor (TGF)-?2 as an IL-1 antagonist.Forty-two porcine eyes were subjected to trabecular meshwork (TM) perfusion with IL-1?, -1?, or -6 for 48 hours. Twelve of the IL-1?-treated eyes also received TGF-?2 for the final 24-hour period. Polymerase chain reaction and Western blot analyses of ELAM-1 expression were then performed on harvested TM samples. mRNA regulation of IL-1?, IL-1?, IL-6, TGF-?2, and P-selectin (SELP) was determined.IL-1? and -1? treatment augmented outflow facility approximately threefold while inducing ELAM-1. IL-6 perfusion neither changed IOP nor induced ELAM-1. IL-1?/TGF-?2 double treatment significantly counteracted the IL-1-induced IOP decrease and markedly reduced the degree of ELAM-1 mRNA upregulation from 22.3- to 3.1-fold, and ELAM-1 protein from 1.9- to 1.2-fold. IL-1? mRNA was upregulated 5.3-, 3.3-, and 5.5-fold after perfusion with IL-1?, -1?, and -1?/TGF-?2, respectively. The respective values for IL-6 mRNA were 2.0-, 2.1- and 2.4-fold. Expression of IL-1? and TGF-?2 mRNA remained unchanged. IL-6 perfusion had no discernible regulatory effect.Simultaneous demonstration of IL-1's lowering of IOP and inducing trabecular ELAM-1 was achieved for the first time in one experiment, and its possible implications in the pathogenesis of glaucoma was further emphasized. The involvement of an autocrine feedback loop was confirmed in the porcine system. TGF-?2 constitutes a potent IL-1 antagonist for IOP and ELAM-1 regulation.
EVALuna2:21022

Dark adapted cone/rod thresholds and ERGs in Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Dias, Sarah; Silva, Leonardo; Damico, Francisco Max; Vidal, Kallene Summer; Costa, Marcelo Fernandes; Grossklauss, Luis Fernando; Nagy, Balazs Vince; Kremers, Jan; Ventura, Dora Fix (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Deep Learning Glaucoma Classification in enface OCTA scans of the human macular region - Schottenhamml, Julia; Ploner, Stefan; Husvogt, Lennart; Mardin, Sophia; Hohberger, Bettina; Mardin, Christian Y.; Maier, Andreas (ARVO Annual Meeting 2021, 2021)
CRIS-Team WoS Importer:2021-09-24

Deep neural network by transfer learning for the analysis of guttae in the patients with Fuchs endothelial corneal dystrophy - Narimoto, Kaito; Okumura, Naoki; Yamada, Shohei; Okamura, Kengo; Izumi, Ayaka; Tourtas, Theofilos; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Defining dry eye from a clinical perspective - Tsubota, Kazuo; Pflugfelder, Stephen C.; Liu, Zuguo; Baudouin, Christophe; Kim, Hyo Myung; Messmer, Elisabeth M.; Kruse, Friedrich; Liang, Lingyi; Carreno-Galeano, Jimena Tatiana; Rolando, Maurizio; Yokoi, Norihiko; Kinoshita, Shigeru; et al. (International Journal of Molecular Sciences, 2020)
Over the past decades, the number of patients with dry eye disease (DED) has increased dramatically. The incidence of DED is higher in Asia than in Europe and North America, suggesting the involvement of cultural or racial factors in DED etiology. Although many definitions of DED have been used, discrepancies exist between the various definitions of dry eye disease (DED) used across the globe. This article presents a clinical consensus on the definition of DED, as formulated in four meetings with global DED experts. The proposed new definition is as follows: “Dry eye is a multifactorial disease characterized by a persistently unstable and/or deficient tear film (TF) causing discomfort and/or visual impairment, accompanied by variable degrees of ocular surface epitheliopathy, inflammation and neurosensory abnormalities.” The key criteria for the diagnosis of DED are unstable TF, inflammation, ocular discomfort and visual impairment. This definition also recommends the assessment of ocular surface epitheliopathy and neurosensory abnormalities in each patient with suspected DED. It is easily applicable in clinical practice and should help practitioners diagnose DED consistently. This consensus definition of DED should also help to guide research and clinical trials that, to date, have been hampered by the lack of an established surrogate endpoint.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Corneal epitheliopathy; Definition; Dry eye; Dry eye signs; Dry eye symptoms; Inflammation; Neuropathic pain; Tear film breakup

Definition of K(trans) and FA Thresholds for Better Assessment of Experimental Glioma Using High-field MRI: A Feasibility Study - Engelhorn, Tobias; Schwarz, Martin; Heß, Andreas; Budinsky, Lubos; Pitann, Patrick; Eyüpoglu, Ilker Yasin; Dörfler, Arnd (Clinical Neuroradiology, 2014)
To define K(trans) and fractional anisotropy (FA) thresholds in correlation to histology for improved magnetic resonance imaging (MRI) tumor assessment in an animal model of brain glioma.Twelve rats underwent 4.7 T MRI at day 10 after tumor implantation. Anatomical scans (T2, T1 at 8 min after double dose contrast application) as well as dynamic contrast-enhanced (DCE) imaging with calculation of K(trans) and diffusion tensor imaging (DTI) with calculation of FA were performed. T2- and T1-derived tumor volumes were calculated and thresholds for K(trans) and FA were defined for best MRI tumor assessment correlated to histology.Tumor volumes were 159 ± 14 mm(3) (histology), 126 ± 26 mm(3) (T1 with contrast, r = 0.76), and 153 ± 12 mm(3) (T2, r = 0.84), respectively. K(trans)- and FA-derived tumor volumes were 160 ± 16 mm(3) (for K(trans) ³ 0.04 min(-1), r = 0.94), and 159 ± 14 mm(3) (for FA £ 0.14, r = 0.96), respectively.DCE-MRI and DTI with calculation of K(trans) and FA maps allow very precise brain glioma assessment comparable to histology if established thresholds for the given tumor model are used.
EVALuna2:8504

Delayed corneal clearance after uneventful Descemet Membrane endothelial keratoplasty - Augustin, Victor A.; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Descemetectomy as therapy option for visually disturbing roll in Descemet's membrane - Cursiefen, C.; Bachmann, B. (Ophthalmologe, 2013)
The aim was to demonstrate the feasibility of targeted removal of a central visually disturbing roll in Descemet's membrane after complicated cataract surgery.Case report: a 76-year-old patient complained of halos and reduced visual acuity after external cataract surgery. At slit-lamp examination a central roll in Descemet's membrane was found (2 × 2 mm).A targeted central descemetectomy was performed by circular descemetorhexis around the defect. Early postoperative visual acuity improved and halos disappeared. At 2 months postoperatively best corrected visual acuity (BCVA) was 1.0 and the endothelial cell count was not significantly changed.Central targeted descemetorhexis is a safe therapeutic option for visually disturbing defects of Descemet's membrane.
EVALuna2:21125

Descemet membrane endothelial keratoplasty: analysis of clinical outcomes of patients with 8-10 years follow-up - Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (International Ophthalmology, 2022)
Purpose This study aimed to evaluate the clinical outcomes up to 10 years after Descemet membrane endothelial keratoplasty (DMEK). Methods In this retrospective, consecutive, single-center case series the medical files of eyes which have received DMEK between 2009 and 2012 for the treatment of endothelial dysfunction was evaluated regarding follow-up time and clinical outcomes. Annual examinations of best-corrected visual acuity (BCVA), endothelial cell density (ECD), central corneal thickness (CCT) of 66 eyes which fulfilled the criterion of a minimum of 8 years follow-up were analyzed. Results BCVA improved from 0.55 +/- 0.37 logMAR (n = 54) to 0.15 +/- 0.11 (n = 47) in eyes without ocular comorbidities one year after DMEK (p < 0.001), and remained stable up to 10 years after DMEK. Mean ECD decreased to 744 +/- 207 cells/mm(2) (n = 39) after 9 years, and to 729 +/- 167 cells/mm(2) (n = 21) after 10 years, respectively. CCT decreased from 650 +/- 67 mu m before DMEK to 525 +/- 40 mu m (n = 56) after 1 year, increasing slowly to 563 +/- 40 mu m (n = 39) after 9 years, and to 570 +/- 42 mu m (n = 21) after 10 years, respectively. Graft failure occurred in 4 of 66 eyes after year 8. These 4 eyes required repeat DMEK after 101-127 months. Conclusion This study shows the long-term outcomes in a small subset of DMEK grafts. Visual acuity remained stable in spite of slowly increasing corneal thickness and diminishing endothelial cell density during the 10-year period after DMEK.
CRIS-Team WoS Importer:2022-01-14

Descemet membrane endothelial keratoplasty as treatment for graft failure after descemet stripping automated endothelial keratoplasty - Weller, Julia M.; Tourtas, Theofilos; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Fuchsluger, Thomas; Bachmann, Bjoern O. (American Journal of Ophthalmology, 2015)
To investigate the outcome of Descemet membrane endothelial keratoplasty (DMEK) in patients with graft failure after Descemet stripping automated endothelial keratoplasty (DSAEK).Retrospective cohort study.setting: Institutional.Fifteen eyes of 15 patients that underwent DMEK for graft failure with corneal decompensation following DSAEK were analyzed; 15 eyes with primary DMEK for Fuchs corneal dystrophy were included as control group.Best-corrected visual acuity (BCVA), endothelial cell density (ECD), central corneal thickness (CCT), and rebubbling rate.DMEK surgery was successful in all cases of both groups. Mean BCVA (logMAR) before DMEK was 1.27 ± 0.34 in the DMEK after DSAEK group and 1.0 ± 0.40 in the Primary DMEK group. After DMEK, mean BCVA increased significantly to 0.23 ± 0.21 (P = .012, DMEK after DSAEK group) and 0.29 ± 0.23 (P = .042, Primary DMEK group) after 3 months. There were no significant differences in mean BCVA between both groups at each visit. The rebubbling rate was 13% in the DMEK after DSAEK group and 40% in the Primary DMEK group (P = .1). Mean CCT decreased significantly in both groups 1 month after DMEK (P < .05). Mean ECD and change of ECD did not differ significantly between both groups at each visit (P > .05).The results after DMEK as a procedure to treat graft failure after DSAEK were as good as in patients that underwent DMEK as primary intervention to treat advanced Fuchs dystrophy. This indicates that the optical quality can be reestablished by DMEK in patients with failed DSAEK.
EVALuna2:21229

Descemet membrane endothelial keratoplasty combined with phacoemulsification and intraocular lens implantation: advanced triple procedure - Laaser, Kathrin; Bachmann, Bjoern O.; Horn, Folkert; Cursiefen, Claus; Kruse, Friedrich (American Journal of Ophthalmology, 2012)
To evaluate the functional and morphologic outcome of Descemet membrane endothelial keratoplasty (DMEK) combined with phacoemulsification and intraocular lens implantation in patients suffering from endothelial dysfunction and cataract.Retrospective, single-center, consecutive case series.Triple-DMEK (DMEK with simultaneous cataract surgery) was performed in 61 consecutive eyes of 56 patients using corneal donor tissue pre-stored in either short-term culture (Optisol-GS) at 4 C or organ culture (Dulbecco's modified Eagle's medium, CorneaMax medium) at 34 C. Main outcome measures included the number of air injections necessary for graft attachment as well as best-corrected visual acuity (BCVA [logMAR]), central corneal thickness (CCT), endothelial cell density (ECD), refractive spherical equivalent, refractive cylinder, and topographic cylinder at 1, 3, and 6 months postoperatively.BCVA increased from 0.6 ± 0.23 logMAR preoperatively (n = 54) to 0.19 ± 0.22 logMAR at 6 months (n = 27) after surgery (P <= .05). ECD of donor corneas decreased from 2573 ± 235 cells/mm(2) (n = 61) to 1550 ± 326 cells/mm(2) (n = 29) after 6 months (P <= .05). CCT decreased from 651 ± 69 ?m (n = 54) preoperatively to 521 ± 65 ?m (n = 27) after 6 months (P <= .05). Refractive spherical equivalent was -0.3 ± 2.8 D (n = 27) preoperatively and 0.9 ± 1.5 D 6 months (n = 27) after surgery. A total of 54.5% of eyes were within 1 D of emmetropia (n = 12) and 77.3% were within 2 D of emmetropia (n = 17) 6 months (n = 22) after surgery. Refractive cylinder was -0.9 ± 1.0 D preoperatively (n = 49) and -1.5 ± 1.0 D 6 months (n = 23) after surgery. The change in refractive cylinder within the first month was statistically significant (P <= .05; Wilcoxon test). Topographic cylinder was 2.1 ± 1.7 D preoperatively (n = 58) and 1.7 ± 1.1 D 6 months (n = 28) after surgery. Between 3 and 6 months a significant change in topographic cylinder towards lower values was measured (P <<= 0.05; Wilcoxon test). Optimized spherical results were achieved by selecting intraocular lenses based on a hyperopic shift of -0.75 D.DMEK combined with cataract surgery (triple procedure) can routinely be performed in cases of endothelial dystrophy and cataract. The addition of cataract surgery to DMEK had no adverse effect on endothelial function or graft adhesion and did not increase the likelihood of postoperative complications.
EVALuna2:21089

Descemet membrane endothelial keratoplasty versus descemet stripping automated endothelial keratoplasty - Tourtas, Theofilos; Laaser, Kathrin; Bachmann, Bjoern O.; Cursiefen, Claus; Kruse, Friedrich (American Journal of Ophthalmology, 2012)
To evaluate visual outcome and endothelial cell survival after Descemet membrane endothelial keratoplasty (DMEK) in comparison with Descemet stripping automated endothelial keratoplasty (DSAEK).Single-center, retrospective, consecutive case series.Thirty-eight eyes of 38 consecutive patients undergoing DMEK, who completed a 6-month follow-up, were compared with 35 eyes of 35 consecutive patients undergoing DSAEK for Fuchs endothelial dystrophy or pseudophakic bullous keratopathy. Main outcome measures included best-corrected visual acuity (in logarithm of the minimal angle of resolution [logMAR] units) and endothelial cell density within a 6-month follow-up.Best-corrected visual acuity increased from 0.70 ± 0.48 logMAR and 0.75 ± 0.32 logMAR before surgery to 0.21 ± 0.14 logMAR and 0.48 ± 0.19 logMAR 3 months after DMEK and DSAEK (P < .001), respectively, and to 0.17 ± 0.12 logMAR and 0.36 ± 0.15 logMAR 6 months after DMEK and DSAEK (P < .001), respectively. Endothelial cell density decreased from 2575 ± 260 cells/mm(2) and 2502 ± 220 cells/mm(2) before surgery to 1498 ± 244 cells/mm(2) and 1778 ± 420 cells/mm(2) 3 months after DMEK and DSAEK (P < .001), respectively, and to 1520 ± 299 cells/mm(2) and 1532 ± 495 cells/mm(2) 6 months after DMEK and DSAEK (P = .483), respectively. Central corneal thickness decreased from 652 ± 92 ?m before surgery to 517 ± 45 ?m 6 months after DMEK, and from 698 ± 137 ?m before surgery to 618 ± 66 ?m 6 months after DSAEK.DMEK provided faster and more complete visual rehabilitation when compared with DSAEK. However, there were no significant differences concerning endothelial cell survival within a 6-month follow-up.
EVALuna2:21063

Descemet's membrane substrate from human donor lens anterior capsule - Kopsachilis, Nikolaos; Tsinopoulos, Ioannis; Tourtas, Theofilos; Kruse, Friedrich; Luessen, Ulrich Welge (Clinical and Experimental Ophthalmology, 2012)
To study the potential use of human donor anterior lens capsule as a Descemet's membrane substrate.Anterior lens capsules were recovered from the lenses of 30 cornea donors. Human corneal endothelial cells were recovered from the remaining corneal sclera rims of 15 donor corneas used for penetrating keratoplasty. Samples were sorted into three groups. Group 1 consisted of 10 samples in which the endothelial cells were allowed to grow on anterior lens capsules. In Group 2 human corneal endothelial cells grew on a collagen membrane and in Group 3 on polystyrene culture plates. Cell density, morphology and adherence of the cell-capsule complex were evaluated at 1, 4, 7 and 14days with a phase-contrast microscope, a scanning electron microscope and by histology. Cell viability was quantified by a microscopic live-dead assay. Expression of zonula occludens-1, Na(+) /K(+) -adenosine triphosphatase, tissue transglutaminase and vimentin were investigated by immunohistochemistry.A mean diameter of 10.05±0.13mm of anterior capsule was obtained as a substrate for cell culture. Endothelial cell density of Group 1 was measured at 2455.4±283.8cells/mm(2) , which was also comparable with the cell density of the control group. Cell viability was 95% or superior in all groups and multiple cellular interconnections developed between growing cells. Immunohistochemical analysis demonstrated strongly positive staining for all investigated proteins. Electron microscopy confirmed the adherence and monolayer growth of the endothelial cells.Human donor anterior lens capsule might therefore be a potential scaffold for the ex vivo expansion of human corneal endothelial cells.
EVALuna2:21107

Designing novel scaffolds for ocular surface reconstruction based on aligned nanofibers - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Design of an Integrated Subretinal Implant Using Cellular Neural Networks for Binary Image Generation in a 130 nm BiCMOS Process - Potschka, Julian; Söll, Christopher; Kirchner, Jens; Mardin, Christian Y.; Stadelmayer, Markus; Maiwald, Tim; Breun, Sascha; Kolb, Katharina; Bauch, Andreas; Dietz, Marco; Beck, Christopher; Völkel, Matthias; et al. (IEEE Engineering in Medicine and Biology Conference (EMBC), 2019)

Detailed Illustration of the Visual Field Representation along the Visual Pathway to the Primary Visual Cortex: A Graphical Summary - Wärntges, Simone; Michelson, Georg (Ophthalmic Research, 2014)
Purpose: In the literature, different graphic illustrations are available, which depict different parts of the visual pathway in relation to visual field sectors, to retinal sectors, the layers of the lateral geniculate nucleus (LGN), or sections of the primary visual cortex (V1). However, a complete overview is missing, which may be useful for a more precise differentiation of predominantly ophthalmological from intracerebral diseases. It may also be of interest to investigate additional intracerebral reasons that are involved in impaired vision of largely unknown pathophysiology. Methods: This work combines the scientific knowledge of partial graphics in one detailed illustration that allows exact follow-up of the neuronal connections from individual visual field sectors to the V1 areas. A selective search for peer-reviewed graphics of the visual pathway was performed in PubMed and Google Pictures. Results: Sixteen different visual field sectors and their 16 corresponding retinal sectors were set in relation to 64 LGN sections and 20 areas of V1. Segmented cross-sectional areas of the optic nerve supplemented the graphical representation of the fiber orientation in relation to the visual field. Conclusion: The detailed illustration of the visual field projection along the visual pathway structures may facilitate a more precise calculation of correlations between morphological and functional measurements of ophthalmological and neuroradiological examinations. © 2013 S. Karger AG, Basel.
EVALuna2:21142

Detection of Mild Traumatic Brain Injury by a Virtual Reality System - Kara, David Delil; Ring, Matthias; Mehringer, Wolfgang; Eskofier, Björn; Hennig, Friedrich; Michelson, Georg (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Detection of surfactant proteins A, B, C, and D in human nasal mucosa and their regulation in chronic rhinosinusitis with polyps - Schicht, Martin; Knipping, Stephan; Hirt, Roman; Beileke, Stephanie; Sel, Saadettin; Paulsen, Friedrich; Bräuer, Lars (American Journal of Rhinology & Allergy, 2013)
Backround: The nasal mucosa is characterized by a multirow high prismatic ciliated epithelium representing the first barrier of the immune defense system against microbial and other environmental pathogenic influences. A number of nonspecific defense mechanisms, including the presence of lactoferrin, peroxidases, proteases, interferons, and lysozymes in nasal secretions, act to counter inflammatory processes. The surfactant proteins (SPs) known from the lungs are important components of the innate immune system. They also influence the rheology of fluids and reduce the surface tension of gas-fluid interphases. The objective of this study was to investigate the protein expression of all four SPs. A specific aim was detection and characterization of SP-C, which had previously not been confirmed in human nasal mucosa. Methods: The expression of mRNA for SP-A, -B, -C and -D was investigated using reverse transcriptase polymerase chain reaction on samples of both healthy nasal mucosa and nasal mucosa altered by inflammatory processes (allergic rhinitis and chronic rhinosinusitis). The distribution of all four proteins was determined with monoclonal antibodies using Western blot analysis as well as immunohistochemical methods. Results: The results show that all four SPs, including SP-C not detected before this, are nasal mucosa components. A shift was also observed in the expression behavior of the SP-A, -B, and -D in nasal mucosa with inflammatory changes. Conclusion: Based on these results, SPs appear to have an important function in immunologic and rheological process of the nasal mucosa and support the prospective therapeutic use of liposomal nasal sprays. Copyright © 2013, OceanSide Publications, Inc., U.S.A.
CRIS-Team Scopus Importer:2022-08-05

Deturgescence using dextran negatively affects corneal endothelial cell viability of pre-stripped grafts for Descemet's Membrane Endothelial Keratoplasty - Menzel-Severing, Johannes; Geerling, Gerd; Kruse, Friedrich; Walter, Peter; Salla, Sabine (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Development of a binocular video-ophthalmoscope to compare parameters of heart beat induced blood volume changes between both eyes - Tornow, Ralf-Peter; Horn, Folkert; Odstrcilik, Jan; Kolar, Radim (2018)
EVALuna2:34921

Developments in non-invasive visual electrophysiology - Kremers, Jan; McKeefry, Declan J.; Murray, Ian J.; Parry, Neil R.A. (Vision research, 2020)
To study the physiology of the primate visual system, non-invasive electrophysiological techniques are of major importance. Two main techniques are available: the electroretinogram (ERG), a mass potential originating in the retina, and the visual evoked potential (VEP), which reflects activity in the primary visual cortex. In this overview, the history and the state of the art of these techniques are briefly presented as an introduction to the special issue “New Developments in non-invasive visual electrophysiology”. The overview and the special issue can be used as the starting point for exciting new developments in the electrophysiology of primate and mammalian vision.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Cortical pathways; Electrophysiology; Electroretinography; Retinal pathways; Visual evoked potentials

Diabetic Macular Edema in Diabetological Practices - Michelson, Georg; Forst, Thomas (Klinische Monatsblätter für Augenheilkunde, 2020)
Using mobile OCT equipment and remote ophthalmological diagnosis of n = 1538 diabetics in 17 diabetes practices in Germany, we found diabetic macular edema in 10.1% of the patients and retinal bleedings or microaneurysms in 15.6%. In 1.62% of the diabetics examined, the size of the edema was > 0.4 mm², in 7% the retinal thickness was > 300 µm and thus in need of treatment. An intravitreal anti-VEGF injection was administered prior to the examination in only 10% of the patients with diabetic macular edema. By means of mobile tele-eye consultation and remote ophthalmological diagnosis using the cloud-based patient file certified as medical device IIa, patients with diabetic macular edema were identified and informed on site quickly and definitively. The data and images were made available to all attending physicians and ophthalmic surgeons.
CRIS-Team Scopus Importer:2020-11-27

Diagnosis of X-Linked Hypohidrotic Ectodermal Dysplasia by Meibography and Infrared Thermography of the Eye - Kärcher, Thomas; Dietz, Jasna; Jacobi, Christina; Berz, Reinhold; Schneider, Holm (Current Eye Research, 2015)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is the most common form of ectodermal dysplasia. Clinical characteristics include meibomian gland disorder and the resulting hyperevaporative dry eye. In this study, we evaluated meibography and ocular infrared thermography as novel methods to diagnose XLHED.Eight infants, 12 boys and 14 male adults with XLHED and 12 healthy control subjects were subjected to a panel of tests including the ocular surface disease index (OSDI), meibography and infrared thermography, non-invasive measurement of tear film break-up time (NIBUT) and osmolarity, Schirmer's test, lissamine green staining and fluorescein staining. Sensitivity and specificity were determined for single tests and selected test combinations.Meibography had 100% sensitivity and specificity for identifying XLHED. Infrared thermography, a completely non-invasive procedure, revealed a typical pattern for male subjects with XLHED. It was, however, less sensitive (86% for adults and 67% for children) than meibography or a combination of established routine tests. In adults, OSDI and NIBUT were the best single routine tests (sensitivity of 86% and 71%, respectively), whereas increased tear osmolarity appeared as a rather unspecific ophthalmic symptom. In children, NIBUT was the most convincing routine test (sensitivity of 91%).Meibography is the most reliable ophthalmic examination to establish a clinical diagnosis in individuals with suspected hypohidrotic ectodermal dysplasia, even before genetic test results are available. Tear film tests and ocular surface staining are less sensitive in children, but very helpful for estimating the severity of ocular surface disease in individuals with known XLHED.
EVALuna2:18886

Dichoptic Binocular Vision Training Improved Stereo Vision in Top Athletes - Michelson, Georg; Kutzner, Benedikt; Mehringer, Wolfgang; Paulus, Jan; Ring, Matthias; Eskofier, Björn (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Die Blut-Augen-Schranken und ihre Störungen: Anatomie, Physiologie, Pathologie - Braunger, Barbara M.; Gießl, Andreas; Schlötzer-Schrehardt, Ursula (Klinische Monatsblätter für Augenheilkunde, 2023)
Complex barriers comprise the blood-aqueous (BAB) and the blood-retinal barrier (BRB), and separate anterior and posterior eye chambers, vitreous body, and sensory retina from the circulation. They prevent pathogens and toxins from entering the eye, control movement of fluid, proteins, and metabolites, and contribute to the maintenance of the ocular immune status. Morphological correlates of blood-ocular barriers are tight junctions between neighboring endothelial and epithelial cells, which function as gatekeepers of the paracellular transport of molecules, thereby limiting their uncontrolled access to ocular chambers and tissues. The BAB is composed of tight junctions between endothelial cells of the iris vasculature, endothelial cells of Schlemm's canal inner wall, and cells of the nonpigmented ciliary epithelium. The BRB consists of tight junctions between endothelial cells of the retinal vessels (inner BRB) and epithelial cells of the retinal pigment epithelium (outer BRB). These junctional complexes respond rapidly to pathophysiological changes, thus enabling vascular leakage of blood-derived molecules and inflammatory cells into ocular tissues and chambers. Blood-ocular barrier function, which can be clinically measured by laser flare photometry or fluorophotometry, is compromised in traumatic, inflammatory, or infectious processes, but also frequently contributes to the pathophysiology of chronic diseases of the anterior eye segment and the retina, as exemplified by diabetic retinopathy and age-related macular degeneration.
CRIS-Team Scopus Importer:2023-06-02

Die „DOG 2020 online“ – erstmals im von-Graefe-Jahr - Hohberger, Bettina (Ophthalmologe, 2021)
CRIS-Team Scopus Importer:2021-02-05

Die Papille als Screening-Parameter auf Glaukom - Die Papille beim Glaukom - Michelson, Georg; Hornegger, Joachim; Lausen, Berthold (Glaukom 2007, 2008)

Die Papille als Screening-Parameter für die Früherkennung des Glaukoms - The papilla as screening parameter for early diagnosis of glaucoma - Michelson, Georg; Hornegger, Joachim; Wärntges, Simone; Lausen, Berthold (Deutsches Ärzteblatt, 2008)

Diet enriched with the Amazon fruit açaí (Euterpe oleracea) prevents electrophysiological deficits and oxidative stress induced by methyl-mercury in the rat retina - Brasil, Aldia; De Farias Rocha, Fernando Allan; Gomes, Bruno Duarte; Oliveira, Karen Renata M.; De Carvalho, Tayana Silva; Batista, Evander De Jesus O.; Borges, Rosivaldo Dos Santos; Kremers, Jan; Herculano, Anderson Manoel (Nutritional Neuroscience, 2016)
Background The protective effect of a diet supplemented by the Amazonian fruit Euterpe oleracea (EO) against methylmercury (MeHg) toxicity in rat retina was studied using electroretinography (ERG) and biochemical evaluation of oxidative stress. Method Wistar rats were submitted to conventional diet or EO-enriched diet for 28 days. After that, each group received saline solution or 5 mg/kg/day of MeHg for 7 days. Full-field single flash, flash and flicker ERGs were evaluated in the following groups: control, EO, MeHg, and EO+MeHg. The amplitudes of the a-wave, b-wave, photopic negative response from rod and/or cone were measured by ERGs as well as the amplitudes and phases of the fundamental component of the sine-wave flicker ERG. Lipid peroxidation was determined by thiobarbituric acid reactive species. Results All ERG components had decreased amplitudes in the MeHg group when compared with controls. EO-enriched food had no effect on the non-intoxicated animals. The intoxicated animals and those that received the supplemented diet presented significant amplitude reductions of the cone b-wave and of the fundamental flicker component when compared with non-intoxicated control. The protective effect of the diet on scotopic conditions was only observed for bright flashes eliciting a mixed rod and cone response. There was a significant increase of lipid peroxidation in the retina from animals exposed to MeHg and EO-supplemented diet was able to prevent MeHg-induced oxidative stress in retinal tissue. Conclusion These findings open up perspectives for the use of diets supplemented with EO as a protective strategy against visual damage induced by MeHg.
EVALuna2:21319
Keywords: Retina; Electroretinogram; Methyl-mercury; Oxidative stress; Euterpe oleracea

Differential Effects of Aging in the Macular Retinal Layers, Neuroretinal Rim, and Peripapillary Retinal Nerve Fiber Layer - Chauhan, Balwantray C.; Vianna, Jayme R.; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Scheuerle, Alexander F.; Burgoyne, Claude F. (Ophthalmology, 2019)
Purpose: We determined the differential aging effects of the inner 6 layers of the macula in contrast to the minimum neuroretinal rim width (MRW) and peripapillary retinal nerve fiber layer (RNFL) thickness. Design: Cross-sectional, multicenter study. Participants: An approximately equal number of white subjects with a normal ocular and visual field examination in each decade group from 20 to 90 years. Methods: OCT of the macula, optic nerve head, and peripapillary retina. Main Outcome Measures: Sectoral measurements of the inner 6 layers of the macula; age-related decline of each of these layers; strength of the associations with age of the macular parameters, MRW, and peripapillary RNFL thickness; and association between ganglion cell layer (GCL) thickness and MRW and peripapillary RNFL thickness. Results: The study sample comprised 1 eye of 246 subjects with a median (range) age of 52.9 (19.8–87.3) years. Of the 6 layers, there was a statistically significant decline with age of only the GCL, inner plexiform layer, and inner nuclear layer thickness with rates of −0.11 μm/year, −0.07 μm/year, and −0.03 μm/year, respectively. These rates corresponded to 2.82%, 2.10%, and 0.78% loss per decade, respectively, and were generally uniform across sectors. The rate of loss of MRW and peripapillary RNFL thickness was −1.22 μm/year and −0.20 μm/year, corresponding to 3.75% and 2.03% loss per decade. However, the association of GCL thickness change with age (R2 = 0.28) was approximately twice that of MRW and RNFL thickness (R2 = 0.14 for each). Conclusions: In concordance with histopathologic studies showing age-related loss of retinal ganglion cell axons, we showed a significant decline in GCL thickness, as well as MRW and peripapillary RNFL thickness. The stronger relationship between aging and GCL thickness compared with the rim or peripapillary RNFL may indicate that GCL thickness could be better suited to measure progression of structural glaucomatous loss.
CRIS-Team Scopus Importer:2019-11-12

Diffusion tensor imaging of the visual pathway in glaucomatous optic nerve atrophy - Engelhorn, Tobias; A. Schmidt, M.; Dörfler, Arnd; Michelson, Georg (Ophthalmologe, 2017)
In Germany more than one million inhabitants suffer from glaucoma, more than 100,000 are threatened with blindness because glaucoma is often diagnosed too late or not at all. Diagnosis and monitoring is usually carried out "only" by examination of the retina and not the whole visual pathway. However, the eye is just "the tip of the iceberg" of the actual visual pathway, which extends through the brain to the visual cortex. The interdisciplinary holistic assessment of the whole visual pathway in glaucoma is of crucial importance because glaucoma is a complex neurodegenerative disease. Subtypes, such as normal tension glaucoma (NTG), seem to originate from primary damage to the intracranial visual pathway with secondary retrograde retinal degeneration. Recent studies including glaucoma patients and healthy controls could show that diffusion tensor imaging with calculation of diffusion coefficients, i.e. fractional anisotropy (FA), mean and radial diffusivity (MD and RD) as markers of axonal integrity, provide the potential to assess the intracranial visual pathway with a high correlation to established ophthalmological examinations. In particular, calculation of FA maps of the visual pathway and accompanying voxel-based approaches, can be integrated into clinical routine. Thus, detection of glaucoma-related intracranial alterations, even in early stages of the disease, as well as differentiation of different glaucoma subtypes, is made possible. Furthermore, the diagnosis of normal tension glaucoma seems to be possible much earlier with these new imaging techniques compared to established ophthalmological work-up. Moreover, holistic imaging provides new insights into the pathophysiology of this form of glaucoma. This review article gives an overview of these novel magnetic resonance imaging techniques for assessment of the visual pathway in glaucomatous optic nerve atrophy and reveals the potential of an interdisciplinary approach.
EVALuna2:21333

Discriminating anomalous trichromacy and cone degeneration in retinitis pigmentosa patients - Fars, Julien; Kremers, Jan; Huchzermeyer, Cord (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Diseases and Surgery of the Orbit - Plontke, Stefan K.; Glien, Alexander; Kisser, Ulrich; Viestenz, Arne; Heichel, Jens (Laryngo-Rhino-Otologie, 2020)
CRIS-Team WoS Importer:2021-01-01

Distribution of the neuro-regulatory peptide galanin in the human eye - Kaser-Eichberger, Alexandra; Trost, Andrea; Strohmaier, Clemens; Bogner, Barbara; Runge, Christian; Bruckner, Daniela; Hohberger, Bettina; Jünemann, Anselm; Kofler, Barbara; Reitsamer, Herbert A.; Schrödl, Falk (Neuropeptides, 2016)
Galanin (GAL) is a neuro-regulatory peptide involved in many physiological and pathophysiological processes. While data of GAL origin/distribution in the human eye are rather fragmentary and since recently the presence of GAL-receptors in the normal human eye has been reported, we here systematically search for sources of ocular GAL in the human eye. Human eyes (n=14) were prepared for single- and double-immunohistochemistry of GAL and neurofilaments (NF). Cross- and flat-mount sections were achieved; confocal laser-scanning microscopy was used for documentation. In the anterior eye, GAL-immunoreactivity (GAL-IR) was detected in basal layers of corneal epithelium, endothelium, and in nerve fibers and keratinocytes of the corneal stroma. In the conjunctiva, GAL-IR was seen throughout all epithelial cell layers. In the iris, sphincter and dilator muscle and endothelium of iris vessels displayed GAL-IR. It was also detected in stromal cells containing melanin granules, while these were absent in others. In the ciliary body, ciliary muscle and pigmented as well as non-pigmented ciliary epithelium displayed GAL-IR. In the retina, GAL-IR was detected in cells associated with the ganglion cell layer, and in endothelial cells of retinal blood vessels. In the choroid, nerve fibers of the choroidal stroma as well as fibers forming boutons and surrounding choroidal blood vessels displayed GAL-IR. Further, the majority of intrinsic choroidal neurons were GAL-positive, as revealed by co-localization-experiments with NF, while a minority displayed NF- or GAL-IR only. GAL-IR was also detected in choroidal melanocytes, as identified by the presence of intracellular melanin-granules, as well as in cells lacking melanin-granules, most likely representing macrophages. GAL-IR was detected in numerous cells and tissues throughout the anterior and posterior eye and might therefore be an important regulatory peptide for many aspects of ocular control. Upcoming studies in diseased tissue will help to clarify the role of GAL in ocular homeostasis.
EVALuna2:21283

Donor tissue culture conditions and outcome after descemet membrane endothelial keratoplasty - Laaser, Kathrin; Bachmann, Bjoern O.; Horn, Folkert; Schlötzer-Schrehardt, Ursula; Cursiefen, Claus; Kruse, Friedrich (American Journal of Ophthalmology, 2011)
To investigate the effect of culture conditions of donor tissue on functional outcome after Descemet membrane endothelial keratoplasty.Retrospective, single-center, consecutive case series.Descemet membrane endothelial keratoplasty was performed routinely in 82 eyes of 82 consecutive patients using corneal donor tissue prestored in either short-term culture (Optisol-GS; Bausch & Lomb) at 4 C (group A; n = 37) or organ culture (Dulbecco Modified Eagle Medium [Biochrom]; CorneaMax Medium [Eurobio]) at 34 C (group B; n = 45) in a randomized fashion. Main outcome measures included the number of air injections necessary for graft attachment as well as best-corrected visual acuity (in logarithm of the minimal angle of resolution [logMAR] units), central corneal thickness, and endothelial cell density at 1, 3, and 6 months after surgery.Best-corrected visual acuity increased from 0.69 ± 0.53 logMAR and 0.67 ± 0.31 logMAR before surgery to 0.33 ± 0.21 logMAR and 0.28 ± 0.18 logMAR after 1 month (P < .05), to 0.24 ± 0.16 logMAR and 0.18 ± 0.16 logMAR after 3 months (P < .05), and to 0.18 ± 0.12 logMAR and 0.15 ± 0.10 logMAR after 6 months (n.s.) in groups A and B, respectively. Endothelial cell density decreased from 2647 ± 236 cells/mm(2) and 2515 ± 249 cells/mm(2) before surgery to 1499 ± 277 cells/mm(2) and 1526 ± 205 cells/mm(2) after 1 month (P < .05), to 1441 ± 213 cells/mm(2) and 1443 ± 316 cells/mm(2) after 3 months (n.s.), and to 1587 ± 366 cells/mm(2) and 1457 ± 285 cells/mm(2) after 6 months (n.s.) in groups A and B, respectively. Central corneal thickness declined from 664 ± 89 and 662 ± 107 ?m before surgery to 529 ± 92 ?m and 517 ± 62 ?m after 1 month (P < .05), to 511 ± 46 ?m and 510 ± 46 ?m after 3 months (P < .05), and to 529 ± 68 ?m and 507 ± 50 ?m after 6 months (n.s.) in groups A and B, respectively. Best-corrected visual acuity, endothelial cell density, and central corneal thickness values showed no significant differences between both groups at any time point after surgery. However, a significantly higher total number of air injections was necessary in group A (n = 34) compared with group B (n = 26) to obtain graft attachment (P < .05).These findings suggest that donor tissue culture conditions have no significant effect on functional outcome, but may influence graft adhesion and rebubbling rate after Descemet membrane endothelial keratoplasty surgery.
EVALuna2:21002

Drug discovery for the treatment of Fuchs corneal endothelial dystrophy by cell-based drug screening system - Nakagawa, Risako; Okumura, Naoki; Onishi, Takako; Oshima, Takeshi; Ueda, Emi; Watanabe, Kyoko; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

DTI analysis in patients with primary open-angle glaucoma: impact of registration on Voxel-Wise statistics - Schmidt, Manuel; Mennecke, Angelika; Michelson, Georg; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2014)
Tract-based spatial statistics (TBSS) has been used to assess the integrity of the visual pathway in glaucoma patients. TBSS uses the subjects' FA data to create a mean FA skeleton of white matter tracts before running voxel-wise cross-subject statistics. We compared four different approaches of registration of FA maps to create the skeleton and evaluated alignment and subsequently the impact of the chosen registration on voxel-wise statistics.Our study comprised 69 subjects, i.e. 46 patients with primary open angle glaucoma (POAG) and a healthy, age-matched control group of 23 subjects. Mean FA skeletons were created using the following registration approaches: registration to a standard template (T), registration to the group mean (GM), registration to a group-wise atlas (GW) and registration to the most typical subject (N). Subsequently, maps of standard deviation of the 4D images were created to assess the alignment. Voxel-wise statistics for each registration approach were performed.We found distinct differences in voxel-wise statistics depending on the chosen registration approach. Best alignment results were achieved by registration to a study specific template, i.e. to the group mean (GM) or to a group-wise atlas (GW). Overall alignment did not differ between these two approaches. However, voxel-wise statistics showed clusters of significantly decreased FA values in the T and GM approach, which were not significant after GW registration. These voxels of significantly decreased FA values after T and GM registration did not represent white matter tracts and correlated with higher standard deviation in FA maps across subjects, thus implying registration errors, especially in the optic radiation.Registration to a study-specific template, i.e. to the group mean or a group-wise atlas seems to be the method of choice in TBSS-analysis of glaucoma patients as it shows better alignment of the optic radiation and helps to rule out registration errors due to misalignment.
EVALuna2:21168

DTI parameters of axonal integrity and demyelination of the optic radiation correlate with glaucoma indices - Michelson, Georg; Engelhorn, Tobias; Wärntges, Simone; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Graefes Archive For Clinical and Experimental Ophthalmology, 2013)
EVALuna2:21070

Dynamics of adaptation process to different light levels in the mouse retina studied with ERGs - Joachimsthaler, Anneka; Tsai, Tina I.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

Dysfunction of the limbal epithelial stem cell niche in aniridia-associated keratopathy: Limbal niche in aniridia-associated keratopathy - Schlötzer-Schrehardt, Ursula; Latta, Lorenz; Gießl, Andreas; Zenkel, Matthias; Fries, Fabian N.; Käsmann-Kellner, Barbara; Kruse, Friedrich; Seitz, Berthold (Ocular Surface, 2021)
Purpose: Abnormalities in the limbal niche microenvironment have been suggested to be causally involved in aniridia-associated keratopathy (AAK), but histological analyses on the limbal structure and composition in AAK are lacking. Here, we investigated morphologic and molecular alterations of the limbal epithelial stem cell niche in human congenital aniridia. Methods: The blind, buphthalmic and painful left eye of a 16-year old girl with congenital aniridia and juvenile glaucoma had to be enucleated because of uncontrolled intraocular pressure. The diagnosis of AAK was based on classical clinical features and partial limbal stem cell deficiency in the superior half. Genetic analysis identified a large heterozygous PAX6 gene deletion encompassing exons 11–15 as well as exon 9 of the neighboring ELP4 gene. Three limbal biopsies were taken from the superior, nasal and temporal regions to isolate and cultivate limbal epithelial progenitor cells and subject them to mRNA expression analyses. The globe was vertically bisected and processed for light and transmission electron microscopy and immunohistochemistry. Results: Comparative analysis of the superior and inferior limbal zones showed a gradual degradation of palisade structures associated with the transition from a hyperplastic to an attenuated corneal epithelium, inflammatory cell infiltrations and basement membrane irregularities. The clinically unaffected inferior part revealed no distinct stem cell clusters in the preserved palisade region, but a uniform population of hyperproliferative, undifferentiated progenitor cells in the basal/suprabasal layers of limbal and corneal epithelia, which gave rise to maldifferentiated epithelial cells exhibiting a conjunctival/epidermal phenotype and nuclear-to-cytoplasmic translocation of Pax6. The structure of the limbal niche was fundamentally perturbed, showing marked alterations in extracellular matrix composition, dislocation of atypical melanocytes lacking melanosomes and melanin, aberrant Wnt/β-catenin and retinoic acid signaling, and massive immune cell infiltration. Conclusions: Considering the limitations of a single Case study, the findings suggest that ocular surface alterations in AAK are caused by a primary dysfunction and gradual breakdown of the limbal stem cell niche through Pax6-related effects on both melanogenesis and epithelial differentiation.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Aniridia-associated keratopathy; Extracellular matrix; Immunohistochemistry; Limbal stem cell niche; Melanocytes; Pax6

Dyslipidaemia and glaucoma - Jünemann, Anselm; Huchzermeyer, Cord; Rejdak, R.; Hohberger, B. (Klinische Monatsblätter für Augenheilkunde, 2014)
Endothelial dysfunction and vascular dysregulation play a role in the multifactorial pathogenesis of glaucomatous optic nerve atrophy. Dyslipidaemia as a risk factor for endothelial dysfunction is associated with glaucoma and cardiovascular morbidity and mortality. In additional to a genetic disposition, a potential mechanism for the pathogenesis of endothelial dysfunction could be an additive effect of several risk factors, like dyslipidaemia, smoking, arterial hypertension, diabetes and hyperhomocysteinaemia. This paper reviews the literature concerning the association between dyslipidaemia and glaucomatous disease and explains the possible role of dyslipidaemia for the pathogenesis and progression of glaucoma. The role of exogeneous modifiable risk factors for prevention and therapy of glaucoma and their neutralisation by changing life style like weight reduction, modifications of nutrition and physical activity, are discussed.
EVALuna2:21178

Dysregulated Retinoic Acid Signaling in the Pathogenesis of Pseudoexfoliation Syndrome - Zenkel, Matthias; Hoja, Ursula; Gießl, Andreas; Berner, Daniel; Hohberger, Bettina; Weller, Julia; König, Loretta; Huebner, Lisa; Ostermann, Thomas A.; Gusek-Schneider, Gabriele; Kruse, Friedrich; Pasutto, Francesca; et al. (International Journal of Molecular Sciences, 2022)
Pseudoexfoliation (PEX) syndrome, a stress-induced fibrotic matrix process, is the most common recognizable cause of open-angle glaucoma worldwide. The recent identification of PEX-associated gene variants uncovered the vitamin A metabolic pathway as a factor influencing the risk of disease. In this study, we analyzed the role of the retinoic acid (RA) signaling pathway in the PEX-associated matrix metabolism and evaluated its targeting as a potential candidate for an anti-fibrotic intervention. We provided evidence that decreased expression levels of RA pathway components and diminished RA signaling activity occur in an antagonistic crosstalk with TGF-beta 1/Smad signaling in ocular tissues and cells from PEX patients when compared with age-matched controls. Genetic and pharmacologic modes of RA pathway inhibition induced the expression and production of PEX-associated matrix components by disease-relevant cell culture models in vitro. Conversely, RA signaling pathway activation by natural and synthetic retinoids was able to suppress PEX-associated matrix production and formation of microfibrillar networks via antagonization of Smad-dependent TGF-beta 1 signaling. The findings indicate that deficient RA signaling in conjunction with hyperactivated TGF-beta 1 /Smad signaling is a driver of PEX-associated fibrosis, and that restoration of RA signaling may be a promising strategy for anti-fibrotic intervention in patients with PEX syndrome and glaucoma.
CRIS-Team WoS Importer:2022-06-24
Keywords: pseudoexfoliation syndrome; pseudoexfoliation glaucoma; retinol; retinoic acid; extracellular matrix; fibrosis; TGF-β1

Dystrophin Is Required for Proper Functioning of Luminance and Red-Green Cone Opponent Mechanisms in the Human Retina - Salgueiro Barboni, Mirella Telles; Gomes Martins, Cristiane Maria; Nagy, Balazs Vince; Tsai, Tina; Damico, Francisco Max; Da Costa, Marcelo Fernandes; Cassia, Rita De; Pavanello, M.; Vilaca Lourenco, Naila Cristina; Pereirade Cerqueira, Antonia Maria; Zatz, Mayana; Kremers, Jan; et al. (Investigative Ophthalmology & Visual Science, 2016)
Visual information is processed in parallel pathways in the visual system. Parallel processing begins at the synapse between the photoreceptors and their postreceptoral neurons in the human retina. The integrity of this first neural connection is vital for normal visual processing downstream. Of the numerous elements necessary for proper functioning of this synaptic contact, dystrophin proteins in the eye play an important role. Deficiency of muscle dystrophin causes Duchenne muscular dystrophy (DMD), an X-linked disease that affects muscle function and leads to decreased life expectancy. In DMD patients, postreceptoral retinal mechanisms underlying scotopic and photopic vision and ON- and OFF-pathway responses are also altered.In this study, we recorded the electroretinogram (ERG) while preferentially activating the (red-green) opponent or the luminance pathway, and compared data from healthy participants (n = 16) with those of DMD patients (n = 10). The stimuli were heterochromatic sinusoidal modulations at a mean luminance of 200 cd/m2. The recordings allowed us also to analyze ON and OFF cone-driven retinal responses.We found significant differences in 12-Hz response amplitudes and phases between controls and DMD patients, with conditions with large luminance content resulting in larger response amplitudes in DMD patients compared to controls, whereas responses of DMD patients were smaller when pure chromatic modulation was given.The results suggest that dystrophin is required for the proper function of luminance and red-green cone opponent mechanisms in the human retina.
EVALuna2:21300

Early Signs of End-Organ Damage in Retinal Arterioles in Patients with Type 2 Diabetes Compared to Hypertensive Patients - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Michelson, Georg; Harazny, Joanna M.; Schmieder, Roland (Microcirculation, 2016)
Eutrophic and hypertrophic remodeling are major vascular hallmarks for hypertension and diabetes-associated microvascular end-organ damage in peripheral arterioles. The aim of this study is to compare retinal arterioles of diabetic, hypertensive, and healthy individuals.Retinal parameters were assessed in 99 patients with T2DM, 158 hypertensive, and 149 healthy individuals. WT and CA of retinal arterioles (80-140 ?m) were measured noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany).After adjustment for values differing between the groups (age, BMI, gender, HDL cholesterol and serum creatinine, systolic office BP), patients with T2DM showed no significant difference in WT (14.2 ± 3), and CA (4199 ± 1107) in comparison with hypertensive patients (WT = 13.3 ± 4, p = 0.18, CA = 3862 ± 1546, p = 0.10) and healthy individuals (WT = 13.1 ± 3, p = 0.55, CA = 3864 ± 1216, p = 0.86). However, the subgroup of patients with diabetes duration of more than 60 months showed greater WT (14.9 ± 4, p = 0.04) and CA (4557 ± 1137, p = 0.02) than the hypertensive group and greater WT (p = 0.04) and CA (p = 0.03) than the healthy group, which is consistent with hypertrophic remodeling.In the early stage of T2DM no hypertrophic remodeling was seen in retinal arterioles. However, hypertrophic remodeling was found in diabetic patients with more than 60 months duration of disease.
EVALuna2:3870

Effective isolation and expansion of human limbal niche cells - Gießl, Andreas; Polisetti, Naresh; Li, Shen; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Effect of CTG repeat expansion in TCF4 on the pathophysiology of Fuchs endothelial corneal dystrophy - Matsuo, Hinata; Okumura, Naoki; Komori, Yuya; Tokunaga, Ayumi; Nakayama, Genta; Nakahara, Makiko; Blake, Derek J.; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Effect of Trinucleotide Repeat Expansion on the Expression of TCF4 mRNA in Fuchs' Endothelial Corneal Dystrophy - Okumura, Naoki; Hayashi, Ryosuke; Nakano, Masakazu; Yoshii, Kengo; Tashiro, Kei; Sato, Takahiko; Blake, Derek J.; Aleff, Ross; Butz, Malinda; Highsmith, Edward W.; Wieben, Eric D.; Fautsch, Michael P.; et al. (Investigative Ophthalmology & Visual Science, 2019)
PURPOSE. CTG trinucleotide repeat (TNR) expansion is frequently found in transcription factor 4 (TCF4) in Fuchs' endothelial corneal dystrophy (FECD), though the effect of TNR expansion on FECD pathophysiology remains unclear. The purpose of this study was to evaluate the effect of TNR expansion on TCF4 expression in corneal endothelium of patients with FECD.
CRIS-Team WoS Importer:2019-03-15

Effects of Mild Traumatic Brain Injury on Stereopsis Detected by a Virtual Reality System: Attempt to Develop a Screening Test - Kara, David Delil; Ring, Matthias; Hennig, Friedrich; Michelson, Georg (Journal of Medical and Biological Engineering, 2020)
Purpose: The study aimed to evaluate stereopsis as a surrogate marker for post-concussion oculomotor function to develop an objective test that can reliably and quickly detect mild traumatic brain injuries (TBI). Methods: The cohort of this prospective clinical study included 30 healthy subjects (mean age 25 ± 2 years) and 30 TBI patients (43 ± 22 years) comprising 11 patients with moderate TBI and 19 patients with mild TBI. The healthy subjects were examined once, whereas the TBI patients were examined immediately after hospitalization, at 1 week, and at 2 months. A virtual reality (VR) program displayed three-dimensional rendering of four rotating soccer balls over VR glasses in different gaze directions. The subjects were instructed to select the ball that appeared to be raised from the screen as quickly as possible via remote control. The response times and fusion abilities in different gaze directions were recorded. Results: The correlation between stereopsis and TBI severity was significant. The response times of the moderate and mild TBI groups were significantly longer than those of the healthy reference group. The response times of the moderate TBI group were significantly longer than those of the mild TBI group. The response times at follow-up examinations were significantly shorter than those immediately after hospitalization. Fusion ability was primarily defective in the gaze direction to the right (90°) and left (270° and 315°). Conclusions: TBI patients showed impaired stereopsis. Measuring stereopsis in different positions of the visual field using VR can be effective for rapid concussion assessment.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Clinical assessment; Concussion; Sports trauma; Stereopsis; Traumatic brain injury; Virtual reality

Effects of Preprocessing Eye Fundus Images on Appearance Based Glaucoma Classification - Meier, Jörg; Bock, Rüdiger; Michelson, Georg; Nyul, Laszlo Gabor; Hornegger, Joachim (Springer-verlag, 2007)
Early detection of glaucoma is essential for preventing one of the most common causes of blindness. Our research is focused on a novel automated classification system based on image features from fundus photographs which does not depend on structure segmentation or prior expert knowledge. Our new data driven approach that needs no manual assistance achieves an accuracy of detecting glaucomatous retina fundus images compareable to human experts. In this paper, we study image preprocessing methods to provide better input for more reliable automated glaucoma detection. We reduce disease independent variations without removing information that discriminates between images of healthy and glaucomatous eyes. In particular, nonuniform illumination is corrected, blood vessels are inpainted and the region of interest is normalized before feature extraction and subsequent classification. The effect of these steps was evaluated using principal component analysis for dimension reduction and support vector machine as classifier. © Springer-Verlag Berlin Heidelberg 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD5.effect_2
Keywords: Classification; Digital color fundus photograph; Glaucoma; Image enhancement; Retina imaging

Efficacy and safety of indomethacin 0.1% eye drops compared with ketorolac 0.5% eye drops in the management of ocular inflammation after cataract surgery - Weber, Michel; Kodjikian, Laurent; Kruse, Friedrich; Zagorski, Zbigniew; Allaire, Catherine M. (Acta Ophthalmologica, 2013)
Purpose: To determine whether indomethacin 0.1% eye drops are at least as effective as ketorolac 0.5% eye drops in treating ocular inflammation following cataract surgery. Methods: Prospective, multicenter, investigator-masked, parallel-group, randomized, active-controlled clinical trial. Cataract patients were randomized in a 1:1 ratio to receive indomethacin or ketorolac administered QID for 3 weeks beginning 1 day before surgery. The primary end-point was aqueous flare measured by laser flare meter at postoperative Days 1 and 7. Secondary end-points included retinal thickness, slit lamp and funduscopic examinations and postsurgical pain ratings. Safety and tolerability were also assessed. Results: A total of 86 patients were included in the per protocol population (n = 43 per treatment group). Indomethacin was found non-inferior to ketorolac for comparison of aqueous flare at postoperative Days 1 and 7 (Day 1: 95% CI: -2.37, 5.50; non-inferiority upper margin, 15 ph/ms and Day 7: 95% CI: -7.83, -0.94; non-inferiority upper margin, 8 ph/ms) and statistically better than ketorolac at Day 7 (p = 0.013). There were no significant between-group differences in aqueous flare and change from baseline in retinal thickness at postoperative Days 30 and 90. Indomethacin showed a higher subjective tolerance rating than ketorolac at postoperative Days 7 and 30 (p <= 0.044). Conclusion: Indomethacin 0.1% was at least as effective as ketorolac 0.5% at Day 1 and more effective than ketorolac 0.5% at Day 7 in treating ocular inflammation after uncomplicated cataract surgery. Indomethacin was better tolerated than ketorolac. There were no clinically meaningful safety concerns with either treatment.
EVALuna2:21108

Efficient and safe gene delivery to human corneal endothelium using magnetic nanoparticles - Czugala, Marta; Mykhaylyk, Olga; Boehler, Philip; Onderka, Jasmine; Stork, Boejrn; Wesselborg, Sebastian; Kruse, Friedrich; Plank, Christian; Singer, Bernhard B.; Fuchsluger, Thomas (Nanomedicine, 2016)
To develop a safe and efficient method for targeted, anti-apoptotic gene therapy of corneal endothelial cells (CECs).Magnetofection (MF), a combination of lipofection with magnetic nanoparticles (MNPs; PEI-Mag2, SO-Mag5, PalD1-Mag1), was tested in human CECs and in explanted human corneas. Effects on cell viability and function were investigated. Immunocompatibility was assessed in human peripheral blood mononuclear cells.Silica iron-oxide MNPs (SO-Mag5) combined with X-tremeGENE-HP achieved high transfection efficiency in human CECs and explanted human corneas, without altering cell viability or function. Magnetofection caused no immunomodulatory effects in human peripheral blood mononuclear cells. Magnetofection with anti-apoptotic P35 gene effectively blocked apoptosis in CECs.Magnetofection is a promising tool for gene therapy of corneal endothelial cells with potential for targeted on-site delivery.
EVALuna2:21292

EFhd2/Swiprosin-1 is a common genetic determinator for sensation-seeking/low anxiety and alcohol addiction - Mielenz, Dirk; Reichel, Martin; Jia, T.; Quinlan, E. B.; Stöckl, Thomas; Mettang, M.; Zilske, Daniel; Kirmizi Alsan, Elif; Schoenberger, P.; Praetner, M.; Huber, Sabine; Amato, Davide; et al. (Molecular Psychiatry, 2017)
In many societies, the majority of adults regularly consume alcohol. However, only a small proportion develops alcohol addiction. Individuals at risk often show a high sensation-seeking/low-anxiety behavioural phenotype. Here we asked which role EF hand domain containing 2 (EFhd2; Swiprosin-1) plays in the control of alcohol addiction-associated behaviours. EFhd2 knockout (KO) mice drink more alcohol than controls and spontaneously escalate their consumption. This coincided with a sensation-seeking and low-anxiety phenotype. A reversal of the behavioural phenotype with β-carboline, an anxiogenic inverse benzodiazepine receptor agonist, normalized alcohol preference in EFhd2 KO mice, demonstrating an EFhd2-driven relationship between personality traits and alcohol preference. These findings were confirmed in a human sample where we observed a positive association of the EFhd2 single-nucleotide polymorphism rs112146896 with lifetime drinking and a negative association with anxiety in healthy adolescents. The lack of EFhd2 reduced extracellular dopamine levels in the brain, but enhanced responses to alcohol. In confirmation, gene expression analysis revealed reduced tyrosine hydroxylase expression and the regulation of genes involved in cortex development, Eomes and Pax6, in EFhd2 KO cortices. These findings were corroborated in Xenopus tadpoles by EFhd2 knockdown. Magnetic resonance imaging (MRI) in mice showed that a lack of EFhd2 reduces cortical volume in adults. Moreover, human MRI confirmed the negative association between lifetime alcohol drinking and superior frontal gyrus volume. We propose that EFhd2 is a conserved resilience factor against alcohol consumption and its escalation, working through Pax6/Eomes. Reduced EFhd2 function induces high-risk personality traits of sensation-seeking/low anxiety associated with enhanced alcohol consumption, which may be related to cortex function.
EVALuna2:4036

Einfluss der Achsenlänge auf die 2-Jahres-Erfolgsrate der Stand-alone-und mit Phako/HKL kombinierten Xen45-Gel-Stentimplantation. - Gernhart, Markus; Hohberger, Bettina; Lämmer, Robert (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Up to now, no data have been available on the therapeutic success rate of Xen45 gel stent with respect to axial length (AL). The present study aimed to investigate a potential influence of AL on therapeutic success in stand-alone Xen45 gel stent implantation or combination with cataract surgery in open-angle glaucoma patients (OAG) with a follow-up of 2 years. Materials and Methods In this retrospective observational study, 98 eyes of 87 glaucoma patients of the Department of Ophthalmology, University of Erlangen Nürnberg, and from the Erlangen Glaucoma Registry (NCT00494923; ISSN 2191-5008, CS-2011) underwent stand-alone Xen45 gel stent implantation or a combination with cataract surgery. Therapeutic success was defined as ≥ 20% IOP reduction with the same or fewer anti-glaucomatous eye drops needed compared to baseline, yet without additional glaucoma-related surgery (expect bleb needling). Therapeutic failure was classified as any additional glaucoma-related surgery, IOP reduction < 20% or if more local anti-glaucomatous eye drops were applied compared to baseline. Results The therapeutic success rate was 60.7% (1 year) and 62.5% (2 years). No statistical difference was observed when procedures were combined with cataract surgery (p > 0.05). Subgroup analysis yielded no significantly different therapeutic success when considering glaucoma subtype [1 year: 61.5% (POAG), 60% (SAOG), 2 years: 54.5% (POAG), 69.2% (SOAG); p > 0.05]. Anti-glaucomatous medication use was lowered from 2.72 ± 1.04 at baseline to 0.61 ± 0.99 (1 year) and 0.7 ± 1.04 (2 years). The therapeutic success rate was seen to be independent of axial length for group and subgroup analysis (p > 0.05). Emmetropic eyes (22.0âŠ-âŠ24.5 mm) showed a statistically higher needling rate than myopic eyes (> 24.5 mm, p = 0.02). Conclusion Minimal invasive glaucoma surgery is one therapeutic option in OAG eyes, with good reduction in IOP even after 24 months (with additional bleb needling). Therapeutic success seemed to be independent of axial length in the present study.
CRIS-Team Scopus Importer:2021-04-02
Keywords: axial length; glaucoma; myopia; open-angle glaucoma; Xen Stent

Electrodiagnosis of dichromacy - Barboni, Mirella Telles Salgueiro; Hauzman, Einat; Nagy, Balázs Vince; Martins, Cristiane Maria Gomes; Aher, Avinash; Tsai, Tina I.; Bonci, Daniela Maria Oliveria; Ventura, Dora Fix; Kremers, Jan (Vision research, 2019)
Retinal and cortical signals initiated by a single cone type can be recorded using the spectral compensation (or silent substitution) paradigm. Moreover, responses to instantaneous excitation increments combined with gradual excitation decreases are dominated by the response to the excitation increment. Similarly, the response to a sudden excitation decrement dominates the overall response when combined with a gradual excitation increase. Here ERGs and VEPs were recorded from 34 volunteers [25.9 ± 10.4 years old (mean ± 1 SD); 25 males, 9 females] to sawtooth flicker (4 Hz) stimuli that elicited L- or M-cone responses using triple silent substitution. The mean luminance (284 cd/m 2 ) and the mean chromaticity (x = 0.5686, y = 0.3716; CIE 1931 color space) remained constant and thus the state of adaptation was the same in all conditions. Color discrimination thresholds along protan, deutan, and tritan axes were obtained from all participants. Dichromatic subjects were genetically characterized by molecular analysis of their opsin genes. ERG responses to L-cone stimuli were absent in protanopes whereas ERG responses to M-cone stimuli were strongly reduced in deuteranopes. Dichromats showed generally reduced VEP amplitudes. Responses to cone-specific stimuli obtained with standard electrophysiological methods may give the same classification as that obtained with the Cambridge Colour Test and in some cases with the genetic analysis of the L- and M-opsin genes. Therefore, cone-specific ERGs and VEPs may be reliable methods to detect cone dysfunction. The present data confirm and emphasize the potential use of cone-specific stimulation, combined with standard visual electrodiagnostic protocols.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Color vision; Cone-isolating stimulus; Electroretinogram; Opsin gene; Silent substitution; Spectral compensation; Visual evoked potential

Electronic patient records and teleophthalmology : Part 1: introduction to the various systems and standards. - Schargus, M.; Michelson, Georg; Grehn, F. (Ophthalmologe, 2011)
Electronic storage of patient-related data will replace paper-based patient records in the near future. Some steps in medical practice can even now not be achieved without electronic data processing. Both systems, conventional paper-based and electronic-based records, have advantages and disadvantages which have to be taken into consideration. The advantages of electronic-based records are e.g. good availability of data, structured storage of data, scientific analysis of long-term data and possible data exchange with colleagues in the context of teleconsultation systems. Problems have to be solved in the field of data security, initial high investment costs and time consumption in learning to use the system as well as in incompatibility of existing IT systems.
EVALuna2:21021

Electronic patient records and teleophthalmology. Part 2: concrete projects in ophthalmology - Schargus, M.; Michelson, Georg; Grehn, F. (Ophthalmologe, 2011)
Electronic storage of patient-related data will replace paper-based patient records in the near future. Because of the high visualization needed in ophthalmology integrated electronic data storage and usage will be very useful. Chronic diseases like glaucoma, macular degeneration and diabetic retinopathy would benefit from long-term data storage and analysis. Unfortunately there are nearly no widely accepted systems available providing these options. Another important point is the simplification of existing diagnostic procedures and nomenclature on an international level. Increasing mobility of patients requires a better portability of existing medical examination data between different physicians. This is the only way to provide continuously high levels of quality in patient care and to simultaneously reduce costs and prevent unnecessary secondary examinations.
EVALuna2:21061

Electrophysiological deficits in the retina of the DBA/2J mouse - Scholz, Michael; Kremers, Jan; et al. (Documenta Ophthalmologica, 2009)
The DBA/2J (D2J) is a genetic mouse model for glaucomatous neurodegeneration because the animals develop anatomical and functional retinal deficits that partially can be correlated with elevated intraocular pressure (IOP). The IOP starts to increase at an age of about 6 months as a result of morphological changes within the anterior eye segment, e.g., pigment dispersion and iris synechiae. The purpose of the present study was to investigate how ERG responses change in individuals at different ages in D2J mice and to compare these changes with normal aging effects in pigmented C57/B6 (B6) mice. IOP was measured in awake, non-sedated D2J and B6 mice with a rebound tonometer. At ages between 2-3 and 10 months, scotopic flash ERGs were measured five times with about 2 months' intervals. In addition, light adapted flicker ERGs were recorded. Our data show that the D2J shows lower flicker ERG responses than the B6 mice already at an age of 2-3 months. Dark adapted flash ERG responses are not decreased at this age. In both mouse strains the ERG responses decrease as a function of age, but there is a stronger decrease in the D2J mice. The data of flicker ERGs suggest the presence of early functional deficits in the D2J retina that possibly have a post-receptoral origin. The scotopic flash ERG reveals a functional deficit that occurs at a later stage and that possibly is IOP dependent. But, the deficits appear at an age at which the IOP is still lower than in the B6 mouse, indicating that other factors play an additional role. © 2009 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2009.med.AI.LAIPDL.electr
Keywords: DBA/2J mouse; Electroretinography; Flash ERG; Flicker ERG; Glaucoma; Intraocular pressure

Electroretinographical determination of human color vision type - Aher, Avinash; Martins, Cristiane M. G.; Barboni, Mirella T. S.; Nagy, Balazs V.; Hauzman, Einat; Bonci, Daniela M. O.; Ventura, Dora F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
It has been previously demonstrated that electroretinography (ERG) elicited by heterochromatically modulated stimuli can be used for objective determination of color vision type. Color vision of trichromatic, deuteranopic, and protanopic participants was psychophysically assessed by the Cambridge Color Test and confirmed genetically. ERG responses to red and green lights modulating in counterphase at 12 and 36 Hz were recorded, while the fraction of red modulation was varied. At 36 Hz (and second harmonics at 12 Hz), the responses were minimal at red fractions that differed significantly in protanopes. At 12 Hz (fundamental component), the responses of the trichromats differed significantly compared to those of the dichromats. An improved protocol shows that the three subject groups can be separated with no overlap. (C) 2018 Optical Society of America

Electroretinographic Recordings in a Mouse Model for CSNB2 Featuring Mutations in the Cacna1f Gene - Atorf, Jenny; Specht, D.; Maw, M.; Brandstätter, Johann Helmut; Dieck, S. Tom; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; electroretinography: non-clinical; synapse

Electroretinographic responses that may reflect activity of parvo- and magnocellular post-receptoral visual pathways - Kremers, Jan; Link, Barbara (Journal of Vision, 2008)
The electroretinogram (ERG) is a complex retinal response to visual stimuli that contains receptoral and post-receptoral components. Here, data are presented using stimuli that isolate the responses of L (long wavelength sensitive)- or M (middle wavelength sensitive)- cones or that stimulate the two simultaneously. The data show that at a temporal frequency of 12 Hz, ERG responses are L- to M-cone opponent with little inter-individual variability. Furthermore, the ratio of L- to M-cone-driven response strengths in the ERGs is about unity. These are also properties of the L- and M-cone opponent chromatic channel mediated by parvocellular activity. Similar to the parvocellular-mediated temporal sensitivity, the ERG response is robust to moderate changes in state of cone adaptation. Thus, the 12-Hz ERG shares distinct characteristics with the post-receptoral red-green sensitive parvocellular pathway. At higher temporal frequencies, the responses are not cone opponent, the inter-individual variability is larger, the mean L/M ratio is larger than unity, and the responses change more strongly when the state of cone adaptation is altered. These properties are reminiscent of the magnocellular non-opponent channel. The data suggest that under well-controlled conditions, the ERG can be used to study post-receptoral processes of the visual system.
Keywords: electroretinography; magnocellular; parvocellular; L-cones; M-cones; cone opponency; luminance

Electroretinographic responses to luminance and cone-isolating white noise stimuli in macaques - Kremers, Jan; Aher, Avinash; Parry, Neil R. A.; Patel, Nimesh B.; Frishman, Laura J. (Frontiers in Neuroscience, 2022)
Electroretinograms (ERGs) are mass potentials with a retinal origin that can be measured non-invasively. They can provide information about the physiology of the retina. Often, ERGs are measured to flashes that are highly unnatural stimuli. To obtain more information about the physiology of the retina, we measured ERGs with temporal white noise (TWN) stimuli that are more natural and keep the retina in a normal range of operation. The stimuli can be combined with the silent substitution stimulation technique with which the responses of single photoreceptor types can be isolated. We characterized electroretinogram (ERG) responses driven by luminance activity or by the L- or the M-cones. The ERGs were measured from five anesthetized macaques (two females) to luminance, to L-cone isolating and to M-cone isolating stimuli in which luminance or cone excitation were modulated with a TWN profile. The responses from different recordings were correlated with each other to study reproducibility and inter-individual variability. Impulse response functions (IRFs) were derived by cross-correlating the response with the stimulus. Modulation transfer functions (MTFs) were the IRFs in the frequency domain. The responses to luminance and L-cone isolating stimuli showed the largest reproducibility. The M-cone driven responses showed the smallest inter-individual variability. The IRFs and MTFs showed early (high frequency) components that were dominated by L-cone driven signals. A late component was equally driven by L- and M-cone activity. The IRFs showed characteristic similarities and differences relative to flash ERGs. The responses to TWN stimuli can be used to characterize the involvement of retinal cells and pathways to the ERG response. It can also be used to identify linear and non-linear processes.
CRIS-Team WoS Importer:2022-09-02

Electroretinographic responses to photoreceptor specific sine wave modulation - Kremers, Jan; Pangeni, Gobinda (Journal of the Optical Society of America A-Optics Image Science and Vision, 2012)
Electroretinographic responses to cone and rod isolating stimuli and to simultaneous L- and M-cone modulation were measured at different temporal frequencies between 2 and 60 Hz and at two mean luminances using a four primary stimulator. The responses driven by each photoreceptor type had distinct characteristics. The responses to stimuli containing L- and/or M-cone stimulation indicated the presence of two underlying mechanisms that were active in distinct frequency regions. Between 2 and 12 Hz, the responses displayed properties that were reminiscent of the L-M-cone opponent system. At higher temporal frequencies, the electroretinograms were more determined by the luminance content in the stimuli.
EVALuna2:21078

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (16th Bayreuther Polymer Symposium, Bayreuth (Deutschland), 2019., 2019)

Electrospun nanofiber membranes as substitutes for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (30th Annual Conference of the European Society for Biomaterials, Dresden (Deutschland), 2019, 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (The Association for Research in Vision and Ophthalmology (ARVO), 2019)

Electrospun PCL-Collagen nanofiber membranes as substitute for posterior lamellar keratoplasty - Himmler, Marcus; Garreis, Fabian; Paulsen, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Nordic Polymer Days, Trondheim (Norwegen),, 2019)

Elevated vitreous body glial fibrillary acidic protein in retinal diseases - Jünemann, Anselm; Rejdak, Robert; Huchzermeyer, Cord; Maciejewski, Ryszard; Grieb, Pawel; Kruse, Friedrich; Zrenner, Eberhart; Rejdak, Konrad; Petzold, Axel (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
Increased expression of glial fibrillary acidic protein (GFAP) is a characteristic of gliotic activation (Müller cells and astrocytes) in the retina. This study assessed vitreous body GFAP levels in various forms of retinal pathology.This prospective study included 82 patients who underwent vitrectomy (46 retinal detachments (RDs), 13 macular hole (MHs), 15 epiretinal glioses (EGs), 8 organ donors). An established enzyme-linked immunosorbent assay (ELISA, SMI26) was used for quantification of GFAP.The highest concentration of vitreous body GFAP in organ donors was 20 pg/mL and it was used as the cutoff. A significant proportion of patients suffering from RD (65 %) to EG (53 %) had vitreous body GFAP levels above this cutoff when compared to organ donors (0 %, p < 0.0001, p = 0.0194, respectively, Fisher's exact test) and MH (8 %, p < 0.0001, p = 0.0157, respectively). In RD and EG, vitreous body GFAP levels were correlated with axial length (R = 0.69, R = 0.52, p < 0.05 for both).The data suggest that human vitreous body GFAP is a protein biomarker for glial activation in response to retinal pathologies. Vitreous body GFAP levels may be of interest as a surrogate outcome for experimental treatment strategies in translational studies.
EVALuna2:21235

Endophthalmitis: Ursachen, Erreger, Therapie und Visusverlauf mit Fokus auf Glaukompatienten - Vorbeck, Julia; Hohberger, Bettina; Bergua, Antonio (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Endophthalmitis is one of the most serious emergencies in ophthalmology. In order to lower their prevalence, the most accurate knowledge of potential risk factors is important. Surgical therapy with targeted, pathogen-specific medication and an intact immune system are fundamental to preserve visual acuity. Furthermore, the question arises whether an unfavorable course can be predicted on the basis of underlying diseases of the eye, therefore a comparison between glaucoma patients (G) and non-glaucoma patients (NG) with regard to causative factors, pathogens, therapy and visual acuity course was drawn. Since a potential alteration of the local immune system in glaucoma disease has been described, it is of interest whether the clinical courses of endophthalmitis differ from non-glaucoma patients. Patients and methods A retrospective analysis of 75 eyes (13 G, 62 NG) who underwent treatment and surgery due to the diagnosis of endophthalmitis in the Department of Ophthalmology, University of Erlangen-Nuremberg has been evaluated over a period of 5 years. Clinical characteristics, surgical treatment, microbial spectrum and visual acuity in glaucoma and non-glaucoma eyes were investigated. Results A drastic vision impairment (44%) with inflammation of the anterior chamber (62.7%), hypopyon (52%) and reduced (40%) or complete missing sight (26.7%) of the fundus were predominantly present at first diagnosis in all patients. A previous eye surgery was observed in a total of 53%, especially cataract surgery. Gram-positive cocci were seen as the most common causing agent in both groups, (G: 23.1%; NG: 38.7%), whereas other rare pathogens were present only in glaucoma eyes. Pars-plana-vitrectomy was performed in 76% and enucleations in 20% of all patients, the latter significantly increased in glaucomateous eyes (p=0.01). A significant postoperative improvement of visual acuity was yielded in non-glaucoma patients (p<0.001); visual acuity outcome was worsen in glaucoma eyes. Conclusion Despite its rareness, early diagnosis and treatment of endophthalmitis is crucial for prognosis. In the present cohort, a worse visual acuity outcome was yielded in glaucoma patients in comparison to non-glaucoma patients.
CRIS-Team Scopus Importer:2022-08-05

Ensemble Pruning for Glaucoma Detection in an Unbalanced Data Set - Adler, Werner; Gefeller, Olaf; Gul, Asma; Horn, Folkert; Khan, Zardad; Lausen, Berthold (Methods of Information in Medicine, 2016)
Random forests are successful classifier ensemble methods consisting of typically 100 to 1000 classification trees. Ensemble pruning techniques reduce the computational cost, especially the memory demand, of random forests by reducing the number of trees without relevant loss of performance or even with increased performance of the sub-ensemble. The application to the problem of an early detection of glaucoma, a severe eye disease with low prevalence, based on topographical measurements of the eye background faces specific challenges.We examine the performance of ensemble pruning strategies for glaucoma detection in an unbalanced data situation.The data set consists of 102 topographical features of the eye background of 254 healthy controls and 55 glaucoma patients. We compare the area under the receiver operating characteristic curve (AUC), and the Brier score on the total data set, in the majority class, and in the minority class of pruned random forest ensembles obtained with strategies based on the prediction accuracy of greedily grown sub-ensembles, the uncertainty weighted accuracy, and the similarity between single trees. To validate the findings and to examine the influence of the prevalence of glaucoma in the data set, we additionally perform a simulation study with lower prevalences of glaucoma.In glaucoma classification all three pruning strategies lead to improved AUC and smaller Brier scores on the total data set with sub-ensembles as small as 30 to 80 trees compared to the classification results obtained with the full ensemble consisting of 1000 trees. In the simulation study, we were able to show that the prevalence of glaucoma is a critical factor and lower prevalence decreases the performance of our pruning strategies.The memory demand for glaucoma classification in an unbalanced data situation based on random forests could effectively be reduced by the application of pruning strategies without loss of performance in a population with increased risk of glaucoma.
EVALuna2:5545

ERG responses to heterochromatic stimuli that reflect L- and M-cone inputs and their additive or opponent interactions - Kremers, Jan; Bhatt, Deepak (Investigative Ophthalmology & Visual Science, 2016)

ERG signals elicited by temporal white noise in macaques - Kremers, Jan; Aher, Avinash; Parry, Neil; Patel, Nimesh Bhikhu; Frishman, Laura J. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Erkrankungen des Tränenapparats, Teil 1: Anatomie, Physiologie und Diagnostik - Heichel, Jens; Struck, Hans-Gert; Viestenz, Arne; Glien, Alexander; Plontke, Stefan (Laryngo-Rhino-Otologie, 2020)
CRIS-Team WoS Importer:2020-02-28

Erlanger glaucoma registry: Effect of a long-term therapy with statins and acetyl salicylic acid on glaucoma conversion and progression - Thiermeier, Nina; Lämmer, Robert; Mardin, Christian Y.; Hohberger, Bettina (Biology, 2021)
Purpose: Drugs with cardiovascular protective properties (statins, acetylsalicylic acid (ASS)) were assumed to have positive effects on patients suffering from glaucoma disease. The present retrospective study aimed to investigate the influence of statins, ASS or a combination of both on the glaucoma conversion and progression rate in glaucoma suspects and glaucoma patients with a 20-year follow-up period. Methods: A retrospective analysis of 199 eyes of 120 patients (63 male, 57 female) of the Erlanger Glaucoma Registry (EGR; ClinicalTrials.gov Identifier: NCT00494923; ISSN 2191-5008, CS-2011) was performed considering systemic therapy with statins, ASS or a combination of both: 107 eyes with ocular hypertension (OHT) and 92 eyes with pre-perimetric primary open-angle glaucoma (pre-POAG). All patients received an ophthalmological examination including morphometric and functional glaucoma diagnostics. Glaucoma conversion was defined as the conversion of OHT to pre-POAG. Glaucoma progression was defined as confirmed visual field loss. Data were shown as percentages. Statistical analysis was performed by Chi-Quadrat tests. Results: 1. Glaucoma conversion/progression was observed in 46.7% of the subjects, additionally in combination with hypercholesterinemia in 76.8%. 2. Statins: 27.3% of eyes under systemic statin therapy showed a conversion/progression. Patients taking statins ≥ 10 years yielded a reduced conversion/progression rate (p = 0.028, non-significant after Bonferroni–Holm). 3. ASS: 34.7% of eyes under systemic ASS therapy showed a conversion/progression. A significantly lower con-version/progression rate was observed after ASS therapy ≥ 12 years (p = 0.017, significant after Bonferroni–Holm). 4. ASS and statins: 25.0% of eyes under combined therapy showed a conver-sion/progression. A significantly reduced conversion/progression rate was reached after 8 years of combined therapy (p = 0.049, non-significant after Bonferroni–Holm). Conclusions: Patients with ocular hypertension and early glaucoma seem to benefit from adjuvant cardiovascular protective therapy. However, the benefits and disadvantages of treatment with statins and/or ASS should be kept in mind. Thus, a thorough risk–benefit evaluation has to be performed for each patient individually to avoid unwanted side effects.
CRIS-Team Scopus Importer:2021-07-09
Keywords: ASS; Cholesterol; Glaucoma; Glaucoma suspect; Progression; Statins

Establishment of a drug screening system for Fuchs endothelial corneal dystrophy - Oshima, Takeshi; Okumura, Naoki; Onishi, Takako; Ueda, Emi; Watanabe, Kyoko; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (2018)
EVALuna2:34744

Estimation of Time Delay between Artery and Vein Pulsation using Experimental Video-Ophthalmoscope - Valterova, Eva; Tornow, Ralf-Peter; Kolar, Radim (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2019)
The fundus observation by ophthalmoscope is a non-invasive approach for diagnosis of various retinal diseases. The vein and artery pulsation are usually clearly apparent on fundus and might be also important for medical practice. Thus our method focuses on these changes and analyzes the time delay between the pulsation signal detected in the vein and the artery region. Data acquired by an experimental video-ophthalmoscope from five subjects with no eye diseases are analyzed. The analysis is based on the selection of artery and vein regions of interest and computation of averaged brightness within these regions for each frame. These extracted signals are filtered, interpolated and the trend is eliminated. Finally, the delays between artery and vein pulsation signals are determined using phase spectra. The measured delays are in the range of 15 to 95 ms, which is comparable with other published results.
CRIS-Team Scopus Importer:2020-02-21

Evaluation of a 345 nm Femtosecond Laser for Corneal Surgery with Respect to Intraocular Radiation Hazard - Menzel-Severing, Johannes; Petsch, Corinna; Tourtas, Theofilos; Polisetti, Naresh; Klenke, Joerg; Skerl, Katrin; Wuellner, Christian; Donitzky, Christof; Kruse, Friedrich; Kremers, Jan; Hammer, Christian (PLoS ONE, 2015)
We report our findings from a preclinical safety study designed to assess potential side effects of corneal ultraviolet femtosecond laser treatment on lens and retina.Refractive lenticules (-5 dpt) with a diameter of 6 mm were created in the right cornea of eight Dutch Belted rabbits. Radiant exposure was 0.5 J/cm² in two animals and 18 J/cm² in six animals. The presence of lens opacities was assessed prior to and up to six months following laser application using Scheimpflug images (Pentacam, Oculus) and backscatter analysis (Opacity Lensmeter 702, Interzeag). Ganzfeld flash and flicker electroretinogram (ERG) recordings were obtained from both eyes prior to and up to six weeks following laser application. At the study endpoint, retinas were examined by light microscopy.Independent of energy dose applied, no cataract formation could be observed clinically or with either of the two objective methods used. No changes in ERG recordings over time and no difference between treated and untreated eye were detected. Histologically, retinal morphology was preserved and retinal pigment epithelium as well as photoreceptor inner and outer segments appeared undamaged. Quantitative digital image analysis did not reveal cell loss in inner or outer nuclear layers.Our analysis confirms theoretical considerations suggesting that ultraviolet femtosecond laser treatment of the cornea is safe for intraocular tissues. Transmitted light including stray light induces no photochemical effects in lens or retina at energy levels much higher than required for the clinical purpose. These conclusions cannot be applied to eyes with pre-existing retinal damage, as these may be more vulnerable to light.
EVALuna2:4434

Evaluation of central corneal thickness after cataract surgery, penetrating keratoplasty and long-term soft contact lens wear - Sel, Saadettin; Trau, Stefanie; Knak, Matthias; Kalinski, Thomas; Kaiser, Delia; Kruse, Friedrich; Huchzermeyer, Cord; Duncker, Gernot I. W.; Paulsen, Friedrich; Auffarth, Gerd U.; Nass, Norbert (Contact Lens and Anterior Eye, 2013)
The aim of this study was to compare central corneal thickness (CCT) between corneas of normal healthy eyes (cNHE), corneas of eyes that had undergone cataract surgery by clear corneal phacoemulsification with implantation of an intracapsular intraocular lens (cIOL), corneal grafts after penetrating keratoplasty (gPK) and corneas of long-term soft contact lens wearers (cCL).The study design was a consecutive cross-sectional trial. CCT was measured using rotating Scheimpflug camera (Pentacam, software version 1.16r04) in 80 cNHE, 79 cIOL, 46 gPK and 78 cCL. Analysis of variance (one-way ANOVA) was performed to compare differences of mean values between these four groups. Pearson's or Spearman's correlation coefficient (r) was determined between CCT value and age, follow up time after penetrating keratoplasty (timePK) or contact lens wearing time (timeCL).Means of CCT measurements were comparable between cNHE (mean CCT±standard deviation, 554±36?m), cIOL (551±40?m) and gPK (534±52?m) as determined by one-way ANOVA. Mean CCT values in cCL (537±37?m) were statistically significantly lower in comparison to cNHE (p=0.026, 95% CI=1.43-31.44). There was no linear correlation between age and CCT values of cNHE and cIOL (p=0.841, r=-0.031 and p=0.931, r=0.011, respectively). No linear relationship was determined between CCT values of cCL and timeCL (p=0.315, r=-0.125). CCT values of gPK did not correlate with timePK (p=0.738, r=0.054).The data reported here indicate that in the same statistical model among CCT values of cNHE, cIOL and gPK only long-term soft contact lenses (CL) wearer have significantly lower CCT measurements.
EVALuna2:4398

Evaluation of lamina cribrosa and peripapillary sclera stiffness in pseudoexfoliation and normal eyes by atomic force microscopy - Braunsmann, Christoph; Hammer, Christian M.; Rheinlaender, Johannes; Kruse, Friedrich; Schäffer, Tilman; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2012)
Pseudoexfoliation (PEX) syndrome is a systemic disorder of the elastic fiber system that can lead to PEX glaucoma. Elastotic alterations in the lamina cribrosa (LC) of PEX eyes suggested biomechanical implications predisposing to pressure-induced optic nerve damage. In this pilot study, the stiffness of LC and peripapillary sclera (ppSC) in eyes with and without PEX syndrome were analyzed by atomic force microscopy (AFM) nanoindentation.Unfixed cryosections (5-?m thick) were prepared from the optic nerve heads (ONH) of three donor eyes with PEX syndrome and three age-matched control eyes. AFM force mapping was performed in selected regions of the central, midperipheral, and peripheral LC and the ppSC using a spherical cantilever tip. To determine the local Young's modulus of elasticity (YME) as a measure of tissue stiffness, force curves were acquired and analyzed using the spherical Hertz model.For the LC, the median YME values calculated from single stiffness maps averaged 17.2 (±2.7) kPa in normal eyes and 10.1 (±1.4) kPa in PEX eyes, indicating a significant PEX-related decrease in stiffness by over 40% (P < 0.01). The corresponding YME values for the ppSC, which revealed a 9-fold higher tissue stiffness than in the LC, averaged 158.3 (±59.8) kPa for control and 85.8 (±16.9) kPa for PEX samples.AFM was proven suitable for determining the stiffness of ONH tissues, encouraging further large-scale analyses. The marked decrease in stiffness, implying an increased deformability of the ONH in PEX eyes, may reflect an inherent tissue weakness rendering these eyes more vulnerable to glaucomatous damage.
EVALuna2:21095

Evidence for RPGRIP1 gene as risk factor for primary open angle glaucoma - Fernández Martinez, Lorena; Letteboer, Stef; Mardin, Christian Y.; Weisschuh, Nicole; Gramer, Eugen; Weber, Bernhard H. F.; Rautenstrauß, Bernd; Ferreira, Paulo A.; Kruse, Friedrich; Reis, André; Roepman, Ronald; Pasutto, Francesca (European journal of human genetics, 2011)
Glaucoma is a genetically heterogeneous disorder and is the second cause of blindness worldwide owing to the progressive degeneration of retinal ganglion neurons. Very few genes causing glaucoma were identified to this date. In this study, we screened 10 candidate genes of glaucoma between the D14S261 and D14S121 markers of chromosome 14q11, a critical region previously linked to primary open-angle glaucoma (POAG). Mutation analyses of two large cohorts of patients with POAG, normal tension glaucoma (NTG) and juvenile open-angle glaucoma (JOAG), and control subjects, found only association of non-synonymous heterozygous variants of the retinitis pigmentosa GTPase regulator-interacting protein 1 (RPGRIP1) with POAG, NTG and JOAG. The 20 non-synonymous variants identified in RPGRIP1 were all distinct from variants causing photoreceptor dystrophies and were found throughout all but one domain (RPGR-interacting domain) of RPGRIP1. Among them, 14 missense variants clustered within or around the C2 domains of RPGRIP1. Yeast two-hybrid analyses of a subset of the missense mutations within the C2 domains of RPGRIP1 shows that five of them (p.R598Q, p.A635G, p.T806I, p.A837G and p.I838V) decrease the association of the C2 domains with nephrocystin-4 (NPHPH). When considering only these five confirmed C2-domain mutations, the association remains statistically significant (P=0.001). Altogether, the data support that heterozygous non-synonymous variants of RPGRIP1 may cause or increase the susceptibility to various forms of glaucoma and that among other factors, physical impairment of the interaction of RPGRIP1with different proteins may contribute to the pathogenesis of forms of glaucoma.
EVALuna2:9085

Evidence for two types of lateral interactions in visual perception of temporal signals - Teixeira, Claudio E. C.; Salomao, Railson C.; Rodrigues, Anderson R.; Horn, Folkert; Silveira, Luiz Carlos L.; Kremers, Jan (Journal of Vision, 2014)
The aim of this work was to investigate the mechanisms of lateral interactions involved in flicker perception. Furthermore, the spatial properties of the monoptic and dichoptic components of these mechanisms were studied. We quantified the perceived flicker strength (PFS) in the center of a test stimulus, which was simultaneously modulated with a surround stimulus of variable size. The modulation depth of a separate stimulus, identical to the center test stimulus but without the surround, was determined using a two-alternative forced choice procedure. Using LCD goggles synchronized to the frame rate of a CRT screen, the center and surround of the test stimulus were presented either monoptically or dichoptically. In the monoptic condition, center-surround interactions have subcortical and cortical origins. In the dichoptic condition, center-surround interactions must have a cortical origin. The difference between the dichoptic and the monoptic data is an estimate of the contribution of the subcortical mechanisms. At each condition (surround stimulus size; monoptic or dichoptic presentation), the PFS was measured for phase differences between center and surround stimuli. The PFS changed systematically with phase difference. It also was observed that the PFS in the center stimulus changed merely be the presence of a surround stimulus independently of the center-surround phase difference. We propose that this is a phase-independent mechanism related to contrast adaptation owing to the presence of surround modulation. Our data suggest that both phase-dependent and -independent mechanisms have cortical and subcortical origins. There were no systematic differences between the spatial properties of subcortical and cortical components involved in PFS modulation.
EVALuna2:21165

Evidence of endothelial cell migration after descemet membrane endothelial keratoplasty - Jacobi, Christina; Zhivov, Andrey; Korbmacher, Judit; Falke, Karen; Guthoff, Rudolf; Schlötzer-Schrehardt, Ursula; Cursiefen, Claus; Kruse, Friedrich (American Journal of Ophthalmology, 2011)
To investigate the hypothesis that adult corneal endothelial cells can migrate after Descemet membrane endothelial keratoplasty (DMEK).Prospective observational study.Five patients with Fuchs endothelial dystrophy were examined 1 year after uneventful DMEK. These patients had been selected on the basis of slightly decentered grafts and/or large descemetorrhexis showing areas of denuded corneal stroma, which were covered by neither the patients' Descemet membrane (DM) nor the graft. These areas were investigated by in vivo confocal laser scanning microscopy using a specially designed Heidelberg Retina Tomograph II and Rostock cornea module equipped with custom-made software. Source data (frame rate 30 Hz, 384 × 384 pixels, 400 × 400 ?m) were used to create large-scale maps of the scanned area in automatic real-time composite mode. In each case an on-line mapping with maximum size up to 3.2 × 3.2 mm (3072 × 3072 pixels) was performed.Corneal stroma overlying areas devoid of DM was transparent. In vivo confocal laser scanning microscopy of stroma devoid of DM revealed a monolayer of endothelial cells in all patients observed. The morphologic pattern of these cells was similar to that of endothelial cells on DM grafts but different from the morphology of the patients' own endothelium, suggesting migration of donor endothelial cells from DMEK grafts.The results strongly support the hypothesis that adult corneal endothelial cells are able to migrate in the human eye. Furthermore, we provide evidence to support the hypothesis that grafted endothelium migrates onto the host tissue, repopulating the corneal stroma with a regular endothelial phenotype.
EVALuna2:21034

Evidence of neurodegeneration in individuals with only mildly elevated blood pressure - Jung, Susanne; Bosch, Agnes; Kohler, Nikolas; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2019)
OBJECTIVE: Initiation of antihypertensive drug treatment in low-risk individuals with grade 1 hypertension is under debate. The aim of this study was to examine the impact of mildly elevated blood pressure (BP) on early neurodegenerative processes independent of ageing. METHODS: Sixty-two individuals were included in this study: 25 young (aged <40 years) and 37 older (aged ≥40 years) individuals at low cardiovascular risk and grade 1 hypertension at most. Macular retinal layer volumes of both eyes were determined by SD-OCT. Total retinal volume but also each inner retinal layer volume separately including retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and GCL-IPL were measured in each individual. RESULTS: Retinal layer volumes were lower among older individuals compared with young individuals (RNFL right eye: P = 0.037/left eye: P = 0.021; GCL and GCL-IPL: both eyes P < 0.001; IPL right eye: P = 0.005/left eye: P = 0.002; total retinal volume: both eyes P = 0.002) and there was an inverse correlation between retinal layer volumes and age. Partial correlation analysis, excluding age as a cofactor, revealed an inverse association between retinal layer volumes and DBP. In multiple regression analysis, DBP was identified as a determinant of retinal neurodegenerative processes. CONCLUSION: In the current study, we observed an inverse association between retinal neurodegenerative processes and DBP, suggesting that BP-lowering therapy by early antihypertensive drug-treatment might be beneficial to avoid early neurodegeneration.
EVALuna2:203883

Expression and Regulation of LOXL1 and Elastin-related Genes in Eyes With Exfoliation Syndrome - Zenkel, Matthias; Schlötzer-Schrehardt, Ursula (Journal of Glaucoma, 2014)
Exfoliation syndrome (XFS) is a complex, late-onset disorder of the elastic fiber system and the most common identifiable cause of open-angle glaucoma. Strong genetic risk is conferred by the lysyl oxidase-like 1 (LOXL1) gene, but additional comodulating factors are necessary for the manifestation of the disease. The aim of this study was to establish a comprehensive expression profile of LOXL1 and elastic proteins in XFS eyes and to analyze their regulation in an in vitro cell culture system. Eyes with XFS with and without glaucoma, and normal control eyes were analyzed for major elastic fiber components (elastin, fibrillin-1, fibulin-4), and lysyl oxidase (LOX) enzymes by real-time PCR, immunohistochemistry, and electron microscopy. Cultured human Tenon's capsule fibroblasts were exposed to transforming growth factor-?1, IL-6, homocysteine, oxidative stress, hypoxia, or ultraviolet radiation, and changes in the expression of LOXL1 and elastic components of XFS material were assessed by real-time PCR, immunohistochemistry, and Western blotting. LOXL1 expression in anterior eye tissues was significantly increased in early XFS stages but was decreased in advanced stages as compared with controls. LOXL1 was also found to be a major component of XFS material and to colocalize with elastin, fibrillin-1, and fibulin-4, which were upregulated in parallel to LOXL1. In contrast, in most posterior segment tissues, LOXL1 and elastic fiber proteins displayed no differential expression. Interestingly, lamina cribrosa specimens of early and late XFS stages without and with glaucoma revealed a selective downregulation of LOXL1 and elastic fiber components on the mRNA and protein level, which was associated with pronounced ultrastructural alterations of the laminar elastic fiber network in XFS eyes. Treatment of cultured cells with XFS-associated pathogenetic stimuli induced a significant increase in the expression of LOXL1 and elastic proteins and resulted in their assembly into XFS-like fibrils in vitro. The findings support the notion that both genetic and nongenetic factors may cooperate in the stable accumulation of XFS aggregates and provide evidence for a XFS-specific elastinopathy of the lamina cribrosa, possibly rendering XFS eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development.
EVALuna2:21182

Expression of HIF1α in intestinal epithelium restricts arthritis inflammation by inhibiting RIPK3-induced cell death machinery - Lyu, Pang; Wen, Jinming; Zhang, Wenshuo; Liu, Ning; Stolzer, Iris; Gießl, Andreas; Jia, Yewei; Mauro, Daniele; Zhang, Fulin; Ciccia, Francesco; Soulat, Didier; Günther, Claudia; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: To investigate the mechanism by which intestinal epithelial cell (IEC) death induces arthritis. Methods: IEC death was assessed by staining for necroptosis and apoptosis markers and fluorescence in situ hybridisation at different time points during collagen-induced arthritis (CIA). During the development of CIA, messenger RNA (mRNA) sequencing was performed, followed by Gene Ontology enrichment analysis of differentially expressed genes. Mice deficient for hypoxia-inducible factor 1α (Hif1a) in IECs (Hif1aΔIEC) were generated and induced for arthritis. mRNA sequencing, chromatin immunoprecipitated (ChIP) DNA sequencing and ChIP-qualitative PCR were performed on IECs from Hif1aΔIEC mice and littermate controls. Effects of HIF1α stabilisation by inhibition of prolyl hydroxylase domain-containing enzymes and treatment with the inhibitor of receptor-interacting protein kinase-3 (RIPK3) were tested in intestinal organoids and in CIA. Results: IEC underwent apoptotic and necroptotic cell death at the onset of arthritis, leading to impaired gut barrier function. HIF1α was identified as one of the most upregulated genes in IECs during the onset of arthritis. Deletion of Hif1a in IEC enhanced IEC necroptosis, triggered intestinal inflammation and exacerbated arthritis. HIF1α was found to be a key transcriptional repressor for the necroptosis-inducing factor RIPK3. Enhanced RIPK3 expression, indicating necroptosis, was also found in the intestinal epithelium of patients with new-onset rheumatoid arthritis. Therapeutic stabilisation of HIF1α as well as small-molecule-based RIPK3 inhibition rescued intestinal necroptosis in vitro and in vivo and suppressed the development of arthritis. Conclusion: Our results identify IEC necroptosis as a critical link between the gut and the development of arthritis.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Immune System Diseases; Inflammation

Extended Ganglion Cell Layer Thickness Deviation Maps With OCT in Glaucoma Diagnosis - Lehmann, Paul; Hohberger, Bettina; Lämmer, Robert; Mardin, Christian (Frontiers in Medicine, 2021)
Purpose: The aim of the present study was to investigate the diagnostic power of RGCL in the macula quantitatively and qualitatively by using a conventional and extended elliptic grid with deviation maps. Subjects and Methods: Thickness of RGCL was measured using SPECTRALIS® OCT (Heidelberg Engineering, Heidelberg, Germany) in 150 eyes of 150 subjects of the Erlangen Glaucoma Registry (EGR; NTC00494923): 26 ocular hypertension (OHT), 39 pre-perimetric open-angle glaucoma (pre-OAG), 19 normal tension glaucoma (NTG), 34 primary open-angle glaucoma (POAG), 16 secondary open-angle glaucoma (SOAG), and 16 controls. Analysis of RGCL was done quantitatively (global value, GV) and qualitatively (qualitative total value, QTV) by using a color-coded point score for data of the common elliptic macular grid of deviation maps. Furthermore, qualitative analysis of RGCL was done for an extended elliptic macula grid (extended qualitative total value, eQTV). Receiver operating characteristic (ROC) curves were calculated for the conventional and the enlarged macular grid for all subjects' groups. Results: GV of RGCL thickness differed significantly between pre-OAG (p < 0.05), NTG (p < 0.001), POAG (p < 0.001), SOAG (p < 0.001), yet not OHT (p > 0.05) and controls, respectively. Quantitative ROC analysis of GV showed AUC of 0.965 (SOAG), 0.942 (POAG), 0.916 (NTG), 0.772 (pre-OAG), and 0.526 (OHT). QTV differed significantly between pre-POAG (p < 0.05), NTG (p < 0.001), POAG (p < 0.001), SOAG (p < 0.001), yet not OHT (p > 0.05) and controls, respectively. Qualitative ROC analysis of QTV showed AUCs of 0.908 (NTG) 0.914 (POAG), 0.930 (SOAG), 0.734 (pre-POAG), and 0.519 (OHT). Implementation of eQTV yielded even higher AUCs for NTG (0.919), POAG (0.969), and SOAG (0.973) compared to GV. Similar AUCs of eQTV and GV were observed for OHT (0.514) and pre-OAG (0.770). Conclusion: The results of the present study showed that quantitative and qualitative analysis of RGCL thickness yielded similar diagnostic impacts compared to RNFL. Qualitative analysis might be a quick and easy useable tool for clinical all-day life. The present data suggest that analysis of an extended macula region might improve its diagnostic impact.
CRIS-Team Scopus Importer:2021-06-25
Keywords: glaucoma; GRID; OCT; retinal ganlion cell; spectralis

Extracellular matrix alterations in late-onset Fuchs' corneal dystrophy - Weller, Julia M.; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Bachmann, Björn; Tourtas, Theofilos; Kruse, Friedrich (Investigative Ophthalmology & Visual Science, 2014)
To characterize the alterations of extracellular matrix proteins in Descemet's membranes (DM) of patients with late-onset Fuchs' corneal dystrophy (FCD) and to differentiate them from nonspecific alterations in pseudophakic bullous keratopathy (PBK).Human DM-endothelial cell complexes were obtained from patients with late-onset FCD (n = 40), PBK (n = 6), and control eyes (n = 5). Gene expression profiles of endothelial cells were compared using a commercial real-time PCR array and quantitative real-time PCR assays for confirmation of differentially expressed genes. A total of 24 extracellular matrix proteins were also localized in cryosections of corneal specimens from FCD (n = 10), PBK (n = 4), and control eyes (n = 5) by immunohistochemistry.Polymerase chain reaction array analysis revealed a significant upregulation of 27 out of 84 extracellular matrix-related genes including collagens, proteoglycans, glycoproteins, cell adhesion molecules, and matrix metalloproteinases in FCD specimens as compared to normal controls, which could be partly confirmed and quantified by real-time PCR. Comparative analysis of FCD and PBK specimens showed a significant and consistent FCD-specific upregulation of collagen types I, III, and XVI; fibronectin; agrin; clusterin; transforming growth factor beta-induced (TGFBI); and integrin ?4 (3- to 18-fold, P < 0.05). Immunohistochemistry revealed an increased labeling of collagen (types III, VII, XV, XVI), agrin, fibulin-2, TGFBI, versican, and clusterin in the DM of FCD specimens compared to PBK specimens.The findings provide evidence for a specific upregulation, production, and deposition of collagen types III and XVI, agrin, TGFBI, and clusterin in late-onset FCD and thus point to the importance of matrix alterations in the pathophysiology of FCD.
EVALuna2:21180

Extracellular matrix regulation of limbal epithelial stem cell function - Schlötzer-Schrehardt, Ursula; Kruse, Franziska; Kraus, Kerstin; Zenkel, Matthias; Kruse, Friedrich (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Extracellular Vesicles of CLL Cells affect T-Cell Activation and promote their Depletion via diverse immunological Checkpoints - Boettcher, M.; Boettcher-Loschinski, R.; Gießl, Andreas; Schlötzer-Schrehardt, Ursula; Bruns, Heiko; Mougiakakos, D. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Eyelid aging: pathophysiology and clinical management - Damasceno, Renato Wendell; Avgitidou, Georgia; Belfort, Rubens; Correa Dantas, Paulo Elias; Holbach, Leonard M.; Heindl, Ludwig M. (Arquivos Brasileiros De Oftalmologia, 2015)
Life expectancy is increasing in most countries. With increasing age, many individuals may develop involutional ophthalmic diseases, such as eyelid aging. Dermatochalasis, ptosis, ectropion, and entropion are common disorders in middle-aged and older adults. This review outlines the pathophysiology and clinical management of these involutional eyelid disorders. Recently, a decrease in elastic fibers with ultrastructural abnormalities and an overexpression of elastin-degrading enzymes have been demonstrated in involutional ectropion and entropion. This may be the consequence of local ischemia, inflammation, and/or chronic mechanical stress. Eyelid aging with progressive loss of tone and laxity may affect the ocular surface and adnexal tissues, resulting in different clinical symptoms and signs. Surgical management depends on the appropriate correction of the underlying anatomical defect.
EVALuna2:21237

Eye movement analysis using a binocular video-ophthalmoscope - Kolar, Radim; Odstrcilik, Jan; Labounkova, Ivana; Hracho, Michal; Tornow, Ralf-Peter (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2019)
This paper describes an application of binocular video-ophthalmoscope for binocular eye movement analysis during target fixation. We analyze eye movements during monocular and binocular fixation and the changes in eye position for 73 subjects. We show that the standard deviations of differences between eye shifts for vertical and horizontal movements are higher for binocular fixation with respect to monocular fixation. We also present different examples of eye movement visualization.
CRIS-Team Scopus Importer:2020-02-21

Factors Influencing Central Lamina Cribrosa Depth: A Multicenter Study - Luo, Haomin; Yang, Hongli; Gardiner, Stuart K.; Hardin, Christy; Sharpe, Glen P.; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Liebmann, Jeffrey M.; Mardin, Christian Y.; Quigley, Harry A.; Scheuerle, Alexander F.; et al. (Investigative Ophthalmology & Visual Science, 2018)
Purpose: To quantify the influence of ocular and demographic factors on central laminar depth (LD) in healthy participants. Methods: A total of 362 normal subjects underwent optical coherence tomography (OCT) enhanced depth imaging of the optic nerve head (ONH) with a 24 radial B-scan pattern aligned to the fovea-to-Bruch's membrane opening (BMO) axis. BMO, anterior lamina, anterior scleral canal opening (ASCO), Bruch's membrane (BM), and the peripapillary scleral surface were manually segmented. The extent of laminar segmentation was quantified within 72 ASCO subsectors. Central LD was quantified relative to four reference planes: BMO, ASCO, BM, and scleral. The effects of age, sex, ethnicity, IOP, BMO area, ASCO area, and axial length on LD were assessed. Results: Laminar visibility was most consistent within the central ASCO (median 89%, range, 69%-95%). LDBMO and LDBM were significantly shallower in eyes with greater age, BMO area, and axial length and in females. LDASCO was shallower in eyes with greater ASCO area and axial length and in European and Hispanic descent compared to African descent eyes. LDSclera behaved similarly, but was not associated with axial length. BMO and ASCO area were not different between African descent and European descent eyes. Conclusions: Central LD was deeper in African descent eyes and influenced least by age, axial length, and sex, but more by ASCO area, when measured relative to the ASCO and sclera. However, the magnitude of these effects for all four reference planes was small, and their clinical importance in the detection of glaucoma and its progression remains to be determined.
EVALuna2:34750

Factors Influencing Optical Coherence Tomography Peripapillary Choroidal Thickness: A Multicenter Study - Yang, Hongli; Luo, Haomin; Gardiner, Stuart K.; Hardin, Christy; Sharpe, Glen P.; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Liebmann, Jeffrey M.; Mardin, Christian Y.; Quigley, Harry A.; Scheuerle, Alexander F.; et al. (Investigative Ophthalmology & Visual Science, 2019)
PURPOSE. To quantify peripapillary choroidal thickness (PCT) and the factors that influence it in healthy participants who represent the racial and ethnic composition of the U.S. population.
CRIS-Team WoS Importer:2019-03-15

Feasibility and Outcome of Descemet Membrane Endothelial Keratoplasty in Complex Anterior Segment and Vitreous Disease - Weller, Julia M.; Tourtas, Theofilos; Kruse, Friedrich (Cornea, 2015)
Descemet membrane endothelial keratoplasty (DMEK) is becoming the method of choice for treating Fuchs endothelial dystrophy and pseudophakic bullous keratopathy. We investigated whether DMEK can serve as a routine procedure in endothelial decompensation even in complex preoperative situations.Of a total of 1184 DMEK surgeries, 24 consecutive eyes with endothelial decompensation and complex preoperative situations were retrospectively analyzed and divided into 5 groups: group 1: irido-corneo-endothelial syndrome (n = 3), group 2: aphakia, subluxated posterior chamber intraocular lens or anterior chamber intraocular lens (n = 6), group 3: DMEK after trabeculectomy (n = 4), group 4: DMEK with simultaneous intravitreal injection (n = 6), and group 5: DMEK after vitrectomy (n = 5). Main outcome parameters were best-corrected visual acuity, central corneal thickness, endothelial cell density, rebubbling rate, and graft failure rate.Best-corrected visual acuity (logMAR) increased from 0.98 to 0.53 (P = 0.002), 0.53 (P = 0.091), and 0.57 (P = 0.203) after 1, 3, and 6 months, respectively. Central corneal thickness decreased from 731 ± 170 to 546 ± 152 ?m (P = 0.001), 514 ± 66 ?m (P = 0.932), and 554 ± 98 ?m (P = 0.004) after 1, 3, and 6 months, respectively. Donor endothelial cell density decreased from 2478 ± 185 to 1454 ± 193/mm (P < 0.001), 1301 ± 298/mm (P = 0.241), and 1374 ± 261/mm (P = 0.213), after 1, 3, and 6 months, respectively. The rebubbling rate was 46% (11/24). Four patients (17%) had secondary graft failure.Our data provide evidence that DMEK is feasible for the treatment of endothelial decompensation in complex preoperative situations.
EVALuna2:21233

Feasibility of cell-based therapy combined with descemetorhexis for treating Fuchs endothelial corneal dystrophy in rabbit model - Okumura, Naoki; Matsumoto, Daiki; Fukui, Yuya; Teramoto, Masataka; Imai, Hirofumi; Kurosawa, Tetta; Shimada, Tomoki; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Kinoshita, Shigeru; Koizumi, Noriko (PLoS ONE, 2018)
Corneal transparency is maintained by the corneal endothelium through its pump and barrier function. Severe corneal endothelial damage results in dysregulation of water flow and eventually causes corneal haziness and deterioration of visual function. In 2013, we initiated clinical research of cell-based therapy for treating corneal decompensation. In that study, we removed an 8-mm diameter section of damaged corneal endothelium without removing Descemet's membrane (the basement membrane of the corneal endothelium) and then injected cultured human corneal endothelial cells (CECs) into the anterior chamber. However, Descemet's membrane exhibits clinically abnormal structural features [i.e., multiple collagenous excrescences (guttae) and thickening] in patients with Fuchs endothelial corneal dystrophy (FECD) and the advanced cornea guttae adversely affects the quality of vision, even in patients without corneal edema. The turnover time of cornea guttae is also not certain. Therefore, we used a rabbit model to evaluate the feasibility of Descemet's membrane removal in the optical zone only, by performing a small 4-mm diameter descemetorhexis prior to CEC injection. We showed that the corneal endothelium is regenerated both on the corneal stroma (the area of Descemet's membrane removal) and on the intact peripheral Descemet's membrane, based on the expression of function-related markers and the restoration of corneal transparency. Recovery of the corneal transparency and central corneal thickness was delayed in areas of Descemet's membrane removal, but the cell density of the regenerated corneal endothelium and the thickness of the central corneal did not differ between the areas with and without residual Descemet's membrane at 14 days after CEC injection. Here, we demonstrate that removal of a pathological Descemet's membrane by a small descemetorhexis is a feasible procedure for use in combination with cell-based therapy. The current strategy might be beneficial for improving visual quality after CEC injection as a treatment for FECD.
EVALuna2:34756

Feasibility of intravitreal injections and ophthalmic safety assessment in marmoset (Callithrix jacchus) monkeys - Niggemann, B.; Korte, S.; Hill, M.; Shenton, J.; Mansfield, K.; Pilling, A.; Mecklenburg, L.; Fridrichs-Gromoll, S.; Wiederhold, A.; Atorf, J.; Kremers, Jan (Toxicology Letters, 2015)

Feasibility of mTOR inhibitor for the treatment of Fuchs endothelial corneal dystrophy - Nakayama, Genta; Okumura, Naoki; Oshima, Takeshi; Ueda, Emi; Watanabe, Kyoko; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

First experience in analysing pulsatile retinal capillary flow and arteriolar structural parameters measured noninvasively in hypertensive patients - Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Welzenbach, Juergen; Kwella, Norbert; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2014)
Increased pulsatile pressure induces as well as aggravates microvascular damage. Scanning laser Doppler flowmetry allows the noninvasive assessment of both retinal capillary flow (RCF) and arteriolar structural parameters of the retinal circulation. Moreover, pulsatile characteristics of the retinal arterioles can be assessed.In study 1, reliability of pulsatile RCF and structural parameters were examined in randomly selected patients. In study 2, pulsatile RCF as well as the structural parameters of retinal arterioles were assessed in hypertension grade 1-2 (HT1-2; n = 20) and treatment-resistant hypertension (TRH; n = 19).In study 1, test-retest, interobserver and intraobserver reliability of all parameters showed coefficients of variation of less than 10%. In study 2, it was shown that patients with TRH had higher pulse pressure (P = 0.003) and pulsed RCF values (P < 0.001) as patients with HT1-2. Patients with HT1-2 had no change in the vessel diameter, but a significant difference in lumen diameter, resulting in an altered wall thickness (P = 0.001) between systole and diastole. In contrast, patients with TRH showed differences in vessel diameter (P = 0.005) as well as lumen diameter (P = 0.001), resulting in an unaltered wall thickness between systole and diastole. Hence, wall thickness change as a result of pulsed flow regulation observed in HT1-2 was missing in TRH.We suggest a new reliable tool for evaluating the pulsatility in the retinal circulation in humans, and found significant differences in pulsatile RCF and structural parameters between patients with HT1-2 and those with TRH.
EVALuna2:3718

Five-Year Long-Term Follow-Up of Selective Laser Trabeculoplasty in Open-Angle Glaucoma - Gack, Christina; Lämmer, Robert; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Selective laser trabeculoplasty (SLT) is known as a safe laser therapy for an effective reduction in intraocular pressure (IOP). The aim of this study was to examine the therapeutic success of SLT in open-angle glaucoma (OAG) patients with a long-term follow-up of 5 years. Methods Forty-six eyes of forty OAG patients, some with previous intraocular surgery, underwent SLT (24 males, 16 females). Therapeutic success was categorized as: category (I) - IOP reduction <= 21 mmHg and > 20% compared to baseline IOP with additional glaucoma medication; category (II) - IOP reduction <= 18 mmHg and > 30% compared to baseline IOP with additional glaucoma medication; category (III) - IOP reduction <= 18 mmHg without any additional glaucoma medication at all follow-ups. Therapeutic failure was defined as the necessity of any further glaucoma surgery (IV). Results (1) SLT was well tolerated in all eyes, and no severe side effects or complications were recorded. (2) After 1-year follow-up, therapeutic success was 27% (I), 30% (II), and 3% (III). The therapeutic failure rate was 40% (IV). (3) After 2 years follow-up, therapeutic success was 7% (I), 10% (II), and 0% (III). The therapeutic failure rate was 83% (IV). (4) After 3 years follow-up, the therapeutic failure rate increased up to 100% (IV). Conclusion SLT seemed to be effective in lowering IOP in the first year in the present cohort, however, the long-term effect is low and additional local therapy or surgical interventions are necessary.
CRIS-Team WoS Importer:2021-12-31

Flicker-defined form perimetry in glaucoma patients - Horn, Folkert; Kremers, Jan; Mardin, Christian Y.; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
To assess the potential of flicker-defined form (FDF) perimetry to detect functional loss in patient groups with beginning glaucoma, and to evaluate the dynamic range of the FDF stimulus in individual patients and at individual test positions.FDF perimetry and standard automated perimetry (SAP) were performed at identical test locations (adapted G1 protocol) in 60 healthy subjects and 111 glaucoma patients. All patients showed glaucomatous optic disc appearance. Grouping within the glaucoma cohort was based on SAP-performance: 33 "preperimetric" open-angle glaucoma (OAG) patients, 28 "borderline" OAG (focal defects and SAP-mean defect (MD) <2 dB), 33 "early" OAG (SAP-MD < 5 dB), 17 "advanced" OAG. All participants were experienced in psychophysical and perimetric tests. Defect values and the areas under receiver operating characteristic curves (ROC) in patient groups were statistically compared.The values of FDF-MD in the preperimetric, borderline, and early OAG group were 2.7 ± 3.4 dB, 5.5 ± 2.6 dB, and 8.5 ± 3.4 dB respectively (all significantly above normal). The percentage of patients exceeding normal FDF-MD was 27.3 %, 60.7 %, and 87.9 % respectively. The age-adjusted FDF-mean defect (MD) of the G1X-protocol was not significantly correlated with refractive error, lens opacity, pupil size, or gender. Occurrence of ceiling effects (inability to detect targets at highest contrast) showed a high correlation with visual field losses (R = 0.72, p < 0.001). Local analysis indicates that SAP losses exceeding 5 dB could not be distinguished with the FDF technique.The FDF stimulus was able to detect beginning glaucoma damage. Patients with SAP-MD values exceeding 5 dB should be monitored with conventional perimetry because of its larger dynamic range.
EVALuna2:5485

Flicker ERGs Representing Chromaticity and Luminance Signals - Kremers, Jan; Rodrigues, Anderson Raiol; De Lima Silveira, Luiz Carlos; Da Silva Filho, Manoel (Investigative Ophthalmology & Visual Science, 2010)
PURPOSE. To test the hypothesis that electroretinograms (ERGs) reflect luminance activity when measured at high temporal frequencies and chromatic activity when measured near 12 Hz.METHODS. The authors measured the responses to stimuli in which the output of red and green light-emitting diodes was modulated in counterphase at different ratios, varying the luminance content in the stimulus while keeping the red-green chromatic contrast and its phase constant.RESULTS. The high temporal frequency electroretinography was determined mainly by the luminance contrast. At 12 Hz, electroretinographic response amplitudes and phases primarily reflected the red-green chromatic content of the stimulus. Control experiments, performed with a deuteranopic subject and with stimuli that silenced the rods and S-cones, excluded an explanation based on intrusion from rod-and S-cone-driven responses.CONCLUSIONS. It now is possible to perform noninvasive measurements of basic electrophysiological properties of the luminance and chromatic pathways on a retinal level, and their disease-related changes, in human observers. (Invest Ophthalmol Vis Sci. 20010;51:577-587) DOI:10.1167/iovs.09-3899

Follicular Conjunctivitis due to Chlamydia felis-Case Report, Review of the Literature and Improved Molecular Diagnostics - Wons, Juliana; Meiller, Ralph; Bergua, Antonio; Bogdan, Christian; Geißdörfer, Walter (Frontiers in Medicine, 2017)
A 29-year-old woman presented with unilateral, chronic follicular conjunctivitis since 6 weeks. While the conjunctival swab taken from the patient's eye was negative in a Chlamydia (C.) trachomatis-specific PCR, C. felis was identified as etiological agent using a pan-Chlamydia TaqMan-PCR followed by sequence analysis. A pet kitten of the patient was found to be the source of infection, as its conjunctival and pharyngeal swabs were also positive for C. felis. The patient was successfully treated with systemic doxycycline. This report, which presents one of the few documented cases of human C. felis infection, illustrates that standard PCR tests are designed to detect the most frequently seen species of a bacterial genus but might fail to be reactive with less common species. We developed a modified pan-Chlamydia/C. felis duplex TaqMan-PCR assay that detects C. felis without the need of subsequent sequencing. The role of chlamydiae-specific serum antibody titers for the diagnosis of follicular conjunctivitis is discussed.
EVALuna2:7759

Four subunits (αβγδ) of the epithelial sodium channel (ENaC) are expressed in the human eye in various locations - Krüger, Bettina; Schlötzer-Schrehardt, Ursula; Härteis, Silke; Zenkel, Matthias; Chankiewitz, Verena E.; Amann, Kerstin Ute; Kruse, Friedrich; Korbmacher, Christoph (Investigative Ophthalmology & Visual Science, 2012)
The epithelial sodium channel (ENaC) is typically expressed in sodium-absorbing epithelia. Several reports suggest that ENaC is also expressed in ocular tissues and may play a role in aqueous humor secretion and glaucoma. However, the precise localization of ENaC in the human eye is still unclear. Here, the authors studied ENaC expression in 12 normal human donor eyes and in six eyes of patients with glaucoma.Quantitative real-time PCR was used to investigate the expression of ?-, ?-, ?-, and ?-ENaC transcripts in ocular tissues. In addition, the authors performed immunohistochemical studies using recently generated antibodies against human ?- and ?-ENaC.At the mRNA level, all four ENaC subunits were found to be expressed in a wide range of ocular tissues from normal and glaucomatous human eyes, with the cornea, ciliary body, iris, and retina showing the highest expression levels. At the protein level, ?- and ?-ENaC subunits showed distinct distribution patterns and could be immunolocalized primarily to the cell membranes of epithelial cells of the cornea and to the conjunctiva, iris, ciliary body, lens, and retinal pigment epithelium but also to vascular endothelial cells, smooth muscle cells, stromal cells, and retinal neurons. The authors found no altered mRNA level of any subunit in glaucomatous eyes.All four ENaC subunits (????) are expressed in the normal human eye, with distinct localization of subunits possibly reflecting different functional states of the channel. The (patho-)physiological roles of ENaC in the various localizations in the eye remain to be determined.
EVALuna2:4482

Frequency dependency of temporal contrast adaptation in normal subjects - Hohberger, Bettina; Roessler, Christopher W.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Vision research, 2011)
The aim of this study was to determine the influence of temporal frequency of temporal contrast adaptation on contrast sensitivity in healthy subjects. Temporal contrast sensitivities (TCS) were measured monocularly in seven healthy subjects with a modified ERG full-field bowl stimulator at eight different test temporal frequencies (9, 15, 20, 25, 31, 37, 44, 51 Hz) using a two-alternative-forced-choice strategy. Before each presentation of the test stimulus, a 100% contrast adapting flicker stimulus was presented (frequencies: 9, 15, 20, 25, 31, 37, 44, 51, 100 Hz). At each adapting frequency, a complete set of TCSs was measured. All temporal contrast sensitivities decreased with increasing temporal frequencies. Adaptation led to a general temporal contrast sensitivity decrease. Largest adaptation effects were seen at an adaptation frequency of 25 Hz. Reduction of contrast sensitivity was significantly larger at 25 Hz adaptation than at 9 Hz adaptation (t-test of paired samples, Bonferroni corrected). The results of this study showed a general TCS decrease with the largest effect at an adaptation frequency of 25 Hz. This finding indicates that the contrast adaptation probably occurred in the magnocellular-pathway. In future clinical studies adaptation effects could be investigated in patients with reduced temporal contrast sensitivity.
EVALuna2:21010

Frequency doubling technique perimetry and spectral domain optical coherence tomography in patients with early glaucoma - Horn, Folkert; Mardin, C. Y.; Bendschneider, D.; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Eye, 2011)
PurposeTo assess the combined diagnostic power of frequency-doubling technique (FDT)-perimetry and retinal nerve fibre layer (RNFL) thickness measurements with spectral domain optical coherence tomography (SDOCT).MethodsThe study included 330 experienced participants in five age-related groups: 77 'preperimetric' open-angle glaucoma (OAG) patients, 52 'early' OAG, 50 'moderate' OAG, 54 ocular hypertensivepatients, and 97 healthy subjects. For glaucoma assessment in all subjects conventional perimetry, evaluation of fundus photographs, FDT-perimetry and RNFL thickness measurement with SDOCT was done. Glaucomatous visual field defects were classified using the Glaucoma Staging System. FDT evaluation used a published method with casewise calculation of an 'FDT-score', including all missed localized probability levels. SDOCT evaluation used mean RNFL thickness and a new individual SDOCT-score considering normal confidence limits in 32 sectors of a peripapillary circular scan. To examine the joined value of both methods a combined score was introduced. Significance of the difference between Receiver-operating-characteristic (ROC) curves was calculated for a specificity of 96%.ResultsSensitivity in the preperimetric glaucoma group was 44% for SDOCT-score, 25% for FDT-score, and 44% for combined score, in the early glaucoma group 83, 81, and 89%, respectively, and in the moderate glaucoma group 94, 94, and 98%, respectively, all at a specificity of 96%. ROC performance of the newly developed combined score is significantly above single ROC curves of FDT-score in preperimetric and early OAG and above RNFL thickness in moderate OAG.ConclusionCombination of function and morphology by using the FDT-score and the SDOCT-score performs equal or even better than each single method alone.
EVALuna2:5300

Fresh and cryopreserved amniotic membrane secrete the trefoil factor family peptide 3 that is well known to promote wound healing - Schulze, Ute; Hampel, Ulrike; Sel, Saadettin; Goecke, Tamme W.; Thaele, Volker; Garreis, Fabian; Paulsen, Friedrich (Histochemistry and Cell Biology, 2012)
Amniotic membrane (AM) is often used for the treatment of ocular surface ulcerations and other corneal defects. Trefoil factor family (TFF) peptide 3 is produced by conjunctival goblet cells, participates in tear film physiology and has also been shown to be involved in ocular surface restitution after corneal injury. In the present study, we questioned whether AM also might be a source of TFF3 and if yes whether the secretion rate of TFF3 is changed by proinflammatory cytokines or by cryoconservation of AM. By means of RT-PCR, the mRNA expression of all three known TFF peptides could be detected in AM. Immunohistochemistry on paraffin-embedded sections localized TFF3 protein and also TFF2 in AM cells and Western blot analysis revealed TFF3 protein in AM. Stimulation experiments with proinflammatory cytokines and subsequent TFF3 ELISA measurements revealed that the secretion rate of fresh or cryoconserved AM was not significantly changed. The results indicate that TFF peptides are produced by AM. TFF3 may contribute to ocular surface wound healing after AM transplantation, but its production by AM is not further inducible by proinflammatory stimuli. Cryopreservation has no effect on the secretion rate of TFF3 supporting the use of cryopreserved AM for transplantation.
EVALuna2:4370

From hair to cornea: toward the therapeutic use of hair follicle-derived stem cells in the treatment of limbal stem cell deficiency - Meyer-Blazejewska, Ewa Anna; Call, Mindy K.; Yamanaka, Osamu; Liu, Hongshan; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Kao, Winston W. (Stem Cells, 2011)
Limbal stem cell deficiency (LSCD) leads to severe ocular surface abnormalities that can result in the loss of vision. The most successful therapy currently being used is transplantation of limbal epithelial cell sheets cultivated from a limbal biopsy obtained from the patient's healthy, contralateral eye or cadaveric tissue. In this study, we investigated the therapeutic potential of murine vibrissae hair follicle bulge-derived stem cells (HFSCs) as an autologous stem cell (SC) source for ocular surface reconstruction in patients bilaterally affected by LSCD. This study is an expansion of our previously published work showing transdifferentiation of HFSCs into cells of a corneal epithelial phenotype in an in vitro system. In this study, we used a transgenic mouse model, K12(rtTA/rtTA) /tetO-cre/ROSA(mTmG) , which allows for HFSCs to change color, from red to green, once differentiation to corneal epithelial cells occurs and Krt12, the corneal epithelial-specific differentiation marker, is expressed. HFSCs were isolated from transgenic mice, amplified by clonal expansion on a 3T3 feeder layer, and transplanted on a fibrin carrier to the eye of LSCD wild-type mice (n = 31). The HFSC transplant was able to reconstruct the ocular surface in 80% of the transplanted animals; differentiating into cells with a corneal epithelial phenotype, expressing Krt12, and repopulating the corneal SC pool while suppressing vascularization and conjunctival ingrowth. These data highlight the therapeutic properties of using HFSC to treat LSCD in a mouse model while demonstrating a strong translational potential and points to the niche as a key factor for determining stem cell differentiation.
EVALuna2:21016

Frontline Science: Aggregated neutrophil extracellular traps prevent inflammation on the neutrophil-rich ocular surface - Mahajan, Aparna; Grüneboom, Anika; Petru, Lenka; Podolska, Malgorzata; Kling, Lasse; Maueröder, Christian; Dahms, Florian; Christiansen, Silke; Günter, Lochnit; Krenn, Veit; Jünemann, Anselm; Bock, Felix; et al. (Journal of Leukocyte Biology, 2019)
Eye rheum is a physiological discharge, which accumulates at the medial angle of the healthy eye soon after opening in the morning. Microscopic evaluation of eye rheum revealed the presence of viable neutrophils, bacteria, epithelial cells, and particles, aggregated by neutrophil extracellular traps. We observed that in the evening, during eye closure, high C5a recruited neutrophils to the tear film and activated them. In this hypoxic area rich in CO 2 , neutrophils fight microbial aggressors by degranulation. Immediately after eye opening, the microenvironment of the ocular surface changes, the milieu gets normoxic, and loss of CO 2 induces subtle alkalinization of tear film. These conditions favored the formation of neutrophil extracellular traps (NETs) that initially covers the ocular surface and tend to aggregate by eyelid blinking. These aggregated neutrophil extracellular traps (aggNETs) are known as eye rheum and contain several viable neutrophils, epithelial cells, dust particles, and crystals packed together by NETs. Similar to aggNETs induced by monosodium urate crystals, the eye rheum shows a robust proteolytic activity that degraded inflammatory mediators before clinically overt inflammation occur. Finally, the eye rheum passively floats with the tear flow to the medial angle of the eye for disposal. We conclude that the aggNETs-based eye rheum promotes cleaning of the ocular surface and ameliorates the inflammation on the neutrophil-rich ocular surfaces.
CRIS-Team Scopus Importer:2019-05-02
Keywords: degranulation; eye rheum; inflammation; NETs; neutrophils; resolution; serine protease

Frosted branch angiitis : Clinical findings and Spectralis OCT follow-up - Bergua, A.; Galiano, M.; Hohberger, B.; Rudolph, Michael (Ophthalmologe, 2016)
Frosted branch angiitis is a special form of retinal vasculitis, which has only rarely been reported in the literature. Although the majority of cases of frosted branch angiitis are idiopathic, a systematic clinical work-up should be done in order to exclude other causes, such as infectious and autoimmune diseases. The aim of this study was to correlate the clinical findings with the images obtained during follow-up by spectral domain optical coherence tomography (OCT).
EVALuna2:21248

Functional and effective connectivity in subthalamic local field potential recordings of patients with Parkinson's disease - Hohlefeld, F. U.; Huchzermeyer, Cord; Huebl, J.; Schneider, G. -H.; Nolte, G.; Bruecke, C.; Schoenecker, T.; Kuehn, A. A.; Curio, G.; Nikulin, V. V. (Neuroscience, 2013)
In Parkinson's disease (PD) levodopa-associated changes in the power and long-range temporal correlations of beta oscillations have been demonstrated, yet the presence and modulation of genuine connectivity in local field potentials (LFP) recorded from the subthalamic nucleus (STN) remains an open question. The present study investigated LFP recorded bilaterally from the STN at wakeful rest in ten patients with PD after overnight withdrawal of levodopa (OFF) and after a single dose levodopa administration (ON). We utilized connectivity measures being insensitive to volume conduction (functional connectivity: non-zero imaginary part of coherency; effective connectivity: phase-slope index). We demonstrated the presence of neuronal interactions in the frequency range of 10-30 Hz in STN-LFP without a preferential directionality of interactions between different contacts along the electrode tracks. While the direction of neuronal interactions per se was preserved after levodopa administration, functional connectivity and the ventral-dorsal information flow were modulated by medication. The OFF-ON differences in functional connectivity were correlated with the levodopa-induced improvement in clinical Unified Parkinson's Disease Rating Scale scores. We hypothesize that regional neuronal interactions, as reflected in STN-LFP connectivity, might represent a basis for the intra-nuclear spatial specificity of deep brain stimulation. Moreover, our results suggest the potential use of volume conduction-insensitive measures of connectivity in STN-LFP as a marker of clinical motor symptoms in PD.
EVALuna2:21135

Functional autoantibodies against G-protein coupled receptors in patients with persistent Long-COVID-19 symptoms - Wallukat, Gerd; Hohberger, Bettina; Wenzel, Katrin; Fürst, Julia; Schulze-Rothe, Sarah; Wallukat, Anne; Hönicke, Anne Sophie; Müller, Johannes (Journal of Translational Autoimmunity, 2021)
Impairment of health after overcoming the acute phase of COVID-19 is being observed more and more frequently. Here different symptoms of neurological and/or cardiological origin have been reported. With symptoms, which are very similar to the ones reported but are not caused by SARS-CoV-2, the occurrence of functionally active autoantibodies (fAABs) targeting G-protein coupled receptors (GPCR-fAABs) has been discussed to be involved. We, therefore investigated, whether GPCR-fAABs are detectable in 31 patients suffering from different Long-COVID-19 symptoms after recovery from the acute phase of the disease. The spectrum of symptoms was mostly of neurological origin (29/31 patients), including post-COVID-19 fatigue, alopecia, attention deficit, tremor and others. Combined neurological and cardiovascular disorders were reported in 17 of the 31 patients. Two recovered COVID-19 patients were free of follow-up symptoms. All 31 former COVID-19 patients had between 2 and 7 different GPCR-fAABs that acted as receptor agonists. Some of those GPCR-fAABs activate their target receptors which cause a positive chronotropic effect in neonatal rat cardiomyocytes, the read-out in the test system for their detection (bioassay for GPCR-fAAB detection). Other GPCR-fAABs, in opposite, cause a negative chronotropic effect on those cells. The positive chronotropic GPCR-fAABs identified in the blood of Long-COVID patients targeted the β2-adrenoceptor (β2-fAAB), the α1-adrenoceptor (α1-fAAB), the angiotensin II AT1-receptor (AT1-fAAB), and the nociceptin—like opioid receptor (NOC-fAAB). The negative chronotropic GPCR-fAABs identified targeted the muscarinic M2-receptor (M2-fAAB), the MAS-receptor (MAS-fAAB), and the ETA-receptor (ETA-fAAB). It was analysed which of the extracellular receptor loops was targeted by the autoantibodies.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Autoantibody; Autoimmunity; COVID-19; Fatigue; Long-COVID; Post-covid-19 symptom

Functional implication of the pseudoexfoliation-associated rare variant p.Y407F at LOXL1 - Berner, Daniel; Hoja, Ursula; Zenkel, Matthias; Pasutto, Francesca; Lee, Mei Chin; Aung, Tin; Khor, Chiea Chuen; Reis, André; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Functional Protective Effects of Long-Term Memantine Treatment in the DBA/2J Mouse. - Atorf, Jenny; Scholz, Michael; Garreis, Fabian; Lehmann, Julia; Bräuer, Lars; Kremers, Jan (Documenta Ophthalmologica, 2013)
Purpose: To analyse the effects of long-term memantine treatment on the retinal physiology and morphology of DBA/2J mice. Methods: DBA/2J (D2J) mice received i.p. injections of the NMDA receptor antagonist memantine, which protects neurons from abnormally elevated glutamate levels, twice a day over a period of 7 months. At the age of 2, 6 and 10 months, the intraocular pressure (IOP) and electroretinograms (ERGs) were measured in all treated D2J mice, in untreated D2J controls and in C57Bl/6 (B6) wild-type mice. After the last measurement at the age of 10 months, the mice were killed and the retinae and the optic nerves were analysed morphologically. Results: The IOP increased with age in both D2J and B6 mice with a larger increase in the D2J strain. IOPs were not influenced by memantine treatment. The response amplitude of the scotopic flash ERG decreased with age in the D2J strain. This amplitude decrease, particularly that of the b-wave, was smaller in treated D2J mice. The retinae of treated D2J mice exhibited less peripheral degeneration of cone photoreceptors, and optic nerve neuropathy was less frequent. Conlcusions: Application of the NMDA receptor antagonist memantine diminished retinal neurodegeneration in the D2J mice and had a protective effect on the b-wave amplitude of the scotopic flash ERG. This protection may occur secondarily as memantine primarily acts on retinal ganglion cells. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-03-09:Pub.2013.med.AI.LAIPDL.functi
Keywords: DBA/2J mouse; Electroretinography; Memantine; Neurodegeneration

Fungal infection after endothelial keratoplasty: Association with hypothermic corneal storage - Lau, Nicola; Sesé, Aida Hajjar; Augustin, Victor A.; Kuit, Geert; Wilkins, Mark R.; Tourtas, Theofilos; Kruse, Friedrich; Højgaard-Olsen, Klavs; Manuel, Rohini; John Armitage, W.; Larkin, Daniel F.; Tuft, Stephen J. (British Journal of Ophthalmology, 2019)
Purpose To compare the incidence of fungal infection after endothelial keratoplasty (EK) when donor tissue had been stored in hypothermic medium or organ culture. Methods We describe the clinical features of 10 cases of fungal infection (keratitis or endophthalmitis) following EK identified at three European centres. Case definition was the culture of fungus or a positive PCR from the host cornea or anterior chamber after EK. A survey of the incidence of infection after EK was conducted by the European Eye Bank Association. The main outcome measure was the number of cases in which donor tissue had been stored in hypothermic medium compared with organ culture. Results The 10 cases occurred between 2014 and 2017. All donor corneas had been stored in hypothermic medium sourced from three US eye banks. Three pairs of mate corneas caused infections in six recipients. Candida spp were identified from nine cases, with one isolate of Purpureocillium lilacinum. Data on 16 862 corneas supplied for EK were available from 16 European eye banks for the 5-year period from 2012. There were 17 reported cases of infection, of which 15 (88%) were fungal infections and 14 (82%) were Candida spp. Fungal infection was reported from 3 of 14 476 (0.02%) corneas supplied in organ culture compared with 12 of 2386 (0.50%) corneas supplied in hypothermic medium (p<0.0001). The incidence of infection after hypothermic storage was similar for material sourced from Europe (0.52%) or the USA (0.61%). Conclusions Infection after EK is strongly associated with Candida spp. The possible explanations for the higher incidence of infection when tissue is stored in hypothermic medium are discussed.
CRIS-Team Scopus Importer:2019-10-01
Keywords: cornea; eye (tissue) banking; infection

Fungal interface keratitis by Candida orthopsilosis following deep anterior lamellar keratoplasty - Wessel, Julia M.; Bachmann, Björn; Meiller, Ralph; Kruse, Friedrich (BMJ Case Reports, 2013)
A 39-year-old male patient underwent uncomplicated deep anterior lamellar keratoplasty due to keratoconus. On day 5 after surgery, small whitish infiltrates developed in the corneal interface. The diagnosis of fungal keratitis was made when the culture medium of the graft grew Candida after the surgical intervention. Despite intensive antimycotic treatment and irrigation of the interface, the infiltrates persisted and eventually enlarged. Therefore, revision surgery with penetrating keratoplasty was performed. Microbiological analysis showed Candida orthopsilosis in the culture of the excised graft button. Histopathological staining of the excised graft showed periodic acid-Schiff-positive and Grocott methenamine silver-positive clusters of yeast between Descemet's membrane and the deep corneal stroma with focal perforations through Descemet's membrane. The treatment of mycotic keratitis caused by C orthopsilosis is challenging. Antimycotic treatment was unsuccessful in this case. Progression of the keratitis and perforation of Descemet's membrane suggest that early surgical intervention by penetrating keratoplasty is required.
EVALuna2:21124

Fuzzy C-means Clustering For Retinal Layer Segmentation On High Resolution OCT Images - Mayer, Markus Anton; Tornow, Ralf-Peter; Hornegger, Joachim; Kruse, Friedrich (Analysis of Biomedical Signals and Images, Proceedings of the Biosignal 2008 International Eurasip Conference, 2008)

Gene Therapy for Modulation of T Cell Mediated Immune Response Provoked by Corneal Transplantation - Pastak, Marko; Kleff, Veronika; Saban, Daniel R.; Czugala, Marta; Steuhl, Klaus-Peter; Erguen, Sueleyman; Singer, Bernhard B.; Fuchsluger, Thomas (Human Gene Therapy, 2017)
Corneal transplantation (=keratoplasty) is the most common type of tissue replacement in the world. The increased rate of graft rejection after keratoplasty is a central problem for repeated transplantations and in inflamed host corneas. It has been shown that apoptosis of grafted epithelium has a role in corneal allograft rejection. Our study focused on the T cell response triggered in BALB/c mice after allogeneic corneal transplantation with and without anti-apoptotic p35-transduced epithelium. To restrict p35 expression to the epithelial cells we created modified allogeneic composite grafts. As a result we found that the proportion of alloreactive CD4+ T cells in postoperatively removed cervical lymph nodes was reduced in the p35-transduced group compared to the allogeneic control group. Diminished priming of the CD4+ T cells was supported by significantly decreased proliferation and lower interferon gamma secretion when compared to allogeneic engraftments. The reduced priming of CD4+ lymphocytes is the first confirmation of the functionality of p35 in the epithelium of corneal grafts to alter the development of the recipient's immune response. Thus, modification of allosensibilization seems to be a promising tool for reducing graft-mediated immune response following corneal transplantation.
EVALuna2:21342

Genetic association study of exfoliation syndrome identifies a protective rare variant at LOXL1 and five new susceptibility loci - Aung, Tin; Ozaki, Mineo; Lee, Mei Chin; Schlötzer-Schrehardt, Ursula; Thorleifsson, Gudmar; Mizoguchi, Takanori; Igo, Robert P.; Haripriya, Aravind; Williams, Susan E.; Astakhov, Yury S.; Orr, Andrew C.; Burdon, Kathryn P.; et al. (Nature Genetics, 2017)
Exfoliation syndrome (XFS) is the most common known risk factor for secondary glaucoma and a major cause of blindness worldwide. Variants in two genes, LOXL1 and CACNA1A, have previously been associated with XFS. To further elucidate the genetic basis of XFS, we collected a global sample of XFS cases to refine the association at LOXL1, which previously showed inconsistent results across populations, and to identify new variants associated with XFS. We identified a rare protective allele at LOXL1 (p.Phe407, odds ratio (OR) = 25, P = 2.9 × 10(-14)) through deep resequencing of XFS cases and controls from nine countries. A genome-wide association study (GWAS) of XFS cases and controls from 24 countries followed by replication in 18 countries identified seven genome-wide significant loci (P < 5 × 10(-8)). We identified association signals at 13q12 (POMP), 11q23.3 (TMEM136), 6p21 (AGPAT1), 3p24 (RBMS3) and 5q23 (near SEMA6A). These findings provide biological insights into the pathology of XFS and highlight a potential role for naturally occurring rare LOXL1 variants in disease biolog
EVALuna2:9376

Genetic disruption of bassoon in two mutant mouse lines causes divergent retinal phenotypes - Ryl, Miriam; Urbasik, Alexander; Gierke, Kaspar; Babai, Norbert; Joachimsthaler, Anneka; Feigenspan, Andreas; Frischknecht, Renato; Stallwitz, Nina; Fejtová, Anna; Kremers, Jan; von Wittgenstein, Julia; Brandstätter, Johann Helmut (The FASEB Journal, 2021)
Bassoon (BSN) is a presynaptic cytomatrix protein ubiquitously present at chemical synapses of the central nervous system, where it regulates synaptic vesicle replenishment and organizes voltage-gated Ca2+ channels. In sensory photoreceptor synapses, BSN additionally plays a decisive role in anchoring the synaptic ribbon, a presynaptic organelle and functional extension of the active zone, to the presynaptic membrane. In this study, we functionally and structurally analyzed two mutant mouse lines with a genetic disruption of Bsn-Bsngt and Bsnko -using electrophysiology and high-resolution microscopy. In both Bsn mutant mouse lines, full-length BSN was abolished, and photoreceptor synaptic function was similarly impaired, yet synapse structure was more severely affected in Bsngt/gt than in Bsnko/ko photoreceptors. The synaptic defects in Bsngt/gt retina coincide with remodeling of the outer retina-rod bipolar and horizontal cell sprouting, formation of ectopic ribbon synaptic sites-and death of cone photoreceptors, processes that did not occur in Bsnko/ko retina. An analysis of Bsngt/ko hybrid mice revealed that the divergent retinal phenotypes of Bsngt/gt and Bsnko/ko mice can be attributed to the expression of the Bsngt allele, which triggers cone photoreceptor death and neurite sprouting in the outer retina. These findings shed new light on the existing Bsn mutant mouse models and might help to understand mechanisms that drive photoreceptor death.
CRIS-Team Scopus Importer:2021-04-16
Keywords: active zone; bassoon; photoreceptor; photoreceptor death; ribbon synapse

Genome-wide association study with DNA pooling identifies variants at CNTNAP2 associated with pseudoexfoliation syndrome - Krumbiegel, Mandy; Pasutto, Francesca; Schlötzer-Schrehardt, Ursula; Uebe, Steffen; Zenkel, Matthias; Mardin, Christian Y.; Weisschuh, Nicole; Paoli, Daniela; Gramer, Eugen; Becker, Christian; Ekici, Arif Bülent; Weber, Bernhard H. F.; et al. (European journal of human genetics, 2011)
Genetic and nongenetic factors contribute to development of pseudoexfoliation (PEX) syndrome, a complex, age-related, generalized matrix process frequently associated with glaucoma. To identify specific genetic variants underlying its etiology, we performed a genome-wide association study (GWAS) using a DNA-pooling approach. Therefore, equimolar amounts of DNA samples of 80 subjects with PEX syndrome, 80 with PEX glaucoma (PEXG) and 80 controls were combined into separate pools and hybridized to 500K SNP arrays (Affymetrix). Array probe intensity data were analyzed and visualized with expressly developed software tools GPFrontend and GPGraphics in combination with GenePool software. For replication, independent German cohorts of 610 unrelated patients with PEX/PEXG and 364 controls as well as Italian cohorts of 249 patients and 190 controls were used. Of 19, 17 SNPs showing significant allele frequency difference in DNA pools were confirmed by individual genotyping. Further single genotyping at CNTNAP2 locus revealed association between PEX/PEXG for two SNPs, which was confirmed in an independent German but not the Italian cohort. Both SNPs remained significant in the combined German cohorts even after Bonferroni correction (rs2107856: P(c)=0.0108, rs2141388: P(c)=0.0072). CNTNAP2 was found to be ubiquitously expressed in all human ocular tissues, particularly in retina, and localized to cell membranes of epithelial, endothelial, smooth muscle, glial and neuronal cells. Confirming efficiency of GWAS with DNA-pooling approach by detection of the known LOXL1 locus, our study data show evidence for association of CNTNAP2 with PEX syndrome and PEXG in German patients.
EVALuna2:9084

Glaucoma and Alzheimer: Neurodegenerative disorders show an adrenergic dysbalance - Hohberger, Bettina; Pruess, Harald; Mardin, Christian Y.; Lämmer, Robert; Mueller, Johannes; Wallukat, Gerd (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Glaucoma and Alzheimer: Neurodegenerative disorders show an adrenergic dysbalance - Hohberger, Bettina; Prüss, Harald; Mardin, Christian; Lämmer, Robert; Müller, Johannes; Wallukat, Gerd (PLoS ONE, 2022)
Glaucoma disease is characterized by an increased intraocular pressure (IOP), glaucomatous alterations of the optic disc and corresponding visual field defects. Even lowering the main risk factor IOP until an individual target level does not prevent this neurodegenerative disorder from proceeding. Several autoimmune mechanisms were discovered, partly showing a functionality. One of these autoimmune phenomena targets the ß2-adrenergic receptor (ß2-AR; i.e. agonistic autoantibodies; ß2-agAAb) and is linked to an elevated IOP and an impaired retinal microcirculation. As neurodegenerative disorder, Alzheimer's Disease (AD) is postulated to share a common molecular mechanism with glaucoma. In the present study we investigated autoimmune phenomena targeting the ß2-AR in patients with AD. Sera of the patients were analyzed in a rat cardiomyocyte bioassay for the presence of functional autoantibodies against ß2-AR. In addition, different species of amyloid beta (Aß) monomers were tested (Aß1-14, Aß10-25, Aβ10-37 Aß1-40, Aß1-42, Aβ28-40, and Aß-[Pyr]3-43). Our results demonstrate that none of the short-chain Aß (Aß1-14, Aß10-25, or Aβ28-40) showed any agonistic or inhibitory effect on ß2-AR. Contrary, long-chain Aß-[Pyr]3-43, representing a major neurogenic plaque component, exerted an activation that after blocking by the ß2-AR antagonist ICI118.551, could be identified as that the effect was realized via the ß2-AR. Moreover, the long chain Aß1-40, Aβ1-42, and Aβ10-37, yet not the short-chain Aß peptides prevented the clenbuterol induced desensitization of the ß2-AR. In addition, we identified functional autoantibodies in the sera of AD patients, activating the ß2-AR, like the ß2-agAAb found in patients with glaucoma. As autoimmune mechanisms were reportedly involved in the pathogenesis of glaucoma and Alzheimer's Disease, we postulate that overstimulation of the ß2-AR pathway can induce an adrenergic overdrive, that may play an important role in the multifactorial interplay of neurodegenerative disorders.
CRIS-Team Scopus Importer:2022-10-21

Glaucoma classification based on histogram analysis of diffusion tensor imaging measures in the optic radiation - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Springer-verlag, 2011)
Glaucoma is associated with axonal degeneration of the optic nerve leading to visual impairment. This impairment can progress to a complete vision loss. The transsynaptic disease spread in glaucoma extends the degeneration process to different parts of the visual pathway. Most of glaucoma diagnosis focuses on the eye analysis, especially in the retina. In this work, we propose a system to classify glaucoma based on visual pathway analysis. The system utilizes diffusion tensor imaging to identify the optic radiation. Diffusion tensor-derived indices describing the underlying fiber structure as well as the main diffusion direction are used to characterize the optic radiation. Features are extracted from the histograms of these parameters in regions of interest defined on the optic radiation. A support vector machine classifier is used to rank the extracted features according to their discrimination ability between glaucoma patients and healthy subjects. The seven highest ranked features are used as inputs to a logistic regression classifier. The system is applied to two age-matched groups of 39 glaucoma subjects and 27 normal controls. The evaluation is performed using a 10-fold cross validation scheme. A classification accuracy of 81.8% is achieved with an area under the ROC curve of 0.85. The performance of the system is competitive to retina based classification systems. However, this work presents a new direction in detecting glaucoma using visual pathway analysis. This analysis is complementary to eye examinations and can result in improvements in glaucoma diagnosis, detection, and treatment. © 2011 Springer-Verlag.

Glaucoma classification based on visual pathway analysis using diffusion tensor imaging - El-Rafei, Ahmed Mohamed Ibrahim; Engelhorn, Tobias; Wärntges, Simone; Dörfler, Arnd; Hornegger, Joachim; Michelson, Georg (Magnetic Resonance Imaging, 2013)
Most of the existing methods for diagnosing glaucoma analyze the eye with a main focus on the retina, despite the transsynaptic nature of the fiber degeneration caused by glaucoma. Thus, they ignore a significant part of the visual system represented by the visual pathway in the brain. The advances in neuroimaging, especially diffusion tensor imaging (DTI), enable the identification and characterization of white matter fibers. In this work, we propose a system based on DTI analysis of the visual pathway fibers in the optic radiation for detecting and discriminating different glaucoma entities. The optic radiation is identified semi-automatically. DTI provides information about the fiber orientation as well as a set of derived parameters describing the degree of diffusion anisotropy and diffusivity. Features for each DTI derived measure are extracted from a specified region of interest on the optic radiation. The features are grouped into three sets: Histogram, co-occurrence matrices, and Laws features. For feature selection, the features are ranked using a support vector machine classifier. The highest ranked features are used for classification. A support vector machine classifier is used for classification in a 10-fold cross validation setup. The system is applied to three age-matched subjects' categories containing 27 healthy, 39 primary open angle glaucoma (POAG), and 18 normal tension glaucoma (NTG) subjects. The discrimination accuracy between healthy and glaucoma (POAG and NTG) subjects is 94.1% with an area under the ROC of 0.97. Classification accuracy of 92.4% is obtained for the normal and the POAG groups while it increased to 100% in case of healthy and NTG groups. In addition, the system could differentiate between glaucoma types (POAG and NTG) with an accuracy of 98.3%. A complementary analysis was performed to estimate the selection bias in the obtained accuracy. The bias ranged from 10% to 20% depending on the group pair under consideration. The classification results indicate the high performance of the system compared to retina-based glaucoma detection systems. The proposed approach utilizes visual pathway analysis rather than the conventional eye analysis which presents a new trend in glaucoma detection. Analyzing the entire visual system could provide significant information that can improve the glaucoma examination flow and treatment. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Diffusion tensor imaging; Glaucoma; Optic radiation; Visual pathway; Classification; Texture features

Glaucoma classification in 3 x 3 mm en face macular scans using deep learning in a different plexus - Schottenhamml, Julia; Wuerfl, Tobias; Mardin, Sophia; Ploner, Stefan; Husvogt, Lennart; Hohberger, Bettina; Lämmer, Robert; Mardin, Christian; Maier, Andreas (Biomedical Optics Express, 2021)
Glaucoma is among the leading causes of irreversible blindness worldwide. If diagnosed and treated early enough, the disease progression can be stopped or slowed down. Therefore, it would be very valuable to detect early stages of glaucoma, which are mostly asymptomatic, by broad screening. This study examines different computational features that can be automatically deduced from images and their performance on the classification task of differentiating glaucoma patients and healthy controls. Data used for this study are 3 x 3 mm en face optical coherence tomography angiography (OCTA) images of different retinal projections (of the whole retina, the superficial vascular plexus (SVP), the intermediate capillary plexus (ICP) and the deep capillary plexus (DCP)) centered around the fovea. Our results show quantitatively that the automatically extracted features from convolutional neural networks (CNNs) perform similarly well or better than handcrafted ones when used to distinguish glaucoma patients from healthy controls. On the whole retina projection and the SVP projection, CNNs outperform the handcrafted features presented in the literature. Area under receiver operating characteristics (AUROC) on the SVP projection is 0.967, which is comparable to the best reported values in the literature. This is achieved despite using the small 3 x 3 mm field of view, which has been reported as disadvantageous for handcrafted vessel density features in previous works. A detailed analysis of our CNN method, using attention maps, suggests that this pertbrmance increase can be partially explained by the CNN automatically relying more on areas of higher relevance for feature extraction. (C) 2021 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2021-12-17

Glaucoma Diagnostic Performance of GDxVCC and Spectralis OCT on Eyes With Atypical Retardation Pattern - Hoesl, Laura Maria; Tornow, Ralf-Peter; Schrems, Wolfgang; Horn, Folkert; Mardin, Christian Y.; Kruse, Friedrich; Jünemann, Anselm; Lämmer, Robert (Journal of Glaucoma, 2013)
: To investigate the impact of typical scan score (TSS) on discriminating glaucomatous and healthy eyes by scanning laser polarimetry and spectral domain optical coherence tomography (SD-OCT) in 32 peripapillary sectors.: One hundred two glaucoma patients and 32 healthy controls underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, GDxVCC, and SD-OCT measurements. For controls, only very typical scans (TSS=100) were accepted. Glaucoma patients were divided into 3 subgroups (very typical: TSS=100; typical: 99>=TSS>=80, atypical: TSS<80). Receiver operating characteristic curves were constructed for mean retinal nerve fiber layer values, sector data, and nerve fiber indicator (NFI). Sensitivity was estimated at >=90% specificity to compare the discriminating ability of each imaging modality.: For discrimination between healthy and glaucomatous eyes with very typical scans, the NFI and inferior sector analyses 26 to 27 demonstrated the highest sensitivity at >=90% specificity in GDxVCC and SD-OCT, respectively. For the typical and atypical groups, sensitivity at >>=90% specificity decreased for all 32 peripapillary sectors on an average by 10.9% and 17.9% for GDxVCC and by 4.9% and 0.8% for SD-OCT. For GDxVCC, diagnostic performance of peripapillary sectors decreased with lower TSS, especially in temporosuperior and inferotemporal sectors (sensitivity at >=90% specificity decreased by 55.3% and by 37.8% in the atypical group).: Diagnostic accuracy is comparable for SD-OCT and GDxVCC if typical scans (TSS=100) are investigated. Decreasing TSS is associated with a decrease in diagnostic accuracy for discriminating healthy and glaucomatous eyes by scanning laser polarimetry. NFI is less influenced than the global or sector retinal nerve fiber layer thickness. The TSS score should be included in the standard printout. Diagnostic accuracy of SD-OCT is barely influenced by low TSS.
EVALuna2:21037

Glaucoma risk index: Automated glaucoma detection from color fundus images - Bock, Rüdiger; Meier, Jörg; Nyul, Laszlo G.; Hornegger, Joachim; Michelson, Georg (Medical Image Analysis, 2010)
Glaucoma as a neurodegeneration of the optic nerve is one of the most common causes of blindness. Because revitalization of the degenerated nerve fibers of the optic nerve is impossible early detection of the disease is essential. This can be supported by a robust and automated mass-screening. We propose a novel automated glaucoma detection system that operates on inexpensive to acquire and widely used digital color fundus images. After a glaucoma specific preprocessing, different generic feature types are compressed by an appearance-based dimension reduction technique. Subsequently, a probabilistic two-stage classification scheme combines these features types to extract the novel Glaucoma Risk Index (GRI) that shows a reasonable glaucoma detection performance. On a sample set of 575 fundus images a classification accuracy of 80% has been achieved in a 5-fold cross-validation setup. The GRI gains a competitive area under ROC (AUC) of 88% compared to the established topography-based glaucoma probability score of scanning laser tomography with AUC of 87%. The proposed color fundus image-based GRI achieves a competitive and reliable detection performance on a low-priced modality by the statistical analysis of entire images of the optic nerve head. © 2009 Elsevier B.V.

Glaucoma-TrEl: A web-based interactive database to build evidence-based hypotheses on the role of trace elements in glaucoma - Choudhari, Jyoti Kant; Eberhardt, Martin; Chatterjee, Tanushree; Hohberger, Bettina; Vera, Julio (BMC Research Notes, 2022)
Objective: Glaucoma is a chronic neurological disease that is associated with high intraocular pressure (IOP), causes gradual damage to retinal ganglion cells, and often culminates in vision loss. Recent research suggests that glaucoma is a complex multifactorial disease in which multiple interlinked genes and pathways play a role during onset and development. Also, differential availability of trace elements seems to play a role in glaucoma pathophysiology, although their mechanism of action is unknown. The aim of this work is to disseminate a web-based repository on interactions between trace elements and protein-coding genes linked to glaucoma pathophysiology. Results: In this study, we present Glaucoma-TrEl, a web database containing information about interactions between trace elements and protein-coding genes that are linked to glaucoma. In the database, we include interactions between 437 unique genes and eight trace elements. Our analysis found a large number of interactions between trace elements and protein-coding genes mutated or linked to the pathophysiology of glaucoma. We associated genes interacting with multiple trace elements to pathways known to play a role in glaucoma. The web-based platform provides an easy-to-use and interactive tool, which serves as an information hub facilitating future research work on trace elements in glaucoma.
CRIS-Team Scopus Importer:2022-12-02
Keywords: glaucoma; Intraocular pressure; Optic nerve; Oxidative stress; Protein-trace element interactions

Global Consensus on Definition, Classification, Diagnosis, and Staging of Limbal Stem Cell Deficiency - Deng, Sophie X.; Borderie, Vincent; Chan, Clara C.; Dana, Reza; Figueiredo, Francisco C.; Gomes, Jose A. P.; Pellegrini, Graziella; Shimmura, Shigeto; Kruse, Friedrich; Cursiefen, Claus; Daya, Sheraz; Djalilian, Ali; et al. (Cornea, 2019)
Purpose: Despite extensive knowledge gained over the last 3 decades regarding limbal stem cell deficiency (LSCD), the disease is not clearly defined, and there is lack of agreement on the diagnostic criteria, staging, and classification system among treating physicians and research scientists working on this field. There is therefore an unmet need to obtain global consensus on the definition, classification, diagnosis, and staging of LSCD.
CRIS-Team WoS Importer:2019-05-03

Global Consensus on the Management of Limbal Stem Cell Deficiency - Deng, Sophie X.; Kruse, Friedrich; Gomes, José A.P.; Chan, Clara C.; Daya, Sheraz; Dana, Reza; Figueiredo, Francisco C.; Kinoshita, Shigeru; Rama, Paolo; Sangwan, Virender; Slomovic, Allan R.; Tan, Donald (Cornea, 2020)
PURPOSE: In recent decades, the medical and surgical treatment of limbal stem cell deficiency (LSCD) has evolved significantly through the incorporation of innovative pharmacological strategies, surgical techniques, bioengineering, and cell therapy. With such a wide variety of options, there is a need to establish a global consensus on the preferred approaches for the medical and surgical treatment of LSCD. METHODS: An international LSCD Working Group was established by the Cornea Society in 2012 and divided into subcommittees. Four face-to-face meetings, frequent email discussions, and teleconferences were conducted since then to reach agreement on a strategic plan and methods after a comprehensive literature search. A writing group drafted the current study. RESULTS: A consensus in the medical and surgical management of LSCD was reached by the Working Group. Optimization of the ocular surface by eyelid and conjunctival reconstruction, antiinflammatory therapy, dry eye and meibomian gland dysfunction treatment, minimization of ocular surface toxicity from medications, topical medications that promote epithelialization, and use of a scleral lens is considered essential before surgical treatment of LSCD. Depending on the laterality, cause, and stage of LSCD, surgical strategies including conjunctival epitheliectomy, amniotic membrane transplantation, transplantation of limbal stem cells using different techniques and sources (allogeneic vs. autologous vs. ex vivo-cultivated), transplantation of oral mucosal epithelium, and keratoprosthesis can be performed as treatment. A stepwise flowchart for use in treatment decision-making was established. CONCLUSIONS: This global consensus provides an up-to-date and comprehensive framework for the management of LSCD.
CRIS-Team Scopus Importer:2020-09-18

Graft adhesion in descemet membrane endothelial keratoplasty dependent on size of removal of host's descemet membrane - Tourtas, Theofilos; Schlomberg, Juliane; Wessel, Julia M.; Bachmann, Bjoern O.; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich (JAMA Ophthalmology, 2014)
It is essential to devise strategies that improve graft adhesion after Descemet membrane endothelial keratoplasty (DMEK) to reduce the rebubbling rate.To evaluate the influence of the extent of descemetorhexis on graft adhesion properties after DMEK.Single-surgeon, retrospective, observational case series conducted in the Department of Ophthalmology, University of Erlangen-Nuremberg, Germany, that reviewed the medical records of 200 consecutive patients undergoing DMEK. Fifty-three eyes of 51 patients undergoing DMEK for Fuchs endothelial dystrophy fulfilling the inclusion criteria were enrolled in this study. Based on intraoperative drawings, postoperative slitlamp examination, and photographs, eyes were divided into 2 groups. The diameter of the descemetorhexis was approximately 10 mm in group A (30 eyes), resulting in a peripheral 1-mm zone of denuded stroma between the graft and the host's Descemet membrane, and approximately 6 mm in group B (23 eyes), resulting in a peripheral 1-mm zone of overlapping between the graft and the host's Descemet membrane.Graft detachment rate, extent of graft detachment (in clock hours of graft's circumference), and rebubbling rate.Four days after DMEK, the graft detachment rate was 33.3% (10 of 30) in group A and 78.3% (18 of 23) in group B (P = .002). The mean (SD) extent of graft detachment was 0.6 (0.9) and 2.8 (2.5) clock hours in groups A and B, respectively (P < .001), 4 days after surgery. The rebubbling rate was 6.7% (2 of 30) and 30.4% (7 of 23) for groups A and B, respectively (P = .03).A larger descemetorhexis in DMEK is correlated with better graft adhesion and lower rebubbling rates. Therefore, patients with a larger descemetorhexis require less intensive follow-up.
EVALuna2:21202

Guest Editorial: Proceedings of the 20th Biennial Symposium of the International Colour Vision Society July 2009, Braga, Portugal - Buck, Steven; Barbur, John; Kremers, Jan; Nascimento, Sergio; Smithson, Hannah (20th Biennial Symposium of the International Colour Vision Society, 2010)

Haemoglobin and vascular function in the human retinal vascular bed - Ritt, Martin; Harazny, Joanna M.; Schmidt, Stefan; Raff, Ulrike; Ott, Christian; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2013)
: Haemoglobin is a potential nitric oxide (NO) scavenger. Haemoglobin is associated with blood viscosity and the red blood cell free layer width of microvessels that impact on shear stress in the microcirculation. We hypothesized that haemoglobin modulates retinal vascular function.: In 139 nondiabetic male patients with haemoglobin levels within the normal range, the vasodilatatory response of retinal capillary blood flow (RCF) to flicker light exposure and the vasoconstrictor response of RCF to infusion of NO synthase inhibitor N-monomethyl-L-arginine (L-NMMA) were assessed. The latter, because of the selective nature of L-NMMA, reflects a parameter of basal NO activity of retinal vasculature. Examinations of retinal parameters were performed noninvasively and in vivo using scanning laser Doppler flowmetry.: Patients with haemoglobin greater or equal the median revealed reduced increase of RCF to flicker light exposure (2.83 ± 12 vs. 9.52 ± 14 (%), P adjusted = 0.002), and greater decrease of RCF to L-NMMA infusion (-7.35 ± 13 vs. -0.92 ± 14 (%), P adjusted = 0.008), compared with patients with haemoglobin below the median. Haemoglobin was negatively related to the percentage change of RCF to flicker light exposure (r = -0.249, P = 0.004) and to L-NMMA infusion (r = -0.201, P = 0.018). In multiple linear regression analysis haemoglobin was an independent determinant of the percentage change of RCF to flicker light exposure (model 1: ß = -0.278, P = 0.003 and model 2: ß = -0.283, P = 0.002) and to L-NMMA infusion (model 1: ß = -0.256, P = 0.005 and model 2: ß = -0.269, P = 0.004).: Haemoglobin emerged as an independent determinant of vascular function in the human retinal vascular bed.
EVALuna2:3613

Hair Follicle Stem Cell Isolation and Expansion - Call, Mindy; Meyer, Ewa Anna; Kao, Winston W.; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Bio-protocol, 2018)
Stem cells are widely used for numerous clinical applications including limbal stem cell deficiency. Stem cell derived from the bulge region of the hair follicle have the ability to differentiate into a variety of cell types including interfollicular epidermis, hair follicle structures, sebaceous glands and corneal epithelial cells when provided the appropriate cues. Hair follicle stem cells are being studied as a valuable source of autologous stem cells to treat disease. The protocol described below details the isolation and expansion of these cells for eventual clinical application. We used a dual-reporter mouse model to visualize both isolation and eventual differentiation of these cells in a limbal stem cell-deficient mouse model.
CRIS-Team WoS Importer:2019-02-21

Heart rate and age modulate retinal pulsatile patterns - Labounkova, Ivana; Labounek, Rene; Kolar, Radim; Tornow, Ralf-Peter; Babbs, Charles F.; Mcclelland, Collin M.; Miller, Benjamin R.; Nestrasil, Igor (Communications Biology, 2022)
Video-recordings of retinal pulsatile patterns in human eye are modulated by heart rate and age. This invivo evidence fundamentally impacts modeling of retinal function and clinical design in wide range of medical specialties.
CRIS-Team WoS Importer:2022-07-01

Hess Screen Revised: How Eye Tracking and Virtual Reality change Strabismus Assessment - Mehringer, Wolfgang; Wirth, Markus; Risch, Franka; Roth, Daniel; Michelson, Georg; Michelson, Georg; Eskofier, Björn (2021 43rd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2021)
Strabismus is a visual disorder characterized by eye misalignment. The extent of ocular misalignment is denoted as the deviation angle. With the advent of Virtual Reality (VR) Head-Mounted-Displays (HMD) and eye tracking technology, new possibilities measuring strabismus arise. Major research addresses the novel field of VR strabismus assessment by replicating prism cover tests while there is a paucity of research on screen tests. In this work the Hess Screen Test was implemented in VR using a HMD with eye tracking for an objective measurement of the deviation angle. In a study, the functionality was tested and compared with a 2D monitor-based test. The results showed significant differences in the measured deviation angle between the methods. This can be attributed to the type of dissociation of the eyes.<br
Keywords: Visualization; Measurement errors; Measurement uncertainty; Gaze tracking; Virtual reality; Resists; Ophthalmology

Heterochromatic flicker electroretinograms reflecting luminance and cone opponent activity in glaucoma patients - Salgueiro Barboni, Mirella Telles; Pangeni, Gobinda; Ventura, Dora Fix; Horn, Folkert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2011)
To measure heterochromatic flicker electroretinograms (ERGs) at high (36 Hz) and intermediate (12 Hz) temporal frequencies to evaluate luminance and cone opponent responses, respectively, in glaucoma eyes with (perimetric) and without (preperimetric) visual field defects.Flicker ERGs were recorded from one randomly chosen dilated eye of 32 patients (mean age, 61 ± 11 years; 15 men, 17 women) from the Erlangen Glaucoma Registry and from 24 healthy volunteers (mean age, 43 ± 11 years; 14 men, 10 women). Red and green light-emitting diodes in a Ganzfeld stimulator were sine wave-modulated in counterphase. The responses were measured at 36 Hz, the frequency at which ERGs reflect activity of the luminance pathway, and at 12 Hz, the frequency at which ERGs reflect chromatic activity.Response amplitudes were similar in glaucoma patients and controls. Phase differences were observed in patients with visual field defects (perimetric) compared with the control group at 36 and 12 Hz in the first harmonic and second harmonic responses. Patients without visual field defects (preperimetric) showed phase differences for the second harmonic component at 36 Hz. No age effect on response amplitudes and phases was found in any of the subject groups (controls and patients).The responses displayed phase differences but not amplitude differences in perimetric glaucoma patients at both 36 and 12 Hz, suggesting that both magnocellular and parvocellular pathways are affected. Preperimetric glaucoma patients also showed phase differences. The response phase may be sensitive to early dysfunction of the inner retina. (ClinicalTrials.gov number, NCT00494923).
EVALuna2:21030

Heterochromatic Modulation Photometry can be used to measure Macular Pigment Optical Density - Huchzermeyer, Cord; Schlomberg, Juliane; Welge-Luessen, Ulrich; Berendschot, Tos T. J. M.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 587 macular pigment; 468 clinical research methodology; 478 contrast sensitivity

Heterogeneous presynaptic distribution of munc13 isoforms at retinal synapses and identification of an unconventional bipolar cell type with dual expression of munc13 isoforms: A study using munc13-exfp knock-in mice - Gierke, Kaspar; von Wittgenstein, Julia; Hemmerlein, Maike; Atorf, Jenny; Joachimsthaler, Anneka; Kremers, Jan; Cooper, Benjamin H.; Varoqueaux, Frederique; Regus-Leidig, Hanna; Brandstätter, Johann Helmut (International Journal of Molecular Sciences, 2020)
Munc13 isoforms are constituents of the presynaptic compartment of chemical synapses, where they govern important steps in preparing synaptic vesicles for exocytosis. The role of Munc13-1,-2 and-3 is well documented in brain neurons, but less is known about their function and distribution among the neurons of the retina and their conventional and ribbon-type chemical synapses. Here, we examined the retinae of Munc13-1-,-2-, and-3-EXFP knock-in (KI) mice with a combination of immunocytochemistry, physiology, and electron microscopy. We show that knock-in of Munc13-EXFP fusion proteins did not affect overall retinal anatomy or synapse structure, but slightly affected synaptic transmission. By labeling Munc13-EXFP KI retinae with specific antibodies against Munc13-1,-2 and-3, we found that unlike in the brain, most retinal synapses seem to operate with a single Munc13 isoform. A surprising exception to this rule was type 6 ON bipolar cells, which expressed two Munc13 isoforms in their synaptic terminals, ubMunc13-2 and Munc13-3. The results of this study provide an important basis for future studies on the contribution of Munc13 isoforms in visual signal processing in the mammalian retina.
CRIS-Team Scopus Importer:2020-11-06
Keywords: BrMunc13-2; Conventional synapse; Munc13-1; Munc13-3; Retina; Ribbon synapse; Type 6 ON bipolar cell; UbMunc13-2

High-frequency characteristics of L- and M-cone driven electroretinograms - Aher, Avinash; Jacob, Mellina M.; Kremers, Jan (Vision research, 2019)
Electroretinograms (ERGs) elicited by high temporal frequency (26–95 Hz) L- and M-cone isolating sine-wave stimuli were investigated in human observers for full-field (FF) and different spatially restricted stimulus sizes (70°, 50°, 30°, and 10° diameter). Responses to L- and M-cone isolating FF stimuli were maximal around 48 Hz and decreased gradually with increasing temporal frequency up to 95 Hz. The response maximum was shifted to about 30–32 Hz for both L- and M-cone driven responses obtained with spatially restricted stimuli. The M-cone driven responses could only be measured up to 54 Hz with 70° stimuli. The response amplitudes for L- and M-cones and L-/M-cone amplitude ratios decreased with decreasing stimulus size. The ERG response phases to L- and M-cone isolating stimuli decreased with increasing temporal frequency and were about −160° apart for all stimulus sizes up to 34 Hz. Further increase in the temporal frequency displayed a positive correlation between stimulus size and L-M phase difference. The ERG data indicate that the responses evoked by high temporal frequency cone isolating stimuli reflect two mechanisms, one that is more centrally located and displays a maximum at about 30–32 Hz and a peripheral mechanism that is sensitive to higher temporal modulations. We propose that the peripheral mechanism (FF ERGs) reflects magnocellular activity, whereas the central mechanism (ERGs with spatially restricted stimuli) is based on a parvocellular activity up to about 30 Hz.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Electroretinograms; Magnocellular; Parvocellular; Stimulus size; Temporal frequency

Histological and biochemical findings in membranous cataract - Gatzioufas, Zisis; Huchzermeyer, Cord; Hasenfus, Andrea; El-Husseiny, Moatasem; Seitz, Berthold (Ophthalmic Research, 2012)
In this report we present a patient with unilateral membranous cataract and describe the histological and biochemical findings accompanying this rare condition.The patient underwent an uneventful cataract extraction. Aqueous humor (20 ?l) was aspirated from the anterior chamber intraoperatively and processed for fibroblast growth factor (FGF) and epidermal growth factor (EGF) using an immunoassay method (ELISA). The lens material was subjected to histological examination.The patient had increased levels of FGF and EGF in the aqueous humor, as measured by ELISA. Histological examination of the lens material showed a marked fibrous metaplasia and thickening of the anterior lens capsule, while the lens epithelial cells were transformed to active myofibroblasts which generated a fibrous matrix of collagen lamellae. Unfortunately, visual function was not restored postoperatively due to underlying amblyopia.Our histological and biochemical findings suggest that FGF and EGF may play a key role in the formation of membranous cataract, and therefore their impact on lens physiology should be further investigated.
EVALuna2:21058

Histological aspects of limbal stem cell transplantation - Gießl, Andreas (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Histologic differences between primary high myopia and secondary high myopia due to congenital glaucoma - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2016)
To search for histomorphometric differences between eyes with primary high myopia (PHM) or secondary high axial myopia (SHM) caused by congenital glaucoma, and non-highly myopic eyes (NHM).Histologic anterior-posterior sections were histomorphometrically examined.The investigation included 58 human globes (mean age: 61.5 ± 18.5 years; axial length: 27.3 ± 4.0 mm; range: 21.0-39.0 mm). Bruch's membrane thickness was thinner in SHM than in PHM (posterior pole: p = 0.007; parapapillary region: p = 0.007); midpoint posterior pole/equator = 0.05) and thinner in SHM than in NHM (all p < 0.04), while PHM and NHM did not differ (all p > 0.50). Choroidal thickness did not differ (all p >= 0.40) at any measurement location between SHM and PHM, and was thinner (p < 0.05) in both myopic groups than in NHM. Posterior sclera was thinner (p < 0.001) in both myopic groups than in NHM, with no significant difference between both myopic groups. Pars plana scleral thickness was thinner (p = 0.02) in SHM than in PHM after adjusting for axial length. Scleral volume (p = 0.41) and choroidal volume (p = 0.74) did not differ between any of the groups.Thinning of Bruch's membrane overall is typical for SHM while eyes with PHM have a normal Bruch's membrane thickness. It may point to Bruch's membrane as an active part in the process of emmetropization/myopization. SHM in contrast to PHM showed scleral thinning in the pars plana region suggesting that the process of emmetropization/myopization takes place posterior to the pars plana. Both SHM and PHM unspecifically showed an axial length associated with thinning of choroid and posterior sclera, while both myopic groups did not differ with NHM in choroidal and scleral volume.
EVALuna2:21289

Histology of myopic posterior scleral staphylomas - Jonas, Jost B.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2020)
Purpose: Since histomorphometric descriptions of posterior scleral staphylomas, although forming a major part of myopic maculopathy, have been scarce so far, we histomorphometrically examined scleral staphylomas in enucleated human eyes. Methods: Using light microscopy, we histomorphometrically examined sagittal histological sections of human globes enucleated due to malignant choroidal melanomas or secondary angle-closure glaucoma. Results: Out of 246 globes included into the study, posterior scleral staphylomas were detected in 10 eyes (mean length: 31.4 ± 3.0 mm; range: 28.0–37.0 mm). In the staphylomatous region in the study group as compared with the corresponding region of a control group adjusted for age and axial length, scleral thickness was significantly lower (109 ± 25 µm versus 319 ± 161 µm; p = 0.001). The study group in the staphylomatous region as compared to the highly myopic control group in the corresponding region did not differ significantly in retinal pigment epithelium (RPE) cell density (19.6 ± 4.9 cells/300 µm versus 21.1 ± 5.7 cells/300 µm; p = 0.84) and RPE height (8.2 ± 2.8 µm versus 6.1 ± 2.5 µm; p = 0.13), Bruch’s membrane (BM) thickness (3.5 ± 1.3 µm versus 4.2 ± 2.3 µm; p = 0.40) and choriocapillaris thickness (5.3 ± 2.8 µm versus 4.4 ± 2.8 µm; p = 0.49) and density (164 ± 99 µm versus 226 ± 38 µm; p = 0.13). All staphylomatous regions showed a localized BM defect. Conclusions: Marked scleral thinning and spatially correlated BM defects histologically characterized myopic scleral staphylomas, while thickness and density of the choriocapillaris and RPE and BM thickness did not differ significantly between staphylomatous versus non-staphylomatous eyes in the respective regions. These findings support the notion that a locally reduced scleral resistance against a backward pushing BM led to a local scleral outpouching. The outpouching-associated increase in curvature length may stretch BM with the sequel of a localized BM rupture.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Bruch’s membrane; choriocapillaris; myopia; myopic maculopathy; scleral staphyloma

Histology of myopic posterior scleral staphylomas - Jonas, Jost; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Histology of myopic scleral staphylomas - Jonas, Jost B.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Histology of the parapapillary region in high myopia - Jonas, Jost B.; Jonas, Shefali B.; Jonas, Rahul A.; Holbach, Leonard; Panda-Jonas, Songhomitra (American Journal of Ophthalmology, 2011)
To examine histomorphometrically the parapapillary region in highly myopic eyes.Retrospective laboratory investigation.We examined a highly myopic glaucomatous group (36 human globes; axial length >26.5 mm) and a non-highly myopic group (28 globes with secondary angle-closure glaucoma; 17 eyes with malignant choroidal melanoma). Using light microscopy, pupil-optic nerve sections were assessed.The length of the scleral flange (sclera between optic nerve border and optic nerve dura mater) increased with axial length (P < .001; correlation coefficient r = 0.70) and decreased with its thickness (P < .001; r = 0.75). In all highly myopic eyes (n = 15) with a distance of >0.5 mm between optic nerve border and beginning of Bruch membrane, the parapapillary region consisted of an elongated parapapillary scleral flange associated with a scleral flange thinning and a retrobulbar cerebrospinal fluid space extended into the retroparapapillary region. The parapapillary retina was composed of retinal nerve fiber layer (or its remnants) only, without elements of any other retinal layer, without underlying Bruch membrane or choroid. These histologic features were not detected in any of the non-highly myopic eyes.Since parapapillary scleral thickness influences the lamina cribrosa biomechanics, the findings may partially explain the increased glaucoma susceptibility in highly myopic eyes. The implications of an absence of Bruch membrane and choroid in the highly myopic parapapillary region, and the implications of the retrobulbar parapapillary extension of the cerebrospinal spinal fluid space for the pathophysiology of the optic nerve head, have to be elucidated.
EVALuna2:21032

Histopathological changes after deep anterior lamellar keratoplasty using the 'big-bubble technique' - Braun, Joachim M.; Hofmann-Rummelt, Carmen; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Cursiefen, Claus (Acta Ophthalmologica, 2013)
Purpose: During deep anterior lamellar keratoplasty (DALK), endothelium and Descemet's membrane are separated from the corneal stroma by intrastromal air injection ('big-bubble technique'). The aim of our study is to analyse histopathological changes in host corneal tissue caused by air insufflation in patients with keratoconus, their variability in 10 patients and their possible clinical implication. Methods: The excised anterior corneal lamellae of 10 patients with keratoconus having undergone DALK using the 'big-bubble technique' were analysed by light and transmission electron microscopy as well as immunohistochemistry. In addition, intrastromal air accumulations were quantified morphometrically. Results: Intrastromal air was detected in all examined excised lamellae (8% of stromal volume), but with large variability (SD 8.8). It was detected preferentially in the inner layer of the corneal stroma and represented there up to 39% of the stromal volume. In addition, the air was predominantly located at one periphery of the excised lamellae. Intrastromal air bubbles were larger in the inner than in the superficial stromal layer and characterized by round shape and a CD68-negative collagenous 'pseudocapsule'. We detected no air-injection-induced alterations in Bowman's layer and epithelium. Conclusion: Our results show that 'big-bubble DALK' causes significant intrastromal air accumulations in the cornea. Pathologists should be conscious of this phenomenon and the high topographic variability. Intrastromal air in the recipient rim may be accompanied by a decrease in mechanical stability and could contribute to postoperative suture loosening.
EVALuna2:21044

Histopathologic findings in early encapsulated blebs of young patients treated with the ahmed glaucoma valve - Thieme, Hagen; Choritz, Lars; Hofmann-Rummelt, Carmen; Schlötzer-Schrehardt, Ursula; Kottler, Ulrike B. (Journal of Glaucoma, 2011)
Uncontrolled glaucoma presents a challenge for the ophthalmic surgeon especially in children and juvenile patients. For many patients who have undergone failed surgical procedures before, episcleral implants remain the last choice. Encapsulated blebs forming over antiglaucoma devices present a complication leading to malfunctioning or even failure with reincrease in intraocular pressure. We report our histopathologic findings of such blebs developing around the Ahmed glaucoma valve (AGV) after a short time period in young patients.Nine young patients (2 to 17 y of age) with otherwise uncontrollable glaucoma were treated with AGV (models FP-7 and FP-8, silicone base plate) by 1 surgeon (H.T.). Four eyes needed surgical revision 2 to 6 months after initial implantation owing to encapsulated bleb development over the valve with total loss of function. The dense capsule around the device was surgically removed and investigated macroscopically, microscopically, and ultrastructurally.The cystic wall of these encapsulated blebs had an overall thickness of 1.5 to 2 mm. Macroscopically, the tissue was split into 2 layers. Histopathologically, the smooth inner surface (facing the base plate of the AGV) consisted of compressed collagen fibers with signs of elastoid degeneration and with formation of a pseudoendothelium toward the base plate. There was a pronounced transformation of fibroblasts into myofibroblasts in this inner layer. The outer area was highly vascularized. In these vessels electron microscopy revealed thrombosis. Inflammatory responses were nearly absent in all areas of the excised material. Intraocular pressure could be controlled by removal of the encapsulated blebs in all 4 cases.Encapsulation of the AGV is an early complication in young patients, leading to inhibition of fluid exchange and failure of the procedure. The valve mechanism is blocked by contracted scar tissue, but the device itself is not affected by the encapsulation. Surgical excision of the capsule immediately leads to an aqueous flow and drop of intraocular pressure.
EVALuna2:21048

How the use of dim red-light pre-recording affects ERG responses of mice with long-wavelength shifted opsin - Joachimsthaler, Anneka; Stallwitz, Nina; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Human anterior lens capsule serving as a substrate for human trabecular meshwork cells cultivation - Kopsachilis, Nikolaos; Tsaousis, Konstantinos; Tsinopoulos, Ioannis T.; Kruse, Friedrich; Welge-Luessen, Ulrich (Cell and Tissue Banking, 2013)
To investigate if human anterior lens capsule is a suitable substrate for the culture of primary human trabecular meshwork (HTM) cells. Trabecular meshwork cells derived from four human donors were seeded on anterior lens capsules that were prepared from the lenses of donor eyes. Cell morphology and viability were examined at 1, 3, 5 and 7 days. Cell viability was measured based on a two-colour fluorescence assay (membrane-impermeable propidium iodide and membrane permeable Hoechst 33342). Immunocytochemistry studied Zonula occludens-1 (ZO-1), vimentin, tissue transglutaminase (tTgase) and Na(+)/K(+)-adenosine triphosphatase (Na(+)/K(+)-ATPase). Morphology of the cultivated cells followed a typical model while their viability was > 95% in all cases. ZO-1 was found at the cell boundaries of the HTM-AC complex. Vimentin was located at the lateral membranes of the HTM cells. Na(+)/K(+)-ATPase was found at the basolateral membrane of the HTM cells. tTgase was also identified. Anterior lens capsule can be considered as a suitable alternative substrate for cultivation of HTM cells and assist the expansion of existing knowledge about glaucoma pathophysiology and therapy.
EVALuna2:21102

Human flicker electroretinography using different temporal modulations at mesopic and photopic luminance levels - Nagy, Balazs Vince; Salgueiro Barboni, Mirella Telles; Gomes Martins, Cristiane Maria; Da Costa, Marcelo Fernandes; Kremers, Jan; Ventura, Dora Fix (Documenta Ophthalmologica, 2014)
Electroretinographic measurement instruments allow the variation of several stimulation parameters enabling to study a wide range of retinal processes. The purpose of the present study was to measure human flicker electroretinograms (ERGs) varying temporal modulation, temporal frequency and mean luminance in the photopic and higher mesopic ranges where the change from cone to rod dominance occurs.Fourteen healthy subjects (mean age = 31 ± 6) participated in this study. ERG recordings were performed with the RetiPort system (Roland Consult, Germany). The stimuli were ON and OFF sawtooth waves, square wave and sine wave. The temporal frequencies were 4 and 8 Hz. The mean luminance varied from 1 to 60 cd/m(2).The results confirmed the possibility to distinguish between rod- and cone-dominated retinal responses when using the flicker ERG at different temporal frequencies and luminances. We have also evaluated the responses at luminance levels at which the transition between rod- and cone-dominated responses occurs. This transition between rod- and cone-dominated flicker ERG responses is indicated by a significant change in the response characteristics between 4 and 8 cd/m(2) (between 200 and 400 phot Td).The findings on the transition between rod- and cone-dominated ERGs along with the demonstration of ERG responses to different temporal flicker modulations might be informative for the electrophysiologists when setting up the stimulus at mesopic and photopic luminance levels.
EVALuna2:21188

Human photopic ON-and OFF-ERG responses elicited by square wave and sawtooth stimuli - Pangeni, Gobinda; Kremers, Jan (Psychology & Neuroscience, 2013)
Keywords: Electroretinogram; Contrast; Square wave stimuli; Sawtooth stimuli; Temporal frequency

Human S-Cone Electroretinograms Obtained by Silent Substitution Stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (i-Perception, 2018)

Human S-cone electroretinograms obtained by silent substitution stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
We used triple silent substitution stimuli to characterize human S-cone electroretinograms (ERGs) in normal trichromats. Short-wavelength-cone (S-cone) ERGs were found to have different morphological features and temporal frequency response characteristics compared to ERGs derived from L-cones, M-cones, and rod photoreceptors in normal participants. Furthermore, in two cases of retinal pathology, blue cone monochromatism (BCM) and enhanced S-cone syndrome (ESCS), S-cone ERGs elicited by our stimuli were preserved and enhanced, respectively. The results from both normal and pathological retinae demonstrate that triple silent substitution stimuli can be used to generate ERGs that provide an assay of human S-cone function. (c) 2018 Optical Society of America

ICare Pro: Age Dependent Effect of Central Corneal Thickness on Intraocular Pressure in Glaucoma and Ocular Hypertension Patients - Hohberger, Bettina; Sommerfeld, Carlos; Lucio, Marianna; Bergua, Antonio (Current Eye Research, 2020)
Purpose: Measurement of the exact intraocular pressure (IOP) is essential in glaucoma diagnosis and follow-up, thus all therapeutic options affect IOP in order to win sighted lifetime. As it is known that corneal properties of glaucoma patients differ from normal subjects, the present study aimed to investigate the influence of CCT on rebound tonometry (ICT, ICare Pro) in glaucoma and ocular hypertension patients in dependency of age additionally considering different times of day. Methods: Three hundred sixty-two eyes of 190 subjects were included: 339 open-angle glaucoma and 23 ocular hypertension. IOP was measured at 5 different times of day (6 a.m., 12 a.m., 4 p.m., 9 p.m., and 0 p.m.) by Goldmann applanation tonometry (GAT) and Icare Pro rebound tonometry in a sitting position. Central corneal thickness was measured by central ultrasonic pachymetry (Pachymeter SP-100). Delta ICT was calculated as the difference of GAT, corrected according to age and CCT, and ICT, respectively at each time point. Results: All different GAT time points data correlated significantly (p < .05) with ICT time points. An age effect was observed on overall ICT (p = .02). A decrease of ICT was observed with increasing age. The within differences among ICT repeated measurements were significant as well. Additionally, repeated means of Delta ICT correlated significantly with age and CCT. Intercepts and coefficients were offered for each time point, respectively. GLM model yielded a relation between MD (dependent variable) and age together with CCT (age: p < .0001) and (CCT: p = .043). Conclusions: IOP measurements with ICare Pro were shown to be dependent on age, CCT and time of day in glaucoma and ocular hypertension patients. Thus, aging, corneal biomechanical properties and circadian rhythms should be taken into consideration when adjusting IOP.
CRIS-Team WoS Importer:2020-01-17

Identification and immunocytochemical characterization of Piccolino, a novel Piccolo splice variant selectively expressed at sensory ribbon synapses of the eye and ear - Regus-Leidig, Hanna; Ott, Corinna; Löhner, Martina; Atorf, Jenny; Fuchs, Michaela; Sedmak, Tina; Kremers, Jan; Fejtova, Anna; Gundelfinger, Eckart D.; Brandstätter, Johann Helmut (PLoS ONE, 2013)
Piccolo is one of the largest cytomatrix proteins present at active zones of chemical synapses, where it is suggested to play a role in recruiting and integrating molecules relevant for both synaptic vesicle exo- and endocytosis. Here we examined the retina of a Piccolo-mutant mouse with a targeted deletion of exon 14 in the Pclo gene. Piccolo deficiency resulted in its profound loss at conventional chemical amacrine cell synapses but retinal ribbon synapses were structurally and functionally unaffected. This led to the identification of a shorter, ribbon-specific Piccolo variant, Piccolino, present in retinal photoreceptor cells, bipolar cells, as well as in inner hair cells of the inner ear. By RT-PCR analysis and the generation of a Piccolino-specific antibody we show that non-splicing of intron 5/6 leads to premature translation termination and generation of the C-terminally truncated protein specifically expressed at active zones of ribbon synapse containing cell types. With in situ proximity ligation assays we provide evidence that this truncation leads to the absence of interaction sites for Bassoon, Munc13, and presumably also ELKS/CAST, RIM2, and the L-type Ca(2) (+) channel which exist in the full-length Piccolo at active zones of conventional chemical synapses. The putative lack of interactions with proteins of the active zone suggests a function of Piccolino at ribbon synapses of sensory neurons different from Piccolo's function at conventional chemical synapses.
EVALuna2:21139

Identification, Isolation, and Characterization of Melanocyte Precursor Cells in the Human Limbal Stroma - Li, Shen; Zenkel, Matthias; Kruse, Friedrich; Gießl, Andreas; Schlötzer-Schrehardt, Ursula (International Journal of Molecular Sciences, 2022)
Given their vital role in the homeostasis of the limbal stem cell niche, limbal melanocytes have emerged as promising candidates for tissue engineering applications. This study aimed to isolate and characterize a population of melanocyte precursors in the limbal stroma, compared with melanocytes originating from the limbal epithelium, using magnetic-activated cell sorting (MACS) with positive (CD117/c-Kit microbeads) or negative (CD326/EpCAM or anti-fibroblast microbeads) selection approaches. Both approaches enabled fast and easy isolation and cultivation of pure limbal epithelial and stromal melanocyte populations, which differed in phenotype and gene expression, but exhibited similar functional properties regarding proliferative potential, pigmentation, and support of clonal growth of limbal epithelial stem/progenitor cells (LEPCs). In both melanocyte populations, limbus-specific matrix (laminin 511-E8) and soluble factors (LEPC-derived conditioned medium) stimulated melanocyte adhesion, dendrite formation, melanogenesis, and expression of genes involved in UV protection and immune regulation. The findings provided not only a novel protocol for the enrichment of pure melanocyte populations from limbal tissue applying easy-to-use MACS technology, but also identified a population of stromal melanocyte precursors, which may serve as a reservoir for the replacement of damaged epithelial melanocytes and an alternative resource for tissue engineering applications.
CRIS-Team Scopus Importer:2022-04-15
Keywords: cultivation; laminin 511-E8; limbal stem cell niche; limbal stem cells; limbal stroma; magnetic-activated cell sorting; melanocytes

Identification of Process Limits for Electro-Spinning of aligned – Nano Fibres of the CPL/PGS 1: 1 blend - Bischoff, S.; Küng, Florian; Stafiej, Piotr; Fuchsluger, Thomas; Boccaccini, Aldo R.; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Identification of the deregulated NEK1 protein network in skeletal ciliopathies - Vogl, C.; Keßler, Kristin; Gießl, Andreas; Kirchner, P.; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Thiel, C. T. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Identifying Design Principles for the Transmission of Visible Light through Electrospun Nanofibrous PCL Scaffolds for Corneal Tissue Engineering - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (4. Baltic Sea Eye Conference, Rostock (Deutschland), 2022, 2022)

Identifying Genes that Underlie Exfoliation Syndrome using Genetically Determined Gene Expression - Hirbo, Jibril; Pasutto, Francesca; Pawar, Priyanka; Sealock, Julia; Evans, Patrick; Gamazon, Eric; Tao, Ran; Reis, Andre; Berner, Daniel; Schlötzer-Schrehardt, Ursula; Brantley, Milam A.; Khor, Chiea Chuen; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Identifying key parameters for the transmission of visible light through electrospun nanofibrous PCL scaffolds for ophthalmic applications - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (31th Annual Conference of the European Society for Biomaterials, Porto (Portugal), 2021, 2021)

Imaging video plethysmography shows reduced signal amplitude in glaucoma patients in the area of the microvascular tissue of the optic nerve head - Tornow, Ralf-Peter; Kolar, Radim; Odstrcilik, Jan; Labounkova, Ivana; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2020)
Purpose: To measure parameters of the cardiac cycle-induced pulsatile light absorption signal (plethysmography signal) of the optic nerve head (ONH) and to compare parameters between normal subjects and patients with different stages of glaucoma. Patients and methods: A recently developed video ophthalmoscope was used to acquire short video sequences (10 s) of the ONH. After image registration and trend correction, the pulsatile changing light absorption at the ONH tissue (excluding large vessels) was calculated. The changing light absorption depends on the pulsatile changing blood volume. Various parameters, including peak amplitude, steepness, time-to-peak, full width at half maximum (FWHM), and pulse duration, were calculated for averaged individual pulses (heartbeats) of the plethysmography signal. This method was applied to 19 healthy control subjects and 91 subjects with ocular hypertension, as well as different stages of primary open-angle glaucoma (17 subjects with ocular hypertension, 24 with preperimetric glaucoma, and 50 with perimetric glaucoma). Results: Compared to the normal subjects, significant reductions (p < 0.001) in peak amplitude and steepness were observed in the group of perimetric glaucoma patients, but no significant difference was found for time-to-peak, FWHM, and pulse duration. Peak amplitude and steepness showed high correlations with RNFL thickness (p < 0.001). Conclusions: The presented low-cost video-ophthalmoscope permits measurement of the plethysmographic signal of the ONH tissue and calculation of different blood flow-related parameters. The reduced values of the amplitude and steepness parameters in perimetric glaucoma patients suggest decreased ONH perfusion and blood volume. This outcome is in agreement with results from other studies using OCT angiography and laser speckle flowgraphy, which confirm reduced capillary density in these patients. Registration site: www.clinicaltrials.gov, Trial registration number: NCT00494923 [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-10-02
Keywords: Blood flow; Blood volume; Glaucoma; Perfusion; Retinal plethysmography

Immature platelets do not reliably predict platelet recovery in patients with intensive chemotherapy or stem cell transplantation - Meintker, Lisa; Fritsch, Juliana; Ringwald, J.; Krause, Stefan (Vox Sanguinis, 2017)
It has been reported that immature platelets may indicate imminent platelet (PLT) recovery following intensive chemotherapy and/or haematopoietic stem cell transplantation with the perspective to withhold unnecessary transfusions. The objective of our prospective study was to test immature PLTs as measured by two haematology analysers to predict PLT recovery.This study monitored 51 courses of severe thrombocytopenia after chemotherapy in 35 adult haematology/oncology patients starting at a PLT count <70 × 10(9) /l until PLT recovery (>20 × 10(9) /l) or discharge from hospital. Immature platelets as measured by immature platelet fraction (IPF) (Sysmex XE-5000) and retPLT (Abbott CD-Sapphire) as well as reticulocyte and leucocyte count were evaluated regarding their usefulness to predict PLT recovery. Furthermore, the influence of platelet concentrate (PC) transfusions upon IPF and retPLT was assessed.With beginning of thrombocytopenia, most patients demonstrated elevated IPF% (median 8·6%) and retPLT% (median 6·8%). These elevated values significantly dropped after transfusions of PCs. IPF and retPLT values during nadir and at imminent PLT recovery were largely overlapping and receiver operating characteristics analysis demonstrated poor separation between both clinical situations. A reasonable cut-off could not be established to prospectively predict imminent PLT recovery for either of the parameters investigated.Measurements of IPF and retPLT lack predictive power regarding imminent PLT recovery in patients with severe thrombocytopenia following intensive chemotherapy. Decisions regarding prophylactic PC transfusions should not be based on these parameters.
EVALuna2:25760

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Patterns of Response and Survival According to the Presence of Hepatic and Extrahepatic Metastasis - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Hohberger, Bettina; Kaehler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; et al. (Cancers, 2021)
Simple Summary This retrospective multicenter study examines the influence of hepatic and extrahepatic metastases on the response of immune checkpoint blockade (ICB) in patients with metastatic uveal melanoma. A better response to dual ICB was observed in the presence of extrahepatic metastases in two recently published phase II trials. Therefore, we investigated two cohorts with and without extrahepatic metastasis and have assembled a population of 178 patients treated with ICB. The survival of this large cohort of patients with advanced UM was more favorable than that reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only. Background: Since there is no standardized and effective treatment for advanced uveal melanoma (UM), the prognosis is dismal once metastases develop. Due to the availability of immune checkpoint blockade (ICB) in the real-world setting, the prognosis of metastatic UM has improved. However, it is unclear how the presence of hepatic and extrahepatic metastasis impacts the response and survival after ICB. Methods: A total of 178 patients with metastatic UM treated with ICB were included in this analysis. Patients were recruited from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of hepatic metastasis, two cohorts were compared: patients with liver metastasis only (cohort A, n = 55) versus those with both liver and extra-hepatic metastasis (cohort B, n = 123). Data were analyzed in both cohorts for response to treatment, progression-free survival (PFS), and overall survival (OS). The survival and progression probabilities were calculated with the Kaplan-Meier method. Log-rank tests, chi(2) tests, and t-tests were performed to detect significant differences between both cohorts. Results: The median OS of the overall population was 16 months (95% CI 13.4-23.7) and the median PFS, 2.8 months (95% CI 2.5-3.0). The median OS was longer in cohort B than in cohort A (18.2 vs. 6.1 months; p = 0.071). The best objective response rate to dual ICB was 13.8% and to anti-PD-1 monotherapy 8.9% in the entire population. Patients with liver metastases only had a lower response to dual ICB, yet without significance (cohort A 8.7% vs. cohort B 16.7%; p = 0.45). Adverse events (AE) occurred in 41.6%. Severe AE were observed in 26.3% and evenly distributed between both cohorts. Conclusion: The survival of this large cohort of patients with advanced UM was more favorable than reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only.
CRIS-Team WoS Importer:2021-07-23

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Re-Induction following Resistance or Toxicity - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; et al. (Cancers, 2022)
Re-induction with immune checkpoint blockade (ICB) needs to be considered in many patients with uveal melanoma (UM) due to limited systemic treatment options. Here, we provide hitherto the first analysis of ICB re-induction in UM. A total of 177 patients with metastatic UM treated with ICB were included from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of ICB re-induction, two cohorts were compared: patients who received at least one ICB re-induction (cohort A, n = 52) versus those who received only one treatment line of ICB (cohort B, n = 125). In cohort A, a transient benefit of overall survival (OS) was observed at 6 and 12 months after the treatment start of ICB. There was no significant difference in OS between both groups (p = 0.1) with a median OS of 16.2 months (cohort A, 95% CI: 11.1–23.8) versus 9.4 months (cohort B, 95% CI: 6.1–14.9). Patients receiving re-induction of ICB (cohort A) had similar response rates compared to those receiving ICB once. Re-induction of ICB may yield a clinical benefit for a small subgroup of patients even after resistance or development of toxicities.
CRIS-Team Scopus Importer:2022-01-28
Keywords: CTLA-4; Immune checkpoint blockade; PD-1; Re-induction; Toxicity; Treatment resistance; Uveal melanoma

Immunofluorescence of intraocular structures combined with the optical clearing method See Deep Brain (SeeDB) - Bergua, Antonio; Baumgart, Carina; Neuhuber, Winfried; Hohberger, Bettina (2018)
EVALuna2:34741

Immunohistochemical detection of urea transporter-A in the tear- producing part of the lacrimal system - Jäger, Franziska; Paulsen, Friedrich; Bergua, Antonio; Jungbauer, Rebecca; Hammer, Christian (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Objective: Urea constitutes a physiological and presumably well-regulated constituent of tear fluid. Its la-crimal concentration is significantly decreased in dry eye disease. Urea homeostasis within the tear fluid may also depend on the expression of urea transporters. The present study reports on the expression patterns of urea transporter A (UT-A) in the cells and tissues of the ocular surface and the lacrimal glands. Methods: UT-A immunohistochemistry was performed on 5 mu m paraffin sections of paraformaldehyde-fixed human, porcine, and murine corneas, eyelids, and lacrimal glands (n = 5 each). Results: UT-A immunostaining was largely comparable in all three species. UT-A signals were detected in the corneal epithelium and endothelium, in the conjunctival epithelium, in the acinar cells and excretory ducts of the lacrimal gland, Meibomian gland, and in the glands of Moll and Zeis. The Meibomian glands and the glands of Zeis exhibited a marked UT-A-positive staining in the basal cells of the alveolar epithelia and in the ductal epithelia. Conclusion: UT-A shows comparable expression patterns to UT-B (previous study) at the ocular surface and in the lacrimal glands, as determined by immunohistochemistry. The presence of both urea transporters in the lacrimal functional unit suggests that they are essential for the normal function of the lacrimal system and the integrity of the tear film. Potential alterations in urea transporter expression might be associated with the significant reduction of urea found in the tear fluid of dry eye patients. They may thus play an important role in the pathogenesis of dry eye disease. (c) 2022 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2022-09-16

Immunotherapy of uveal melanoma: vaccination against cancer : Multicenter adjuvant phase 3 vaccination study using dendritic cells laden with tumor RNA for large newly diagnosed uveal melanoma - Schuler-Thurner, Beatrice; Bartz-Schmidt, K. -U.; Bornfeld, N.; Cursiefen, C.; Fuisting, B.; Grisanti, S.; Heindl, L. M.; Holbach, L.; Keserue, M.; Knorr, H.; Koch, K.; Kruse, Friedrich; et al. (Ophthalmologe, 2015)
Uveal melanomas are the most common malignant tumors of the eye. With modern molecular biological diagnostic methods, such as chromosome 3 typing and gene expression analysis, these tumors can be categorized into highly aggressive (monosomy 3, class II) and less aggressive forms. This molecular biological stratification is primarily important for determining the risk of these tumors as no therapy is currently available that is able to prevent or delay metastases. A randomized study of patients with a poor prognosis (monosomy 3) is currently being carried out in order to determine whether a cancer vaccine prepared from autologous (patient's own) dendritic cells and uveal melanoma RNA can prevent or delay progression and further metastases of this extremely aggressive form of cancer. Inclusion in the uveal melanoma study, which hopes to provide a potential therapeutic option for patients, is only possible if patients are referred to an institution that is able to manufacture and provide this vaccination before the patient is operated on or treated with radiation. Untreated tumor material is necessary for producing the vaccine on an individualized patient basis.
EVALuna2:19521

Impact of acquisition area on deep-learning-based glaucoma detection in OCTA - Schottenhamml, Julia; Würfl, Tobias; Ploner, Stefan; Husvogt, Lennart; Maier, Andreas; Hohberger, Bettina; Mardin, Christian Y. (Investigative Ophthalmology & Visual Science, 2023)

IMPACT OF BLOOD PRESSURE AND AGEING ON RETINAL NEURODEGENERATION ASSESSED BY SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY - Jung, Susan; Bosch, Agnes; Kohler, N.; Ott, Christian; Kannenkeril, D.; Dienemann, T.; Harazny, J. M.; Michelson, Georg; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Impaired increase of retinal capillary blood flow to flicker light exposure in arterial hypertension - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Bauernschubert, Philipp; Lehmann, Marina; Michelson, Georg; Schmieder, Roland (Hypertension, 2012)
We hypothesized that the increase of retinal capillary blood flow (RCF) to flicker light exposure is impaired in subjects with arterial hypertension. In 146 nondiabetic untreated male subjects with (n=50) or without (n=96) arterial hypertension, RCF was measured before and after flicker light exposure noninvasively and in vivo using scanning laser Doppler flowmetry. In addition, in a subgroup of 28 subjects, the change of RCF to flicker light exposure was again assessed during parallel infusion of nitric oxide synthase inhibitor N-monomethyl-l-arginine (L-NMMA). The increase of RCF to flicker light exposure was lower in patients with untreated hypertension compared with normotensive subjects when expressed in absolute terms (7.69±54 versus 27.2±44 AU; P adjusted=0.013) or percent changes (2.95±14 versus 8.33±12%; P adjusted=0.023). Systolic (?=-0.216; P=0.023) but not diastolic blood pressure (?=-0.117; P=0.243) or mean arterial pressure (?=-0.178; P=0.073) was negatively related to the percent change of RCF to flicker light exposure, independently of other cardiovascular risk factors. In the subgroup of 28 subjects, the increase of RCF to flicker light exposure was similar at baseline and during parallel infusion of L-NMMA when expressed in absolute terms (20.0±51 versus 22.6±56 AU; P=0.731) or percent changes (7.12±16 versus 8.29±18%; P=0.607). The increase of RCF to flicker light exposure is impaired in arterial hypertension. In the subgroup of the total study cohort, nitric oxide was not a major determinant of the increase of RCF to flicker light exposure.
EVALuna2:3575

Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis - Zhou, Xiang; Trinh, Minh Thuong; TRAN MANH, CUONG; Gießl, Andreas; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (Arthritis and Rheumatology, 2022)
Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin-induced skin fibrosis, bleomycin-induced lung fibrosis, and skin fibrosis induced by overexpression of constitutively active transforming growth factor beta type I receptor (TGF beta R Iota). Results TFAM expression was down-regulated in fibroblasts in SSc skin and in cultured SSc fibroblasts. The down-regulation of TFAM was associated with decreased mitochondrial number and accumulation of damaged mitochondria with release of mitochondrial DNA (mtDNA), accumulation of deletions in mtDNA, metabolic alterations with impaired oxidative phosphorylation, and release of the mitokine GDF15. Normal fibroblasts subjected to long-term, but not acute, exposure to TGF beta mimicked SSc fibroblasts, with down-regulation of TFAM and accumulation of mitochondrial damage. Down-regulation of TFAM promoted fibroblast activation with up-regulation of fibrosis-relevant Gene Ontology terms in RNA-Seq, partially in a reactive oxygen species-dependent manner. Mice with fibroblast-specific knockout of Tfam were prone to fibrotic tissue remodeling, with fibrotic responses even to NaCl instillation and enhanced sensitivity to bleomycin injection and overexpression of constitutively active TGF beta RI. TFAM knockout fostered Smad3 signaling to promote fibroblast activation. Conclusion Alterations in the key mitochondrial transcription factor TFAM in response to prolonged activation of TGF beta and associated mitochondrial damage induce transcriptional programs that promote fibroblast-to-myofibroblast transition and drive tissue fibrosis.
CRIS-Team WoS Importer:2022-04-15

Impaired visual field while wearing mouth-nose masks in normal eyes - Bergua, Antonio; Weber, Annika; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-01

Impairment of the Visual System in Glaucoma - Schmidt, Manuel; Engelhorn, Tobias; Dörfler, Arnd; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2019)
MR Diffusion Tensor Imaging (DTI) enables visualisation of the visual system in glaucoma; it has been shown that the atrophy of the optic radiation is more pronounced in glaucoma than in age-matched controls. The atrophy of the optic radiation thereby correlates with OCT and visual field measures. Diffusion tensor imaging permits quantification of the axonal integrity of the optic radiation by calculation of fractional anisotropy (FA) and radial diffusivity (RD). Both within and also outside the visual system, there are substantial changes in FA and RD, changes suggesting a complex neurodegenerative disease. Metabolic MRI by specific Na+-coils and by the CEST-technique (CEST: chemical exchange saturation transfer) will enable visualisation of neuronal cell death and pathological protein accumulation in the visual system. It is proposed that glaucomatous atrophy of the visual system may be induced by antero- and retrograde axonal degeneration. In normal tension glaucoma and PEX glaucoma, retrograde degeneration is induced by ischemic lesions or pathological protein accumulation within the cerebral portion of the visual system. Magnetic resonance imaging of the visual system with DTI and metabolic imaging will potentially improve therapeutic monitoring and diagnosis of glaucoma.
CRIS-Team WoS Importer:2019-03-06

Incremental and decremental L- and M-cone driven ERG responses: II. Sawtooth stimulation - Kremers, Jan; Pangeni, Gobinda; Tsaousis, Konstantinos; Mckeefry, Declan; Murray, Ian J.; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
L- and M-cone driven on- and off-ERG responses and their interactions were examined using full field stimuli with sawtooth temporal profiles. The effects of temporal frequency and contrast were studied. ERG recordings were obtained from 21 trichromatic, 1 protanopic, and 1 deuteranopic subjects. ERGs to L-cone increments and decrements resembled those to M-cone decrements and increments, respectively (i.e., of the opposite polarity). Temporal frequency and contrast had little effect on the implicit times. All response components varied linearly with contrast. When stimulated simultaneously, the responsivities of most components were larger for counterphase than for inphase modulation. The retinal processing leading to an ERG response is reversed for L-and M-cone driven responses. (c) 2014 Optical Society of America

Incremental and decremental L- and M-cone-driven ERG responses: I. Square-wave pulse stimulation - Mckeefry, Declan; Kremers, Jan; Kommanapalli, Deepika; Challa, Naveen K.; Murray, Ian J.; Maguire, John; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
Electroretinograms (ERGs) elicited by transient, square-wave L- and M-cone isolating stimuli were recorded from human trichromatic (n=19) and dichromatic (n=4) observers. The stimuli were generated on a four primary LED stimulator and were equated in terms of cone modulation (cone contrast=0.11) and retinal illuminance (12,000 trolands). L- and M-cone isolated ERGs had waveforms similar to those observed for luminance responses. However, M-cone ERGs exhibited a phase reversal in their responses to onset and offset stimuli relative to the L-cone responses. This on-off response reversal was observed in trichromats but not dichromats. Simultaneous counterphase and inphase combinations of L- and M-cone isolating stimuli generated responses that reflected chromatic and luminance processing, respectively. We conclude that L- and M-cone specific ERGs provide a measure of how photoreceptors contribute to postreceptoral mechanisms.
EVALuna2:21214

Inflammation of the Eye in Systemic Inflammatory Disorders: Keratitis. - Bachmann, B.; Jacobi, Christina; Cursiefen, C. (Klinische Monatsblätter für Augenheilkunde, 2011)
Systemic inflammatory diseases are associated with keratitis. In addition to the much less frequently occurring non-ulcerative keratitis, ulcerative inflammation of the corneal periphery is common in systemic inflammatory diseases. Significant systemic inflammatory diseases in this context are autoimmune connective tissue diseases (including rheumatoid arthritis, systemic lupus erythematosus or primary vasculitides such as polyarteritis nodosa or Wegener's granulomatosis), systemic autoimmune dermatological disorders (such as the cicatrising pemphigoid or Stevens-Johnson syndrome) and autoimmune diseases of the lacrimal system (such as the lacrimal gland involvement in primary Sjogren's syndrome or in graft-versus-host disease). In severe cases of peripheral ulcerative keratitis intensive topical therapy is initially combined with a systemic high-dose steroid therapy. In further progressing ulceration, surgery may help to preserve or restore the integrity of the eye and may suppress the autoimmune response by shielding the corneal antigens from blood and the lymphatic system. Systemic immune modulating therapy has to be done in close consultation with the rheumatologist.
EVALuna2:21024

Influence of atypical retardation pattern on the peripapillary retinal nerve fibre distribution assessed by scanning laser polarimetry and optical coherence tomography - Schrems, Wolfgang; Lämmer, Robert; Hoesl, L. M.; Horn, Folkert; Mardin, C. Y.; Kruse, Friedrich; Tornow, Ralf-Peter (British Journal of Ophthalmology, 2011)
To investigate the influence of atypical retardation pattern (ARP) on the distribution of peripapillary retinal nerve fibre layer (RNFL) thickness measured with scanning laser polarimetry in healthy individuals and to compare these results with RNFL thickness from spectral domain optical coherence tomography (OCT) in the same subjects.120 healthy subjects were investigated in this study. All volunteers received detailed ophthalmological examination, GDx variable corneal compensation (VCC) and Spectralis-OCT. The subjects were divided into four subgroups according to their typical scan score (TSS): very typical with TSS=100, typical with 99 >= TSS >= 91, less typical with 90 >= TSS >= 81 and atypical with TSS <= 80. Deviations from very typical normal values were calculated for 32 sectors for each group.There was a systematic variation of the RNFL thickness deviation around the optic nerve head in the atypical group for the GDxVCC results. The highest percentage deviation of about 96% appeared temporal with decreasing deviation towards the superior and inferior sectors, and nasal sectors exhibited a deviation of 30%. Percentage deviations from very typical RNFL values decreased with increasing TSS. No systematic variation could be found if the RNFL thickness deviation between different TSS-groups was compared with the OCT results.The ARP has a major impact on the peripapillary RNFL distribution assessed by GDx VCC; thus, the TSS should be included in the standard printout.
EVALuna2:21007

Influence of blood flow on arteriolar wall-to-lumen ratio in the human retinal circulation in vivo - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Lehmann, Marina; Michelson, Georg; Schmieder, Roland (Microvascular Research, 2012)
We hypothesized that blood flow impacts on arteriolar wall-to-lumen ratio and that vasodilatory capacity is negatively related to arteriolar wall-to-lumen ratio in the human retinal vascular bed.The study cohort comprised 141 non-diabetic untreated male patients with (n=52) or without (n=89) arterial hypertension but without evidence for cardiovascular disease. Retinal capillary blood flow (RCF) before and after exposure to flicker light and to infusion of nitric oxide (NO) synthase inhibitor N-monomethyl-l-arginine (L-NMMA), and parameters of retinal arteriolar morphology, e.g. wall-to-lumen ratio, were assessed non-invasively and in vivo by scanning laser Doppler flowmetry.The study cohort was grouped according to the median RCF into two groups. Patients with RCF above the median revealed lower wall-to-lumen ratio (0.30±0.1 vs 0.34±0.1 (-), P adjusted=0.023) compared to patients with RCF equal or below the median. In addition, RCF was negatively related to wall-to-lumen ratio independently of cardiovascular risk factors (ß=-0.224, P=0.026). In parallel, the decrease of RCF to L-NMMA infusion was greater in patients with RCF above the median compared to the counter group (-8.95±11 vs. 0.35±15 (%), P adjusted <0.001). The increase in RCF to flicker light exposure was negatively related to wall-to-lumen ratio in hypertensive but not in normotensive or all patients (r=-0.292, P=0.047, r=-0.035, P=0.746 and r=-0.126, P=0.144, respectively).In the retinal circulation blood flow impacts on arteriolar wall-to-lumen ratio. Basal NO activity might modulate blood flow and arteriolar morphological changes. In hypertensive, but not in normotensive patients, the vasodilatory capacity is negatively related to arteriolar wall-to-lumen ratio in the human retinal vascular bed.
EVALuna2:3527

Influence of corneal guttae and nuclear cataract on contrast sensitivity - Augustin, Victor A.; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2020)
AIMS: To evaluate the contrast sensitivity in patients with nuclear cataract and corneal guttae compared to patients with nuclear cataract without guttae. METHODS: In this retrospective, single-centre case series, 50 eyes of 50 patients fulfilling the inclusion criteria were enrolled. Patients with corneal guttae and nuclear cataract (n=25, study group) underwent triple Descemet membrane endothelial keratoplasty (DMEK). Patients with nuclear cataract and healthy corneas underwent cataract surgery (n=25, control group). Inclusion criteria were preoperative best-corrected visual acuity ≥20/40, no corneal oedema and similar lens opacity (nuclear opalescence 2.0-2.9). Outcome measures included MARS letter and OPTEC 6500P contrast sensitivity test, corneal volume, central corneal thickness and anterior and posterior corneal densitometry. RESULTS: Preoperative MARS letter and OPTEC 6500P contrast sensitivity was significantly worse in the study group (MARS: p<0.001; OPTEC 6500P: p<0.007 at low spatial frequencies in daylight with and without glare and nightlight without glare). After surgery, there was no significant difference in MARS letter contrast sensitivity between groups (p=0.225). OPTEC 6500P contrast sensitivity remained significantly lower in the study group in daylight and nightlight with and without glare at most spatial frequencies (p<0.01) postoperatively. Preoperative and postoperative corneal volume, central corneal thickness and anterior corneal densitometry were equal in both groups (p>0.05). Posterior densitometry was significantly higher in the study group than in the control group preoperatively (p<0.001) but turned into equal values postoperatively (p=0.07). CONCLUSIONS: Corneal guttae cause an additional significant decrease in contrast sensitivity in eyes with nuclear cataract. This is in favour of performing a triple DMEK even in eyes with a visual acuity of ≥20/40.
CRIS-Team Scopus Importer:2020-10-09

Influence of Fuchs endothelial corneal dystrophy on contrast sensitivity in cataract patients - Tourtas, Theofilos; Augustin, Victor A.; Weller, Julia; Kruse, Friedrich (2018)
EVALuna2:34746

Influence of Mitomycin C on the Therapeutic Success of Stand-Alone Xen45 Gel Stents and Its Combination with Cataract Surgery in Open-Angle Glaucoma Patients - Denkel, Laura; Hohberger, Bettina; Lämmer, Robert (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Minimally invasive glaucoma surgery (MIGS), like Xen45 gel stents, is known as effective therapy in lowering intraocular pressure (IOP); however, fibrotic reactions are a common problem in postoperative management. It was the aim of this study to investigate the therapeutic success of Xen45 gel stents as a stand-alone technique (Xen) and combined with cataract surgery (XenPhaco), and with antimetabolites (mitomycin C, MMC) in open-angle glaucoma patients. Methods Retrospective analysis was performed of 199 eyes of 177 glaucoma patients of the Department of Ophthalmology, University of Erlangen Nürnberg, and from the Erlangen Glaucoma Registry (NCT00494923; ISSN 2191-5008, CS-2011) who underwent implantation of a Xen45 gel stent. Therapeutic success was defined as IOP reduction of ≥ 20% on the same or less anti-glaucomatous medication after 12 months compared to preoperative and without any additional glaucoma-related surgery (except bleb needling). IOP reduction, reduction in local anti-glaucomatous eye drops, and intra- and postoperative complications were monitored. Results Stand-alone Xen45 gel stent: therapeutic success was reached in 39% (-MMC) and 55% (+MMC). Failure rate was 61% (-MMC) and 45% (+MMC). XenPhaco: therapeutic success was achieved in 57% (-MMC) and 46% (+MMC). Failure rate was 43% (-MMC) and 54% (+MMC). Data were not different for group and subgroup analyses (p > 0.05). Conclusions The use of MMC seemed to increase the therapeutic success rate after stand-alone Xen45 gel stent implantation and combined with cataract surgery, yet statistical significant was not reached.
CRIS-Team Scopus Importer:2021-06-04
Keywords: fibrosis; glaucoma; IOP; MIGS; MMC; Xen Stent

Influence of operating parameters on the suture retention test for scaffolds in ophthalmology - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
The strength of a suture used to attach a graft to a patient can be quantified using the suture retention test. In order to gain deeper insight on the influence of testing and application conditions testing parameters were varied. Different pull rates, suture and jaw positions, and suture materials were tested to show their influence on the result of the test. The results of the different states were analyzed using statistical tests. Based on the statistic analysis conditions for testing with a maximum of accuracy and as close as possible to in vivo conditions have been revealed.
EVALuna2:21344

Influence of the molar mass distribution on the suture-ability of nanofiber meshes for tissue engineering - Hehn, Markus; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Influence of the molecular weight on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Influence of Ultrastructural Corneal Graft Abnormalities on the Outcome of Descemet Membrane Endothelial Keratoplasty - Weller, Julia M.; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos; Kruse, Friedrich (American Journal of Ophthalmology, 2016)
To investigate if ultrastructural alterations in the Descemet membrane (DM) are correlated with the clinical outcome after Descemet membrane endothelial keratoplasty (DMEK).Retrospective cohort study.setting: Institutional, single-center.One hundred and twelve residual DM specimens obtained after DM stripping.Incidence of ultrastructural abnormalities in transmission electron microscopy, graft detachment rate, graft failure rate, best-corrected visual acuity (BCVA), endothelial cell density (ECD), and central corneal thickness (CCT). Examination dates were on the day before DMEK and 1, 3, 6, and 12 months after surgery.Abnormalities in the ultrastructure of DM were found in 16 of 112 specimens (14%) (abnormal DM group), comprising deposits of long-spacing collagen, fine filaments (proteoglycans), a posterior collagenous layer, pseudoexfoliative material, and guttae. The secondary graft failure rate was significantly higher in the abnormal DM group compared with the normal DM group (P = .001). There was a trend for an increased graft detachment rate in the abnormal DM group (11/16) compared with the normal DM group (42/96) (P = .103). There was no significant difference in mean CCT and ECD after surgery. Mean CCT in the eyes with graft failure in the abnormal DM group at the last follow-up before regrafting was 850 ?m, indicating endothelial failure with stromal edema.This study reveals a correlation between ultrastructural alterations of DM in donor corneas and the graft failure rate after DMEK. Thus, graft failure after DMEK not only is determined by surgical trauma and postoperative events but may also be influenced by intrinsic, graft-specific features.
EVALuna2:21302

Infrared thermography: different options of thermal eyelid warming - Kremers, Inge; Hohberger, Bettina; Bergua, Antonio (Graefes Archive For Clinical and Experimental Ophthalmology, 2020)
Purpose Current therapies of Meibomian gland dysfunction (MGD) include thermal eyelid warming. It was the aim of the study to investigate the temperature run after eyelid warming using 3 different techniques (hot compresses, Blephasteam (R) (Thea Pharma GmbH, France), and having a sauna) in patients with MGD compared with normal subjects by infrared thermography. Methods A prospective case-control study was done. Temperature profiles of the eyelids were investigated in 93 subjects (49 normals, 44 MGD patients) after warming of the eyelids by 3 methods: hot compresses, Blephasteam (R), and having a sauna. Temperature runs of the eyelids were measured with an infrared thermal imaging camera (VarioCAM (R) HD research 675/30 mm, InfraTec GmbH) at baseline and after eyelid warming for 10 min. Statistical analysis were done by Wilcoxon test or t tests for unpaired samples. Results The initial eyelid temperature was significantly increased after the use of Blephasteam (R) compared with hot compresses in MGD and normal patients (p < 0.001). Having a sauna showed a similar warming effect of the eyelids than Blephasteam (R) in normals and MGD patients (p > 0.05). Additionally, the warming effect of the eyelids after having a sauna was significantly longer than after the use of Blephasteam (R) in MGD (p = 0.016) and normal patients (p = 0.01). Conclusion Eyelid temperature after having a sauna was similar to commonly used warming devices; yet, the duration of the eyelid warming effect was longer. Thus, having a sauna might be an alternative option for warming of the eyelids.
CRIS-Team WoS Importer:2020-04-28

Inhibitory and Agonistic Autoantibodies Directed Against the β2-Adrenergic Receptor in Pseudoexfoliation Syndrome and Glaucoma - Hohberger, Bettina; Schlötzer-Schrehardt, Ursula; Mardin, Christian; Lämmer, Robert; Munoz, Luis Enrique; Kunze, Rudolf; Herrmann, Martin; Wallukat, Gerd (Frontiers in Neuroscience, 2021)
Pseudoexfoliation syndrome (PEXS) and glaucoma (PEXG) are assumed to be caused by a generalized elastosis leading to the accumulation of PEX material in ocular as well as in extraocular tissues. The exact pathophysiology of PEXS is still elusive. PEXG, the most common type of secondary open-angle glaucoma (OAG), is characterized by large peaks of intraocular pressure (IOP) with a progressive loss of the visual field. Agonistic autoantibodies (agAAbs) against the β2-adrenergic receptor (AR) have been shown to be present in sera of patients with primary and secondary OAG and ocular hypertension and are seemingly linked to IOP. In the present study, we investigated the autoantibodies directed against the β2-AR in sera of patients with PEXS and PEXG. We recruited 15, 10, and 15 patients with PEXG, PEXS, and primary OAG, respectively. Ten healthy individuals served as controls. All patients underwent standard ophthalmological examination with Octopus G1 perimetry. agAAbs prepared from serum samples were analyzed in a rat cardiomyocyte–based bioassay for the presence of agAAbs. We identified the interacting loop of the β2-AR and the immunoglobulin G (IgG) subclasses using synthetic peptides corresponding to the extracellular loops of the receptors and enzyme-linked immunosorbent assay, respectively. None of the controls were β2-agAAb–positive (0.2 ± 0.5 U). No β2-agAAbs (0.2 ± 0.4 U), but inhibitory β2-AAbs were observed in 80% of the patients that partially blocked the drug-induced β2-adrenergic stimulation; 5.8 ± 1.7 U vs. 11.1 ± 0.9 U for clenbuterol in the absence and the presence of sera from patients with PEXS, respectively. Epitope analyses identified the third extracellular loop of the β2-AR as the target of the inhibitory β2-AAbs, being of IgG3 subtype in PEXS patients. In contrast, patients with PEXG showed β2-agAAbs (5.6 ± 0.9 U), but no inhibitory ones. The β2-agAAbs levels of patients with PEXG and primary OAG patients (3.9 ± 2.8 U; p > 0.05) were at a similar level. In two cases of PEXG, the β2-agAAbs exert synergistic effects with clenbuterol. The activity increased from 11.5 ± 0.3 (clenbuterol only) to 16.3 ± 0.9 U. As autoimmune mechanisms were reportedly involved in the pathogenesis of glaucoma, agonistic and inhibitory β2-AAbs seem to be a part of this multifactorial interplay.
CRIS-Team Scopus Importer:2021-09-03
Keywords: autoantibodies; glaucoma; imbalanced autonomic theory; pseudoexfoliation; β

Innervation pattern of the preocular human central retinal artery - Bergua, Antonio; Kapsreiter, Markus; Neuhuber, Winfried; Reitsamer, Herbert A.; Schroedl, Falk (Experimental Eye Research, 2013)
The central retinal artery (CRA) is the main vessel for inner retinal oxygen and nutrition supply. While the intraocular branches lack autonomic innervation, the innervation pattern of the extra-ocular part of this vessel along its course within the optic nerve is poorly investigated. This part however is essential for maintenance of retinal blood supply, in physiological and pathological conditions. Therefore, the aim of this study was the characterization of the autonomic innervation of the preocular CRA in humans with morphological methods. Meeting the Declaration of Helsinki, eyes of body or cornea donors were processed for single or double immunohistochemistry against tyrosine hydroxilase (TH), dopamine-?-hydroxylase (DBH), choline acetyl-transferase (ChAT), vesicular acetylcholine transporter (VAChT), neuronal nitric oxide synthase (nNOS), calcitonin gene-related peptide (CGRP), substance P (SP), vasoactive intestinal polypeptide (VIP), and cytochemistry for NADPH-diaphorase (NADPH-d). For documentation, light-, fluorescence-, and confocal laser-scanning microscopy were used. TH and DBH immunoreactive nerve fibres were detected in the CRA vessel wall, although a distinct perivascular plexus was missing. Further, nerve fibres immunoreactive for ChAT and VAChT were found, while CGRP, SP, and VIP were not detected. NADPH-d staining revealed scattered nerve fibres in the adventitia of the CRA and in close vicinity; however, nNOS-immunostaining could not confirm this finding. The CRA receives adrenergic and cholinergic innervations, indicating sympathetic and parasympathetic components, respectively. Remarkably, a peptidergic primary afferent innervation was missing. Since clinical results suggest an autoregulation of intraretinal vessels, further studies are needed to clarify the impact of CRA innervation for retinal perfusion.
EVALuna2:4135

In Reply: Precision of Optic Nerve Head and Retinal Nerve Fiber Layer Parameter Measurements by Spectral-domain Optical Coherence Tomography, Methodological Issues on Reproducibility - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Lämmer, Robert; Kruse, Friedrich; Mardin, Christian Y. (Journal of Glaucoma, 2018)
Purpose:We report the occurrence of an extensive submacular hemorrhage after trabeculectomy with mitomycin C in a patient with an occult choroidal neovascular membrane (CNVM).Patients and Methods:A 66-year-old man had a 3-year history of primary open-angle glaucoma in the left eye, which had been treated with topical antiglaucoma medication. The patient had age-related macular degeneration with an occult CNVM, for which he had received 5 intravitreal injections of ranibizumab and 5 intravitreal injections of bevacizumab in the left eye over a 3-year period. As intraocular pressure was not under control in the left eye over a 2-month period, trabeculectomy with mitomycin C was performed.Results:On the first postoperative day, intraocular pressure was 8mmHg with a well-formed bleb in the left eye. However, extensive subretinal hemorrhage was observed, and the patient underwent pneumatic displacement and pars plana vitrectomy to remove the hemorrhage. After 7 months, extensive subretinal fibrosis was observed and visual acuity was low (hand movement only).Conclusions:To our knowledge, this is the first report of an extensive submacular hemorrhage after trabeculectomy with mitomycin C in a patient with an occult CNVM.
EVALuna2:34752

Instrument to Enhance Visualization of Descemet Membrane During Graft Preparation for DMEK Surgery - Menzel-Severing, Johannes; Salla, Sabine; Plum, Wolfgang Joachim; Tourtas, Theofilos; Fuchsluger, Thomas; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich Eduard (Cornea, 2016)
Descemet membrane (DM) endothelial keratoplasty has improved outcomes of corneal transplantation in patients with corneal endothelial disease. However, the procedure has been criticized for jeopardizing donor tissue during graft preparation. Standardization of this procedure may provide a way toward minimizing tissue loss. For this purpose, we propose the use of a novel tool.Computerized numerical control milling was used to create a blunt instrument, which was used to remove endothelial cells within a defined area in the periphery of donor corneas. Trypan blue was used to stain denuded DM. Graft preparation was continued as per our standard protocol. Transmission electron microscopy was performed on the treated area, and endothelial cell counts were obtained.Use of the modified procedure resulted in delineation of a peripheral band of denuded DM, which readily stained with trypan blue. This provided increased visibility of DM during subsequent steps. Transmission electron microscopy confirmed that no structural deficits of DM were induced. Mean endothelial cell loss (±SD) at 24 hours after preparation was 63 (±130) cells per square millimeter in the group prepared with the use of the new instrument (n = 7), versus 116 (±107) cells per square millimeter in the group prepared without the new instrument (n = 7; P = 0.45).The device presented here enhances visualization of DM during creation of the peripheral margin for subsequent lifting of the margin and stripping of the graft. This may increase success rates and shorten preparation times and learning periods for DM preparation. DM ultrastructure and endothelial cells were not negatively affected.
EVALuna2:21287

Insulin-like factor 3 promotes wound healing at the ocular surface - Hampel, Ulrike; Klonisch, Thomas; Sel, Saadettin; Schulze, Ute; Paulsen, Friedrich (Endocrinology, 2013)
Tear fluid is known to contain many different hormones with relevance for ocular surface homeostasis. We studied the presence and functional role of insulin-like factor 3 (INSL3) and its cognate receptor RXFP2 (relaxin/insulin-like family peptide receptor 2) at the ocular surface and in tears. Expression of human INSL3 and RXFP2 was determined in tissues of the ocular surface and lacrimal apparatus; in human corneal (HCE), conjunctival (HCjE), and sebaceous (SC) epithelial cell lines; and in human tears by RT-PCR and ELISA. We investigated effects of human recombinant INSL3 (hrINSL3) on cell proliferation and cell migration and the influence of hrINSL3 on the expression of MMP2, -9, and -13 and TIMP1 and -2 was quantified by real-time PCR and ELISA in HCE, HCjE, and SC cells. We used a C57BL/6 mouse corneal defect model to elucidate the effect of topical application of hrINSL3 on corneal wound healing. INSL3 and RXFP2 transcripts and INSL3 protein were detected in all tissues and cell lines investigated. Significantly higher concentrations of INSL3 were detected in tears from male vs. female volunteers. Stimulation of HCE, HCjE, and SC with hrINSL3 significantly increased cell proliferation in HCjE and SC and migration of HCjE. Treatment with hrINSL3 for 24 hours regulated MMP2, TIMP1, and TIMP2 expression. The local application of hrINSL3 onto denuded corneal surface resulted in significantly accelerated corneal wound healing in mice. These findings suggest a novel and gender-specific role for INSL3 and cognate receptor RXFP2 signaling in ocular surface homeostasis and determined a novel role for hrINSL3 in corneal wound healing. Copyright © 2013 by The Endocrine Society.
CRIS-Team Scopus Importer:2022-08-05

Integrity/Demyelination of the optic radiation, morphology of the papilla, and contrast sensitivity in glaucoma patients - Michelson, Georg; Wärntges, Simone; Engelhorn, Tobias; El-Rafei, Ahmed Mohamed Ibrahim; Hornegger, Joachim; Dörfler, Arnd (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: In primary open angle glaucoma (POAG) and its non-barotraumatic subgroup, normal tension glaucoma (NTG), the pathophysiological differences are not clear. A participation of the 4th neuron of the visual pathway (optic radiation) appears possible on the basis of related experimental studies. The goal of the present study was the evaluation of the optic radiation by diffusion tensor imaging (DTI), which is based on the magnetic resonance imaging. The diffusion and anisotropy parameters of the optic radiation as a marker of axonal integrity and demyelination/damage of glial cells, respectively, were used to investigate the relation between the morphology of the papilla (BLDF, linear discriminant function of Burk) and the contrast sensitivity (FDT, frequency doubling test). Patients and Methods: In this prospective observational study 13 POAG patients, 13 NTG patients, and 7 control patients of the same mean age were included. For segmentation of the optic radiation a semi-automated algorithm was applied and the diffusion and anisotropy parameters were calculated. The importance of the covariates age, BLDF, and FDT for the DTI parameters was determined using partial correlation analysis. Results: Analysis of the covariates partially showed a clear autocorrelation. The correlations between the DTI parameters and BLDF were significant in all groups after correction of the measurement values for the covariates. FDT correlated with DTI parameters in controls and POAG. The NTG group did not show this correlation due to a strong spreading of the FDT values. Conclusion: After statistical elimination of the autocorrelation of the covariates age, BLDF, and FDT the morphology of the papilla correlated with the axonal integrity and demyelination/glia cell impairment of the optic radiation in controls and glaucoma. In NTG the impaired contrast sensitivity is highly variable and is not associated with the condition of the 3rd or 4th neuron, respectively, as compared to POAG. The autocorrelation between individual covariates represents an important element for the judgement of the visual pathway. © Georg Thieme Verlag KG · Stuttgart · New York.

Intensified secondary prevention intending a reduction of recurrent events in TIA and minor stroke patients (INSPiRE-TMS): a protocol for a randomised controlled trial - Leistner, Stefanie; Michelson, Georg; Laumeier, Inga; Ahmadi, Michael; Smyth, Maureen; Nieweler, Gabriele; Doehner, Wolfram; Sobesky, Jan; Fiebach, Jochen B.; Marx, Peter; Busse, Otto; Koehler, Friedrich; et al. (BMC Neurology, 2013)
Patients with recent stroke or TIA are at high risk for new vascular events. Several evidence based strategies in secondary prevention of stroke are available but frequently underused. Support programs with multifactorial risk factor modifications after stroke or TIA have not been investigated in large-scale prospective controlled trials so far. INSPiRE-TMS is a prospective, multi-center, randomized open intervention trial for intensified secondary prevention after minor stroke and TIA.Patients with acute TIA or minor stroke admitted to the participating stroke centers are screened and recruited during in-hospital stay. Patients are randomised in a 1:1 ratio to intervention (support program) and control (usual care) arms. Inclusion of 2.082 patients is planned. The support program includes cardiovascular risk factor measurement and feedback, monitoring of medication adherence, coaching in lifestyle modifications, and active involvement of relatives. Standardized motivational interviewing is used to assess and enhance patients' motivation. Primary objective is a reduction of new major vascular events defined as nonfatal stroke and myocardial infarction or vascular death. Recruitment time is planned for 3.5 years, follow up time is at least 2 years for every patient resulting in a total study time of 5 years (first patient in to last patient out).Given the high risk for vascular re-events in acute stroke and the available effective strategies in secondary prevention, the INSPIRE-TMS support program has the potential to lead to a relevant reduction of recurrent events and a prolongation of the event-free survival time. The trial will provide the basis for the decision whether an intensified secondary prevention program after stroke should be implemented into regular care. A cost-effectiveness evaluation will be performed.clinicaltrials.gov: 01586702.
EVALuna2:21121

Interactions between rod and L-cone signals in deuteranopes: Gains and phases - Kilavik, B.E.; Kremers, Jan (Visual Neuroscience, 2006)
The dynamics of interactions between rod and L-cone driven signals were studied psychophysically in two deuteranopic observers. Flicker detection thresholds for different ratios of rod to L-cone modulation were measured at temporal frequencies between 1 and 15 Hz. A model, which assumes that rod and L-cone driven signals are vector added, can describe the threshold data adequately. We found that up to about 8-10 Hz temporal frequency, rod and L-cone signals interact additively, whereas at higher frequencies the interaction is subtractive. Rod and L-cone signal strengths depend similarly on temporal frequency and are maximal between 3 and 5 Hz. The phase difference between rod and L-cone signals increases linearly with temporal frequency, indicating that their responses have a delay difference of about 20 to 30 ms, consistent with involvement of the faster rod pathway. The data would suggest a nearly complete additivity of the rod and cone driven signals when using flashed stimuli. But, literature data showed only partial additivity of the two, suggesting that different postreceptoral mechanisms are involved in the two tasks.
Keywords: rod; L-cone; temporal frequency; gain; latency difference

INTESTINAL HIF1 alpha EXPRESSION PROTECTS AGAINST EPITHELIAL CELL DEATH IN ARTHRITIS - Lyu, Pang; Wen, Jinming; Stolzer, Iris; Gießl, Andreas; Song, Rui; Meng, Xiangjun; Cao, Shan; Günther, Claudia; Schett, Georg; Bozec, Aline (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Intraocular pressure is influenced by ambient temperature in glaucoma patients - Krebs, Johann Ferdinand; Hosari, Sami; Lämmer, Robert; Mardin, Christian; Hohberger, Bettina (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Invasion of lymphatic vessels into the eye after open globe injuries - Wessel, Julia M.; Hofmann-Rummelt, Carmen; Kruse, Friedrich; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2012)
We analyzed whether lymphatic vessels can be detected in eyes enucleated after an open globe injury.The presence of lymphatic vessels was analyzed immunohistochemically using podoplanin as a specific lymphatic endothelial marker in 21 globes that had been enucleated after open globe injury. The localization of pathologic lymphatic vessels (within the eye wall or inside the eye) was correlated with the mechanism of trauma, anatomic site of perforation or rupture, and time interval between trauma and enucleation.Pathologic lymphatic vessels were detected in 15 of 21 eyes (71%) enucleated after an open globe injury. In 5 globes (24%) they were found within the eye, located in retrocorneal membranes, underneath the sclera, and adjacent to uveal tissue (ciliary body, iris). No significant association was observed between the presence of pathologic lymphatic vessels and the mechanism of trauma (P = 0.598), anatomic site of perforation or rupture (P = 0.303), and time interval between trauma and enucleation (P = 0.145).The human eye can be invaded secondarily by lymphatic vessels if the eye wall is opened by trauma. This mechanism could be important for wound healing, immunologic defense against intruding microorganisms, and autoimmune reactions against intraocular antigens.
EVALuna2:21111

Investigation of lateral geniculate nucleus volume and diffusion tensor imaging in patients with normal tension glaucoma using 7 tesla magnetic resonance imaging - Schmidt, Manuel; Knott, Michael; Heidemann, Robin; Michelson, Georg; Kober, Tobias; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2018)
BACKGROUND: There is evidence that glaucoma is a neurodegenerative disease involving the whole visual pathway. We prospectively examined potential benefits of volumetry of the lateral geniculate nucleus (LGN) and diffusion tensor imaging (DTI) using a new 7T scanner. METHODS: 20 patients with normal tension glaucoma and 16 control individuals were examined. LGN volume and fractional anisotropy (FA) of the optic tract (OT) and the optic radiation (OR) and their correlation with RNFL (retinal nerve fiber layer) thickness were analyzed. RESULTS: LGN volume was significantly reduced in NTG (60.9 vs 88.3; p < 0.05). FA of the OT (right: 0.35 vs 0.66, left: 0.36 vs 0.67; p < 0.05) and of the OR (right: 0.41 vs 0.70, left: 0.41 vs 0.69; p < 0.05) was also significantly reduced. Nasal RNFL thickness correlated with the volume of the contralateral LGN (r = 0.471, p = 0.05). Temporal RNFL thickness correlated with the volume of the ipsilateral LGN (r = 0.603, p = 0.015). CONCLUSION: NTG leads to significant atrophy of the LGN compared to controls. FA of the optic tract and the optic radiation is reduced in NTG as sign of axonal degeneration. RNFL thickness but not FA correlates with LGN volume.
EVALuna2:34502

Investigation of OCTA Biomarkers in Fabry Disease: A Long Term Follow-Up of Macular Vessel Area Density and Foveal Avascular Zone Metrics - Hufendiek, Katerina; Lindziute, Migle; Kaufeld, Jessica; Volkmann, Ingo; Brockmann, Dorothee; Hosari, Sami; Hohberger, Bettina; Mardin, Christian; Framme, Carsten; Tode, Jan; Hufendiek, Karsten (Ophthalmology and Therapy, 2023)
Introduction: Retinal microvasculature is known to be altered in patients with Fabry disease (FD). We aimed to investigate the long-term changes in macular microvasculature and explore a reliable retinal biomarker for treatment monitoring in FD. Methods: Prospective study of 26 eyes with FD followed up to 48 months (mean 24, range 8–48). OCT angiography (OCTA) images (2.9 × 2.9 mm) were obtained using Heidelberg Spectralis II at baseline and follow-up. Macular vessel area density (VAD, %) was measured in three layers: superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP) in three peri-macular circular sectors (c1, c2, c3). Additionally, foveal avascular zone (FAZ) area (mm2) and horizontal and vertical diameters (µm) were assessed. Results: VAD decreased over time in SVP, ICP (in sectors c2 and c3) and DCP (all sectors) (p < 0.04). VAD reduction was predominantly seen in treated FD patients. FAZ and horizontal diameters increased at follow-up in FD patients compared to baseline (p ≤ 0.025). Correlation analysis showed a moderate to strong negative correlation between VAD of SVP and DCP in the innermost circle and FAZ in treated patients (r = − 0.6; p < 0.0001). Conclusions: This is the first long-term follow-up OCTA study in FD to our knowledge. A decrease in VAD, pronounced in the peripheral circle and deeper layers, as well as an enlargement of the FAZ could be observed over time. These changes reflect the vascular remodelling during the course of the disease. Interestingly, the reduction of VAD was more pronounced in treated patients. This could be a result of enzyme replacement therapy and could be potentially used as a reliable biomarker for monitoring the treatment of the disease. A baseline examination of VAD and FAZ before treatment initiation is meaningful. Larger studies are needed to establish the use of VAD and FAZ as biomarkers for treatment monitoring.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Fabry disease (FD); OCTA biomarkers; Retinal microcirculation; Treatment monitoring

In Vitro Study of the Deturgescence Ability of Cultivated Human Corneal Endothelial Cells - Tsaousis, Konstantinos T.; Kopsachilis, Nikolaos; Tsinopoulos, Ioannis T.; Dimitrakos, Stavros A.; Kruse, Friedrich; Welge-Luessen, Ulrich (Cornea, 2016)
To evaluate the efficiency of cultivated human corneal endothelial cells (HCECs) to dehydrate the cornea, using models of the posterior cornea, composed of artificial collagen mass (to represent corneal stroma) and equine collagen membranes (to represent Descemet membrane).HCECs were isolated from donor corneal rings and cultivated at 37°C in 5% CO2 and 95% humidified air. The study design included 4 different sets of models: in set 1, the HCECs were placed directly on the collagen mass complex; in set 2, HCECs were placed on a thin equine collagen membrane and laid over the collagen mass; in set 3, HCECs were placed on a thick equine collagen membrane laid over the collagen mass; and in set 4 (the control group), the hydrophilic collagen mass was left alone to interact with the nutritional medium. The minimum thickness of each sample was measured with optical coherence tomography directly before placement of cells and after exposure to the nutritional fluid for 48 hours.After 2 days of exposure to the nutritional medium, the percentage decreases in thickness in "posterior cornea" models were 66% for set 1, 57% for set 2, and 13% set 3. In the control set, measurement of thickness after 2 days of exposure was not possible because of excessive fluid absorption.This in vitro study of HCECs showed that the dehydrating ability of HCECs is adversely affected by increased thickness of the artificial (Descemet) membrane. Further studies with similar models would aid better understanding of corneal diseases.
EVALuna2:21290

In vivo electroretinographic differentiation of rod, short-wavelength and long/medium-wavelength cone responses in dogs using silent substitution stimuli - Mowat, Freya M.; Wise, Elisabeth; Oh, Annie; Foster, Melanie L.; Kremers, Jan (Experimental Eye Research, 2019)
The canine species has dichromatic color vision comprising short-wavelength (S-) and long/medium (L/M-) wavelength-sensitive cones with peak spectral sensitivity of 429–435 nm and 555 nm respectively. Although differentiation of rod- and cone-mediated responses by electroretinogram (ERG) in dogs is commonly performed, and standards have been developed based on standards for human observers, methods to differentiate S- and L/M-cone responses in dogs have not been described. We developed flicker protocols derived from previously published rod and cone spectral sensitivities. We used a double silent substitution paradigm to isolate responses from each of the 3 photoreceptor subclasses. ERG responses were measured to sine-wave modulation of photoreceptor excitation at different temporal frequencies (between 4 and 56 Hz) and mean luminance (between 3.25 and 130 cd/m2) on 6 different normal dogs (3 adult female, and 3 adult male beagles) and one female beagle dog with suspected hereditary congenital stationary night blindness (CSNB). Peak rod driven response amplitudes were achieved with low frequency (4 Hz, maximal range 4–12 Hz) and low mean luminance (3.25 cd/m2). In contrast, peak L/M-cone driven response amplitudes were achieved with high frequency (32 Hz, maximal range 28–44 Hz) and high mean luminance (32.5–130 cd/m2). Maximal S-cone driven responses were obtained with low frequency stimuli (4 Hz, maximal range 4–12 Hz) and 32.5–130 cd/m2 mean luminance. The dog with CSNB had reduced rod- and S-cone-driven responses, but normal/supernormal L/M cone-driven responses. We have developed methods to differentiate rod, S- and L/M-cone function in dogs using silent substitution methods. The influence of temporal frequency and mean luminance on the ERGs originating in each photoreceptor type can now be studied independently. Dogs and humans have similar L/M cone responses, whereas mice have significantly different L/M responses. This work will facilitate a greater understanding of canine retinal electrophysiology and will complement the study of canine models of human hereditary photoreceptor disorders.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Congenital stationary night blindness; dog; Electroretinogram; L/M-cone; Photoreceptor; Rod; S-Cone; Silent substitution

Involvement of a disintegrin and metalloproteinase 10 (ADAM10) in excessive extracellular matrix production in Fuchs endothelial corneal dystrophy - Komori, Yuya; Okumura, Naoki; Hanada, Naoya; Tokunaga, Ayumi; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Involvement of caspase 7 in the excessive production of extracellular matrix in Fuchs endothelial corneal dystrophy - Tonomura, Shigehito; Okumura, Naoki; Endo, Mako; Nakahara, Makiko; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Involvement of ZEB1 and Snail1 in excessive production of extracellular matrix in Fuchs endothelial corneal dystrophy - Okumura, Naoki; Minamiyama, Ryuki; Ho, Leona T. Y.; Kay, Eunduck P.; Kawasaki, Satoshi; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Young, Robert D.; Quantock, Andrew J.; Kinoshita, Shigeru; Koizumi, Noriko (Laboratory Investigation, 2015)
Fuchs endothelial corneal dystrophy (FECD) due to corneal endothelial cell degeneration is a major cause of corneal transplantation. It is characterized by abnormal deposition of extracellular matrix (ECM), such as corneal guttae, accompanied by a loss of endothelial cells. Although recent studies have revealed several genomic factors, the molecular pathophysiology of FECD has not yet been revealed. In this study, we establish a cellular in vitro model by using immortalized corneal endothelial cells obtained from late-onset FECD and control patients and examined the involvement of epithelial mesenchymal transition (EMT) on excessive ECM production. We demonstrate that the EMT-inducing genes ZEB1 and SNAI1 were highly expressed in corneal endothelial cells in FECD and were involved in excessive production of ECM proteins, such as type I collagen and fibronectin through the transforming growth factor (TGF)-? signaling pathway. Furthermore, we found that SB431542, a specific inhibitor of TGF-? type I ALK receptors, suppressed the expression of ZEB1 and Snail1 followed by reduced production of ECM. These findings suggest that increased expression levels of ZEB1 and Snail1 in FECD cells were responsible for an increased responsiveness to TGF-? present in the aqueous humor and excessive production of ECM. In addition, these results suggest that the regulation of EMT-related genes by blocking the TGF-? signaling pathway may be a feasible therapeutic strategy for FECD.
EVALuna2:21239

ISCEV extended protocol for the photopic negative response (PhNR) of the full-field electroretinogram - Frishman, Laura; Sustar, Maja; Kremers, Jan; Mcanany, J. Jason; Sarossy, Marc; Tzekov, Radouil; Viswanathan, Suresh (Documenta Ophthalmologica, 2018)
The International Society for Clinical Electrophysiology of Vision (ISCEV) Standard for full-field electroretinography (ERG) describes a minimum procedure, but encourages more extensive testing. This ISCEV extended protocol describes an extension to the ERG Standard, namely the photopic negative response (PhNR) of the light-adapted flash ERG, as a well-established technique that is broadly accepted by experts in the field. The PhNR is a slow negative-going wave after the b-wave that provides information about the function of retinal ganglion cells and their axons. The PhNR can be reduced in disorders that affect the innermost retina, including glaucoma and other forms of optic neuropathy. This document, based on existing literature, provides a protocol for recording and analyzing the PhNR in response to a brief flash. The protocol includes full-field stimulation, a frequency bandwidth of the recording in which the lower limit does not exceed 0.3 Hz, and a spectrally narrowband stimulus, specifically, a red flash on a rod saturating blue background. Suggested flash strengths cover a range up to and including the minimum required to elicit a maximum amplitude PhNR. This extended protocol for recording the PhNR provides a simple test of generalized retinal ganglion cell function that could be added to standard ERG testing.
EVALuna2:34923

ISCEV extended protocol for the photopic On-Off ERG - Sustar, Maja; Holder, Graham E.; Kremers, Jan; Barnes, Claire S.; Lei, Bo; Khan, Naheed W.; Robson, Anthony G. (Documenta Ophthalmologica, 2018)
The International Society for Clinical Electrophysiology of Vision (ISCEV) standard for full-field electroretinography (ERG) describes a minimum procedure, but encourages more extensive testing. This ISCEV extended protocol describes an extension to the ERG standard, namely the photopic On-Off ERG, and outlines common clinical applications. A light stimulus duration of 150-200 ms is used in the presence of a rod-suppressing background to elicit cone-driven On- and Off-system ERG components. The On-response occurs after the stimulus onset and has a negative a-wave and positive b-wave. The Off d-wave is a positive component evoked by stimulus offset. Common diagnoses that may benefit from additional photopic On-Off ERG testing include retinal dystrophies and retinal disorders that cause dysfunction at a level that is post-phototransduction or post-receptoral. On-Off ERGs assess the relative involvement of On- and Off-systems and may be of use in the diagnosis of disorders such as complete and incomplete congenital stationary night blindness (complete and incomplete CSNB), melanoma-associated retinopathy, and some forms of autoimmune retinopathy. The photopic On-Off ERGs may also be useful in X-linked retinoschisis, Batten disease, Duchenne muscular dystrophy, spinocerebellar degeneration, quinine toxicity, and other retinal disorders.
EVALuna2:34922
Keywords: Retinopathy; Retinal dystrophy; On–Off ERG; Long-duration ERG; Bipolar cells; Full-field ERG; International Society of Clinical Electrophysiology of Vision (ISCEV); Clinical standards; Electroretinogram (ERG)

Isolated Unilateral Strabismus Sursoadductorius (Congenital Trochlear Palsy) with and without Hypotrophia of the Superior Oblique Muscle-Orthoptic Differences in Adulthood - Gusek-Schneider, Gabriele-Charlotte; Kaestle, Nicola; Reil, Franziska; Schuerhoff, Sabine; Engelhorn, Tobias (Klinische Monatsblätter für Augenheilkunde, 2018)
PURPOSE: The clinical feature of unilateral decompensating strabismus sursoadductorius (dSSA; often called congenital superior oblique palsy, CSOP) is not an etiologically uniform entity. Hypotrophy of the superior oblique muscle (HMOS) is a frequent and immediate cause of dSSA/CSOP. In this study, clinical characteristics of dSSA/CSOP with and without HMOS are compared. PATIENTS AND METHODS: Twenty-five consecutive patients (age 14 - 69 years; median 43 years) were included in this study, 14 with 3T MRI-proven HMOS (group 1) and 11 without HMOS (group 2). HMOS was defined as a reduction of the medio-lateral (ML) as well as based on ML and cranio-caudal (CC) diameter calculated area = (ML · CC/4) · π of the affected superior oblique muscle (SOM) < 80% in comparison to the contralateral SOM (measured on the single coronal image on which the muscle has its greatest extent). The two groups were compared in terms of head tilt, cyclo- and vertical deviation and the Bielschowsky head tilt test. Patients were classified according the Knapp's classification. RESULTS: Both the incidence of head tilt with 14/14 vs. 5/11 (χ2 = 0.003) and its degree: 11.1 ± 4.5° vs. 3.2 ± 4.1° (p < 0.001) was higher in group 1 than in group 2, as well as the Bielschowsky head tilt test: 9.3 ± 4.3° vs. 3.8 ± 4.9° (p = 0.008). The average amount of hypertropia was larger in group 1 than in group 2 during adduction: 16.7 ± 5.3° vs. 9.3 ± 3.4° (p < 0.001) as well as during adduction and downgaze of the affected eye: 14.6 ± 7.1 vs. 7.2 ± 3.7° (p = 0.03). In the sagittal plane, the increase of vertical deviation was larger in group 1 than in group 2: 2.8 ± 7.8 vs. - 2.4 ± 4.2 (p = 0.04); the excyclodeviation was larger in group 1 in all three planes (sagittal plane, adduction and abduction) in comparison to group 2: 1.3 ± 4.1 vs. - 2.9 ± 2.8 (p = 0.006), 2.4 ± 5.2 vs. - 2.2 ± 2.9 (p = 0.01), 0.5 ± 3.8 vs. - 2.7 ± 3.9 (p = 0.05). Knapp's class II was found in 6 of 15 patients in group 1 and only in this patient group (χ2 = 0.03). CONCLUSIONS: In both groups, the vertical deviation showed a great dispersion. In patients without HMOS (group 2), vertical deviation in adduction did not exceed 15°. Patients with HMOS (group 1) do not show the typical features of a later acquired trochlear palsy due to an early developed compensating innervation. A vertical deviation in adduction of more than 15°, increasing excyclodeviation towards downgaze in all three planes (sagittal plane, adduction and abduction) and Knapp's class II are relatively reliable predictors of a hypoplasia of the SOM. An internationally uniform term for this group of patients, such as superior oblique weakness or superior oblique hypotrophy, would be desirable.
EVALuna2:34915

Isolation and ex vivo Expansion of Human Limbal Epithelial Progenitor Cells - Polisetti, Naresh; Schlunck, Gunther; Reinhard, Thomas; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Bio-protocol, 2020)
Limbal stem cell transplantation has been used successfully to treat patients with limbal stem cell deficiency all over the world. However, long term clinical results often proved less satisfactory due to the low quality of the graft or inadequate properties of transplanted cells. To enhance the ex vivo expansion of human limbal epithelial stem or progenitor cells (LEPC) by preserving stem cell phenotype and to improve subsequent transplantation efficiency, cell-matrix interactions ex vivo should mimic the condition in vivo. The laminin isoforms preferentially expressed in the limbal niche can be used as a culture matrix for epithelial tissue engineering. We recently published the expansion of LEPC on various laminin isoforms and observed that laminin alpha 5-derived matrices support the efficient expansion of LEPC compared to tissue culture plates and other laminin isoforms by preserving stem/progenitor cell phenotype. Here, we describe an optimized protocol for the isolation of LEPC from cadaveric corneal limbal tissue by collagenase digestion and efficient expansion of LEPC using recombinant human laminin-511 E8 fragment (LN-511E8) as culture substrate.
CRIS-Team WoS Importer:2020-11-20

Klinische Entscheidungsfindung bei der Behandlung des diabetischen Makulaödems mit DEX-Implantat: ein Konsenspapier - Augustin, Albert J.; Feltgen, Nicolas; Haritoglou, Christos; Hoerauf, Hans; Maier, Mathias M.; Mardin, Christian Y.; Schargus, Marc (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Currently two intravitreally applied corticosteroids (dexamethasone and fluocinolone) are licensed in Germany for treatment of diabetic macular oedema (DME). The use of DEX implant for DME in daily clinical practice has not been defined in detail. Following a Delphi panel survey, a group of retina experts set out to come up with a consensus for use of the DEX implant in DME. Material and Methods International and national treatment recommendations were identified from the literature. A steering group generated a catalogue of 72 statements on the aetiology and pathogenesis of DME, therapy with DEX implant, use of DEX implant in patients previously treated with VEGF-inhibitors, use of DEX implant in combination therapy, safety of DME therapies as well as patientsÊ burden of treatment. Twenty-Two ophthalmologists from private practice and 6 hospital ophthalmologists participated in the Delphi panel via Survey Monkey. Consensus was reached if at least 75% of participants agreed or disagreed with a statement. Statements for which consensus was not reached were discussed once more during the expert consensus meeting and a vote was taken. Based on these results a treatment algorithm for foveal DME was proposed. Results If a patient does not show sufficient response after 3â Š-â Š6 months of anti-VEGF treatment (visual acuity gain of < 5Â ETDRS letters or reduction of central retinal thickness ≤ 20%), a switch to DEX implant should take place. DEX implant is also suitable in eyes with longer presentation of DME, showing e.g. massive lipid exudates. DEX implant is suitable as first-line therapy especially in pseudophakic patients, patients unwilling or able to comply with tight anti-VEGF injection intervals or patients with known vascular diseases. With fixed control visits every 4â Š-â Š8 weeks, use of DEX implant is flexible and individual. Decision parameters for repeated use should be visual acuity, retinal thickness and intraocular pressure. Treatment of both eyes on the same day should not take place. Conclusion The algorithm presented reflects survey as well as expert discussion results and may differ from recommendations issued by the German professional society. The consensus recommendations for the treatment of DME generated during the survey and meeting of retina experts are intended to guide use of DEX implant in daily practice.
CRIS-Team Scopus Importer:2021-02-12
Keywords: clinical practice; Delphi consensus; DEX implant; diabetic macular edema; treatment algorithm

Klinische und echographische Untersuchungsbefunde bei Patienten mit Carotis-Sinus-cavernosus-Fisteln - Huebner, L.; Struffert, T.; Mardin, Christian; Engelhorn, Tobias; Holbach, L.; Weller, J.; Hohberger, Bettina; Gusek-Schneider, Gabriele (Ophthalmologe, 2021)
Background: Symptoms and clinical findings in patients with carotid-cavernous fistulas are specific. Nevertheless, they can be very mildly expressed. This study aims to point out the potential diagnostic value of ultrasound of the orbit. Methods: A total of 25 patients with a reliable angiographic diagnosis of a fistula were reviewed retrospectively. We analyzed the symptoms, clinical findings and demonstrability in ultrasound of the orbit. Results: The most common clinical findings were nerve palsy, dilation of episcleral vessels and exophthalmos. If an ultrasound had been part of the examination a dilation of the superior ophthalmic vein could be demonstrated in all cases. Conclusion: The expeditious ultrasound investigation provides valuable information for the diagnosis of red eyes which are resistant to treatment. The examiner has to consider a fistula and perform an ultrasound especially when diplopia has newly occurred. Finally, the expedient neuroimaging can be arranged.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Diplopia; Echography; Exophthalmos; Red eye; Superior ophthalmic vein

Lack of a Retinal Phenotype in a Syne-2/Nesprin-2 Knockout Mouse Model - Falk, Nathalie; Joachimsthaler, Anneka; Keßler, Kristin; Lux, Uwe; Noegel, Angelika Anna; Kremers, Jan; Brandstätter, Johann Helmut; Gießl, Andreas (Cells, 2019)
Syne-2 (also known as Nesprin-2) is a member of a family of proteins that are found primarily in the outer nuclear membrane, as well as other subcellular compartments. Syne-2 contains a C-terminal KASH transmembrane domain and is part of a protein network that associates the nuclear envelope to the cytoskeleton via the binding to actin filaments. Syne-2 plays a role in nuclear migration, nuclear positioning during retinal development, and in ciliogenesis. In a previous study, we showed a connection between Syne-2 and the multifunctional scaffold protein Pericentrin (Pcnt). The elimination of the interaction of Syne-2 and Pcnt showed defects in nuclear migration and the formation of outer segments during retinal development, as well as disturbances in centrosomal migration at the beginning of ciliogenesis in general. In this study, the Syne-2 KO mouse model Nesprin-2oABD (Syne-2(tm1Ngl), MGI) with special attention to Pcnt and ciliogenesis was analyzed. We show reduced expression of Syne-2 in the retina of the Syne-2 KO mouse but found no significant structural-and only a minor functional-phenotype. For the first time, detailed expression analyses showed an expression of a Syne-2 protein larger than 400 kDa (similar to 750 kDa) in the Syne-2/Nesprin-2 KO mouse. In conclusion, the lack of an overt phenotype in Syne-2/Nesprin-2 KO mice suggests the usage of alternative translational start sites, producing Syne-2 splice variants with an intact Pcnt interaction site. Nevertheless, deletion of the actin-binding site in the Syne-2/Nesprin-2 KO mouse revealed a high variability in scotopic oscillatory potentials assuming a novel function of Syne-2 in synchronizing inner retinal processes.
CRIS-Team WoS Importer:2019-11-29

Laminin-511 and -521-based matrices for efficient ex vivo-expansion of human limbal epithelial progenitor cells - Polisetti, Naresh; Sorokin, Lydia; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Scientific Reports, 2017)
Optimization of culture conditions for human limbal epithelial stem/progenitor cells (LEPC) that incorporate the in vivo cell-matrix interactions are essential to enhance LEPC ex vivo-expansion and transplantation efficiency. Here, we investigate the efficacy of laminin (LN) isoforms preferentially expressed in the limbal niche as culture matrices for epithelial tissue engineering. Analyses of expression patterns of LN chains in the human limbal niche provided evidence for enrichment of LN-?2, -?3, -?5, -?1, -?2, -?3, -?1, -?2 and -?3 chains in the limbal basement membrane, with LN-?5 representing a signature component specifically produced by epithelial progenitor cells. Recombinant human LN-521 and LN-511 significantly enhanced in vitro LEPC adhesion, migration and proliferation compared to other isoforms, and maintained phenotype stability. The bioactive LN-511-E8 fragment carrying only C-terminal domains showed similar efficacy as full-length LN-511. Functional blocking of ?3?1 and ?6?1 integrins suppressed adhesion of LEPC to LN-511/521-coated surfaces. Cultivation of LEPC on fibrin-based hydrogels incorporating LN-511-E8 resulted in firm integrin-mediated adhesion to the scaffold and well-stratified epithelial constructs, with maintenance of a progenitor cell phenotype in their (supra)basal layers. Thus, the incorporation of chemically defined LN-511-E8 into biosynthetic scaffolds represents a promising approach for xeno-free corneal epithelial tissue engineering for ocular surface reconstruction.
EVALuna2:21349

Laminin-511 and -521 enable efficient in vitro expansion of human corneal endothelial cells - Okumura, Naoki; Kakutani, Kazuya; Numata, Ryohei; Nakahara, Makiko; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Kinoshita, Shigeru; Koizumi, Noriko (Investigative Ophthalmology & Visual Science, 2015)
The purpose of this study was to investigate the usefulness of laminin isoforms as substrates for culturing human corneal endothelial cells (HCECs) for clinical application of tissue engineering therapy.Expression of specific laminin chains in human corneal endothelium and Descemet's membrane was analyzed at the mRNA and protein levels. The effect of laminin-511 and -521 on cell adhesion and proliferation was evaluated. Recombinant laminin E8 fragments (E8s), which represent functionally minimal forms of laminins, were also evaluated for their effects on cell density and cellular phenotype. The potential involvement of ?3?1 and ?6?1 integrins in laminin signal transduction was also investigated using neutralizing antibodies.Laminin-511 and -521 were expressed in Descemet's membrane and corneal endothelium. These laminin isoforms significantly enhanced the in vitro adhesion and proliferation, and differentiation of HCECs. A cell density of 2200 to 2400 cells/mm2 was achieved when HCECs were cultured on laminin-511 or -521, whereas the density was only 1100 cells/mm2 on an uncoated control. E8s also supported HCEC cultivation with a similar efficacy to that obtained with full-length laminin. Functional blocking of ?3?1 and ?6?1 integrins suppressed the adhesion of HCECs even in the presence of laminin-511.Laminin-511 and -521 were the laminin isoforms present in Descemet's membrane, and these laminins modulate the adhesion and proliferation of CECs. Laminin E8s represent an ideal xeno-free defined substrate for the culture of CECs for clinical applications.
EVALuna2:21243

Laminin-511-E8 promotes efficient in vitro expansion of human limbal melanocytes - Polisetti, Naresh; Gießl, Andreas; Li, Shen; Sorokin, Lydia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Scientific Reports, 2020)
Limbal melanocytes, located in the basal epithelial layer of the corneoscleral limbus, represent essential components of the corneal epithelial stem cell niche, but, due to difficulties in their isolation and cultivation, their biological roles and potential for stem cell-based tissue engineering approaches have not been comprehensively studied. Here, we established a protocol for the efficient isolation and cultivation of pure populations of human limbal melanocytes, which could be expanded at high yield by using recombinant laminin (LN)-511-E8 as culture substrate. Co-cultivation of limbal melanocytes with limbal epithelial stem/progenitor cells on fibrin hydrogels pre-incubated with LN-511-E8 resulted in multilayered stratified epithelial constructs within ten days. By reproducing physiological cell–cell and cell–matrix interactions of the native niche environment, these biomimetic co-culture systems provide a promising experimental model for investigating the functional roles of melanocytes in the limbal stem cell niche and their suitability for developing advanced epithelial grafts for ocular surface surface reconstruction.
CRIS-Team Scopus Importer:2020-07-17

L- and M-cone driven temporal contrast sensitivity is reduced at low frequencies in patients with Stargardt's disease - Huchzermeyer, Cord; Pasutto, Francesca; Wiesmann da Silva Reis, André; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

L- and M-cone input to 12Hz and 30Hz flicker ERGs across the human retina - Challa, N. K.; Mckeefry, D.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Panorgias, Athanasios (Ophthalmic and Physiological Optics, 2010)
Keywords: Human retina; Luminance; Electroretinograms; Colour

L- and M-Cone Input to Opponent and Non-Opponent Channels as a Function of Retinal Eccentricity in the Human Erg - Kremers, Jan; Challa, N. K.; Parry, N. R. A.; Murray, I. J.; Panorgias, A.; Mckeefry, D. (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: non-clinical; color vision; photoreceptors

L- and M-cone isolating ERGs: LED versus CRT stimulation - Murray, I. J.; Kremers, Jan; Parry, N. R. A. (Visual Neuroscience, 2008)
Keywords: CRT; L-cones; Electroretinograms; M-cones; LED

Larger Descemetorhexis to Improve Graft Adhesion in Descemet Membrane Endothelial Keratoplasty Does Not Cause Postoperative Peripheral Corneal Edema - Tourtas, Theofilos; Weller, Julia M.; Bachmann, Björn; Kruse, Friedrich (Eye & Contact Lens-Science and Clinical Practice, 2015)
To evaluate the incidence of peripheral corneal edema after Descemet membrane endothelial keratoplasty (DMEK) with respect to the size of the descemetorhexis.A single-center retrospective review of data of 200 consecutive DMEK surgeries for Fuchs endothelial dystrophy was performed. Forty-eight eyes of 47 patients were enrolled in this study based on the presence of a peripheral zone of free denuded stroma between the margin of the graft and the host's Descemet membrane (DM) (group A) or a peripheral overlap between the graft and the host's DM (group B). In group A (n=26 eyes), the diameter of the descemetorhexis was approximately 10 mm, whereas in group B (n=22 eyes), the diameter was approximately 6 mm. Both groups received an 8-mm graft. Main outcome measures included peripheral corneal thickness (PCT) at 4 mm from the center, central corneal thickness (CCT), central-to-peripheral thickness ratio (CPTR), and endothelial cell density (ECD).Mean preoperative PCT±SD in group A was 728±52 ?m and in group B was 708±49 ?m (P=0.192). Four weeks after DMEK, mean PCT±SD was 703±43 ?m in group A and 691±59 ?m in group B (P=0.368). Mean preoperative CCT±SD was 642±53 ?m and 627±58 ?m in groups A and B, respectively (P=0.306). There was no significant difference in CCT between groups A and B 4 weeks after surgery (P=0.268). Mean preoperative CPTR±SD in group A was 0.88±0.05 and in group B was 0.89±0.05 (P=0.934). Four weeks after DMEK, CPTR was not significantly different between groups A and B (P=0.893). There was no significant difference in ECD between groups A and B, before and at 4 weeks after DMEK (P=0.093 and P=0.831, respectively).A larger descemetorhexis in DMEK resulting in a peripheral small zone of denuded stroma does not increase the incidence of peripheral corneal edema as compared with a small descemetorhexis with overlapping DMs.
EVALuna2:21238

Late complications after chemical burns of the ocular surface : Surgical strategies for ocular surface reconstruction - Bachmann, B.; Cursiefen, C. (Ophthalmologe, 2011)
Severe chemical burns of the ocular surface frequently result in long-standing and ongoing disorders of the conjunctiva and the cornea including conjunctival scarring with shortening of the fornix, cicatricial entropion, complications caused by trichiasis and scarring or chronic ulceration of the cornea. Advanced destruction of limbal stem cells leads to limbal stem cell deficiency with conjunctivalization of the cornea. Surgical therapy aims at the correction of malpositioning of the lids, the reconstruction of the conjunctiva and the fornix utilizing applicable tissue grafts and the reestablishment of a stable, avascular and transparent corneal epithelium by e.g. transplantation of epithelial stem cells. Progressive corneal ulcerations unresponsive to medical therapy can be treated by amniotic membrane transplantation, corneal transplantation or by conjunctival covering depending on the extent of damaged tissue. The surgical therapy of patients after severe chemical burns of the ocular surface is generally performed in specialized centers and occasionally requires a multidisciplinary approach.
EVALuna2:21050

Late-onset lattice corneal dystrophy without typical lattice lines caused by a novel mutation in the TGFBI gene - Oldak, Monika; Szaflik, Jacek P.; Sciezynska, Aneta; Udziela, Monika; Maksym, Radoslaw B.; Rymgayllo-Jankowska, Beata; Hofmann-Rummelt, Carmen; Menzel-Severing, Johannes; Ploski, Rafal; Zarnowski, Tomasz; Kruse, Friedrich; Szaflik, Jerzy (Cornea, 2014)
The aim of this study was to report the clinical, histopathological, and molecular findings in a patient with late-onset lattice corneal dystrophy (LCD) without typical lattice lines and a novel mutation in the TGFBI gene.Corneal lesions were visualized by slit-lamp examination and by in vivo confocal microscopy. Histopathological examination was performed on the patient's corneal specimen obtained during a deep anterior lamellar keratoplasty. By using genomic DNA as a template, all coding regions of the TGFBI gene were amplified and directly sequenced. The presence of the mutation was verified using restriction endonuclease digestion. Eight different computational methods and multiple sequence alignments were used to predict the pathogenicity of the novel genetic variant.The corneal phenotype was characterized by the presence within the stroma of round, oval, and short comma-shaped structures with indistinct margins. Lattice lines were not visible. Histopathological study revealed positive Congo red areas of amyloid deposits typical for LCD. A novel heterozygous missense mutation p.Leu565Pro was identified in exon 13 of the TGFBI gene. The amino acid substitution was unambiguously predicted to have a high pathogenic potential.The mutant codon 565 is located at the C-terminus in the region corresponding to a highly conserved amino acid in the fourth fascilin domain of the TGFBI protein. The novel variant expands the spectrum of TGFBI mutations causing LCD and located in this region. An increased number of known mutations will facilitate future studies of genotype-phenotype correlations and molecular pathogenesis of corneal dystrophies.
EVALuna2:21208

Lateral interactions in visual perception of temporal signals: Cortical and subcortical components - Teixeira, Claudio E.C.; Silveira, Luiz Carlos L.; Kremers, Jan (Psychology & Neuroscience, 2011)
Keywords: Dichoptic lateral interactions; Cortical interactions; Monoptic lateral interactions; Flicker perception; Temporal processing; Subcortical interactions

Length and width of the peripapillary scleral flange in relation to axial length and lamina cribrosa thickness - Jonas, Shefali B.; Jonas, Rahul Arvo; Holbach, Leonard; Jonas, Jost (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Levels of Aqueous Humor Trace Elements in Patients with Non-Exsudative Age-related Macular Degeneration: A Case-control Study - Jünemann, Anselm; Stopa, Piotr; Michalke, Bernhard; Chaudhri, Anwar; Reulbach, Udo; Huchzermeyer, Cord; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Zrenner, Eberhart; Rejdak, Robert (PLoS ONE, 2013)
Trace elements might play a role in the complex multifactorial pathogenesis of age-related macular degeneration (AMD). The aim of this study was to measure alterations of trace elements levels in aqueous humor of patients with non-exsudative (dry) AMD.For this pilot study, aqueous humor samples were collected from patients undergoing cataract surgery. 12 patients with dry AMD (age 77.9±6.62, female 8, male 4) and 11 patients without AMD (age 66.6±16.7, female 7, male 4) were included. Aqueous levels of cadmium, cobalt, copper, iron, manganese, selenium, and zinc were measured by use of Flow-Injection-Inductively-Coupled-Plasma-Mass-Spectrometry (FI-ICP-MS), quality controlled with certified standards.PATIENTS WITH AMD HAD SIGNIFICANTLY HIGHER AQUEOUS HUMOR LEVELS OF CADMIUM (MEDIAN: 0.70 µmol/L, IQR: 0.40-0.84 vs. 0.06 µmol/L; IQR: 0.01-.018; p = 0.002), cobalt (median: 3.1 µmol/L, IQR: 2.62-3.15 vs. 1.17 µmol/L; IQR: 0.95-1.27; p<0.001), iron (median: 311 µmol/L, IQR: 289-329 vs. 129 µmol/L; IQR: 111-145; p<0.001) and zinc (median: 23.1 µmol/L, IQR: 12.9-32.6 vs. 5.1 µmol/L; IQR: 4.4-9.4; p = 0.020) when compared with patients without AMD. Copper levels were significantly reduced in patients with AMD (median: 16.2 µmol/L, IQR: 11.4-31.3 vs. 49.9 µmol/L; IQR: 32.0-.142.0; p = 0.022) when compared to those without. No significant differences were observed in aqueous humor levels of manganese and selenium between patients with and without AMD. After an adjustment for multiple testing, cadmium, cobalt, copper and iron remained a significant factor in GLM models (adjusted for age and gender of the patients) for AMD.Alterations of trace element levels support the hypothesis that cadmium, cobalt, iron, and copper are involved in the pathogenesis of AMD.
EVALuna2:21116

Levels of aqueous humor trace elements in patients with open-angle glaucoma - Hohberger, Bettina; Chaudhri, Anwar; Michalke, Bernhard; Lucio, Marianna; Nowomiejska, Katarzyna; Schlötzer-Schrehardt, Ursula; Grieb, Pawel; Rejdak, Robert; Juenemann, Anselm G. M. (Journal of Trace Elements in Medicine and Biology, 2018)
PURPOSE: Trace elements might play a role in the complex multifactorial pathogenesis of open-angle glaucoma. The aim of this study was to analyze concentrations of trace elements in aqueous humor samples of patients with primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma (PEXG). PATIENTS AND METHODS: Thirty-three aqueous humor samples were obtained from patients undergoing cataract surgery: 12 patients with POAG (age 65.3±10.50, female 8, male 4), 10 patients with PEXG (age 65.9±11.27, female 6, male 4) and 11 patients without glaucoma (age 69.5±13.70, female 7, male 4) serving as controls. Aqueous humor levels of cadmium, iron, manganese, cobalt, copper and zinc were measured by Flow-Injection-Inductively-Coupled-Plasma-Mass-Spectrometry (FI-ICP-MS). RESULTS: From the statistical evaluation, we observed that patients with POAG had significantly higher aqueous humor levels of zinc (p=0.006) compared to controls. Increased aqueous humor levels of zinc were also observed in patients with PEXG in relation to control (p=0.0006). For iron we observed a significantly reduction in PEXG compared to control (p=0.002) and a significant difference between POAG and PEXG (p=0.0091). No significant differences were observed in aqueous humor levels of manganese, cobalt, copper, cadmium between glaucoma and control patients. No differences were seen for iron (POAG vs. controls). Analysis of trace element ratios was added. CONCLUSION: Significant differences in aqueous humor levels of zinc and iron between glaucoma and control patients support the hypothesis that these trace elements are involved in the pathogenesis of open-angle glaucoma.
EVALuna2:34759

Light and electron microscopic features of preclinical pseudoexfoliation syndrome - Suwan, Yanin; Kulnirandorn, Tuangporn; Schlötzer-Schrehardt, Ursula; Wongchaya, Sattawat; Petpiroon, Purit; Supakontanasan, Wasu; Tantraworasin, Apichat; Teekhasanee, Chaiwat (PLoS ONE, 2023)
Purpose This study sought to explore the features of the anterior lens capsule in patients with preclinical pseudoexfoliation syndrome (pPEX) via light microscopy (LM) and transmission electron microscopy (TEM). Design Cross-sectional, prospective, and observational case series. Methods We recruited consecutive patients with and without pPEX who underwent routine cataract surgery at Ramathibodi Hospital, between April 2018 and November 2020. pPEX can be characterized by pigmented spoke-wheel deposition (P) on the anterior lens capsule, midperiphery cleft/lacunae (C), faint central disc present within the photopic pupil (D), white-spoke pattern (W) noted at the midperiphery, and a combination of at least two signs (Co). LM and TEM were used to examine anterior lens capsule specimens for the presence of characteristic pseudoexfoliation material (PXM). The features of the anterior lens capsule in pPEX explored via LM and TEM were recorded. Results This study included a total of 96 patients (101 excised anterior lens capsules); among them, 34 (35 excised anterior lens capsules) exhibited pPEX signs (pPEX group) but 62 (66 excised anterior lens capsules) did not (control group). The patients had a mean age of 74 ± 7 (range, 58–89) years. LM and TEM revealed no definite PXM in any patient. In the pPEX group, LM analysis identified two capsule specimens with suspected PXM; PXM precursors were observed in 1 of the 34 excised capsule specimens analyzed via TEM. Furthermore, 39 eyes (59.09%) exhibited signs of true exfoliation syndrome (TEX) in LM analysis (12.82%, 25.64%, 10.26%, 10.26%, and 41.03% for patients exhibiting P, D, C, W, and Co, respectively). However, no TEX signs were observed in the control group. We found that the anterior lens capsules exhibiting C and D were significantly associated with TEX (odds ratio = 5.4 and 7.9; P = 0.007 and 0.004, respectively). Conclusions LM analysis revealed no definite PXMs were detected in the excised anterior lens capsules, whereas TEM analysis showed PXM precursors in one specimen (2.94%). Notably, a significant association was observed between C and D signs and TEX.
CRIS-Team Scopus Importer:2023-03-24

Limbal Stem Cells and their Niche: Implications for Bioengineered Tissue Constructs - Menzel-Severing, Johannes; Polisetti, N.; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich (Klinische Monatsblätter für Augenheilkunde, 2012)
Regeneration and repair of corneal epithelium rely on a reservoir of unipotent progenitor cells, which is situated within the basal epithelial layer at the corneoscleral limbus. If these cells are lost, corneal surface integrity is disturbed, which may lead to a painful loss of vision. Since the late 1990s cultivated grafts of limbal epithelium are being used therapeutically. Limbal epithelial cells are obtained from the fellow eye or from an allogeneic donor, propagated in culture on different types of carriers, and subsequently transplanted. This process entails removal of progenitor cells from their natural environment. However, surrounding cells and extracellular matrix are widely believed to provide important stimuli for stem cell maintenance and for correct differentiation. Therefore, new approaches aim at providing this so-called stem cell niche ex vivo and following transplantation. Niche factors can also drive transdifferentiation of alternative progenitor cell types towards a corneal phenotype. This permits the use of autologous cells in cases of bilateral limbal stem cell insufficiency. Several biosynthetic substrates have been devised for culture, transdifferentiation and transplantation of donor cells. This work intends to provide an overview of constructs that are currently available and to some extent clinically employed. In addition, a summary is given of novel concepts which aim at integrating putative niche factors into the stem cell carriers to replicate the stem cell niche.
EVALuna2:21097

Linking ERG recordings to psychophysical data in human subjects - Kremers, Jan; Aher, Avinash; Stuewe, Karin (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Linking lateral interactions in flicker perception to lateral geniculate nucleus cell responses - Kozyrev, Vladislav; Silveira, Luiz Carlos L.; Kremers, Jan (The Journal of Physiology, 2007)
The perception of flicker strength in a circular stimulus can be changed by altering the relative temporal phase of a simultaneously flickering surrounding annulus: perceived flicker is weak when the two stimuli are modulated in-phase and strong when the two are modulated in counter-phase. Previously, we found that responses of single neurons in the monkey lateral geniculate nucleus (LGN) to such stimuli resemble the psychophysical data. On the basis of the resemblance in data, it was proposed that the physiological basis for the flicker perception may be present as proximal as the LGN. To strengthen this hypothesis, we simulated the response of an array of LGN neurons, the receptive fields (RFs) of which are covered by the stimulus. The simulations were based upon single-cell recordings in the LGN of anaesthetized marmosets (Callithrix jacchus) using the same stimuli as previously. The measurements were repeated for different spatial displacement between the stimulus and the RF. The responses depended upon the spatial displacement and the relative phase between centre and surround stimuli. The neuronal responses can be adequately described by a difference-of-Gaussians (DOG) model with a time delay in the RF surround. The model responses at different displacements can be considered to be identical to the output of an array of ideal and identical LGN cells with different RF locations. To be able to describe physiological and psychophysical data, obtained at different stimulus contrasts, it was necessary to consider previously described non-linear interactions between the RF centres and surrounds. We applied a spatial peak-to-trough detector with a subsequent saturation and threshold to simulate a simple cortical decision mechanism. The output of this peak-to-trough detector could adequately describe the psychophysical data.

Liver-directed treatment is associated with improved survival and increased response to immune checkpoint blockade in metastatic uveal melanoma: results from a retrospective multicenter trial - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Eckstein, Markus; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers of Medicine, 2023)
Metastases of uveal melanoma (UM) spread predominantly to the liver. Due to low response rates to systemic therapies, liver-directed therapies (LDT) are commonly used for tumor control. The impact of LDT on the response to systemic treatment is unknown. A total of 182 patients with metastatic UM treated with immune checkpoint blockade (ICB) were included in this analysis. Patients were recruited from prospective skin cancer centers and the German national skin cancer registry (ADOReg) of the German Dermatologic Cooperative Oncology Group (DeCOG). Two cohorts were compared: patients with LDT (cohort A, n = 78) versus those without LDT (cohort B, n = 104). Data were analyzed for response to treatment, progression-free survival (PFS), and overall survival (OS). The median OS was significantly longer in cohort A than in cohort B (20.1 vs. 13.8 months; P = 0.0016) and a trend towards improved PFS was observed for cohort A (3.0 vs. 2.5 months; P = 0.054). The objective response rate to any ICB (16.7% vs. 3.8%, P = 0.0073) and combined ICB (14.1% vs. 4.5%, P = 0.017) was more favorable in cohort A. Our data suggest that the combination of LDT with ICB may be associated with a survival benefit and higher treatment response to ICB in patients with metastatic UM.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-CTLA-4; anti-PD-1; immune checkpoint blockade; liver-directed therapy; SIRT; uveal melanoma

L-/M-cone opponency in visual evoked potentials of human cortex - Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Gomes Martins, Cristiane Maria; Oliveria Bonci, Daniela Maria; Hauzman, Einat; Aher, Avinash; Tsai, Tina I.; Kremers, Jan; Ventura, Dora Fix (Journal of Vision, 2017)
L and M cones send their signals to the cortex using two chromatic (parvocellular and blue-yellow koniocellular) and one luminance (magnocellular) pathways. These pathways contain ON and OFF subpathways that respond to excitation increments and decrements respectively. Here, we report on visually evoked potentials (VEP) recordings that reflect L- and M-cone driven increment (LI and MI) and decrement (LD and MD) activity. VEP recordings were performed on 12 trichromats and four dichromats (two protanopes and two deuteranopes). We found that the responses to LI strongly resembled those to MD, and that LD and MI responses were very similar. Moreover, the lack of a photoreceptor type (L or M) in the dichromats led to a dominance of the ON pathway of the remaining photoreceptor type. These results provide electrophysiological evidence that antagonistic L/M signal processing, already present in the retina and the lateral geniculate nucleus (LGN), is also observed at the visual cortex. These data are in agreement with results from human psychophysics where MI stimuli lead to a perceived brightness decrease whereas LI stimuli resulted in perceived brightness increases. VEP recording is a noninvasive tool that can be easily and painlessly applied. We propose that the technique may provide information in the diagnosis of color vision deficiencies.
EVALuna2:21340

Local application of tropicamide 0.5% reduces retinal capillary blood flow - Harazny, Joanna M.; Schmieder, Roland; Welzenbach, Juergen; Michelson, Georg (Blood Pressure, 2013)
Abstract Introduction. Scanning laser Doppler flowmetry (SLDF) plays an important role in the study of arterial hypertension, diabetes and stroke. The technology enables non-invasive measurement of the retinal capillary perfusion (RCF), retinal haemodynamics and arteriolar morphology in human. The values can be measured in mydriasis or in non-mydriatic eyes. It is not clear whether the using of vasoactive mydriatica for pupil dilation affects the measured parameters in retina. Acetylcholine, a vasoactive neurotransmitter in human retina, affects the contractility of pericytes using muscarinic receptors and stimulates endothelial synthesis of nitric oxide (NO). We examined whether blockade of the retinal cholinergic receptors by tropicamide affects the RCF. Methods. We measured RCF in both eyes of 13 healthy subjects before and 30 min after the local application of one drop of 0.5% tropicamide to the right eye. The mean age of the group was 44 ± 14 years. The left eye was used as control. RCF was measured by Heidelberg retina flowmetry. Results. Thirty minutes after local application of one drop of 0.5% tropicamide to the right eye RCF decreased significantly (p = 0.001) by 31.9 ± 13% but did not change in the control eye. The maximal decrease was observed 20 min after application of the tropicamide. Conclusion. Locally administered tropicamide profoundly affects the RCF. Thus pupil dilatation impairs any assessment of retinal microcirculation.
EVALuna2:3619

Locally Adaptive Frames in the Roto-Translation Group and Their Applications in Medical Imaging - Duits, R.; Janssen, M. H J; Hannink, Julius; Sanguinetti, G. R. (Journal of Mathematical Imaging and Vision, 2016)
Locally adaptive differential frames (gauge frames) are a well-known effective tool in image analysis, used in differential invariants and PDE-flows. However, at complex structures such as crossings or junctions, these frames are not well defined. Therefore, we generalize the notion of gauge frames on images to gauge frames on data representations (Formula presented.) defined on the extended space of positions and orientations, which we relate to data on the roto-translation group SE(d), (Formula presented.). This allows to define multiple frames per position, one per orientation. We compute these frames via exponential curve fits in the extended data representations in SE(d). These curve fits minimize first- or second-order variational problems which are solved by spectral decomposition of, respectively, a structure tensor or Hessian of data on SE(d). We include these gauge frames in differential invariants and crossing-preserving PDE-flows acting on extended data representation U and we show their advantage compared to the standard left-invariant frame on SE(d). Applications include crossing-preserving filtering and improved segmentations of the vascular tree in retinal images, and new 3D extensions of coherence-enhancing diffusion via invertible orientation scores.
Keywords: Exponential curves; Gauge frames; Left-invariant image processing; Non-linear diffusion; Orientation scores; Roto-translation group

Long COVID: Association of Functional Autoantibodies against G-Protein-Coupled Receptors with an Impaired Retinal Microcirculation - Szewczykowski, Charlotte; Mardin, Christian; Lucio, Marianna; Wallukat, Gerd; Hoffmanns, Jakob; Schröder, Tim; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; Beitlich, Lorenz; Schottenhamml, Julia; et al. (International Journal of Molecular Sciences, 2022)
Long COVID (LC) describes the clinical phenotype of symptoms after infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Diagnostic and therapeutic options are limited, as the pathomechanism of LC is elusive. As the number of acute SARS-CoV-2 infections was and is large, LC will be a challenge for the healthcare system. Previous studies revealed an impaired blood flow, the formation of microclots, and autoimmune mechanisms as potential factors in this complex interplay. Since functionally active autoantibodies against G-protein-coupled receptors (GPCR-AAbs) were observed in patients after SARS-CoV-2 infection, this study aimed to correlate the appearance of GPCR-AAbs with capillary microcirculation. The seropositivity of GPCR-AAbs was measured by an established cardiomyocyte bioassay in 42 patients with LC and 6 controls. Retinal microcirculation was measured by OCT–angiography and quantified as macula and peripapillary vessel density (VD) by the Erlangen-Angio Tool. A statistical analysis yielded impaired VD in patients with LC compared to the controls, which was accentuated in female persons. A significant decrease in macula and peripapillary VD for AAbs targeting adrenergic β2-receptor, MAS-receptor angiotensin-II-type-1 receptor, and adrenergic α1-receptor were observed. The present study might suggest that a seropositivity of GPCR-AAbs can be linked to an impaired retinal capillary microcirculation, potentially mirroring the systemic microcirculation with consecutive clinical symptoms.
CRIS-Team Scopus Importer:2022-07-15
Keywords: chronic fatigue syndrome; COVID-19; functionally GPCR autoantibodies; glaucoma; Long-COVID syndrome; OCT–angiography

Longitudinal analysis of progression in glaucoma using spectral-domain optical coherence tomography - Wessel, Julia M.; Horn, Folkert; Tornow, Ralf-Peter; Schmid, Matthias; Mardin, Christian Y.; Kruse, Friedrich; Jünemann, Anselm; Lämmer, Robert (Investigative Ophthalmology & Visual Science, 2013)
To compare the longitudinal loss of RNFL thickness measurements by SD-OCT in healthy individuals and glaucoma patients with or without progression concerning optic disc morphology.A total of 62 eyes, comprising 38 glaucomatous eyes with open angle glaucoma and 24 healthy controls, were included in the study (Erlangen Glaucoma Registry, NTC00494923). All patients were investigated annually over a period of 3 years by Spectralis SD-OCT measuring peripapillary RNFL thickness. By masked comparative analysis of photographs, the eyes were classified into nonprogressive and progressive glaucoma cases. Longitudinal loss of RNFL thickness was compared with morphological changes of optic disc morphology.Mixed model analysis of annual OCT scans revealed an estimated annual decrease of the RNFL thickness by 2.12 ?m in glaucoma eyes with progression, whereas glaucoma eyes without progression in optic disc morphology lost 1.18 ?m per year in RNFL thickness (P = 0.002). The rate of change in healthy eyes was 0.60 ?m and thereby also significantly lower than in glaucoma eyes with progression (P < 0.001). The intrasession variability of three successive measurements without head repositioning was 1.5 ± 0.7 ?m. The loss of mean RNFL thickness exceeded the intrasession variability in 60% of nonprogressive eyes, and in 85% of progressive eyes after 3 years.LONGITUDINAL MEASUREMENTS OF RNFL THICKNESS USING SD-OCT SHOW A MORE PRONOUNCED REDUCTION OF RNFL THICKNESS IN PATIENTS WITH PROGRESSION COMPARED WITH PATIENTS WITHOUT PROGRESSION IN GLAUCOMATOUS OPTIC DISC CHANGES. (www.clinicaltrials.gov number, NTC00494923.).
EVALuna2:5384

Longitudinal retinal vessel loss indicates progressive grey matter atrophy in patients with relapsing remitting multiple sclerosis - Romahn, E. F.; Bussas, M.; Wiltgen, T.; Noll, C.; Wicklein, R.; Aly, L.; Berthele, A.; Mardin, Christian Y.; Kirschke, J. S.; Zimmer, C.; Korn, T.; Hemmer, B.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Longitudinal stability of the diurnal rhythm of intraocular pressure in subjects with healthy eyes, ocular hypertension and pigment dispersion syndrome - Huchzermeyer, Cord; Reulbach, Udo; Horn, Folkert; Lämmer, Robert; Mardin, Christian Y.; Jünemann, Anselm (Bmc Ophthalmology, 2014)
The diurnal fluctuation of intraocular pressure may be relevant in glaucoma. The aim of this study was to find out whether the timing of diurnal fluctuation is stable over the years.Long-term IOP data from the Erlangen Glaucoma Registry, consisting of several annual extended diurnal IOP profiles for each patient, was retrospectively analyzed. Normal subjects, patients with ocular hypertension and with pigment dispersion syndrome were included because these subjects had not been treated with antiglaucomatous medications at the time of data acquisition. A cosine curve was fitted to the IOP data and the stability of individual rhythms over the years was tested using the Rayleigh test. To compare the peak times among groups, means were calculated only from subjects with a significant Rayleigh test.Of the fifty-two eligible subjects, a total of 364 extended diurnal IOP profiles measured in a sitting position had been collected over a period of 114 ± 39 months. The Rayleigh test indicated intraindividual stability of phase timing only in 19 subjects (36%). In subjects with pigment dispersions syndrome, peak IOP occurred on average two hours and seven minutes later during the day compared with subjects without this condition (p = 0.05).Fitting of cosine curves to the clinical IOP profiles was generally feasible, although careful interpretation is warranted due to lack of measurements in supine position and between midnight and 7 am. The interesting observation of a phase lag in eyes with pigment dispersion syndrome warrants confirmation and exploration in future prospective studies. The analysis of the IOP data showed no stable individual rhythm in the long term in a majority of patients.
EVALuna2:21175

Long-term Clinical Outcome After Descemet Membrane Endothelial Keratoplasty - Schlögl, Andreas; Tourtas, Theofilos; Kruse, Friedrich; Weller, Julia M. (American Journal of Ophthalmology, 2016)
To evaluate the long-term clinical outcome up to 5 years after Descemet membrane endothelial keratoplasty (DMEK).Retrospective, consecutive case series.In this single-center study, 310 consecutive DMEK operations for endothelial decompensation were reviewed; 97 eyes of 84 patients met the inclusion criterion of a minimum 3-year follow-up. Retrospective evaluation of clinical examinations occurred at 1 and 3 months and annually up to 5 years after DMEK at the Department of Ophthalmology, Friedrich-Alexander-University Erlangen-Nürnberg, Erlangen (FAU), Germany. Main outcome measures were corrected distance visual acuity (CDVA), endothelial cell density (ECD), central corneal thickness (CCT), and graft survival (Kaplan-Meier analysis).Mean follow-up was 53 ± 13 months. CDVA improved from 0.62 ± 0.42 logMAR before DMEK to 0.13 ± 0.12 logMAR (P < .001); 57% of eyes without ocular comorbidities reached >=20/25 at 5 years after DMEK. ECD was stable after the initial postsurgical decrease (42% at 1 month, 44% at 5 years), from 2602 ± 243 cells/mm(2) before DMEK to 1460 ± 179 cells/mm(2) at 5 years. CCT decreased from 644 ± 67 ?m before DMEK to 557 ± 49 ?m at 5 years, with a minimum (530 ± 54 ?m) at 3 months. Cumulative probability of 5-year graft survival was 95%.The long-term sustainability of DMEK was confirmed. DMEK not only provides fast visual rehabilitation but maintains its clinical outcome within a follow-up of 5 years. Visual acuity and endothelial cell loss remain stable between 3 months and 5 years after DMEK.
EVALuna2:21324

Long Term Follow-Up of Preperimetric Open-Angle Glaucoma: Improvement of the Visual Field in Morphological Stable Patients Only - Jünemann, Anselm; Bellios, N.; Lämmer, Robert; Link, B.; Mardin, C. Y.; Kremers, Jan; Kruse, Friedrich; Horn, Folkert (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields

Long-term outcome after penetrating keratoplasty for bullous keratopathy - influence of preoperative visual acuity on final outcome - Reimer, A.; Langenbucher, A.; Cursiefen, Claus (Klinische Monatsblätter für Augenheilkunde, 2012)
The aim of this study was to analyse the long-term functional results of penetrating keratoplasty for pseudophacic bullous keratopathy and Fuchs endothelial dystrophy and to analyse the potential influence of the preoperative visual acuity on the final outcome.This retrospective study describes the postoperative results of 413 patients. 154 of them with bullous keratopathy and 259 patients with Fuchs dystrophy. All received penetrating excimer laser keratoplasty (PK).The results include the examination of the patients 1 / 3 / 5 / 8 / > 9 years postoperatively. For analysis the patients were divided in two groups: group I includes patients with a visual acuity <= 0.1 and group II with a visual acuity > 0.1. The trephination was performed using a 193 nm excimer laser. The transplanted cornea was fixed by using a double running cross-stitch suture. The outcome measures included best corrected visual acuity (CCV), keratometric equivalent (KEQ), keratometric astigmatism (AST), spherical equivalent (SEQ), refractive cylinder (CYL), best corrected visual acuity (BCVA), surface regularity index (SRI), surface asymmetry index (SAI), potential visual acuity (PVA), pachymetry (PAC), endothelial cell count (ECC), intraocular tension (TEN), topographic equivalent (T-EQ) and topographic astigmatism (T-AST).5 / 8 years postoperatively CCV was 0.55 / 0.58; KEQ was 43.75 / 45.64 D; SEQ - 0.88 /- 1.88 D; AST was 3.91 / 4.41 D; CYL was 3.09 / 3.40 D; ECC was 1230 / 1080 cells/mm (2); TEN was 13.61 / 14.36 mmHg; PAC was 593.21 / 579.50 µm; SRI was 1.08 / 0.89; SAI was 1.31 / 1.10; PVA was 0.77 / 0.83; T-EQ was 44.78 / 44.92 D and T-AST was 4.85 / 3.92 D. The outcome of patients with a preoperative visual acuity of <<= 0.1 was significantly worse than the group with the visual acuity of > 0.1.This study shows that the long-term results after penetrating keratoplasty for pseudophacic bullous keratopathy and Fuchs endothelial dystrophy are good. Patients with preoperative visual acuity of <= 0.1 had worse final results.
EVALuna2:21055

Low- vs. high-dose radiotherapy in Graves’ ophthalmopathy: a retrospective comparison of long-term results - Weissmann, Thomas; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Bert, Christoph; Schmidt, Manfred; Kruse, Friedrich; Ott, Oliver; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Putz, Florian (Strahlentherapie und Onkologie, 2021)
Purpose: Radiotherapy represents an effective treatment option in Graves’ ophthalmopathy (GO), leading to palliation of clinical symptoms. However, there are only a limited number of trials comparing the effectiveness of low- vs. high-dose radiotherapy. Methods: We analyzed 127 patients treated with radiotherapy for stage 3/4 GO (NOSPECS classification). Patients were treated with single doses of 2.0 Gy (cumulative dose 20 Gy) until 2007, afterwards a single dose of 0.8 Gy (cumulative dose 4.8 Gy) was applied. With a median follow-up-time of 9.0 years, the treatment efficacy (overall improvement, sense of eye pressure, lid edema, ocular motility, exophthalmos, subjective vision, and diplopia) and adverse effects were analyzed by a standardized survey. Results: Overall, 63.8% described improvement of symptoms after radiotherapy. No significant differences in overall treatment response and improvement of main outcome measures between low- or high-dose radiotherapy treatments are detectable, while low-dose radiotherapy leads significantly more often to retreatment (13.1% vs. 1.7%, p = 0.016). The main independent predictor of treatment response is the presence of lid edema (odds ratio, OR, 3.53; p = 0.006). Conclusion: At long-term follow-up, the majority of patients reported palliation of symptoms with limited adverse effects, suggesting clinical effectiveness of radiotherapy for amelioration of GO symptoms independent of low- or high-dose radiotherapy.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Exophthalmos; Graves’ ophthalmopathy; Low dose radiation therapy; Radiotherapy; Thyroid eye disease

LOXL1 deficiency in the lamina cribrosa as candidate susceptibility factor for a pseudoexfoliation-specific risk of glaucoma - Schlötzer-Schrehardt, Ursula; Hammer, Christian; Krysta, Anita W.; Hofmann-Rummelt, Carmen; Pasutto, Francesca; Sasaki, Takako; Kruse, Friedrich; Zenkel, Matthias (Ophthalmology, 2012)
To test the hypothesis that a primary disturbance in lysyl oxidase-like 1 (LOXL1) and elastin metabolism in the lamina cribrosa of eyes with pseudoexfoliation syndrome constitutes an independent risk factor for glaucoma development and progression.Observational, consecutive case series.Posterior segment tissues obtained from 37 donors with early and late stages of pseudoexfoliation syndrome without glaucoma, 37 normal age-matched control subjects, 5 eyes with pseudoexfoliation-associated open-angle glaucoma, and 5 eyes with primary open-angle glaucoma (POAG).Protein and mRNA expression of major elastic fiber components (elastin, fibrillin-1, fibulin-4), collagens (types I, III, and IV), and lysyl oxidase crosslinking enzymes (LOX, LOXL1, LOXL2) were assessed in situ by quantitative real-time polymerase chain reaction, (immuno)histochemistry, and light and electron microscopy. Lysyl oxidase-dependent elastin fiber assembly was assessed by primary optic nerve head astrocytes in vitro.Expression levels of elastic proteins, collagens, and lysyl oxidases in the lamina cribrosa.Lysyl oxidase-like 1 proved to be the major lysyl oxidase isoform in the normal lamina cribrosa in association with a complex elastic fiber network. Compared with normal and POAG specimens, lamina cribrosa tissues obtained from early and late stages of pseudoexfoliation syndrome without and with glaucoma consistently revealed a significant coordinated downregulation of LOXL1 and elastic fiber constituents on mRNA and protein level. In contrast, expression levels of collagens and other lysyl oxidase isoforms were not affected. Dysregulated expression of LOXL1 and elastic proteins was associated with pronounced (ultra)structural alterations of the elastic fiber network in the laminar beams of pseudoexfoliation syndrome eyes. Inhibition of LOXL1 interfered with elastic fiber assembly by optic nerve head astrocytes in vitro.The findings provide evidence for a pseudoexfoliation-specific elastinopathy of the lamina cribrosa resulting from a primary disturbance in LOXL1 regulation and elastic fiber homeostasis, possibly rendering pseudoexfoliation syndrome eyes more vulnerable to pressure-induced optic nerve damage and glaucoma development and progression.
EVALuna2:1645

Luminance white noise electroretinograms (wnERGs) in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in neuroscience, 2022)
PurposeTo record and analyse electroretinograms (ERGs) to luminance stimuli with white noise temporal profiles in mice. White noise stimuli are expected to keep the retina in a physiologically more natural state than, e.g., flashes. The influence of mean luminance (ML) was studied. MethodsElectroretinograms to luminance temporal white noise (TWN) modulation (wnERGs) were measured. The white noise stimuli contained all frequencies up to 20 Hz with equal amplitudes and random phases. Responses were recorded at 7 MLs between -0.7 and 1.2 log cd/m(2). Impulse response functions (IRFs) were calculated by cross correlating the averaged white noise electroretinogram (wnERG) responses with the stimulus. Amplitudes and latencies of the initial trough and subsequent peak in the IRFs were measured at each ML. Fourier transforms of the IRFs resulted in modulation transfer functions (MTFs). wnERGs were averaged across different animals. They were measured twice and the responses at identical instances in the 1st and 2nd recordings were plotted against each other. The correlation coefficient (r(repr)(2)) of the linear regression quantified the reproducibility. The results of the first and second measurement were further averaged. To study the underlying ERG mechanisms, the ERG potentials at the different MLs were plotted against those at the lowest and highest ML. The correlation coefficients (r(ML)(2)) were used to quantify their similarities. ResultsThe amplitudes of the initial (a-wave-like) trough of the IRFs increased with increasing ML. The following positive (b-wave-like) peak showed a minimum at -0.4 log cd/m(2) above which there was a positive correlation between amplitude and ML. Their latencies decreased monotonously with increasing ML. In none of the IRFs, oscillatory potential (OP)-like components were observed. r(repr)(2) values were minimal at a ML of -0.1 log cd/m(2), where the MTFs changed from low-pass to band-pass. r(ML)(2) values increased and decreased with increasing ML when correlated with responses obtained at the highest or the lowest ML, respectively. ConclusionWhite noise electroretinograms can be reliably recorded in mice with luminance stimuli. IRFs resemble flash ERGs superficially, but they offer a novel procedure to study retinal physiology. New components can be described in the IRFs. The wnERGs are either rod- or cone-driven with little overlap.
CRIS-Team WoS Importer:2023-01-06

Macular Bruch's membrane defects and axial length: association with gamma zone and delta zone in peripapillary region - Jonas, Jost B.; Ohno-Matsui, Kyoko; Spaide, Richard F.; Holbach, Leonard; Panda-Jonas, Songhomitra (Investigative Ophthalmology & Visual Science, 2013)
To examine histomorphometrically the macular region of highly myopic eyes.On horizontal anterior-posterior histological sections, we examined the posterior pole of 138 human globes (axial length: 20-35 mm). In the parapapillary region, we differentiated between the beta zone (Bruch's membrane without RPE), gamma zone (parapapillary region without Bruch's membrane), and delta zone (elongated and thinned gamma zone).In 12 (8.7%) eyes, a macular Bruch's membrane defect (MBMD) was detected. The MBMD showed a complete lack of RPE and choriocapillaris, and an almost complete lack of photoreceptors. Presence of MBMD was associated with longer axial length (P < 0.001), longer gamma zone (P = 0.04) and delta zone (P < 0.001), thinner peripapillary scleral flange, and thinner sclera just outside of the optic nerve meninges (P < 0.001) and at the posterior pole (P < 0.001). An MBMD was found only in eyes with an axial length of 27 mm or longer. MBMD prevalence in highly myopic eyes was 12/39 or 30.8%. MBMD presence was not significantly related to length of beta zone (P = 0.09). In multivariate binary regression analysis, MBMD presence was significantly (P < 0.001) associated only with axial length.Highly myopic eyes (axial length >=27mm) can show an MBMD associated with complete loss of RPE and choriocapillaris, and marked reduction of photoreceptors and large choroidal vessels. MBMD presence was strongly associated with axial length and indirectly with parapapillary gamma zone and delta zone. The myopia-associated secondary MBMDs may occur parallel to the myopia-associated widening of Bruch's membrane opening around the optic nerve head.
EVALuna2:21118

Macular pigment optical density measured by heterochromatic modulation photometry - Huchzermeyer, Cord; Schlomberg, Juliane; Welge-Lüssen, Ulrich-Christoph; Berendschot, Tos T. J. M.; Pokorny, Joel; Kremers, Jan (PLoS ONE, 2014)
To psychophysically determine macular pigment optical density (MPOD) employing the heterochromatic modulation photometry (HMP) paradigm by estimating 460 nm absorption at central and peripheral retinal locations.For the HMP measurements, two lights (B: 460 nm and R: 660 nm) were presented in a test field and were modulated in counterphase at medium or high frequencies. The contrasts of the two lights were varied in tandem to determine flicker detection thresholds. Detection thresholds were measured for different R:B modulation ratios. The modulation ratio with minimal sensitivity (maximal threshold) is the point of equiluminance. Measurements were performed in 25 normal subjects (11 male, 14 female; age: 30±11 years, mean ± sd) using an eight channel LED stimulator with Maxwellian view optics. The results were compared with those from two published techniques - one based on heterochromatic flicker photometry (Macular Densitometer) and the other on fundus reflectometry (MPR).We were able to estimate MPOD with HMP using a modified theoretical model that was fitted to the HMP data. The resultant MPODHMP values correlated significantly with the MPODMPR values and with the MPODHFP values obtained at 0.25° and 0.5° retinal eccentricity.HMP is a flicker-based method with measurements taken at a constant mean chromaticity and luminance. The data can be well fit by a model that allows all data points to contribute to the photometric equality estimate. Therefore, we think that HMP may be a useful method for MPOD measurements, in basic and clinical vision experiments.
EVALuna2:21179

Macular Vessel Density and Foveal Avascular Zone Metrics Using Optical Coherence Tomography Angiography in Fabry Disease. Long Term Follow Up - Hufendiek, Katerina; Lindziute, Migle; Kaufeld, Jessica; Volkmann, Ingo Roland; Brockmann, Dorothee; Hosari, Sami; Hohberger, Bettina; Mardin, Christian Y.; Framme, Carsten; Tode, Jan; Hufendiek, Karsten (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Management of Late Descemet's Membrane Detachment after Penetrating Keratoplasty in Keratoconus - Weller, Julia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos (Cornea, 2022)
Purpose:The purpose of this study was to describe the feasibility of Descemet membrane endothelial keratoplasty (DMEK) as a treatment modality for spontaneous detachment of DM (DMD) decades after penetrating keratoplasty (PK) for keratoconus.Methods:We describe the clinical characteristics and therapeutic surgical approach in 6 eyes of 5 patients with DMD. Clinical images, anterior segment optical coherence tomography scans, and histological findings are presented.Results:Mean age of patients at time of diagnosis was 60 years (range 56-66 years). Mean interval between PK and occurrence of DM detachment was 36 years (range 29-45 years). In 4 of 6 eyes, air injections into the anterior chamber were initially attempted to reattach DM to the stroma but without long-lasting effect. Two eyes underwent repeat PK because of pronounced ectasia after long-standing DMD and stromal scars. DMEK was performed successfully in 4 eyes leading to an increase in visual acuity and a reduction in central corneal thickness. Electron microscopy showed abnormal vacuolar inclusions and collagenous material in the posterior nonbanded layer and a separation of the anterior banded layer from the posterior nonbanded layer.Conclusions:This case series provides evidence that DMEK is a viable option in eyes with spontaneous DM detachment after PK. Visual outcome is limited by the persisting high astigmatism in the ectatic cornea. Illustrated by a small series of patients, the results of DMEK in this condition are presented and new findings about the pathophysiology are given.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Descemet membrane detachment; DMEK; keratoconus

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Mapping of the electrospinning parameters for PLGA-Nanofibers - Regelmann, Christian; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Measurement of individual changes in the performance of human stereoscopic vision for disparities at the limits of the zone of comfortable viewing - Paulus, Jan; Michelson, Georg; Hornegger, Joachim; Eskofier, Björn; Schmidt, Michael; et al. (2013 International Conference on 3D Vision - 3DV 2013, 2013)
3D displays enable immersive visual impressions but the impact on the human perception still is not fully understood. Viewing conditions like the convergence-accommodation (C-A) conflict have an unnatural influence on the visual system and might even lead to visual discomfort. As visual perception is individual we assumed the impact of simulated 3D content on the visual system to be as well. In this study we aimed to analyze the stereoscopic visual performance of 17 subjects for disparities inside and outside the in literature defined zone of comfortable viewing to provide an individual evaluation of the impact of increased disparities on the performance of the visual system. Stereoscopic stimuli were presented in a four-alternative forced choice (4AFC) setup in different disparities. The response times as well as the correct decision rates indicated the performance of stereoscopic vision. The results showed that increased disparities lead to a decline in performance. Further, the impact of the presented disparities is dependent on the difficulty of the task. The decline of performance as well as the deciding disparities for the decline were subject dependent. © 2013 IEEE.
UnivIS-Import:2017-01-09:Pub.2013.tech.IMMD.IMMD5.measur_1
Keywords: 3D displays; 3D perception; stereo vision; stereopsis; visual discomfort

Measurement of retinal wall-to-lumen ratio by adaptive optics retinal camera: a clinical research - Meixner, Eva; Michelson, Georg (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
To measure the wall-to-lumen ratio (WLR) and the cross-sectional area of the vascular wall (WCSA) of retinal arterioles by an Adaptive Optics (AO) retinal camera.Forty-seven human subjects were examined and their medical history was explored. WLR and WCSA were measured on the basis of retinal arteriolar wall thickness (VW), lumen diameter (LD) and vessel diameter (VD) assessed by rtx1 Adaptive Optics retinal camera. WLR was calculated by the formula [Formula: see text]. Arterio-venous ratio (AVR) and microvascular abnormalities were attained by quantitative and qualitative assessment of fundus photographs. Influence of age, arterial hypertension, body mass index (BMI) and retinal microvascular abnormalities on the WLR was examined. An age-adjusted WLR was created to test influences on WLR independently of age. Considering WLR and WCSA, a distinction between eutrophic and hypertrophic retinal remodeling processes was possible.The intra-observer variability (IOV) was 6 % ± 0.9 for arteriolar wall thickness and 2 % ± 0.2 for arteriolar wall thickness plus vessel lumen. WLR depended significantly on the wall thickness (r = 0.715; p < 0.01) of retinal arterioles, but was independent of the total vessel diameter (r = 0.052; p = 0.728). WLR correlated significantly with age (r = 0.769; p < 0.01). Arterial hypertension and a higher BMI were significantly associated with an increased age-adjusted WLR. WLR correlated significantly with the stage of microvascular abnormalities. 55 % of the hypertensive subjects and 11 % of the normotensive subjects showed eutrophic remodeling, while hypertrophic remodeling was not detectable. WLR correlated inversely with AVR. AVR was independent of the arteriolar wall thickness, age and arterial hypertension.The technique of AO retinal imaging allows a direct measurement of the retinal vessel wall and lumen diameter with good intra-observer variability. Age, arterial hypertension and an elevated BMI level are significantly associated with an increased WLR. The wall-to-lumen ratio measured by AO can be used to detect structural retinal microvascular alterations in an early stage of remodeling processes.
EVALuna2:21242

Measuring retinal function in the mouse - Kremers, Jan; Tanimoto, Naoyuki (Mouse Retinal Phenotyping, 2018)
Keywords: Anesthesia; B-wave; A-wave; Analysis; ERG; Oscillatory potentials; Electroretinogram; Equipment; Stimulators

Medicinal glaucoma therapy. What can we learn from large randomized clinical trials? - Jünemann, Anselm; Huchzermeyer, Cord; Rejdak, R. (Ophthalmologe, 2013)
The prospective multicenter randomized controlled clinical trials (RCTs) Ocular Hypertension Glaucoma Treatment Study (OHTS), Early Manifest Glaucoma Trial (EMGT), Advanced Glaucoma Intervention Study (AGIS), Collaborative Initial Glaucoma Treatment Study (CITGS) and Collaborative Normal Tension Glaucoma Study (CNGTS) are often named as landmarks for glaucoma management as the results of these studies provided the evidence for numerous therapeutic decisions in clinical practice. The studies confirmed the consensus that reduction of intraocular pressure reduces the risk of glaucoma progression covering the whole spectrum of glaucoma from ocular hypertension to advanced glaucoma. Furthermore, the identification of new risk factors allows a higher precision of assessment of the risk of progression. The RCTs achieved the main goal of high level of evidence, thus making progress in the understanding of glaucoma and its treatment and bridging consensus-based and evidence-based decisions. However, the implementation of the results into clinical practice needs adequate and accurate interpretation of the results.
EVALuna2:21167

Melanocytes as an emerging key player in niche regulation of limbal stem cells - Schlötzer-Schrehardt, Ursula; Polisetti, Naresh; Zenkel, Matthias; Naschberger, Elisabeth; Heger, Lukas; Dudziak, Diana; Stürzl, Michael; Kruse, Friedrich (2018)
EVALuna2:34738

Melanocytes as emerging key players in niche regulation of limbal epithelial stem cells - Polisetti, Naresh; Gießl, Andreas; Zenkel, Matthias; Heger, Lukas; Dudziak, Diana; Naschberger, Elisabeth; Stich, Lena; Steinkasserer, Alexander; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Ocular Surface, 2021)
Purpose: Limbal melanocytes (LMel) represent essential components of the corneal epithelial stem cell niche and are known to protect limbal epithelial stem/progenitor cells (LEPCs) from UV damage by transfer of melanosomes. Here, we explored additional functional roles for LMel in niche homeostasis, immune regulation and angiostasis. Methods: Human corneoscleral tissues were morphologically analyzed in normal, inflammatory and wound healing conditions. The effects of LMel on LEPCs were analyzed in direct and indirect co-culture models using electron microscopy, immunocytochemistry, qRT-PCR, Western blotting and functional assays; limbal mesenchymal stromal cells and murine embryonic 3T3 fibroblasts served as controls. The immunophenotype of LMel was assessed by flow cytometry before and after interferon-γ stimulation, and their immunomodulatory properties were analyzed by mixed lymphocytes reaction, monocyte adhesion assays and cytometric bead arrays. Their angiostatic effects on human umbilical cord endothelial cells (HUVECs) were evaluated by proliferation, migration, and tube formation assays. Results: LMel and LEPCs formed structural units in the human limbal stem cell niche in situ, which could be functionally replicated, including melanosome transfer, by co-cultivation in vitro. LMel supported LEPCs during clonal expansion and during epithelial wound healing by stimulating proliferation and migration, and suppressed their differentiation through direct contact and paracrine effects. Under inflammatory conditions, LMel were increased in numbers and upregulated expression of ICAM-1 and MHC II molecules (HLA-DR), but lacked expression of HLA-G, -DP, -DQ and costimulatory molecules CD80 and CD86. They were also found to be potent suppressors of alloreactive T- cell proliferation and cytokine secretion, which largely depended on direct cell-cell interaction. Moreover, the LMel secretome exerted angiostatic activity by inhibiting vascular endothelial cell proliferation and capillary network formation. Conclusion: These findings suggest that LMel are not only professional melanin-producing cells, but exert various non-canonical functions in limbal niche homeostasis by regulating LEPC maintenance, immune responses, and angiostasis. Their potent regulatory, immunomodulatory and anti-angiogenic properties may have important implications for future regenerative cell therapies.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Angiostasis; Immune regulation; Inflammation; Limbal niche; Limbal stem cells; Melanocytes; Wound healing

Melanopsin interacting with the cone-mediated white noise electroretinogram (wnERG) - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix K. (Investigative Ophthalmology & Visual Science, 2018)

Melatonin analogue agomelatine reduces rabbit's intraocular pressure in normotensive and hypertensive conditions - Martinez-Aguila, Alejandro; Fonseca, Begona; Bergua, Antonio; Pintor, Jesus (European Journal of Pharmacology, 2013)
In the search for new compounds to reduce intraocular pressure (IOP), with fewer side effects, we have found that agomelatine, a melatonin analogue, can reduce IOP being, therefore, interesting for the treatment of ocular hypertension and glaucoma. In normotensive conditions, agomelatine (10?l 100?M) reduced IOP by 20.8±1.4% (n=18) with a maximal effect 180min after the compound application and 68.8±5.7% (n=8) in a hypertensive condition. Concentration-response curve depicted a sigmoid behaviour presenting a pD2 value of 9.7±0.3 which was equivalent to an EC50 of 0.19nM. The effect of agomelatine was partially antagonized by 4PPDOT (MT2 antagonist receptor. 10?l 100?M) and prazosin (MT3 antagonist receptor. 10?l 100?M) (85.6±1.6% and 87.2±1.9%, N=18 respectively.) Agomelatine hypotensive effect in normotensive condition was comparable to latanoprost (40?l) and brimonidine (40?l) and it was no so effective as dorzolamide (40?l) or timolol (40?l). These results may suggest the use of this melatonin analogue for the treatment of those ocular conditions, which involve an abnormal raise of intraocular pressure.
EVALuna2:21136

Mesopic and Photopic Rod and Cone Photoreceptor-Driven Visual Processes in Mice With Long-Wavelength-Shifted Cone Pigments - Tsai, Tina I.; Joachimsthaler, Anneka; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)
The clearer divergence in spectral sensitivity between native rod and human L-cone (L*-cone) opsins in the transgenic Opn1lwLIAIS mouse (LIAIS) allows normal visual processes mediated by these photoreceptor subtypes to be isolated effectively using the silent substitution technique. The objective of this study was to further characterize the influence of mean luminance and temporal frequency on the functional properties of signals originating in each photoreceptor separately and independently of adaptation state in LIAIS mice.Electroretinographic (ERG) recordings to sine-wave rod and L*-cone modulation at different mean luminances (0.1-130.0 cd/m2) and temporal frequencies (6-26 Hz) were examined in anesthetized LIAIS (N = 17) and C57Bl/6 mice (N = 8).We report maximum rod-driven response with 8-Hz modulation at 0.1 to 0.5 cd/m2, which was almost four times larger than maximum cone-driven response at 8 Hz, 21.5 to 130 cd/m2. Over these optimal luminances, both rod- and cone-driven response amplitudes exhibited low-pass functions with similar frequency resolution limits, albeit their distinct luminance sensitivities. There were, however, two distinguishing features: (1) the frequency-dependent amplitude decrease of rod-driven responses was more profound, and (2) linear relationships describing rod-driven response phases as a function of stimulus frequency were steeper.Employing the silent substitution method with stimuli of appropriate luminance on the LIAIS mouse (as on human observers) increases the specificity, robustness, and scope to which photoreceptor-driven responses can be reliably assayed compared to the standard photoreceptor isolation methods.
EVALuna2:21338
Keywords: Cone; Photoreceptor isolation; Rod; Electrophysiology; Mouse model

Mesopic rod and S-cone interactions revealed by modulation thresholds - Zele, Andrew J.; Kremers, Jan; Feigl, Beatrix (Journal of the Optical Society of America A-Optics Image Science and Vision, 2012)
We analyzed mesopic rod and S-cone interactions in terms of their contributions to the blue-yellow opponent pathway. Stimuli were generated using a four-primary colorimeter. Mixed rod and S-cone modulation thresholds (constant L-, M-cone excitation) were measured as a function of their phase difference. Modulation amplitude was equated using threshold units and contrast ratios. This study identified three interaction types: (1) a linear and antagonistic rod:S-cone interaction, (2) probability summation, and (3) a previously unidentified mutual nonlinear reinforcement. Linear rod:S-cone interactions occur within the blue-yellow opponent pathway. Probability summation involves signaling by different postreceptoral pathways. The origin of the nonlinear reinforcement is possibly at the photoreceptors.
EVALuna2:21077

Messung der „visuellen Performance“ hinsichtlich des 3D-Sehens - Michelson, Georg; Schoemann, Johannes; Paulus, Jan; Lochmann, Matthias (Jahrestagung dvs-Kommission Fußball 2015, 2015)

Metabolic profile of porcine corneas after photodynamic cross-linking treatment - Kryczka, Tomasz; Sel, Saadettin; Wollensak, Gregor; Midelfart, Anna (Acta Ophthalmologica, 2012)
EVALuna2:21104

Microbubble incision as a new rescue technique for big-bubble deep anterior lamellar keratoplasty with failed bubble formation - Riss, Stephan; Heindl, Ludwig M.; Bachmann, Bjoern O.; Kruse, Friedrich; Cursiefen, Claus (Cornea, 2013)
To describe a new surgical technique allowing dissection down to Descemet membrane in big-bubble deep anterior lamellar keratoplasty (DALK) with failed big-bubble formation (the "microbubble incision technique").This is an interventional case series of 10 consecutive patients with keratoconus undergoing intended big-bubble DALK with failure to establish a normal big bubble. In all patients, repeated air injections into the stroma were performed, leaving a whitish colored stroma. Lamellar dissection as far down as possible was then performed within this white tissue. As soon as the anterior chamber was visible, a large remaining intrastromal air bubble was incised with a sharp 15-degree knife introduced perpendicular to the tissue to open up this predescemetic bubble. If deeper air bubbles were still visible, this approach was repeated. Using a blunt spatula, this new layer was then prepared and viscodissection performed.Using this novel approach, in 9 of the 10 patients, it was possible to dissect down to Descemet membrane. Macroperforation made conversion to penetrating keratoplasty necessary in 1 patient. Microperforations not necessitating conversion occurred in 2 patients. All 9 patients with "rescued" DALK had an uneventful postoperative course and had a mean visual acuity of 20/63 ± 20/125 (range, 20/500-20/50) and a mean endothelial cell count of 1672 ± 163 cells per square millimeter (range, 1493-1867 cells/mm) at 3 months.Microbubble incision is a new rescue technique for big-bubble DALK patients without bubble formation allowing for a safer dissection down to Descemet membrane.
EVALuna2:21090

Microvascular effects of the inhibition of dipeptidylpeptidase IV by linagliptin in nondiabetic hypertensive patients - Forst, Thomas; Michelson, Georg; Diessel, Stephan; Jahnke, Johannes; Kapitza, Christoph (Journal of Hypertension, 2016)
Recent studies suggest vascular benefits of dipeptidylpeptidase IV (DPP-IV) inhibition in patients with diabetes mellitus. Only little is known about potential vascular effects of DPP-IV inhibitors in nondiabetic individuals. The aim of this study was to investigate the effect of DPP-IV inhibition in a nondiabetic hypertensive population.This was a double-blinded, randomized, placebo-controlled, mechanistic study, comparing microvascular effects of the DPP-IV inhibitor linagliptin with placebo in nondiabetic individuals with a history of arterial hypertension. Twenty-one patients received 5 mg linagliptin (5 women; age 67.6 ± 6.0 years; mean ± SD), whereas 22 patients were randomized to placebo (5 women; age 64.8 ± 7.1 years).At baseline, after 6 and 12 weeks, retinal microcirculation and arterial blood pressure profiles were assessed. Moreover, blood samples were taken for the measurement of HbA1c, asymmetric dimethylarginine, C-reactive peptide, cyclic guanosinmonophosphate, transforming growth factor beta (TGF-ß1) and cystatin C. Retinal capillary perfusion increased by 23.7 ± 10.3% (mean ± SEM; P < 0.05), retinal arterial flow by 7.6 ± 0.6 (P < 0.05) and the retinal hyperemic response by 290 ± 263% (P < 0.05) during treatment with linagliptin. No change in retinal blood flow was found in the placebo group. Although blood pressure declined in both groups, a significant decline in TGF-ß1 by 9.3 ± 4.5% (P < 0.05) could only be observed in the linagliptin group. No significant change in other laboratory parameters could be observed in both groups.Our study suggests microvascular and antifibrotic effects of linagliptin in a nondiabetic, hypertensive population.
EVALuna2:21245

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

MIGS – eine Off-label-Option für eine therapierefraktäre, steroidinduzierte okuläre Hypertension - Hohberger, Bettina; Haug, Marius; Bergua, Antonio; Lämmer, Robert (Ophthalmologe, 2019)
Steroid-induced ocular hypertension (SIOH), which cannot be regulated by topical antiglaucoma agents, is a rare complication after intravitreal implantation of diverse cortisone derivatives. This case report presents a therapeutic approach for treatment-refractory SIOH after intravitreal implantation of fluocinolone acetonide using various minimally invasive glaucoma surgery (MIGS) techniques.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Glaucoma; iStent inject; MIGS; Ocular hypertension; Xen gel stent

MIGS: therapeutic success of combined Xen Gel Stent implantation with cataract surgery - Hohberger, Bettina; Welge-Luessen, Ulrich-Christoph; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: Glaucoma, a common disease in the elderly population, is frequently coexistent with cataract. While the combination of filtration surgery and cataract surgery is a challenging topic with limited success, minimal invasive glaucoma surgery (MIGS), such as Xen Gel Stents, seems to provide promising results. The aim of this study was to investigate the complete and qualified therapeutic success of Xen Gel Stent implantation with (XenPhaco) and without cataract surgery. METHODS: One hundred and eleven open-angle glaucoma eyes underwent implantation of Xen45 Gel Stent (AqueSys, Inc.) with or without cataract operation. Complete therapeutic success was defined as target intraocular pressure (IOP) < 18 mmHg at any time point within 6 months of follow-up without local antiglaucomatous therapy or further surgical interventions. Qualified success was defined as target IOP <18 mmHg with additional 1-2 local antiglaucomatous eye drops. Failure included all cases with the necessity of at least three local antiglaucomatous eye drops or additional glaucoma surgery. RESULTS: Combined implantation of Xen Gel Stent with cataract surgery was performed in 30 eyes and stand-alone Xen Gel Stent implantation was performed in 81 eyes. A complete therapeutic success was achieved in 46.9% of single Xen Gel Stent implantation, whereas 53.3% was reached with combined XenPhaco. Qualified success was seen in 2.5% in the eyes of the single Xen Gel Stent implantation group and in 3.3% of the combined surgery group. Therapeutic failure rate was 49.4% in the stand-alone group vs 46.7% in the combined group. Data were not significantly different for group and subgroup analyses. CONCLUSIONS: Complete and qualified therapeutic success is similar for the combination of Xen Gel Stent implantation with and without cataract surgery in open-angle glaucoma patients. MIGS using Xen Gel Stent can be recommended in situations if glaucoma surgery is indicated besides coexisting cataract.
EVALuna2:34754

Minderung der Erwerbsfähigkeit bei der Berufskrankheit 5103: Trends und Vergleich der Begutachtungspraxis von 2010 – 2015 - Hiller, Julia; Braun, Michael; Drexler, Hans (Dermatologie in Beruf und Umwelt, 2016)
Introduction: New recommendations for the assessment of the loss of earning capacity (LEC) were compiled after "squamous cell carcinoma and multiple actinic keratoses of the skin through natural UV radiation" and introduced as an occupational disease (BK 5103) in Germany in January 2015. The practice of medical reporting and principles for the estimation of LEC were analyzed. Methods: 108 consecutive medical expert reports from 2010 until July 2015 were identified and the LEC as well as further data were recorded. Additionally the data were used to determine and compare the LEC according to the two available assessment charts. Results: Recognition as an occupational disease was recommended for 59,2% of the collective and the LEC was predominantly (> 80%) rated with less than 20%. A comparison between the LEC values determined by the two varying LEC charts showed a slightly higher average value under the old chart (8,4% vs. 6,9%), which was also applicable to more cases and therefore included more cases with precanceroses (63% vs. 56%). In a direct comparison of the two charts higher differences of 10-20% in the determined LEC appeared especially among cases with squamous cell carcinoma. This was caused by a modification of the assigned LEC rates and standards for the disease activity between the two charts. Conclusions: A revision of the recommendations for the LEC was necessary after the introduction of a new occupational disease. By this, consistent standards for the evaluation of disease cases are provided and more fairness among different occupational diseases can be reached.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Actinic keratosis; Loss in earning capacity; Occupational disease; Squamous cell carcinoma

Mitochondrial and Morphologic Alterations in Native Human Corneal Endothelial Cells Associated With Diabetes Mellitus - Aldrich, Benjamin T.; Schlötzer-Schrehardt, Ursula; Skeie, Jessica M.; Burckart, Kimberlee A.; Schmidt, Gregory A.; Reed, Cynthia R.; Zimmerman, M. Bridget; Kruse, Friedrich; Greiner, Mark A. (Investigative Ophthalmology & Visual Science, 2017)
To characterize changes in the energy-producing metabolic activity and morphologic ultrastructure of corneal endothelial cells associated with diabetes mellitus.Transplant suitable corneoscleral tissue was obtained from donors aged 50 to 75 years. We assayed 3-mm punches of endothelium-Descemet membrane for mitochondrial respiration and glycolysis activity using extracellular flux analysis of oxygen and pH, respectively. Transmission electron microscopy was used to assess qualitative and quantitative ultrastructural changes in corneal endothelial cells and associated Descemet membrane. For purposes of analysis, samples were divided into four groups based on a medical history of diabetes regardless of type: (1) nondiabetic, (2) noninsulin-dependent diabetic, (3) insulin-dependent diabetic, and (4) insulin-dependent diabetic with specified complications due to diabetes (advanced diabetic).In total, 229 corneas from 159 donors were analyzed. Insulin-dependent diabetic samples with complications due to diabetes displayed the lowest spare respiratory values compared to all other groups (P <= 0.002). The remaining mitochondrial respiration and glycolysis metrics did not differ significantly among groups. Compared to nondiabetic controls, the endothelium from advanced diabetic samples had alterations in mitochondrial morphology, pronounced Golgi bodies associated with abundant vesicles, accumulation of lysosomal bodies/autophagosomes, and focal production of abnormal long-spacing collagen.Extracellular flux analysis suggests that corneal endothelial cells of donors with advanced diabetes have impaired mitochondrial function. Metabolic findings are supported by observed differences in mitochondrial morphology of advanced diabetic samples but not controls. Additional studies are needed to determine the precise mechanism(s) by which mitochondria become impaired in diabetic corneal endothelial cells.
EVALuna2:21336

Modulation of flash ERGs by dynamic backgrounds - Kremers, Jan; Aher, Avinash; Huchzermeyer, Cord (Documenta Ophthalmologica, 2022)
Purpose The aim of this study was to characterize the signal processing mechanisms that lead to an ERG response and to use this characterization for obtaining more robust responses in patients who display feeble responses with standard recordings. We studied the influence of sinusoidally modulating backgrounds on flash ERGs and the relationship between the ERG components' amplitudes and the momentary Weber fraction of the flash stimulus. Methods ERG recordings were performed in nine healthy subjects and three RP patients. In four normal subjects, we measured the response to flashes (500 cd/m(2), 1 ms duration) on a steady background (50 cd/m(2)) and on a sine wave (50 cd/m(2) mean luminance) modulating background at 1, 5, 10, and 25 Hz temporal frequencies. The flashes were delivered at eight different phases (0-315 degrees in a step of 45 degrees) during the modulating background sine wave. The responses to the backgrounds were also recorded and subtracted from the responses to flash plus modulating backgrounds to obtain the flash ERGs at the different phases. The recordings in the remaining five normal subjects and the RP patients were performed with a subset of these stimuli. Results The flash ERGs were strongly modulated by the backgrounds particularly at low frequencies and were enhanced when the momentary Weber fraction was large. The amplitudes of the components could be described by the Weber fraction plus a saturating nonlinearity and a delay in the processing of background luminance. The strength of the modulation decreased with increasing peak time of the component. Furthermore the background luminance delay was positively correlated with the peak time. The effect was also present in RP patients. Conclusions A sine wave background of about 1 Hz can be used to enhance ERG responses. Weber fraction of the flashes is an adequate quantification of stimulus for describing the amplitudes of the ERGs. The data provide basic information on how background luminance is processed in ERG generating mechanisms. The response enhancement can be used in clinical applications to obtain a more robust comparison between normal and patient data.
CRIS-Team WoS Importer:2022-11-04

Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17

Morphological characterization and clinical effects of stromal alterations after intracorneal ring segment implantation in keratoconus - Hamon, Loic; Schlötzer-Schrehardt, Ursula; Flockerzi, Fidelis A.; Seitz, Berthold; Daas, Loay (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: To analyze the histological and (ultra)structural stromal tissue changes after femtosecond (Fs) laser–assisted intracorneal ring segment (ICRS) implantation and their refractive and topographic effects in patients with keratoconus. Methods: This monocentric retrospective case series included 15 consecutive patients with clinical peri-segmental lamellar channel deposits after treatment with Fs-ICRS implantation for keratoconus. The stromal changes were investigated using in vivo confocal microscopy. Two patients underwent a penetrating keratoplasty after the Fs-ICRS implantation; the explanted corneas were processed for histopathology and transmission electron microscopy (TEM). Refractive and topographic effects were investigated comparing the uncorrected (UDVA) and corrected (CDVA) distance visual acuity, spherical equivalent (SE), flat (K1), steep (K2), and steepest (Kmax) keratometry before and after detection of lamellar channel deposits. Results: In vivo confocal microscopy revealed diffuse linear and focal granular hyperreflective structures. Histologically, there was mild proliferation of fibroblasts and fibrosis. TEM demonstrated focal accumulations of degenerated keratocytes with cytoplasmic lipid inclusions. There were no significant changes for UDVA (Δ = 0.0 ± 0.2 logMAR; p = 0.67), CDVA (Δ = 0.0 ± 0.1 logMAR; p = 0.32), SE (Δ 0.1 ± 0.9 D; p = 0.22), K1 (Δ = 0.3 ± 1.0 D; p = 0.28), K2 (Δ = 0.1 ± 0.9 D; p = 0.51), and Kmax (Δ = 0.3 ± 1.5 D; p = 0.17). Conclusions: Two types of structural stromal changes were identified: (1) diffuse peri-segmental fibrosis and (2) lamellar channel deposits. These structural changes showed no evidence of a relevant refractive or topographic effect.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Intracorneal ring segments; Keratoconus; Lamellar channel deposits; Peri-segmental fibrosis; Ultrastructural changes

Morphometric analysis of postoperative corneal neovascularization after high-risk keratoplasty: herpetic versus non-herpetic disease - Altenburger, Amadeus; Bachmann, Bjoern; Seitz, Berthold; Cursiefen, Claus (Graefes Archive For Clinical and Experimental Ophthalmology, 2012)
Postoperative complications after high-risk corneal grafting are decisively associated with corneal neovascularization (CNV). This study aimed to identify the incidence, extent, speed, localization, and influence of surgery-related factors on CNV after high-risk penetrating keratoplasty (PK) and to evaluate the effect of removing the angiogenic stimulus, i.e., residual components of herpes simplex virus (HSV) on postkeratoplasty CNV in patients with herpetic stromal keratitis (HSK).All primary high-risk PK performed for HSK and non-herpetic keratitis (controls) between 1 January 1998 and 31 December 2003 at our department with available standardized corneal photographs taken preoperatively as well as 6 weeks, 3, 6 and 12 months postoperatively were evaluated (n (herpes) = 19, n (controls) = 5 patients). Maximal extension of CNV, limbus suture distance (LSD), limbus graft distance (LGD) and graft size in digitalized pictures were measured in each of the 16 sectors of the cornea at every visit.One hundred percent of the prevascularized corneas (n = 24) showed further CNV outgrowth within 1 year after keratoplasty, while 58 % of these patients featured high-grade CNV reaching the host-graft junction or invading the donor tissue. Overall, CNV outgrowth was fastest during the first 6 weeks after PK, with a mean speed of 48 ?m/week. Mean CNV growth speed within 6 months post-PK was significantly lower in the herpes group (13 ?m/week) than in the non-herpes group (25 ?m/week, p = 0.017). Corneal location around the 12 o'clock position showed the most intense vessel outgrowth, which proved to be an independent risk factor for high-grade CNV (p = 0.025). Inverse correlation was evident between CNV growth speed and LSD (p = 0.032).Additional intense CNV outgrowth is a common phenomenon after high-risk keratoplasty, strongly marked in the early postoperative period. The removal of residual HSV components representing a potential angiogenic stimulus leads to a reduction in corneal angiogenesis not in the short term, but in the long term after PK in patients with HSK. In addition to preferable atraumatic operation techniques, modern antiviral prophylaxis and anti-angiogenic therapy should be applied early, possibly even prior to transplantation. Short LSD seems to be an intraoperative adjustable risk factor for CNV in high-risk setting. Attention should also be paid to the superior site around the 12 o'clock position.
EVALuna2:21091

Mouse Cones Adapt Fast, Rods Slowly In Vivo - Joachimsthaler, Anneka; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2019)
Purpose: To study rod- and cone-driven adaptation dynamics separately, we used the silent substitution technique to selectively stimulate rods or cones in the Opn1lwLIAIS (LIAIS) mouse, in which the native M-cone pigment is replaced by a human L-cone pigment (L*). Methods: ERG recordings were performed on anesthetized LIAIS mice. ERG stimuli were sinusoidally modulated. After 10 minutes of adaptation to 0.4 candela per square meter (cd/m2) ERGs were measured, followed by 11-minute adaptation to 8.8 cd/m2 background and recordings directly after the luminance increase and every second minute. Finally, during adaptation to 0.4 cd/m2 for 32 minutes, ERG responses were recorded directly after the change in background and every second minute. This protocol was repeated with rod-isolating stimuli (8 Hz; 75% rod contrast), L*-cone-isolating stimuli (12 Hz; 55% cone contrast) and white light (8 Hz and 12 Hz; 100% Michelson contrast). Results: At 8.8 cd/m2, responses directly displayed photopic response properties without further changes in either cone or white light responses. Rod-driven responses were very small. After the return to 0.4 cd/m2, both rod-driven and white light responses increased over a time course of about 30 minutes. Cone-driven responses were very small. Response phases changed directly after a change in background without further alterations. Conclusions: Rod- and cone-driven signal pathways display strongly different adaptation characteristics: adaptation of cone-driven responses to photopic conditions is very fast, whereas rod-driven responses change with a time course up to 30 minutes during scotopic conditions. Luminance responses are cone-driven at 8.8 cd/m2 and rod-driven at 0.4 cd/m2.
CRIS-Team Scopus Importer:2019-06-21

Multifocal electroretinographical changes in monkeys with experimental ocular hypertension: a longitudinal study - Kremers, Jan; Doelemeyer, Arno; Polska, Elzbieta A.; Moret, Fabrice; Lambert, Christian; Lambrou, George N. (Documenta Ophthalmologica, 2008)
Purpose To study the time course of changes in the multifocal electroretinograms (mfERG) in monkeys with experimental ocular hypertension (OHT). Methods The mfERGs were recorded in 12 eyes out of 6 monkeys. Two baseline measurements were used to quantify the reproducibility, the inter-ocular and the inter-individual variability of the ERG signals. Thereafter, the trabeculum of one eye of each animal was laser-coagulated in one to three sessions to induce OHT. ERG measurements were repeated regularly in a period of 18 months and the changes in ERG waveforms were quantified. Results All animals displayed OHT (between 20 and 50 mmHg) in the laser-coagulated eyes. An ERG change was defined as the sum of differences during the first 90 ms between the laser-coagulated eye and the same eye before laser coagulation and between the laser-coagulated eye and the non-treated fellow eye. Three animals displayed significant changes for nearly all retinal areas and all stimulus conditions. The three remaining animals displayed significant changes only in one comparison, indicating very mild changes. The data indicate that a high stimulus contrast is more sensitive to detect changes, probably because of a better signal-to-noise ratio. Moreover, the comparisons with the fellow eye are more sensitive to detect changes than comparisons with the measurements before laser-coagulation. Conclusions OHT does not always lead to ERG changes. Comparisons with fellow eyes using high contrast stimuli are more sensitive to detect changes related to OHT.
Keywords: glaucoma; multifocal electroretinograms; non-human primates; ocular hypertension

Multifocal electroretinography after high dose chloroquine therapy for malaria - de Carvalho, Aline Correa; Schwarz, Martin; Souza, Givago da Silva; Gomes, Bruno Duarte; Rosa, Alexandre Antônio Marques; da Silva Ventura, Ana Maria Revoredo; de Souza, José Maria; Silveira, Luiz Carlos de Lima; Kremers, Jan (Journal of Ophthalmic & Vision Research, 2013)
To investigate changes in multifocal electroretinography (mfERG) parameters associated with high dose chloroquine therapy for treatment of malaria in the Amazonia region of Brazil.Forty-eight subjects who had received chloroquine treatment for single or multiple malaria infections with a cumulative dose ranging from 1,050 to 27,000mg were included. The control group consisted of 37 healthy aged-matched subjects. Data was collected on amplitude and implicit time of the N1, P1 and N2 waves in the central macular hexagon (R1) and in five concentric rings at different retinal eccentricities (R2-R6).No significant difference was observed in any mfERG parameter between chloroquine treated patients and control subjects. A comparison with previous data obtained from patients with rheumatologic disorders in the same region of Brazil who had received larger cumulative doses of chloroquine and had displayed mfERG changes, indicated that retinal toxicity seems to be dependent on cumulative dose.Lack of mfERG changes in the current study suggests that intensive high dose chloroquine therapy for treatment of malaria is not associated with retinal toxicity.
EVALuna2:21145

Multifocal Electroretinography with simultaneous fundus imaging in mice - Dutescu, R. Michael; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 508 electrophysiology: non-clinical; 578 laser; 612 neuro-ophthalmology: diagnosis

Multifocal ERG recordings under visual control of the stimulated fundus in mice - Dutescu, Ralf M.; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia M.; Strauss, Olaf; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Therapeutic approaches to retinal disease require a continuous monitoring of functional improvement over lesion areas that sometimes cannot be shown in full-field ERG. The aim of this study was to assess the usefulness of multifocal electroretinograms (mfERGs) under visual control using scanning laser ophthalmoscopy (SLO) for evaluation of local retinopathy in mice.mfERGs were optimized for recordings in C57BL/6 mice by varying dark steps between each stimuli, background intensity, and the numbers of hexagons. Local retinopathy was induced by argon laser photocoagulation with different spot sizes and retinal irradiances. mfERG recordings were performed before, and 10 days and 4 weeks after laser treatment. In each recording, the central hexagon was positioned on the optic nerve head visualized by SLO images. The amplitudes of the P1 response components were analyzed as a function of retinal location.The mfERG amplitudes depended on stimulus condition. The P1 amplitudes increased with increasing number of dark frames in the m-sequence and with decreasing number of hexagons. A stimulus with 19 hexagons and four dark frames was chosen because substantial response amplitudes could be achieved while preserving sufficient spatial resolution. In the untreated eyes, the response to the central hexagon, stimulating the optic nerve head, was smaller than those to the surrounding hexagons. The responses to hexagons stimulating photocoagulated areas were reduced compared with the responses of surrounding areas. The amplitude reduction was more pronounced when the coagulated areas were larger and when higher energies were used.Areas with decreased sensitivities to light stimulation (either the optic nerve head or damaged retinal areas) can be detected and correlated with the retinal images and in the mfERG responses. We demonstrate that the mfERG technique is able to reproducibly detect the functional consequences of a local treatment.
EVALuna2:21138

Multi-Frame Super-Resolution with Quality Self-Assessment for Retinal Fundus Videos - Köhler, Thomas; Brost, Alexander; Mogalle, Katja; Zhang, Qianyi; Köhler, Christiane; Michelson, Georg; Hornegger, Joachim; Tornow, Ralf-Peter (Medical Image Computing and Computer-Assisted Intervention – MICCAI 2014, 2014)
This paper proposes a novel super-resolution framework to reconstruct high-resolution fundus images from multiple low-resolution video frames in retinal fundus imaging. Natural eye movements during an examination are used as a cue for super-resolution in a robust maximum a-posteriori scheme. In order to compensate heterogeneous illumination on the fundus, we integrate retrospective illumination correction for photometric registration to the underlying imaging model. Our method utilizes quality self-assessment to provide objective quality scores for reconstructed images as well as to select regularization parameters automatically. In our evaluation on real data acquired from six human subjects with a low-cost video camera, the proposed method achieved considerable enhancements of low-resolution frames and improved noise and sharpness characteristics by 74%. In terms of image analysis, we demonstrate the importance of our method for the improvement of automatic blood vessel segmentation as an example application, where the sensitivity was increased by 13% using super-resolution reconstruction. © 2014 Springer International Publishing.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.multif

Multi-modal Retinal Image Registration Using a Keypoint-Based Vessel Structure Aligning Network - Sindel, Aline; Hohberger, Bettina; Maier, Andreas; Christlein, Vincent (Medical Image Computing and Computer Assisted Intervention – MICCAI 2022, 2022)
In ophthalmological imaging, multiple imaging systems, such as color fundus, infrared, fluorescein angiography, optical coherence tomography (OCT) or OCT angiography, are often involved to make a diagnosis of retinal disease. Multi-modal retinal registration techniques can assist ophthalmologists by providing a pixel-based comparison of aligned vessel structures in images from different modalities or acquisition times. To this end, we propose an end-to-end trainable deep learning method for multi-modal retinal image registration. Our method extracts convolutional features from the vessel structure for keypoint detection and description and uses a graph neural network for feature matching. The keypoint detection and description network and graph neural network are jointly trained in a self-supervised manner using synthetic multi-modal image pairs and are guided by synthetically sampled ground truth homographies. Our method demonstrates higher registration accuracy as competing methods for our synthetic retinal dataset and generalizes well for our real macula dataset and a public fundus dataset.
Keywords: Multi-modal retinal image registration; Convolutional neural networks; Graph neural networks

Multiscale Blood Vessel Segmentation in Retinal Fundus Images - Budai, Attila; Michelson, Georg; Hornegger, Joachim (Bildverarbeitung für die Medizin 2010 - Algorithmen, Systeme, Anwendungen,, 2010)

Multispectral retinal video-ophthalmoscope with fiber optic illumination - Kolar, Radim; Vicar, Tomas; Odstrcilik, Jan; Valterova, Eva; Skorkovska, Karolina; Kralik, Martin; Tornow, Ralf-Peter (Journal of Biophotonics, 2022)
Multispectral imaging is used in various applications including astronomy, industry and agriculture. In retinal imaging, the single-shot multispectral image stack is typically acquired and analyzed. This multispectral analysis can provide information on various structural or metabolic properties. This paper describes the multispectral improvement of a video-ophthalmoscope, which can acquire retinal video sequences of the optic nerve head and peripapillary area using various spectral light illumination. The description of the multispectral video imaging is provided and several applications are described. These applications include multispectral retinal photoplethysmography, visualization of spontaneous vein pulsation and multispectral RGB image generation.
CRIS-Team Scopus Importer:2022-06-17
Keywords: fundus imaging; multispectral imaging; retinal photoplethysmography; tissue light attenuation; video-ophthalmoscopy

"Multisystem Inflammatory Syndrome in Children"-Like Disease after COVID-19 Vaccination (MIS-V) with Potential Significance of Functional Active Autoantibodies Targeting G-Protein-Coupled Receptors (GPCR-fAAb) for Pathophysiology and Therapy. - Schmidt, Marius; Hébert, Steven; Wallukat, Gerd; Ponader, Rolf; Krickau, Tobias; Galiano, Matthias; Reutter, Heiko Martin; Wölfle, Joachim; Agaimy, Abbas; Mardin, Christian; Hörning, André; Hohberger, Bettina (Children, 2023)
BACKGROUND: An infection with SARS-CoV-2 can trigger a systemic disorder by pathological autoimmune processes. A certain type of this dysregulation is known as Multisystemic inflammatory syndrome in children (MIS-C). However, similar symptoms may occur and have been described as Multisystemic inflammatory syndrome after SARS-CoV-2 Vaccination (MIS-V) following vaccination against SARS-CoV-2. We report the case of a 12-year-old boy who was identified with MIS-C symptoms without previous SARS-CoV-2 infection after receiving two doses of the Pfizer-BioNTech COVID-19 vaccine approximately one month prior to the onset of symptoms. He showed polyserositis, severe gastrointestinal symptoms and, consequently, a manifestation of a multiorgan failure. IgG antibodies against spike proteins of SARS-CoV-2 were detected, indicating a successful vaccination, while SARS-CoV-2 Nucleocapsid protein antibodies and SARS-CoV-2 PCR were not detected. Several functional, active autoantibodies against G-protein-coupled receptors (GPCR-fAAb), previously associated with Long COVID disease, were detected in a cardiomyocyte bioassay. Immunosuppression with steroids was initiated. Due to side effects, treatment with steroids and later interleukin 1 receptor antagonists had to be terminated. Instead, immunoadsorption was performed and continued with tacrolimus and mycophenolic acid therapy, leading to improvement and discharge after 79 days. GPCR-fAAb decreased during therapy and remained negative after clinical curing and under continued immunosuppressive therapy with tacrolimus and mycophenolic acid. Follow-up of the patient showed him in good condition after one year. CONCLUSIONS: Infection with SARS-CoV-2 shows a broad and severe variety of symptoms, partly due to autoimmune dysregulation, which, in some instances, can lead to multiorgan failure. Despite its rarity, post-vaccine MIS-C-like disease may develop into a serious condition triggered by autoimmune dysregulation. The evidence of circulating GPCR-fAAb and their disappearance after therapy suggests a link of GPCR-fAAb to the clinical manifestations. Thus, we hypothesize a potential role of GPCR-fAAb in pathophysiology and their potential importance for the therapy of MIS-C or MIS-V. However, this observation needs further investigation to prove a causative correlation.
EVALuna2:547545

“Multisystem Inflammatory Syndrome in Children” (MIS-C) after COVID-19 Infection in the Metropolitan Area of Nuremberg-Erlangen, Germany—Expectations and Results of a Two-Year Period - Hébert, Steven; Schmidt, Marius; Topf, Georg; Rieger, Daniel; Klinge, Jens; Vermehren, Jan; Fusch, Christoph; Grillhösl, Christian; Schroth, Michael; Toni, Irmgard; Reutter, Heiko Martin; Morhart, Patrick; et al. (Children, 2023)
Background: Multisystemic Inflammatory Syndrome in children (MIS-C) is a rare autoimmune disorder occurring after a latency period following acute SARS-CoV-2 infection. The therapeutic regime of MIS-C is adapted to the therapy of the Kawasaki disease, as clinical symptoms are similar. Since the Kawasaki disease can potentially result in severe symptoms, which may even affect long-term health, it is essential to gain further knowledge about MIS-C. Thus, we aimed to investigate the incidence, symptoms, therapeutical procedure and outcome of MIS-C patients in the metropolitan area of Nuremberg-Erlangen during the SARS-CoV2 pandemic. Material and Methods: Retrospective analysis of clinical charts of MIS-C patients was carried out at three children’s hospitals covering the medical care of the metropolitan area of Nuremberg-Erlangen in Germany. Demographic characteristics and symptoms at first visit, their clinical course, therapeutic regime and outcome were recorded within the time period January 2021–December 2022. Results: Analysis of 10 patients (5 male, 5 female) with MIS-C resulting in an incidence of 2.14/100.000 children. The median time between COVID-19 infection and admission to hospital was 5 weeks. The median age was 7 years. Symptoms comprised fever (100%), rash (70%), bilateral non-purulent conjunctivitis (70%) and urticaria (20%). At the time of presentation, diagnosis-defining inflammation parameters were increased and the range for C-reactive protein was 4.13 mg/dL to 28 mg/dL, with a median of 24.7 mg/dL. Procalcitonin was initially determined in six patients (1.92 ng/mL to 21.5 ng/mL) with a median value of 5.5 pg/mL. Two patients displayed leukocytosis and two displayed leukopenia. None of the patients presented coronary pathologies. Nine of the ten patients received intravenous immunoglobulin (IVIG) therapy. In addition, patients received intravenous steroids (80%) and acetylsalicylic acid (80%). Conclusion: SARS-CoV virus may rarely exert multiorgan manifestations due to hyperinflammatory immunological processes. Within two years of the COVID-19 pandemic, we identified ten patients with COVID-induced MIS-C in the metropolitan area Nuremberg-Erlangen. In the description of the patient collective, we can confirm that MIS-C is distinguished from the Kawasaki disease by the lack of coronary manifestations. Interestingly, although having monitored all pediatric facilities in the investigated area, we find lower incidences of MIS-C compared to findings in the literature. In conclusion, an overestimation of incidences in the upcoming MIS-C during the pandemic needs to be considered.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; intravenous immunoglobulins; IVIG; mAbs; MIS-C; monoclonal antibodies; Multisystem Inflammatory Syndrome in children

Murine Hair Follicle Derived Stem Cell Transplantation onto the Cornea Using a Fibrin Carrier - Call, Mindy; Meyer, Ewa Anna; Kao, Winston W.; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Bio-protocol, 2018)
The goal of this protocol is to establish a procedure for cultivating stem cells on a fibrin carrier to allow for eventual transplantation to the eye. The ability to transfer stem cells to a patient is critical for treatment for a variety of disorders and wound repair. We took hair follicle stem cells from the vibrissae of transgenic mice expressing a dual reporter gene under the control of the Tet-on system and the keratin 12 promoter (Meyer-Blazejewska et al., 2011). A clonal growth assay was performed to enrich for stem cells. Once holoclones formed they were transferred onto a fibrin carrier and cultivated to obtain a confluent epithelial cell layer. Limbal stem cell deficient (LSCD) mice were used as the transplant recipient in order to test for successful grafting and eventual differentiation into a corneal epithelial phenotype.
CRIS-Team WoS Importer:2019-02-21

Mutant RAMP2 causes primary open-angle glaucoma via the CRLR-cAMP axis - Gong, Bo; Zhang, Houbin; Huang, Lulin; Chen, Yuhong; Shi, Yi; Tam, Pancy Oi Sin; Zhu, Xianjun; Huang, Yi; Lei, Bo; Sundaresan, Periasamy; Li, Xi; Jiang, Linxin; et al. (Genetics in Medicine, 2019)
Purpose: Primary open-angle glaucoma (POAG) is the leading cause of irreversible blindness worldwide and mutations in known genes can only explain 5–6% of POAG. This study was conducted to identify novel POAG-causing genes and explore the pathogenesis of this disease. Methods: Exome sequencing was performed in a Han Chinese cohort comprising 398 sporadic cases with POAG and 2010 controls, followed by replication studies by Sanger sequencing. A heterozygous Ramp2 knockout mouse model was generated for in vivo functional study. Results: Using exome sequencing analysis and replication studies, we identified pathogenic variants in receptor activity-modifying protein 2 (RAMP2) within three genetically diverse populations (Han Chinese, German, and Indian). Six heterozygous RAMP2 pathogenic variants (Glu39Asp, Glu54Lys, Phe103Ser, Asn113Lysfs*10, Glu143Lys, and Ser171Arg) were identified among 16 of 4763 POAG patients, whereas no variants were detected in any exon of RAMP2 in 10,953 control individuals. Mutant RAMP2s aggregated in transfected cells and resulted in damage to the AM-RAMP2/CRLR-cAMP signaling pathway. Ablation of one Ramp2 allele led to cAMP reduction and retinal ganglion cell death in mice. Conclusion: This study demonstrated that disruption of RAMP2/CRLR-cAMP axis could cause POAG and identified a potential therapeutic intervention for POAG.
CRIS-Team Scopus Importer:2019-05-02
Keywords: exome sequencing; heterozygous pathogenic variant; primary open-angle glaucoma (POAG); receptor activity-modifying protein 2 (RAMP2); retinal ganglion cell (RGC)

Mutation in Bmpr1b Leads to Optic Disc Coloboma and Ventral Retinal Gliosis in Mice - Yan, Xiaohe; Atorf, Jenny; Ramos, David; Thiele, Frank; Weber, Susanne; Dalke, Claudia; Sun, Minxuan; Puk, Oliver; Michel, Dian; Fuchs, Helmut; Klaften, Matthias; Przemeck, Gerhard K. H.; et al. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. The clinical phenotype of retinal gliosis occurs in different forms; here, we characterize one novel genetic feature, (i.e., signaling via BMP-receptor 1b).
CRIS-Team WoS Importer:2020-03-20

Mutations in PIK3C2A cause syndromic short stature, skeletal abnormalities, and cataracts associated with ciliary dysfunction - Tiosano, Dov; Baris, Hagit N.; Chen, Anlu; Hitzert, Marrit M.; Schüler, Markus; Gulluni, Federico; Wiesener, Antje; Bergua, Antonio; Mory, Adi; Copeland, Brett; Gleeson, Joseph G.; Rump, Patrick; et al. (PLoS Genetics, 2019)
PIK3C2A is a class II member of the phosphoinositide 3-kinase (PI3K) family that catalyzes the phosphorylation of phosphatidylinositol (PI) into PI(3)P and the phosphorylation of PI(4)P into PI(3,4)P2. At the cellular level, PIK3C2A is critical for the formation of cilia and for receptor mediated endocytosis, among other biological functions. We identified homozygous loss-of-function mutations in PIK3C2A in children from three independent consanguineous families with short stature, coarse facial features, cataracts with secondary glaucoma, multiple skeletal abnormalities, neurological manifestations, among other findings. Cellular studies of patient-derived fibroblasts found that they lacked PIK3C2A protein, had impaired cilia formation and function, and demonstrated reduced proliferative capacity. Collectively, the genetic and molecular data implicate mutations in PIK3C2A in a new Mendelian disorder of PI metabolism, thereby shedding light on the critical role of a class II PI3K in growth, vision, skeletal formation and neurological development. In particular, the considerable phenotypic overlap, yet distinct features, between this syndrome and Lowe's syndrome, which is caused by mutations in the PI-5-phosphatase OCRL, highlight the key role of PI metabolizing enzymes in specific developmental processes and demonstrate the unique non-redundant functions of each enzyme. This discovery expands what is known about disorders of PI metabolism and helps unravel the role of PIK3C2A and class II PI3Ks in health and disease.
CRIS-Team Scopus Importer:2019-05-28

Myofibroblast metaplasia after descemet membrane endothelial keratoplasty - Heindl, Ludwig M.; Schlötzer-Schrehardt, Ursula; Cursiefen, Claus; Bachmann, Bjoern O.; Hofmann-Rummelt, Carmen; Kruse, Friedrich (American Journal of Ophthalmology, 2011)
To describe myofibroblastic metaplasia of corneal endothelial cells in 2 cases with impaired visual function despite complete graft adherence after Descemet membrane endothelial keratoplasty (DMEK).Interventional case series.In 2 of 90 consecutive DMEK surgeries, the cornea failed to clear up to 6 months postoperatively despite complete graft attachment. After secondary penetrating keratoplasty, both corneal buttons were examined using histopathologic analysis and transmission electron microscopy.Light microscopy revealed distinct corneal endothelial cell attenuation with the presence of an abnormal posterior collagenous layer in both cases. Most of the remaining endothelial cells had an elongated fibroblast-like appearance with immunopositivity for ?-smooth muscle actin indicative of myofibroblast metaplasia. Transmission electron microscopy showed a slightly thickened Descemet membrane with an abnormal posterior fibrillar collagenous layer and a myofibroblast-like transformation of the remaining endothelial cells. Descemet membrane grafts closely adjoined the collagen lamellae of the host corneal stroma similar to the Descemet membrane-stroma interface of a normal cornea.Myofibroblastic metaplasia of attenuated corneal endothelial cells with formation of an abnormal posterior collagenous layer may contribute to an impaired visual function despite complete graft adherence after Descemet membrane endothelial keratoplasty (DMEK).
EVALuna2:21011

Nanofaserscaffolds als DMEK-& Amnionmembranersatz – Anforderungen und Eigenschaften - Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas (iSearch 2021, Münster (Deutschland), 2021, 2021)

Natural history of X-linked hypohidrotic ectodermal dysplasia: a 5-year follow-up study - Wohlfart, Sigrun; Meiller, Ralph; Hammersen, Johanna; Park, Jung; Menzel-Severing, Johannes; Melichar, Volker O.; Huttner, Kenneth; Johnson, Ramsey; Porte, Florence; Schneider, Holm (Orphanet Journal of Rare Diseases, 2020)
BACKGROUND: X-linked hypohidrotic ectodermal dysplasia (XLHED) is caused by pathogenic variants of the gene EDA disrupting the prenatal development of ectodermal derivatives. Cardinal symptoms are hypotrichosis, lack of teeth, and hypo- or anhidrosis, but the disease may also evoke other clinical problems. This study aimed at investigating the clinical course of XLHED in early childhood as the basis for an evaluation of the efficacy of potential treatments. METHODS: 25 children (19 boys and 6 girls between 11 and 35 months of age) with genetically confirmed XLHED were enrolled in a long-term natural history study. Clinical data were collected both retrospectively using parent questionnaires and medical records (pregnancy, birth, infancy) and prospectively until the age of 60 months. General development, dentition, sweating ability, ocular, respiratory, and skin involvement were assessed by standardized clinical examination and yearly quantitative surveys. RESULTS: All male subjects suffered from persistent anhidrosis and heat intolerance, although a few sweat ducts were detected in some patients. Sweating ability of girls with XLHED ranged from strongly reduced to almost normal. In the male subjects, 1-12 deciduous teeth erupted and 0-8 tooth germs of the permanent dentition became detectable. Tooth numbers were higher but variable in the female group. Most affected boys had no more than three if any Meibomian glands per eyelid, most girls had fewer than 10. Many male subjects developed additional, sometimes severe health issues, such as obstructive airway conditions, chronic eczema, or dry eye disease. Adverse events included various XLHED-related infections, unexplained fever, allergic reactions, and retardation of psychomotor development. CONCLUSIONS: This first comprehensive study of the course of XLHED confirmed the early involvement of multiple organs, pointing to the need of early therapeutic intervention.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Dry eye; Ectodysplasin A; Heat intolerance; Hypohidrotic ectodermal dysplasia; Natural history; Oligodontia

Neue Techniken zur Quantifizierung des Farbsinns bei Störungen der Zapfenfunktion - Huchzermeyer, Cord; Fars, Julien; Stöhr, Heidi; Kremers, Jan (Ophthalmologe, 2020)
Background: Inherited retinal diseases with cone dysfunction can be accompanied by severe visual loss and a marked loss of color vision despite relatively normal fundus appearance. Autosomal dominant occult macular dystrophy (RP1L1 gene) and X‑chromosomal retinitis pigmentosa (RPGR gene, including heterozygous female carriers) are important examples. New examination techniques enable quantification of the extent of color vision disturbances. Methods: After a thorough clinical examination, color discrimination and cone function were quantified. The Cambridge color test is a computer-based test that generates pseudo-isochromatic plates with Landolt C figures for quantifying color discrimination along several axes in color space. Examination of photorecepor-specific temporal contrast sensitivity is performed by subtle cyclic modulation of the spectral composition of a light stimulus. Molecular diagnostics were carried out by next generation sequencing (NGS)-based targeted gene panel analysis and Sanger sequencing. Results: Markedly reduced color discrimination as well as reduced photoreceptor-specific temporal contrast sensitivity could be demonstrated in two patients with occult macular dystrophy and two heterozygous female carriers of RPGR mutations. Conclusion: The demonstration of dyschromatopsia is very helpful in the diagnosis of inherited retinal diseases, in addition to modern imaging techniques, such as optical coherence tomography (OCT) and fundus fluorescence. New functional techniques enable quantification of color vision disturbances and could be useful as outcome parameters in clinical trials of new gene and stem cell-based therapies.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Color vision; Cone dystrophy; Contrast sensitivity; Photoreceptors; Retinitis pigmentosa

Neuroimmunological Aspects in Glaucoma Neuroimmunologische Auffälligkeiten beim Glaukom - Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Glaucoma pathogenesis hast still to be elucidated. Next to its main risk factor, an increased intraocular pressure, an e.g. altered biomechanics of the lamina cribrosa, oxidative stress-mediated changes and glutatmate toxicity are involved in this multifactorial pathophysiology. Recent experimental studies and clinical findings suggest an involvement of the immune system in glaucoma. This review will give an overview of the different immunologic aspects being involved in glaucoma pathogenesis.
CRIS-Team Scopus Importer:2021-03-05
Keywords: autoantibody; glaucoma; immune system

New developments in non-invasive visual electrophysiology. - Parry, Neil. R. A.; Mckeefry, Declan J.; Murray, Ian J.; Kremers, Jan (Vision research, 2020)
EVALuna2:419179

New method for remote and repeatable monitoring of intraocular pressure variations - Margalit, Israel; Beiderman, Yevgeny; Skaat, Alon; Rosenfeld, Elkanah; Belkin, Michael; Tornow, Ralf-Peter; Mico, Vicente; Garcia, Javier; Zalevsky, Zeev (Journal of Biomedical Optics, 2014)
We present initial steps toward a new measurement device enabling high-precision, noncontact remote and repeatable monitoring of intraocular pressure (IOP)-based on an innovative measurement principle. Using only a camera and a laser source, the device measures IOP by tracking the secondary speckle pattern trajectories produced by the reflection of an illuminating laser beam from the iris or the sclera. The device was tested on rabbit eyes using two different methods to modify IOP: via an infusion bag and via mechanical pressure. In both cases, the eyes were stimulated with increasing and decreasing ramps of the IOP. As IOP variations changed the speckle distributions reflected back from the eye, data were recorded under various optical configurations to define and optimize the best experimental configuration for the IOP extraction. The association between the data provided by our proposed device and that resulting from controlled modification of the IOP was assessed, revealing high correlation (R2=0.98) and sensitivity and providing a high-precision measurement (5% estimated error) for the best experimental configuration. Future steps will be directed toward applying the proposed measurement principle in clinical trials for monitoring IOP with human subjects.
EVALuna2:21170

New possibilities for ocular surface reconstruction : Collagen membranes and biocompatible elastomer nanofibers - Fuchsluger, Thomas; Salehi, S.; Petsch, Christina; Bachmann, B. (Ophthalmologe, 2014)
Amniotic membranes have been used for many years for reconstruction of the ocular surface. Despite having anti-inflammatory and antiangiogenic properties as well as being suitable as a carrier for corneal epithelial cells, amniotic membranes also have some limitations for use at the human cornea: availability is limited, there are major interindividual variations in structure and growth factor content and are not free from the risk of disease transmission. Progress in tissue engineering has been made aiming at the development and improvement of alternative biomaterials.This article presents new approaches for reconstruction of the corneal surface with collagen-based biomaterials and polymers.Electronic databases were searched for articles which evaluated collagenous biomaterials for use at the corneal surface. In addition the authors' own experiences with novel biomaterials are described.In vitro evaluation of the described biomaterials suggested a high biocompatibility with corneal epithelial cells in cell cultures. In vivo experiments with these materials in animal corneas demonstrated a certain variability in degradation and remodeling. Although some materials showed promising experimental results none of these are established in the clinical routine and only few clinical studies have so far been conducted with collagen-based biomaterials.Although the majority of the described biomaterials are currently still in the experimental stage, a transfer into the clinical routine is conceivable and of great therapeutic interest.
EVALuna2:21193

New software analyses increase the reliability of measurements of retinal arterioles morphology by scanning laser Doppler flowmetry in humans - Harazny, Joanna M.; Raff, Ulrike; Welzenbach, Juergen; Ott, Christian; Ritt, Martin; Lehmann, Maria; Michelson, Georg; Schmieder, Roland; Lehmann, Maria (Journal of Hypertension, 2011)
The investigation of the retinal arterioles offers the unique opportunity to analyze in vivo arteriolar remodeling in arterial hypertension in humans. We analyzed the reliability of assessing retinal arteriolar morphology with our new version of the software analyses for scanning laser Doppler flowmetry.In the test-retest reliability study, 10 eyes of 10 healthy persons were measured during 5 days under routine laboratory conditions with the Heidelberg Retinal Flowmetry. In a second study, interobserver and intraobserver reliability was analyzed from retinal images of 18 patients with three types of arterial hypertension by three readers and the most experienced reader analyzed all images twice on two different days. Images were analyzed by the old and the newly developed software versions. To characterize the reliability, the coefficients of variation were calculated.The test-retest study analyzed with the new program showed that the variation coefficients of vessel and lumen diameter, wall thickness, wall/lumen ratio and new calculated parameter: lumen/vessel diameter ratio of retinal arterioles were significantly less than 10%, with the exception of the wall cross-sectional area (12.5%). The interobserver and intraobserver reliability showed in nearly all circumstances coefficients of variations of less than 10% and did not differ across various readers and patient groups.The new software 'SLDF version 4.0' clearly improved the reliability of assessing the structural parameters of the retinal arterioles. The application delivers reliable measurements of the retinal arteriolar structure in vivo in human
EVALuna2:3487

Non-linear imaging as tool in biomaterials research - Thieme, Daniel; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien - Annual Meeting, 2018)
Keywords: biomaterial; bioprinting

Non-mydriatic, 68 wide fundus imaging with low cost components - Höher, Bernhard; Köhler, Aaron; Schmauß, Bernhard; Michelson, Georg (ARVO Annual Meeting 2012, 2012)
lhft_intern.bib::Hoeher2012a

Non-mydriatic, wide field, fundus video camera - Höher, Bernhard; Voigtmann, Peter; Michelson, Georg; Schmauß, Bernhard (SPIE Photonics West, 2014)
We describe a method we call "stripe field imaging" that is capable of capturing wide field color fundus videos and images of the human eye at pupil sizes of 2mm. This means that it can be used with a non-dilated pupil even with bright ambient light. We realized a mobile demonstrator to prove the method and we could acquire color fundus videos of subjects successfully. We designed the demonstrator as a low-cost device consisting of mass market components to show that there is no major additional technical outlay to realize the improvements we propose. The technical core idea of our method is breaking the rotational symmetry in the optical design that is given in many conventional fundus cameras. By this measure we could extend the possible field of view (FOV) at a pupil size of 2mm from a circular field with 20° in diameter to a square field with 68° by 18° in size. We acquired a fundus video while the subject was slightly touching and releasing the lid. The resulting video showed changes at vessels in the region of the papilla and a change of the paleness of the papilla. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Hoeher2014

No-reference quality index for color retinal images - Abdel-Hamid, Lamiaa; El-Rafei, Ahmed; Michelson, Georg (Computers in Biology and Medicine, 2017)
Retinal image quality assessment (RIQA) is essential to assure that the images investigated by ophthalmologists or automatic systems are suitable for reliable medical diagnosis. Measure-based RIQA techniques have several advantages over the more commonly used binary classification-based RIQA methods. Numeric quality measures can aid ophthalmologists in associating a degree of confidence to the diagnosis performed through the investigation of a certain retinal image. Moreover, a numeric quality index can provide a mean for identifying the degree of enhancement required as well as to evaluate and compare the improvement achieved by enhancement techniques. In this work, a no-reference retinal image sharpness numeric quality index is introduced that is computed from the wavelet decomposition of the images. In order to account for the obscured retinal structures in unevenly illuminated image regions, the quality index is modified by a homogeneity parameter calculated from the previously introduced retinal image saturation channel. The proposed quality index was validated and tested on two datasets having different resolutions and quality grades. A strong (Spearman's coefficient > 0.8) and statistically highly significant (p-value < 0.001) correlation was found between the introduced quality index and the subjective human scores for the two different datasets. Moreover, multiclass classification using solely the devised retinal image quality index as a feature resulted in a micro average F-measure of 0.84 and 0.95 using the high and low resolution datasets, respectively. Several comparisons with other retinal image quality measures demonstrated superiority of the proposed quality index in both performance and speed.
EVALuna2:21356

No-reference wavelet based retinal image quality assessment - Abdel Hamid, L. S.; El-Rafei, A.; El-Ramly, S.; Michelson, Georg; Hornegger, Joachim (5th Eccomas Thematic Conference on Computational Vision and Medical Image Processing, VipIMAGE 2015, 2016)
Retinal Image Quality Assessment (RIQA) is an essential preliminarily step in Automatic Retinal Screening Systems (ARSS) to avoid misdiagnosis of retinal disease. In this work, a no-reference wavelet based RIQA algorithm suitable for real-time ARSS is introduced. Retinal images are classified into good and bad quality images using two proposed metrics. These measures are extracted from the wavelet decomposition subbands of the image to reflect sharpness and contrast. Wavelet level and regional analyses are performed to determine the most relevant levels and retinal region to be used in the RIQA. The algorithm is tested on two publicly available datasets with different resolutions. Area under the ROC curve (AUC) of 1 and 0.985 are obtained for the low and high resolution datasets respectively with runtime ranging between 0.1 and 2 seconds depending on image resolution. Comparison with other RIQA algorithms shows superiority of the proposed algorithm in both performance and time.
Keywords: Real-time system; Retinal Image Quality Assessment; Wavelet transform

Novel Biallelic CTSD Gene Variants Cause Late-Onset Ataxia and Retinitis Pigmentosa - Regensburger, Martin; Minakaki, Georgia; Kettwig, Matthias; Huchzermeyer, Cord; Eisenhut, Felix; Haack, Tobias B.; Kohl, Zacharias; Winkler, Jürgen (Movement Disorders, 2020)
CRIS-Team Scopus Importer:2020-05-29

Novel biomaterials for ocular surface surgery - Thieme, Daniel; Fuchsluger, Thomas; Schubert, Dirk W. (Acta Ophthalmologica, 2018)

Novel collagen membranes for the reconstruction of the corneal surface - Petsch, Corinna; Schlötzer-Schrehardt, Ursula; Meyer-Blazejewska, Ewa; Frey, Markus; Kruse, Friedrich; Bachmann, Björn (Tissue Engineering: Parts A, B, and C, 2014)
No standardized biomaterial exists for the surgical treatment of persistent corneal erosions and ulcerations. We analyzed the suitability and biocompatibility of defined noncross-linked and UV/riboflavin cross-linked equine type I collagen membranes for the reconstruction of the corneal surface. Isolated human oral mucosa epithelial cells, a cell type in clinical use for the treatment of ocular surface diseases, were subcultivated on both types of membranes and examined concerning cell adhesion, proliferation, and differentiation. Biocompatibility was evaluated following superficial and intrastromal corneal transplantation in New Zealand white rabbits. In cell cultures all collagen membranes supported adhesion of oral mucosa epithelial cells leading to the formation of multilayered epithelial cell sheets. After intrastromal corneal implantation clinical signs of degradation were seen in all variants of collagen membranes, which was fastest in noncross-linked variants. The histological and ultrastructural level invasion of keratocytes and production of new collagen fibers inside the collagen membranes could be detected in noncross-linked variants. After superficial corneal implantation covering of the membranes by corneal epithelium over time was visible. Ultrastructural analysis showed a slower rate of degradation and less invading keratocytes in cross-linked variants compared with noncross-linked collagen membranes. Cross-linked and noncross-linked variants of the collagen membrane proofed to be suitable to serve as a carrier for epithelial stem cells in vitro and showed a high biocompatibility in vivo. These results indicate that the tested collagen membranes might be suitable for the reconstruction of the corneal surface in patients with nonhealing ulcerations. Whether membranes with faster or slower degradation properties are preferable for the treatment of persistent corneal ulcerations might depend on the underlying corneal pathology and the degree of concomitant inflammation.
EVALuna2:21203

Novel concepts for treatment of the corneal endothelium with nanoparticles - Fuchsluger, Thomas (Ophthalmologe, 2018)
The number of corneal transplantations has increased in Germany in recent years. One reason is an earlier time point of surgery due to less invasive posterior lamellar grafting techniques. To date, penetrating and lamellar corneal transplantations are the only established therapeutic options to treat corneal diseases resulting from endothelial cell pathologies.This review article provides an insight into nanoparticle-related translational strategies to improve or to avoid corneal transplantation.Nanoparticle-based strategies for optimization of the corneal endothelium have different fields of application: 1. during donor cornea cultivation in culture medium, 2. for single cell injection therapies and 3. to treat the patients' own endothelium in an effort to avoid transplantation.Several translational concepts exist to improve or to avoid grafting of a donor cornea. The coming decade will provide established alternatives to conventional corneal transplantation.
EVALuna2:21361

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317

Novel truncating mutation in CACNA1F in a young male patient diagnosed with optic atrophy - Pasutto, Francesca; Ekici, Arif Bülent; Reis, André; Kremers, Jan; Huchzermeyer, Cord (Ophthalmic Genetics, 2018)
BACKGROUND: Low vision in children can be accompanied by pallor of the optic disc with little or no characteristic morphologic changes of the retina. A variety of diseases can be the underlying cause, including hereditary optic atrophy, Leber's congenital amaurosis (LCA), achromatopsia, and calcium channel, voltage-dependent, L-type, alpha-1F subunit gene (CACNA1F)-associated retinopathy (most widely known as incomplete congenital stationary night blindness: iCSNB). Differentiation at early age is desirable due to large differences in prognosis, but may be difficult because phenotypes overlap and electrophysiological testing is challenging in young patients. We present the case of a 6-year-old boy with unexplained low vision and pallor of the optic disc who originally had been diagnosed with hereditary optic atrophy in the absence of recordable full-field electroretinography (ERG) due to poor patient cooperation. MATERIALS AND METHODS: Standard Sanger sequencing excluded mutations in the OPA1 gene (autosomal-dominant optic atrophy). To identify the underlying genetic cause, whole-exome sequencing was performed on patient's DNA. Recording of the full-field ERG was successfully performed 6 months later. RESULTS: We identified a novel truncating mutation in CACNA1F gene (NM_001256789: c.3895C > T in exon 33) which led to the correct diagnosis of CACNA1F-associated retinopathy in the young boy. ERG recordings showed a negative scotopic mixed response with preserved oscillatory potentials and a flicker ERG with reduced amplitude and biphasic waveform, compatible with a CACNA1F-asssociated phenotype. CONCLUSIONS: We show that genetic testing may help to differentiate between optic atrophy, LCA, and CACNA1F-associated retinopathy at a much earlier age, in absence of electrophysiological examination and by widely overlapping phenotypes.
EVALuna2:34838

Novel Visualization Approach of an Automated Image Based Glaucoma Risk Index for Intuitive Diagnosis - Meier, Jörg; Bock, Rüdiger; Nyul, Laszlo G.; Hornegger, Joachim; Michelson, Georg (Analysis of Biomedical Signals and Images, Proceedings of the Biosignal 2008 International Eurasip Conference, 2008)

Nutritional and hormonal regulation of lysyl oxidase-like 1 and elastic proteins involved in pseudoexfoliation syndrome/glaucoma - Zenkel, Matthias; Berner, Daniel; Hoja, Ursula; Pasutto, Francesca; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (2018)
EVALuna2:34739

Objective detection of visual field defects with multifrequency VEPs - Crux, Katja; Huchzermeyer, Cord; Kremers, Jan; Horn, Folkert (Documenta Ophthalmologica, 2023)
Purpose: To correlate multifrequency pattern reversal VEPs in quadrants (QmfrVEPs) with perimetric field losses for objective detection of visual field losses. Methods: QmfrVEP measurements were performed using four LED-based checkerboard stimulators to stimulate the four quadrants of the visual field. QmfrVEPs were measured monocularly in 5 normal subjects and in 5 glaucoma patients who showed losses in conventional Octopus perimetry. The pattern reversal frequency varied slightly between the stimulators: (11.92, 12.00, 12.08 and 12.16 reversals/sec). The responses to the different stimuli were identified by discrete Fourier analysis. VEPs were recorded using different electrode configurations, and the recording with the highest signal-to-noise ratio (SNR) was used for further analysis. Results: QmfrVEP responses from the different quadrants can be reliably measured and separated using the 0.08 reversals/sec interstimulus reversal frequency differences. The signal-to-noise ratio in the four quadrants was significantly correlated with the equivalent visual field losses obtained with perimetry (Spearman rank correlation: P < 0.001). In the five glaucoma patients, the SNR was reduced in 15 out of the 16 quadrants with a perimetric defect, in comparison to the results in quadrants of healthy subjects. This confirms the sensitivity of the procedure. Conclusion: QmfrVEP responses can be measured reliably. This pilot study suggests that high SNR values exclude visual field defects and that focal defects can be identified in glaucoma patients. Trial registration: www.clinicaltrials.gov . NCT00494923.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Objective visual field test; Pattern reversal; Quadrant multifrequency VEP; Signal-to-noise ratio; Steady state

Objective perimetry using a four-channel multifocal VEP system: correlation with conventional perimetry and thickness of the retinal nerve fibre layer - Horn, Folkert; Kaltwasser, Christoph; Jünemann, Anselm; Kremers, Jan; Tornow, Ralf-Peter (British Journal of Ophthalmology, 2012)
There is evidence that multifocal visual evoked potentials (VEPs) can be used as an objective tool to detect visual field loss. The aim of this study was to correlate multifocal VEP amplitudes with standard perimetry data and retinal nerve fibre layer (RNFL) thickness.Multifocal VEP recordings were performed with a four-channel electrode array using 58 stimulus fields (pattern reversal dartboard). For each field, the recording from the channel with maximal signal-to-noise ratio (SNR) was retained, resulting in an SNR optimised virtual recording. Correlation with RNFL thickness, measured with spectral domain optical coherence tomography and with standard perimetry, was performed for nerve fibre bundle related areas.The mean amplitudes in nerve fibre related areas were smaller in glaucoma patients than in normal subjects. The differences between both groups were most significant in mid-peripheral areas. Amplitudes in these areas were significantly correlated with corresponding RNFL thickness (Spearman R=0.76) and with standard perimetry (R=0.71).The multifocal VEP amplitude was correlated with perimetric visual field data and the RNFL thickness of the corresponding regions. This method of SNR optimisation is useful for extracting data from recordings and may be appropriate for objective assessment of visual function at different locations.This study has been registered at http://www.clinicaltrials.gov (NCT00494923).
EVALuna2:21033

Objective visual field determination in forensic ophthalmology with an optimized 4-channel multifocal VEP perimetry system: a case report of a patient with retinitis pigmentosa - Kaltwasser, C.; Horn, Folkert; Kremers, Jan; Jünemann, Anselm; Bergua, A. (Documenta Ophthalmologica, 2011)
We present the case of a 59-year-old male patient with progressive vision impairment and consecutive visual field narrowing ("tunnel view") for 7 years and a known retinitis pigmentosa for 5 years. The remaining Goldmann perimetric visual field at time reported was less than 5°. A request for blindness-related social benefits was rejected because an ophthalmologic expert assessment suggested malingering. This prompted us to assess an objective determination of the visual field using multifocal VEPs. Objective visual field recordings were performed with a four-channel multifocal VEP-perimeter using 58 stimulus fields (pattern reversal dartboard stimulus configuration). The correlated signal data were processed using an off-line method. At each field, the recording from the channel with the maximal signal-to-noise ratio (SNR) was retained, thus resulting in an SNR optimized virtual recording. Analysis of VEP signals was performed for each single field and concentric rings and compared to an average response measured in five healthy subjects. Substantial VEP responses could be identified in three fields within the innermost ring (eccentricity, 1.7°) for both eyes, although SNR was generally low. More eccentric stimuli did not elicit reliable VEP responses. The mfVEP recording was correlated with perimetric visual field data. The current SNR optimization by using the channel with the largest SNR provides a good method to extract useful data from recordings and may be appropriate for the use in forensic ophthalmology.
EVALuna2:21039

OCT and IOP findings in a healthy worker cohort: results from a teleophthalmic study in occupational medicine - Grau, Elisabeth; Horn, Folkert; Nixdorff, U.; Michelson, Georg (Graefes Archive For Clinical and Experimental Ophthalmology, 2019)
Purpose: To avoid significant loss of vision in employees, the working population could be examined with ophthalmic methods as OCT and IOP measurement for detection of serious eye diseases. The value of “virtual eye clinics” in occupational preventive medicine has been previously shown. We used a telemedical approach to gather epidemiological information about prevalence of eye diseases such as glaucoma, ocular hypertension, hypertensive retinopathy, diabetic retinopathy, epiretinal membrane, AMD, adult vitelliform maculopathy, cystoid maculopathy, choroidal nevi, and macular drusen. Methods: The study included 931 people ranging from age 39 to 65 years. Using a telemedical approach, all medical examinations and the ophthalmic examination were performed by a technician using an optical coherence tomography (SD-OCT) and a pulse air tonometer. The data were saved in the web-based patient chart MedStage® of the Talkingeyes® Collaboration Network. Results: We found a high prevalence of eye diseases in a group representative for the working-age population by telemedical examination. 13.47% of the workers examined showed ocular findings necessitating treatment or control by an ophthalmologist, including ocular hypertension (5.7%), hypertensive retinopathy with loss of temporal retinal nerve fiber thickness (2.3%), epiretinal membrane (1.07%), glaucoma (0.97%), age-related macular degeneration and adult vitelliform maculopathy (0.53%), and diabetic retinopathy (0.2%). Two of the examined persons presented ocular findings requiring urgent treatment to prevent serious vision loss. Conclusion: Using a telemedical approach, we collected epidemiological information about prevalence of eye diseases in the working-age population. Virtual eye clinics in occupational preventive medicine are a useful method to improve sight and reduce vision loss of workers by reducing travel time and inconvenience associated with an in-person appointment with an ophthalmologist.
CRIS-Team Scopus Importer:2019-10-29
Keywords: IOP; Occupational medicine; OCT scan; RNFL; Teleophthalmology

OCT-Angiography: agonistic beta 2-adrenergic receptor autoantibodies and FAZ-to-FAZ-ratio in glaucoma patients - Mardin, Christian Y.; Hosari, Sami; Wallukat, Gerd; Kunze, Rudolf; Herrmann, Martin; Lämmer, Robert; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

OCT Angiography as an Interdisciplinary Diagnostic Tool for Systemic Diseases OCT-Angiografie als interdisziplinäres Diagnostikum für Systemerkrankungen - Hohberger, Bettina; Mardin, Christian Y. (Klinische Monatsblätter für Augenheilkunde, 2021)
In recent years, OCT angiography (OCT-A) has emerged as a well established imaging modality of the retina. This allows non-invasive visualisation of the retinal circulation at a micrometer scale in eye disorders and systemic diseases with potential ocular involvement. This review summarises the current state of this topic.
CRIS-Team Scopus Importer:2021-12-24
Keywords: capillary; COVID-19; microcirculation; OCT-angiography; SARS-CoV-2; vessel density

OCT Angiography: Measurement of Retinal Macular Microvasculature with Spectralis II OCT Angiography - Reliability and Reproducibility - Hosari, Sami; Hohberger, Bettina; Theelke, Luisa; Sari, Hasan; Lucio, Marianna; Mardin, Christian Y. (Ophthalmologica, 2019)
Aim: The aim of the present study was to investigate the reliability of macular microvasculature measurements in normal subjects by Heidelberg Spectralis II optical coherence tomography angiography (OCT-A) in combination with a newly made software. Subjects and Methods: This prospective study included 23 eyes of 23 persons from the Erlangen Glaucoma Registry (ISSN 2191-5008, CS-2011; NTC00494923). The subjects underwent a complete clinical, standardized ophthalmologic examination to rule out any eye disease. En face OCT-A imaging was done using Heidelberg Spectralis II OCT (Heidelberg, Germany). Images were recorded with a 15 × 15° angle and a lateral resolution of 5.7 μm/pixel, resulting in a retinal section of 2.9 × 2.9 mm. The Erlangen-Angio-Tool (EA-Tool) OCT-A application performed multiple segmentations, allowing analysis of the vessel density in 12 segments. The software was coded in MATLAB. Macular data on the superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP) were exported into the application and analyzed separately. The EA-Tool calculated the percentage of "white area" in the "total area" of the region of interest, called vessel density. Foveolar avascular zones (FAZs) of the SVP, ICP, and DCP were calculated manually. To investigate the reproducibility of the new software, individual scans (SVP, ICP, and DCP) were analyzed twice with the EA-Tool and intraclass coefficients (ICCs) of the vessel density values were calculated. Statistical analysis was performed with SPSS version 21.0. Results: The mean vessel density of the SVP ranged between 30.4 and 33.5, that of the ICP between 20.9 and 24.7, and that of the DCP between 23.5 and 27.6. Bland-Altman plots showed a good reliability of two consecutive scans of each sector (S1-S12) in the SVP, ICP, and DCP. Testing reproducibility, no statistically significantly different sectorial coefficients of variation of the SVP, ICP, and DCP were observed (p > 0.05). The mean FAZ area of the SVP was 0.43 ± 0.16 mm2, that of the ICP 0.28 ± 0.1 mm2, and that of the DCP 0.44 ± 0.12 mm2. Conclusions: Spectralis OCT II, in combination with the semiautomated vessel density software EA-Tool, showed good or even excellent ICCs in 75% of all segments of the SVP, ICP, and DCP. The ICCs for the FAZ area in the SVP, ICP, and DCP were excellent.
CRIS-Team Scopus Importer:2019-09-24

OCT angiography: Measurement of retinal macular microvasculature with Spectralis II OCT angiography - reliability and reproducibility - Hosari, Sami; Mardin, Christian; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2021-10-18

OCT-Angiography: Mydriatic phenylephrine and tropicamide do not influence retinal microvasculature in macula and peripapillary region - Hohberger, Bettina; Müller, Manuela; Hosari, Sami; Mardin, Christian Y. (PLoS ONE, 2019)
PURPOSE: Optical coherence tomography angiography (OCT-A) enables visualization of retinal microcirculation. As a potential influence of mydriatic eye drops on retinal vessel density (VD) was proposed, the purpose of the present study was to investigate an influence of 5% phenylephrine and 0.5% tropicamide on macula and peripapillary VD. METHODS: 30 eyes of 30 healthy persons were measured by en face OCT-A (Spectralis OCT II, Heidelberg Engineering, Heidelberg). Scans of the macula (12 sectors, region of interest, ROI: 6.10 mm2) and peripapillary region (4 sectors, ROI: 2.67 mm2) were performed before (-) and 30 minutes after application of phenylephrine 5% and tropicamide 0.5% (+) eye drops (scan size was 8.41 mm2). Macula microcirculation was quantified in 3 retinal layers (superficial vascular plexus (SVP), deep capillary plexus (DCP), intermediate capillary plexus (ICP)). Data analysis was performed with the Erlangen-Angio-Tool. RESULTS: (I) Mean VD was 33.03±2.3 (SVP), 23.53±2.9 (ICP) and 25.48±4.2 (DCP) before and 33.12±2.4 (SVP), 23.74±2.9 (ICP) and 25.82±4.0 (DCP) with mydriasis respectively. (II) Sectorial analysis: 30.63±2.9-34.45±2.9 (-) and 31.04±2.9-34.34±2.7 (+) in SVP; 22.61±2.9-24.93±3.2 (-) and 22.75±2.5-25.20±3.0 (+) in ICP; 24.56±4.7-26.45±3.4 (-) and 25.00±4.1-27.07±3.5 (+) in DCP. (III) Peripapillary region showed a mean VD of 31.82±3.8 before and 31.59±4.3 after mydriasis. Sectorial analysis of VD yielded a range of 31.04±4.1-32.65±3.8 (-) and 30.98±4.4-31.89±4.1 (+). (IV) Macula and peripapillary VD were not different before and after mydriasis (p>0.05). CONCLUSION: Pharmacologic mydriasis did not influence retinal microcirculation in macula and peripapillary region enabling OCT-A scans with enhanced imaging process and scan quality.
CRIS-Team Scopus Importer:2019-10-25

OCT-angiography: Mydriatic phenylephrine and tropicamide do not influence retinal microvasculature in the macula and peripapillary region - Hohberger, Bettina; Müller, Meike; Hosari, Sami; Mardin, Christian (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

OCT-angiography: Regional reduced macula microcirculation in ocular hypertensive and pre-perimetric glaucoma patients - Hohberger, Bettina; Lucio, Marianna; Schlick, Sarah; Wollborn, Antonia; Hosari, Sami; Mardin, Christian Y. (PLoS ONE, 2021)
Purpose OCT-angiography (OCT-A) offers a non-invasive method to visualize retinochoroidal microvasculature. As glaucoma disease affects retinal ganglion cells in the macula, macular microcirculation is of interest. The purpose of the study was to investigate regional macular vascular characteristics in patients with ocular hypertension (OHT), pre-perimetric primary open-angle glaucoma (pre-POAG) and controls by OCT-A in three microvascular layers. Material and methods 180 subjects were recruited from the Erlangen Glaucoma Registry, the Department of Ophthalmology, University of Erlangen and residents: 38 OHT, 20 pre-POAG, 122 controls. All subjects received an ophthalmological examination including measurements of retinal nerve fibre layer (RNFL), retinal ganglion cell layer (RGC), inner nuclear layer (INL), and Bruch’s Membrane Opening-Minimum Rim Width (BMO-MRW). Macular vascular characteristics (vessel density, VD, foveal avascular zone, FAZ) were measured by OCT-A (Spectralis OCT II) in superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). Results With age correction of VD data, type 3 tests on fixed effects showed a significant interaction between diagnosis and sectorial VD in SVP (p = 0.0004), ICP (p = 0.0073), and DCP (p = 0.0003). Moreover, a significance in sectorial VD was observed within each layer (p<0.0001) and for the covariate age (p<0.0001). FAZ differed significantly between patients’ groups only in ICP (p = 0.03), not in SVP and DCP. For VD the AUC values of SVP, ICP, and DCP were highest among diagnostic modalities (AUC: 0.88, 95%-CI: 0.75–1.0, p<0.001). Conclusion Regional reduced macula VD was observed in all three retinal vascular layers of eyes with OHT and pre-POAG compared to controls, indicating localized microvascular changes as early marker in glaucoma pathogenesis.
CRIS-Team Scopus Importer:2021-03-05

OCT-Detected Optic Nerve Head Neural Canal Direction, Obliqueness, and Minimum Cross-Sectional Area in Healthy Eyes - Hong, Seungwoo; Yang, Hongli; Gardiner, Stuart K.; Luo, Haomin; Hardin, Christy; Sharpe, Glen P.; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Liebmann, Jeffrey M.; Mardin, Christian Y.; Quigley, Harry A.; et al. (American Journal of Ophthalmology, 2019)
Purpose: To assess anterior scleral canal opening (ASCO) offset relative to Bruch's membrane opening (BMO) (ASCO/BMO offset) so as to determine neural canal direction, obliqueness, and minimum cross-sectional area (NCMCA) in 362 healthy eyes. Design: Cross-sectional study. Methods: After optical coherence tomography optic nerve head and retinal nerve fiber layer thickness (RNFLT) imaging, BMO and ASCO were manually segmented. Planes, centroids, size, and shape were calculated. Neural canal direction was defined by projecting the neural canal axis vector (connecting BMO and ASCO centroids) onto the BMO plane. Neural canal obliqueness was defined by the angle between the neural canal axis and the BMO plane perpendicular vector. NCMCA was defined by projecting BMO and ASCO points onto a neural canal axis perpendicular plane and measuring the area of overlap. The angular distance between superior and inferior peak RNFLT was measured, and correlations between RFNLT, BMO, ASCO, ASCO/BMO offset, and NCMCA were assessed. Results: Mean (SD) NCMCA was significantly smaller than either the BMO or ASCO area (1.33 (0.42), 1.82 (0.38), 2.22 (0.43) mm2, respectively), and most closely correlated to RNFLT (P <.001, R2 = 0.158). Neural canal direction was most commonly superior-nasal (55%). Mean neural canal obliqueness was 39.4° (17.3°). The angular distance between superior and inferior peak RNFLT correlated to neural canal direction (P ≤.008, R2 = 0.093). Conclusions: ASCO/BMO offset underlies neural canal direction, obliqueness, and NCMCA. RNFLT is more strongly correlated to NCMCA than to BMO or ASCO, and its peripapillary distribution is influenced by neural canal direction.
CRIS-Team Scopus Importer:2019-10-11

Ocular diseases in metastatic cutaneous melanoma: review of 108 consecutive patients in two German tertiary centers - Grajewski, Rafael S.; Schuler-Thurner, Beatrice; Mauch, Cornelia; Kreuzberg, Nicole; Koch, Konrad R.; Bergua, Antonio; Cursiefen, Claus; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2014)
To analyze the incidence and spectrum of ocular disease in patients with metastatic cutaneous melanoma.One hundred and eight consecutive patients with metastatic cutaneous melanoma were screened for ocular diseases using standardized eye examination, including measurement of visual acuity and intraocular pressure, slit-lamp examination, funduscopy in mydriasis, and spectral-domain optical coherence tomography (SDOCT) of the retina. Selected cases with atypical findings underwent electrophysiological studies. One patient was examined for hypercortisolism by a dexamethasone suppression test.Ocular diseases were found in 65 out of 108 patients (60 %) with metastatic cutaneous melanoma, significantly more often in older patients (p = 0.004). Cataract was present in 27 patients (25 %), pseudophakia in 22 patients (20 %), macular disease in 29 patients (28 %), diabetic retinopathy in ten patients (9 %), hypertensive retinal disease in 14 patients (13 %), retinal venous and arterial occlusive disease in three patients (3 %), optic neuropathy in four patients (4 %), and uveitis in one patient (1 %). Eight patients (8 %) had choroidal or iridal nevi, one patient (1 %) choroidal hemangioma, and one patient (1 %) choroidal metastasis. No patient had periocular neoplastic lesions. Paraneoplastic retinopathy manifesting as acute exudative polymorphous vitelliform maculopathy (AEPVM)-like disease was diagnosed in two patients (2 %) with multifocal central serous chorioretinopathy and development of vitelliform or fibrin-like subretinal deposits in one patient.Patients with metastatic cutaneous melanoma reveal ocular diseases with a spectrum similar to the normal population of this age range. Very rarely, uveal metastasis as well as paraneoplastic retinopathy can occur.
EVALuna2:19483

Oligophrenin-1 (Ophn1) is expressed in mouse retinal vessels - Sel, Saadettin; Kaiser, Maja; Nass, Norbert; Trau, Stefanie; Roepke, Albrecht; Storsberg, Joachim; Hampel, Ulrike; Paulsen, Friedrich; Kalinski, Thomas (Gene Expression Patterns, 2012)
The Rho GTPase activating protein (RhoGAP) Oligophrenin 1 (Ophn1) regulates numerous members of the Rho family that are involved in neuronal morphogenesis of the central and peripheral nervous system. In the present study we investigated the spatial and temporal expression of Ophn1 in the mouse eye. The expression of Ophn1 was analysed on both mRNA and protein level. To identify the Ophn1 transcripts, adult retina and cerebrum (positive control) of postnatal day (P) 158 was subjected to reverse transcription polymerase chain reaction (RT-PCR) and sequencing of the amplified cDNA. The Ophn1 protein was analyzed in adult retina by Western blotting and in developing eyes at embryonic day (E) 12, E14, E16, E18, P0, P3, P7, P14 and P158 by immunohistochemistry. Ophn1 transcripts were detected in adult retina by RT-PCR and confirmed by sequencing. Western blot analysis revealed the expression of Ophn1 protein in the adult retina. Immunohistochemical examination of developing eyes localized the protein to retinal vasculature with an onset of Ophn1 expression from P14 onwards. The specific expression pattern suggests that Ophn1 could have a physiological role in the retinal vasculatures. At P14, the vessel development in the retina is widely completed, implying that Ophn1 has either a function during adulthood or for the generation of the intermediate plexus during the late vessel development of the retina.
EVALuna2:4385

ON and OFF electroretinography and contrast sensitivity in Duchenne muscular dystrophy - Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; De Araujo Moura, Ana Laura; Damico, Francisco Max; Da Costa, Marcelo Fernandes; Kremers, Jan; Ventura, Dora Fix (Investigative Ophthalmology & Visual Science, 2013)
The study investigated possible asymmetric dysfunction of the ON and OFF visual mechanisms in DMD (Duchenne muscular dystrophy) patients associated with specific genetic alterations. Methods: nineteen DMD patients and 7 heterozygous dmd carriers were tested, as well as 19 age-matched controls.Full-field ergs were recorded using mesopic (1 cd/m(2)) and photopic (250 cd/m(2)) sawtooth luminance modulations as stimuli: rapid increase and ramping decrease (to isolate ON responses) or rapid decrease and ramping increase (for OFF responses). In addition, a psychophysical study comprised contrast sensitivity tests using two checkerboard stimuli at either higher (ON) or lower (OFF) luminance relative to the background: 0.3 cycles per degree (cpd) presented for 33 ms (low spatial frequency, short duration) and 2 cpd presented for 1500 ms (high spatial frequency, long duration).A significant ERG amplitude reduction, relative to controls, was detected in the DMD patients in the mesopic positive peaks for both ON and OFF stimuli, as well as for the photopic ON stimulus (P < 0.05). Contrast sensitivity was significantly lower in the DMD patients (P < 0.05) relative to controls for the ON stimuli. Neither the ERG nor the contrast sensitivities were altered in the carriers.This study suggests that there are ON and OFF ERG alterations when both rods and cones contribute to the ERG responses in DMD patients. When only cones are activated there is an asymmetrical ERG alteration, also revealed by the contrast sensitivity measurements.
EVALuna2:21134
Keywords: Electroretinogram; ON OFF pathways; Contrast sensitivity; Dystrophin; Retina

On- and off-response ERGs elicited by sawtooth stimuli in normal subjects and glaucoma patients - Pangeni, Gobinda; Lämmer, Robert; Tornow, Ralf-Peter; Horn, Folkert; Kremers, Jan (Documenta Ophthalmologica, 2012)
The aim of this study is to measure the on- and off-responses and their response asymmetries elicited by sawtooth stimuli in normal subjects and glaucoma patients. Furthermore, the correlation between the ERGs and other functional and structural parameters are investigated. Full-field stimuli were produced using a Ganzfeld bowl with Light Emitting Diodes (LEDs) as light sources. On- and off-response ERGs were recorded from 17 healthy subjects, 12 pre-perimetric and 15 perimetric glaucoma patients using 4-Hz luminance rapid-on and rapid-off sawtooth stimuli (white light; mean luminance 55 cd/m(2)) at 100% contrast. The on- and off-responses were added to study response asymmetries. In addition, flash ERGs were elicited by red stimuli (200 cd/m(2)) on a blue background (10 cd/m(2)). The mean deviations (MD) of the visual field defects were obtained by standard automated perimetry. The retinal nerve fibre layer thickness (RNFLT) was measured with Spectral Domain Optical Coherence Tomography (SOCT). We studied the correlation between ERG response amplitudes, visual field mean deviation (MDs) and RNFLT values. The on-responses showed an initial negative (N-on) followed by a positive (P-on), a late positive (LP-on) and a late negative responses (LN-on). The off-responses showed an initial positive (P-off) a late positive (LP-off) and a late negative response (LN-off). The addition of on- and off-responses revealed an initial positive (P-add) and a late negative response (LN-add). The on-response components (N-on, P-on and LN-on) in the glaucoma patients were relatively similar to those of the control subjects. However, the LP-on was significantly elevated (p = 0.03) in perimetric patients. The LP-off was significantly elevated (p < 0.001), and the amplitude of LN-off was significantly reduced in perimetric patients (p = 0.02). The LN-add amplitude was significantly reduced (p < 0.001) and delayed (p = 0.03) in perimetric patients. The amplitudes of the LN-off and LN-add ERG components were significantly correlated with the PhNR in the flash ERG (LN-off: p = 0.01; LN-add: p < 0.001) and with RNFLT (LN-off: p = 0.006; LN-add: p = 0.001). On- and off-response ERGs and their response asymmetries, elicited by sawtooth stimuli, are altered in the glaucoma patients. The late components are affected. Changes in the late negative components are correlated with structural and other functional changes.
EVALuna2:21076
Keywords: Electroretinogram; On- and off-responses; Glaucoma; Sawtooth stimuli

On and off responses of the photopic fullfield ERG in normal subjects and glaucoma patients - Horn, Folkert; Gottschalk, Kristina; Mardin, Christian Y.; Pangeni, Gobinda; Jünemann, Anselm; Kremers, Jan (Documenta Ophthalmologica, 2011)
Recent studies suggest a diagnostic value of the photopic negative response (PhNR) with a long-duration stimulus. The aim of this study was to record the on and off responses of the photopic fullfield electroretinogram (ERG) in normal subjects and glaucoma patients. We focused on different waves of the responses after onset and offset of the long-duration stimulus ERG. Photopic fullfield ERGs were recorded in response to a white bright LED flash on a white 20 cd/m(2) background. Stimulus luminances were 40, 60 and 80 cd/m(2). Responses were averaged using a flash duration of 240 ms and an offset period of 500 ms. We examined 19 healthy subjects, 27 patients with glaucomatous optic disc atrophy and 7 ocular hypertensive patients. The amplitudes and implicit times of the on and off responses of the human ERG depended on flash luminance. Comparing patients with glaucoma and healthy subjects for the 60 cd/m² flash, there was a significant change in the PhNRs (at onset: P < 0.01, at offset: P < 0.001) of the d-wave and of the i-wave at offset (P < 0.01). No significant difference was found for peak times of the fullfield ERG and for a- and b-wave amplitudes. PhNR amplitudes were significantly correlated with mean thickness of retinal nerve fibre layer as measured with OCT. In comparison with the normal photopic long-flash ERG, glaucoma patients showed changes in the PhNR amplitude following stimulus onset and in waves following stimulus offset.
EVALuna2:20998
Keywords: Electroretinogram; Glaucoma; Onset/offset fullfield ERG; Photopic negative response

Optical clearing of the eye using the See Deep Brain technique - Hohberger, B.; Baumgart, Carina; Bergua, A. (Eye, 2017)
PurposeTissue clearing has been used in anatomy for the first time in Germany over a century ago. Neuronal tissue, like cortex, was investigated in mice using a water-based optical clearing method termed See Deep Brain (SeeDB). However, although the eye belongs to the central nervous system, this histological technique was not applied in the eye up to date. We applied SeeDB for the visualization of intraocular structures.Patients and methodsFour eyes of cornea donors (two male, two female: 73-84 years) obtained from the Cornea Bank of the Department of Ophthalmology Erlangen, four chicken eyes and two mices' optic nerve were used. Bulbi were fixed in 4% paraformaldehyde in phosphate-buffered saline and treated with increasing concentrations of aqueous fructose solution with 0.5% ?-thioglycerol. After SeeDB, transscleral macrophotographs of the choroid were performed.ResultsComplete transparency of the sclera was obtained in enucleated human and chicken eyes after SeeDB treatment. Macroscopical anatomy of the choroid (partially transparent due to the remaining retinal pigment epithelium and melanocytes) showing vessels and other related structures was possible without preparing slides. Mice optic nerves were also transparent after SeeDB treatment.ConclusionThe SeeDB method allows visualization of intraocular structures through a completely translucent sclera. This innovative processing technique could facilitate comprehensive qualitative and quantitative topographical anatomical studies of human and animal eyes, preserving their 3D architecture. Supra- and intrachoroidal ganglionic plexus could potentially be visualized transsclerally. Finally, clinical-pathological correlations of intraocular diseases-for example, retinal tumors-will be possible in non-dissected eyes.Eye advance online publication, 2 June 2017; doi:10.1038/eye.2017.83.
EVALuna2:21275

Optical Coherence Tomographic Optic Nerve Head Morphology in Myopia III: The Exposed Neural Canal Region in Healthy Eyes—Implications for High Myopia - Hong, Seungwoo; Yang, Hongli; Gardiner, Stuart K.; Luo, Haomin; Sharpe, Glen P.; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Quigley, Harry A.; Scheuerle, Alexander F.; Fortune, Brad; et al. (American Journal of Ophthalmology, 2024)
Purpose: To determine the prevalence and magnitude of optical coherence tomography (OCT) exposed neural canal (ENC), externally oblique choroidal border tissue (EOCBT), and exposed scleral flange (ESF) regions in 362 non–highly myopic (spherical equivalent –6.00 to 5.75 diopters) eyes of 362 healthy subjects. Design: Cross-sectional study. Methods: After OCT optic nerve head (ONH) imaging, Bruch membrane opening (BMO), the anterior scleral canal opening (ASCO), and the scleral flange opening (SFO) were manually segmented. BMO, ASCO, and SFO points were projected to the BMO reference plane. The direction and magnitude of BMO/ASCO offset as well as the magnitude of ENC, EOCBT, and ESF was calculated within 30° sectors relative to the foveal-BMO axis. Hi-ESF eyes demonstrated an ESF ≥100 µm in at least 1 sector. Sectoral peri–neural canal choroidal thickness (pNC-CT) was measured and correlations between the magnitude of sectoral ESF and proportional pNC-CT were assessed. Results: Seventy-three Hi-ESF (20.2%) and 289 non–Hi-ESF eyes (79.8%) were identified. BMO/ASCO offset as well as ENC, EOCBT, and ESF prevalence and magnitude were greatest inferior temporally where the pNC-CT was thinnest. Among Hi-ESF eyes, the magnitude of each ENC region correlated with the BMO/ASCO offset magnitude, and the sectors with the longest ESF correlated with the sectors with proportionally thinnest pNC-CT. Conclusions: ONH BMO/ASCO offset, either as a cause or result of ONH neural canal remodeling, corresponds with the sectoral location of maximum ESF and minimum pNC-CT in non–highly myopic eyes. Longitudinal studies to characterize the development and clinical implications of ENC Hi-ESF regions in non–highly myopic and highly myopic eyes are indicated.
CRIS-Team Scopus Importer:2023-12-22

Optical coherence tomography angiography for differential diagnosis of multiple sclerosis and Sjogren's syndrome - Wolf, E.; Wicklein, R.; Aly, L.; Schmaderer, C.; Berthele, A.; Mardin, Christian Y.; Korn, T.; Hemmer, B.; Hofauer, B.; Knier, B. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Optical coherence tomography in patients with a history of juvenile multiple sclerosis reveals early retinal damage - Huhn, K.; Lämmer, Robert; Oberwahrenbrock, T.; Laemmer, A.; Waschbisch, Anne; Gosar, D.; Brandt, A.; Paul, Friedemann; Linker, R. A.; Lee, D. -H. (European Journal of Neurology, 2015)
Some 3%-10% of patients with multiple sclerosis (MS) experience disease onset before the age of 18 years ('early' onset MS, EOMS). Optical coherence tomography is a non-invasive method to measure retinal nerve fibre layer thickness (RNFLT) and total macular volume (TMV) and may be useful to differentiate axonal and neuronal damage in the retina of patients with a history of EOMS. Here RNFLT and TMV in EOMS patients after a mean disease duration of 11.6 years were compared with patients with age- or disease-duration-matched later onset MS (LOMS) and healthy controls (HCs).In this observational cross-sectional study at two German academic MS centres, RNFLT and TMV were measured by spectral-domain optical coherence tomography in 32 HCs, 36 EOMS (mean age at onset 15.5 ± 2.0 years) and 58 LOMS patients.In comparison with HCs, EOMS patients displayed a significant reduction of RNFLT and TMV independently of a history of optic neuritis. In particular, RNFLT loss in EOMS was similar to that in LOMS and TMV loss was slightly higher compared with disease-duration-matched LOMS. In a generalized estimating model, the EOMS group also displayed a similar correlation between disease duration and RNFLT or TMV loss to LOMS patients.These data argue for a significant amount of axonal and neuronal damage in the retina of EOMS patients and may provide a structural basis for the observation that EOMS patients reach states of irreversible disability at a younger age than patients with LOMS.
EVALuna2:21183

Optical Coherence Tomography (OCT) Anterior Scleral Canal Opening (ASCO) Tilt and Rotation relative to Bruch's Membrane Opening (BMO) and Peripapillary Scleral Bowing (PSB) in Healthy Eyes - Wang, Ya Xing; Yang, Hongli; Luo, Haomin; Hong, Seung Woo; Gardiner, Stuart Keith; Jeoung, Jin Wook; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Liebmann, Jeffrey M.; Mardin, Christian Y.; Quigley, Harry A.; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Optimierte Segmentierung der Papille in HRT-Retinaaufnahmen - Arold, Oliver; Bock, Rüdiger; Meier, Jörg; Michelson, Georg; Hornegger, Joachim (Bildverarbeitung für die Medizin 2008 - Algorithmen, Systeme, Anwendungen, 2008)

Optimized human platelet lysate as novel basis for a serum-, xeno- and additive-free corneal endothelial cell and tissue culture - Thieme, Daniel; Reuland, Lynn; Lindl, Toni; Kruse, Friedrich; Fuchsluger, Thomas (Journal of Tissue Engineering and Regenerative Medicine, 2017)
The expansion of donor derived corneal endothelial cells is a promising approach for regenerative therapies in corneal diseases. To achieve the best GMP standard the entire cultivation process should be devoid of non-human components. However, so far there is no suitable xeno-free protocol for clinical applications.We therefore introduce a processed variant of a platelet lysate for the use in corneal cell and tissue culture based on a GMP-grade thrombocyte concentrate. This processed human platelet lysate (phPL), free of any animal components and of anti-coagulants like heparin with a physiological ionic composition, was used to cultivate corneal endothelial cells (EC) in vitro and ex vivo in comparison to standard cultivation with FCS. Human donor corneas were cut in quarters while two quarters of each cornea were incubated with the respective medium supplement. Three fields of view per quarter were taken into account for the analysis.Evaluation of phPL as a medium supplement in cell culture of immortalized EC showed a superior viability compared to fetal calf serum (FCS) control with reduced cell proliferation. Furthermore, the viability during the expansion of primary cells is significantly (3fold+-0.5) increased with phPL compared to FCS standard medium. Quartering donor corneas was traumatic for the endothelium and therefore resulted in increased EC loss. Interestingly, however, cultivation of the quartered pieces for two weeks in 0.1mg/mL pHPL in Biochrome I showed a 21 (+-10) % EC loss compared to 67 (+-12) % EC loss when cultivated in 2% FCS in Biochrome I.The cell culture protocol with pHPL as FCS replacement seems to be superior to the standard FCS protocols with respect to EC survival. It offers a xeno-free and physiological environment for corneal endothelial cells. This alternative cultivation protocol could facilitate the use of EC for human corneal cell therapy.
EVALuna2:21343

Optimizing outcomes with Descemet's membrane endothelial keratoplasty - Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos (Current Opinion in Ophthalmology, 2014)
To review recent advances in posterior lamellar keratoplasty and to describe strategies that enhance the outcome of Descemet's membrane endothelial keratoplasty (DMEK) and should lead to a more widespread use of this technique.DMEK offers significant advantages over Descemet's stripping automated endothelial keratoplasty (DSAEK) such as less immune reaction and better visual acuity because of less higher order aberrations. Donor selection should exclude donors under 50 years because of tissue elasticity; several advanced techniques now allow donor preparation from both cold and organ-cultured tissue in about 99% minimizing the risk of graft loss. Oversizing the area of Descemet's stripping in relationship to graft size enhances graft attachment and use of a standardized approach for graft delivery. Air bubble-driven nontouch unfolding techniques and, possibly, gas tamponade in the anterior chamber further enhance graft attachment and reduce surgery-induced endothelial cell loss. Graft orientation is made earlier by marking, slit beam and optical coherence tomography. Novel understanding of the functional anatomy of Descemet's membrane as well as migration of endothelial cells will allow to further refine DMEK and improve its outcome.Although the superiority of DMEK over Descemet's stripping automated endothelial keratoplasty in terms of safety and functionality had been further elucidated, remarkable progress has been made in the recent past regarding tissue preparation, insertion and intraoperative manipulation that will foster the more widespread use of DMEK among corneal surgeons.
EVALuna2:21204

Optische Kohärenztomographie-Angiographie bei neuronalen Erkrankungen - Mardin, Christian; Hosari, Sami (Ophthalmologe, 2019)
Background: Optical coherence tomography angiography (OCTA) enables a noninvasive detailed imaging of retinal and choroidal vessels of the fundus. In neuronal diseases changes in retinal structures can be imaged and measured with OCT and OCTA. Objective: Can OCTA be used in neuronal diseases? Material and methods: Evaluation of recent scientific articles and studies extracted from Medline on the topic of OCTA and neuronal diseases. Results: It could be shown that Alzheimer type dementia, Parkinson’s disease, multiple sclerosis. cerebral infarction and CADASIL are neuronal diseases with rarification of retinal vessels and atrophy of the retinal layers in the ocular fundus. Conclusion: These findings are beyond all changes which can be appreciated with ophthalmoscopy and OCTA parameters could serve in the future as supplementary biomarkers for assessment of the retinal-neurovascular coupling in these diseases.
EVALuna2:205877
Keywords: Alzheimer’s disease; CADASIL; Cerebral infarction; Multiple sclerosis; Parkinson’s disease

Optische Kohärenztomographie-Angiographie: Stellenwert in der Glaukomdiagnostik - Alnawaiseh, M.; Lahme, L.; Eter, N.; Mardin, C. (Ophthalmologe, 2019)
Background: Optical coherence tomography angiography (OCTA) is a novel noninvasive method which enables a quantitative evaluation of retinal and optic nerve head (ONH) perfusion. In this article, we discuss the principles of the application of OCTA and give a summary of the knowledge gained by using this method in glaucoma patients. Methods: This article is based on a selective literature search and the analysis of own data. Results: Quantitative OCTA parameters have a good reproducibility in glaucoma patients. Glaucoma patients show a reduced flow density (FD) in the ONH and in the area of the macula compared with a healthy control group. The FD parameters show a good diagnostic discriminatory power but are not superior to the structural parameters used in routine diagnostics. The reduced FD measured using OCTA correlates with the extent of functional and structural glaucoma damage. Conclusion: The OCTA is noninvasive, fast and reproducible. Initial results from studies on glaucoma patients show the high diagnostic potential of this method. The OCTA could become a part of clinical glaucoma management in the future.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Flow density; Foveal avascular zone; Glaucoma; Optical coherence tomography angiography; Reproducibility

Organ-cultured, prestripped donor tissue for DMEK surgery: clinical outcomes - Menzel-Severing, Johannes; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2017)
To determine whether clinical performance is negatively affected by prestripping Descemet membrane endothelial keratoplasty (DMEK) grafts from organ-cultured corneas.We reviewed clinical records of all patients who underwent DMEK surgery for Fuchs endothelial dystrophy between 28 October 2014 and 11 August 2015. Grafts had been prepared from organ-cultured corneoscleral buttons 24 hours prior to surgery or during surgery. We included only patients for which at least one follow-up examination was available at a minimum of 2 months postoperatively.best-corrected visual acuity (BCVA), central corneal thickness, endothelial cell count and rebubbling rates.Data given are mean±SD. No statistically significant differences were recorded at baseline between the partially stripped group (n=65) and the control group (n=72) with regard to donor age (70±9 vs 69±8 years; p=0.49), donor cornea endothelial cell density (2586±604 vs 2522±186 cells/mm(2); p=0.6), BCVA (before DMEK: 0.77±0.5 vs 0.63±0.3 logMAR; p=0.27; before triple-DMEK: 0.56±0.2 vs 0.52±0.2 logMAR; p=0.33) or central corneal thickness (621±72 vs 607±53 ?m; p=0.49). Mean follow-up was 149±83 versus 148±77 days; p=0.79. No statistically significant differences were observed between the two groups postoperatively with regard to BCVA (after DMEK: 0.25±0.2 vs 0.21±0.2 logMAR; p=0.59; after triple-DMEK: 0.22±0.2 vs 0.2±0.1 logMAR; p=0.98), central corneal thickness (502±42 vs 508±41 ?m; p=0.47), endothelial cell count (1537±245 vs 1551±287 cells/mm(2); p=0.65) and number of graft detachments requiring rebubbling (4.6% vs 9.7%; p=0.33).We found no evidence that the use of prestripped DMEK grafts is inferior to same-day preparation in organ-cultured corneas within the given follow-up.
EVALuna2:21351

Other Causes of Limbal Stem Cell Deficiency Reply - Deng, Sophie X.; Borderie, Vincent; Chan, Clara C.; Dana, Reza; Figueiredo, Francisco C.; Gomes, Jose A. P.; Pellegrini, Graziella; Shimmura, Shigeto; Kruse, Friedrich (Cornea, 2019)
CRIS-Team WoS Importer:2020-02-14

Palate Lung Nasal Clone (PLUNC), a Novel Protein of the Tear Film: Three-Dimensional Structure, Immune Activation, and Involvement in Dry Eye Disease (DED) - Schicht, Martin; Rausch, Felix; Beron, Martin; Jacobi, Christina; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Kruse, Friedrich; Bräuer, Lars; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Palate Lung Nasal Clone (PLUNC) is a hydrophobic protein belonging to the family of surfactant proteins that is involved in fluid balance regulation of the lung. Moreover, it is known to directly act against gram-negative bacteria. The purpose of this study was to investigate the possible expression and antimicrobial role of PLUNC at the healthy ocular surface and in tears of patients suffering from dry eye disease (DED).Bioinformatics and biochemical and immunologic methods were combined to elucidate the structure and function of PLUNC at the ocular surface. Tissue-specific localization was performed by using immunohistochemistry. The PLUNC levels in tear samples from non-Sjögren's DED patients with moderate dry eye suffering either from hyperevaporation or tear deficiency were analyzed by ELISA and compared with tears from healthy volunteers.Palate Lung Nasal Clone is expressed under healthy conditions at the ocular surface and secreted into the tear film. Protein modeling studies and molecular dynamics simulations performed indicated surface activity of PLUNC. In vitro experiments revealed that proinflammatory cytokines and bacterial supernatants have only a slight effect on the expression of PLUNC in HCE and HCjE cell lines. In tears from DED patients, the PLUNC concentration is significantly increased (7-fold in evaporative dry eye tears and 17-fold in tears from patients with tear deficiency) compared with healthy subjects.The results show that PLUNC is a protein of the tear film and suggest that it plays a role in fluid balance and surface tension regulation at the ocular surface.
EVALuna2:4442

Papilledema and Echographically Detectable Retro-orbital Dilatation of the Sub-arachnoidal Space with open Fontanelle - Six Case Reports - Gusek-Schneider, G. C.; Mardin, Christian Y.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas (Klinische Monatsblätter für Augenheilkunde, 2011)
This paper analyses the case reports for three children in which a papilledema occurred before the age of one year. Furthermore, an analysis is also given of three further case reports for children aged less than one year in which, in spite of open fontanelle, no papilledema was found, however, a dilatation of the sub-arachnoidal space was demonstrated echographically. Even in children less than one year of age in which an open fontanelle still exists and in whom a neuro-paediatric clarification of internal hydrocepalus is made, in spite of opththalmoscopically inconspicuous findings for the papilla an echography is indispensable for the evaluation of the sub-arachnoidal space. Here, the early recognition of a dilatation of the retro-bulbar sub-arachnoidal space can possibly prevent the occurrence of a consecutive optic atrophy. At the present time, the data available do not allow the recommendation of an upper age limit for an echographic examination.
EVALuna2:21040

Paradoxical pupil responses to isolated M-cone increments - Murray, Ian J.; Kremers, Jan; Mckeefry, Declan; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
M-cone onsets appear dimmer than the background and elicit electroretinograms (ERGs) resembling the light offset response. We sought a corresponding anomalous pupillary light reflex (PLR) using a 4-primary ganzfeld as stimulator and pupillometer. Increments and decrements of white light were compared with M- and L-cone onsets and offsets using silent substitution. Luminance bias (LB) could be added to or subtracted from the cone-isolating stimuli. There was a normal PLR to L-cone increments, but the pupil constricted mainly to M-cone decrements. Changing LB produced a neutral point where on and off responses were balanced. The results reflect ERG and psychophysical studies. This observation may be linked to the antagonistic nature of the M-cone input to cone opponent mechanisms.
EVALuna2:34924

Parapapillary atrophy: histological gamma zone and delta zone - Jonas, Jost B.; Jonas, Shefali B.; Jonas, Rahul A.; Holbach, Leonhard; Dai, Yi; Sun, Xinghuai; Panda-Jonas, Songhomitra (PLoS ONE, 2012)
To examine histomorphometrically the parapapillary region in human eyes.The histomorphometric study included 65 human globes (axial length:21-37 mm). On anterior-posterior histological sections, we measured the distance Bruch's membrane end (BME)-optic nerve margin ("Gamma zone"), BME-retinal pigment epithelium (RPE) ("Beta zone"), BME-beginning of non-occluded choriocapillaris, and BME-beginning of photoreceptor layer. "Delta zone" was defined as part of gamma zone in which blood vessels of at least 50 µm diameter were not present over a length of >300 µm. Beta zone (mean length:0.35±0.52 mm) was significantly (P = 0.01) larger in the glaucoma group than in the non-glaucomatous group. It was not significantly (P = 0.28) associated with axial length. Beta zone was significantly (P = 0.004) larger than the region with occluded choriocapillaris. Gamma zone (mean length:0.63±1.25 mm) was associated with axial length (P<0.001;r(2) = 0.73) with an increase starting at an axial length of 26.5 mm. It was not significantly (P = 0.24) associated with glaucomatous optic neuropathy. Delta zone (present only in eyes with axial length of >=27 mm) was associated with axial length (P = 0.001) and scleral flange length (P<0.001) but not with glaucoma (P = 0.73).Parapapillary gamma zone (peripapillary sclera without overlying choroid, Bruch's membrane and deep retinal layers) was related with axial globe elongation and was independent of glaucoma. Delta zone (no blood vessels >50 µm diameter within gamma zone) was present only in highly axially elongated globes and was not related with glaucoma. Beta zone (Bruch's membrane without RPE) was correlated with glaucoma but not with globe elongation. Since the region with occluded choriocapillaris was smaller than beta zone, complete loss of RPE may have occurred before complete choriocapillaris closure.
EVALuna2:21086

Pathogenesis of involutional ectropion and entropion: the involvement of matrix metalloproteinases in elastic fiber degradation - Damasceno, Renato W.; Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Belfort, Rubens; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Holbach, Leonard M. (Orbit, 2011)
Purpose: To determine the elastic fiber content and ultrastructure as well as the expression of elastin-degrading enzymes in biopsy specimens from patients with involutional ectropion and entropion. Materials and Methods: Twenty consecutive patients with involutional ectropion (group 1) and twenty consecutive patients with entropion (group 2) were matched with twenty control patients (basal cell carcinoma) regarding age and gender. Full-thickness eyelid resections performed in study and control patients were examined by light and transmission electron microscopy, computer-assisted measurements, and immunohistochemistry using antibodies against matrix metalloproteinase (MMP)-2, MMP- 7, and MMP-9. The Kruskal-Wallis test and the Pearson chi-square test were performed. Results: Histopathologic analysis of the surgical specimens from patients with involutional ectropion and entropion showed a significant loss of elastic fibers in the eyelid skin, the pretarsal orbicularis oculi muscle, the perimeibomian tarsal stroma, and the intermeibomian tarsal stroma (P < 0.001). Residual elastic fibers revealed an abnormal ultrastructure. Immunohistochemistry demonstrated a significant overexpression of MMP- 2, MMP-7, and MMP-9 in the eyelid skin, the pretarsal orbicularis oculi muscle, the perimeibomian tarsal stroma, the intermeibomian tarsal stroma, and the conjunctiva in groups 1 and 2 compared to controls (P < 0.001). Conclusions: The present findings indicate that upregulation of elastolytic enzymes contributes to elastic fibre degradation in patients with involutional ectropion and entropion.
EVALuna2:21015

Pathology and prognostic factors of conjunctival melanoma - Berta-Antalics, A. I.; Kruse, Friedrich; Holbach, L. (Ophthalmologe, 2015)
Conjunctival melanoma is a rare but potentially fatal disease. The 10-year melanoma mortality can be up to 30 %, recurrence rates after treatment up to 50 % and the overall incidence of metastasis is 26 %. Improved treatment options are needed to increase the tumor-free survival of affected patients.The aim of the study was to perform clinical and pathological staging using the TNM classification and to correlate the results with treatment modalities and recurrence rates.The study included a case series of 80 eyes from 80 patients (42 females and 38 males, age 28-90 years) with histopathologically proven conjunctival melanoma studied by reviewing medical records, pathology reports and color photographs. The main evaluated characteristics were demographic information, tumor size, thickness, pathological diagnosis, BRAF mutation testing, clinical and pathological staging, recurrence, metastasis and duration of follow-up (mean 48 months).The lesions predominantly involved the bulbar conjunctiva (60 %) and other sites that were less often involved were the palpebral conjunctiva (23 %), conjunctival fornix (22 %) and lacrimal caruncle (15 %). Of the tumors 36 % were TNM classified as pTis, 34 % as pT1, 20 % as pT2 (palpebral, fornix and caruncle) and 10 % as pT3. Local recurrences were noted in 36 % of the patients (18 % Tis, 26 % T1, 32 % T2 and 70 % T3) and regional and distant metastasis in 20 % of the patients (0 % Tis, 10 % T1, 15 % T2 and 60 % T3).In this study increasing T stages were more often associated with recurrences and metastasis. Future studies correlating the TNM staging with histopathological and genetic predictors may help to improve the management of patients with conjunctival melanoma.
EVALuna2:21241

Pathway-specific light adaptation in human electroretinograms - Brasil, Alódia; Tsai, Tina I.; da Silva Souza, Givago; Herculano, Anderson Manoel; Ventura, Dora Fix; de Lima Silveira, Luiz Carlos; Kremers, Jan (Journal of Vision, 2019)
The cellular origins of slow ERG changes during light adaptation following a dark-adapted state are still unclear. To study light adaptation, six healthy, normal trichromats were dark-adapted for 30 min prior to full-field ERG recordings to sinusoidal stimuli that isolate responses of the L- or M-cones or that stimulate luminance and chromatic mechanisms at 12 or 36 Hz. Recordings were performed for 16 min with 2-min intervals after onset of a constant background. Generally, the responses were sine-wave-like, and the first harmonic (fundamental) component dominated the Fourier spectrum except for the 12-Hz luminance stimulus in which two components, a sine-wave-like component and a transient component, determined the response profiles, leading to large second harmonic components. The amplitude of the first harmonic component (F) increased as a function of the light-adaptation time except for the 12-Hz luminance stimulus at which the F component decreased as a function of the light-adaptation period. The phase of the first harmonic component changed only slightly (less than 30°) during the light-adaptation period for all stimuli conditions. The L/M ratio in luminance reflecting ERGs decreased with increasing adaptation time. Our present data suggest that the light-adaptation process mainly reflects changes in the luminance pathway. The responses to 12-Hz luminance stimuli are determined by two different luminance driven pathways with different adaptation characteristics.
CRIS-Team Scopus Importer:2019-05-02

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

Pattern electroretinogram, blue-yellow visual evoked potentials and the risk of developing visual field defects in glaucoma suspects: a longitudinal “survival” analysis with a very long follow-up - Huchzermeyer, Cord; Lämmer, Robert; Mardin, Christian Y.; Kruse, Friedrich; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2024)
Purpose: Estimating glaucoma suspects’ risk for visual field defects helps to avoid under- and over-treatment. In this retrospective, longitudinal cohort study with a very long follow-up, we studied whether pattern electroretinograms (PERG) amplitudes and blue-on-yellow visual evoked potential (BY-VEP) latencies can predict visual field defects. Methods: Participants of the Erlangen Glaucoma Study were examined with PERG and BY-VEP between 9/1991 and 8/2001. Stimuli were created using an optical bench with Maxwellian view and consisted of vertical gratings (0,88 cpd) in a 32° field for both PERG and BY-VEP. Patients were treated according to clinical standards and performed standard automated perimetry (SAP) annually. Retrospectively, patients with normal SAP at baseline were selected. Primary endpoint was conversion to perimetric glaucoma. Predictive value was modeled using Kaplan–Meier analyses and a multivariate cox proportional hazards model with the continuous variables PERG amplitude, BY-VEP peak time and SAP square-root of loss variance (sLV) after stratification for Jonas classification of the optic discs. Results: Of 412 patients (288: Jonas 0, 103: I, and 21: II; baseline age: 20–60 years), 65 converted to perimetric glaucoma during follow-up (0.5–23.3 years; median 5.5 years). Optic disc classification was a strong risk factor for conversion (log rank p < 0.0001), and patients with more advanced changes progressed earlier. In the multivariate analysis (log rank p = 0.005), only PERG amplitude remained an independent risk factor after stratification for optic disc morphology (p = 0.021), with a 30% higher risk per μV amplitude decrease. Conclusions: PERG helps to estimate glaucoma suspects’ risk for visual field defects.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Electroretinogram; Glaucoma; Perimetry; Survival analysis; Visually evoked potentials

Pattern electroretinograms during the cold pressor test in normals and glaucoma patients - La Mancusa, Antonia; Horn, Folkert; Kremers, Jan; Huchzermeyer, Cord; Rudolph, Michael; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2014)
To examine the influence of the cold pressor test (CPT) on steady-state pattern electroretinograms (PERG) in healthy subjects and glaucoma patients.Steady-state PERGs to 7.8 Hz pattern reversal stimuli were recorded in 63 subjects. Fifteen healthy control subjects, 14 patients with ocular hypertension (OHT), and 34 patients with open-angle glaucoma (20 normotensive [NTG] and 14 high tension glaucoma [HTG]) were examined. Steady-state PERG amplitudes and latencies were analyzed at baseline, during cold stimulus using a modified CPT, and during the subsequent recovery phase. Blood pressure and heart rate were simultaneously recorded in 10 normals and 11 glaucoma patients.During the three test conditions (baseline, ice water, and warm water) glaucoma patients (NTG and HTG) showed significantly reduced PERG amplitudes in comparison with control subjects (P < 0.001) and with OHT patients (P < 0.004). Patients with OHT displayed lower PERG amplitudes than control subjects (nonsignificant, with consideration of Bonferroni). Only NTG patients showed a significant effect of the CPT on PERG amplitude (significant decrease during warm water P = 0.02). Latencies shortened significantly during warm-water period after cold stimulus in control subjects (P = 0.05) and in NTG patients (P = 0.02) with a nonsignificant trend of shortened latencies in the OHT (P = 0.06) and HTG groups (P = 0.3). Systolic and diastolic blood pressure increased during cold water (P < 0.001) and decreased during warming-up conditions (P < 0.001).This study shows that a CPT influences the PERG responses particularly in NTG. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21162

Patterns of photoreceptor-specific temporal contrast sensitivity losses in patients with different phenotypic variants of retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Lorenz, Birgit; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Pentacam-based big bubble deep anterior lamellar keratoplasty in patients with keratoconus - Riss, Stephan; Heindl, Ludwig M.; Bachmann, Bjoern O.; Kruse, Friedrich; Cursiefen, Claus (Cornea, 2012)
To describe the clinical results of Pentacam-based big bubble deep anterior lamellar keratoplasty (DALK) to achieve an intended 90% depth of initial lamellar trephination.Fifty consecutive eyes of 50 patients with keratoconus, keratoglobus, and anterior stromal scars were included. DALK was performed with the big bubble technique using a 90% intended depth for initial lamellar trephination based on preoperative pachymetry by Pentacam. Main outcome measures were success of surgery, best spectacle-corrected visual acuity, endothelial cell count, refractive astigmatism at 12-month follow-up, and rate of intra- and postoperative complications.In 84% of the patients (n = 42), Pentacam-based big bubble DALK could be performed successfully. Successful big bubble formation could be achieved in 80% of the patients (n = 34). In case of macroperforation (n = 8), surgery was converted to standard penetrating keratoplasty representing a conversion rate of 16%. Intraoperative microperforation (n = 5) could be handled by an intracameral air injection at the end of operation with successful completion of the lamellar procedure. No allograft rejection was observed. Best spectacle-corrected visual acuity improved from 20/125 ± 20/160 preoperatively to 20/40 ± 20/80 at 12-month follow-up. Endothelial cell count was 2102 ± 318 cells per square millimeter preoperatively and 1735 ± 420 cells per square millimeter at 12-month follow-up. Refractive astigmatism was 7.09 ± 3.13 diopters preoperatively and decreased to 4.13 ± 2.41 diopters.Pentacam-based big bubble DALK using a 90% intended depth of initial lamellar trephination seems to be a safe and effective procedure for anterior corneal stromal disorders such as keratoconus. We suggest that Pentacam-based depth assessment allows for reliably deep initial preparation and may allow more successful bubble formation in DALK surgery.
EVALuna2:21074

Perifoveal cone- And rod-mediated temporal contrast sensitivities in stargardt disease/fundus flavimaculatus - Fars, Julien; Pasutto, Francesca; Kremers, Jan; Huchzermeyer, Cord (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. The purpose of this study was to compare L-cone–driven, S-cone–driven, and rod-driven temporal contrast sensitivities (tCSs) in patients with Stargardt disease 1/fundus flavimaculatus (STGD1/FF). METHODS. Fourteen patients (eight male, six female; mean age, 43.21 ± 13.18 years) with genetically confirmed STGD1/FF participated in this study. A dedicated light-emitting diode stimulator was used to measure perifoveal tCSs in an annular test field (1°–6° of visual eccentricity) at temporal frequencies between 1 and 20 Hz. Photoreceptor classes were isolated with the triple silent substitution technique. To compare functional damage among photoreceptor classes, sensitivity deviations (decibels) were calculated based on age-related normal values and then averaged across those frequencies where perception is mediated by the same post-receptoral pathway (L-cone red–green opponent pathway: 1, 2, 4 Hz; luminance pathway: 12, 16, 20 Hz; S-cone pathway: 1, 2, 4 Hz; fast rod pathway: 8, 10, 12 Hz). Sensitivity deviations were compared with infrared scanning laser ophthalmoscopy (IR-SLO) and standard automated perimetry (SAP). RESULTS. Photoreceptor-driven tCSs were generally lower in patients with STGD1/FF than in normal subjects but were without systematic differences among photoreceptors. Although sensitivity deviations were significantly correlated between each other, only luminance-driven L-cone sensitivity deviations were significantly correlated with the IR-SLO area of hyporeflectance (AoH) and SAP central mean deviation within 6° eccentricity (MD6deg). CONCLUSIONS. No systematic differences between photoreceptor classes were detected; however, our data suggest that temporal contrasts detected by the luminance pathway were closely correlated with other clinical parameters (AoH and MD6deg) and might be most useful as functional biomarkers in clinical trials.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Fundus flavimaculatus; Perifovea; Photoreceptors; Stargardt disease; Temporal contrast sensitivity

Perifoveal L- and M-cone-driven temporal contrast sensitivities at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We established a protocol using a well-established LED stimulator to measure temporal contrast sensitivities driven by sine-wave modulation of L- and M-cones in the perifovea using triple silent substitution. The stimulus was presented in an annular field (2° inner diameter, 13° outer diameter). We validated this technique by studying the contrast sensitivity of three color normal observers at 10 different temporal frequencies (between 1 and 28 Hz) over a large range of retinal illuminances (between 0.07 and 587 phot Td), spanning the complete mesopic range. In one subject, sensitivities to counterphase modulation of L- and M-cones and in-phase modulation of L, M, and S-cones were additionally measured, which putatively reflected the parvo- and magnocellular retinogeniculate pathways, respectively. Furthermore, we performed measurements of temporal contrast sensitivities as a function of frequency at 294 phot Td in two protanopes, in two deuteranopes, and in one subject with S-cone monochromacy. Quality of isolation was satisfactory and we were able to reproduce known physiological patterns of temporal vision, such as the typical temporal contrast sensitivity functions of the L- and M-cone, the parvo- and magnocellular retinogeniculate pathways, as well as the light adaptation curves. These results will help determine optimal stimulus conditions in future studies. Results from the dichromats and the S-cone monochromat also support the quality of isolation of our protocol and underpin its potential clinical value.
EVALuna2:21317

Perifoveal S-cone and rod-driven temporal contrast sensitivities at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2017)
We evaluated a technique for measuring temporal contrast sensitivities to sine-wave modulation driven by S-cones and rods in the perifovea using triple silent substitution. Isolating stimuli for S-cones and rods were created using an eight-channel, four-primary LED stimulator that has been validated before. Sensitivities were measured at 10 different temporal frequencies between 1 and 28 Hz in three normal observers at 14 different retinal illuminances between 0.07 and 587 photopic troland (phot Td) and at three different retinal illuminances over the same range in one S-cone monochromat. The technique was further validated by measuring bleaching adaptation in two normal subjects, demonstrating sufficient isolation in rods. Good isolation was apparent from the differences in the temporal contrast sensitivity functions and the sensitivity-versus-retinal illuminance functions between S-cones and rods, and also from the results in the S-cone monochromats and the delayed recovery of rod sensitivities after bleaching. The results will help to determine optimal stimulus conditions in future studies. The results in the S-cone monochromat demonstrate the potential clinical value of our protocol.
EVALuna2:21334

Perimetric measurements with flicker-defined form stimulation in comparison with conventional perimetry and retinal nerve fiber measurements - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
We compared the results of flicker-defined form (FDF) perimetry with standard automated perimetry (SAP) and retinal nerve fiber layer (RNFL) thickness measurements using spectral domain optical coherence tomography (OCT).A total of 64 healthy subjects, 45 ocular hypertensive patients, and 97 "early" open-angle glaucoma (OAG) patients participated in this study. Definition of glaucoma was based exclusively on glaucomatous optic disc appearance. All subjects underwent FDF perimetry, SAP, and peripapillary measurements of the RNFL thickness. The FDF perimetry and SAP were performed at identical test locations (G1 protocol). Exclusion criteria were subjects younger than 34 years, SAP mean defect (SAP MD) > 5 dB, eye diseases other than glaucoma, or nonreliable FDF measurements. The correlations between the perimetric data on one hand and RNFL thicknesses on the other hand were analyzed statistically.The age-corrected sensitivity values and the local results from the controls were used to determine FDF mean defect (FDF MD). The FDF perimetry and SAP showed high concordance in this cohort of experienced patients (MD values, R = -0.69, P < 0.001). Of a total of 42 OAG patients with abnormal SAP MD, 38 also displayed abnormal FDF MD. However, FDF MD was abnormal in 28 of 55 OAG patients with normal SAP MD. The FDF MD was significantly (R = -0.61, P < 0.001) correlated with RNFL thickness with a (nonsignificantly) larger correlation coefficient than conventional SAP MD (R = -0.48, P < 0.001).The FDF perimetry is able to uncover functional changes concurrent with the changes in RNFL thickness. The FDF perimetry may be an efficient functional test to detect early glaucomatous nerve atrophy. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21150

Perimetrie in der Glaukomdiagnostik - Lämmer, Robert; Huchzermeyer, Cord (Klinische Monatsblätter für Augenheilkunde, 2021)
CRIS-Team Scopus Importer:2021-03-05
Keywords: early detection; frequency doubling perimetry; glaucoma; visual field

Perimetry in the Diagnosis of Glaucoma - Lämmer, Robert; Huchzermeyer, Cord (Augenheilkunde up2date, 2021)
CRIS-Team WoS Importer:2021-03-12

Peripapillary arterial circle of zinn-haller: location and spatial relationships with myopia - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (PLoS ONE, 2013)
To measure histomorphometrically the location of the peripapillary arterial circle of Zinn-Haller (ZHAC) and assess its associations with axial length.Using a light microscope, we measured the distance from the ZHAC to the peripapillary ring (optic disc border), the merging point of the dura mater with the posterior sclera ("dura-sclera point"), and the inner scleral surface. In the parapapillary region, we differentiated between beta zone (presence of Bruch's membrane, absence of retinal pigment epithelium) and gamma zone (absence of Bruch's membrane). The peripapillary scleral flange as roof of the orbital cerebrospinal fluid space was the connection between the end of the lamina cribrosa and the posterior full-thickness sclera starting at the dura-sclera point.The study included 101 human globes (101 patients) with a mean axial length of 26.7±3.7 mm (range: 20.0-39.0 mm). The distance between the ZHAC and the peripapillary ring increased significantly with longer axial length (P<0.001; correlation coefficient r = 0.49), longer parapapillary gamma zone (P<0.001;r = 0.85), longer (P<0.001;r = 0.73) and thinner (P<0.001;r = -0.45) peripapillary scleral flange, and thinner sclera posterior to the equator (P<0.001). ZHAC distance to the peripapillary ring was not significantly associated with length of parapapillary beta zone (P = 0.33). Including only non-highly myopic eyes (axial length <26.5 mm), the ZHAC distance to the disc border was not related with axial length (P = 0.84). In non-highly myopic eyes, the ZHAC was located close to the dura-sclera point. With increasing axial length and decreasing thickness of the peripapillary scleral flange, the ZHAC was located closer to the inner scleral surface.The distance between the ZHAC and the optic disc border is markedly enlarged in highly myopic eyes. Since the ZHAC is the main arterial source for the lamina cribrosa blood supply, the finding may be of interest for the pathogenesis of the increased glaucoma susceptibility in highly myopic eyes.
EVALuna2:21141

Peripapillary border tissue of the choroid and peripapillary ccleral flange in human eyes - Jonas, Rahul Arvo; Holbach, Leonard (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Peripapillary border tissue of the choroid and peripapillary scleral flange in human eyes - Jonas, Rahul A.; Holbach, Leonard (Acta Ophthalmologica, 2019)
Purpose: To assess dimensions and associations of the peripapillary border tissue of the choroid (PBT-C) and peripapillary scleral flange (PBT-S). Methods: The histomorphometric investigation included histological sections of enucleated eyes of Caucasian patients. Using light microscopy, the PBT dimensions were measured. Results: The study included 85 eyes (85 patients) with an age of 62.0 years (14.1 years) (mean (SD)) (range:37–87 years) and mean axial length of 26.7 mm (3.5 mm) (range:21.0–37.0 mm). Thicker PBT-C thickness (mean: 68.8 μm (35.7 μm)) was associated with shorter axial length (p < 0.001; standardized regression coefficient beta: −0.50), and longer PBT-C length (mean: 531 μm (802 μm)) was correlated with longer axial length (p < 0.001;beta:0.66). PBT-C cross-sectional area (mean 17 050 μm2 (10 420 μm2)) was not significantly associated with axial length (p = 0.37). Decreasing with longer axial length (p < 0.001;beta:0.64), the angle between PBT-C and Bruch's membrane was approximately 90° in non-highly myopic eyes without overhanging Bruch's membrane (BM), it ranged between 100° and 180° in eyes with BM overhanging into the intrapapillary region, and it was close to 0° in eyes with parapapillary gamma zone. Thicker thickness of PBT-S (mean:83 μm (21 μm)) was correlated with presence of glaucoma (p = 0.02). Optic nerve pia mater thickness (mean:109 μm (44 μm)) increased with glaucoma presence (p = 0.046;beta:0.31) but not with axial length (p = 0.34). Conclusions: Peripapillary border tissue of the choroid (PBT-C) and PBT-S as continuation of the optic nerve pia mater are distinct structures, with PBT-C remodelling during myopic axial elongation and PBT-S being mostly independent of axial elongation. PBT-C and PBT-S may be of importance for the optic nerve head biomechanics and PBT-C for separation of the choroidal space from the intrapapillary compartment.
CRIS-Team Scopus Importer:2019-08-27
Keywords: axial length; Bruch's membrane; choroid; histomorphometry; lamina cribrosa; myopia; parapapillary beta zone; parapapillary gamma zone; peripapillary border tissue; peripapillary scleral flange

Peripapillary ring: histology and correlations - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2014)
To assess the histologic correlate of the peripapillary ring (PPR) as the optic disc boundary, to measure it histomorphometrically and to assess its associations with glaucoma and axial length.Using a light microscope, we measured the width of the PPR and optic nerve pia mater. We additionally had measured the axial length, length of parapapillary beta and gamma zones, and thickness of the sclera and choroid.The study included 83 human globes with a mean axial length of 26.1 ± 3.3 mm (range: 20.0-35.0 mm). In the non-highly myopic (axial length <26.5 mm) non-glaucomatous eyes, mean PPR width was 55 ± 14 ?m (range: 26-88 ?m) and mean thickness of the optic nerve pia mater was 52 ± 22 ?m (range: 20-84 ?m). PPR width and pia mater thickness were significantly associated with each other (p = 0.001; correlation coefficient r = 0.37). PPR width increased significantly with longer axial length (p = 0.001; r = 0.35) and with the length of the peripapillary scleral flange (p = 0.02; r = 0.34). Pia mater thickness increased significantly with longer axial length (p = 0.03; r = 0.24) and with presence of glaucoma (p = 0.03). In eyes without parapapillary gamma zone, PPR was covered or was at least touched by the end of Bruch's membrane and separated the peripapillary choroid from the prelaminar optic nerve head tissue. In eyes with parapapillary gamma zone, PPR was the continuation of the optic nerve pia mater and reached the undersurface of the peripapillary retinal nerve fibre layer. In these eyes, Bruch's membrane started in a distance of up to 5 mm from PPR, and the thin space of peripapillary choroid ended by an attachment of Bruch's membrane to the thinned sclera.Peripapillary ring width (mean: 55 ± 14 ?m) increases slightly with longer axial length and is independent of glaucoma. It is strongly correlated with the pia mater thickness and is the continuation of the pia mater to the ocular surface.
EVALuna2:21189

Peripheral hypertrophic subepithelial corneal degeneration presenting with bilateral nasal and temporal corneal changes - Schargus, M.; Kusserow, C.; Schlötzer-Schrehardt, Ursula; Hofmann-Rummelt, C.; Schlunck, G.; Geerling, G. (Eye, 2015)
PurposeTo characterise the history, clinical and histopathological features of patients with bilateral nasal and temporal peripheral hypertrophic subepithelial corneal degeneration in a German population.MethodsA detailed ophthalmological and dermatological history and clinical findings were recorded of nine patients with bilateral simultaneous nasal and temporal peripheral corneal degeneration from two centers in Germany. Excised tissues were studied by histopathology, immunohistochemistry, and transmission electron microscopy.ResultsForeign body sensation and need of artificial tear substitutes were the only symptoms reported regularly. Schirmer's and Jones-test were normal in all, but fluorescein break-up time of >10 s was found in five eyes of four patients. Best corrected visual acuity was reduced only under glare conditions. Corneal topography revealed irregular astigmatism in 13 of 14 eyes. Follow-up median time was 35 months. Most cases were stable within the follow-up period. Light and electron microscopy revealed the findings of superficial vascularised corneal hypertrophic scars, oxytatlan fibers, and discontinued Bowmans layer.ConclusionIn this series of German patients with peripheral hypertrophic subepithelial corneal degeneration, the changes were predominantly located in the palpebral aperture and often present in both eyes. No associated surface disease could be established in this study. Light and transmission electron microscopy showed histological features that are similar to Salzmann's corneal changes without any inflammation. We hypothesise that light exposure and a localised limbal insufficiency could be involved in the pathogenesis.
EVALuna2:21217

Perspectives of deep anterior lamellar keratoplasty - Cursiefen, Claus; Heindl, L. M. (Ophthalmologe, 2011)
The current indications, techniques, results and complications of deep anterior lamellar keratoplasty are described.The study comprised a literature review and own clinical and experimental results.The main advantage of DALK in patients with keratoconus and other anterior stromal diseases is the avoidance of endothelial immune reactions and the main drawback is the conversion rate to penetrating keratoplasty of around 15%.Using the big bubble approach DALK is a safe and reliable technique for treating keratoconus and anterior stromal dystrophy.
EVALuna2:21056

Phase Changes in the Chromaticity and Luminance Driven Flicker Electroretinograms (ERGs) of Glaucoma Patients - Barboni, M. T.; Pangeni, G.; Ventura, D. F.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: clinical; retina; color vision

Photoplethysmographic analysis of retinal videodata based on the Fourier domain approach - Kolar, Radim; Ilik, Jan Odstrc; Tornow, Ralf-Peter (Biomedical Optics Express, 2021)
Assessment of retinal blood flow inside the optic nerve head (ONH) and the peripapillary area is an important task in retinal imaging. For this purpose, an experimental binocular video ophthalmoscope that acquires precisely synchronized video sequences of the optic nerve head and peripapillary area from both eyes has been previously developed. It enables to compare specific characteristics of both eyes and efficiently detect the eye asymmetry. In this paper, we describe a novel methodology for the analysis of acquired video data using a photoplethysmographic approach. We describe and calculate the pulsatile attenuation amplitude (PAA) spatial map, which quantifies the maximum relative change of blood volume during a cardiac cycle using a frequency domain approach. We also describe in detail the origin of PAA maps from the fundamental (the first) and the second harmonic component of the pulsatile signal, and we compare the results obtained by time-based and frequency-based approaches. In several cases, we show the advantages and possibilities of this device and the appropriate image analysis approach-fast measurement and comparison of blood flow characteristics of both eyes at a glance, the robustness of this approach, and the possibility of easy detection of asymmetry.
CRIS-Team Scopus Importer:2021-12-10

Photoreceptor degeneration in two mouse models for congenital stationary night blindness type 2 - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Kremers, Jan; Maw, Marion A.; Brandstätter, Johann Helmut (PLoS ONE, 2014)
Light-dependent conductance changes of voltage-gated Cav1.4 channels regulate neurotransmitter release at photoreceptor ribbon synapses. Mutations in the human CACNA1F gene encoding the ?1F subunit of Cav1.4 channels cause an incomplete form of X-linked congenital stationary night blindness (CSNB2). Many CACNA1F mutations are loss-of-function mutations resulting in non-functional Cav1.4 channels, but some mutations alter the channels' gating properties and, presumably, disturb Ca(2+) influx at photoreceptor ribbon synapses. Notably, a CACNA1F mutation (I745T) was identified in a family with an uncommonly severe CSNB2-like phenotype, and, when expressed in a heterologous system, the mutation was shown to shift the voltage-dependence of channel activation, representing a gain-of-function. To gain insight into the pathomechanism that could explain the severity of this disorder, we generated a mouse model with the corresponding mutation in the murine Cacna1f gene (I756T) and compared it with a mouse model carrying a loss-of-function mutation (?Ex14-17) in a longitudinal study up to eight months of age. In ?Ex14-17 mutants, the b-wave in the electroretinogram was absent, photoreceptor ribbon synapses were abnormal, and Ca(2+) responses to depolarization of photoreceptor terminals were undetectable. In contrast, I756T mutants had a reduced scotopic b-wave, some intact rod ribbon synapses, and a strong, though abnormal, Ca(2+) response to depolarization. Both mutants showed a progressive photoreceptor loss, but degeneration was more severe and significantly enhanced in the I756T mutants compared to the ?Ex14-17 mutants.
EVALuna2:21185

Photoreceptor driven non-invasive electrophysiology in humans and mice - Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Photoreceptor-specific light adaptation of critical flicker frequency in trichromat and dichromat observers - Huchzermeyer, Cord; Martins, Cristiane M. G.; Nagy, Balazs; Barboni, Mirella T. S.; Ventura, Dora F.; Costa, Marcelo F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
The silent substitution paradigm offers possibilities to investigate and compare the temporal properties of mechanisms driven by single photoreceptor types, including the critical flicker frequency (CFF), in which the state of adaptation can be kept as invariant. We have (1) measured CFFs using triple silent substitutions to isolate L-, M-, and S-cone as well as rod-driven pathways under identical mean luminances and chromaticities; (2) repeated the CFF measurements at different mean luminances in order to validate the Ferry-Porter law (stating that the relationship between CFF and the log retinal illuminance-log I-is linear); and (3) compared these CFF versus log I functions for L-, M-, S-cone-, and rod-isolating stimuli for five trichromats and four X-linked dichromats (two protanopes, two deuteranopes). We show that the effects of luminance on the CFFs with silent substitution are comparable to those measured previously with chromatic stimuli. We found that M-cone-driven CFFs are smaller in trichromats than in protanopes. Furthermore, the slopes of the M-cone-driven CFF versus log I functions are smaller in trichromats. Possibly, the lacking L-cones are replaced by M-cones in these two protanopes and the CFF depends on cone density. Furthermore, we found that in trichromats, the slopes of the CFF-log I functions are smaller for M-cone-than for L-cone-isolating stimuli. This contradicts the current interpretation of the CFF-log I functions for chromatic stimuli, which states that CFF is mediated by the most strongly modulated photoreceptor type. Thus, the larger slopes that were previously found with medium-wavelength chromatic stimuli compared with long-wavelength chromatic stimuli seem to be the result of an addition of signals from different photoreceptors and do not necessarily result from M-cones being inherently faster. (C) 2018 Optical Society of America

Photoreceptor-specific loss of perifoveal temporal contrassensitivity in retinitis pigmentosa - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (Translational Vision Science & Technology, 2020)
Purpose: Inherited retinal diseases affect the L-, M-, S-cones and rods in distinct ways, which calls for new methods that enable quantification of photoreceptor-specific functions. We tested the feasibility of using the silent substitution paradigm to estimate photoreceptor-driven temporal contrast sensitivity (tCS) functions in patients with retinitis pigmentosa. Methods: The silent substitution paradigm is based on substitution of lights of different spectral composition; this offers considerable advantage over other stimulation techniques. We used a four-primary LED stimulator to create perifoveal annular stimuli (2° inner, 12° outer diameters) and used a triple silent substitution to probe photoreceptor-selective tCS. Measurements were performed in a heterogeneous cohort of 15 patients with retinitis pigmentosa and related to those in a control group of nine color-normal healthy observers. Age differences between groups were addressed with a model of age-related normal contrast sensitivity derived from measurements in 20 healthy observers aged between 23 and 83 years. Results: The age-related loss of tCS amounted to 0.1 dB/year in healthy subjects across all photoreceptor subtypes. In patients, tCS was decreased for every photoreceptor subtype; however, S-cone-and rod-driven sensitivities were most strongly affected. Postreceptoral mechanisms were not affected. Conclusions: This feasibility study provides evidence that the silent substitution technique enables the estimation of photoreceptor-selective tCS functions and can serve as an accurate biomarker of photoreceptor-specific contrast sensitivity loss in patients with retinitis pigmentosa. Translational Relevance: We aim to develop tests of visual function for clinical trials of novel therapies for inherited retinal diseases from methods that can currently be used only in vision research labs.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Contrast sensitivity; Photoreceptors; Retinal dystrophy; Retinitis pigmentosa; Temporal vision

Photoreceptor-Specific Temporal Contrast Sensitivities in RP1L1-Associated Occult Macular Dystrophy - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan; Kühlewein, Laura; Kempf, Melanie; Ott, Saskia; Stingl, Krunoslav; Stingl, Katarina (Investigative Ophthalmology & Visual Science, 2023)
Purpose: The purpose of this study was to compare L-, M-, S-cone-, and rod-driven temporal contrast sensitivities (tCS) in patients with RP1L1-associated autosomal-dominant occult macular dystrophy (OMD), and to investigate how photoreceptor degeneration determines which post-receptoral channels dominate perception. Methods: Photoreceptor isolating stimuli were created with the silent substitution technique. Photoreceptor-selective tCS deviations (D L-cone/M-cone/S-cone/Rod) were obtained as a function of temporal frequency with identical retinal adaptation, by subtracting tCS from age-corrected normal values. A linear-mixed effects model was used for analysis. Results: Eleven genetically confirmed patients were included (7 women, 5 men; age = 52.27 ± 14.44 years). Overall, L- and M-cone-driven sensitivity deviations (DL-cone and DM-cone) were more negative than DS-cone; DRod was normal at frequencies between 8 and 12 Hz in all subjects. Rod-driven tCS functions allowed identification of two subgroups of patients: one with band-pass properties and one with low-pass properties, suggesting dominance of different post-receptoral filters. The same filtering properties were observed in L-cone-driven tCS functions. Furthermore, the two subgroups also differed in clinical parameters (spherical equivalent, BCVA, perimetry, and ocular coherence tomography (OCT) reflectivity of the ellipsoid zone relative to the RPE). Conclusions: OMD was characterized predominantly by deterioration of L- and M-cone-cone driven function in the perifovea. Rod-driven functions were normal. Differences in the photoreceptor signals were further modified by postreceptoral filters.
CRIS-Team Scopus Importer:2023-07-07

Physical phenotype of blood cells is altered in COVID-19 - Kubankova, Marketa; Hohberger, Bettina; Hoffmanns, Jakob; Fürst, Julia; Herrmann, Martin; Guck, Jochen; Kraeter, Martin (Biophysical Journal, 2021)
Clinical syndrome coronavirus disease 2019 (COVID-19) induced by severe acute respiratory syndrome coronavirus 2 is characterized by rapid spreading and high mortality worldwide. Although the pathology is not yet fully understood, hyperinflammatory response and coagulation disorders leading to congestions of microvessels are considered to be key drivers of the still-increasing death toll. Until now, physical changes of blood cells have not been considered to play a role in COVID-19 related vascular occlusion and organ damage. Here, we report an evaluation of multiple physical parameters including the mechanical features of five frequent blood cell types, namely erythrocytes, lymphocytes, monocytes, neutrophils, and eosinophils. More than four million blood cells of 17 COVID-19 patients at different levels of severity, 24 volunteers free from infectious or inflammatory diseases, and 14 recovered COVID-19 patients were analyzed. We found significant changes in lymphocyte stiffness, monocyte size, neutrophil size and deformability, and heterogeneity of erythrocyte deformation and size. Although some of these changes recovered to normal values after hospitalization, others persisted for months after hospital discharge, evidencing the long-term imprint of COVID-19 on the body.
CRIS-Team Scopus Importer:2021-07-30

Pigment dispersion syndrome and pigmentary glaucoma. Morphometric analysis of the anterior chamber segment with SL-OCT - Birner, Barbara; Tourtas, T.; Wessel, J. M.; Jünemann, Anselm; Mardin, Christian Y.; Kruse, Friedrich; Lämmer, Robert (Ophthalmologe, 2014)
The purpose of this study was to analyze if anterior chamber parameters are risk factors for the development of pigment dispersion syndrome (PDS) and/or for the conversion to pigmentary glaucoma (PG).This study included a total of 63 eyes from 35 patients with PDS and PG and 65 eyes from 49 unaffected volunteers as the control group. The following parameters were measured by slit lamp optical coherence tomography (SL-OCT): anterior chamber volume (ACV) and depth (ACD), angle opening distance (AOD) and the trabecular iris space area (TISA) at 500 µm and 750 ?m from the scleral spur. Comparisons between the following groups were performed: between the PDS/PG and the control group, between PDS and PG and between male and female patients.The results of ACV, ACD, AOD and TISA were significantly higher in PDS/PG patients when compared to the control group. There were no significant differences between PDS and PG. The gender-specific comparison also showed no significant differences.Significantly higher anterior chamber parameters are a possible risk factor for development of PDS; however, a higher risk of conversion to PG does not seem to correlate with increased anterior chamber parameters. The parameters of the anterior chamber are apparently not associated with the male predominance of PDS and PG.
EVALuna2:21131

Pilot study for the evaluation of morphological and functional changes in retinal blood flow in patients with insulin resistance and/or type 2 diabetes mellitus - Forst, Thomas; Weber, Matthias M.; Mitry, Michael; Schon̈dorf, Thomas; Forst, Senait; Tanis, Mukadar; Pfuẗzner, Andreas; Michelson, Georg (Journal of diabetes science and technology, 2012)
The aim of this study was to investigate early morphological and functional pathology in the retinal micro-circulation in patients with insulin resistance and/or type 2 diabetes mellitus (T2DM).Fifty-four subjects, without features of retinopathy under ophthalmological investigation, were recruited for study participation and were classified into three study groups according to their metabolic staging: (1) Group C comprised nondiabetic, insulin-sensitive subjects with a BMI <28 kg/m(2); (2) Group IR comprised nondiabetic, insulin-resistant, obese subjects with a BMI >=28 kg/m(2); and (3) Group DM comprised patients with manifested T2DM. Retinal microvascular blood flow was assessed using scanning laser doppler flowmetry (Heidelberg Retina Flowmeter) before and after flicker light stimulation (10 Hz; Photo Stimulater 750).No significant difference was observed in retinal blood flow (RBF) among the three groups, neither at baseline nor after stimulating the retina with flicker light. The arterial wall-to-lumen ratio (WLR) tended to be smaller in Group DM compared with Group C, and was significantly lower when comparing Group IR with Group C. When the subjects were grouped according to their insulin resistance, a steady decline in RBF and WLR could be observed with increasing insulin resistance.In conclusion, laser scanner flowmetry of the retina was found to detect very early changes in microvascular blood flow. Development of insulin resistance seems to be an important component in the deterioration of RBF.
EVALuna2:21085

"PISK-itis" or "PISK-opathy"? - Tourtas, Theofilos; Cursiefen, Claus (Cornea, 2012)
EVALuna2:21113

Poly (glycerol sebacate)-poly (?-caprolactone) blend nanofibrous scaffold as intrinsic bio- and immunocompatible system for corneal repair - Salehi, Sahar; Czugala, Marta; Stafiej, Piotr; Fathi, Mohammadhossein; Bahners, Thomas; Gutmann, Jochen S.; Singer, Bernhard B.; Fuchsluger, Thomas (Acta Biomaterialia, 2017)
A major challenge in corneal tissue engineering and lamellar corneal transplantation is to develop synthetic scaffolds able to simulate the optical and mechanical properties of the native cornea. As a carrier, the graft scaffolds should provide the basis for anchorage, repair and regeneration. Although quite a number of scaffolds have been engineered to date, they have not been able to simultaneously recapitulate chemical, mechanical, and structural properties of the corneal extracellular matrix (ECM). Here, we examined different compositions of elastomeric biodegradable poly (glycerol sebacate) (PGS)-poly (?-caprolactone) (PCL) nanofibrous scaffolds with respect to their cyto- and immunocompatibility. These scaffolds were semi-transparent with well-defined mechanical properties and direct positive effects on viability of human corneal endothelial cells (HCEC) and human conjunctival epithelial cells (HCjEC). Moreover, within 3days HCEC established monolayers with the hexagonal morphology typical for this cell type. All PGS-PCL mixtures analyzed did not trigger effects in granulocytes, naïve and activated peripheral blood mononuclear cells (PBMCs). However, scaffolds with a higher content of PGS-PCL ratio showed the best cell organization, cyto- and immunocompatibility. Subsequently, this PGS-PCL composition could be used for further development of clinical constructs to support corneal tissue repair.In corneal tissue engineering a major challenge is the development of synthetic scaffolds with similar properties to native cornea. In our recent works, we introduced the biodegradable, polymeric nanofibrous scaffolds with similar optical and mechanical properties for corneal regeneration and here we examined the cyto- and immunocompatibility of biodegradable nanofibrous scaffolds in contact to white blood cells. Directing the alignment of human corneal cells by nanofibrous scaffolds and high viability of cells was detected by forming of endothelium monolayer with hexagonal morphology on the nanofibrous scaffold. In addition, our results for the first time show that these nanofibrous scaffolds did not trigger effects in white blood cells. These results highlight the considerable translational potential of the nanofibrous scaffolds to clinical applications.
EVALuna2:21330

Possible Impact of functional active GPCR-autoantibodies on retinal microcirculation in Long-COVID - Mardin, Christian Y.; Lucio, Marianna; Wallukat, Gerd; Szewczykowski, Charlotte; Hoffmanns, Jacob; Raith, Franziska; Schröder, Tim; Schottenhamml, Julia; Lämmer, Robert; Hohberger, Bettina (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Post-COVID-19 Syndrome: Retinal Microcirculation as a Potential Marker for Chronic Fatigue - Schlick, Sarah; Lucio, Marianna; Wallukat, Gerd; Bartsch, Alexander; Skornia, Adam; Hoffmanns, Jakob; Szewczykowski, Charlotte; Schröder, Thora; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; et al. (International Journal of Molecular Sciences, 2022)
Post-COVID-19 syndrome (PCS) is characterized by persisting sequelae after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). PCS can affect patients with all COVID-19 disease severities. As previous studies have revealed impaired blood flow as a provoking factor triggering PCS, it was the aim of the present study to investigate the potential association between self-reported chronic fatigue and retinal microcirculation in patients with PCS, potentially indicating an objective biomarker. A prospective study was performed, including 201 subjects: 173 patients with PCS and 28 controls. Retinal microcirculation was visualized by OCT angiography (OCT-A) and quantified using the Erlangen-Angio-Tool as macula and peripapillary vessel density (VD). Chronic fatigue (CF) was assessed according to the variables of Bell’s score, age and gender. VDs in the superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP) were analyzed, considering the repetitions (12 times). Seropositivity for autoantibodies targeting G protein-coupled receptors (GPCR-AAbs) was determined by an established cardiomyocyte bioassay. Taking account of the repetitions, a mixed model was performed to detect possible differences in the least square means between the different groups included in the analysis. An age effect in relation to VD was observed between patients and controls (p < 0.0001). Gender analysis showed that women with PCS showed lower VD levels in the SVP compared to male patients (p = 0.0015). The PCS patients showed significantly lower VDs in the ICP as compared to the controls (p = 0.0001 (CI: 0.32; 1)). Moreover, considering PCS patients, the mixed model revealed a significant difference between those with chronic fatigue (CF) and those without CF with respect to VDs in the SVP (p = 0.0033 (CI: −4.5; −0.92)). The model included variables of age, gender and Bell’s score, representing a subjective marker for CF. Consequently, retinal microcirculation might serve as an objective biomarker in subjectively reported chronic fatigue in patients with PCS.
CRIS-Team Scopus Importer:2022-12-09
Keywords: chronic fatigue; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; long COVID syndrome; OCT angiography; post-COVID-19 syndrome; retinal microcirculation

Posttranscriptional Regulation of LOXL1 Expression Via Alternative Splicing and Nonsense-Mediated mRNA Decay as an Adaptive Stress Response - Berner, Daniel; Zenkel, Matthias; Pasutto, Francesca; Hoja, Ursula; Liravi, Panah; Gusek-Schneider, Gabriele C.; Kruse, Friedrich; Schödel, Johannes; Reis, André; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2017)
Alternative mRNA splicing coupled to nonsense-mediated decay (NMD) is a common mRNA surveillance pathway also known to dynamically modulate gene expression in response to cellular stress. Here, we investigated the involvement of this pathway in the regulation of lysyl oxidase-like 1 (LOXL1) expression in response to pseudoexfoliation (PEX)-associated pathophysiologic factors.Transcript levels of LOXL1 isoforms were determined in ocular tissues obtained from donor eyes without and with PEX syndrome. Pseudoexfoliation-relevant cell types, including human Tenon's capsule fibroblasts (hTCF) and trabecular meshwork cells (hTMC), were exposed to puromycin, caffeine, TGF-?1, homocysteine, IL-6, retinoic acid, UV-B radiation, oxidative stress, and mechanical stress for up to 48 hours. Western blot analysis was carried out using antibodies against LOXL1, (phosphorylated-) eukaryotic initiation factor 2-? (eIF2-?), and regulator of nonsense transcripts 2 (UPF2). RNA interference was used to knockdown UPF1-3 and Serine/threonine-protein kinase (SMG1).Constitutive expression of wild-type LOXL1 and alternatively spliced LOXL1-a transcripts was detected in all ocular tissues showing highest levels in trabecular meshwork and differential expression between PEX and control specimens. LOXL1-a transcripts were upregulated in hTCF and hTMC by NMD inhibitors puromycin and caffeine (>=6-fold; P < 0.01) or after knockdown of NMD core factors (>=2-fold; P < 0.05), whereas mRNA and protein levels of LOXL1 were reduced (<=0.8 fold; P < 0.05). Exposure of cells to various PEX-associated (stress) factors, including TGF-?1, UV-B light, oxidative stress, mechanical stress, and retinoic acid enhanced LOXL1-a transcript levels (>=1.5-fold; P < 0.05), while partially downregulating LOXL1 levels (<=0.7-fold; P < 0.05). Stress-induced inhibition of NMD was dependent on phosphorylation of eIF2?.These findings provide evidence for a functional role of alternative splicing coupled to NMD in the posttranscriptional regulation of LOXL1 gene expression and suggest this mechanism to represent a dynamic mode of adapting LOXL1 expression to PEX-associated environmental and nutritional cues.
EVALuna2:9393

Potential functional restoration of corneal endothelial cells in Fuchs corneal dystrophy by ROCK inhibitor (Ripasudil) - Kruse, Friedrich; Tourtas, Theofilos; Zenkel, Matthias; Kinoshita, Shigeru; Schlötzer-Schrehardt, Ursula (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Potential Functional Restoration of Corneal Endothelial Cells in Fuchs Endothelial Corneal Dystrophy by ROCK Inhibitor (Ripasudil) - Schlötzer-Schrehardt, Ursula; Zenkel, Matthias; Strunz, Maria; Gießl, Andreas; Schondorf, Hannah; da Silva, Heather; Schmidt, Gregory A.; Greiner, Mark A.; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; et al. (American Journal of Ophthalmology, 2021)
Purpose: Rho-associated kinase (ROCK) inhibitors have been successfully used as a rescue strategy in eyes that failed to clear after descemetorhexis without endothelial graft for treatment of Fuchs endothelial corneal dystrophy (FECD). The functional mechanisms by which ROCK inhibitors modulate corneal endothelial cell regeneration in FECD patients have, however, not been clarified. Here, we analyzed the effect of the ROCK inhibitor ripasudil on corneal endothelial cells of FECD patients and normal donors using ex vivo tissue and in vitro cellular models. Design: Experimental study: laboratory investigation. Methods: This institutional study used endothelial cell–Descemet membrane lamellae from FECD patients (n = 450) undergoing Descemet membrane endothelial keratoplasty (FECD ex vivo model), normal research-grade donor corneas (n = 30) after scraping off central endothelial cells (ex vivo wound healing model), normal donor corneas (n = 20) without endothelial injury, and immortalized cell lines (n = 3) generated from FECD patients (FECD in vitro model). Descemet membrane lamellae were dissected into halves and incubated for 24-72 hours in storage medium with or without a single dose of 30 μM ripasudil. The effects of ripasudil on expression of genes and proteins related to endothelial cell proliferation, migration, functionality, and endothelial-to-mesenchymal transition were analyzed and complemented by functional assays on FECD cell lines. Results: A single dose of ripasudil induced significant upregulation of genes and proteins related to cell cycle progression, cell-matrix adhesion and migration, as well as endothelial barrier and pump function up to 72 hours, whereas classical markers of endothelial-to-mesenchymal transition were downregulated in both FECD and normal specimens compared to unstimulated controls ex vivo. In addition to stimulation of proliferation and migration, ripasudil-induced changes in expression of functional signature genes could be also verified in FECD cell lines in vitro. Conclusions: These data support the concept that inhibition of ROCK signaling represents a potent tool in regenerative therapies in FECD patients through reactivation of cell proliferation and migration as well as restoration of endothelial pump and barrier function without inducing adverse phenotypic changes.
CRIS-Team Scopus Importer:2021-02-12

Precision of Optic Nerve Head and Retinal Nerve Fiber Layer Parameter Measurements by Spectral-domain Optical Coherence Tomography - Schrems-Hösl, Laura-Maria; Schrems, Wolfgang; Lämmer, Robert; Kruse, Friedrich; Mardin, Christian Y. (Journal of Glaucoma, 2018)
PURPOSE: The aim of this study was to assess the repeatability and reproducibility (R&R) of Bruch membrane opening based on minimum rim width (BMO-MRW), minimum rim area (BMO-MRA) and peripapillary retinal nerve fiber layer thickness (RNFLT) with the Spectralis optical coherence tomography (Heidelberg Engineering) for normal and glaucoma subjects. Precise measurement of these parameters can support detection of structural glaucomatous damage and progression. METHODS: This cross-sectional study included 16 healthy controls and 16 patients with glaucoma. One eye was randomly selected and included in this study. Subjects underwent 1 baseline and 3 follow-up measurements, using 3 different Spectralis optical coherence tomography devices in randomized order, each operated by a single operator. Outcome measures were global and sectorial averages of BMO-MRW and BMO-MRA, and of peripapillary RNFLT obtained from 12/14/16-degree circle scans. Coefficients of variation (COV) were calculated and a mixed-effects analysis of variance was performed to compare R&R between devices. RESULTS: COVs of global and sectorial BMO-MRW measurement under repeatability conditions ranged from 0.51% to 1.7% (normal, 0.62% to 1.3%; glaucoma, 0.64% to 2.3%). Respective COVs under reproducibility conditions ranged from 0.89% to 1.9% (normal, 0.77% to 2.8%; glaucoma, 1.1% to 2.6%). COVs of global and sectorial RNFLT measurements under repeatability conditions ranged from 0.5% to 2.8%. Respective COVs under reproducibility conditions ranged from 1.6% to 3.5%. CONCLUSIONS: For R&R, the COVs of measured parameters were by trend higher for glaucoma eyes compared with normal controls. The BMO-MRW measurement system has an excellent precision taking into account that major and minor corrections of segmentation have to be done by the examiner before evaluation.
EVALuna2:34751

Predicted and Measured Retinal Nerve Fiber Layer Thickness From Time-Domain Optical Coherence Tomography Compared With Spectral-Domain Optical Coherence Tomography - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Bendschneider, Delia; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Horn, Folkert (JAMA Ophthalmology, 2015)
New methods are needed to compare peripapillary retinal nerve fiber layer thickness (pRNFLT) measurements taken from time-domain optical coherence tomography (TD-OCT) and spectral-domain OCT (SD-OCT).To compare the agreement of measured and predicted pRNFLT using different equations based on pRNFLT measurements obtained by TD-OCT and SD-OCT.Cross-sectional single-center study that took place at the Department of Ophthalmology, University of Erlangen-Nuremberg from November 16, 2005, to June 3, 2015, and included 138 eyes of control participants, 126 eyes of patients with ocular hypertension, 128 eyes of patients with preperimetric glaucoma, and 160 eyes of patients with perimetric glaucoma. All participants had standard clinical examinations to obtain TD-OCT (via Stratus OCT) and SD-OCT (via Spectralis OCT) measurements of pRNFLT. Two groups were matched for diagnostic subgroup, eye side, sex, and age. The TD-OCT measurements of the first group were used to predict the mean SD-OCT and 6-sector vertical-split pRNFLT measurements of the second group and vice versa. The agreement between the predicted pRNFLT calculations of conversion equations and measured pRNFLT of the second group was evaluated by intraclass correlation coefficients and Bland-Altman plots.Mean and sectoral pRNFLT measurements obtained by TD-OCT and SD-OCT as well as the agreement between measured and predicted pRNFLT.The agreement for all investigated equations to predict mean pRNFLT measurements with intraclass correlation coeffecients ranged from 0.937 to 0.939. Bland-Altman plots demonstrated systemic biases between -0.7 ?m and +1.1 ?m for measured and predicted mean pRNFLT measurements. The ratio method demonstrated an intraclass correlation coefficient of 0.969 for the temporal-inferior sector. The best color-code agreement between both OCT devices was achieved by the no conversion method, with ? = 0.731 (95% CI, 0.656-0.806) for the mean pRNFLT.These data suggest that the prediction of mean pRNFLT values by equations derived from TD-OCT and SD-OCT can be conducted with high levels of agreement. In individual cases and singular sectors, high prediction errors may occur. When longitudinal imaging data from both TD-OCT and SD-OCT are available, conversion equations may provide longitudinal comparability.
EVALuna2:21226

Predictive Factors for Visual Field Conversion: Comparison of Scanning Laser Polarimetry and Optical Coherence Tomography - Diekmann, Theresa; Schrems-Hösl, Laura-Maria; Mardin, Christian Y.; Lämmer, Robert; Horn, Folkert; Kruse, Friedrich; Schrems, Wolfgang (Journal of Glaucoma, 2018)
PURPOSE: The purpose of this study was to compare the ability of scanning laser polarimetry (SLP) and spectral-domain optical coherence tomography (SD-OCT) to predict future visual field conversion of subjects with ocular hypertension and early glaucoma. METHODS: All patients were recruited from the Erlangen glaucoma registry and examined using standard automated perimetry, 24-hour intraocular pressure profile, and optic disc photography. Peripapillary retinal nerve fiber layer thickness (RNFL) measurements were obtained by SLP (GDx-VCC) and SD-OCT (Spectralis OCT). Positive and negative predictive values (PPV, NPV) were calculated for morphologic parameters of SLP and SD-OCT. Kaplan-Meier survival curves were plotted and log-rank tests were performed to compare the survival distributions. Contingency tables and Venn-diagrams were calculated to compare the predictive ability. RESULTS: The study included 207 patients-75 with ocular hypertension, 85 with early glaucoma, and 47 controls. Median follow-up was 4.5 years. A total of 29 patients (14.0%) developed visual field conversion during follow-up. SLP temporal-inferior RNFL [0.667; 95% confidence interval (CI), 0.281-0.935] and SD-OCT temporal-inferior RNFL (0.571; 95% CI, 0.317-0.802) achieved the highest PPV; nerve fiber indicator (0.923; 95% CI, 0.876-0.957) and SD-OCT mean (0.898; 95% CI, 0.847-0.937) achieved the highest NPV of all investigated parameters. The Kaplan-Meier curves confirmed significantly higher survival for subjects within normal limits of measurements of both devices (P<0.001). Venn diagrams tested with McNemar test statistics showed no significant difference for PPV (P=0.219) or NPV (P=0.678). CONCLUSIONS: Both GDx-VCC and SD-OCT demonstrate comparable results in predicting future visual field conversion if taking typical scans for GDx-VCC. In addition, the likelihood ratios suggest that GDx-VCC's nerve fiber indicator<30 may be the most useful parameter to confirm future nonconversion. (http://www.ClinicalTrials.gov number, NTC00494923; Erlangen Glaucoma Registry).
EVALuna2:34215

Presence and distribution of L-kynurenine aminotransferases immunoreactivity in human cataractous lenses - Rejdak, Robert; Oleszczuk, Agnieszka; Rummelt, Carmen; Turski, Waldemar A.; Choragiewicz, Tomasz; Nowomiejska, Katarzyna; Ksiazek, Katarzyna; Thaler, Sebastian; Zarnowski, Tomasz; Okuno, Etsuo; Grieb, Pawel; Zrenner, Eberhart; et al. (Acta Ophthalmologica, 2013)
To investigate the presence and distribution of l-kynurenine aminotransferases immunoreactivity in human and animal lenses during cataract formation.Immunohistochemistry was conducted using polyclonal antibodies against KAT I, KAT II and KAT III on sections of 26 anterior capsules from patients undergoing surgical treatment of anterior subcapsular cataract (ASC) and 22 cataractous lenses from human eyes enucleated because of choroidal malignant melanoma. Additionally, the eyes of 11-month-old DBA/2J mice (6 eyes) were investigated (with KAT I and II). Ten clear human lenses and four BL6 mice lenses were used as controls. Spatial immunoreactivity patterns of enzymes were compared with Periodic Acid - Schiff (PAS)-stained sections.Immunohistochemical analysis revealed presence of KAT I, KAT II and KAT III in extracellular structures of all studied types of cataract in human eyes showing specific pattern of the stain. In cortical cataract, immunoreactivity was observed on cortical lens fibres. In nuclear cataract, KAT II revealed stronger and diffused staining than KAT I. Additionally, both KAT showed more pronounced staining at the edge of small clefts. In normal human lenses, KAT I, II and III, immunoreactivity was not observed. Presence of KAT I and KAT II in the intercellular substance of DBA/2J mice cataract was observed. In BL6 mice lenses without cataract, only weak KAT I and KAT II staining was observed.Presence of l-kynurenine aminotransferases in extracellular matrix (ECM) during human cataract formation suggests that products of l-kynurenine pathway might be involved in mechanisms of cataractogenesis.
EVALuna2:21117

Presence of HLA-B27 is associated with changes of serum levels of mediators of the Wnt and hedgehog pathway - Aschermann, Sarah; Englbrecht, Matthias; Bergua, Antonio; Spriewald, Bernd M.; Said-Nahal, Rhula; Breban, Maxime; Schett, Georg; Rech, Juergen (Joint Bone Spine, 2016)
HLA-B27 is present in 5% of the Caucasian population and is strongly associated with the development of spondyloarthritis (SpA), a disease characterized by inflammation and substantial bone changes. We hypothesized that the presence of HLA-B27 in itself is associated with alterations of key regulatory of bone homeostasis.Sera of 241 individuals were assessed for the serum levels of Wnt pathway regulators, sclerostin and dickkopf (Dkk)-1 as well as Indian hedgehog (IHH) and collagen type I cleavage products (CTX1). Of the 151 HLA-B27+ subjects, 31 had SpA, 30 had anterior uveitis, 30 were healthy individuals and 60 healthy siblings of patients with SpA.Sclerostin levels were significantly (P<0.001) lower in HLA-B27+ subjects (314±21pg/mL) compared to HLA-B27 negative controls (mean±SEM: 492±30pg/mL), no matter if subjects were either healthy, or affected by SpA or uveitis. Similar results were found for Dkk-1. No differences between the groups with respect to the bone resorption marker CTX1 were found. In contrast, IHH levels were significantly (P<0.001) higher in the carriers of HLA-B27 than in the negative controls.Changes in key regulators of the Wnt pathway as well as IHH, a molecule regulating endochondral ossification, are found in HLA-B27 carriers, independent if they were healthy or affected by uveitis or SpA.
EVALuna2:13168

Presence of L-kynurenine aminotransferase III in retinal ganglion cells and corpora amylacea in the human retina and optic nerve - Rejdak, Robert; Rummelt, Carmen; Zrenner, Eberhart; Grieb, Pawel; Rejdak, Konrad; Okuno, Etsuo; Thaler, Sebastian; Nowomiejska, Katarzyna; Kruse, Friedrich; Turski, Waldemar; Jünemann, Anselm (Folia Neuropathologica, 2011)
Corpora amylacea (CAm) are a hallmark of aging and neurodegeneration. The presence of kynurenine aminotransferases I and II (KAT I and II) in CAm in the human retina and optic nerve has been already shown. The present study aimed to examine kynurenine aminotransferase III (KAT III) immunoreactivity in CAm in the human retina and optic nerve.Polyclonal antibody against KAT III was used on sections of human eyes enucleated due to malignant uveal melanoma. PAS-stained sections of CAm were compared with KAT III stained ones.KAT III immunoreactivity was observed in CAm in the retina, prelaminar, laminar and retrolaminar region of the optic nerve with similar location to PAS-stained sections. The most intense staining was observed in the retrolaminar part of the optic nerve. KAT III immunoreactivity was also present in the cytoplasm of retinal ganglion cells.Expression of KAT III in CAm in the human retina and optic nerve indicates that this enzyme may be relevant in mechanisms of neurodegeneration leading to CAm formatio
EVALuna2:21028

Pressure-Dependent Elevation of Vasoactive Intestinal Peptide Level in Chicken Choroid - Privalov, Evgeny; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Kuerten, Stefanie; Bergua, Antonio; Hohberger, Bettina (Biology, 2023)
Simple Summary Autonomic ocular control is mediated by sympathetic, parasympathetic, and primary trigeminal afferent nerve fibers. Intrinsic choroidal neurons (ICN) contribute to this complex neuronal network. Vasoactive intestinal peptide (VIP), a major transmitter of ICN, mediates choroidal vasodilation and, thus, potentially choroidal thickness and intraocular pressure (IOP). Therefore, it was the aim of the present study to investigate the choroidal VIP level (VIPchor) in the presence of an increased atmospheric pressure in a chicken model. Chicken choroidal whole mounts were exposed to ambient pressure (n = 20) and 40 mmHg (n = 20) in a PC-controlled, open chamber system for 24 and 72 h, respectively. VIPchor was significantly increased after exposure to 40 mmHg compared to exposure to ambient pressure. This increase of the VIPchor level, representing the intracellular choroidal VIP level, might argue for a retention of VIP within the neurons, consequently decreasing vasodilatation and choroid thickness. Purpose: Autonomic control is important in maintaining ocular integrity. As recent data suggested that intrinsic choroidal neurons (ICN), an intrinsic choroidal autonomic control, may regulate choroidal thickening via release of the vasodilative vasoactive intestinal peptide (VIP), it was the aim of the study to investigate the level of choroidal VIP (VIPchor) in the presence of an increased atmospheric pressure in a chicken model. Methods: Chicken choroidal whole mounts were exposed to ambient pressure (n = 20) and 40 mm Hg (n = 20) in a PC-controlled, open chamber system for 24 and 72 h, respectively. The VIP concentration was analyzed by ELISA, and the total protein concentration was measured by the BCA assay. Statistical analysis was done using an unpaired two-tailed t-test. Results: The pressurization systems enabled choroidal whole mount pressurization (40 mm Hg) with humidifying, pressure, temperature, and gas exchange. Overall, the VIPchor level concentration was significantly increased at 40 mmHg compared to the ambient pressure (30.09 +/- 7.18 pg vs. 20.69 +/- 3.24 pg; p < 0.0001). Subgroup analysis yielded a significantly increased VIPchor level at 40 mmHg compared to the ambient pressure after 24 h (28.42 +/- 6.03 pg vs. 20.76 +/- 4.06 pg; p = 0.005) and 72 h (31.77 +/- 7.82 pg vs. 20.61 +/- 2.12 pg; p = 0.002), respectively. The VIPchor elevation at 40 mm Hg ranged between 1.37- (24 h) and 1.54-fold (72 h) compared to the ambient pressure. No difference was observed between the VIPchor level at 24 h and 72 h (p > 0.05). Conclusions: The increase of the total choroidal VIP level, representing the intracellular VIP content, in the presence of an increased ambient pressure argues for a retention of VIP within the neurons, decreasing both vasodilatation and, consequently, choroid thickness. This finding might be a passive or even active function of ICN in the regulation of choroidal thickness, ocular integrity and IOP.
CRIS-Team WoS Importer:2023-05-12

Pressure-induced interlamellar stromal keratitis after laser in situ keratomileusis - Kruse, Friedrich; et al. (Cornea, 2011)
To describe a patient with interlamellar stromal keratitis induced by increased intraocular pressure (IOP) [Pressure-induced interlamellar stromal keratitis (PISK)] after laser in situ keratomileusis (LASIK) surgery.Case report and review of the literature.We report a case of interlamellar stromal keratitis induced by increased IOP after LASIK surgery. A 42-year-old man presented with persistent interface haze after uneventful LASIK. The patient described onset of decreased visual acuity after the first 2 postoperative weeks, failed to improve with high-dose topical steroid drops, and had significantly elevated IOP values up to 48 mm Hg. IOP was resistant to maximal topical antiglaucomatous therapy. The patient showed both improvement in visual acuity and decrease in interface haze after discontinuation of topical steroids and lowering of IOP by both topical and systemic treatment. Slit-lamp optical coherence tomography ruled out a fluid accumulation in the interface.PISK appears clinically almost identical to diffuse lamellar keratitis after LASIK. It is important to measure the IOP and be suspicious when a diffuse interface haze occurs after the first postoperative week, is resistant to or even exacerbates in response to an increase in topical steroid treatment, and is not associated with other causative events. Slit-lamp optical coherence tomography is a valuable tool that allows differentiation between space-occupying interface fluid collection and non-space-occupying interface fluid collection to avoid falsely low or normal IOP measurements in PISK.
EVALuna2:21052

Pre-stimulus bioelectrical activity in light-adapted ERG under blue versus white background - Tsay, Katherine; Safari, Sara; Abu-Samra, Abdullah; Kremers, Jan; Tzekov, Radouil (Visual Neuroscience, 2023)
To compare the baseline signal between two conditions used to generate the photopic negative response (PhNR) of the full-field electroretinogram (ERG): red flash on a blue background (RoB) and white flash on a white background (LA3). The secondary purpose is to identify how the level of pre-stimulus signal affects obtaining an unambiguous PhNR component. A retrospective chart review was conducted on four cohorts of patients undergoing routine ERG testing. In each group, LA3 was recorded the same way while RoB was generated differently using various luminances of red and blue light. The background bioelectrical activity 30 ms before the flash was extracted, and the root mean square (RMS) of the signal was calculated and compared between RoB and LA3 using Wilcoxon test. Pre-stimulus noise was significantly higher under RoB stimulation versus LA3 in all four conditions for both right and left eyes (ratio RoB/LA3 RMS 1.70 and 1.57 respectively, p < 0.033). There was also no significant difference between the RMS of either LA3 or RoB across protocols, indicating that the baseline noise across cohorts were comparable. Additionally, pre-stimulus noise was higher in signals where PhNR was not clearly identifiable as an ERG component versus signals with the presence of unambiguous PhNR component under RoB in all four groups for both eyes (p < 0.05), whereas the difference under LA3 was less pronounced. Our study suggests that LA3 produces less background bioelectrical activity, likely due to decreased facial muscle activity. As it seems that the pre-stimulus signal level affects PhNR recordability, LA3 may also produce a better-quality signal compared to RoB. Therefore, until conditions for a comparable bioelectrical activity under RoB are established, we believe that LA3 should be considered at least as a supplementary method to evaluate retinal ganglion cell function by ERG.
CRIS-Team Scopus Importer:2023-12-22
Keywords: electroretinography; ERG; eye; PhNR; photopic negative response; retina

Preventive effects of omega-3 and omega-6 Fatty acids on peroxide mediated oxidative stress responses in primary human trabecular meshwork cells - Tourtas, Theofilos; Birke, Marco; Kruse, Friedrich; Welge-Lüssen, Ulrich-Christoph; Birke, Kerstin (PLoS ONE, 2012)
Pathologic processes in glaucoma include increased apoptosis, accumulation of extracellular material in the trabecular meshwork and optic nerve, condensations of the cytoskeleton and precocious cellular senescence. Oxidative stress was shown to generate these alterations in primary ocular cells. Fatty acids omega-3 and -6 are alleged to constitute a prophylaxis against these deleterious effects. Here, we tested actual preventive effects omega-3 and -6 against peroxide induced stress responses in primary human trabecular meshwork cells. Changes of mitochondrial activity, proliferation, heat shock proteins, extracellular matrix components, and inflammatory markers were evaluated. Alterations of the cytoskeleton were evaluated by phalloidin labeling. Here we report a repressive effect of omega-6 on metabolic activity and proliferation, which was not detected for omega-3. Both agents were able to prevent the anti-proliferative effect of H?O?, but only omega-3 prevented metabolic repression. Expression of heat shock protein 27 was unaltered by both fatty acids, whereas heat shock protein 90 was significantly induced by both. Omega-6 increased fibronectin and connective tissue growth factor synthesis, as well as the amount of secreted fibronectin. Omega-3, instead, induced plasminogen activator inhibitor 1 synthesis. H?O? further increased fibronectin production in omega-6 supplemented cells, which was not the case in omega-3 treated cells. H?O? stimulation of plasminogen activator inhibitor 1 and connective tissue growth factor was repressed by both fatty acids. Both fatty acids appeared to abolish H?O? mediated stimulation of nuclear factor ?B and IL-6, but not IL-1? and IL-8. H?O? induced formation of cross-linked actin networks and stress fibers, which was reduced by preemptive application of omega-3. Omega-6, in contrast, had no protective effect on that, and even seemed to promote condensation. Based on the observed side effects of omega-6, omega-3 appears to be the more beneficial fatty acid in respect of prophylactic intake for prevention of a glaucomatous disease.
EVALuna2:21079

Principles of glaucoma diagnostics with optical coherence tomography - Mardin, Christian Y. (Ophthalmologe, 2015)
In recent years many applications of optical coherence tomography (OCT) have led to a better understanding of glaucoma morphology. The clinical routine in the treatment of glaucoma is strongly influenced by the modern diagnostic aspects.A selective search of the literature was carried out and the important aspects are presented taking own experiences into account. The measurement principles, diagnostic ability and pitfalls of the three OCT measurement procedures are highlighted.Retinal nerve fiber layer, macula and ganglion cell layer thickness as well as the minimum neuroretinal rim width have facilitated in particular the objective early diagnosis and follow-up measurements.For glaucoma, OCT measurements cannot replace the medical expert diagnosis but they represent a valuable decision-making aid for diagnostics and follow-up examinations.
EVALuna2:21225

Probability map based localization of optic disk - Budai, Attila; Laurik, Lenke; Hornegger, Joachim; Somfai, Gábor M.; Michelson, Georg (2012 19th International Conference on Systems, Signals and Image Processing, IWSSIP 2012, 2012)
Fundus imaging is one of themost commonly used modalities for examining retinal structures. The images are mostly analyzed by physicians. These diagnoses are subjective with a high rate of inter-observer variability, therefore an automated or a computer aided diagnosis is needed to speed up the monotonous screening process and to provide objective measurements. In this article we present an automatic algorithm for localization of the optic disk center in fundus images. The application field of the algorithm is preprocessing for further algorithms such as segmentation of the optic disk boundary, vessel tracking etc. The algorithm is evaluated using the DRIVE database and our own public high resolution image database. The tests show a localization error less than 0.2 optic disk diameter (ODD) in case of the high resolution database, and less than 0.35 ODD in case of the lower resolution DRIVE database. © 2012 Institute of Telecommunica.

Prognostic significance of tumor-associated lymphangiogenesis in malignant melanomas of the conjunctiva - Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Adler, Werner; Bosch, Jacobus J.; Holbach, Leonard M.; Naumann, Gottfried; Kruse, Friedrich; Cursiefen, Claus (Ophthalmology, 2011)
To evaluate whether tumor-associated lymphangiogenesis contributes to prognosis of conjunctival malignant melanomas and to study its association with other tumor characteristics.Nonrandomized, retrospective case series.A total of 109 consecutive patients with primary conjunctival malignant melanoma.Proliferating lymphatic vessels were identified immunohistochemically using lymphatic vascular endothelial hyaluronan receptor-1 and podoplanin as specific lymphatic endothelial markers and Ki-67 as proliferation marker. Baseline tumor characteristics included tumor location, tumor thickness, tumor diameter, tumor origin, and tumor growth pattern. Kaplan-Meier and Cox regression analyses of the risk of local recurrence, lymphatic spread, distant metastasis, and melanoma-related death were performed.Intratumoral lymphatic vascular density and its association with tumor characteristics and recurrence-free, lymphatic spread-free, distant metastasis-free, and melanoma-specific survival.Intratumoral and peritumoral proliferating lymphatic vessels could be detected in all of the 109 conjunctival melanoma samples. High intratumoral lymphatic density was significantly associated with palpebral tumor location (P<0.001), greater tumor thickness (P<0.001), larger tumor diameter (P = 0.001), tumor origin de novo (P= 0.002), and nodular tumor growth pattern (P = 0.037). Patients with high intratumoral lymphatic density revealed significantly lower recurrence-free, lymphatic spread-free, distant metastasis-free, and melanoma-specific survival rates (P<0.001 for all). By multivariate Cox regression, factors predictive of local recurrence included palpebral tumor location (hazard ratio [HR] 2.66, P = 0.014), large tumor diameter (HR 5.48, P<0.001), and high intratumoral lymphatic density (HR 2.48, P = 0.043); factors predictive of lymphatic spread included palpebral tumor location (HR 4.13, P = 0.009), high tumor thickness (HR 12.17, P<0.001), and high intratumoral lymphatic density (HR 6.79, P = 0.019); factors predictive of distant metastasis included palpebral tumor location (HR 7.63, P<0.001), high tumor thickness (HR 8.60, P<0.001), large tumor diameter (HR 0.30, P = 0.029), and high intratumoral lymphatic density (HR 8.90, P = 0.047); and factors predictive of melanoma-related death included palpebral tumor location (HR 7.74, P<0.001), high tumor thickness (HR 10.88, P<0.001), large tumor diameter (HR 0.28, P = 0.018), and, with borderline significance, high intratumoral lymphatic density (HR 8.46, P = 0.052).Tumor-associated lymphangiogenesis seems to be associated with an increased risk of local recurrence, lymphatic spread, distant metastasis, and melanoma-related death in patients with conjunctival malignant melanomas.The author(s) have no proprietary or commercial interest in any materials discussed in this article.
EVALuna2:5322

Proof of concept data logger for non-active power measurement - Martindale, Christine; Gaunt, Charles Trevor; Verrinder, Robyn (49th International Universities Power Engineering Conference (UPEC), 2014)
This paper discusses a metering concept design based on equipment cheaper and smaller than a laptop and able to meet the requirements of power measurements that need relatively high frequency, simultaneous sampling. Its size and cost make it useful when developing hardware for smart grid systems. Non-active power is a term used to describe both distortion and reactive power. In conventional power theory, the apparent power, S, and non-active power, Q, are based on RMS measurements of voltages and line currents. A novel general power theory was proposed recently to give a measure of the true efficiency of power delivery under conditions of distortion, unbalance and direct current components, and the approach requires the simultaneous sampling of all voltages and currents at relatively high frequency. A metering device was designed for the measurement of instantaneous, simultaneously sampled voltages and currents in a three-phase system. The system has an upper sampling frequency limit of 2 000 Hz. The prototype design was fast enough to perform the general power theory calculations and log the data accurately. The project provides direction for the further development of this type of device for measuring non-active power, power quality and power electronic control.

Prospective, randomized, controlled comparison of SYSTANE UD eye drops versus VISINE INTENSIV 1% EDO eye drops for the treatment of moderate dry eye - Jacobi, Christina; Kruse, Friedrich; Cursiefen, Claus (Journal of Ocular Pharmacology and Therapeutics, 2012)
The aim of this prospective, randomized, clinical, single-center study was to compare the safety and efficacy of 2 ocular surface lubricant eye drops: preservative-free hydroxypropyl (HP)-Guar (SYSTANE UD(®)) eye drops versus preservative-free Tamarindus indica seed polysaccharide (TSP) 1% (VISINE INTENSIV 1% EDO(®)) eye drops.Fifty-six eyes of 28 patients with moderate keratoconjunctivitis sicca (DEWS severity level 2) were enrolled in the trial. Patients were randomized for 2 treatment groups (SYSTANE UD eye drops vs. VISINE INTENSIV 1% EDO eye drops). The eye drops in both groups were applied 5 times per day for 3 months. Statistical analyses were performed using Statistica(TM) software (Mann-Whitney U-test and Wilcoxon test). P-Values<0.05 were considered significant.After 3 months of treatment the patients of both groups had subjective benefit in the relief of symptoms of dry eye disease evaluated by the Ocular Surface Disease Index (OSDI) questionnaire score. Patients treated with HP-Guar and TSP showed improvements in tear film stability measured by tear break-up time (TBUT), which are statistically significant in the HP-Guar group (P=0.02).The results of this clinical trial show improvements of symptoms and signs in patients with moderate dry eye after the consistent use of preservative-free HP-Guar and TSP lubricant eye drops. Both artificial tear formulations produce amelioration in tear film stability improving eye conditions and patient quality of life. HP-Guar seems to be slightly more effective in improving ocular surface protection by decreasing tear film evaporation.
EVALuna2:21112

Protection of corneal endothelium from apoptosis by gene and cell therapy - Fuchsluger, Thomas (Ophthalmologe, 2016)
Protection of corneal endothelium from apoptosis using gene and cell therapy is in a translational phase. This approach offers advantages for eye banking and after transplantation. Safe vehicles for gene or cell therapeutic transduction of corneal endothelium with nucleic acids are available. This strategy will be further developed in consultation with the Paul Ehrlich Institute and European regulatory authorities.
EVALuna2:21284

Proteomic analysis of TCF4 knock-out corneal endothelial cells derived from thepatients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Okumura, Naoki; Hanada, Naoya; Padmanabhan, Prema; Elchuri, Sailaja; Chatterjee, Amit; Janakiraman, Narayanan; Sathe, Gajanan; Ghose, Vivek; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Pseudoexfoliation associated protective variant, rs7173049, reveals a novel regulatory region downstream of LOXL1 - Berner, Daniel; Pasutto, Francesca; Hoja, Ursula; Zenkel, Matthias; Ozaki, Mineo; Williams, Susan; Ramsay, Michele; Carmichael, Trevor R.; Kruse, Friedrich; Aung, Tin; Khor, Chiea Chuen; Reis, André; et al. (2018)
EVALuna2:34734

Pseudoexfoliation syndrome-associated genetic variants affect transcription factor binding and alternative splicing of LOXL1 - Pasutto, Francesca; Zenkel, Matthias; Hoja, Ursula; Berner, Daniel; Uebe, Steffen; Ferrazzi, Fulvia; Schoedel, Johannes; Liravi, Panah; Ozaki, Mineo; Paoli, Daniela; Frezzotti, Paolo; Mizoguchi, Takanori; et al. (Nature Communications, 2017)
Although lysyl oxidase-like 1 (LOXL1) is known as the principal genetic risk factor for pseudoexfoliation (PEX) syndrome, a major cause of glaucoma and cardiovascular complications, no functional variants have been identified to date. Here, we conduct a genome-wide association scan on 771 German PEX patients and 1,350 controls, followed by independent testing of associated variants in Italian and Japanese data sets. We focus on a 3.5-kb four-component polymorphic locus positioned spanning introns 1 and 2 of LOXL1 with enhancer-like chromatin features. We find that the rs11638944:C>G transversion exerts a cis-acting effect on the expression levels of LOXL1, mediated by differential binding of the transcription factor RXR? (retinoid X receptor alpha) and by modulating alternative splicing of LOXL1, eventually leading to reduced levels of LOXL1 mRNA in cells and tissues of risk allele carriers. These findings uncover a functional mechanism by which common noncoding variants influence LOXL1 expression.
EVALuna2:9367

Pseudorandom full-field electroretinograms reflect different light adaptation mechanisms - Assis, Juliana Bizerra; Brasil, Alódia; Loureiro, Terezinha Medeiros Gonçalves; da Silva, Veronica Gabriela Ribeiro; Herculano, Anderson Manoel; Ventura, Dora Fix; Silveira, Luiz Carlos Lima; Kremers, Jan; Souza, Givago Silva (Documenta Ophthalmologica, 2021)
Purpose: To investigate the magnitude and time course of pseudorandom ffERG during light adaptation. Methods: Ten healthy subjects (26 ± 10.1 years) underwent 20 min of dark adaptation, and then the ffERG was evoked by pseudorandom flash sequences (4 ms per flash, 3 cd.s/m2) driven by m-sequences (210–1 stimulus steps) using Veris Science software and a Ganzfeld dome over a constant field of light adaptation (30 cd/m2). The base period of the m-sequence was 50 ms. Each stimulation sequence lasting 40 s was repeated at 0, 5, 10, 15 and 20 min of light adaptation. Relative amplitude and latency (corrected by values found at 0 min) of the three components (N1, P1, and N2) of first-order (K1) and first slice of the second-order (K2.1) kernel at 5 time points were evaluated. An exponential model was fitted to the mean amplitude and latency data as a function of the light adaptation duration to estimate the time course (τ) of the light adaptation for each component. Repeated one-way ANOVA followed by Tukey post-test was applied to the amplitude and latency data, considering significant values of p < 0.05. Results: Regarding the K1 ffERG, N1 K1, P1 K1, and N2 K1 presented an amplitude increase as a function of the light adaptation (N1 K1τ value = 2.66 min ± 4.2; P1 K1τ value = 2.69 min ± 2.10; and N2 K1 τ value = 3.49 min ± 2.96). P1 K1 and N2 K1 implicit time changed as a function of the light adaptation duration (P1 K1τ value = 3.61 min ± 5.2; N2 K1τ value = 3.25 min ± 4.8). N1 K1 had small implicit time changes during the light adaptation. All the K2,1 components also had nonsignificant changes in amplitude and implicit time during the light adaptation. Conclusions: Pseudorandom ffERGs showed different mechanisms of adaptation to retinal light. Our results suggest that K1 ffERG is generated by retinal mechanisms with intermediate- to long-term light adaptation, while K2.1 ffERG is generated by retinal mechanism with fast light adaptation course.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Full-field ERG; Light adaptation; Pseudorandom stimulation; Retina; Visual electrophysiology

Psychometric curves in retinitis pigmentosa patients - Fars, Julien; Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-01

Psychophysical temporal contrast sensitivities for modulation of the four photoreceptor types using the silent substitution paradigm at different retinal illuminances - Huchzermeyer, Cord; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 730 temporal vision; 471 color vision; 693 retinal connections; networks; circuitry

Quality-Guided Denoising for Low-Cost Fundus Imaging - Köhler, Thomas; Hornegger, Joachim; Mayer, Markus Anton; Michelson, Georg (Bildverarbeitung für die Medizin 2012, 2012)
The restoration of noisy images is an essential pre-processing step in many medical applications to ensure sufficient quality for diagnoses. In this paper we present a new quality-guided approach for denoising of eye fundus images that suffer from high noise levels. The denoising is based on image sequences and an adaptive frame averaging approach. The novelty of the method is that it takes an objective image quality criteria to assess the different frames and tries to maximize the quality of the resulting image. It can be implemented in an incremental manner which allows real-time denoising. We evaluated our approach on real image sequences captured by a low-cost fundus camera and obtained competitive results to a state-of-the-art method in terms of signal-to-noise ratio whereas our method performs denoising about four times faster.

Randomized comparison of topical prednisolone acetate 1% versus fluorometholone 0.1% in the first year after descemet membrane endothelial keratoplasty - Price, Marianne O.; Price, Francis W.; Kruse, Friedrich; Bachmann, Björn; Tourtas, Theofilos (Cornea, 2014)
The aim of this study was to compare the efficacy and side effects of prednisolone acetate 1% versus fluorometholone 0.1% after Descemet membrane endothelial keratoplasty (DMEK).DMEK recipients used prednisolone acetate 1% for 1 month, and they were randomized to either prednisolone or fluorometholone for months 2 through 12. Dosing was 4 times daily in months 1 to 3, thrice daily in month 4, twice daily in month 5, and once daily in months 6 to 12. The main outcomes were immunologic rejection episodes and intraocular pressure (IOP) elevation (defined as >=24 mm Hg or >=10 mm Hg increase over the preoperative baseline level), assessed by the Kaplan-Meier survival analysis.The study included 325 eyes (99% were white, 96% had Fuchs dystrophy, and 9% had a previous glaucoma diagnosis). No eyes (0%) assigned to prednisolone versus 2 eyes (1.4%) assigned to fluorometholone experienced a possible (n = 1) or probable (n = 1) rejection episode (P = 0.17). Both rejection episodes resolved successfully with increased topical steroids. In the prednisolone arm, a significantly higher proportion exceeded the defined IOP elevation threshold (22% vs. 6%, P = 0.0005), and glaucoma medications were initiated or increased more often (17% vs. 5%, P = 0.0003). The most frequent reasons for discontinuing the assigned intervention were IOP management (n = 13 eyes assigned to prednisolone) or inflammation management (n = 3 eyes assigned to fluorometholone). One-year endothelial cell loss was comparable in both arms (30% vs. 31%, P = 0.50).DMEK has a remarkably low rejection episode rate (<1% through 1 year), as confirmed in this prospective randomized study. This provides a unique opportunity to reduce postoperative topical corticosteroid strength and thereby reduce the risk of steroid-associated complications.
EVALuna2:21205

Reactive uveitis, retinal vasculitis and scleritis as ocular end-stage of Acanthamoeba keratitis: a histological study - Shi, Lei; Hager, Tobias; Fries, Fabian Norbert; Daas, Loay; Holbach, Leonard; Hofmann-Rummelt, Carmen; Zemova, Elena; Seitz, Berthold; Szentmary, Nora (International Journal of Ophthalmology, 2019)
We analysed histologically two Acanthamoeba keratitis (AK) eyes with anterior and posterior segment inflammation and blindness. Two enucleated eyes of 2 patients (age 45 and 51y) with AK (PCR of epithelial abrasion positive) were analysed. Histological analysis was performed using hematoxylin-eosin, periodic acid-Schiff and Gomori-methenamine silver staining. We could not observe Acanthamoeba trophozoites or cysts neither in the cornea nor in other ocular tissues. Meanwhile, we found uveitis, retinal vasculitis and scleritis in these eyes, due to the long-standing, recalcitrant AK. So in this stage of AK, systemic immune suppression may be necessary for a longer time period.
CRIS-Team WoS Importer:2019-12-27

Real-time Simulation of Human Vision using Temporal Compositing with CUDA on the GPU - Nießner, Matthias; Kuhnert, Nadine; Selgrad, Kai; Stamminger, Marc; Michelson, Georg (Proceedings 25th Workshop on Parallel Systems and Algorithms (PARS 2013), 2013)
We present a novel approach that simulates human vision including visual defects such as glaucoma by temporal composition of human vision in real-time on the GPU. Therefore, we determine eye focus points every time step and adapt the lens accommodation of our virtual eye model accordingly. The focal distance is then used to determine bluriness of observed scene regions; i.e., we compute defocus for all visible pixels. In order to simulate the visual memory we introduce a sharpness field where we integrate defocus values temporally. That allows for memorizing sharply perceived scene points. For visualization, we ray trace the virtual scene environment while incorporating depth of field based on the sharpness field data. Thus, our algorithm facilitates the simulation of human vision mimicing the visual memory. We consider this to be particularly useful for illustration purposes for patients with visual defects such as glaucoma. In order to run our algorithm in real-time we employ massively parallel graphics hardware.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD9.realti_9
Keywords: GRK-1773

Recovery time as a potential new progression parameter for patients with advanced glaucomatous optic atrophy - Hohberger, B.; Misslinger, S.; Horn, Folkert; Kremers, J. (Ophthalmologe, 2016)
Functional tests in glaucoma diagnosis can monitor a potential perimetric progression. However white-on-white perimetry is limited in advanced glaucoma, whereas contrasts were detected reproducibly. Especially when stressing (i. e. adapting) the visual system, subsequent measurements yielded different results-the visual system needs a "recovery time". In the present study the recovery time was investigated in patients with advanced glaucoma. Additionally correlation analysis was done with standard perimetric parameters.Temporal contrast sensitivity (TCS) and recovery time (RT) were measured using the Erlanger Flicker Test in 61 probands (15 normals, 25 primary open-angle glaucomas, 17 secondary open-angle glaucomas, 4 narrow-angle glaucoma). Additionally, ophthalmological examinations and perimetry (Octopus G1) was done.(1) TCS was significantly reduced in patients with advanced glaucoma (p < 0.001). (2) Test stimuli with 3 and 5 % contrast showed a large variability in contrast to higher contrasts (12 %, 25 %, 35 %). (3) RT12%, RT25% and RT35% were significantly prolonged in advanced glaucoma (p < 0.001). (4) RT25% correlated significantly with mean defect (p = 0.015).Recovery time seems to be a potential parameter in advanced glaucoma follow-up, as it is reproducible, independently of cataract and fixation.
EVALuna2:21310

Refractive Outcomes After Descemet Membrane Endothelial Keratoplasty plus Cataract/Intraocular Lens Triple Procedure: A Fellow Eye Comparison - Augustin, Victor A.; Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2021)
Purpose: Descemet membrane endothelial keratoplasty is often combined with phacoemulsification and intraocular lens implantation (DMEK + cataract/IOL triple procedure) in phakic patients. This procedure results in a refractive shift that is difficult to predict. The aim of this study was to evaluate the hypothesis that the refractive shift in the second eye follows the shift in the first eye. Methods: In this retrospective, single-center, consecutive case series, the refractive outcomes of 254 eyes of 127 patients who underwent DMEK + cataract/IOL triple procedure in both eyes for Fuchs endothelial corneal dystrophy have been analyzed. Main outcome measures were spherical equivalent outcome (shift calculations), best spectacle-corrected visual acuity, central corneal thickness, and posterior simulated keratometry. Results: The mean best spectacle-corrected visual acuity before surgery was 0.51 +/- 0.24 and increased to 0.19 +/- 0.15 (logMAR) after surgery (P < 0.001). After surgery, a mean hyperopic shift of 0.98 +/- 0.89 D was observed. The refractive shift was 1.03 +/- 0.93 D and 0.92 +/- 1.02 D, in the first and second eyes, respectively (P = 0.435). In a paired analysis, the mean difference of the refractive shift between the first and second eyes was 0.49 +/- 0.43 D. Conclusions: In our fellow eye comparison, the refractive shift after DMEK + cataract/IOL triple procedure in the second eye was comparable with the shift in the first eye. As a consequence, the refractive outcome of the first eye might serve as a reference for optimizing the refractive target in the second eye. Further studies investigating the influence of corneal parameters on refractive shift are needed for a more predictable lens power selection.
CRIS-Team WoS Importer:2021-11-26

Regulation of Lysyl Oxidase-like 1 (LOXL1) and Elastin-Related Genes by Pathogenic Factors Associated with Pseudoexfoliation Syndrome - Zenkel, Matthias; Krysta, Anita; Pasutto, Francesca; Jünemann, Anselm; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Investigative Ophthalmology & Visual Science, 2011)
Purpose. Pseudoexfoliation (PEX) syndrome/glaucoma is a complex, late-onset disorder of the elastic fiber system. Strong genetic risk is conferred by the lysyl oxidase-like 1 (LOXL1) gene, but additional comodulating factors are necessary for the manifestation of the disease. The aim of this study was to analyze the effect of various PEX-associated pathogenic factors on the genotype-correlated expression of LOXL1 and elastin-related genes. Methods. Cultured human Tenon's capsule fibroblasts with high- and low-risk LOXL1 haplotypes were exposed to transforming growth factor (TGF)-?1, interleukin (IL)-6, homocysteine, oxidative stress, hypoxia, or ultraviolet (UV) radiation. Changes in the expression of LOXL1 and elastic constituents of PEX material and TGF-?1 were assessed by quantitative real-time PCR, Western blotting, immunohistochemistry, and electron microscopy. Results. Treatment of fibroblasts with TGF-?1, oxidative stress, UV light, and hypoxia induced a significant increase in expression levels of LOXL1 and elastic proteins, whereas the effect of IL-6 was limited to induction of elastic constituents. Immunohistochemistry and electron microscopy confirmed an upregulation of LOXL1 and elastic fiber proteins and their assembly into extracellular microfibrillar networks with focal aggregation of microfibrils into PEX-like fibrils on stimulation with TGF-?1 and oxidative stress. Basal and stimulated expression of LOXL1 mRNA and protein was slightly decreased in cells carrying the high-risk compared with the low-risk haplotype of LOXL1, but the differences between groups were statistically not significant. Conclusions. The findings support the notion that both genetic and nongenetic fibrogenic factors, particularly TGF-?1 and oxidative stress, may cooperate in the stable accumulation of PEX aggregates.
EVALuna2:9087

Regulatory eosinophils induce the resolution of experimental arthritis and appear in remission state of human rheumatoid arthritis - Andreev, Darja; Liu, Mengdan; Kachler, Katerina; Llerins Perez, Mireia; Kirchner, Philipp; Kölle, Julia; Gießl, Andreas; Rauber, Simon; Song, Rui; Aust, Oliver; Grüneboom, Anika; Kleyer, Arnd; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives: Eosinophils possess pro-inflammatory functions in asthma. However, our recent studies have suggested that innate lymphoid cells type 2 (ILC2s) and eosinophils have proresolving properties in rheumatoid arthritis (RA). Nothing is known yet about the mechanisms determining the double-edged role of eosinophils. Therefore, we investigated whether asthma, a paradigm eosinophilic disease, can elicit resolution of chronic arthritis. Methods: Ovalbumin-triggered eosinophilic asthma was combined with K/BxN serum-induced arthritis, where lung and synovial eosinophil subsets were compared by single-cell RNA sequencing (scRNA-seq). To investigate the involvement of the ILC2-interleukin-5 (IL-5) axis, hydrodynamic injection (HDI) of IL-25 and IL-33 plasmids, IL-5 reporter mice and anti-IL-5 antibody treatment were used. In patients with RA, the presence of distinct eosinophil subsets was examined in peripheral blood and synovial tissue. Disease activity of patients with RA with concomitant asthma was monitored before and after mepolizumab (anti-IL-5 antibody) therapy. Results: The induction of eosinophilic asthma caused resolution of murine arthritis and joint tissue protection. ScRNA-seq revealed a specific subset of regulatory eosinophils (rEos) in the joints, distinct from inflammatory eosinophils in the lungs. Mechanistically, synovial rEos expanded on systemic upregulation of IL-5 released by lung ILC2s. Eosinophil depletion abolished the beneficial effect of asthma on arthritis. rEos were consistently present in the synovium of patients with RA in remission, but not in active stage. Remarkably, in patients with RA with concomitant asthma, mepolizumab treatment induced relapse of arthritis. Conclusion: These findings point to a hitherto undiscovered proresolving signature in an eosinophil subset that stimulates arthritis resolution.
CRIS-Team Scopus Importer:2020-11-20
Keywords: arthritis; autoimmune diseases; cytokines; immune system diseases; inflammation; rheumatoid

Relationship between stimulus size and different components of the electroretinogram (ERG) elicited by flashed stimuli - Nittmann, Mathias; Aher, Avinash; Kremers, Jan; Tzekov, Radouil T. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Relationship between stimulus size and different components of the electroretinogram (ERG) elicited by flashed stimuli - Nittmann, Mathias G.; Aher, Avinash; Kremers, Jan; Tzekov, Radouil (Documenta Ophthalmologica, 2020)
Purpose: To investigate how light stimulus conditions of varying spatial sizes affect components of the flash and long-flash electroretinogram (ERG) in normal subjects. Method: Three stimulus conditions were generated by a Ganzfeld stimulator: a white flash on white background (WoW), a red flash on a blue background (RoB) and an L+M-cone isolating on–off (long flash) stimulus (Cone Iso). ERGs were recorded from six subjects (5 M, 1 F) with DTL electrodes to full-field (FF), 70°, 60°, 50°, 40°, 30° and 20° diameter circular stimuli. Amplitudes and peak times for a-, b-, d- and i-wave, and PhNR were examined. PhNR amplitudes were estimated in two different ways: from baseline (fB) and from preceding b-wave peak (fP). Results: With decreasing stimulus size, amplitudes for all ERG waveform components attenuated and peak times increased, although the effect varied across different components. An exponential fit described the relationship between amplitudes and size of stimulated retinal area well for most components and conditions (R2= 0.75-0.99), except for PhNR(fB) (R2= − 0.16–0.88). For peak times, an exponential decay function also fitted the data well (R2= 0.81–0.97), except in a few cases where the exponential constant was too small and a linear regression function was applied instead (a-wave Cone Iso, b- and i-wave WoW). The exponential constants for RoB amplitudes (b-wave, PhNR(fB), PhNR(fP)) were larger compared to their counterparts under WoW (p < 0.05), while there was no difference between the constants for a-wave amplitudes and peak times and for PhNR peak times. The exponential constants of amplitudes vs. area under WoW and Cone Iso were remarkably similar, while under RoB PhNR(fB) showed larger constants compared to either a- or b-wave (p < 0.05). Conclusion: ERG components change in a predictable way with stimulus size and spectral characteristics of the stimulus under these conditions. This predictability could allow a modified version of these sets of stimuli to be tested for clinical applicability.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Electroretinogram; Flash stimuli; Photopic negative response; Square wave stimuli; Stimulus size

Relationship between temporal L-coneflicker sensitivity and established clinical parameters in Stargardt's disease - Huchzermeyer, Cord; Fars, Julien; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Relaxin 2 is functional at the ocular surface and promotes corneal wound healing - Hampel, Ulrike; Klonisch, Thomas; Sel, Saadettin; Schulze, Ute; Garreis, Fabian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2012)
We aimed to determine if the insulin-like peptide hormone relaxin 2 (RLN2) is expressed at the ocular surface and in tears and if RLN2 influences wound healing at the ocular surface, which is associated with extracellular matrix (ECM) remodeling.We analyzed transcript levels of human RLN2 and its cognate relaxin-like receptors RXFP1 and RXFP2 in tissues of the ocular surface, lacrimal apparatus, and human corneal (HCE), conjunctival (HCjE) and sebaceous (SC) cell lines. We analyzed effects of human RLN2 on cell proliferation and migration and quantified mRNA expression of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in HCE, HCjE, and SC. Using an alkali-induced corneal wounding model, we analyzed the wound healing rate in C57BL/6 mice eyes after topically applied RLN2.The presence of RLN2, RXFP1, and RXFP2 transcripts was detected in lacrimal gland, eyelid, conjunctiva, cornea, primary corneal fibroblasts, nasolacrimal ducts, and all three cell lines. ELISA revealed RLN2 protein in all ocular surface tissues analyzed and in human tears. Stimulation of HCE, HCjE, and SC with RLN2 significantly increased cell proliferation and migration. Relative mRNA expression levels of MMP2, MMP9, TIMP1, and TIMP2 were significantly influenced by RLN2 in all three cell lines at different time points studied. The local application of RLN2 onto denuded corneal surface resulted in significantly elevated corneal wound healing.Our data support a novel role for the RLN2 ligand-receptor system at the ocular surface and in the lacrimal apparatus as a potential future therapeutic during wound healing at the ocular surface.
EVALuna2:4369

Repetitive dynamic stereo test improved processing time in young athletes - Schoemann, MD; Lochmann, Matthias; Paulus, J; Michelson, Georg (Restorative Neurology and Neuroscience, 2017)

Repetitive tests of visual function improved visual acuity in young subjects - Otto, Juliane; Michelson, Georg (British Journal of Ophthalmology, 2014)
To test visual function after repetitive tests of visual acuity (VA) and contrast sensitivity (CS).Ten young female subjects performed repetitive tests of visual functions over ten sessions within 5 weeks. Per week they performed two 30 min sessions of repetitive tests of central VA, CS and vernier acuity (VT) using Michael Bach's Freiburg Vision Test FrACT 3.5.5. FrACT presents an optotype in different spatial frequencies or an optotype with decreasing contrast. Using SPSS Statistics we analysed the correlation between the number of repetitive test sessions and the change in visual function of the total group and of the individuals.After ten sessions, we found a significant improvement in VA, CS and VT. When compared with the initial session, VA increased by 32%, mean CS improved by 40% and mean VT enhanced by 47%. We also found a significant correlation between the number of test sessions and VA (r=-0.374, p<0.01), CS (r=-0.258, p<0.05) and VT (r=-0.379, p<0.01). Individual changes in vision were variable. In eight subjects, VA and CS improved significantly. VT improved in nine subjects. Our data suggest that repetitive tests of visual function may improve VA significantly.
EVALuna2:21166

Reply to the Letter to the Editor titled, "Bruch's membrane does not seem to have a role in myopization" - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2017)
EVALuna2:21173

Reproducibility of graft preparations in Descemet's membrane endothelial keratoplasty - Schlötzer-Schrehardt, Ursula; Bachmann, Björn; Tourtas, Theofilos; Cursiefen, Claus; Zenkel, Matthias; Roessler, Kathrin; Kruse, Friedrich (Ophthalmology, 2013)
To assess the reproducibility of manual graft preparation and evaluate the incidence rate and nature of structural anomalies of Descemet's membrane (DM) preventing successful graft preparation in DM endothelial keratoplasty (DMEK).Prospective, single-center, nonrandomized, consecutive case series.We analyzed 350 corneoscleral buttons from donors aged 18-95 years stored in Optisol-GS or Dulbecco's modified Eagle's medium and used for DMEK surgery in 343 consecutive patients with Fuchs' endothelial dystrophy or pseudophakic bullous keratopathy.Residual endothelial cell-DM complexes obtained after successful DM stripping for DMEK and whole donor corneas obtained after unsuccessful DM stripping were examined by transmission electron microscopy and immunohistochemistry.Accuracy of the cleavage plane between DM and corneal stroma and structural abnormalities of the DM-stroma interface.Uneventful manual separation without any disruption of DM was achieved in 335 of 350 donor corneas (95.7%) by use of a previously established bimanual submerged preparation technique. Correspondingly, the peeled DM specimens revealed a regular and smooth cleavage plane exposing the amorphous interfacial matrix on their anterior surface. Although 8 of 350 donor corneas (2.3%) showed focal adhesions of DM to the corneal stroma and developed isolated tears during stripping, preparation of the graft could be successfully completed. However, 7 of the 350 donor corneas (2.0%) showed extremely strong adhesion and multiple tears of DM, preventing successful preparation of the graft. These specimens revealed either ultrastructural (peg-like interlockings) or biochemical abnormalities (increased staining intensities for adhesive glycoproteins) along the DM-stroma interface.Using an appropriate technique, manual preparation of grafts for DMEK with reproducible tissue qualities is possible in the vast majority (98%) of donor corneas. Although a relatively rare phenomenon, interindividual variations in DM structure and composition may be responsible for failure of graft preparation in about 2% of donor corneas.The authors have no proprietary or commercial interest in any of the materials discussed in this article.
EVALuna2:21132

Reproducibility of Multifocal Erg Responses in Patients and Healthy Subjects - Link, B.; Ruehl, S.; Jünemann, Anselm; Horn, Folkert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2010)
Keywords: electroretinography: clinical

Rescue of Defective Electroretinographic Responses in Dp71-Null Mice With AAV-Mediated Reexpression of Dp71 - Salgueiro Barboni, Mirella Telles; Vaillend, Cyrille; Joachimsthaler, Anneka; Passos Liber, Andre Mauricio; Khabou, Hanen; Roux, Michel J.; Vacca, Ophelie; Vignaud, Lucile; Dalkara, Deniz; Guillonneau, Xavier; Ventura, Dora Fix; Rendon, Alvaro; et al. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. To study the potential effect of a gene therapy, designed to rescue the expression of dystrophin Dp71 in the retinas of Dp71-null mice, on retinal physiology.
CRIS-Team WoS Importer:2020-03-20

Responses of postreceptoral pathways elicited by L- And M-cone isolating ON- And OFF-electroretinograms in glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. To compare the electroretinographical (ERG) responses elicited by L- and M-cone isolating ON- and OFF-sawtooth stimuli in normal subjects and glaucoma patients. METHODS. Twenty-one normal subjects and 44 primary open-angle glaucoma patients participated in the study. L- and M-cone isolating (18% cone contrast; 284 cd/m2) rapid ON- and rapid OFF-sawtooth (4 Hz) stimuli with two stimulus sizes (full-field (FF) and central 70° diameter) were generated using the triple silent substitution technique. ON- and OFF-response asymmetries were studied by adding the two (to obtain L-add and M-add responses). The initial positive (P) and subsequent late negative (LN) components of the L-add and M-add ERGs were compared between the subject groups and correlated with retinal nerve fiber layer thickness (RNFLT) and pattern ERG responses. RESULTS. The responses to L-ON and to M-OFF stimuli and vice versa resembled each other particularly with 70° stimuli. The PL-add amplitudes were not significantly different between the normal subjects and glaucoma patients, whereas the LNL-add amplitude was significantly (P < 0.01) smaller in the glaucoma patients. Both PM-add and LNM-add were not significantly different between the subject groups. The PERG amplitude with 0.8° check sizes and the 0.8°/16° amplitude ratio (PERG ratio) were significantly (P < 0.05) different between the subject groups. The 70° LNL-add amplitude and the 0.8° PERG amplitude were significantly correlated with RNFLT. CONCLUSIONS. The ERGs to 70° cone isolating sawtooth stimuli reflect cone opponency. The cone opponent ERG responses were not significantly different between glaucoma patients and normal subjects. Luminance driven L-add responses were significantly different, indicating that central luminance signals are mainly affected in glaucoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Glaucoma; Magnocellular; ON- and OFF electroretinogram; Parvocellular; Sawtooth stimuli; Silent substitution; Stimulus size

Retina Image Analysis System for Glaucoma Detection - Bock, Rüdiger; Meier, Jörg; Nyul, Laszlo Gabor; Michelson, Georg; Hornegger, Joachim (Biomedizinische Technik, BMT 2007, 2007)

Retinal disorders in northern Brazilian patients treated with chloroquine assessed by multifocal ERG - Raster, M.; Horn, Folkert; Jünemann, Anselm; Rosa, A. A. M.; Souza, G. S.; Gomes, B. D.; Lima, M. G.; Silveira, L. C. L.; Kremers, Jan (Documenta Ophthalmologica, 2011)
The effects of chloroquine intake on the retinal function in a Brazilian population of patients were assessed by multifocal electroretinography. Twenty-four randomly chosen eyes of patients treated with chloroquine for rheumatoid arthritis and systemic lupus erythematosus were examined using multifocal electroretinography (mfERG). Control measurements were acquired from 21 randomly chosen eyes of age-matched healthy subjects. None of the study participants had an inherited retinal disease or a Snellen visual acuity reduced to less than 20/40. In patients and control subjects, cumulative chloroquine dose, total daily dose, duration of treatment, retinal examination, visual field defects, visual acuity, and the mfERG were assessed. The average amplitudes and implicit times of the N1, P1, and P2 components of the mfERGs were measured in the central hexagon (R1) and in five rings (R2-R6). The values measured in patients and normal subjects were compared. The P1 amplitudes in R2 were significantly decreased in the patients. In addition, the amplitudes of N1 and N2 in R1 were significantly smaller in the patients. The implicit times of none of the components were significantly different between patients and controls. The response amplitude was not significantly correlated with cumulative dose and duration of intake. There was no correlation with retinal appearance, visual field, and visual acuity. In agreement with earlier data, the central mfERG amplitudes were decreased in chloroquine patients indicating functional alterations in the retina. These changes are also present in a Brazilian population suggesting that the effects of chloroquine are general and that genetic background and life circumstances probably have, if at all, only little effect.
EVALuna2:21006

Retinal dystrophins and the retinopathy of Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Joachimsthaler, Anneka; Roux, Michel J.; Nagy, Zoltán Zsolt; Ventura, Dora Fix; Rendon, Alvaro; Kremers, Jan; Vaillend, Cyrille (Progress in Retinal and Eye Research, 2022)
Duchenne muscular dystrophy (DMD) is caused by X-linked inherited or de novo DMD gene mutations predominantly affecting males who develop early-onset muscle degeneration, severely affecting their quality of life and leading to reduced life expectancy. DMD patients may also develop proliferative retinopathy, cataract, ERG abnormalities, altered contrast sensitivity, color vision losses, and elevated flash detection thresholds during dark adaptation. Depending on the position of the genetic alteration in the large DMD gene, it is associated with a lack of the full-length dystrophin protein possibly with an additional loss of one or several other dystrophins, which are normally transcribed from internal promoters in retina and crystalline lens. During the last decades, the properties of the dystrophins have been characterized in patients with different genetic alterations and in genetic mouse models of DMD. The complex expression pattern of the dystrophins in photoreceptors, Müller glial cells and astrocytes, likely influences synaptic transmission, ionic balance and vascular integrity of the retina. However, the specific function of each retinal dystrophin remains largely unknown. This review describes the current knowledge on dystrophin expression, the putative molecular, structural, and physiological properties of retinal dystrophins, and the main clinical implications associated with the loss of dystrophins in DMD patients and mouse models. Current data and working hypotheses warrant future research on retinal dystrophins to increase our understanding of dystrophin function in the central nervous system in general and to unveil new retinal mechanisms and therapeutic avenues for retinal diseases.
CRIS-Team Scopus Importer:2022-12-02
Keywords: DMD gene; Duchenne and becker muscular dystrophy; Dystrophin; Electroretinogram; Gene therapy; Retina

Retinal dystrophy with kidney disease - Hohberger, B.; Reil, F.; Meiller, R. (Ophthalmologe, 2018)
EVALuna2:34731

Retinal image quality assessment based on image clarity and content - Abdel-Hamid, Lamiaa; El-Rafei, Ahmed; El-Ramly, Salwa; Michelson, Georg; Hornegger, Joachim (Journal of Biomedical Optics, 2016)
EVALuna2:21281

Retinal image registration for eye movement estimation - Kolar, Radim; Tornow, Ralf-Peter; Odstrcilik, Jan (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2015)
This paper describes a novel methodology for eye fixation measurement using a unique videoophthalmoscope setup and advanced image registration approach. The representation of the eye movements via Poincare plot is also introduced. The properties, limitations and perspective of this methodology are finally discussed.
EVALuna2:21269

Retinal imaging and axonal degeneration in later onset multiple sclerosis - Huhn, Konstantin; Lämmer, Robert; Meng, Hanna Zimmermann; Laemmer, Alexandra; Waschbisch, Anne; Utz, Kathrin; Giess, Rene Markus; Paul, Friedemann; Linker, Ralf; Lee, De-Hyung (Journal of the Neurological Sciences, 2016)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the CNS typically affecting younger adults and resulting in neuro-axonal degeneration already at early stages of the disease. Less is known about the effects of a later disease onset (LOMS, onset >50years of age). Analysis of retinal layers by optical coherence tomography (OCT) is a non-invasive method to investigate retinal and neuro-axonal degeneration. We applied OCT to detect differences in retinal damage depending on a later disease manifestation.14 LOMS patients, 14 age- and 14 disease duration-matched normal onset (NOMS) patients with a relapsing remitting disease course and 15 healthy controls (HC) were included. OCT measurement of peripapillary retinal nerve fiber layer (RNFL), total macular volume (TMV), combined ganglion cell/inner plexiform layer (GCIPL), inner nuclear layer (INL) and outer retinal layers (ORL) was conducted. Furthermore, analysis of clinical features and of effects of previous optic neuritis (ON) was performed RESULTS: In a GEE based analysis of age- and disease duration matched NOMS, LOMS patients show no significant differences in retinal layer thickness whereas ON significantly reduced thickness of retinal layers. All MS groups display lower retinal layer thickness as compared to HC independently of type of onset.Our LOMS findings are well in line with published OCT data of normal onset MS. As the degree of retinal layer thinning was similar in MS subgroups, retinal neurodegeneration in MS may occur independently of time of disease onset.
EVALuna2:21282

Retinal microangiopathy in arterial hypertension as an early marker of a cerebral macroangiopathy - Michelson, Georg; Engelhorn, Tobias; Dörfler, Arnd (Deutsche Medizinische Wochenschrift, 2011)
A 54-year-old man reported having had nonspecific attacks of dizziness. His BMI was 27.7. Since 11 years he had been treated for arterial hypertension and had received oral medication for type 2 diabetes for one year. The latest blood pressure value was 134/109 mm Hg during treatment with a combination of atenolol, chlortalidone und hydralazine-HCl; furthermore hr received simvastatin, metformin, glimepirid und ramipril. A standardized telemedical imaging of the retina ("talkingeyes (®) ") was undertaken, revealing focal and generalized arteriolar narrowing of the retinal vessels and a retinal microinfarction (cotton wool spot) in the right eye. The arterial/venous ratio was decreased to 0.74 in the right and 0.77 in the left eye.Optical coherence tomographie (OCT) revealed an ischemic microinfarction of the retina with marked axonal swelling. The digital subtraction angiography of the cerebral vessels revealed a 40 % stenosis of the right internal carotid artery and a proximal, highgrade stenosis of the basilary artery.Angioplasty with stent insertion of the basilary artery was performed. Long-term observation showed no restenosis and a reduction in the size of the the retinal microinfarct.Retinal microinfarctions denote localized retinal areas of hypoxia and underperfusion. They may act as markers of a generalized micro- and macroangiopathy. Patients with severe retinal microangiopathic changes should be examined thoroughly to detect early macroangiopathic changes. These can be treated by interventional procedures thus avoiding irreversible end-organ damages.
EVALuna2:21059

Retinal Microcirculation as a Correlate of a Systemic Capillary Impairment After Severe Acute Respiratory Syndrome Coronavirus 2 Infection - Hohberger, Bettina; Ganslmayer, Marion; Lucio, Marianna; Kruse, Friedrich; Hoffmanns, Jakob; Moritz, Michael; Rogge, Lennart; Heltmann, Felix; Szewczykowski, Charlotte; Fürst, Julia; Raftis, Maximilian; Bergua, Antonio; et al. (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), affects the pulmonary systems via angiotensin-converting enzyme-2 (ACE-2) receptor, being an entry to systemic infection. As COVID-19 disease features ACE-2 deficiency, a link to microcirculation is proposed. Optical coherence tomography angiography (OCT-A) enables non-invasive analysis of retinal microvasculature. Thus, an impaired systemic microcirculation might be mapped on retinal capillary system. As recent OCT-A studies, analyzing microcirculation in two subdivided layers, yielded contrary results, an increased subdivision of retinal microvasculature might offer an even more fine analysis. The aim of the study was to investigate retinal microcirculation by OCT-A after COVID-19 infection in three subdivided layers (I). In addition, short-term retinal affections were monitored during COVID-19 disease (II). Considering (I), a prospective study (33 patientspost−COVID and 28 controls) was done. Macula and peripapillary vessel density (VD) were scanned with the Spectralis II. Macula VD was measured in three layers: superficial vascular plexus (SVP), intermediate capillary plexus (ICP), and deep capillary plexus (DCP). Analysis was done by the EA-Tool, including an Anatomical Positioning System and an analysis of peripapillary VD by implementing Bruch's membrane opening (BMO) landmarks. Overall, circular (c1, c2, and c3) and sectorial VD (s1-s12) was analyzed. Considering (II), in a retrospective study, 29 patients with severe complications of COVID-19 infection, hospitalized at the intensive care unit, were monitored for retinal findings at bedside during hospitalization. (I) Overall (p = 0.0133) and circular (c1, p = 0.00257; c2, p = 0.0067; and c3, p = 0.0345). VD of the ICP was significantly reduced between patientspost−COVID and controls, respectively. Overall (p = 0.0179) and circular (c1, p = 0.0189) peripapillary VD was significantly reduced between both groups. Subgroup analysis of hospitalized vs. non-hospitalized patientspost−COVID yielded a significantly reduced VD of adjacent layers (DCP and SVP) with increased severity of COVID-19 disease. Clinical severity parameters showed a negative correlation with VD (ICP) and peripapillary VD. (II) Funduscopy yielded retinal hemorrhages and cotton wool spots in 17% of patients during SARS-CoV-2 infection. As VD of the ICP and peripapillary regions was significantly reduced after COVID-19 disease and showed a link to clinical severity markers, we assume that the severity of capillary impairment after COVID-19 infection is mapped on retinal microcirculation, visualized by non-invasive OCT-A.
CRIS-Team Scopus Importer:2021-08-06
Keywords: COVID-19; macula; microcirculation; OCT-angiography; optic nerve head; retina; SARS-CoV-2

Retinal Microcirculation in Type 1 Diabetic Patients With and Without Peripheral Sensory Neuropathy - Forst, Thomas; Weber, Matthias M.; Mitry, Michael; Müller, Lena; Forst, Senait; Tanis, Mukkadar; Pfützner, Andreas; Michelson, Georg (Journal of diabetes science and technology, 2014)
In patients with diabetes mellitus (DM), early retinal microvascular alterations can be observed even before the clinical diagnosis of diabetic retinopathy. This study aimed to investigate morphological and functional changes in retinal microvascular blood flow in type 1 diabetic patients with and without peripheral neuropathy (PNP) as compared to nondiabetic controls. Retinal microvascular blood flow (RBF) was assessed using scanning laser Doppler flowmetry (Heidelberg Retina Flowmeter, Heidelberg Engineering, Germany) before and after stimulation with flicker light. PNP was assessed using the neuropathy disability score (NDS) and by the evaluation of the vibration perception threshold (VPT). A total of 41 subjects were recruited for study participation and were stratified to 3 different groups according to their metabolic and neurological status: 14 nondiabetic subjects without PNP, 14 diabetic patients without PNP, and 13 diabetic patients with PNP. All subjects were free from diabetic retinopathy as assessed by fundoscopy. In diabetic patients with PNP, baseline and stimulated RBF was higher compared with diabetic patients without PNP and the nondiabetic control group. No difference with regard to RBF could be observed between the nondiabetic control subjects and patients with type 1 DM without PNP. No difference in the arterial WLR could be observed between the 3 groups. A linear correlation was found for VPT and RBF (r = .38, P < .001) and for NDS and RBF (r = .44, P < .0001). In our study population of patients with type 1 diabetes, PNP was associated with functional but not morphological changes in RBF.
EVALuna2:21192

Retinal microperfusion after renal denervation in treatment-resistant hypertensive patients - Ott, Christian; Harazny, Joanna M.; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Bladowski, Marek; Michelson, Georg; Uder, Michael; Schmieder, Roland (Clinical Research in Cardiology, 2015)
High pulsatile pressure and flow in the arteries causes microvascular damage, and hence increased cardio-, and cerebrovascular complications. With advanced stages of hypertensive disease, an exaggerated pulsatile retinal capillary flow (RCF) has been shown, but data about interventional effect are missing.Fifty-one patients with true treatment-resistant hypertension (TRH) underwent renal denervation (RDN) using the Symplicity Flex(TM) catheter and were followed for 12 months. RCF was assessed non-invasively using Scanning laser Doppler flowmetry (SLDF) before, 6 (6 M), and 12 (12 M) months after RDN. RCF was measured in systole and diastole and pulsed RCF (difference of RCF in systole minus diastole) was calculated. In addition, flicker light-induced vasodilation (representing vasodilatory capacity) was assessed.Systolic and diastolic office blood pressure (BP) as well as 24-h ABPM decreased significantly 6 M and 12 M after RDN, compared to baseline values (all p < 0.001). There was a significant reduction of pulsed RCF 6 M (231 ± 81 versus 208 ± 68 AU, p = 0.046) and 12 M (194 ± 72 AU, p = 0.001) after RDN, whereas the mean RCF was unchanged. Moreover, there was a significant increase of flicker light-induced vasodilation after RDN (p = 0.043).In hypertensive patients with TRH, we observed a decrease of pulsed RCF 6 M and 12 M after RDN and an increase of vasodilatory capacity, in parallel to decreases in BP and heart rate. The reduction of pulsed RCF after RDN implies a decrease of shear stress on the vascular wall by the pulsed blood flow. This and the increment of vasodilatory capacity suggest an improvement of retinal (and potentially cerebral) microcirculation.
EVALuna2:3762

Retinal microvascular signs and recurrent vascular events in patients with TIA or minor stroke - Klyscz, Philipp; Ihl, Thomas; Laumeier, Inga; Steinicke, Maureen; Endres, Matthias; Michelson, Georg; Audebert, Heinrich J. (Stroke and Vascular Neurology, 2023)
Background and purposeRetinal pathologies are an independent risk factor for ischaemic stroke, but research on the predictive value of retinal abnormalities for recurrent vascular events in patients with prior stroke is inconclusive. We investigated the association of retinal pathologies with subsequent vascular events. MethodsIn a substudy of the Intensified secondary prevention intending a reduction of recurrent events in TIA and minor stroke patients (INSPiRE-TMS) trial, we enrolled patients with recent transient ischaemic attack (TIA) or minor stroke with at least one modifiable risk factor. Primary outcome was the composite of subsequent vascular events. Retinal photographs were taken at baseline and categorised into three different fundus groups by a telemedically linked ophthalmologist. Results722 patients participated in the current study and 109 major vascular events occurred. After multivariable adjustments, we did not find a significant association between fundus categories and risk for subsequent vascular events (HRs for moderate vascular retinopathy and vascular retinopathy with vessel rarefaction in comparison to no vascular retinopathy 1.03 (95% CI 0.64 to 1.67), p=0.905 and 1.17 (95% CI 0.62 to 2.20), p=0.626). In a selective post hoc analysis in patients with diabetes mellitus and hypertension, patients with vascular retinopathy with vessel rarefaction had a higher risk for recurrent stroke (HR 24.14 (95% CI 2.74 to 212.50), p=0.004). ConclusionsRetinal changes did not predict major subsequent vascular events in patients with recent TIA or minor stroke. Further studies are needed to examine the utility of fundus photography in assessing the risk of stroke recurrence in patients with diabetes mellitus and hypertension.
CRIS-Team WoS Importer:2023-03-31

Retinal nerve fiber layer segmentation on FD-OCT scans of normal subjects and glaucoma patients - Mayer, Markus Anton; Hornegger, Joachim; Mardin, Christian Y.; Tornow, Ralf-Peter (Biomedical Optics Express, 2010)
Automated measurements of the retinal nerve fiber layer thickness on circular OCT B-Scans provide physicians additional parameters for glaucoma diagnosis. We propose a novel retinal nerve fiber layer segmentation algorithm for frequency domain data that can be applied on scans from both normal healthy subjects, as well as glaucoma patients, using the same set of parameters. In addition, the algorithm remains almost unaffected by image quality. The main part of the segmentation process is based on the minimization of an energy function consisting of gradient and local smoothing terms. A quantitative evaluation comparing the automated segmentation results to manually corrected segmentations from three reviewers is performed. A total of 72 scans from glaucoma patients and 132 scans from normal subjects, all from different persons, composed the database for the evaluation of the segmentation algorithm. A mean absolute error per A-Scan of 2.9 μm was achieved on glaucomatous eyes, and 3.6 μm on healthy eyes. The mean absolute segmentation error over all A-Scans lies below 10 μm on 95.1% of the images. Thus our approach provides a reliable tool for extracting diagnostic relevant parameters from OCT B-Scans for glaucoma diagnosis. © 2010 Optical Society of America.

Retinal neurodegeneration in patients with end-stage renal disease assessed by spectral-domain optical coherence tomography - Jung, Susanne; Bosch, Agnes; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Scientific Reports, 2020)
Spectral-domain optical coherence tomography (SD-OCT) represents a reliable tool for retinal layer volume and thickness measurement. The aim of this study was to evaluate retinal changes indicating neurodegenerative processes in patients with end-stage renal disease (ESRD) compared to healthy controls. This was a cross-sectional, single-center study comprising 32 ESRD patients and 38 controls. Sectoral retinal nerve fiber layer (RNFL) thickness and retinal layer volumes were obtained by SD-OCT. Age- and gender-adjusted retinal layer volumes such as total retinal volume (p = 0.037), ganglion cell layer volume (GCL, p = 0.003), ganglion cell layer – inner plexiform layer volume (GCL-IPL, p = 0.005) and inner retinal layer volume (IRL, p = 0.042) of the right eye were lower in ESRD patients. Inner plexiform layer volume of both eyes (IPL, right eye: p = 0.017; left eye: 0.044) was reduced, as was RNFL thickness in the temporal superior sector (right eye: p = 0.016). A subgroup analysis excluding patients with diabetes revealed that GCL (p = 0.014) and GCL-IPL volume of the right eye (p = 0.024) and temporal superior sector of the RNFL scan (p = 0.021) in ESRD patients were still significantly thinner. We observed a decrease in several retinal layer volumes and temporal RNFL thickness indicative of retinal neurodegenerative processes in patients with ESRD.
CRIS-Team Scopus Importer:2020-04-03

Retinal Pigment Epithelium Cell Density and Bruch’s Membrane Thickness in Secondary versus Primary High Myopia and Emmetropia - Jonas, Jost B.; Li, Dong; Holbach, Leonard; Panda-Jonas, Songhomitra (Scientific Reports, 2020)
To assess differences between secondary high myopia (SHM) due to congenital glaucoma and primary high myopia (PHM) and non-highly myopic eyes (NHM) in the relationships between axial length and Bruch’s membrane (BM) thickness and retinal pigment epithelium (RPE) density. The histomorphometric study included human globes enucleated for reasons such as malignant uveal melanoma, end-stage painful secondary angle-closure glaucoma and congenital glaucoma. BM thickness and RPE cell density were measured upon light microscopy. The investigation included 122 eyes (mean axial length: 26.7 ± 3.7 mm; range: 20.0–37.0 mm): 7 eyes with SHM (axial length: 33.7 ± 2.1 mm; range: 31.0–37.0 mm), 56 eyes with PHM (mean axial length: 29.1 ± 2.4 mm; range: 26.0–36.0 mm) and 59 eyes in the NHM-group (axial length: 23.5 ± 1.3 mm; range: 20.0–25.5 mm). In the SHM group, longer axial length was associated with lower RPE cell density at the posterior pole (standardized regression coefficient beta: 0.92; non- standardized regression coefficient B: −2.76; 95% confidence interval (CI): −4.41, −1.10;P = 0.01), at the midpoint posterior pole/equator (beta: −0.87; B: −3.60; 95% CI: −6.48, −0.73;P = 0.03), and at the equator (beta: −0.88; B: −0.95; 95% CI: −1.68, −0.23; P = 0.02), but not at the ora serrata (P = 0.88). In the PHM-group and NHM group, RPE cell density at the posterior pole (P = 0.08) and ora serrata (P = 0.88) was statistically independent of axial length, while at the midpoint posterior pole/equator (P = 0.01) and equator (P < 0.001), RPE cell density decreased with longer axis. BM thickness in the SHM group decreased with longer axial length at the posterior pole (beta: −0.93;B: −0.29; 95% CI: −0.39, −0.14; P = 0.003), midpoint posterior pole/equator (beta: −0.79; B: −0.22; 95% CI: −0.42, −0.02; P = 0.035) and equator (beta: −0.84; B: −0.21; 95% CI: −0.37, −0.06; P = 0.017), while in the PHM-group and NHM-group, BM thickness at any ocular region was not statistically significantly correlated with axial length (all P > 0.05). In the SHM-group, but not in the PHM-group or NHM-group (P = 0.98), lower BM thickness was associated with lower RPE cell density (beta: 0.93; B: 0.09; 95% CI: 0.04, 0.14; P = 0.007), while in the eyes without congenital glaucoma the relationship was not statistically significant. In SHM in contrast to PHM, BM thickness and RPE cell density decrease in a parallel manner with longer axial length. The findings fit with the notion of BM being a primary driver in the process of axial elongation in PHM as compared to SHM.
CRIS-Team Scopus Importer:2020-03-31

Retinal pigment epithelium cell density in relationship to axial length in human eyes - Jonas, Jost B.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2017)
To assess associations between axial length and density of retinal pigment epithelium (RPE) cells in various ocular regions.The histomorphometric investigation included histological sections of enucleated eyes of Caucasian patients. Using a light microscope, we counted the number of RPE cells on Bruch's membrane at the ora serrata, in the pre-equatorial region, the equatorial and retro-equatorial region, at the midpoint equator/posterior pole, and at the posterior pole.The study included 65 globes with a mean axial length 25.9 ± 3.5 mm (range: 21.0-34.0 mm). Retinal pigment epithelium (RPE) cell count in the equatorial to retro-equatorial region (p < 0.001; correlation coefficient r(2) : 0.44), in the pre-equatorial region (p < 0.001; r(2) : 0.39) and at the midpoint equator/posterior pole (p = 0.03; r(2) : 0.12) decreased with increasing axial length. Retinal pigment epithelium (RPE) cell count at the ora serrata (p = 0.49) and posterior pole (p = 0.44) was not significantly correlated with axial length. As a corollary, mean RPE cell density was higher (p < 0.001) at the posterior pole than at the midpoint equator/posterior pole or at the ora serrata region, where it was higher than in pre-equatorial region (p < 0.001) and in the equatorial to retro-equatorial region (p < 0.001).The decrease in the RPE cell density mainly in the equatorial to retro-equatorial region in association with longer axial length suggests a region of enlargement of Bruch's membrane in the equatorial to retro-equatorial area in association with axial elongation. The finding may be of interest to elucidate the process of emmetropization/myopization.
EVALuna2:21313

Retinal pulsatile shift enhancement with blind source separation - Labounkova, Ivana; Labounek, Rene; Odstrcilik, Jan; Hracho, Michal; Nestrasil, Igor; Tornow, Ralf-Peter; Kolar, Radim (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2021-10-18

Retinal Thickness and Axial Length - Jonas, Jost B.; Xu, Liang; Wei, Wen Bin; Pan, Zhe; Yang, Hua; Holbach, Leonard; Panda-Jonas, Songhomitra; Wang, Ya Xing (Investigative Ophthalmology & Visual Science, 2016)
To examine the relationships between axial length and foveal and peripheral retinal thickness.Using optical coherence tomography, foveal retinal thickness was measured in participants of the population-based Beijing Eye Study without optic nerve or macula diseases. Inner and outer nuclear layer thickness as surrogate for retinal thickness was assessed in the fundus periphery in human globes enucleated due to malignant uveal melanoma or painful glaucoma.The study included 1117 individuals with a mean age of 64.2 ± 9.7 years (range: 50-93 years) and mean axial length of 23.4 ± 1.04 mm (range: 20.29-28.68 mm). In multivariate analysis, thicker central foveal thickness was associated with male sex (P < 0.001; standardized regression coefficient beta: -0.13; nonstandardized regression coefficient B: -5.84; 95% confidence interval (CI): -8.56, -3.13); urban region of habitation (P = 0.02; beta: 0.07; B: 3.56; 95% CI: 0.55, 6.57); thinner lens thickness (P = 0.01; beta: -0.08; B: -5.11; 95% CI: -9.01, -1.21); thinner subfoveal choroidal thickness (P = 0.04; beta: -0.07; B: -0.01; 95% CI: -0.03, -0.001); and longer axial length (P < 0.001; beta: 0.18; B: 3.79; 95% CI: 2.41, 5.17). In the same multivariate model, superior, inferior, and temporal foveal thickness was not significantly associated with axial length (P = 0.26, P = 0.19, P = 0.08, respectively), while thicker nasal foveal thickness was associated with longer axial length (P = 0.009; beta: 0.09; B: 1.50; 95% CI: 0.37, 2.62). In the histomorphometric part of the study including 32 eyes (sagittal diameter: 27.0 ± 4.2 mm; range: 22-37 mm), mean thickness of the inner and outer nuclear layers at the equator and at the midpoint equator/posterior pole decreased with longer axial length (P = 0.004; beta: -0.48; and P = 0.02; beta: -0.44, respectively).Myopic axial globe elongation was associated with retinal thinning in the equatorial and pre-equatorial region, while foveal retinal thickness was mostly unaffected by axial length. It suggests that axial elongation takes place predominantly in the equatorial and pre-equatorial region of the eye.
EVALuna2:21295

Retinal vascular resistance in arterial hypertension - Kannenkeril, Dennis; Harazny, Joanna M.; Bosch, Agnes; Ott, Christian; Michelson, Georg; Schmieder, Roland; Friedrich, Stefanie (Blood Pressure, 2017)
Retinal microcirculation represents an easily accessible, non-invasive, in-vivo possibility to assess early microvascular changes. In addition to the assessment of functional (e.g. retinal capillary flow, RCF) and retinal arteriolar structural parameters (e.g. wall-to-lumen-ratio, WLR) we now suggest a new parameter reflecting the resistance in small retinal arterioles (RVR).In 45 normotensive (NT) subjects and 123 patients with hypertension stage 1 (HT) we assessed RCF, WLR, arteriolar diameter, lumen diameter and wall cross section area in the retinal circulation by using scanning laser Doppler flowmetry (SLDF). Mean arterial pressure (MAP) was measured immediately before the SLDF measurement and retinal vascular resistance was calculated (RVR = MAP/RCF). In a separate study the test-retest reliability was determined in 6 volunteers from our clinical staff by assessing RVR three times within six weeks.The analysis of the volunteers revealed a coefficient of variation for RVR of 7.75 ± 2.11% and Cronbach´s alpha was 0.90. WLR, a marker of vascular remodeling did not differ between NT and HT. In contrast, RCF and inner diameter of the retinal arterioles (ID) were significantly lower (RCF: p = .045 and ID: p = .001) in the HT group than in the NT group and RVR was significantly higher in the HT group than in the NT group (p < .001). In both groups we found no correlation of RVR with age, but a significant correlation of RVR with WLR (NT: r = 0.34, p = .006; HT: r = 0.25, p = .01), indicating that the RVR reflects vascular remodeling in the retinal circulation.Our data showed an increased retinal vascular resistance in hypertensive patients compared to non-hypertensive patients prior to the occurrence of structural retinal vascular remodeling. The correlation between RVR and WLR indicates that RVR is a reliable, non-invasive and early-sensitive marker of vascular remodeling in early hypertension.
EVALuna2:4030

Retinal vessel loss indicates disability and grey matter atrophy in patients with relapsing remitting multiple sclerosis - Romahn, E. F.; Bussas, M.; Grahl, S.; Noll, C.; Wicklein, R.; Aly, L.; Berthele, A.; Hosari, Sami; Mardin, Christian Y.; Kirschke, J. S.; Zimmer, C.; Korn, T.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-03

Revision after filtration surgery - Juenemann, A. G. M.; Rejdak, R.; Hohberger, B. (Ophthalmologe, 2016)
In contrast to all other glaucoma surgeries, filtration surgery is associated with biomicroscopically visible wound healing, which enables the surgeon to perform revision surgeries if necessary.The aim of this review is to provide general considerations and to give a structured overview about bleb revisions after trabeculectomy.The different revision techniques are explained in detail and in the context of perioperative management.Preoperative preparation and modifications of the surgical techniques reduce the incidence of postoperative revisions. The site of the fibrosis defines the revision technique (bleb needling, needle revision, bleb revision with reopening). The increased percolation rate of aqueous humor in postoperative hypotony contributes to fibrosis and may lead to maculopathy, choroidal effusion, and suprachoroidal hemorrhage.Discontinuing administration of local medication and pretreatment with steroids without preservative for at least one week prior to surgery increase surgical success of trabeculectomy and reduce the incidence of postoperative revisions. Postoperative management after filtration surgery should be performed after consulting the surgeon. The primary endpoint of trabeculectomy is an intraocular pressure between 8 and 12 mm Hg without local antiglaucomatous medication. In postoperative hypotony revisions should be done earlier and based on the pathological findings.
EVALuna2:21325

Risk factors for ocular hypotony after XEN Gel Stent implantation - Galimi, Maria E.; Weller, Julia; Kruse, Friedrich; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: To investigate the incidence of postoperative hypotony, and risk factors for the development of hypotony in eyes who had undergone XEN Gel Stent implantation. Methods: In this retrospective, single-centre case series, medical records of 170 consecutive eyes who had undergone XEN Gel Stent implantation with or without simultaneous phacoemulsification for primary or secondary open angle glaucoma were analysed. Primary outcome parameters were the incidence of postoperative hypotony and potential risk factors for its development, and secondary parameters were pre- and postoperative visual acuity, intraocular pressure (IOP), and number of IOP-lowering eye drops. Results: Postoperative hypotony ≤ 6 mmHg occurred in 57% of eyes. Hypotony was without complications in 70.1%, 13.4% had transient complications with spontaneous resolution, and 16.5% had complications requiring treatment. Mean visual acuity logMAR before surgery accounted for 0.47 ± 0.46 in all eyes and 0.47 ± 0.48 at the 4-week visit. There was no significant difference of BCVA in the group of eyes with and without postoperative hypotony before and after surgery. The mean IOP before surgery was 24.6 ± 8.4 mmHg and decreased significantly to 18.4 ± 10.2 after 4 weeks. Eyes with an axial length over 24.3 mm had a threefold increased risk for postoperative hypotony (OR 3.226, 95% confidence interval 1.121–9.279). This risk was decreased in eyes with simultaneous cataract surgery (OR 0.483, 95% confidence interval 0.258–0.903). Conclusion: In our sample, postoperative hypotony was a common complication after XEN Gel Stent implantation, but serious, persistent complications were rare. A longer axial length predisposes the eye for the development of hypotony.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-10-21
Keywords: Glaucoma; Hypotony; Minimal invasive glaucoma surgery (MIGS); XEN Gel Stent

RNA-seq and pathway analysis of ocular tissues in PEX patients and healthy subjects - Pasutto, Francesca; Zenkel, Matthias; Berner, Daniel; Uebe, Steffen; Ekici, Arif Bülent; Kruse, Friedrich; Reis, André; Schlötzer-Schrehardt, Ursula (2018)
EVALuna2:34745

RNA-Seq–based transcriptome analysis of corneal endothelial cells derived from patients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Tokuda, Yuichi; Nakano, Masakazu; Komori, Yuya; Hanada, Naoya; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Tashiro, Kei; Koizumi, Noriko; Okumura, Naoki (Scientific Reports, 2023)
Fuchs endothelial corneal dystrophy (FECD) is the most common inherited corneal disease. Fibrillar focal excrescences called guttae and corneal edema due to corneal endothelial cell death result in progressive vision loss. Multiple genetic variants have been reported, but the pathogenesis of FECD is not fully understood. In this study, we used RNA-Seq to analyze differential gene expression in the corneal endothelium obtained from patients with FECD. Differential expression analysis of transcriptomic profiles revealed that expression of 2366 genes (1092 upregulated and 1274 downregulated genes) was significantly altered in the corneal endothelium of patients with FECD compared to healthy subjects. Gene ontology analysis demonstrated an enrichment of genes involved in extracellular matrix (ECM) organization, response to oxidative stress, and apoptotic signaling. Several pathway analyses consistently indicated the dysregulation of ECM-associated pathways. Our differential gene expression findings support the previously proposed underlying mechanisms, including oxidative stress and apoptosis of endothelial cells, as well as the phenotypic clinical FECD hallmark of ECM deposits. Further investigation focusing on differentially expressed genes related to these pathways might be beneficial for elucidating mechanisms and developing novel therapies.
CRIS-Team Scopus Importer:2023-06-30

RNA-Seq based transcriptome analysis of corneal endothelial cells derived from the patients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Okumura, Naoki; Komori, Yuya; Hanada, Naoya; Tokuda, Yuichi; Nakano, Masakazu; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Robust Vessel Segmentation in Fundus Images - Budai, Attila; Bock, Rüdiger; Maier, Andreas; Hornegger, Joachim; Michelson, Georg (International Journal of Biomedical Imaging, 2013)
One of the most common modalities to examine the human eye is the eye-fundus photograph. The evaluation of fundus photographs is carried out by medical experts during time-consuming visual inspection. Our aim is to accelerate this process using computer aided diagnosis. As a first step, it is necessary to segment structures in the images for tissue differentiation. As the eye is the only organ, where the vasculature can be imaged in an in vivo and noninterventional way without using expensive scanners, the vessel tree is one of the most interesting and important structures to analyze. The quality and resolution of fundus images are rapidly increasing. Thus, segmentation methods need to be adapted to the new challenges of high resolutions. In this paper, we present a method to reduce calculation time, achieve high accuracy, and increase sensitivity compared to the original Frangi method. This method contains approaches to avoid potential problems like specular reflexes of thick vessels. The proposed method is evaluated using the STARE and DRIVE databases and we propose a new high resolution fundus database to compare it to the state-of-the-art algorithms. The results show an average accuracy above 94% and low computational needs. This outperforms state-of-the-art methods. © 2013 A. Budai et al.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD5.robust

Rod- and cone-driven responses in mice expressing human L-cone pigment - Tsai, Tina I.; Atorf, Jenny; Neitz, Maureen; Neitz, Jay; Kremers, Jan (Journal of Neurophysiology, 2015)
The mouse is commonly used for studying retinal processing, primarily because it is amenable to genetic manipulation. To accurately study photoreceptor driven signals in the healthy and diseased retina, it is of great importance to isolate the responses of single photoreceptor types. This is not easily achieved in mice because of the strong overlap of rod and M-cone absorption spectra (i.e., maxima at 498 and 508 nm, respectively). With a newly developed mouse model (Opn1lw(LIAIS)) expressing a variant of the human L-cone pigment (561 nm) instead of the mouse M-opsin, the absorption spectra are substantially separated, allowing retinal physiology to be studied using silent substitution stimuli. Unlike conventional chromatic isolation methods, this spectral compensation approach can isolate single photoreceptor subtypes without changing the retinal adaptation. We measured flicker electroretinograms in these mutants under ketamine-xylazine sedation with double silent substitution (silent S-cone and either rod or M/L-cones) and obtained robust responses for both rods and (L-)cones. Small signals were yielded in wild-type mice, whereas heterozygotes exhibited responses that were generally intermediate to both. Fundamental response amplitudes and phase behaviors (as a function of temporal frequency) in all genotypes were largely similar. Surprisingly, isolated (L-)cone and rod response properties in the mutant strain were alike. Thus the LIAIS mouse warrants a more comprehensive in vivo assessment of photoreceptor subtype-specific physiology, because it overcomes the hindrance of overlapping spectral sensitivities present in the normal mouse.
EVALuna2:21228

Rod and S-cone driven ERG signals at high retinal illuminances - Kremers, Jan; Czop, Dariusz; Link, Barbara (Documenta Ophthalmologica, 2009)
The purpose of the present study was to investigate whether L- and M-cone driven responses can be influenced by concomitant modulation in the rods or the S-cones. In addition, it was studied whether a change in the state of adaptation in L- or M-cones can have a different influence on ERG data when simultaneously the mean number of photoisomerizations in either rods or S-cones is altered. It was found that rods and/or S-cones cannot be neglected when measuring L- or M-cone driven ERGs.
Keywords: Electroretinogram; Rod driven signals; S-cone driven signals; Temporal frequency; Retinal illuminance

Rod Electroretinograms Elicited by Silent Substitution Stimuli from the Light-Adapted Human Eye - Maguire, John; Parry, Neil R. A.; Kremers, Jan; Kommanapalli, Deepika; Murray, Ian J.; Mckeefry, Declan J. (Translational Vision Science & Technology, 2016)
To demonstrate that silent substitution stimuli can be used to generate electroretinograms (ERGs) that effectively isolate rod photoreceptor function in humans without the need for dark adaptation, and that this approach constitutes a viable alternative to current clinical standard testing protocols.Rod-isolating and non-isolating sinusoidal flicker stimuli were generated on a 4 primary light-emitting diode (LED) Ganzfeld stimulator to elicit ERGs from participants with normal and compromised rod function who had not undergone dark-adaptation. Responses were subjected to Fourier analysis, and the amplitude and phase of the fundamental were used to examine temporal frequency and retinal illuminance response characteristics.Electroretinograms elicited by rod-isolating silent substitution stimuli exhibit low-pass temporal frequency response characteristics with an upper response limit of 30 Hz. Responses are optimal between 5 and 8 Hz and between 10 and 100 photopic trolands (Td). There is a significant correlation between the response amplitudes obtained with the silent substitution method and current standard clinical protocols. Analysis of signal-to-noise ratios reveals significant differences between subjects with normal and compromised rod function.Silent substitution provides an effective method for the isolation of human rod photoreceptor function in subjects with normal as well as compromised rod function when stimuli are used within appropriate parameter ranges.This method of generating rod-mediated ERGs can be achieved without time-consuming periods of dark adaptation, provides improved isolation of rod- from cone-based activity, and will lead to the development of faster clinical electrophysiologic testing protocols with improved selectivity.
EVALuna2:21318

Rod photoreceptor ribbon synapses in DBA/2J mice show progressive age-related structural changes. - Fuchs, Michaela; Scholz, Michael; Sendelbeck, Anna; Atorf, Jenny; Schlegel, Christine Julie; Enz, Ralf; Brandstätter, Johann Helmut (PLoS ONE, 2012)
The DBA/2J mouse is a commonly used animal model in glaucoma research. The eyes of DBA/2J mice show severe age-related changes that finally lead to the degeneration of retinal ganglion cells and the optic nerve. Recent electroretinogram studies identified functional deficits, which suggest that also photoreceptor cells are involved in the pathological processes occurring in the DBA/2J mouse retina. In a comparative study, we examined anatomical and molecular changes in the retinae of DBA/2J and C57BL/6 control mice with light and electron microscopy and with PCR analyses. In the retina of the DBA/2J mouse, we found a thinning of the outer plexiform layer, the first synaptic layer in the transfer of visual signals, and age-dependent and progressive degenerative structural changes at rod photoreceptor ribbon synapses. The structural ribbon changes represent a photoreceptor synaptic phenotype that has not yet been described in this animal model of secondary angle-closure glaucoma. Furthermore, genes of the classical complement cascade were upregulated in the photoreceptor cells of aging DBA/2J mice, suggesting a putative link between ribbon synapse degradation and the innate immune system. © 2012 Fuchs et al.
UnivIS-Import:2015-04-14:Pub.2012.med.IB.profes_1.rodpho

Rod versus cone driven ERGs at different stimulus sizes - Aher, Avinash; Mckeefry, Declan J.; Parry, Neil Robert Alan; Maguire, John; Murray, Ian J.; Tsai, Tina I.; Huchzermeyer, Cord; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2017)

Rod- versus cone-driven ERGs at different stimulus sizes in normal subjects and retinitis pigmentosa patients - Aher, Avinash; Mckeefry, Declan J.; Parry, Neil R. A.; Maguire, John; Murray, I. J.; Tsai, Tina I.; Huchzermeyer, Cord; Kremers, Jan (Documenta Ophthalmologica, 2018)
Purpose To study how rod- and cone-driven responses depend on stimulus size in normal subjects and patients with retinitis pigmentosa (RP), and to show that comparisons between responses to full-field (FF) and smaller stimuli can be useful in diagnosing and monitoring disorders of the peripheral retina without the need for lengthy dark adaptation periods.Method The triple silent substitution technique was used to isolate L-cone-, M-cone- and rod-driven ERGs with 19, 18 and 33% photoreceptor contrasts, respectively, under identical mean luminance conditions. Experiments were conducted on five normal subjects and three RP patients. ERGs on control subjects were recorded at nine different temporal frequencies (between 2 and 60 Hz) for five different stimulus sizes: FF, 70A degrees, 60A degrees, 50A degrees and 40A degrees diameter circular stimuli. Experiments on RP patients involved rod- and L-cone-driven ERG measurements with FF and 40A degrees stimuli at 8 and 48 Hz. Response amplitudes were defined as those of the first harmonic component after Fourier analysis.Results In normal subjects, rod-driven responses displayed a fundamentally different behavior than cone-driven responses, particularly at low temporal frequencies. At low and intermediate temporal frequencies (<= 12 Hz), rod-driven signals increased by a factor of about four when measured with smaller stimuli. In contrast, L- and M-cone-driven responses in this frequency region did not change substantially with stimulus size. At high temporal frequencies (>= 24 Hz), both rod- and cone-driven response amplitudes decreased with decreasing stimulus size. Signals obtained from rod-isolating stimuli under these conditions are likely artefactual. Interestingly, in RP patients, both rod-driven and L-cone-driven ERGs were similar using 40A degrees and FF stimuli.Conclusion The increased responses with smaller stimuli in normal subjects to rod-isolating stimuli indicate that a fundamentally different mechanism drives the ERGs in comparison with the cone-driven responses. We propose that the increased responses are caused by stray light stimulating the peripheral retina, thereby allowing peripheral rod-driven function to be studied using the triple silent substitution technique at photopic luminances. The method is effective in studying impaired peripheral rod- and cone- function in RP patients.
Keywords: Rods; Cones; Stimulus size; Electroretinogram; Retinitis pigmentosa

Salt intake determines retinal arteriolar structure in treatment resistant hypertension independent of blood pressure - Raff, Ulrike; Harazny, Joanna M.; Titze, Stephanie I.; Schmidt, Bernhard Magnus Wilhelm; Michelson, Georg; Schmieder, Roland (Atherosclerosis, 2012)
Patients with treatment resistant hypertension are at increased risk of developing cardiovascular end organ damage. The role of sodium in end organ damage is gaining interest and an independent association of sodium and cardiovascular morbidity and mortality has been described.In an observational study including 40 patients with treatment resistant hypertension, we analysed retinal arteriolar structure in vivo as a determinant of remodelling of small resistant vessels (wall/lumen ratio, wall thickness, wall cross section area) using scanning laser Doppler flowmetry and automatic full-field perfusion imaging analysis. Urinary sodium excretion was determined by 24h urine sample and, in parallel 24h ambulatory blood pressure was measured. We analysed the association of the retinal arterial structure with urinary sodium excretion and blood pressure.Wall to lumen ratio, wall thickness and wall cross section area were strongly associated with urinary sodium excretion but not with 24h blood pressure. In a multiple regression analysis including urinary sodium excretion, BMI, age and 24h blood pressure, urinary sodium excretion emerged as the only independent determinant of wall thickness (?=0.432, p=0.01), and wall cross section area (?=0.439, p=0.008).Our results clearly demonstrate that salt intake influences the structure of retinal arterioles independent of blood pressure in treatment resistant hypertension. Considering the morphologic relation of retinal arteriolar and cerebral vascular structure these results might prove to have important implications on risk stratification in patients with treatment resistant hypertension.
EVALuna2:3574

SARS-CoV-2: Impact on, Risk Assessment and Countermeasures in German Eye Banks - Trigaux, Celine; Salla, Sabine; Schroeter, Jan; Tourtas, Theofilos; Thomasen, Henning; Maier, Philip; Hellwinkel, Olaf J. C.; Wittmershaus, Ilka; Merz, Patrick R.; Seitz, Berthold; Noelle, Bernhard; Schrage, Norbert; et al. (Current Eye Research, 2020)
Introduction: Since the beginning of the COVID-19 pandemic there has been some debate regarding the risk of transmission through tissue transplantation and tissue banking processes. Aim of the study: To analyze the changes that SARS-CoV-2 has caused regarding the harvesting of corneal donor tissue and eye bank activities in Germany. Methods: A questionnaire was provided to 26 eye banks in Germany, consisting of questions about adaptations made in the screening of potential donors and the harvesting of corneal tissue following the pandemic spread of SARS-CoV-2. Results: Eighteen eye banks actively reduced recruitment of donors and two banks ceased all activity. Additional diagnostic screening was performed in eight banks, using conjunctival swabs and/or nasopharyngeal swabs. In six eye banks, additional protective measures, such as FFP2 masks and/or facial shields, were implemented. Overall, a mean reduction in the number of obtained donor tissues of 17% was observed. Discussion: Conjunctival and/or nasopharyngeal swabs of donors have been implemented by a minority. Reasons for not performing additional tests may be moderate sensitivity and lack of validation for postmortem use of RT-PCR testing. Also, the hazard of SARS-CoV-2 entering the corneal donor pool with subsequent transmission might be perceived as theoretical. Face shields provide a sufficient barrier against splash and splatter contamination but may be insufficient against aerosols. Additional face masks would provide support against aerosols, but it remains debatable if corneal harvesting can be considered an aerosol-producing procedure. In the future we expect to see changes in current guidelines because of a surge in scientific activities to improve our understanding of the risks involved with cornea donation in the COVID-19 pandemic, and because current practice may reduce the availability of donor corneas due to new exclusion criteria while the demand remains unchanged.
CRIS-Team Scopus Importer:2020-10-16
Keywords: cornea; corona virus; COVID-19; eye banking; SARS-CoV-2; tissue banking; transplantation

Scleral cross section area and volume and axial length - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (PLoS ONE, 2014)
To examine whether the scleral cross sectional area and estimated scleral volume are associated with a longer axial length in human eyes.Histologic anterior-posterior sections running through the pupil and the optic nerve head were examined. Using a light microscope, we measured the thickness of the sclera at the limbus, ora serrata, equator, midpoint between equator and posterior pole (MPEPP), peripapillary region and posterior pole. Additionally we determined the length and the cross section area of the sclera.The histomorphometric study included 214 human globes of 214 subjects (mean age: 62.5±13.9 years) (147 eyes enucleated due to malignant choroidal melanoma or due to other non-glaucomatous reasons; 67 eyes enucleated due to secondary angle-closure glaucoma). Mean axial length was 25.1±1.8 mm (median: 24.0 mm; range: 20-35 mm). Scleral thickness measurements decreased with increasing axial length for values taken at the equator (P = 0.008; correlation coefficient r = -0.18), MPEPP (P<0.001;r:-0.47), optic nerve head border (P<0.001;r = -0.47) and posterior pole (P<0.001;r = -0.54). Scleral cross section area decreased significantly with increasing axial lengths for the regions at or behind the equator (P = 0.002;r = -0.21), at or behind the MPEPP (P = 0.001;r = -0.25), and at or behind the optic nerve head border (P = 0.001;r = -0.24). Scleral volume measurements were not significantly associated with axial length.Despite an associated increase in surface area, eyes with longer axial length do not have an increase in scleral volume. It may point against a scleral volume enlargement to play a role in the process of axial elongation.
EVALuna2:21190

Screening questionnaire for documentation of medical history and diagnostic findings in dry eye disease - Jacobi, Christina; Bellios, N.; Jacobi, A.; Kruse, Friedrich; Cursiefen, Claus (Klinische Monatsblätter für Augenheilkunde, 2011)
Keratoconjunctivitis sicca is one of the most common ocular diseases world-wide. These patients suffer from severe symptoms which lead to an extremely reduced quality of life. Dry eye syndrome constitutes a major diagnostic and therapeutic challenge to all ophthalmologists because there is often a discrepancy between objective ocular signs and subjective symptoms of the patients. Furthermore, there exist only few causal therapeutic options. The physician-patient relationship plays an outstanding role in this condition. For the treatment of moderate to severe dry eye syndrome, special dry eye clinics have proved to be extremely useful. For follow-up measurements as well as the realisation of evidence-based medicine and quality control, it is a fundamental necessity to document symptoms, signs and therapy of these patients in order to optimise therapeutic strategies. For this purpose, we have developed special forms and standardised questionnaires for the individual documentation of medical history and diagnostic findings. To objectively assess the patient's complaints we use the "ocular surface disease index" (OSDI score). Only the establishment of standardised diagnostic and therapeutic algorithms with the help of special forms and questionnaires can help in the long run to improve the treatment of these severely affected patients.
EVALuna2:21043

Secondary Reconstruction of Posttraumatic Enophthalmos: Prefabricated Implants vs Titanium Mesh - Nkenke, Emeka; Vairaktaris, Eleftherios; Spitzer, Martin; Kramer, Manuel; Stamminger, Marc; Holbach, Leonard; Knipfer, Christian; Stelzle, Florian (Archives of Facial Plastic Surgery, 2011)
Objective To compare individually prefabricated computer-assisted designed/computer-assisted manufactured (CAD/CAM) glass-bioceramic implants with nonpreformed titanium meshes for orbital floor reconstruction in secondary correction of enophthalmos. Methods In a nonrandomized, comparative, prospective cohort study, 2 groups of 10 patients received secondary correction of enophthalmos with CAD/CAM implants in one group and titanium meshes in the other. Relative enophthalmometry and exophthalmometry data were assessed preoperatively, at the end of the operation, at day 90 postoperatively, and at day 365 postoperatively. Results In both groups, the globe position improved significantly at the end of the operation (P = .005 in both groups). At day 90, there was a significant tendency toward relapse of enophthalmos in both groups (P = .005 in the CAD/CAM group and P = .008 in the titanium mesh group). However, the globe position did not change significantly between postoperative days 90 and 365 in both groups (P = .57 in the CAD/CAM group and P = .35 in the titanium mesh group). Conclusions Individually prefabricated CAD/CAM glass-bioceramic implants and nonpreformed titanium meshes produce similar results in secondary enophthalmos correction. Because of higher costs, the use of CAD/CAM implants should be confined to selected cases in secondary enophthalmos correction.
EVALuna2:21025

Selektive Stimulation der verschiedenen Fotorezeptorklassen mittels Silent Substitution bei psychophysischen und elektroretinografischen Messungen - Huchzermeyer, Cord; Kremers, Jan (Klinische Monatsblätter für Augenheilkunde, 2022)
The silent substitution technique allows creating photoreceptor- selective stimuli for psychophysical and electrophysiological tests. In contrast to other techniques, the purpose of silent substitution is not to make the targeted photoreceptor type more sensitive in comparison to the other types, but to make the stimulus invisible ("silent") to the other photoreceptor types. This allows selectivity independent of the retinal state of adaptation and enables comparing photoreceptor types under identical conditions. The foundations of these techniques will be explained in this paper. Furthermore, the importance of postreceptoral processing for the perception of photoreceptor-selective stimuli is discussed here. Although this technique is currently only available in specialized vision science labs, there is an enormous potential for clinical application.
CRIS-Team Scopus Importer:2022-12-23
Keywords: electrophysiology; glaucoma; psychophysics; retina

Self-Complementary Adeno-Associated Virus Vectors Improve Transduction Efficiency of Corneal Endothelial Cells - Gruenert, Anja K.; Czugala, Marta; Mueller, Chris; Schmeer, Marco; Schleef, Martin; Kruse, Friedrich; Fuchsluger, Thomas (PLoS ONE, 2016)
Transplantation of a donor cornea to restore vision is the most frequently performed transplantation in the world. Corneal endothelial cells (CEC) are crucial for the outcome of a graft as they maintain corneal transparency and avoid graft failure due to corneal opaqueness. Given the characteristic of being a monolayer and in direct contact with culture medium during cultivation in eye banks, CEC are specifically suitable for gene therapeutic approaches prior to transplantation. Recombinant adeno-associated virus 2 (rAAV2) vectors represent a promising tool for gene therapy of CEC. However, high vector titers are needed to achieve sufficient gene expression. One of the rate-limiting steps for transgene expression is the conversion of single-stranded (ss-) DNA vector genome into double-stranded (ds-) DNA. This step can be bypassed by using self-complementary (sc-) AAV2 vectors. Aim of this study was to compare for the first time transduction efficiencies of ss- and scAAV2 vectors in CEC. For this purpose AAV2 vectors containing enhanced green fluorescent protein (GFP) as transgene were used. Both in CEC and in donor corneas, transduction with scAAV2 resulted in significantly higher transgene expression compared to ssAAV2. The difference in transduction efficiency decreased with increasing vector titer. In most cases, only half the vector titer of scAAV2 was required for equal or higher gene expression rates than those of ssAAV2. In human donor corneas, GFP expression was 64.7±11.3% (scAAV) and 38.0±8.6% (ssAAV) (p<0.001), respectively. Furthermore, transduced cells maintained their viability and showed regular morphology. Working together with regulatory authorities, a translation of AAV2 vector-mediated gene therapy to achieve a temporary protection of corneal allografts during cultivation and transplantation could therefore become more realistic.
EVALuna2:21299

Self-inflicted laser-induced maculopathy in adolescence - Hohberger, B.; Bergua, A. (Ophthalmologe, 2016)
Reports of laser-induced ocular injuries have become more frequent in recent years, especially due to high-energy laser pointers. The article presents for the first time in the German literature a case of self-inflicted laser-induced maculopathy in an adolescent. In addition to the clinical findings, the results of funduscopy and spectral domain optical coherence tomography (SD-OCT) follow-up are presented.
EVALuna2:21314

Serum levels of olanzapine are associated with acute cognitive effects in bipolar disorder - Shoshina, Irina I.; Almeida, Natalia L.; Oliveira, Milena E.C.; Trombetta, Bianca N.T.; Silva, Gabriella M.; Fars, Julien; Santos, Natanael A.; Fernandes, Thiago P. (Psychiatry Research, 2022)
Bipolar (BPD) patients have deficits in cognition, but there are still controversies about the effects of some medications on their cognitive performance. Here, we investigated the relationship between cognition in terms of executive functions, memory, and attention in both first-episode medication-naive BPD patients and BPD patients taking olanzapine. Forty-one healthy controls, 40 unmedicated drug-naive BPD patients, and 34 BPD patients who took only olanzapine were recruited for the study. Cognitive performance was assessed using the Flanker test, Stroop test, and Corsi-block test. Bayesian multivariate regression analysis was run considering maximum robustness to avoid bias and to predict the outcomes. Our results revealed that unmedicated medication-naive BPD patients performed worse than healthy controls and the olanzapine group in some tasks. Additionally, BPD patients who took olanzapine had better cognitive performance than healthy controls and unmedicated BPD patients. The acute cognitive effects were predicted by olanzapine dosage and serum levels (i.e., large effects). The potential pro-cognitive effects of olanzapine in BPD patients should be carefully interpreted by considering various other clinical variables. We expect that our findings will contribute to further research in this area, with the goal of helping other researchers, patients, and the population.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Bipolar disorder; Cognition; Cognitive tests; Medication; Olanzapine; Serum levels

Serum Selenium Levels in Glaucoma: A Pilot Study - Lucio, Marianna; Fick, Alexander; Michalke, Bernhard; Lämmer, Robert; Hosari, Sami; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Trace elements are assumed to be involved in glaucoma pathogenesis via changes in oxidative stress. Especially serum selenium (Se) has been linked to this neurodegenerative disease. Serum Se levels differ between countries due to nutrition and ethnicity. It was the aim of the present study to investigate serum Se levels in primary open-angle glaucoma (POAG) patients and controls in Germany and to consider potential age and gender effects. Material and Methods The Se concentration of 39 serum samples (22 patients with POAG, 17 controls) were analyzed by inductively coupled plasma-sector field mass spectrometry (ICP-sf-MS) in high resolution mode. Covariance and percentile regression were analyzed. Age and gender were defined as confounding factors and their different trends were investigated. Moreover, age was examined across different quantiles of Se levels. Results Total serum least-squares means (LS-means) Se levels were 132.02 μg/L (controls) and 134.86 μg/L (POAG). Total serum Se levels did not differ between the study groups (p > 0.05). Significant age and gender effects of serum Se were observed. Quantile analysis showed that the 1st serum Se quantile decreased with increasing age in POAG patients in contrast to controls. The odds ratios of the 1st serum Se were 1.3 (with 2nd quantile) and 1.3 (with 3rd quantile), respectively. Conclusion The serum Se level of the German cohort was almost half of those of the published US cohort (glaucoma 209.11 ng/mL; control 194.45 ng/mL). Age and gender effects were observed; the serum Se level increased with age in women (controls and POAG), however, Se levels decreased with age in men (controls and POAG).
CRIS-Team Scopus Importer:2021-03-05
Keywords: age; gender; glaucoma; ICP-sf-MS; selenium; trace element

Severe chronic blepharitis and scarring ectropion associated with discoid lupus erythematosus - Kopsachilis, Nikolaos; Tsaousis, Konstantinos T.; Tourtas, Theofilos; Tsinopoulos, Ioannis T. (Clinical and Experimental Optometry, 2013)
Discoid lupus erythematosus is a common form of chronic cutaneous lupus erythematosus, an autoimmune inflammatory disease that affects most of the human organs, including the skin, kidneys, joints, heart and lungs. We describe a 45-year-old Caucasian woman with a 21-year history of eyelid redness and irritation. She had been treated with antibiotics, steroids and eyelid hygiene, a therapy that resulted to brief periods of relief of symptoms. In the last 12 months, her symptoms seemed to have exacerbated, despite the administration of a local therapy. Following biopsy, a diagnosis of discoid lupus erythematosus was confirmed and the patient was placed on a systemic therapy with hydroxychloroquine. The eyelid inflammation decreased but severe scarring of the marginal eyelids persisted, resulting in cicatricial ectropion.
EVALuna2:21195

Short-term fluctuation of intraocular pressure is higher in patients with pseudoexfoliation syndrome despite similar mean intraocular pressure: a retrospective case-control study - Huchzermeyer, Cord; Horn, Folkert; Lämmer, Robert; Mardin, Christian Y.; Junemann, Anselm G. M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
Higher levels of short-term fluctuation of intraocular pressure (IOP) are characteristic of pseudoexfoliation syndrome (PEX). However, it is not known whether they are just a side effect of the higher mean intraocular pressure (IOP) or an independent feature. The purpose of this study was to compare short-term fluctuation of IOP between eyes with PEX and control eyes that were matched as closely as possible for mean IOP.In this retrospective case-control study, all patients with confirmed PEX were identified from the database of the Erlangen Glaucoma Registry. From the same database, matched control eyes with similar treatment, age, glaucoma stage, and mean IOP were identified. For each patient, data from multiple extended diurnal IOP profiles were available.Seventy-eight eyes were included in the study (39 with PEX and 39 matched control eyes). Although a very close match was achieved, a small but statistically significant difference in mean IOP was still present, but this did not seem to explain the differences in IOP fluctuation levels. Eyes with PEX had significantly higher short-term IOP fluctuations (SD of IOP and range of IOP).The higher levels of short-term fluctuation in IOP appear to be an independent feature of PEX and not merely a secondary effect of the higher mean IOP. We suggest that this may have practical implications, even if IOP fluctuation levels should not prove to be an independent risk factor for development/progression of glaucoma, because more frequent measurements are needed in these patients to obtain good estimates of mean IOP and changes in IOP under treatment.
EVALuna2:21176

Significance of Homocysteine in Glaucoma - Juenemann, Anselm; Rejdak, Robert; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2018)
Endothelial dysfunction and vascular dysregulation play a role in the multifactorial pathogenesis of glaucomatous optic nerve atrophy. Hyperhomocysteinemia is a risk factor for endothelial dysfunction and is associated with primary open-angle glaucoma as well as secondary open-angle glaucoma in the pseudoexfoliation syndrome. This paper reviews the literature on the association between homocysteine metabolism and glaucomatous disease and explains the possible role of hyperhomocysteinemia in the pathogenesis and progression of glaucoma. We discuss the role of exogenous modifiable risk factors for the prevention and therapy of glaucoma, as well as modification of these factors by changes in life style, such as weight reduction, changes in nutrition and physical activity. The roles of homocysteine in regulating the extracellular matrix, vasotoxicity, neurodegeneration, and epigenetics are explained. Prevention and therapy of glaucoma by regulation of homocysteine levels are discussed.
EVALuna2:34848

Silencing of pro-apoptotic proteins as anti-apoptotic therapy for corneal endothelium - Fuchsluger, Thomas Armin; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Simultaneous amniotic membrane patch in high-risk keratoplasty - Seitz, Berthold; Das, Sujata; Sauer, Rolf; Hofmann-Rummelt, Carmen; Beckmann, Matthias; Kruse, Friedrich (Cornea, 2011)
To analyze the short- and intermediate-term results of simultaneous transplantation of amniotic membrane with high-risk keratoplasty.Between January 2002 and February 2004, a simultaneous amniotic membrane patch was transplanted with penetrating keratoplasty in 16 eyes of 16 patients. In 13 eyes, a soft contact lens was applied afterward. Corneal perforation was present in 10 of 14 eyes with emergency keratoplasty. Five patients received systemic immunosuppressive medication for 4-6 months after penetrating keratoplasty.The amniotic membrane patch fell off after 8 ± 3 (range: 4-14) days without residual tissue except in 1 case. In 15 of 16 eyes, the epithelium was completely closed after 10 ± 8 (range: 4-30) days. In 3 eyes, recurrence of the epithelial defect occurred after 3-6 months. During a follow-up period of 18 ± 6 months, 13 of 16 corneal grafts were clear.Simultaneous amniotic membrane transplantation and penetrating keratoplasty may improve the prognosis of corneal graft in eyes with risk of epithelial healing problems.
EVALuna2:17178

Simultaneous chromatic and luminance human electroretinogram responses - Parry, Neil R. A.; Murray, Ian J.; Panorgias, Athanasios; Mckeefry, Declan J.; Lee, Barry B.; Kremers, Jan (The Journal of Physiology, 2012)
The parallel processing of information forms an important organisational principle of the primate visual system. Here we describe experiments which use a novel chromatic-achromatic temporal compound stimulus to simultaneously identify colour and luminance specific signals in the human electroretinogram (ERG). Luminance and chromatic components are separated in the stimulus; the luminance modulation has twice the temporal frequency of the chromatic modulation. ERGs were recorded from four trichromatic and two dichromatic subjects (1 deuteranope and 1 protanope). At isoluminance, the fundamental (first harmonic) response was elicited by the chromatic component in the stimulus. The trichromatic ERGs possessed low-pass temporal tuning characteristics, reflecting the activity of parvocellular post-receptoral mechanisms. There was very little first harmonic response in the dichromats' ERGs. The second harmonic response was elicited by the luminance modulation in the compound stimulus and showed, in all subjects, band-pass temporal tuning characteristic of magnocellular activity. Thus it is possible to concurrently elicit ERG responses from the human retina which reflect processing in both chromatic and luminance pathways. As well as providing a clear demonstration of the parallel nature of chromatic and luminance processing in the human retina, the differences that exist between ERGs from trichromatic and dichromatic subjects point to the existence of interactions between afferent post-receptoral pathways that are in operation from the earliest stages of visual processing.
EVALuna2:21088

Single opsin driven white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in Neuroscience, 2023)
Purpose: Electroretinograms elicited by photopigment isolating white noise stimuli (wnERGs) in mice were measured. The dependency of rod- and cone-opsin-driven wnERGs on mean luminance was studied. Methods: Temporal white noise stimuli (containing all frequencies up to 20 Hz, equal amplitudes, random phases) that modulated either rhodopsin, S-opsin or L*-opsin, using the double silent substitution technique, were used to record wnERGs in mice expressing a human L*-opsin instead of the native murine M-opsin. Responses were recorded at 4 mean luminances (MLs). Impulse response functions (IRFs) were obtained by cross-correlating the wnERG recordings with the corresponding modulation of the photopigment excitation elicited by the stimulus. So-called modulation transfer functions (MTFs) were obtained by performing a Fourier transform on the IRFs. Potentials of two repeated wnERG recordings at corresponding time points were plotted against each other. The correlation coefficient (r2repr) of the linear regression through these data was used to quantify reproducibility. Another correlation coefficient (r2ML) was used to quantify the correlations of the wnERGs obtained at different MLs with those at the highest (for cone isolating stimuli) or lowest (for rod isolating stimuli) ML. Results: IRFs showed an initial negative (a-wave like) trough N1 and a subsequent positive (b-wave like) peak P1. No oscillatory potential-like components were observed. At 0.4 and 1.0 log cd/m2 ML robust L*- and S-opsin-driven IRFs were obtained that displayed similar latencies and dependencies on ML. L*-opsin-driven IRFs were 2.5–3 times larger than S-opsin-driven IRFs. Rhodopsin-driven IRFs were observed at −0.8 and − 0.2 log cd/m2 and decreased in amplitude with increasing ML. They displayed an additional pronounced late negativity (N2), which may be a correlate of retinal ganglion cell activity. R2repr and r2ML values increased for cones with increasing ML whereas they decreased for rods. For rhodopsin-driven MTFs at low MLs and L*-opsin-driven MTFs at high MLs amplitudes decreased with increasing frequency, with much faster decreasing amplitudes for rhodopsin. A delay was calculated from MTF phases showing larger delays for rhodopsin- vs. low delays for L*-opsin-driven responses. Conclusion: Opsin-isolating wnERGs in mice show characteristics of different retinal cell types and their connected pathways.
CRIS-Team Scopus Importer:2023-08-25
Keywords: electroretinography (ERG); mouse retina; photopigment; silent substitution; temporal white noise (TWN)

Solitary sarcoid granuloma of the iris mimicking tuberculosis: a case report - Rejdak, Robert; Pogorelov, Pavel; Mardin, Christian Y.; Szkaradek, Malgorzata; Jünemann, Anselm (Journal of Ophthalmology, 2014)
Introduction. We report a case of a male patient presented with sarcoid lesions of the iris and conjunctiva, mimicking tuberculosis due to epithelioid cell granulomas with small central necrosis in conjunctival biopsy. Patient. A 25-year-old man was referred to our department for further management of an "iris tumor with iridocyclitis" in his right eye. Initial examination showed an isolated vascular tumor of the iris and ciliary body with anterior uveitis and mutton-fat keratic precipitates, suggesting the diagnosis of a granulomatous disease. Conjunctival biopsy revealed granulomatous epithelioid cell inflammation with small central necrosis without acid-fast bacilli. Extensive systemic examination, including bronchoscopy and transbronchial biopsy, provided the diagnosis of sarcoidosis stage 2 with pulmonary involvement, thus ruling out tuberculosis. Systemic and local steroid therapy was initiated, leading to complete recovery of our patient with complete disappearance of the iris lesion and improvement of the pulmonary function. Conclusion. Although noncaseating epithelioid cell granulomas are typical for sarcoidosis, small central necrosis can be found in some granulomas, leading to presumption of tuberculosis. Extensive systemic checkup in cooperation with other specialists is essential to confirm the correct diagnosis and to initiate the appropriate therapy.
EVALuna2:21186

Spatial distributions of on- and off-responses determined with the multifocal ERG - Rodrigues, Anderson R.; Da Silva Filho, Manoel; Silveira, Luiz Carlos L.; Kremers, Jan (Documenta Ophthalmologica, 2010)
We studied the contribution of retinal on- and off-mechanisms in the multifocal electroretinogram (mfERG) by measuring responses to sawtooth stimuli. Six healthy subjects participated in this study. Rapid-on and rapid-off sawtooth stimuli with a period of 427 ms were presented in a multifocal pattern composed of 19 hexagons. The stimuli were interleaved with a blank field of the mean luminance and chromaticity. On- and off-responses were added to extract response asymmetries. The amplitudes of on-, off-, and added-responses were determined for different eccentricities relative to a signal baseline that was defined as the average of the electrical level recorded in two different time windows in which no responses were present. Measurements were repeated with eight different stimulus stretch factors to account for changes in retinal cell density as a function of eccentricity. The amplitudes of all ERG components decreased with increasing eccentricity for all stretch factors. For stretch factors between 0 and 20, responses to the central and immediately adjacent hexagons were large in amplitude. For more peripheral hexagons, the responses were very small or absent. Three components were identified in the on-responses (N20(on), P46(on) and N100(on)). In the off-responses, we found one positive (P20(off)) and one negative (N90(off)) component, whereas in the addition, three components (N20(add), P46(add) and N100(add)) could be observed. The N20(on) and P46(on) amplitudes decreased less steeply with eccentricity than the N100(on) amplitude, whilst the P20(off) and N90(off) amplitudes exhibited a similar decrease with eccentricity. In the addition, the two negative components exhibited a similar decrease in amplitude as a function of eccentricity and decreased more steeply than the positive component. The number of stimulated cones and retinal ganglion cells was estimated from anatomical data and compared with the responses. The spatial properties of the amplitudes of N20(on), P46(on), P20(off), and N90(off) and P46(add) were similar to those of the stimulated cone numbers. The remaining components had spatial characteristics that resembled those of the retinal ganglion cells. It is proposed that the ERG asymmetries revealed in the summed responses have post-receptoral origins, some of them reflecting the activity of the ganglion cell population. The use of sawtooth stimuli provide, similar to the pattern ERG, a way to record the ERG asymmetries.
Keywords: On- and off-mechanisms; Multifocal ERG; Retinal pathways; Retinal eccentricity

Spatial Properties of Electroretinograms Elicited by High Temporal Frequency L- and M-cone Isolating Stimuli - Aher, Avinash; Jacob, Mellina M.; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Spatial properties of L- and M-cone driven incremental (On-) and decremental (Off-) electroretinograms: evidence for the involvement of multiple post-receptoral mechanisms - Tsai, Tina I.; Jacob, Mellina M.; Mckeefry, Declan; Murray, Ian J.; Parry, Neil R. A.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
An overview of electroretinogram response components to incremental and decremental steps in L- and M-cone excitation was obtained in human observers, while varying the spatial properties of the stimulus. Responses to L- and M-cone stimuli of opposite polarity resembled each other, particularly within the central 35° of the retina. All amplitudes grew as stimulus size increased; however, earlier and later components of the On- and Off-responses showed differing degrees of dependency on stimulus size. Thus, they may reflect different proportions of responses originating in parvocellular (less stimulus size-dependent) and magnocellular (more stimulus size-dependent) streams.
EVALuna2:21297

Spatial properties of L- and M-cone driven incremental (on-) and decremental (off-) electroretinograms: normal subjects Vs. glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Spatial receptive field properties of lateral geniculate cells in the owl monkey (Aotus azarae) at different contrasts: a comparative study - Kilavik, B.E.; Silveira, L. C. L.; Kremers, Jan (European Journal of Neuroscience, 2007)
Several physiological properties of owl monkey lateral geniculate nucleus (LGN) cells were studied to verify whether its nocturnal habit has an influence on the organization of its subcortical visual system. Receptive field (RF) dimensions were measured using drifting gratings and bipartite field stimuli. We found that owl monkey cells LGN have larger RFs and were on average more non-linear than those of diurnal monkeys. But, as in other anthropoids, there is an increase in RF centre size with increasing eccentricity, and there is a limited correlation between these centre sizes and retinal ganglion cell dendritic tree sizes. The influence of contrast on sizes and peak sensitivities of RF centres and surrounds and on the response phases was studied. Both the sizes and peak sensitivities of the RF centres and surrounds decrease as contrast increases. As a result, the responses to low spatial frequency stimuli saturate with increasing contrast. Estimates of contrasts at half-maximal responses confirm the presence of saturation. It was found that the magnocellular cells saturate more strongly than parvocellular cells. The response phase increases with increasing contrast. These data resemble those obtained in the common marmoset, indicating that these are basic features of the primate visual system. We conclude that during evolution and as an adaptation to a nocturnal lifestyle, cells in the owl monkey LGN display an increased spatial integration in comparison with diurnal primate species, without a change in the basic organization common to the primate subcortical visual system.
Keywords: contrast sensitivity; koniocellular; lateral geniculate nucleus; magnocellular; parvocellular; primates

Spectral characteristics of the PhNR in the full-field flash electroretinogram of normals and glaucoma patients - Kremers, Jan; Jertila, Mounira; Link, Barbara; Pangeni, Gobinda; Horn, Folkert (Documenta Ophthalmologica, 2012)
Flash electroretinogram responses were measured in normal subjects to different chromatic combinations of flashes and backgrounds. The amplitudes of the flash response components were measured at different flash strengths and could be described by a generalized Naka-Rushton function. The measurements were repeated at different background luminances to study adaptation effects. It was found that when flash strength and background luminance were expressed in photometric terms (cd s/m² and cd/m², respectively), then the responses were very similar for all chromatic combinations with the exception of the condition in which blue (peak wavelength 458 nm) was flashed upon an orange (peak wavelength 591 nm) background. We propose that in this condition, a second (possibly S-cone or rod-driven) mechanism intrudes. The negative response after the b-wave (here called "photopic negative response" or PhNR for all conditions) is thought to reflect ganglion cell activity and was also largest at this condition. Responses were measured to the 458 nm flash on 591 nm background and the reversed combination in a population of 39 normal subjects and 49 glaucoma patients. It was found that the PhNR amplitude was affected by glaucoma in all conditions. Other component parameters, reflecting responses and adaptation dynamics, were not altered. The best stimulus condition among the conditions used to separate the PhNR amplitude of normals and patients was a 1 cd s/m² 458 nm flash on a 10 cd/m² 591 nm background.
EVALuna2:21075

Split cornea transplantation for 2 recipients: a new strategy to reduce corneal tissue cost and shortage - Heindl, Ludwig M.; Riss, Stephan; Bachmann, Bjoern O.; Laaser, Kathrin; Kruse, Friedrich; Cursiefen, Claus (Ophthalmology, 2011)
To evaluate the feasibility of using a single donor cornea for 2 recipients by combining deep anterior lamellar keratoplasty (DALK) and Descemet's membrane endothelial keratoplasty (DMEK) surgeries on the same day.Single-center, nonrandomized, prospective, interventional case series.Twelve consecutive donor corneas were scheduled for split cornea transplantation combining DALK for a keratoconus patient and DMEK for a Fuchs' endothelial dystrophy patient on the same surgery day.First, a big-bubble DALK procedure was performed for the keratoconus eye. When bare Descemet's membrane was prepared successfully requiring no conversion to penetrating keratoplasty (PK), then during surgery the donor, endothelium-Descemet's membrane layer was removed and stored for subsequent DMEK in a second patient, and the remaining anterior lamella of the donor cornea was used to complete the DALK surgery. Afterward, a DMEK procedure was performed on the second patient with Fuchs' endothelial dystrophy, grafting the stored endothelium-Descemet's membrane layer of the original donor button.Success of using a single donor cornea for 2 recipient eyes, best spectacle-corrected visual acuity (BSCVA), and complication rates within 6 months follow-up.A single donor cornea could be used for 2 recipients in 10 of 12 donor buttons (83%). In 2 cases (17%), the DALK procedure had to be converted to PK requiring a full-thickness corneal graft. Therefore, 10 donor corneas (45%) could be saved. Six months after surgery, mean BSCVA was 20/35 (range, 20/50-20/25) in 10 eyes that underwent successful DALK, 20/50 (range, 20/63-20/40) in 2 eyes that underwent conversion from DALK to PK, and 20/31 (range, 20/50-20/16) in 10 eyes that underwent DMEK. Postoperative complications after DALK included Descemet's folds in 3 eyes (30%) and epitheliopathy in 2 eyes (20%). After DMEK, partial graft detachment occurred in 5 eyes (50%) and was managed successfully with intracameral air reinjection. All corneas remained clear up to 6 months after surgery.Split use of donor corneal tissue for combined DALK and DMEK procedures in 2 recipients on the same surgery day is a promising strategy to reduce donor shortage and cost in corneal transplantation surgery in the future.
EVALuna2:21012

Split cornea transplantation for 2 recipients - review of the first 100 consecutive patients - Heindl, Ludwig M.; Riss, Stephan; Laaser, Kathrin; Bachmann, Bjoern O.; Kruse, Friedrich; Cursiefen, Claus (American Journal of Ophthalmology, 2011)
To evaluate the feasibility of split cornea transplantation for 2 recipients by combining deep anterior lamellar keratoplasty (DALK) and Descemet membrane endothelial keratoplasty (DMEK).Interventional case series.Fifty consecutive eyes with anterior stromal disease suitable for DALK and 50 eyes with endothelial disease suitable for DMEK were scheduled for split cornea transplantation combining both procedures within 72 hours. Main outcome measures included success of using a single donor cornea for 2 recipients, best spectacle-corrected visual acuity (BSCVA), and complication rates within 6 months' follow-up.A single donor cornea could be used for 2 recipients in 47 cases (94%). In 3 eyes (6%), the DALK procedure had to be converted to penetrating keratoplasty (PK) requiring a full-thickness corneal graft. Thereby, 47 donor corneas (47%) could be saved. Six months after surgery, mean BSCVA was 20/36 in the 47 eyes that underwent successful DALK, 20/50 in the 3 eyes that underwent conversion from DALK to PK, and 20/29 in the 50 eyes that underwent DMEK. Postoperative complications after DALK included Descemet folds in 5 eyes (11%) and epitheliopathy in 3 eyes (6%). After DMEK, partial graft detachment occurred in 26 eyes (52%) and was managed successfully with intracameral air reinjection. All corneas remained clear up to 6 months after surgery. No intraocular infections occurred.Split use of donor corneal tissue for combined DALK and DMEK procedures in 2 recipients within 3 subsequent days is a feasible approach to reduce donor shortage in corneal transplantation in the future.
EVALuna2:21041

Splitting of the Recipient's Descemet Membrane in Descemet Membrane Endothelial Keratoplasty-Ultrastructure and Clinical Relevance - Weller, Julia M.; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Tourtas, Theofilos (American Journal of Ophthalmology, 2016)
In Descemet membrane endothelial keratoplasty (DMEK), lamellar splitting of the Descemet membrane (DM) may occur during stripping of host DM, leaving residual DM on the recipient's DMEK interface. The purpose of this study was to determine the incidence rate of lamellar splitting of DM during DMEK and to describe the ultrastructure of DM in these eyes.Retrospective consecutive case series.setting: Institutional, single-center.Total of 664 eyes with Fuchs endothelial corneal dystrophy (FECD) scheduled for primary DMEK.DMEK.The incidence rate of lamellar DM splitting in the recipients' eyes; ultrastructural alterations of stripped DM specimens (transmission electron microscopy); preoperative best-corrected visual acuity (BCVA), central corneal thickness (CCT), and prevalence of diabetes mellitus.Sixty-three of 664 eyes (9.5%) with FECD showed lamellar splitting of DM resulting in the dissociation of 2 separate layers. Transmission electron microscopy revealed accumulations of banded and wide-spaced collagen between the thicker posterior banded layer and the thin anterior banded layer, which is adhesive to the corneal stroma. Lamellar splitting occurred along these abnormal collagen inclusions, demarcating the borderline between both layers of DM.Lamellar DM splitting occurs during DM stripping in almost 10% of eyes with FECD. This phenomenon appears to be caused by abnormal collagenous material deposits at the borderline between anterior and posterior layers of DM.
EVALuna2:21303

Spontaneous resolution of corneal decompensation after big-bubble deep anterior lamellar keratoplasty with intraoperative Descemet's membrane perforation - Kopsachilis, Nikolaos; Tsinopoulos, Ioannis; Tourtas, Theofilos; Kruse, Friedrich; Cursiefen, Claus (Clinical and Experimental Ophthalmology, 2011)
EVALuna2:20990

SRD5A3-CDG: Twins with an intragenic tandem duplication - Rieger, Melissa; Türk, Matthias; Kraus, Cornelia; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Huchzermeyer, Cord; Wiesmann da Silva Reis, André; Thiel, Christian (European Journal of Medical Genetics, 2022)
Steroid 5α-reductase type 3 congenital disorder of glycosylation (SRD5A3-CDG) is a rare metabolic disease mainly characterized by psychomotor disability, visual impairment, and variable eye malformations caused by bi-allelic pathogenic variants in SRD5A3. So far, only 23 distinct mutations were described. Exome sequencing in 32-year old monozygotic male twins revealed only the heterozygous splice variant c.562+3delG in SRD5A3, but no second variant. The twins presented with psychomotor deficit and a complex eye disease including retinal dystrophy, pallor of the papilla, nystagmus, and strabismus suggestive of SRD5A3-CDG. Only when applying exome-based copy number analysis, we identified as a second compound heterozygous variant a previously not reported tandem duplication of exons 2–4 in SRD5A3. Next to the typical skeletal anomalies of SRD5A3-CDG such as kyphosis and scoliosis, extension deficits of the proximal interphalangeal (PIP) joints IV were observed. Since similar contractures were described once in a patient with SRD5A3-CDG, we suggest that this rare symptom is possibly associated with SRD5A3-CDG. Our findings further expand the mutational and clinical spectrum of SRD5A3-CDG and emphasize the importance of an intragenic copy number analysis in patients with strong clinical suspicion of SRD5A3-CDG and only one detectable sequence variant.
CRIS-Team Scopus Importer:2022-04-15
Keywords: CDG; Exon duplication; SRD5A3

Steady-state multifocal visual evoked potential (ssmfVEP) using dartboard stimulation as a possible tool for objective visual field assessment - Horn, Folkert; Selle, Franziska; Hohberger, Bettina; Kremers, Jan (Graefes Archive For Clinical and Experimental Ophthalmology, 2016)
To investigate whether a conventional, monitor-based multifocal visual evoked potential (mfVEP) system can be used to record steady-state mfVEP (ssmfVEP) in healthy subjects and to study the effects of temporal frequency, electrode configuration and alpha waves.Multifocal pattern reversal VEP measurements were performed at 58 dartboard fields using VEP recording equipment. The responses were measured using m-sequences with four pattern reversals per m-step. Temporal frequencies were varied between 6 and 15 Hz. Recordings were obtained from nine normal subjects with a cross-shaped, four-electrode device (two additional channels were derived). Spectral analyses were performed on the responses at all locations. The signal to noise ratio (SNR) was computed for each response using the signal amplitude at the reversal frequency and the noise at the neighbouring frequencies.Most responses in the ssmfVEP were significantly above noise. The SNR was largest for an 8.6-Hz reversal frequency. The individual alpha electroencephalogram (EEG) did not strongly influence the results. The percentage of the records in which each of the 6 channels had the largest SNR was between 10.0 and 25.2 %.Our results in normal subjects indicate that reliable mfVEP responses can be achieved by steady-state stimulation using a conventional dartboard stimulator and multi-channel electrode device. The ssmfVEP may be useful for objective visual field assessment as spectrum analysis can be used for automated evaluation of responses. The optimal reversal frequency is 8.6 Hz. Alpha waves have only a minor influence on the analysis. Future studies must include comparisons with conventional mfVEP and psychophysical visual field tests.
EVALuna2:21244

Steady-State Visually Evoked Potentials Elicited by Multifrequency Pattern-Reversal Stimulation - Hohberger, Bettina; Kremers, Jan; Horn, Folkert (Translational Vision Science & Technology, 2019)
Purpose: It has been shown that multifrequency stimulation with multifocal electroretinography can reduce recording time without a loss in signal-to-noise ratio. Here, we studied the applicability of multifrequency stimulations for steady-state visually evoked potential (VEP) recordings.
CRIS-Team WoS Importer:2019-03-15
Keywords: Objective visual field test; Multifocal VEP; Signal-to-noise ratio; Pattern reversal; Steady-state

Stem cell-based approaches to diseases of the ocular surface - Schlötzer-Schrehardt, Ursula; Kruse, Friedrich (Ophthalmologe, 2017)
EVALuna2:21337

Stem cell-based therapy for corneal epithelial reconstruction: present and future - Menzel-Severing, Johannes; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Canadian Journal of Ophthalmology-Journal Canadien D Ophtalmologie, 2013)
Limbal stem cell deficiency is a painful and potentially blinding disease. Cultured limbal epithelial transplantation (CLET) is frequently performed for corneal surface reconstruction with variable clinical success. This work summarizes recent developments and trends that have the potential to increase safety and efficacy of CLET in the future. Apart from gradual transition to xenobiotic-free culture systems, novel biofunctional scaffolds presenting components of stem cell microenvironments aim at promoting long-term maintenance of stem cells in vitro and after transplantation. Hair follicles and other tissues may serve as autologous sources of adult stem cells in bilateral ocular surface disease. However, despite all progress made in the fields of tissue engineering and cell therapy, it is unlikely that CLET will yield fully satisfactory clinical results until the factors that govern limbal stem cell maintenance and differentiation are identified.
EVALuna2:21130

Stereopsis Only: Validation of a Monocular Depth Cues Reduced Gamified Virtual Reality with Reaction Time Measurement - Mehringer, Wolfgang; Wirth, Markus; Roth, Daniel; Michelson, Georg; Eskofier, Björn (IEEE Transactions on Visualization and Computer Graphics, 2022)
CRIS-Team Scopus Importer:2022-02-25
Keywords: Games; Headphones; Software verification and validation; Stereo image processing; Stereo vision; Task analysis; Training; Virtual reality; Vision defects; Visualization; Visualization design

Stereoscopic visual perceptual learning in seniors - Erbes, Sabine; Michelson, Georg (Geriatrics, 2021)
Background: We showed that seniors can improve their stereoscopic ability (stereoacuity) and corresponding reaction time with repetitive training and, furthermore, that these improvements through training are still present even after a longer period of time without training. Methods: Eleven seniors (average age: 85.90 years) trained twice a week for six weeks with dynamic stereoscopic perception training using a vision training apparatus (c-Digital Vision Trainer®). Stereoscopic training was performed in 12 training session (n = 3072) of visual tasks. The task was to identify and select one of four figures (stereoscopic stimuli) that was of a different disparity using a controller. The tests included a dynamic training (showing rotating balls) and a static test (showing plates without movement). Before and after training, the stereoacuity and the corresponding reaction times were identified with the static stereotest in order to determine the individual training success. The changes in respect to reaction time of stereoscopic stimuli with decreasing disparity were calculated. Results: After 6 weeks of training, reaction time improved in the median from 936 arcsec to 511 arcsec. Stereoscopic vision improved from 138 arcsec to 69 arcsec, which is an improvement of two levels of difficulty. After 6 months without training, the improvement, achieved by training, remained stable. Conclusions: In older people, visual training leads to a significant, long-lasting improvement in stereoscopic vision and the corresponding reaction time in seniors. This indicates cortical plasticity even in old age.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Ageing; Binocular disparity; Learning effect; Neuroplasticity/cortical plasticity; Oldest old/highest aged patients; Stereopsis; Targeted visual stimulation; Visual perceptual learning; Visual performance

Strain differences in illumination-dependent structural changes at mouse photoreceptor ribbon synapses - Fuchs, Michaela; Sendelbeck, Anna; Atorf, Jenny; Kremers, Jan; Brandstätter, Johann Helmut (Journal of Comparative Neurology, 2013)
Photoreceptor cells encode light signals over a wide range of intensities with graded changes in their membrane potential. At their highly specialized ribbon synapses they transmit the signals to the postsynaptic neurons by the tonic release of glutamate, which is continuously adjusted to changes in light intensity. Such a level of performance requires adaptive mechanisms, and it is suggested that illumination-dependent changes in ribbon shape and size are one of these adaptive processes. In this study we compared structural properties of synaptic ribbons under various illumination conditions between three mouse strains: the pigmented C57BL/6 and the two albino strains Balb/c and B6(Cg)-Tyr(c-2J) /J (coisogenic to C57BL/6). In addition, electroretinograms (ERGs) recorded in the same groups were compared. In the C57BL/6 mouse a change in illumination did not result in structural alterations of the synaptic ribbon. Similarly, in the B6(Cg)-Tyr(c-2J) /J mouse only minor structural changes were detected. In contrast, the state of adaptation had a large influence on the ribbon structure of the Balb/c mouse. The ERG recordings showed only small functional differences between C57BL/6 and B6(Cg)-Tyr(c-2J) /J mice, but the retinal function of Balb/c mice was strongly compromised. We conclude that illumination-dependent changes of photoreceptor ribbon structure differ between strains and thus cannot be regarded as a general mechanism for light adaptation.
EVALuna2:21087

Structural alterations during the course of glaucoma disease - Mardin, C. Y.; Schlötzer-Schrehardt, Ursula (Ophthalmologe, 2015)
Structural changes in the course of glaucoma disease affect the trabecular meshwork and ciliary body in addition to the optic disc as the primary site of glaucoma damage.Latest results from experimental studies, animal models and measurements in human eyes are presented and discussed.The presenting scenario is complex with age, biochemical and mechanical stress factors leading to subsequent, irreversible tissue change in the trabecular meshwork and cribriform plate of the optic nerve, resulting in neuronal tissue loss.Knowledge of these changes will be the key for future glaucoma therapies.
EVALuna2:21159

Structural changes of macular inner retinal layers in early normal-tension and high-tension glaucoma by spectral-domain optical coherence tomography - Edlinger, Florian S. M.; Schrems-Hösl, Laura-Maria; Mardin, Christian Y.; Lämmer, Robert; Kruse, Friedrich; Schrems, Wolfgang (Graefes Archive For Clinical and Experimental Ophthalmology, 2018)
PURPOSE: Assessment of the diagnostic ability of segmented macular inner retinal layer thickness and peripapillary retinal nerve fiber layer (pRNFL) measured by spectral-domain optical coherence tomography (SD-OCT) in patients with normal-tension (NT) and high-tension (HT) perimetric and preperimetric glaucoma. METHODS: The 212 participants included 45 healthy subjects, 55 patients with ocular hypertension, 56 patients with preperimetric glaucoma, and 56 patients with perimetric glaucoma. The preperimetric and perimetric groups were further subdivided into NT and HT groups. Sectoral and global thickness of macular retinal nerve fiber layer (mRNFL), ganglion cell layer (mGCL), inner plexiform layer (mIPL), ganglion cell complex (mGCC), and pRNFL were measured using SD-OCT (Spectralis, Heidelberg Engineering, Germany). Diagnostic performance was ascertained by sectoral and global comparison of the sensitivities at specificity ≥ 95%. RESULTS: For all layers, the largest thickness decrease was reported in the HT perimetric group. In all groups, the sensitivities of mGCL showed a comparable diagnostic value to pRNFL in order to distinguish between healthy subjects and glaucoma patients. In the perimetric group, mGCL (85.7%) exhibited higher sensitivities than mRNFL (78.6%) and mGCC (78.6%). Both mRNFL and pRNFL demonstrated equal diagnostic performance in the HT perimetric group (88.5 and 96.2%), in the NT groups, mRNFL was inferior to all other layers. CONCLUSION: The sensitivities of mGCL and mRNFL were comparable to the sensitivities of pRNFL. In clinical application, mGCL and mRNFL, with a focus on the temporal and inferior sectors, may provide a convincing supplementation to pRNFL. CLINICAL TRIAL REGISTRATION: Erlangen Glaucoma Registry www.clinicaltrials.gov ID: NCT00494923.
EVALuna2:34747

Structural diagnostics of course observation for glaucoma - Mardin, Christian Y. (Ophthalmologe, 2013)
Imaging of the structural progression of glaucoma enables measurement of the neuroretinal rim of the optic disc, retinal nerve fibre layer and thickness of the ganglion layer.High resolution disc photography, laser scanning tomography, scanning laser polarimetry and optical coherence tomography (OCT) are the current methods of choice to document and measure progression of this chronic degenerative disease.Loss of the neuroretinal rim is only a few mm(2) or mm(3) per year and has to be differentiated from age-related loss which shows less change over the years. The most pronounced loss is temporal both superior and inferior. Thinning of the retinal nerve fibre layer follows the same pattern with significant annual changes of only 6-7 µm. Modern OCT devices deliver measurements of the macula ganglion cell complex which can be even more sensitive than the thickness of the retinal nerve fibre layer. Qualitative criteria for structural progression are papillary hemorrhage, rarification of papillary vessels and specific changes of the retinal pigment epithelium.Structural loss due to glaucoma can be imaged and measured with different methods in different tissues. The evaluation of significant changes is still the responsibility of the ophthalmologist by taking all findings into account.
EVALuna2:21140

Successful brachytherapy of a clinically unapparent ciliary body melanoma - Cirkovic, Aleksandar; Roessler, T.; Wildner, K.; Mardin, C. Y.; Knorr, H. L. (Ophthalmologe, 2015)
We report on a typical case of a ciliary body melanoma in a 59-year-old female, which was only noticed due to nonspecific unilateral vision disorders and which could only be seen in maximal mydriasis via a gonioscopic three-mirror lens. We further discuss tumor monitoring via ultrasound biomicroscopy (UBM) and execution and prognosis of Ru-106 brachytherapy.
EVALuna2:21221

Successful remission induction with a combination therapy of rituximab, cyclophosphamide, and steroids in a patient with refractory optic neuritis in Wegener's granulomatosis - Huchzermeyer, Cord; Mardin, Christian Y.; Holbach, Leonard; Zwerina, Jochen; Schett, Georg; Rech, Juergen (Clinical Rheumatology, 2013)
A 56-year old patient with a history of limited Wegener's granulomatosis presented with signs and symptoms of optic neuritis. Radiologic signs of orbital inflammation were absent. Testing of visual acuity and visual field allowed close monitoring of disease activity. Thus, rapid improvement of visual function was achieved with high-dose steroids. Despite maintenance therapy with cyclophosphamide recurrence occurred repeatedly as soon as tapering of steroids was begun. After remission induction with rituximab, the patient retained good visual function under maintenance therapy with azathioprine and low-dose corticosteroids. Optic neuritis in Wegener's granulomatosis without signs of orbital involvement is rare and most likely caused by occlusive vasculitis of the vasa nervorum. In this patient with optic neuritis refractory to conventional therapy, rituximab in combination with cyclophosphamide and corticosteroids was well tolerated and successfully used for remission induction, followed by maintenance therapy with azathioprine and low dose corticosteroids.
EVALuna2:12699

Summation of Temporal L-Cone- and M-Cone-Contrast in the Magno- and Parvocellular Retino-Geniculate Systems in Glaucoma - Huchzermeyer, Cord; Horn, Folkert; Lämmer, Robert; Mardin, Christian; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
Purpose: The purpose of this study was to characterize summation of temporal L- and M-cone contrasts in the parvo- (P-) and magnocellular (M-) pathways in glaucoma and the relationship between the respective temporal contrast sensitivities (tCS) and clinical parameters. Methods: Perifoveal tCS to isolated or combined L- and M-cone contrasts (with different contrast ratios, and therefore different luminance and chromatic components) were measured at different temporal frequencies (at 1 or 2 Hz and at 20 Hz) using triple silent substitution in 73 subjects (13 healthy, 25 with glaucoma, and 35 with perimetric glaucoma). A vector summation model was used to analyze whether perception was driven by the P-pathway, the M-pathway, or both. Using this model, L- and M-cone input strengths (AL, AM) and phase differences between L- and M-cone inputs were estimated. Results: Perception was always mediated by the P-pathway at low frequencies, as indicated by a median phase angle of 179.84 degrees (cone opponency) and a median AL/AM ratio of 1.04 (balanced L- and M-cone input strengths). In contrast, perception was exclusively mediated by the M-pathway at higher frequencies (input strength not balanced: AL/AM = 2.94, median phase angles = 130.17 degrees). Differences in phase were not significant between diagnosis groups (Kruskal-Wallis = 0.092 for P- and 0.35 for M-pathway). We found differences between groups only for the M-pathway (L-cone tCS deviations at 20 Hz were significantly lower in the patients with glaucoma P = 0.014, with a strong tendency in M-cones P = 0.049). L-cone driven tCS deviations at 20 Hz were linearly correlated with perimetric mean defect (MD) and quadratically correlated with retinal nerve fiber layer (RNFL) thickness. Conclusions: Unaltered phase angles between L- and M-cone inputs in glaucoma indicated intact temporal processing. Only in the M-pathway, contrast sensitivity deviations were closely related to diagnosis group, MD, and RNFL thickness, indicating M-pathway involvement.
CRIS-Team Scopus Importer:2021-06-04

Super-Resolved Retinal Image Mosaicing - Köhler, Thomas; Heinrich, Axel; Maier, Andreas; Hornegger, Joachim; Tornow, Ralf-Peter (2016 IEEE 13th International Symposium on Biomedical Imaging, 2016)
The acquisition of high-resolution retinal fundus images with a large field of view (FOV) is challenging due to technological, physiological and economic reasons. This paper proposes a fully automatic framework to reconstruct retinal images of high spatial resolution and increased FOV from multiple low-resolution images captured with non-mydriatic, mobile and video-capable but low-cost cameras. Within the scope of one examination, we scan different regions on the retina by exploiting eye motion conducted by a patient guidance. Appropriate views for our mosaicing method are selected based on optic disk tracking to trace eye movements. For each view, one super-resolved image is reconstructed by fusion of multiple video frames. Finally, all super-resolved views are registered to a common reference using a novel polynomial registration scheme and combined by means of image mosaicing. We evaluated our framework for a mobile and low-cost video fundus camera. In our experiments, we reconstructed retinal images of up to 30° FOV from 10 complementary views of 15° FOV. An evaluation of the mosaics by human experts as well as a quantitative comparison to conventional color fundus images encourage the clinical usability of our framework.
UnivIS-Import:2017-11-07:Pub.2016.tech.IMMD.IMMD5.superr_1
Keywords: eye tracking; fundus video imaging; mosaicing; Retinal imaging; super-resolution

Supplementation of amphotericin B in Optisol-GS for Descemet membrane endothelial keratoplasty (DMEK) - Galimi, Maria Elena; Weller, Julia M.; Kruse, Friedrich; Augustin, Victor A.; Tourtas, Theofilos (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Supplementation of organ culture medium with dextran is not required in pre-stripped human donor tissue for DMEK surgery - Salla, Sabine; Kruse, Friedrich; Walter, Peter; Menzel-Severing, Johannes (Cell and Tissue Banking, 2019)
To assess corneal endothelial cell (CEC) quantity and quality in eye-bank prepared lamellar grafts for Descemet Membrane Endothelial Keratoplasty (DMEK) from organ cultured donor corneas that have not undergone de-swelling by media supplementation with dextran. Prior to graft preparation, corneas that had not undergone de-swelling (n = 30) were placed into fresh storage medium without dextran (KMI). Corneas in the control group (n = 30) were placed in dehydration medium containing 5% dextran (KMII). Subtotal stripping of Descemet’s membrane (DM) was performed manually. Following graft preparation, 10 corneas of each group were cultured further in their respective medium for 24 h, 72 h, or 120 h, respectively. Before and after DM stripping, as well as at the end of culture, CEC numbers were obtained. At the end of culture, CEC morphology was graded using a scoring system and CEC metabolism was assessed by detection of adenosine triphosphate. At 24 h after DM stripping, mean CEC counts (in cells/mm2) were 2204 in corneas stored in KMII, and 2391 in corneas stored in KMI (p = 0.003). This corresponds to a mean relative CEC loss of 12.4% with dextran versus 9.7% without dextran (p = 0.04). At 72 h, CEC counts were 1946 in KMII, and 2289 in KMI (p = 0.004). This corresponds to CEC loss of 23% with dextran versus 14% without dextran (p = 0.009). At 120 h, CEC counts were 2047 in KMII, and 2230 in KMI (p = 0.14). This corresponds to CEC loss of 22.7% with dextran versus 17.2% without dextran (p = 0.14). Also, at 120 h after DM stripping, 6/10 corneas fell below a threshold of 2000 cells/mm2 if stored in medium containing dextran, versus 1/9 corneas if stored without dextran (p = 0.003). Morphological assessment of CEC quality revealed equal scores for cell polymorphism (median = 1), granulation (median = 0) and segmentation (median = 1) in all groups. Lower ATP/protein ratios were observed in corneas stored in medium without dextran at 24 h (p < 0.001), 72 h (p < 0.001), and 120 h (p = 0.02). Abandoning the use of dextran in corneas destined for DMEK surgery leads to increased CEC counts and thereby serves to reduce tissue loss.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Corneal transplantation; DMEK; Lamellar keratoplasty; Tissue banking

Suppression of inflammatory corneal lymphangiogenesis by application of topical corticosteroids - Hos, Deniz; Saban, Daniel R.; Bock, Felix; Regenfuss, Birgit; Onderka, Jasmine; Masli, Sharmila; Cursiefen, Claus (Archives of Ophthalmology, 2011)
To analyze whether topical application of corticosteroids inhibits inflammatory corneal lymphangiogenesis and to study the potential underlying antilymphangiogenic mechanisms.Inflammatory corneal neovascularization was induced by suture placement, and the corneas were then treated with topical fluorometholone, prednisolone acetate, or dexamethasone sodium phosphate. After 1 week, the corneas were stained with lymphatic vessel endothelial hyaluronan receptor 1 for detection of pathological corneal lymphangiogenesis. The effect of these corticosteroids on macrophage recruitment was assessed via fluorescence-activated cell sorting analysis. The effect of these corticosteroids on proinflammatory cytokine expression by peritoneal exudate cells was tested via real-time polymerase chain reaction. Furthermore, the effect of steroid treatment on the proliferation of lymphatic endothelial cells was assessed via enzyme-linked immunosorbent assay.Treatment with corticosteroids resulted in a significant reduction of inflammatory corneal lymphangiogenesis. The antilymphangiogenic effect of fluorometholone was significantly weaker than that of prednisolone and dexamethasone. Corneal macrophage recruitment was also significantly inhibited by the application of topical steroids. Treatment of peritoneal exudate cells with corticosteroids led to a significant downregulation of the RNA expression levels of tumor necrosis factor and interleukin 1?. Additionally, proliferation of lymphatic endothelial cells was also inhibited.Corticosteroids are strong inhibitors of inflammatory corneal lymphangiogenesis, with significant differences between various corticosteroids in terms of their antilymphangiogenic potency. The main mechanism of the antilymphangiogenic effect seems to be through the suppression of macrophage infiltration, proinflammatory cytokine expression, and direct inhibition of proliferation of lymphatic endothelial cells.Steroids block corneal lymphangiogenesis, the main risk factor for immune rejections after corneal transplantation. The different antilymphangiogenic potency of these drugs should be taken into account when using steroids in clinical practice (eg, after keratoplasty).
EVALuna2:21051

Surprising histologic findings in a chronic corneal ulcer Überraschung in der Histologie bei einem chronischen Hornhautulkus - Steinhorst, K. A.; Weller, Julia (Die Ophthalmologie, 2023)
CRIS-Team Scopus Importer:2023-10-20

Sustained Activation of the Unfolded Protein Response Induces Cell Death in Fuchs' Endothelial Corneal Dystrophy - Okumura, Naoki; Kitahara, Miu; Okuda, Hirokazu; Hashimoto, Keisuke; Ueda, Emi; Nakahara, Makiko; Kinoshita, Shigeru; Young, Robert D.; Quantock, Andrew J.; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; et al. (Investigative Ophthalmology & Visual Science, 2017)
The unfolded protein response (UPR) is believed to play a role in the pathogenesis of Fuchs' endothelial corneal dystrophy (FECD). The purpose of this study was to investigate whether unfolded proteins accumulate in the corneal endothelium in FECD and if they are involved in triggering cell death.Descemet's membranes with corneal endothelial cells (CECs) were obtained during keratoplasty, and expression of aggresomes, type 1 collagen, fibronectin, and agrin was evaluated. Endoplasmic reticulum (ER) stress of immortalized human CECs from non-FECD subjects and from FECD patients (iHCEC and iFECD, respectively) were evaluated. The effect of MG132-mediated aggresome formation on the UPR and intrinsic pathway and the effect of mitochondrial damage on UPR were also examined. The effect of CHOP knockdown on the ER stress-mediated intrinsic pathway was also evaluated.Aggresome formation was higher in iFECD than in iHCEC and was colocalized with type 1 collagen, fibronectin, and agrin. GRP78, phosphorylated IRE1, PERK, and CHOP showed higher activation in iFECD than in iHCEC. MG132-mediated aggresome formation upregulated ER stress sensors, the mitochondrial membrane potential drop, cytochrome c release to the cytoplasm, and activation of caspase-9 and -3. By contrast, staurosporine-mediated mitochondrial damage did not induce ER stress. Knockdown of CHOP attenuated the ER stress-induced cleavage of caspase-9, which is caused by intrinsic pathway activation.Excessive synthesis of extracellular matrix proteins induced unfolded protein accumulation in FECD. Prolonged ER stress-mediated cell death, occurring via the intrinsic apoptotic signaling pathway, therefore might be associated with the pathogenesis of FECD.
EVALuna2:21347

Suture-ability of patch grafts for ocular surface reconstruction - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Suture retension test method for opthalmological materials - Voigt, Monika; Thieme, Daniel; Küng, Florian; Schubert, Dirk W.; Kruse, Friedrich; Fuchsluger, Thomas (Deutsche Gesellschaft für Biomaterialien, 2018)
Keywords: biomaterialien; espinning suture retension

Switch of inhibitory to agonistic autoantibodies directed against the beta 2-adrenergic receptor in the pathogenesis of pseudoexfoliation syndrome and glaucoma - Hohberger, Bettina; Herrmann, Martin; Schlötzer-Schrehardt, Ursula; Mardin, Christian Y.; Lämmer, Robert; Kunze, Rudolf; Wallukat, Gerd (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-17

Sympathetic ophthalmia following repeated pars plana vitrectomy : Clinical findings and spectral domain OCT follow-up - Bergua, A.; Mardin, C.; Holbach, L.; Meiller, R.; Hohberger, B. (Ophthalmologe, 2016)
Sympathetic ophthalmia is a rare form of bilateral granulomatous panuveitis, occurring after penetrating trauma. Hitherto, sympathetic ophthalmia after vitrectomy has only occasionally been described in the literature. This case report presents a female patient with sympathetic ophthalmia after repeated pars plana vitrectomy on the basis of clinical findings and follow-up with fluorescein angiography, spectral domain OCT, and histopathology.
EVALuna2:21309

Teaching NeuroImages: Stroke and bilateral visual loss in a young adult: More than coincidence - Volbers, Bastian; Kaldefoss, K.; Bergua, A.; Kloska, Stephan; Schwab, Sibylle; Köhrmann, Martin (Neurology, 2012)
EVALuna2:21072

Tear film osmolarity measurements in dry eye disease using electrical impedance technology - Jacobi, Christina; Jacobi, Arnd; Kruse, Friedrich; Cursiefen, Claus (Cornea, 2011)
: Tear film hyperosmolarity is recognized as an important pathogenetic factor in dry eye syndrome, but difficulties in its measurement have limited its utility in the recent past. This prospective, nonrandomized, clinical single-center study investigates the osmolarity in tear samples of patients with keratoconjunctivitis sicca compared with healthy controls.: One hundred thirty-three patients [aged 58 years (51-64 years), 86 women and 47 men] with moderate to severe keratoconjunctivitis sicca and 95 controls [aged 52 years (48-61 years), 55 women and 40 men] were enrolled in the trial. Tear samples were collected directly from the inferior lateral tear meniscus. Inclusion criteria were a tear breakup time of less than 5 seconds, a Schirmer test with anesthesia less than 5 mm, and positive symptoms (Ocular Surface Disease Index score > 83). Tear film osmolarity was analyzed by the TearLab osmometer.: In our study, patients with moderate to severe keratoconjunctivitis sicca showed a tear film osmolarity of 320 mOsmol/L (301-324 mOsmol/L). The results of the control group were 301 mOsmol/L (298-304 mOsmol/L). Our results revealed a significantly higher tear film osmolarity in patients with moderate to severe keratoconjunctivitis sicca compared with the control group. The sensitivity was 87%, and the specificity was 81%.: Our results approved the referent value in moderate to severe dry eye of approximately 316 mOsmol/L, as described in the literature. The results showed a significantly higher tear film osmolarity in patients with severe keratoconjunctivitis sicca compared with the healthy controls. Testing tear film osmolarity can be a very effective objective diagnostic tool in the diagnosis of dry eye disease.
EVALuna2:21036

Teleglaucoma Using a New Smartphone-Based Tool for Visual Field Assessment - Grau, Elisabeth; Andrae, Stefan; Horn, Folkert; Hohberger, Bettina; Ring, Matthias; Michelson, Georg (Journal of Glaucoma, 2023)
Précis: COVID-19 underlines the importance of telemedical diagnostics. The smartphone-based campimetry (Sb-C) is a newly developed digital application allowing visual field testing using a head-mounted device and a smartphone. It enables visual field screening remotely from a clinic. Background: Sb-C is a newly developed tool for functional ophthalmic diagnosis. This study aimed to examine the comparability of the Sb-C and Octopus 900 to ensure ophthalmological care in times of social distancing. Methods: Total 93 eyes were included in the study. After an ophthalmological examination, the visual field was tested by the Octopus program G1 and by the smartphone-based campimeter. The Sb-C was performed using VR glasses and an iPhone 6. The software Sb-C was downloaded and installed as SmartCampiTracker app and is examining the 30-degree visual field with 59 test positions corresponding to the G pattern of Octopus G1. Sensitivities were recorded and saved on the app. In addition, test-retest reliability was tested on 6 ophthalmologically healthy participants. Results: The group comprised 48 women and 45 men (mean age: 62.52±12.2 y) including 19 controls, 17 patients with ocular hypertension, 11 preperimetric glaucomas, and 46 perimetric glaucomas. The mean sensitivity (MS) of all points of G1 perimetry was 23.13 dB (95% CI, 22.08-24.18). The MS of the Sb-C was 21.23 dB (95% CI, 20.37-22.08). The correlation between the mean MS measured by G1 perimetry and the Sb-C was strong (r=0.815, P<0.05). The test-retest reliability showed a correlation of r=0.591 (P<0.05). Conclusions: With some technical adjustments, the Sb-C shows promise for screening glaucoma and monitoring disease progression remotely from an ophthalmologic clinic.
CRIS-Team Scopus Importer:2023-03-24
Keywords: glaucoma; perimetry; smartphone; telemedicine

Telemedical assessment of optic nerve head and retina in patients after recent minor stroke or TIA - Wolz, Johannes; Audebert, Heinrich; Laumeier, Inga; Ahmadi, Michael; Steinicke, Maureen; Ferse, Caroline; Michelson, Georg (International Ophthalmology, 2016)
The aim of the study is to telemedically assess the prevalence of simple optic nerve atrophy and retinal arteriolar anomalies in subjects who have had a minor stroke or TIA within 14 days, and to compare these results with an age-matched control group. By using a mobile examination unit, retinal photographs were taken with a 45° non-mydriatic colour fundus camera (KOWA NM-45, non-mydriatic-alpha) in patients who had suffered from a minor stroke or TIA within 14 days of the time of the examination. Retinal photographs were focused on the optic nerve head region. Pupils were not dilated. The documented medical history and the retinal images were stored on a server using browser independent web-based software running on PCs, tablets and smartphones. After completing the upload of the medical interview and the retinal images into the electronic patient chart, all retinal images were evaluated via telemedicine by an experienced senior consultant ophthalmologist. Age-matched normotensive, non-diabetic subjects (aged 40-89 years) who reported no systemic or ocular diseases were used as the control group. Both study groups were divided into five decades of life (40-49; 50-59; 60-69; 70-79; 80-89 years). We calculated the prevalences and the ratios of prevalences of optic nerve atrophy and retinal arteriolar anomalies between the stroke and the control group per decades of life. 139 minor stroke or TIA subjects (aged 40-89 years) and 1611 age-matched control subjects were examined. In the stroke group, we found significantly increased prevalences of optic nerve atrophy and retinal arteriolar anomalies throughout the 5th-8th decade of life when compared to age-matched controls. The prevalence of optic nerve atrophy in stroke subjects outranged the prevalence in the controls depending on age-class by a factor of 3-21. Simple optic nerve atrophy is frequent in patients who have suffered from an ischemic stroke or TIA, and it seems to indicate vascular damage, indicating the necessity for telemedically assisted assessment of the optic nerve.
EVALuna2:21301

Telemedizinisch unterstütztes Screening der retinalen Gefäße („Talking Eyes”) - Michelson, Georg; Groh, M.; Groh, M. J.M.; Baleanu, D.; Harazny, J.; Horstmann, R.; Kolominsky-Rabas, Peter (Klinische Monatsblätter für Augenheilkunde, 2005)
Background: Cerebral and retinal vessels behave similarly under the influence of vascular risk factors. Several groups have shown that retinal microvascular abnormalities represent an independent risk factor with regard to strokes and heart attacks. Aim of the Study: The aim of this study was to perform a prospective screening examination with regard to retinal microvascular abnormalities as well as an extended vessel diagnosis in a subgroup of patients with lower arteriovenous risk values. Methods: In the course of a prospective cross-sectional study ("Talking Eyes") between 1.9.2001 and 1.8.2002 a telemedical-supported screening of the retina (study 1) was carried out in 7,163 subjects. The patients were selected without any inclusion or exclusion criteria. The mean age was 48.2 ± 8 years (18-83 years) with a sex distribution of 39.2% females to 60.8% males. Digital fundus photos of the right and left eyes were taken for all patients. The pictures were taken without pupil dilation using a CANON-NM camera. The pictures and case histories were stored in a central server using web-based software (MedStage, Siemens). In a central reading centre, the arteriovenous ratio of both eyes was determined telemedically using the Parr-Hubbard formula and the retinas subjected to a standardised examination by an ophthalmologist. The retinal risk factor was calculated on the basis of the arteriovenous ration, the presence of microvascular abnormalities and the case history. The reproducibility of measurement of the arteriovenous ratio (Kronbach alpha coefficient) was evaluated by double measurements on 1,332 images. In a subgroup of study 1 with arteriovenous ratio values < 0.76 (N = 107), an extended vessel diagnosis with measurement of 24-h blood pressure and vessel-relevant blood values (homocysteine, cholesterol, LDL, HDL, CRP, TG, HbA1c) was carried out (study II). Results: Study 1: The Kronbach alpha coefficient as a measure of reproducibility amounted to 0.77. The mean arteriovenous ratio of the retinal vessels was 0.83 ± 0.09 and showed a pronounced age dependence (R = 0.9, p < 0.0001). On multivariate testing the arteriovenous ratio correlated significantly (R = 0.33, p < 0.001) with the factors age, systolic blood pressure, diastolic blood pressure and body mass index. Diastolic blood pressure followed by age had the largest influence. The prevalence of microvascular abnormalities in the right (RE) and left (LE) eyes, respectively were: cotton wool foci RE 0.0015%, LE 0.003%, retinal haemorrhage RE 0.1%, LE 0.1%, focal stenoses RE 3.4%, LE 3.4%, tortuositas vasorum RE 4.1%, LE 4.0%, arteriovenous crossing signs RE 11.2%, LE 11.2%. On multivariate testing the occurrence of microvascular abnormalities correlated significantly (R = 0.38, p < 0.001) with the factors high blood pressure known from case history, body mass index, and gender. Arterial hypertension had the strongest influence followed by diastolic blood pressure. The calculated retinal risk factor correlated with the prevalence of angina pectoris. Study 11: 2/3 of the subjects with arteriovenous risk factor values < 0.76 exhibited pathologically high 24-h blood pressure values. For these patients there were significant correlations between the arteriovenous ratio and the low-density lipoprotein concentration as well as the Framingham risk score. Conclusion: In the course of a prospective, telemedical-supported screening examination of the retinal vessels of more than 7,000 subjects the arteriovenous ratio exhibited a strong dependence on age and blood pressure. Among the subjects with lowered arteriovenous ratio values, 2/3 exhibited arterial hypertension in the 24-h blood pressure determination.
Created from Fastlane, Scopus look-up
Keywords: Retinal mikroangiopathy; Screening; Talking Eyes; Telemedicine

Teleophthalmology in Preventive Medicine - Höher, Bernhard; Michelson, Georg; Voigtmann, Peter; Schmauß, Bernhard (Teleophthalmology in Preventive Medicine, 2015)
lhft_intern.bib::Hoeher2015

Temporal characteristics of L- and M-cone isolating steady-state electroretinograms - Kommanapalli, Deepika; Murray, Ian J.; Kremers, Jan; Parry, Neil R. A.; Mckeefry, Declan J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
Cone isolating stimuli were used to assess the temporal frequency response characteristics of L- and M-cone electroretinograms (ERGs) in nine trichromatic and four dichromatic human observers. The stimuli comprised sinusoidal temporal modulations varying from 5 to 100 Hz. ERGs were recorded using corneal fiber electrodes and subjected to fast Fourier transform analysis. At low temporal frequencies (<10 Hz) the L- and M-cone ERGs had similar amplitude and exhibited minimal differences in apparent latency. At higher flicker rates (>20 Hz) L-cone ERGs had greater amplitudes and shorter apparent latencies than the M-cone responses. These differences between the L- and M-cone ERGs are consistent with their mediation by chromatic and luminance postreceptoral processing pathways at low and high temporal frequencies, respectively.
EVALuna2:21213

Temporal Contrast Sensitivities are Locally Reduced around 4Hz for L-cone- and around 10Hz for M-cone isolating stimuli in Glaucoma Patients - Huchzermeyer, Cord; Haubner, Sarah; Lämmer, Robert; Mardin, Christian Y.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

Temporal contrast sensitivities elicited by the four photoreceptor classes using the silent substitution paradigm in retinitis pigmentosa - Huchzermeyer, Cord; Auer, Judith; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2015)

Test anxiety among German medical students and its impact on lifestyle and substance abuse - Tektas, Ozan Yüksel; Paulsen, Friedrich; Sel, Saadetin (Medical Teacher, 2013)
CRIS-Team Scopus Importer:2022-08-05

Testosterone Replacement Therapy in Hypogonadal Men Following Prostate Cancer Treatment: A Questionnaire-Based Retrospective Study among Urologists in Bavaria, Germany - Kühn, Charlotte; Strasser, Hans; Romming, Alexander; Wullich, Bernd; Goebell, Peter (Urologia Internationalis, 2015)
Several reports suggest testosterone replacement therapy (TRT) may be an option in selected hypogonadal patients with a history of prostate cancer (PCa) and no evidence of disease after curative treatment. Our aim was to assess TRT experience and patient management among urologists in Bavaria.Questionnaires were developed and mailed to all registered urologists in Bavaria (n = 420) regarding their experience with TRT in patients with treated PCa.One hundred and ninety-three (46%) urologists returned the questionnaire and reported their experience with TRT in hypogonadal patients after curative treatment for PCa. Complete data was available for 32 men. Twenty-six patients (81%) received TRT after prostatectomy, 1 patient after external beam radiation, 3 patients after high-dose brachytherapy and 2 patients after high-intensity focused ultrasound. Of the PCa cases, 88.5% (23/26) were organ confined (pT2a-c), and 3 were pT3 tumors. All patients were pN0/cN0, and only 1 patient (pT3a) had a positive surgical margin status postoperatively. After a mean follow-up of 39.8 months, no biochemical relapse was observed.To date, there is no clear evidence to withhold TRT from hypogonadal men after curative PCa treatment. Our findings, although with limitations, fit in with the available data showing that TRT does not put patients at an increased risk after curative treatment of PCa.
EVALuna2:16276

The Association Between Acquired Color Deficiency and PET Imaging of Neurodegeneration in Mild Cognitive Impairment and Alzheimer Disease - Vidal, Kallene Summer Moreira; Decleva, Diego; Barboni, Mirella Telles Salgueiro; Nagy, Balazs Vince; De Menezes, Paulo Augusto Hidalgo; Aher, Avinash; Coutinho, Artur Martins; Squarzoni, Paula; Faria, Daniele De Paula; Duran, Fabio Luis De Souza; Buchpiguel, Carlos Alberto; Kremers, Jan; et al. (Investigative Ophthalmology & Visual Science, 2022)
PURPOSE. To evaluate color vision changes and retinal processing of chromatic and lumi-nance pathways in subjects with Alzheimer disease (AD) and mild cognitive impairment (MCI) compared with a matched control group and whether such changes are associated with impaired brain glucose metabolism and beta-amyloid deposition in the brain.METHODS. We evaluated 13 patients with AD (72.4 +/- 7.7 years), 23 patients with MCI (72.5 +/- 5.5 years), and 18 controls of comparable age (P = 0.44) using Cambridge color test and the heterochromatic flicker ERG (HF-ERG). The Cambridge color test was performed using the trivector protocol to estimate the protan, deutan and tritan color confusion axes. HF-ERG responses were measured at a frequency of 12 Hz, which ERGs reflect chromatic activity, and at 36 Hz, reflecting luminance pathway. A study subsample was performed using neuropsychological assessments and positron emission tomography.RESULTS. Patients with AD presented higher mean values indicating poorer color discrim-ination for protan (P = 0.04) and deutan (P = 0.001) axes compared with the controls. Along the tritan axis, both patients with AD and patients with MCI showed decreased color vision (P = 0.001 and P = 0.001) compared with controls. The analyses from the HF-ERG protocol revealed no differences between the groups (P = 0.31 and P = 0.41). Diffuse color vision loss was found in individuals with signs of neurodegeneration (protan P = 0.002, deutan P = 0.003 and tritan P = 0.01), but not in individuals with signs of beta-amyloid deposition only (protan P = 0.39, deutan P = 0.48, tritan P = 0.63), regardless of their clinical classification.CONCLUSIONS. Here, patients with AD and patients with MCI present acquired color vision deficiency that may be linked with impaired brain metabolism.
CRIS-Team WoS Importer:2023-04-28

The association between corneal neovascularization and visual acuity: a systematic review - Bachmann, Bjoern; Taylor, Rod S.; Cursiefen, Claus (Acta Ophthalmologica, 2013)
Corneal neovascularization (CNV) is thought to negatively influence visual acuity. New therapeutic options that offer a differentiated influence on the ingrowths or regression of either corneal blood or lymphatic vessels force us to re-evaluate the association between CNV and visual acuity.A systematic review was conducted. Electronic databases were searched up to August 2009. Given the heterogeneity in study populations, interventions and measures of association, we were unable to undertake meta-analysis. The association between CNV and visual acuity was reported descriptively for each study.Eleven studies using either vascular endothelial growth factor inhibitor treatments (i.e. bevacizumab, Avastin(®) ; Hoffmann-La Roche AG, Basel, Switzerland) or an antiangiogenic treatment based on IRS-1 modulation [Gene-Signal (GS) 101, Aganirsen(®) ; GeneSignal, Evry (Paris), France] in a total of 131 patients (142 eyes) with corneal neovascularization were included. Ten of the eleven studies reported evidence of a statistically significant reduction in neovascularization following treatment. However, only four studies reported a statistically significant improvement in visual acuity following therapy. We found no studies that assessed the patient-level association between the change in neovascularization and visual acuity.This systematic review found that there is currently weak evidence to support the hypothesis that in patients with pathological neovascularization, a treatment-related reduction in neovascularization is associated with an increase in visual acuity. There is a need for future appropriately designed studies.
EVALuna2:21049

The BEACH Protein LRBA Promotes the Localization of the Heterotrimeric G-protein Golf to Olfactory Cilia - Kurtenbach, Stefan; Gießl, Andreas; Stromberg, Siv; Kremers, Jan; Atorf, Jenny; Rasche, Sebastian; Neuhaus, Eva M.; Herve, Denis; Brandstätter, Johann Helmut; Asan, Esther; Hatt, Hanns; Kilimann, Manfred W. (Scientific Reports, 2017)
BEACH domain proteins are involved in membrane protein traffic and human diseases, but their molecular mechanisms are not understood. The BEACH protein LRBA has been implicated in immune response and cell proliferation, and human LRBA mutations cause severe immune deficiency. Here, we report a first functional and molecular phenotype outside the immune system of LRBA-knockout mice: compromised olfaction, manifesting in reduced electro-olfactogram response amplitude, impaired food-finding efficiency, and smaller olfactory bulbs. LRBA is prominently expressed in olfactory and vomeronasal chemosensory neurons of wild-type mice. Olfactory impairment in the LRBA-KO is explained by markedly reduced concentrations (20-40% of wild-type levels) of all three subunits ?olf, ?1 and ?13 of the olfactory heterotrimeric G-protein, Golf, in the sensory cilia of olfactory neurons. In contrast, cilia morphology and the concentrations of many other proteins of olfactory cilia are not or only slightly affected. LRBA is also highly expressed in photoreceptor cells, another cell type with a specialized sensory cilium and heterotrimeric G-protein-based signalling; however, visual function appeared unimpaired by the LRBA-KO. To our knowledge, this is the first observation that a BEACH protein is required for the efficient subcellular localization of a lipid-anchored protein, and of a ciliary protein.
EVALuna2:21341

The composition of exfoliation material and the cells involved in its production - Zenkel, Matthias; Schlötzer-Schrehardt, Ursula (Journal of Glaucoma, 2014)
The hallmark of exfoliation syndrome is the pathologic production and stable accumulation of an abnormal, fibrillar, extracellular material (XFM). Although the exact biochemical composition of the pathologic matrix product is still not known, immunohistochemical and biochemical approaches have shown XFM to represent a highly glycosylated, cross-linked, and enzymatically resistant glycoprotein/proteoglycan complex, composed of a protein core surrounded by glycoconjugates. The protein core includes basement membrane components, such as laminin, nidogen, and fibronectin, and components of the elastic fiber system, such as fibrillin-1, elastin, and latent transforming growth factor binding proteins, as well as enzymatically active components, such as metalloproteinases, the extracellular chaperone clusterin, and the cross-linking enzyme lysyl oxidase-like 1 (LOXL1). Ultrastructural evidence suggests that XFM is multifocally produced by intraocular cells, such as ciliary epithelial cells, preequatorial epithelial cells of the lens, trabecular and corneal endothelial cells, all cell types of the iris, as well as by extraocular cells, such as fibrocytes, vascular cells, and muscle cells. All cells involved in the exfoliation syndrome process disclosed common ultrastructural signs of active fibrillogenesis and metabolic activation, such as increased vesicular transport to the cell surface, XFM formation within infoldings of cellular surfaces, and a prominent rough endoplasmic reticulum. Finally, cells involved in the production of XFM displayed a gene expression pattern characterized by the upregulation of elastic components, the transient upregulation of LOXL1, and the dysregulated expression of cytoprotective gene products, matrix metalloproteinases, and their inhibitors, possibly leading to the accumulation and stable deposition of XFM.
EVALuna2:21181

The dynamics of rod and cone driven ERG adaptation using the silent substitution stimulation technique - Kremers, Jan; Joachimsthaler, Anneka (2018)
EVALuna2:34920

The Effect of Long-term Antiglaucomatous Drug Administration on Central Corneal Thickness - Schrems, Wolfgang; Schrems-Hösl, Laura-Maria; Mardin, Christian Y.; Horn, Folkert; Jünemann, Anselm; Kruse, Friedrich; Braun, Joachim M.; Lämmer, Robert (Journal of Glaucoma, 2016)
To evaluate rates of changes per year of central corneal thickness after antiglaucomatous drug administration with ?-blockers, prostaglandin analogs, and carbonic anhydrase inhibitors monotherapy and combined topical antiglaucomatous therapy, in a cohort of patients with ocular hypertension, glaucoma suspects, and patients with perimetric glaucoma as compared with normal controls.This retrospective single-center study included 130 eyes as healthy controls, 121 eyes of ocular hypertensive patients, 105 eyes of glaucoma suspects, and 49 eyes of perimetric glaucoma patients. All patients underwent standard automated perimetry, 24-hour intraocular pressure profile, optic disc photography, and optical coherence pachymetry (OCP; Heidelberg Engineering). The cohort was divided into 8 groups on the basis of topical antiglaucomatous medication. Linear regression analysis was conducted to analyze the relationship between central corneal thickness and exposure to antiglaucomatous medication during the follow-up.Central corneal thickness did not change during the follow-up for investigated diagnostic subgroups. There was a statistically significant decrease in central corneal thickness for eyes treated with prostaglandin monotherapy (-3.1 ?m/y for left eye), and a combined therapy with prostaglandins, carbonic anhydrase inhibitors, and ?-blockers (-5.8 and -3.8 ?m/y for right and left eye, respectively).We recommend regular measurements before and during therapy with prostaglandin monotherapy and a combined therapy with prostaglandins, carbonic anhydrase inhibitors, and ?-blockers. Follow-up intraocular pressure measurements may be underestimated for eyes treated with the aforementioned treatment regimens if central corneal thickness is not measured on a regular basis.
EVALuna2:21177

The effect of sinusoidally modulating backgrounds on flash electroretinograms - Aher, Avinash; Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

The emerging technology of tissue engineering : Focus on stem cell niche - Schlötzer-Schrehardt, Ursula; Freudenberg, U.; Kruse, Friedrich (Ophthalmologe, 2017)
Limbal stem cells reside in a highly specialized complex microenvironment that is known as the stem cell niche, an anatomically protected region at the bottom of the Palisades of Vogt, where the stem cells are located and where their quiescence, proliferation and differentiation are maintained in balance. Besides the epithelial stem and progenitor cell clusters, the limbal niche comprises several types of supporting niche cells and a specific extracellular matrix mediating biochemical and biophysical signals. Stem cell-based tissue engineering aims to mimic the native stem cell niche and to present appropriate microenvironmental cues in a controlled and reproducible fashion in order to maintain stem cell function within the graft. Current therapeutic approaches for ex vivo expansion of limbal stem cells only take advantage of surrogate niches. However, new insights into the molecular composition of the limbal niche and innovative biosynthetic scaffolds have stimulated novel strategies for niche-driven stem cell cultivation. Promising experimental approaches include collagen-based organotypic coculture systems of limbal epithelial stem cells with their niche cells and biomimetic hydrogel platforms prefunctionalized with appropriate biomolecular and biophysical signals. Future translation of these novel regenerative strategies into clinical application is expected to improve long-term outcomes of limbal stem cell transplantation for ocular surface reconstruction.
EVALuna2:21332

The Erlangen Glaucoma Registry: a Scientific Database for Longitudinal Analysis of Glaucoma - Lauterwald, Frank; Neumann, Christoph; Lenz, Richard; Jünemann, Anselm; Mardin, Christian Y.; Meyer-Wegener, Klaus; Horn, Folkert (2011)
UnivIS-Import:2017-12-18:Pub.2011.tech.IMMD.IMMD6.theerl
Keywords: Glaukom; Elektronische Patientenakte; Register; Längsschnittuntersuchung; Wissenschaftliche Datenbank; Relationale Datenbank

The Impact of Luminance and Temporal Frequency on S-Cone-Driven ERGs in Wildtype Mice and Mice with Long-Wavelength Absorption Spectra - Joachimsthaler, Anneka; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

The influence of donor factors on corneal organ culture contamination - Gruenert, Anja K.; Rosenbaum, Katja; Geerling, Gerd; Fuchsluger, Thomas (Acta Ophthalmologica, 2017)
To evaluate the contamination rate and the corresponding spectrum of microbes and to identify donor risk factors for corneal organ culture contaminations.A total of 3306 organ-cultured donor corneas were included in the study. We performed a retrospective database analysis to evaluate donor factors such as gender, age, death-to-explantation interval (DEI), procurement site and cause of death and to determine their influence on donor cornea contaminations. Odds ratios (ORs) were calculated for each factor.The overall contamination rate was 7.8% (n = 259). Younger donor age (OR: 2.2, p = 0.003, chi-squared test), a DEI of more than 24 hr (OR: 1.6, p < 0.001), hospitalization prior to death (OR: 2.2, p < 0.001) and death caused by sepsis (OR: 2.7, p < 0.001) were associated with an increased risk of contamination, whereas donor gender did not have an effect on donor cornea contaminations. The most frequently isolated microbes were Enterococci (19%), Staphylococci (10.8%) and Candida (37.4%).This study helps to estimate the contamination risk of a cultured cornea based on specific donor factors. However, donors with risk factors should not be generally excluded from cornea donation. Further studies including antibiograms might clarify whether a change in the antibiotic composition of the culture medium would be useful to deal with the increasing number of multi-resistant microbes.
EVALuna2:21327

The influence of melanopsin activation on the cone-mediated photopic white noise electroretinogram (wnERG) in humans - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix (Frontiers in Optics, FIO 2018, 2018)

The influence of retinal illuminance on L- and M-cone driven electroretinograms - Kremers, Jan; Parry, Neil R. A.; Panorgias, Athanasios; Murray, Ian J. (Visual Neuroscience, 2011)
The electroretinographic response to L- and M-cone isolating stimuli was measured at different luminance levels to study the effect of retinal illuminance on amplitude and phase, and how this may influence estimates of L:M ratios in the retina. It was found that the amplitude of L- and M-cone driven responses increases differently with increasing retinal illuminance: L-cone responses increase more quickly than those of M-cones. The L:M ratio does not change strongly with retinal illuminance. The phase of both L- and M-cone driven responses advances with increasing retinal illuminance. There is considerable interindividual variability in the phase difference between the two, but generally M-cone driven responses are phase advanced.
EVALuna2:21018

The influence of stimulus size on heterochromatic modulation electroretinograms - Gomes Martins, Cristiane Maria; Tsai, Tina; Salgueiro Barboni, Mirella Telles; Da Costa, Marcelo Fernandes; Nagy, Balazs; Ventura, Dora Fix; Kremers, Jan (Journal of Vision, 2016)
When combined with the electroretinogram (ERG), the heterochromatic flicker photometry procedure allows an objective in vivo assessment of postreceptoral activity. Responses evoked at intermediate (approximately 12 Hz) and high (>30 Hz) temporal frequencies reflect the red-green cone opponent (possibly parvocellular) and the luminance (possibly magnocellular) responses, respectively. Previously, we found that cone-isolating stimuli at intermediate temporal frequencies elicited ERG responses with similar amplitudes and phases for different spatial arrangements of the stimuli, whereas response amplitudes at high temporal frequencies were positively correlated with stimulus size. The purpose of this study was to investigate whether the influence of stimulus size was confined to cone-isolating stimuli or whether it was a general feature of heterochromatic stimulation. Furthermore, we aimed to determine the smallest spatial extent for a significant response in the two postreceptoral mechanisms. Monocular ERGs were recorded to red-green counterphase modulated sinusoidal stimuli (mean luminance of 200 cd/m2) presented at 12 and 36 Hz at different stimulus sizes. At each stimulus condition, a series of ERGs were recorded with the red-contrast fraction (FR) [FR = CR/(CR + CR)] of the stimulus varying between 0.0 and 1.0. Response amplitudes at 36 Hz changed with FR for all subjects, exhibiting a V-shaped amplitude profile with a minimum close to the psychophysics-based isoluminance, where the ERG phase changed by 180°. As stimulus size decreased, the amplitudes to 36 Hz also decreased. In contrast, amplitudes and phases at 12 Hz generally were constant for all values of FR. These amplitudes were invariant to stimulus sizes larger than 10° but decreased with decreasing stimulus size below 10°. Phase also changed in this range. Thus, luminance pathway ERG responses (36 Hz) show direct dependency on stimulus size, whereas chromatic pathway responses (12 Hz) are independent of the stimulus size above 10°.
EVALuna2:21293

The influence of stimulus size on L- and M-cone driven electroretinograms - Jacob, Mellina Monteiro; Gomes, Bruno Duarte; Souza, Givago S.; Da Silva, Manoel; Mckeefry, Declan J.; Parry, Neil Robert Alan; Silveira, Luiz Carlos L.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
Keywords: 510 electroretinography: non-clinical; 688 retina; 471 color vision

The influence of trace elements on the therapeutic success of suprachoroidal draining devices - Wörn, Maximilian; Lämmer, Robert; Lucio, Marianna; Michalke, Bernhard; Rühl, Eva; Hohberger, Bettina (Journal of Trace Elements in Medicine and Biology, 2023)
Purpose: The therapeutic success of minimal invasive glaucoma surgery (MIGS) is challenging due to many factors including fibrotic or occlusive events. Recent clinical data show sudden peaks of intraocular pressure (IOP) in the postoperative care of glaucoma patients after suprachoroidal draining stents. Yet, the reasons for the IOP peaks are speculative. As a link between trace elements and fibrosis had been previously observed in systemic disorders, the present study aimed to investigate the impact of trace elements on the therapeutic success of the suprachoroidal draining stents in patients with open-angle glaucoma (OAG). Material and Methods: An analysis of a prospective single-center study was done: fifty-five eyes of patients with OAG (29 female, 26 male) underwent Cypass Micro-Stent implantation either as a stand-alone procedure or combined with cataract surgery. All patients underwent pre-operatively an ophthalmological examination which included slit lamp biomicroscopy and fundoscopy. IOP was measured by Goldmann applanation tonometry. Functional and morphometric data were assessed by Octopus G1-perimetry, which included measurement of retinal nerve fiber layer thickness (Spectralis OCT). Data of the patients’ follow-ups were recorded during 18 months post-operatively. The therapeutic success of CyPass Micro-Stent was classified as ‘success’ (IOP reduction ≥20% compared to a pre-operative baseline without any medication), ‘qualified success’ (IOP reduction ≥20 % with same or lower additional eye medication), and ‘failure’ (IOP reduction ≤20 % or additional surgical treatment necessary). Aqueous humour was extracted once during surgery for analysis of the level of 14 trace elements: Copper (Cu), Cadmium (Cd), Cobalt (Co), Chromium (Cr), Iron (Fe), Lithium (Li), Magnesium (Mg), Manganese (Mn), Phosphorus (P), Lead (Pb), Titanium (Ti), Uranium (U), Vanadium (V), and Zinc (Zn). Analysis of the trace elements was done using an ELEMENT 2, ICP-sf-MS instrument (Thermo-Fisher Scientific, Bremen, Germany). Analysis of levels of trace elements was done across the patients’ groups of the three subclasses of therapeutic success. Statistical investigations for substantial differences were conducted using the method of least squares to fit general linear models and mixed models. The last one for the repeated measurements of IOP. Results: Levels of Mg were significantly lower one month postoperatively in the success group (LS-Mean 1.30 mg/L) compared to the qualified success group (LS-Mean 1.22 mg/L; p-value = 0.04). Fe was significantly increased in the failure group (LS-Mean 2.07 µg/L) compared to the qualified success group (LS-Mean 1.64 µg/L; p-value = 0.019) after 3 months of follow-up. Additionally, Fe levels were significantly lower in the success group (LS-Mean 1.47 µg/L) compared to the failure cohort (LS-Mean 2.07 µg/L; p-value = 0.009). After a period of 18 months, significantly higher levels of Mn were observed in the success group (LS-Mean 1.24 µg/L) than in the failure group (LS Mean 0.30 µg/L, p-value = 0.019). Conclusion: The present data might suggest that trace elements can influence therapeutic success of suprachoroidal draining devices postoperatively and thus offer first hints for potential novel therapeutic options.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Fibrosis; Glaucoma; Suprachoroidal draining stents; Surgery; Trace elements

The light adaptation phenomenon in human: receptoral and post-receptoral involvement - Brasil, Alodia; Tsai, Tina I.; Souza, Givago S.; Herculano, Anderson Manoel; Ventura, Dora Fix; Silveira, Luiz Carlos L.; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)

The limbal epithelial stem cell niche in aniridia-related keratopathy - Kruse, Friedrich; Latta, Lorenz; Holbach, Leonard; Kaesmann-Kellner, Barbara; Seitz, Berthold; Schlötzer-Schrehardt, Ursula (2018)
EVALuna2:34736

The melanopsin-directed white noise electroretinogram (wnERG) - Adhikari, Prakash; Zele, Andrew J.; Cao, Dingcai; Kremers, Jan; Feigl, Beatrix (Vision research, 2019)
The white noise electroretinogram (wnERG) provides a measure of the impulse response function under conditions of retinal equilibrium; it is yet to be determined how the electrical response generated by melanopsin ganglion cell photoreception is expressed in the impulse response. To this end, we recorded the human wnERG to continuous temporal white noise (TWN) stimuli that were melanopsin-directed (rod and cone silent) or cone-directed (rod and melanopsin silent). The impulse response of the electroretinogram was derived by cross-correlating the TWN stimulus with the wnERG response. We observed that the LMS-cone directed wnERG contained the expected N1 wave (24.1 ± 2.4 ms; mean ± SEM) and P1 wave (49.7 ± 1.8 ms). Melanopsin-directed stimuli produced a unique wnERG with a slower negative deflection (Nm) at 62.9 ± 3.3 ms followed by a positive deflection (Pm) at 126.3 ± 5.1 ms. Additional experiments indicated this melanopsin-directed wnERG response was not due to cone intrusion. The Nm and NmPm amplitudes increased with illuminance (32,000–80,000 Td; no rod intrusion) and melanopsin contrast (10–36% Michelson contrast). As there are known pathways connecting melanopsin cells to the outer retina, we then measured the wnERG to combined melanopsin and cone-directed stimuli to quantify melanopsin interactions with cone signalling. With the combined stimuli, the N1P1 amplitudes were suppressed by 59%, which may be a result of a destructive interference between the positive (P1) and negative (Nm) waves generated by the cone and melanopsin pathways. We conclude that the human wnERG to melanopsin-directed stimuli may reflect the combined response of intra-retinal melanopsin pathways, independent of rod and cone photoreception.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Electroretinogram; Melanopsin; Silent substitution; White noise electroretinogram (wnERG)

The morphology of human rod ERGs obtained by silent substitution stimulation - Maguire, J.; Parry, N. R. A.; Kremers, Jan; Murray, I. J.; Mckeefry, D. (Documenta Ophthalmologica, 2017)
To record transient ERGs from the light-adapted human retina using silent substitution stimuli which selectively reflect the activity of rod photoreceptors. We aim to describe the morphology of these waveforms and examine how they are affected by the use of less selective stimuli and by retinal pathology.Rod-isolating stimuli with square-wave temporal profiles (250/250 ms onset/offset) were presented using a 4 primary LED ganzfeld stimulator. Experiment 1: ERGs were recorded using a rod-isolating stimulus (63 ph Td, rod contrast, C rod = 0.25) from a group (n = 20) of normal trichromatic observers. Experiment 2: Rod ERGs were recorded from a group (n = 5) using a rod-isolating stimulus (C rod = 0.25) which varied in retinal illuminance from 40 to 10,000 ph Td. Experiment 3: ERGs were elicited using 2 kinds of non-isolating stimuli; (1) broadband and (2) rod-isolating stimuli which contained varying degrees of L- and M-cone excitation. Experiment 4: Rod ERGs were recorded from two patient groups with rod monochromacy (n = 3) and CSNB (type 1; n = 2).The rod-isolated ERGs elicited from normal subjects had a waveform with a positive onset component followed by a negative offset. Response amplitude was maximal at retinal illuminances <100 ph Td and was virtually abolished at 400 ph Td. The use of non-selective stimuli altered the ERG waveform eliciting more photopic-like ERG responses. Rod ERGs recorded from rod monochromats had similar features to those recorded from normal trichromats, in contrast to those recorded from participants with CSNB which had an electronegative appearance.Our results demonstrate that ERGs elicited by silent substitution stimuli can selectively reflect the operation of rod photoreceptors in the normal, light-adapted human retina.
EVALuna2:21335

The papilla as screening parameter for early diagnosis of glaucoma - Michelson, Georg; Hornegger, Joachim; Wärntges, Simone; Lausen, Berthold (Deutsches Ärzteblatt, 2008)
Introduction: In the industrialized countries 67 million people suffer from glaucoma, which represents the third most common cause of blindness and thus has a high economic impact. Early diagnosis of glaucoma, which does not necessarily involve raised intraocular pressure, is essential because by the time the patient notices functional impairment the damage is irreversible. Early treatment can decrease the rate of blindness 20 years later by about 50%. Methods: Selective literature review and clinical investigation of early glaucoma detection and of screening methods. Results: Currently, no evidence-based recommendations for glaucoma screening can be found in the literature. No single method or combination of screening procedures can be recommended unambiguously on economic grounds. Discussion: From the clinical perspective sensitive, specific, and cost-effective glaucoma screening seems feasible. The high-risk group would need to be defined on the basis of age and family history. A two-stage screening process would then have to be established with initial computer-supported telemedical sorting followed by telemedical ophthalmological diagnosis of cases selected for clarification.

The photopic negative response of the blue-on-yellow flash-electroretinogram in glaucomas and normal subjects - Wakili, Nina; Horn, Folkert; Jünemann, Anselm; Nguyen, Nhung; Mardin, Christian Y.; Korth, Matthias-Johannes; Kremers, Jan (Documenta Ophthalmologica, 2008)
The photopic negative response of the flash-electroretinogram driven by the middle- and long-wavelength cones has been shown to be reduced in non-human primates with experimental glaucoma and in human patients with glaucoma. The photopic negative response for the blue-sensitive response has been studied using a blue-green silent-substitution-technique on a red background. The aim of this study was to re-evaluate the value of the photopic negative response of the blue-sensitive pathway in glaucoma using a conventional flash-electroretinogram. In 37 eyes of 37 controls (age: 53 +/- 13.6 years) and 37 eyes of 37 patients with open-angle glaucoma of different perimetric visual field defects (age: 58.3 +/- 10 years; MD: 11.7 +/- 6.7 dB) of the Erlangen glaucoma registry Ganzfeld flash-electroretinograms (LKC, UTAS 3000) were recorded using blue Xenon-flashes of increasing photopic luminance (0.013, 0.018, 0.030, and 0.052 cd s/m(2); 440 nm) on a bright yellow background (238 cd/m(2); 550 nm) after 2 min of light adaptation. Amplitudes and implicit times of the photopic negative response and of L&M-cone- and S-cone-driven b-waves were compared between glaucomas and controls for all flash energies (unpaired t-test). The amplitudes of the photopic negative response were significantly reduced in glaucoma patients for all flash energies (P < 0.001). The implicit times of L&M-cone-driven b-wave (0.013, 0.018, 0.030, and 0.052 cd s/m(2)) and S-cone-driven b-wave (0.030 and 0.052 cd s/m(2)) were significantly prolonged in glaucoma patients (P < 0.05). The changes in these implicit times, however, are very small (1.5 ms or less). The other measures did not differ significantly. The amplitude of the photopic negative response and the implicit times of the L&M-cone and S-cone b-wave in the same responses of the blue-on-yellow flash-electroretinogram are potentially useful in the evaluation of inner-retinal function in glaucoma.
Keywords: electroretinogram; glaucoma; L&M-cone; photopic negative response; S-cone

The photopic negative response of the Light-adapted 3.0 ERG in clinical settings - Ortiz, Gonzalo; Drucker, David; Hyde, Connor; Staffetti, Joseph; Kremers, Jan; Tzekov, Radouil (Documenta Ophthalmologica, 2019)
Purpose To analyze the effects of different methods of measurement on the photopic negative response (PhNR), recorded as part of a standard ISCEV Photopic 3.0 ERG responses from patients with a variety of clinical diagnoses. Methods ERGs were recorded from both eyes of 97 patients (187 eyes) as part of a standard clinical assessment. The average age was 56.4 +/- 15.7 years, the gender balance was 35 M, 62F, and only recordable responses of acceptable quality were included. PhNR was measured at an identifiable trough before (PhNR1) and after the i-wave (PhNR2), and the amplitudes and peak times were compared with a-, b- and i-wave corresponding parameters. PhNR components were measured: from baseline and from b-wave peak. Correlation between PhNR troughs and with ERG parameters were tested for right eyes. The possibility to predict and substitute PhNR2 amplitude from PhNR1 amplitude was also tested. Results PhNR1 was recordable in 97.3% of eyes and PhNR2 in 85.6%. An identifiable PhNR2 peak was found to occur before 65 ms at similar to 50% of the records, while in similar to 38% of the cases was within 65-75 ms in similar to 12%-after 75 ms. The correlation between the PhNR1 and PhNR2 peaks was quite strong (with coefficients 0.81-0.98, depending on method of measurement, and slopes close to 1). The average difference between predicted and measured PhNR2 was reasonably small in absolute (< 2 mu V) and relative (< 2%) terms. The correlations between PhNR amplitudes and other ERG component amplitudes showed different ranges of correlation coefficients depending on the method of measurement: for the a-wave amplitudes the range of coefficients was 0.48-0.73, while for the b-wave amplitudes it was 0.30-0.95 and 0.39-0.65 for i-wave. Conclusion The strong correlation between the two PhNR troughs could allow using PhNR1 when PhNR2 is poorly defined due to artifacts. Different methods of PhNR measurement lead to different correlations with other ERG parameters, and this needs to be considered when analyzing and comparing PhNR data between studies.
CRIS-Team WoS Importer:2019-10-25

The Photoreceptor Ribbon Synapse in the Absence of Piccolo: An RNAi Approach - Regus-Leidig, Hanna; Atorf, Jenny; Feigenspan, Andreas; Boye, S.; Chiodo, V.; Seigel, G. M.; Hauswirth, W. W.; Kremers, Jan; Brandstätter, Johann Helmut (Investigative Ophthalmology & Visual Science, 2010)
Keywords: photoreceptors; synapse

The protective variant rs7173049 at LOXL1 locus impacts on retinoic acid signaling pathway in pseudoexfoliation syndrome - Berner, Daniel; Hoja, Ursula; Zenkel, Matthias; Ross, James Julian; Uebe, Steffen; Paoli, Daniela; Frezzotti, Paolo; Rautenbach, Robyn M.; Ziskind, Ari; Williams, Susan E.; Carmichael, Trevor R.; Ramsay, Michele; et al. (Human Molecular Genetics, 2019)
LOXL1 (lysyl oxidase-like 1) has been identified as the major effect locus in pseudoexfoliation (PEX) syndrome, a fibrotic disorder of the extracellular matrix and frequent cause of chronic open-angle glaucoma. However, all known PEX-associated common variants show allele effect reversal in populations of different ancestry, casting doubt on their biological significance. Based on extensive LOXL1 deep sequencing, we report here the identification of a common non-coding sequence variant, rs7173049A>G, located downstream of LOXL1, consistently associated with a decrease in PEX risk (odds ratio, OR=0.63; P=6.33x10(-31)) in nine different ethnic populations. We provide experimental evidence for a functional enhancer-like regulatory activity of the genomic region surrounding rs7173049 influencing expression levels of ISLR2 (immunoglobulin superfamily containing leucine-rich repeat protein 2) and STRA6 [stimulated by retinoic acid (RA) receptor 6], apparently mediated by allele-specific binding of the transcription factor thyroid hormone receptor beta. We further show that the protective rs7173049-G allele correlates with increased tissue expression levels of ISLR2 and STRA6 and that both genes are significantly downregulated in tissues of PEX patients together with other key components of the STRA6 receptor-driven RA signaling pathway. siRNA-mediated downregulation of RA signaling induces upregulation of LOXL1 and PEX-associated matrix genes in PEX-relevant cell types. These data indicate that dysregulation of STRA6 and impaired retinoid metabolism are involved in the pathophysiology of PEX syndrome and that the variant rs7173049-G, which represents the first common variant at the broad LOXL1 locus without allele effect reversal, mediates a protective effect through upregulation of STRA6 in ocular tissues.
CRIS-Team WoS Importer:2019-11-12

Therapeutic Value of Ginkgo biloba Extract EGb 761® in an Animal Model (Meriones unguiculatus) for Noise Trauma Induced Hearing Loss and Tinnitus - Krauß, Patrick; Tziridis, Konstantin; Buerbank, Stefanie; Schilling, Achim; Schulze, Holger (PLoS ONE, 2016)
Noise induced hearing loss (NIHL) is a common disease in modern societies and may lead to maladaptations within the auditory system that finally result in subjective tinnitus. Available therapies may only alleviate the symptoms rather than restore normal hearing. In a previous study we demonstrated that the prophylactic application of Ginkgo biloba extract EGb 761® significantly reduces NIHL and tinnitus development in our Mongolian gerbil (Meriones unguiculatus) animal model. Here, we tested whether the application of EGb 761® has beneficial effects after the formation of permanent NIHL and tinnitus. To this end we monitored the therapeutic effects of EGb 761® on noise trauma-induced changes in signal processing within the auditory system of our animal model by behavioral (acoustic startle response, ASR) and electrophysiological approaches (auditory brainstem responses, ABR). We found that-in contrast to vehicle-three weeks of daily oral EGb 761® treatment (100 mg/kg body weight) led to a restoration of hearing thresholds back to pre-trauma conditions. In addition, all 9 animals that displayed behavioral signs of subjective tinnitus showed improvement, with 7 of them showing complete relief of tinnitus symptoms during the time of EGb 761® treatment. After discontinuation of EGb 761® treatment, tinnitus related behavior reappeared in all but one of these animals while auditory thresholds remained restored. A detailed analysis of ABR waves revealed that EGb 761® treatment did not simply change auditory processing back to pre-trauma conditions, but led to subtle changes of ABR wave amplitude and latency at different levels of the auditory pathway, with an overall increase of response to low stimulus intensities and a decrease at high intensities. The functional relevance of these changes may be the observed improvement of hearing thresholds while at the same time suppression of responses to high stimulus intensities may point to a global inhibitory mechanism that counteracts tinnitus.
EVALuna2:20023

Therapy-associated corneal pathologies - Fuchsluger, Thomas; Geerling, G. (Ophthalmologe, 2017)
EVALuna2:21345

Therapy options for malignant eyelid tumors - Weiling, Max; Bergua, A.; Kruse, Friedrich; Holbach, L. (Ophthalmologe, 2016)
Basal cell carcinomas are the most common malignant tumors of the eyelids. Patient history, clinical symptoms and signs, inspection, palpation and slit-lamp examination usually allow a working diagnosis; however, the clinical diagnosis requires histopathological confirmation and determination of the histopathological type. Squamous cell carcinomas, sebaceous gland carcinomas, melanomas and Merkel cell carcinomas can metastasize usually via the lymph vessels into the regional lymph nodes. Microscopically controlled excision of the primary tumor into healthy tissue is most commonly the first goal. Palpation and ultrasonography of the regional lymph nodes and also computed tomography (CT) with contrast enhancement and magnetic resonance imaging (MRI) for tumors with perineural sheath cell invasion are necessary to define the TNM stage. Non-surgical treatment options are becoming more popular in the further management of malignant eyelid tumors.
EVALuna2:21311

The role of lysyl oxidase-like 1 (LOXL1) in exfoliation syndrome and glaucoma - Schlötzer-Schrehardt, Ursula; Zenkel, Matthias (Experimental Eye Research, 2019)
Exfoliation syndrome (XFS) is an age-related systemic disease that affects the extracellular matrix. It increases the risk of glaucoma (exfoliation glaucoma, XFG) and susceptibility to diseases of elastin-rich connective tissues. LOXL1 (lysyl oxidase-like 1) is still recognized as the major genetic effect locus in XFS and XFG in all populations worldwide, although its genetic architecture is incompletely understood. LOXL1 is a key cross-linking enzyme in elastic fiber formation and remodeling, which is compatible with the pathogenetic concept of XFS as a specific type of elastosis. This review provides an overview on the current knowledge about the role of LOXL1 in the etiology and pathophysiology of XFS and XFG. It covers the known genetic associations at the LOXL1 locus, potential mechanisms of gene regulation, implications of LOXL1 in XFS-associated fibrosis and connective tissue homeostasis, its role in the development of glaucoma and associated systemic diseases, and the currently available LOXL1-based in vivo and in vitro models. Finally, it also identifies gaps in knowledge and suggests potential areas for future research.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Elastic fibers; Exfoliation glaucoma; Exfoliation syndrome; Extracellular matrix; LOXL1; Lysyl oxidase-like 1; Pseudoexfoliation syndrome

The role of TCF4 in the pathophysiology of Fuchs endothelial corneal dystrophy - Sato, Masakazu; Okumura, Naoki; Nakahara, Makiko; Sato, Takahiko; Kitazawa, Koji; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (2018)
EVALuna2:34737

The spatial distribution of ERGs reflecting luminance and L-/M-cone-opponent signals - Vidal, Kallene Summer; Aher, Avinash; Ventura, Dora Fix; Kremers, Jan (Documenta Ophthalmologica, 2021)
Purpose: To study the spatial retinal distribution of electroretinographic (ERG) responses that reflect signals in the L-/M-cone-opponent and luminance post-receptoral pathways. Methods: ERG recordings to heterochromatic stimuli (sinusoidal counter-phase modulation of red and green LED light sources) were performed, while varying fractions of red and green modulation. Two temporal frequencies of the stimuli were employed: 12 Hz to record ERGs that reflect L-/M-cone-opponent signal and 36 Hz for recording ERG signals sensitive to stimulus luminance. Stimuli were about 20° in diameter and projected on various retinal locations: the fovea and four eccentricities (10°, 19°, 28° and 35°), each presented nasally, temporally, inferiorly and superiorly from the fovea. Results: The 36 Hz stimuli elicited responses that strongly varied with red fraction and were minimal at iso-luminance. Moreover, response phases changed abruptly at the minimum by 180°. In contrast, the responses to the 12 Hz stimuli had amplitudes and phases that changed more gradually with red fraction. The 36 Hz response amplitudes were maximal close to the fovea and sharply decreased with increasing distance from the fovea. The responses to 12 Hz stimuli were more broadly distributed across the retina. Conclusions: In the present study, it was found that retinal eccentricity and direction from the fovea have distinct effects on ERGs reflecting different post-receptoral mechanisms. The results are in accord with previous findings that ERGs to 12 Hz stimuli are predominantly determined by the red–green chromatic content of the stimuli, thus reflecting activation in the L-/M-cone-opponent pathway, while responses to 36 Hz stimuli manifest post-receptoral luminance-dependent activation. We found that the response in the cone-opponent pathway is broadly comparable across the retina; in comparison, response amplitude of the luminance pathway strongly depends on retinal stimulus position.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cone opponency; Electroretinography; Luminance; Post-receptoral pathways; Spatial distribution

The Spatial Distribution of L- and M-Cone Driven ERGs Reflecting Parvo- and Magnocellular Activity - Gomes, Bruno; Souza, Givago; Filho, Manoel; Pangeni, Gobinda; Silveira, Luiz Carlos; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Keywords: 688 retina; 510 electroretinography: non-clinical; 508 electrophysiology: non-clinical

The spatial extent of lateral interactions in flicker perception - Kremers, Jan; Rimmele, Ulrike (Vision research, 2007)
We investigated the influence of the relative phase of a temporally modulated annulus on the perceived flicker strength of a center stimulus having the same temporal modulation. These measurements were performed in two subjects at two temporal frequencies and with different outer diameters of the annulus. The perceived flicker strength was strongly modulated by the phase difference between center and surround stimulus. This modulation depended on the size of the annulus. In the absence of an annulus the perceived flicker strength was not modulated. The modulation initially increased with increasing annulus size and reached a plateau. The space constant of the function describing the modulation as a function of annulus size was about 0.5 degrees and is similar to the sizes of receptive field surrounds of subcortical cells. This finding is in favor of the hypothesis that the physiological basis of the perceived flicker strength in the center stimulus is present already at a subcortical level. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: lateral interactions; flicker; psychophysics; linking hypothesis

The spatial properties of L- and M-cone inputs to electroretinograms that reflect different types of post-receptoral processing - Jacob, Mellina M.; Pangeni, Gobinda; Gomes, Bruno D.; Souza, Givago S.; Da Silva Filho, Manoel; Silveira, Luiz Carlos L.; Maguire, John; Parry, Neil R. A.; Mckeefry, Declan J.; Kremers, Jan (PLoS ONE, 2015)
We studied the spatial arrangement of L- and M-cone driven electroretinograms (ERGs) reflecting the activity of magno- and parvocellular pathways. L- and M-cone isolating sine wave stimuli were created with a four primary LED stimulator using triple silent substitution paradigms. Temporal frequencies were 8 and 12 Hz, to reflect cone opponent activity, and 30, 36 and 48 Hz to reflect luminance activity. The responses were measured for full-field stimuli and for different circular and annular stimuli. The ERG data confirm the presence of two different mechanisms at intermediate and high temporal frequencies. The responses measured at high temporal frequencies strongly depended upon spatial stimulus configuration. In the full-field conditions, the L-cone driven responses were substantially larger than the full-field M-cone driven responses and also than the L-cone driven responses with smaller stimuli. The M-cone driven responses at full-field and with 70° diameter stimuli displayed similar amplitudes. The L- and M-cone driven responses measured at 8 and 12 Hz were of similar amplitude and approximately in counter-phase. The amplitudes were constant for most stimulus configurations. The results indicate that, when the ERG reflects luminance activity, it is positively correlated with stimulus size. Beyond 35° retinal eccentricity, the retina mainly contains L-cones. Small stimuli are sufficient to obtain maximal ERGs at low temporal frequencies where the ERGs are also sensitive to cone-opponent processing.
EVALuna2:21160

The transcription factor Foxk1 is expressed in developing and adult mouse neuroretina - Sel, Saadettin; Muenzenberg, Christoph; Nass, Norbert; Kalinski, Thomas; Datan, Maja; Auffarth, Gerd U.; Toeteberg-Harms, Marc; Zenkel, Matthias; Kruse, Friedrich; Paulsen, Friedrich; Schicht, Martin (Gene Expression Patterns, 2013)
The forkhead transcription factor Foxk1 is an important regulator of myogenic progenitor cells. Since our previous data from mouse retina revealed that Foxk1 is upregulated in Ptf1a-deficient mice we investigated the spatial and temporal expression of Foxk1 during development of mouse retina. Expression of Foxk1 was analyzed on both mRNA and protein level. To identify Foxk1 transcripts, retina and cerebrum (positive control) of adult animals (postnatal day 90 (P90)) was subjected to reverse transcription polymerase chain reaction (RT-PCR) and sequencing of the amplified cDNA. The Foxk1 protein was analyzed in adult retina by Western blotting and in developing eyes at embryonic day (E) 13, 15, E17, P0, P4, P7, P10 and P90 by immunohistochemistry. Localization of Foxk1 expression was determined using cell-specific markers by double labelling. Foxk1 transcripts were detected in adult retina by RT-PCR and confirmed by sequencing. Western blot analysis confirmed the expression of Foxk1 protein in the adult retina. Immunohistochemical examination of developing eyes localized the protein to bipolar, amacrine and ganglion cells with an onset of Foxk1 expression from E15 onwards. The expression pattern during development suggests that Foxk1 may have an important role in retinal cells. © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Foxk1; Retinal development; Retinogenesis; Transcription factor

Thickness related textural properties of retinal nerve fiber layer in color fundus images - Odstrcilik, Jan; Kolar, Radim; Tornow, Ralf-Peter; Jan, Jiri; Budai, Attila; Mayer, Markus Anton; Vodakova, Martina; Lämmer, Robert; Lamos, Martin; Kuna, Zdenek; Gazarek, Jiri; Kubena, Tomas; et al. (Computerized Medical Imaging and Graphics, 2014)
Images of ocular fundus are routinely utilized in ophthalmology. Since an examination using fundus camera is relatively fast and cheap procedure, it can be used as a proper diagnostic tool for screening of retinal diseases such as the glaucoma. One of the glaucoma symptoms is progressive atrophy of the retinal nerve fiber layer (RNFL) resulting in variations of the RNFL thickness. Here, we introduce a novel approach to capture these variations using computer-aided analysis of the RNFL textural appearance in standard and easily available color fundus images. The proposed method uses the features based on Gaussian Markov random fields and local binary patterns, together with various regression models for prediction of the RNFL thickness. The approach allows description of the changes in RNFL texture, directly reflecting variations in the RNFL thickness. Evaluation of the method is carried out on 16 normal ("healthy") and 8 glaucomatous eyes. We achieved significant correlation (normals: ?=0.72±0.14; p<<0.05, glaucomatous: ?=0.58±0.10; p<<0.05) between values of the model predicted output and the RNFL thickness measured by optical coherence tomography, which is currently regarded as a standard glaucoma assessment device. The evaluation thus revealed good applicability of the proposed approach to measure possible RNFL thinning.
EVALuna2:21169

Threshold Optimization for Tumor Markers S100b and MIA in Uveal Melanoma - A Single Center Analysis - Glaser, Naemi; Petzold, Anne; Wessely, Anja; Kaufmann, Matthias; Koch, Elias; Knorr, Harald; Voskens, Caroline; Heppt, Markus; Berking, Carola; Erdmann, Michael (Anticancer Research, 2023)
Background/Aim: Uveal melanoma (UM) is the most common malignant tumor of the eye in adults. Metastases develop in 50% of the patients, predominantly in the liver. In UM, the cut-off concentrations of the bloodbased tumor markers S100b and MIA are inconclusive. Patients and Methods: In this retrospective monocenter study, we statistically evaluated 1,878 S100b and 1,768 MIA measurements in 244 patients with UM from 2011-2020. Threshold optimization was performed using receiver operating characteristic (ROC) curves. Results: A total of 171 patients with non-metastatic UM (nmUM) and 73 patients with metastatic UM (mUM) showed no differences in sex, age at diagnosis or the affected eye. In mUM, 80% of the patients developed metastases to the liver at a median of 46 months after initial diagnosis. The sensitivity and specificity of S100b was 16.10% and 94.52%, and that of MIA was 31.86% and 81.42%, respectively. ROC curves revealed poor values for the area under the curve of 0.57 for S100b and 0.55 for MIA. The optimal cut-off concentration to detect metastases was 0.14 μg/l for S100b and 17.4 ng/ml for MIA. With at least one tumor marker elevated, optimized sensitivity was 20.40% and specificity 96.76%. Conclusion: Current thresholds for S100b and MIA in UM are not able to detect early metastatic disease and require additional diagnostics to clarify false positive results. Threshold optimization considering both S100b and MIA results in a better diagnostic validity with an acceptable specificity and a poor sensitivity. Highly sensitive blood-based and imaging methods to detect metastases early in UM are urgently needed.
CRIS-Team Scopus Importer:2023-11-03
Keywords: MIA; S100b; threshold optimization; tumor marker; Uveal melanoma

Thrombospondin 1 inhibits inflammatory lymphangiogenesis by CD36 ligation on monocytes - Cursiefen, Claus; Maruyama, Kazuichi; Bock, Felix; Saban, Daniel; Sadrai, Zahra; Lawler, Jack; Dana, Reza; Masli, Sharmila (Journal of Experimental Medicine, 2011)
Lymphangiogenesis plays an important role in tumor metastasis and transplant outcome. Here, we show that thrombospondin-1 (TSP-1), a multifunctional extracellular matrix protein and naturally occurring inhibitor of angiogenesis inhibits lymphangiogenesis in mice. Compared with wild-type mice, 6-mo-old TSP-1-deficient mice develop increased spontaneous corneal lymphangiogenesis. Similarly, in a model of inflammation-induced corneal neovascularization, young TSP-1-deficient mice develop exacerbated lymphangiogenesis, which can be reversed by topical application of recombinant human TSP-1. Such increased corneal lymphangiogenesis is also detected in mice lacking CD36, a receptor for TSP-1. In these mice, repopulation of corneal macrophages with predominantly WT mice via bone marrow reconstitution ameliorates their prolymphangiogenic phenotype. In vitro, exposure of WT macrophages to TSP-1 suppresses expression of lymphangiogenic factors vascular endothelial growth factor (VEGF)-C and VEGF-D, but not of a primarily hemangiogenic factor VEGF-A. Inhibition of VEGF-C is not detected in the absence or blockade of CD36. These findings suggest that TSP-1, by ligating CD36 on monocytic cells, acts as an endogenous inhibitor of lymphangiogenesis.
EVALuna2:21017

Time course of induced astigmatism after canaloplasty - Moelle, Michaela C.; Cursiefen, Claus; Rejdak, Robert; Horn, Folkert; Jünemann, Anselm (Journal of Glaucoma, 2014)
To study the changes in astigmatism after canaloplasty and to analyze its correlation with long-term intraocular pressure (IOP) results.Twenty-six eyes of 26 consecutive patients with primary open-angle glaucoma (n=14) and pseudoexfoliative glaucoma (n=12) undergoing canaloplasty were included in this retrospective study. Canaloplasty comprised of 360-degree catheterisation of Schlemm canal by means of a flexible microcatheter with distension of the canal by 2 tensioning 10-0 polypropylene sutures. Primary outcome measures included IOP, glaucoma medication usage, astigmatism, and adverse events at 2, 4, 12, and 24 weeks postoperatively.The mean preoperative IOP was 21.1±5.8 mm Hg. The mean IOP decreased to 14.25 ±4.3 mm Hg at 6 months. Mean astigmatism preoperatively was 0.77±0.5 D, which increased to 3.3±1.7 D at 2 weeks postoperatively (P<=0.05; Wilcoxon-test). Thereafter, the astigmatism underwent a spontaneous decline, reaching 1.9±0.8 D at 4 weeks and 1.2±0.74 D at 12 weeks postoperatively. Best-corrected visual acuity did not change significantly. Six months after canaloplasty, mean astigmatism reached the preoperative range of 0.86±0.52 D. Astigmatism at 2 weeks correlated significantly and inversely with IOP at 6 months (r=0.59, P=0.005; Spearman).The change of astigmatism after canaloplasty follows a clear time course with a maximum at 2 weeks reaching preoperative values at 6 months. The amount of surgically induced astigmatism might be helpful to predict outcome of canaloplasty in terms of IOP reduction.
EVALuna2:21164

Time-dependent morphological alterations and viability of cultured human trabecular cells after exposure to Trypan blue - Tsaousis, Konstantinos; Kopsachilis, Nikolaos; Tsinopoulos, Ioannis T.; Dimitrakos, Stavros A.; Kruse, Friedrich; Welge-Luessen, Ulrich (Clinical and Experimental Ophthalmology, 2013)
To determine the time-dependent toxicity of Trypan blue at 0.06% concentration in cultured human trabecular meshwork cells.Human trabecular meshwork cells cultured in vitro were exposed to Trypan blue and acute toxicity was evaluated. Cells were exposed for 5, 30, 60 s and for 5, 15, 30, 60 min to a commercially available Trypan blue preparation (Vision Blue; DORC International Zuidland, The Netherlands). Morphology was observed by phase-contrast microscopy and cell viability was measured using Hoechst 33342 (Intergen; Purchase, NY, USA) and propidium iodide assays to determine the percentage of living and dead cells.Morphological changes occurred mainly after 5 min of exposure to Trypan blue. Viability was 96.0% ± 3.6%, 94.8% ± 3.5% and 92.5% ± 4.4% after 5, 30 and 60 s of exposure, respectively; a significant toxic effect of Trypan blue was observed after 5, 15, 30 and 60 min of exposure with a viability of 85.0% ± 3.7%, 77.0% ± 6.7%, 70.8% ± 5.9% and 68.3% ± 8.7%, respectively.Trypan blue is not toxic, in terms of cell viability, over an exposure time of up to 60 s; however, further exposure results in a gradual increase in damage of cultured human trabecular meshwork cells.
EVALuna2:21109

Topical application of soluble CD83 induces IDO-mediated immune modulation, increases Foxp3+ T cells, and prolongs allogeneic corneal graft survival - Bock, Felix; Roessner, Susanne; Onderka, Jasmine; Lechmann, Matthias; Pallotta, Maria Teresa; Fallarino, Francesca; Boon, Louis; Nicolette, Charles; Debenedette, Mark A.; Tcherepanova, Irina Y.; Grohmann, Ursula; Steinkasserer, Alexander; et al. (Journal of Immunology, 2013)
Modulation of immune responses is one of the main research aims in transplant immunology. In this study, we investigate the local immunomodulatory properties of soluble CD83 (sCD83) at the graft-host interface using the high-risk corneal transplantation model. In this model, which mimics the inflammatory status and the preexisting vascularization of high-risk patients undergoing corneal transplantation, allogeneic donor corneas are transplanted onto sCD83-treated recipient animals. This model allows the direct and precise application of the immune modulator at the transplantation side. Interestingly, sCD83 was able to prolong graft survival after systemic application as well as after topical application, which is therapeutically more relevant. The therapeutic effect was accompanied by an increase in the frequency of regulatory T cells and was mediated by the immune-regulatory enzyme IDO and TGF-?. In vitro, sCD83 induced long-term IDO expression in both conventional and plasmacytoid dendritic cells via autocrine or paracrine production of TGF-?, a cytokine previously shown to be an essential mediator of IDO-dependent, long-term tolerance. These findings open new treatment avenues for local immune modulation after organ and tissue transplantation.
EVALuna2:21223

Topical cyclosporine A 0.05% in the treatment of keratoconjunctivitis sicca - Schrell, C.; Cursiefen, Claus; Kruse, Friedrich Eduard; Jacobi, Christina (Klinische Monatsblätter für Augenheilkunde, 2012)
The current understanding of the pathogenesis of dry eye disease has proceeded to recognition of inflammation as the key pathogenetic mechanism. The purpose of this study was to evaluate the effect of cyclosporine 0.05% eye drops on subjective symptoms and objective signs of patients with keratoconjunctivitis sicca.In this clinical trial 62 patients with severe keratoconjunctivitis sicca (DEWS grade 3) were included. Over a time period of 3 months all patients received treatment with preservative-free hyaluronic acid artificial tears at one drop 5 times per day and in addition 31 patients received one drop of cyclosporine 0.05% twice daily. Screening parameters were LIPCOF, tear break-up time (BUT), fluorescein and rose bengal staining, the intraocular pressure (IOP) and the OSDI score.In the cyclosporine A group BUT, Jones test and OSDI score improved significantly after 3 months in contrast to the controls. Moreover the values of BUT and Jones test in the cyclosporine A group were significantly higher after 3 months compared to the healthy controls. Fluorescein and rose bengal staining improved only in the cyclosporine A group after 3 months.Anti-inflammatory therapy with cyclosporine A 0.05% eye drops as off label use significantly improves subjective symptoms and objective signs in patients with severe dry eye disease providing a good safety profile. These findings suggest a widespread use of cyclosporine A 0.05% eye drops in patients with moderate to severe keratoconjunctivitis sicca.
EVALuna2:21106

Topical Omega-3 Polyunsaturated Fatty Acids for the Treatment of Dry Eye - Results from a Pilot Randomized Controlled Masked-Observer Study - Kaercher, Thomas; Messmer, Elisabeth M.; Berninger, Thomas; Huber-Van Der Velden, Klaudia K.; Geiger, Raphaela; Cipriano-Bonvin, Pauline; Jacobi, Christina (Clinical Ophthalmology, 2022)
Purpose: To investigate the efficacy, safety and tolerability of topical omega-3 polyunsaturated fatty acids (PUFA) as an innovative treatment of dry eye disease (DED).Patients and Methods: In a pilot, multicenter, masked-observer, randomized, active-controlled, non-inferiority study in Germany, patients self-treated their eyes with daily instillations of eye drops containing either omega-3 PUFA or povidone as major components for three months. At four and twelve weeks, efficacy was among others evaluated based on Ocular Surface Disease Index (OSDI), ocular surface symptoms intensity, general clinical impression, tear break-up time (TBUT), corneal fluorescein staining using the Oxford grading scale, tear volume, and matrix metalloproteinase-9 (MMP-9) concentration in the tear film. Safety evaluation included visual acuity, intraocular pressure, and the incidence of adverse events. Co-primary endpoints were the mean percent changes from baseline of TBUT and OSDI after four weeks. Results: In total 80 patients were included, of whom 37 in the PUFA group and 39 in the povidone group were evaluable for the co -primary endpoints. Patients had a mean age of 52 years and >80% were women. Both co-primary endpoints (TBUT and OSDI) significantly improved from baseline in both treatment groups, at Week 4 and Week 12 and the statistical analysis demonstrated topical omega-3 PUFA to be non-inferior to 2% povidone for these two parameters. Both treatments resulted in a significant improvement of most secondary efficacy endpoints as well, often with a slight difference in favor of PUFA, not reaching statistical significance though. One non-severe, treatment-related local AE was reported in each group.Conclusion: Omega-3 PUFA-based eye drops proved to be non-inferior to povidone-containing eye drops in the treatment of signs and symptoms of dry eye. This treatment may thus be an additional tool for the management of DED.
CRIS-Team WoS Importer:2022-12-23

Topical Ranibizumab inhibits inflammatory corneal hem- and lymphangiogenesis - Bucher, Franziska; Parthasarathy, Anand; Bergua, Antonio; Onderka, Jasmine; Regenfuss, Birgit; Cursiefen, Claus; Bock, Felix (Acta Ophthalmologica, 2014)
Purpose: Ranibizumab (Lucentis(®) ) is a Fab-Fragment of a recombinant, humanized, monoclonal VEGF (anti-vascular endothelial growth factor) antibody. This study analyzed the ability of topical Ranibizumab to inhibit lymphangiogenesis in addition to hemangiogenesis after acute corneal inflammation in vivo. In addition, the effect of Ranibizumab on the proliferation of human lymphatic endothelial cells (LECs) and blood endothelial cells (BECs) in vitro was studied. Methods: The inhibitory effect of Ranibizumab on LECs and BECs was studied in vitro using a proliferation enzyme-linked immunosorbent assay (ELISA) assay. To study the in vivo effects of Ranibizumab, the mouse model of suture induced inflammatory corneal neovascularization was used. Study mice received topical Ranibizumab as eye drops. After 1 week excised corneas were stained with LYVE-1 and CD31. Hemangiogenesis and lymphangiogenesis were analyzed morphometrically by using a semiautomatic method based on the image analyzing program Cell^F. Results: An antiproliferative effect of Ranibizumab was seen in vitro on both human BECs and LECs with a significance of p < 0.0001 and p < 0.0004, respectively. In vivo experiments showed that topical application of Ranibizumab significantly inhibits both hemangiogenesis (p = 0.0026) and lymphangiogenesis (p = 0.0026) in the cornea. Conclusion: Ranibizumab is a potent inhibitor of inflammatory corneal hemangiogenesis and lymphangiogenesis in vivo with a direct inhibitory effect on both endothelial cell types in vitro. This study for the first time demonstrates an inhibitory effect of Ranibizumab on lymphatic vessels which could have a wider range of clinical applications.
EVALuna2:21062

Towards an electroretinographic assay for studying colour vision in human observers - Kremers, Jan; Bhatt, Deepak (Documenta Ophthalmologica, 2016)
To determine whether electroretinograms (ERGs) to heterochromatic stimulation can detect and quantify hereditary colour vision deficiency.ERGs were measured to counterphase modulation of red and green stimuli. The total modulation depth of the red and green stimuli was constant. The ratio of red to green modulation was varied, and the responses were measured at two temporal frequencies: 12 and 36 Hz. Subjects were 13 protanopes, 19 protanomalous trichromats, 38 deuteranopes, 16 deuteranomalous trichromats and 22 normal trichromats.The responses are in agreement with previous findings: they were determined by a vector additive input of L- and M-cones (and thus is luminance sensitive) at 36 Hz. At 12 Hz, the responses can be modelled a vector addition of an L-/M-additive response (as determined by the 36 Hz ERGs) and an L-/M-opponent response. From the models, L-cone input fraction (36 Hz) and luminance input fraction (12 Hz) were estimated. The five groups showed different characteristics. However, the signal-to-noise ratio (SNR) at 12 Hz was not always satisfactory.The ERGs to heterochromatic stimuli are potentially interesting for determining the presence and the type of colour vision deficiencies, provided some measures are taken to improve the 12 Hz SNRs.
EVALuna2:21315

Towards Speech-Act-Based Compliance - Tenschert, Johannes; Michelson, Georg; Lenz, Richard (Proc. 18th Conf. on Business Informatics, 2016)
UnivIS-Import:2018-09-06:Pub.2016.tech.IMMD.IMMD6.toward_9
Keywords: business data processing; knowledge management; law; organisational aspects; BPMS; CTL rules; JBoss Drools; LTL rules; US; ad-hoc interactions; compliance monitoring; cross-cutting concerns; daily business; knowledge work; legal requirements; organizations; rete-based b

Toxic retrobulbar neuritis due to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-based chronic sinusitis in the left sphenoid sinus: a case report - Schapher, Mirco; Brügel, Jacob; Güner, Fabian; Volbers, Bastian; Eichhorn, Philip; Agaimy, Abbas; Berger, Magdalena; Mardin, Christian; Dörfler, Arnd; Hock, Stefan (Journal of Medical Case Reports, 2023)
BACKGROUND: Abrupt visual impairment constitutes a medical urgency, necessitating an interdisciplinary diagnostic and therapeutic approach owing to the broad spectrum of potential etiologies, thereby engaging numerous medical specialties. CASE PRESENTATION: A 21-year-old Mixed White and Asian female patient, with medical history of nonsteroidal antiinflammatory drug-exacerbated respiratory disease necessitating previous sinus surgery, reported sudden monocular vision loss. Unremarkable ophthalmological examination of the fellow eye and hematological parameters, save for a slight elevation in lymphocytes and eosinophils, were observed. Imaging studies indicated recurrence of bilateral chronic rhinosinusitis with nasal polyps and a mucocele in the left sphenoid sinus, accompanied by bony structural deficits. Emergency revision sinus surgery, guided by navigation, was promptly performed. The patient received treatment with methylprednisolone, ceftriaxone, cyanocobalamin, pyridoxine, thiamine, and acetylsalicylic acid. During the hospital stay, she developed steroid-induced glaucoma, which was subsequently managed successfully. Negative microbiological swabs, along with pathohistological evidence of increased tissue eosinophilia and the patient's clinical history, led to the diagnosis of toxic retrobulbar neuritis secondary to recurrent nonsteroidal antiinflammatory drug-exacerbated respiratory disease-associated chronic rhinosinusitis of the left sphenoid sinus. CONCLUSIONS: In cases of acute unilateral vision loss, optic neuritis is a highly probable differential diagnosis and may be induced by pathologies of the paranasal sinuses. Nonsteroidal antiinflammatory drug-exacerbated respiratory disease, a subtype of chronic rhinosinusitis, is associated with type 2 inflammation, which is increasingly recognized for its role in the pathogenesis of bronchial asthma, eosinophilic esophagitis, and atopic eczema. Clinicians should consider chronic rhinosinusitis as a potential differential diagnosis in unilateral visual loss and be cognizant of the rising significance of type 2 inflammations, which are relevant to a variety of diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Blindness; Case report; Inflammation mediators; Neuritis; Optic; Sinusitis

Trabecular micro-invasive glaucoma surgery : Procedures and clinical results - Juenemann, A. G. M.; Rejdak, R.; Hohberger, B. (Ophthalmologe, 2018)
The management of glaucoma therapy to reduce intraocular pressure commonly consists of a gradual approach with local monotherapy, combined therapy, laser surgery and finally filtration surgery. The local side effects of glaucoma medications and the lack of adherence and persistence to the medical therapy as well as the complication profile of the established glaucoma surgical techniques justify the introduction of new surgical procedures. Micro-invasive glaucoma surgery (MIGS) is a promising new surgical approach. Microstents can reduce the medication burden and prolong the need for filtration surgery. This review article presents the different trabecular implants (iStent, iStent inject, HydrusTM Microstent) in detail and discusses the effectiveness and safety of the procedures based on the currently available data.
EVALuna2:34749

Transcription factor profiling identifies Sox9 as regulator of proliferation and differentiation in corneal epithelial stem/progenitor cells - Menzel-Severing, Johannes; Zenkel, Matthias; Polisetti, Naresh; Sock, Elisabeth; Wegner, Michael; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Scientific Reports, 2018)
Understanding transcription factor (TF) regulation of limbal epithelial stem/progenitor cells (LEPCs) may aid in using non-ocular cells to regenerate the corneal surface. This study aimed to identify and characterize TF genes expressed specifically in LEPCs isolated from human donor eyes by laser capture microdissection. Using a profiling approach, preferential limbal expression was found for SoxE and SoxF genes, particularly for Sox9, which showed predominantly cytoplasmic localization in basal LEPCs and nuclear localization in suprabasal and corneal epithelial cells, indicating nucleocytoplasmic translocation and activation during LEPC proliferation and differentiation. Increased nuclear localization of Sox9 was also observed in activated LEPCs following clonal expansion and corneal epithelial wound healing. Knockdown of SOX9 expression in cultured LEPCs by RNAi led to reduced expression of progenitor cell markers, e.g. keratin 15, and increased expression of differentiation markers, e.g. keratin 3. Furthermore, SOX9 silencing significantly suppressed the proliferative capacity of LEPCs and reduced levels of glycogen synthase kinase 3 beta (GSK-3ß), a negative regulator of Wnt/ß-catenin signaling. Sox9 expression, in turn, was significantly suppressed by treatment of LEPCs with exogenous GSK-3ß inhibitors and enhanced by small molecule inhibitors of Wnt signaling. Our results suggest that Sox9 and Wnt/ß-catenin signaling cooperate in mutually repressive interactions to achieve a balance between quiescence, proliferation and differentiation of LEPCs in the limbal niche. Future molecular dissection of Sox9-Wnt interaction and mechanisms of nucleocytoplasmic shuttling of Sox9 may aid in improving the regenerative potential of LEPCs and the reprogramming of non-ocular cells for corneal surface regeneration.
EVALuna2:34733

Transforming growth factor beta1, matrix-metalloproteinase-2 and its tissue inhibitor in patients with pseudoexfoliation glaucoma/syndrome - Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; et al. (Vojnosanitetski Pregled, 2012)
Transforming growth factor-beta1 (TGF-beta1), oxidative stress and imbalance between matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) may play an important role in pathogenesis of pseudoexfoliation syndrome/glaucoma (PEX Sy/Gl). The aim of the study was to measure concentrations of TGF-beta1, MMP-2, TIMP-2 in the aqueous humor in the examined group, as well as to compare the biochemical findings with the following clinical parameters: degree of chamber angle pigmantation, presence of pseudoexfoliation and the value of intraocular pressure (IOP).Aqueous samples from 30 patients with cataract, 30 patients with PEX Sy, 36 patients with PEX Gl, and 42 patients with primary open-angle glaucoma (POAG) were collected during phacoemulsification cataract surgery. TGF beta1, MMP-2, TIMP-2 Fluotokine Multi Analyze Profiling kits and Luminex technology were used to simultaneously measure TGF beta1, MMP-2 and TIMP-2.TGF-beta1, MMP-2, TIMP-2 were detected in human aqueous from all the groups with the highest level in the group with PEX Gl. Statistically, a significant correlation between the levels of TGF beta1, MMP-2, TIMP-2 in the aqueous humor of the patients with PEX Gl and the IOP value was confirmed (p < 0.05). In this group, the positive correlations between the TGF beta1 concentration in the aqueous humor and the presence of pseudoexfoliation (p < 0.01), on the one hand, and between the TIMP-2 level and the presence of pseudoexfoliation (p < 0.05), on the other, were reported. A statistically significant positive correlation of TGF-beta1 and MMP-2, and the degree of chamber angle pigmentation in the PEX Gl group was confirmed (p < 0.05). In the POAG group, TIMP-2 values were in a negative correlation with the degree of pigmentation (p < 0.05), and the IOP value (p < 0.05).TGF beta1 and MMP-2 affect the degree of chamber angle pigmentation and the degree of pseudoexfoliation in patients with pseudoexfoliative glaucom
EVALuna2:21101

Transparency of nanofiber reinforced alginate hydrogels for corneal wound healing - Stafiej, Piotr; Küng, Florian; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds for medical application in the eye - Stafiej, Piotr; Fuchsluger, Thomas; Schubert, Dirk W. (54th Nordic Polymer Days, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds (NFHC) for medical application in ophthalmology - Stafiej, Piotr; Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien 2017, 2017)

Trauma of periorbital soft tissue. Reconstruction with regard to functional and aesthetic aspects - Reich, W.; Sel, Saadettin; Holbach, L.; Paulsen, Friedrich; Scheller, K. (Ophthalmologe, 2013)
Complex midfacial trauma requires interdisciplinary management. A wide range of reconstructive procedures are needed and if necessary secondary and even tertiary interventions should be performed at the appropriate time. We present the case of a 45-year-old man who was involved in a car accident and presented with severe injuries to the periorbital soft tissue. The focus was on the reconstruction of this sensitive region with regard to functional and aesthetic aspects. In view of the severity of the injuries the final clinical status is considered to be very important. Special issues and pitfalls in the reconstruction of trauma cases and potential management are discussed.
EVALuna2:21119

Treatment of optic neuritis with erythropoietin (TONE): a randomised, double-blind, placebo-controlled trial-study protocol - Diem, Ricarda; Molnar, Fanni; Beisse, Flemming; Gross, Nikolai; Drueschler, Katharina; Heinrich, Sven P.; Joachimsen, Lutz; Rauer, Sebastian; Pielen, Amelie; Suehs, Kurt-Wolfram; Linker, Ralf; Huchzermeyer, Cord; et al. (BMJ Open, 2016)
Optic neuritis leads to degeneration of retinal ganglion cells whose axons form the optic nerve. The standard treatment is a methylprednisolone pulse therapy. This treatment slightly shortens the time of recovery but does not prevent neurodegeneration and persistent visual impairment. In a phase II trial performed in preparation of this study, we have shown that erythropoietin protects global retinal nerve fibre layer thickness (RNFLT-G) in acute optic neuritis; however, the preparatory trial was not powered to show effects on visual function.Treatment of Optic Neuritis with Erythropoietin (TONE) is a national, randomised, double-blind, placebo-controlled, multicentre trial with two parallel arms. The primary objective is to determine the efficacy of erythropoietin compared to placebo given add-on to methylprednisolone as assessed by measurements of RNFLT-G and low-contrast visual acuity in the affected eye 6 months after randomisation. Inclusion criteria are a first episode of optic neuritis with decreased visual acuity to <= 0.5 (decimal system) and an onset of symptoms within 10 days prior to inclusion. The most important exclusion criteria are history of optic neuritis or multiple sclerosis or any ocular disease (affected or non-affected eye), significant hyperopia, myopia or astigmatism, elevated blood pressure, thrombotic events or malignancy. After randomisation, patients either receive 33,000 international units human recombinant erythropoietin intravenously for 3 consecutive days or placebo (0.9% saline) administered intravenously. With an estimated power of 80%, the calculated sample size is 100 patients. The trial started in September 2014 with a planned recruitment period of 30 months.TONE has been approved by the Central Ethics Commission in Freiburg (194/14) and the German Federal Institute for Drugs and Medical Devices (61-3910-4039831). It complies with the Declaration of Helsinki, local laws and ICH-GCP.NCT01962571.
EVALuna2:21279

Treatment of severe recurrent symblepharopterygium: combined ipsilateral autologous limbus and homologous amniotic membrane transplantation - Huchzermeyer, Cord; Gatzioufas, Z.; Kruse, Friedrich; Seitz, B. (Ophthalmologe, 2014)
This retrospective study reports on four patients with severe recurrent symblepharopterygium formation and extensive subconjunctival scarring who were treated with a novel surgical technique combining free limbal autografting and amniotic membrane transplantation.The surgical technique included symblepharolysis, meticulous removal of subconjunctival scar tissue, ipsilateral free limbal autograft and homologous amniotic membrane transplantation.There were no intraoperative or postoperative adverse events and three patients had no manifestation of recurrence of pterygium, symblepharon or diplopia during a mean follow-up period of 172 ± 18 weeks (39 ± 4 months) postoperatively. Only one patient had persistent symblepharon and experienced a recurrence of pterygium approximately 40 weeks (9 months) after surgery.The results suggest that ipsilateral autologous limbal and homologous amniotic membrane transplantation can be an effective therapeutic approach in the treatment of recurrent pterygium with symblepharon formation.
EVALuna2:21026

Treatment-resistant nodular scleritis Therapieresistente noduläre Skleritis - Hübner, L.; Mardin, Christian; Held, Jürgen; Tappe, D.; Hammer, Christian; Bergua, Antonio (Ophthalmologe, 2022)
CRIS-Team Scopus Importer:2022-03-18

Tumor-associated lymphangiogenesis in the development of conjunctival melanoma - Heindl, Ludwig M.; Hofmann-Rummelt, Carmen; Adler, Werner; Bosch, Jacobus J.; Holbach, Leonard M.; Naumann, Gottfried; Kruse, Friedrich; Cursiefen, Claus (Investigative Ophthalmology & Visual Science, 2011)
Purpose. To analyze whether tumor-associated lymphangiogenesis is concurrent with the progression of premalignant conjunctival melanocytic intraepithelial neoplasia (C-MIN) into invasive conjunctival melanoma (CM) and to study its association with prognosis. Methods. Twenty patients with CM were closely matched with 20 patients with C-MIN with atypia and 20 with C-MIN without atypia regarding tumor size, tumor location, tumor extension, and patient's age. All conjunctival specimens were analyzed for the immunohistochemical presence of proliferating lymphatic vessels, with LYVE-1 and podoplanin used as specific lymphatic endothelial markers and Ki-67 as a proliferation marker. Lymphatic vascular density was measured within the mass (intratumoral) and within an area <=500 ?m from the tumor border (peritumoral) and was correlated with recurrence, metastasis, and survival rates. Results. Intratumoral and peritumoral proliferating lymphatic vessels were detected in none of the C-MINs without atypia, in 10 of the 20 C-MINs with atypia, and in all 20 CMs. Invasive CM showed a significantly higher intra- and peritumoral density of proliferating lymphatics than did C-MIN with atypia (P <= 0.001). Patients with high intratumoral lymphatic density revealed significantly lower recurrence-free survival rates (P = 0.041) in C-MIN with atypia and significantly lower recurrence-free (P = 0.006), lymphatic-spread-free (P = 0.041), distant-metastasis-free (P = 0.029), and melanoma-specific survival rates (P = 0.029) in CM. Conclusions. Development of CM from premalignant precursors is concurrent with the outgrowth of lymphatic vessels. This active lymphangiogenesis seems to be associated with an increased risk of local recurrence in patients with C-MIN with atypia and with an increased risk of local recurrence, lymphatic spread, distant metastasis, and tumor-related death in patients with invasive CM.
EVALuna2:5320

Type II Diabetes Mellitus Causes Extracellular Matrix Alterations in the Posterior Cornea That Increase Graft Thickness and Rigidity - Kingsbury, Kenten D.; Skeie, Jessica M.; Cosert, Krista; Schmidt, Gregory A.; Aldrich, Benjamin T.; Sales, Christopher S.; Weller, Julia; Kruse, Friedrich; Thomasy, Sara M.; Schlötzer-Schrehardt, Ursula; Greiner, Mark A. (Investigative Ophthalmology & Visual Science, 2023)
PURPOSE. There is a pressing need to investigate the impact of type II diabetes mellitus on the posterior cornea in donor tissues given its increasing prevalence and potential impact on endothelial keratoplasty surgical outcomes. METHODS. Immortalized human cultured corneal endothelial cells (CECs; HCEC-B4G12) were grown in hyperglycemic media for 2 weeks. Extracellular matrix (ECM) adhesive glycoprotein expression and advanced glycation end products (AGEs) in cultured cells and corneoscleral donor tissues, as well as the elastic modulus for the Descemet membrane (DMs) and CECs of diabetic and nondiabetic donor corneas, were measured. RESULTS. In CEC cultures, increasing hyperglycemia resulted in increased transforming growth factor beta-induced (TGFBI) protein expression and colocalization with AGEs in the ECM. In donor corneas, the thicknesses of the DM and the interfacial matrix (IFM) between the DM and stroma both increased from 8.42 ± 1.35 μm and 0.504 ± 0.13 μm in normal corneas, respectively, to 11.13 ± 2.91 μm (DM) and 0.681 ± 0.24 μm (IFM) in non-advanced diabetes (P = 0.013 and P = 0.075, respectively) and 11.31 ± 1.76 μm (DM) and 0.744 ± 0.18 μm (IFM) in advanced diabetes (AD; P = 0.0002 and P = 0.003, respectively). Immunofluorescence in AD tissues versus controls showed increased AGEs (P < 0.001) and markedly increased labeling intensity for adhesive glycoproteins, including TGFBI, that colocalized with AGEs. The elastic modulus significantly increased between AD and control tissues for the DMs (P < 0.0001) and CECs (P < 0.0001). CONCLUSIONS. Diabetes and hyperglycemia alter human CEC ECM structure and composition, likely contributing to previously documented complications of endothelial keratoplasty using diabetic donor tissue, including tearing during graft preparation and reduced graft survival. AGE accumulation in the DM and IFM may be a useful biomarker for determining diabetic impact on posterior corneal tissue.
CRIS-Team Scopus Importer:2023-08-11
Keywords: corneal biomechanics; corneal endothelial cells; corneal transplantation

Ultrasound diagnostics in ophthalmology (standardized echography) : Part 1: principles and diseases of the eyeball - Hasenfratz, G.; Mardin, C. (Ophthalmologe, 2014)
Ultrasound diagnostics has been one of the most important additional diagnostic non-invasive techniques in ophthalmology for many decades and is essential for many intraocular and orbital diseases. When echographic investigations and analysis of the echograms obtained are correctly carried out, ultrasound diagnostics demonstrates a high degree of specificity and sensitivity.
EVALuna2:21187

Ultrasound diagnostics in ophthalmology (standardized echography) : Part 2: diseases of the orbit - ultrasound biomicroscopy diagnostics - Hasenfratz, G.; Mardin, Christian Y. (Ophthalmologe, 2014)
Ultrasound diagnostics have been one of the most important noninvasive supplementary diagnostic procedures in ophthalmology for many decades and are indispensable for many intraocular and orbital diseases. When the echography examination and analysis of the echograms obtained are correctly carried out, ultrasound diagnostics are characterized by a high measure of specificity and sensitivity.
EVALuna2:21194

Ultrastructural analysis of explanted CyPass microstents and correlation with clinical findings - Hübner, Lisa; Schlötzer-Schrehardt, Ursula; Weller, Julia; Hohberger, Bettina; Mardin, Christian; Lämmer, Robert (Graefes Archive For Clinical and Experimental Ophthalmology, 2022)
Purpose: The purpose of this study was to obtain insight into cellular processes after CyPass microstent implantation into the supraciliary space. With this knowledge, we expected to find some reason for surgical failure. Methods: Nine CyPass microstents of 8 patients with primary open-angle glaucoma (n = 1), pseudoexfoliation glaucoma (n = 5), uveitic glaucoma (n = 1), and posttraumatic open-angle glaucoma (n = 1) were explanted due to recurrence of IOP elevation, corneal decompensation, or persistent hypotony. The explants were processed for light and transmission electron microscopy. Results: Fibrotic material, consisting of collagen fibrils, microfibrils, pseudoexfoliation fibrils produced by activated fibroblasts, was detected in the stent lumen of 4/5 pseudoexfoliation glaucoma patients and also in posttraumatic open-angle glaucoma. Fibrotic material was also present on the outer surface and within fenestrations of the majority of stents. Complete absence of fibrotic reaction was noticed in 3 of 9 microstents. Conclusion: Although MIGS is known to be less invasive than conventional surgery, implants placed in the suprachoroidal space may be adversely affected by a fibrotic tissue reaction resulting in implant failure. Understanding mechanisms and risk factors leading to fibrotic scarring following antiglaucomatous surgery may help to develop novel strategies that improve surgical outcome.
CRIS-Team Scopus Importer:2022-03-18
Keywords: CyPass microstent; Fibrosis; Glaucoma; MIGS; Surgery failure

Ultrastructure of the posterior corneal stroma - Schlötzer-Schrehardt, Ursula; Bachmann, Bjoern O.; Tourtas, Theofilos; Torricelli, Andre A. M.; Singh, Arun; Gonzalez, Sheyla; Mei, Hua; Deng, Sophie X.; Wilson, Steven E.; Kruse, Friedrich (Ophthalmology, 2015)
To reinvestigate the ultrastructure of the posterior stroma of the human cornea and to correlate the findings with the stromal behavior after big-bubble creation.Observational consecutive 3-center case series.Fresh corneoscleral buttons from human donors (n = 19) and organ-cultured corneoscleral buttons (n = 10) obtained after Descemet's membrane endothelial keratoplasty.Corneal specimens were divided into central (3 mm), mid peripheral (8 mm), and peripheral parts by trephination and processed for transmission electron microscopic and immunohistochemical analyses. A big bubble was created by air injection into the stroma of organ-cultured corneas before fixation.The distance of keratocytes to Descemet's membrane, number of collagen lamellae between keratocytes and Descemet's membrane, diameter and arrangement of collagen fibrils, thickness of stromal lamella created by air injection, and immunopositivity for collagen types III, IV, and VI.Stromal keratocytes were observed at variable distances from Descemet's membrane, increasing from 1.5 to 12 ?m (mean, 4.97±2.19 ?m) in the central, 3.5 to 14 ?m (mean, 8.03±2.47 ?m) in the midperipheral, and 4.5 to 18 ?m (mean, 9.77±2.90 ?m) in the peripheral regions. The differences in mean distances were significant (P < 0.0001). The number of collagen lamellae between Descemet's membrane and most posterior keratocytes varied from 2 to 10 and the diameter of collagen fibrils averaged 23.5±1.8 nm and corresponded with that of the remaining stroma. A thin layer (0.5-1.0 ?m thick) of randomly arranged, unaligned collagen fibers, which was positive for collagen types III and VI, was observed at the Descemet-stroma interface. The residual stromal sheet separated by air injection in 8 of 10 donor corneas varied in thickness from 4.5 to 27.5 ?m, even within individual corneas (<=3-fold), and was composed of 5 to 11 collagen lamellae that revealed keratocytes on their anterior surface and in between.Barring an anchoring zone of interwoven collagen fibers at the Descemet-stroma interface, the findings did not provide any evidence for the existence of a distinctive acellular pre-Descemet's stromal layer in the human cornea. The intrastromal cleavage plane after pneumodissection seems to be nonreproducibly determined by the intraindividually and interindividually variable distances of keratocytes to Descemet's membrane.
EVALuna2:21206

Understanding, diagnosing, and treating Myalgic encephalomyelitis/chronic fatigue syndrome – State of the art: Report of the 2nd international meeting at the Charité Fatigue Center - Steiner, Sophie; Fehrer, Annick; Hoheisel, Friederike; Schoening, Simon; Aschenbrenner, Anna; Babel, Nina; Bellmann-Strobl, Judith; Finke, Carsten; Fluge, Øystein; Froehlich, Laura; Goebel, Andreas; Grande, Bettina; et al. (Autoimmunity Reviews, 2023)
Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a devastating disease affecting millions of people worldwide. Due to the 2019 pandemic of coronavirus disease (COVID-19), we are facing a significant increase of ME/CFS prevalence. On May 11th to 12th, 2023, the second international ME/CFS conference of the Charité Fatigue Center was held in Berlin, Germany, focusing on pathomechanisms, diagnosis, and treatment. During the two-day conference, more than 100 researchers from various research fields met on-site and over 700 attendees participated online to discuss the state of the art and novel findings in this field. Key topics from the conference included: the role of the immune system, dysfunction of endothelial and autonomic nervous system, and viral reactivation. Furthermore, there were presentations on innovative diagnostic measures and assessments for this complex disease, cutting-edge treatment approaches, and clinical studies. Despite the increased public attention due to the COVID-19 pandemic, the subsequent rise of Long COVID-19 cases, and the rise of funding opportunities to unravel the pathomechanisms underlying ME/CFS, this severe disease remains highly underresearched. Future adequately funded research efforts are needed to further explore the disease etiology and to identify diagnostic markers and targeted therapies.
CRIS-Team Scopus Importer:2023-10-13
Keywords: Coronavirus disease 2019 (COVID-19); Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS); Post-COVID fatigue (PCF); Post-COVID syndrome (PCS); Severe acute respiratory syndrome 2 (SARS-CoV-2)

Unilateral retinitis pigmentosa: 30 years follow-up - Weller, Julia M.; Michelson, Georg; Jünemann, Anselm (BMJ Case Reports, 2014)
This case report depicts the clinical course of a female patient with unilateral retinitis pigmentosa (RP), who presented first in 1984 at the age of 43 years. At the beginning, there were cells in the vitreous leading to the diagnosis of uveitis with vasculitis. Within 30 years, the complete clinical manifestation of RP developed with bone spicule-shaped pigment deposits, pale optic disc, narrowed arterioles, cystoid macular oedema, posterior subcapsular cataract, concentric narrowing of the visual field and undetectable electroretinogram signal. At the age of 72 years, there are still no signs of retinal dystrophy in the other eye.
EVALuna2:21211

Unilateral swelling of the lacrimal gland in a 15-year-old female patient - Berta, A. I.; Naumann-Bartsch, N.; Agaimy, Abbas; Metzler, Markus; Kruse, Friedrich; Holbach, L. (Ophthalmologe, 2013)
EVALuna2:6506

Unilateral visual field defect in a seemingly normal eye - Huchzermeyer, Cord; Bergua, A. (Klinische Monatsblätter für Augenheilkunde, 2013)
EVALuna2:21120

Unsupervised OCT Denoising using speckle split - Schottenhamml, Julia; Würfl, Tobias; Ploner, Stefan; Husvogt, Lennart; Hohberger, Bettina; Fujimoto, James G.; Maier, Andreas (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Updated incidence of dry eye syndrome in Germany - Posa, A.; Sel, S.; Dietz, R.; Sander, R.; Bräuer, Lars; Paulsen, Friedrich (Klinische Monatsblätter für Augenheilkunde, 2014)
Dry eye is one of the most common eye surface disorders. Patients suffer in particular from annoying subjective symptoms that compromise quality of life. The aim of the study was to find out when patients consult ophthalmologists in Germany and what symptoms they present.170 patients treated at ophthalmological practices in Bavaria, Saxony and Saxony-Anhalt with dry eye were surveyed regarding their symptoms.The majority of those questioned were 40 years of age or older (88 %) (average: 60), female (59 %) and described a variety of subjective symptoms (65 %). More than five different concurrent symptoms were named. There is a recognisable increase in cases - by more than 3.5 times - at the age of forty (in women) and fifty (in men).We hope to contribute with the data obtained to a more complete understanding of this highly complex pathological process. A further aim is to facilitate recognition of this mostly chronic condition in its early stages when the symptoms are still poorly defined. The data on the German population obtained here should become part of a comparative analysis within the international context. Despite considerable scientific effort, dry eye remains a difficult challenge for both patients and attending physicians.
EVALuna2:4437

Use of accidentally torn descemet membrane to successfully complete descemet membrane endothelial keratoplasty - Tourtas, Theofilos; Heindl, Ludwig M.; Kopsachilis, Nikolaos; Bachmann, Bjoern O.; Kruse, Friedrich; Cursiefen, Claus (Cornea, 2013)
To describe the use of an accidentally torn Descemet membrane (DM) to successfully complete Descemet membrane endothelial keratoplasty (DMEK) surgery.Retrospective, observational case series of 3 eyes of 3 patients undergoing DMEK with a DM accidentally torn into 2 pieces during graft preparation. The mean outcome measures included best-corrected visual acuity, endothelial cell density, and central corneal thickness, before and at 1, 3, and 6 months after the DMEK surgery was performed.During graft preparation, immediately before transplantation, a large tear within the 8.0-mm marking line of the DM occurred, resulting in a DM torn into 2 pieces. In all the eyes, both pieces were successfully implanted into the anterior chamber, unfolded and attached to the posterior corneal stroma, one after the other. Six months after the surgery was performed, the best-corrected visual acuity ranged between 20/30 and 20/25. Endothelial cell loss was about 30% (range 28%-32%) 6 months after the surgery. Pachymetry findings showed normal corneal thickness 6 months after the surgery. All corneas remained clear without any signs of graft failure within 6 months of follow-up.DMEK surgery can be successfully completed despite the accidental tearing of donor DMs during the preparation of DMEK grafts by the sequential implantation of both DM pieces.
EVALuna2:21133

UVA irradiation of riboflavin generates oxygen-dependent hydroxyl radicals - Sel, Saadettin; Nass, Norbert; Poetzsch, Sandy; Trau, Stefanie; Simm, Andreas; Kalinski, Thomas; Duncker, Gernot I. W.; Kruse, Friedrich; Auffarth, Gerd U.; Broemme, Hans-Juergen (Redox Report, 2014)
The aim of this study was to verify the formation of hydroxyl radicals (·OH) after ultraviolet A (UVA) irradiation of riboflavin (RF) by spin trapping with 5,5-dimethyl-1-pyrroline-N-oxide (DMPO), and electron spin resonance spectroscopy.We found that ·OH were generated via hydrogen peroxide (H?O?) formation during UVA irradiation of RF. The ·OH radicals were trapped with DMPO yielding 2-hydroxy-5,5-dimethyl-1-pyrroline-N-oxide (·DMPO-OH). The formed radical adduct (·DMPO-OH) accumulated in the RF solution. Argon equilibration of the RF solution completely blocked the formation of the ·DMPO-OH adduct whereas subsequent aeration restored radical adduct generation. The presence of catalase inhibited ·DMPO-OH generation whereas BSA had no influence on ·DMPO-OH formation. Stopping UVA irradiation led to decay of radical adducts. UVA irradiation of H?O? in the presence of DMPO but without RF also induced the formation of ·DMPO-OH adduct. When adding DMPO to an already irradiated RF solution significantly less ·DMPO-OH was formed during further irradiation. Ultraviolet-visible spectroscopy and high-performance liquid chromatography analysis of RF indicated that RF decayed during UVA irradiation.The formation of ·OH during UVA irradiation of RF may be part of the oxygen-dependent mechanism involved in the cross-linking therapy of collagen in corneal stroma.
EVALuna2:21207

Validation of telemedical fundus images from patients with retinopathy - Michelson, Georg; Laser, M.; Mueller, S.; Weber, F.; Wärntges, Simone (Klinische Monatsblätter für Augenheilkunde, 2011)
The degree of retinal microangiopathy is important foran estimation of the vascular risk and for the optimisation of therapy in hypertensive and diabetic patients. Retinal microangiopathy may be determined by examination of the retinal fundus. We examined the reliability of the ophthalmoscopic diagnosis and of the telemedical judgement of fundus images in relation to the presence and the degree of retinopathy.This comparative observational study included 47 inpatient hypertensive and/or diabetic subjects. The fundus was judged ophthalmoscopically and subsequently, a fundus image was generated by use of a KOWA camera. The images were sent to the Interdisciplinary Center of Ophthalmologic Preventive Medicine. The reliability of the two diagnostic methods was calculated for one of the two eyes, which was selected by a random generator.The largest concordance of the two diagnosis methods was achieved, in descending order, for retinal bleeding, stage of diabetic retinopathy and the papilla findings. Additionally, there were no differences for the stage of hypertensive retinopathy und tortuosity. The reliability of arterio-venous nicking related to the right and the left eye was low or absent, respectively.The teleophthalmologic diagnosis achieves good results as compared to the ophthalmoscopic judgement in relation to retinopathy assessment criteria.
EVALuna2:21020

Variants in ASB10 are associated with open-angle glaucoma - Pasutto, Francesca; Keller, Kate E.; Weisschuh, Nicole; Sticht, Heinrich; Samples, John R.; Yang, Yong-Feng; Zenkel, Matthias; Schlötzer-Schrehardt, Ursula; Mardin, Christian Y.; Frezzotti, Paolo; Edmunds, Beth; Kramer, Patricia L.; et al. (Human Molecular Genetics, 2012)
The molecular events responsible for obstruction of aqueous humor outflow and the loss of retinal ganglion cells in glaucoma, one of the main causes of blindness worldwide, remain poorly understood. We identified a synonymous variant, c.765C>T (Thr255Thr), in ankyrin repeats and suppressor of cytokine signaling box-containing protein 10 (ASB10) in a large family with primary open angle glaucoma (POAG) mapping to the GLC1F locus. This variant affects an exon splice enhancer site and alters mRNA splicing in lymphoblasts of affected family members. Systematic sequence analysis in two POAG patient groups (195 US and 977 German) and their respective controls (85 and 376) lead to the identification of 26 amino acid changes in 70 patients (70 of 1172; 6.0%) compared with 9 in 13 controls (13 of 461; 2.8%; P = 0.008). Molecular modeling suggests that these missense variants change ASB10 net charge or destabilize ankyrin repeats. ASB10 mRNA and protein were found to be strongly expressed in trabecular meshwork, retinal ganglion cells and ciliary body. Silencing of ASB10 transcripts in perfused anterior segment organ culture reduced outflow facility by 50% compared with control-infected anterior segments (P = 0.02). In conclusion, genetic and molecular analyses provide evidence for ASB10 as a glaucoma-causing gene.
EVALuna2:9125

Vildagliptin in addition to metformin improves retinal blood flow and erythrocyte deformability in patients with type 2 diabetes mellitus - results from an exploratory study - Berndt-Zipfel, Christine; Michelson, Georg; Dworak, Markus; Mitry, Michael; Loeffler, Andrea; Pfuetzner, Andreas; Forst, Thomas (Cardiovascular Diabetology, 2013)
Numerous rheological and microvascular alterations characterize the vascular pathology in patients with type 2 diabetes mellitus (T2DM). This study investigated effects of vildagliptin in comparison to glimepiride on retinal microvascular blood flow and erythrocyte deformability in T2DM.
EVALuna2:21122

VIP changes during daytime in chicken intrinsic choroidal neurons - Hohberger, Bettina; Jeßberger, Carmen; Hermann, Franz; Zenkel, Matthias; Kaser-Eichberger, Alexandra; Bergua, Antonio; Juenemann, Anselm G.; Schrödl, Falk; Neuhuber, Winfried (Experimental Eye Research, 2018)
PURPOSE: Ocular autonomic control is mediated by sympathetic and parasympathetic nerve fibres. Their interactions are complemented by primary afferent nerve fibers of and intrinsic choroidal neurons (ICN). As the vasodilatative neuropeptide, vasoactive intestinal peptide (VIP), is expressed in extrinsic and intrinsic ocular neurons, it is of special interest in ophthalmic research. Since circadian changes of ocular blood flow are known in humans and birds, this study aimed at investigating VIP expression at different daytimes in chicken choroid, the preferred model species in ICN research. METHODS: 12 eyes of 12 chickens were retrieved, slaughtered at 8.00-9.30 a.m. (n = 6) and 8.00 p.m. (n = 6), respectively, and choroidal wholemounts were prepared for immunofluorescence of VIP. VIP-positive ICN of both groups were quantified and density of VIP-positive axons assessed semi-quantitatively. In 28 additional eyes retrieved in the morning (n = 14) and evening (n = 14), choroidal VIP content was determined by ELISA. Morning and evening data were analyzed statistically. NADPH-diaphorase (NADPH-d, ICN cell marker) was done at additional 12 whole mount choroids of 12 chicken, retrieved in the morning (n = 6) and evening (n = 6). RESULTS: (1) Numbers of VIP positive neurons differed significantly between morning: (239.17 ± 113.9) and evening: (550.83 ± 245.7; p = 0.018). (2) Numbers of VIP-positive perikarya were significantly more accumulated in the temporal part of the choroid in the evening than in the morning (p = 0.026). (3) VIP positive axon density was found to be similar throughout the choroid in the morning and evening. (4) Number of NADPH-d positive neurons was not significantly different between morning (848.8 ± 399.5) and evening (945.8 ± 622.1, p > 0.05). (5) ELISA demonstrated a significant difference of VIP content (p = 0.012) in tissues harvested in the morning (145.41 ± 43.3 pg/ml) compared to evening (221.44 ± 106.3 pg/ml). CONCLUSIONS: As VIP positive axon density was similar in the morning and the evening throughout the choroid, PPG and ICN seemed to contribute equally to the axon network. Yet, changes in the total choroidal VIP content, the numbers of VIP positive perikarya, reflecting the intracellular VIP content, and their topographical distribution at two different days-times argue for a different status of activation of both neuronal sources in contrast to the equal amount of NADPHD-d positive neurons. The higher VIP content in the evening, compared to the morning, correlates with a known circadian rhythm of a lower IOP and a higher choroidal thickness at night. Thus, these changes may argue for a potential role of ICN in the regulation of ocular homeostasis and integrity.
EVALuna2:34748

Virtual reality for assessing stereopsis performance and eye characteristics in Post-COVID - Mehringer, Wolfgang; Stöve, Maike; Krauß, Daniel; Ring, Matthias; Steussloff, Fritz; Güttes, Moritz; Zott, Julia; Hohberger, Bettina; Michelson, Georg; Eskofier, Björn (Scientific Reports, 2023)
In 2019, we faced a pandemic due to the coronavirus disease (COVID-19), with millions of confirmed cases and reported deaths. Even in recovered patients, symptoms can be persistent over weeks, termed Post-COVID. In addition to common symptoms of fatigue, muscle weakness, and cognitive impairments, visual impairments have been reported. Automatic classification of COVID and Post-COVID is researched based on blood samples and radiation-based procedures, among others. However, a symptom-oriented assessment for visual impairments is still missing. Thus, we propose a Virtual Reality environment in which stereoscopic stimuli are displayed to test the patient's stereopsis performance. While performing the visual tasks, the eyes' gaze and pupil diameter are recorded. We collected data from 15 controls and 20 Post-COVID patients in a study. Therefrom, we extracted features of three main data groups, stereopsis performance, pupil diameter, and gaze behavior, and trained various classifiers. The Random Forest classifier achieved the best result with 71% accuracy. The recorded data support the classification result showing worse stereopsis performance and eye movement alterations in Post-COVID. There are limitations in the study design, comprising a small sample size and the use of an eye tracking system.
CRIS-Team Scopus Importer:2023-08-25

Visual Field Progression Rates in Glaucoma Eyes With Progressive Optic Disc Change - Bellios, N.; Horn, Folkert; Lämmer, Robert; Link, B.; Kremers, Jan; Mardin, C. Y.; Junemann, A. G. (Investigative Ophthalmology & Visual Science, 2010)
Keywords: visual fields

Visual function is compromised in patients with vitreous floaters - Ankamah, E.; Moran, R.; Green-Gomez, M.; Ng, E.; Welge-Luessen, U.; Kaercher, T.; Barbur, J.; Nolan, J. M. (2018)
EVALuna2:34758

Visuell-motorisches Sehtraining verbessert 3D-Sehvermögen bei Torhütern - Michelson, Georg; Schoemann, M; Paulus, Jan; Lochmann, Matthias (Tagungsband, Jahrestagung dvs-Kommission Fußball 2015, 2015)

Vitamin E reduces TGF-beta2-induced changes in human trabecular meshwork cells - Yu, Alice L.; Moriniere, Jerome; Welge-Lussen, Ulrich (Current Eye Research, 2013)
To determine the effects of vitamin E on transforming growth factor-beta2 (TGF-?2)-induced cellular changes in cultured human trabecular meshwork (TM) cells.Human TM cells were pre-treated with different concentrations of vitamin E. Afterwards, cells were exposed to 1.0 ng/ml TGF-?2 for 24 h. Expressions of the heat shock protein ?B-crystallin, the extracellular matrix (ECM) component fibronectin and the ECM-degrading enzyme matrix metalloproteinase-2 (MMP-2) were examined by real-time polymerase chain reaction (PCR) analyses. The cytoskeleton was investigated by phalloidin staining.TGF-?2 increased the expressions of ?B-crystallin and fibronectin and reduced the levels of MMP-2. TGF-?2 induced the formation of actin stress fibers and cross-linked actin networks. Pre-treatment with different concentrations of vitamin E reversed the TGF-?2-induced cellular changes in cultured human TM cells.TGF-?2-mediated changes in human TM cells could be reduced by pre-treatment with vitamin E. Therefore, it may be speculated that increasing the antioxidative capacity may help to lower the incidence of characteristic glaucomatous changes in the TM.
EVALuna2:21137

Wavelet denoising of multi frame optical coherence tomography data - Mayer, Markus Anton; Borsdorf, Anja; Wagner, Martin; Hornegger, Joachim; Mardin, Christian Y.; Tornow, Ralf-Peter (Biomedical Optics Express, 2012)
We introduce a novel speckle noise reduction algorithm for OCT images. Contrary to present approaches, the algorithm does not rely on simple averaging of multiple image frames or denoising on the final averaged image. Instead it uses wavelet decompositions of the single frames for a local noise and structure estimation. Based on this analysis, the wavelet detail coefficients are weighted, averaged and reconstructed. At a signal-to-noise gain at about 100% we observe only a minor sharpness decrease, as measured by a full-width-half-maximum reduction of 10.5%. While a similar signal-to-noise gain would require averaging of 29 frames, we achieve this result using only 8 frames as input to the algorithm. A possible application of the proposed algorithm is preprocessing in retinal structure segmentation algorithms, to allow a better differentiation between real tissue information and unwanted speckle noise. © 2012 Optical Society of America.

What is Important in Diagnosing Dry Eye Disease - Recommendations According to current Guidelines (DEWS II, DOG/BVA) Was ist bei der Diagnostik des Trockenen Auges zu beachten? - Jacobi, Christina (Klinische Monatsblätter für Augenheilkunde, 2022)
Dry Eye is one of the most common ocular diseases worldwide with an increasing number of patients. The pathogenesis of this disease is multifactorial and complex and the basis for diagnostic strategies and therapies. The current definition of dry eye disease as described in DEWS II includes inflammatory mechanisms at the ocular surface, a loss of homeostasis, hyperosmolarity of the tear film and neurosensory abnormalities. Subject symptom scores, a detailed patient history, certain diagnostic tools, and interdisciplinary interactions are necessary to enable an efficient, individualized and successful therapy. Important diagnostics include risk factor analysis, slit lamp examination, tear secretion tests, tearfilm stability tests, and tests for measuring the ocular surface inflammation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: diagnostics; Dry Eye; hyperevaporation; hyposecretion; inflammation

Wound healing in rabbit corneas after flapless refractive lenticule extraction with a 345 nm ultraviolet femtosecond laser - Hammer, Christian M.; Petsch, Corinna; Klenke, Joerg; Skerl, Katrin; Wuellner, Christian; Donitzky, Christof; Paulsen, Friedrich; Scholz, Michael; Seiler, Theo; Kruse, Friedrich; Menzel-Severing, Johannes (Journal of Cataract and Refractive Surgery, 2017)
PURPOSE: To characterize corneal wound healing in a rabbit model after flapless refractive lenticule extraction with a 345 nm ultraviolet femtosecond laser. SETTING: Departments of Ophthalmology and Anatomy II, University of Erlangen-Nürnberg and Wavelight GmbH, Erlangen, Germany. DESIGN: Experimental study. METHODS: Flapless refractive lenticule extraction was performed in 1 eye each of 20 New Zealand white rabbits (-5.0 diopters). Groups of 4 animals were euthanized after 48 hours, 1 week, 2 weeks, 4 weeks, and 3 months, respectively. Corneal samples were prepared for histology and fluorescence microscopy. To assess corneal cell death, proliferation, and myofibroblastic transdifferentiation, terminal uridine deoxynucleotidyl nick end-labeling (TUNEL) assay as well as immunostaining for Ki67 and α-smooth muscle actin (αSMA) were performed on sagittal cryosections. RESULTS: Histology revealed a zone of keratocyte depletion with a thickness of approximately 50 μm around the extraction site. At 48 hours, pronounced TUNEL staining of keratocytes was detected around the interface (159.9 cells/mm ± 18.4 [SD]), which steadily decreased to 74.9 ± 19.8 cells/mm at 1 week and 5.7 ± 4.8 cells/mm at 2 weeks. Ki67 staining of keratocytes was evident at 48 hours (10.0 ± 3.8 cells/mm), which then decreased at 1 week (5.2 ± 1.7 cells/mm) and 2 weeks (0.4 ± 0.5 cells/mm). From 4 weeks onward, no TUNEL or Ki67 staining was detected. The corneal stroma was αSMA-negative at all timepoints. CONCLUSION: Application of the 345 nm laser showed no signs of problematic repair processes in the cornea, which supports the initiation of the clinical phase.
EVALuna2:35326

Yield and Viability of Human Limbal Stem Cells From Fresh and Stored Tissue - Mason, Sharon L.; Stewart, Rosalind M. K.; Sheridan, Carl M.; Keshtkar, Fatemeh; Rooney, Paul; Austin, Eric; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Kaye, Stephen B. (Investigative Ophthalmology & Visual Science, 2016)
We compared cell number, putative stem cell markers, and clonogenic ability in fresh uncultured human limbal epithelial cells to that obtained from stored organ-cultured tissue.Cell suspensions were formed from fresh and organ culture-stored human limbal epithelium. Expression of putative stem cell markers ?Np63 and TrkA was performed using immunofluorescent staining before culture. Colony-forming efficiency (CFE) assays were performed at first passage. The effects of tissue storage, age, and postmortem/culture times were analyzed in a general linear model.Limbal tissue from 94 donors (34 fresh and 60 stored) was compared. Three times more cells were obtained per eye from fresh (35.34 × 104; SD, 17.39) than stored (11.24 × 104; SD, 11.57; P < 0.01) tissue. A higher proportion of cells from fresh tissue were viable (91.9%; SD, 5.7 vs. 85%; SD, 10.8) P < 0.01. Higher total cell expression of ?Np63 (20.19 × 104; SD, 15.5 vs. 3.28 104; SD, 4.33) and TrkA (59.24 × 104; SD, 13.21 vs. 7.65 × 104; SD, 1.05) was observed in fresh than stored tissue (P < 0.01). Colony-forming efficiency was higher for fresh (1.42; SD, 0.12) than stored (0.43; SD, 0.15; P < 0.01) cells. For stored tissue only, there was a significant inverse relationship between donor age and total number of cells isolated (R2 = 0.27, P < 0.001).Storage of corneoscleral discs in organ culture medium leads to significant reduction in limbal epithelial cell number, expression of ?Np63 and TrkA, and viability compared to fresh tissue. There is a smaller basal stem cell population in stored compared to fresh tissue.
EVALuna2:21288

A decellularized human corneal scaffold for anterior corneal surface reconstruction - Polisetti, Naresh; Schmid, Anke; Schlötzer-Schrehardt, Ursula; Maier, Philip; Lang, Stefan J.; Steinberg, Thorsten; Schlunck, Günther; Reinhard, Thomas (Scientific Reports, 2021)
Allogenic transplants of the cornea are prone to rejection, especially in repetitive transplantation and in scarred or highly vascularized recipient sites. Patients with these ailments would particularly benefit from the possibility to use non-immunogenic decellularized tissue scaffolds for transplantation, which may be repopulated by host cells in situ or in vitro. So, the aim of this study was to develop a fast and efficient decellularization method for creating a human corneal extracellular matrix scaffold suitable for repopulation with human cells from the corneal limbus. To decellularize human donor corneas, sodium deoxycholate, deoxyribonuclease I, and dextran were assessed to remove cells and nuclei and to control tissue swelling, respectively. We evaluated the decellularization effects on the ultrastructure, optical, mechanical, and biological properties of the human cornea. Scaffold recellularization was studied using primary human limbal epithelial cells, stromal cells, and melanocytes in vitro and a lamellar transplantation approach ex vivo. Our data strongly suggest that this approach allowed the effective removal of cellular and nuclear material in a very short period of time while preserving extracellular matrix proteins, glycosaminoglycans, tissue structure, and optical transmission properties. In vitro recellularization demonstrated good biocompatibility of the decellularized human cornea and ex vivo transplantation revealed complete epithelialization and stromal repopulation from the host tissue. Thus, the generated decellularized human corneal scaffold could be a promising biological material for anterior corneal reconstruction in the treatment of corneal defects.
CRIS-Team Scopus Importer:2021-02-19

A decellularized human limbal scaffold for limbal stem cell niche reconstruction - Polisetti, Naresh; Roschinski, Benjamin; Schlötzer-Schrehardt, Ursula; Maier, Philip; Schlunck, Günther; Reinhard, Thomas (International Journal of Molecular Sciences, 2021)
The transplantation of ex vivo expanded limbal epithelial progenitor cells (LEPCs) on amniotic membrane or fibrin gel is an established therapeutic strategy to regenerate the damaged corneal surface in patients with limbal stem cell deficiency (LSCD), but the long-term success rate is restricted. A scaffold with niche-specific structure and extracellular matrix (ECM) composition might have the advantage to improve long-term clinical outcomes, in particular for patients with severe damage or complete loss of the limbal niche tissue structure. Therefore, we evaluated the decellularized human limbus (DHL) as a biomimetic scaffold for the transplantation of LEPCs. Corneoscleral tissue was decellularized by sodium deoxycholate and deoxyribonuclease I in the presence or absence of dextran. We evaluated the efficiency of decellularization and its effects on the ultrastructure and ECM composition of the human corneal limbus. The recellularization of these scaffolds was studied by plating cultured LEPCs and limbal melanocytes (LMs) or by allowing cells to migrate from the host tissue following a lamellar transplantation ex vivo. Our decellularization protocol rapidly and effectively removed cellular and nuclear material while preserving the native ECM composition. In vitro recellularization by LEPCs and LMs demonstrated the good biocompatibility of the DHL and intrastromal invasion of LEPCs. Ex vivo transplantation of DHL revealed complete epithelialization as well as melanocytic and stromal repopulation from the host tissue. Thus, the generated DHL scaffold could be a promising biological material as a carrier for the transplantation of LEPCs to treat LSCD.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Decellularization; Decellularized limbal tissue; Ex vivo transplantation; Limbal melanocytes; Limbal stem cells; Limbal tissue engineering; Limbal transplantation; Recellularization

Adhesion/growth-regulatory galectins in the human eye: localization profiles and tissue reactivities as a standard to detect disease-associated alterations - Schlötzer-Schrehardt, Ursula; Andre, Sabine; Janko, Christina; Kaltner, Herbert; Kopitz, Juergen; Gabius, Hans-Joachim; Herrmann, Martin (Graefes Archive For Clinical and Experimental Ophthalmology, 2012)
To characterize the localization profiles of seven adhesion/growth-regulatory galectins in the normal human eye using immunodetection of endogenous galectins and binding of labeled galectins to sections, useful as a basis to detect disease-associated alterations.Non-cross-reactive anti-galectin antibodies and biotinylated galectins were tested on acetone-fixed cryosections of normal human donor eyes. Controls included omission of first-step reagent, testing of an antibody against a galectin specific for rat (galectin-5), and blocking of galectin binding with lactose.Galectin presence was not restricted to one or few members of this family. Signal occurrence can even include all tested or most proteins (conjunctival or corneal epithelium), whereas choroid positivity is fully accounted for by galectin-9. Regional specificity and characteristic profiles for each protein, immuno- and galectin histochemically, were determined. Differences in tissue reactivity among the galectins were detected.That the galectins have characteristic localization/reactivity profiles supports the concept of a network with potential for non-overlapping functions. The reported data thus prompt to proceed to the respective analysis of specimens from ocular diseases.
EVALuna2:12715

Aqueous humor selenium level and open-angle glaucoma - Juenemann, Anselm G. M.; Michalke, Bernhard; Lucio, Marianna; Chaudhri, Anwar; Schlötzer-Schrehardt, Ursula; Rejdak, Robert; Rekas, Marek; Hohberger, Bettina (Journal of Trace Elements in Medicine and Biology, 2018)
PURPOSE: Selenium supplementation was seen to be linked to glaucoma disease in a previous study (Lillico A. JE, Reid M et al. (2002) Selenium Supplementation and Risk of Glaucoma in the NPC trial University of Arizona, Tucson, AZ., Arizona Cancer Center). As aqueous humor levels of selenium seemed to be associated with primary open-angle glaucoma (POAG), the aim of this study was to analyze concentrations of selenium in aqueous humor samples of patients with POAG and pseudoexfoliation glaucoma (PEXG) in comparison to normal samples. PATIENTS AND METHODS: Thirty-eight aqueous humor samples from patients undergoing cataract surgery were collected: Eleven patients with PEXG (age 65.8 ± 10.69, female 6, male 5), 12 patients with POAG (age 65.3 ± 10.50, female 7, male 5) and 15 patients without glaucoma (age 70.9 ± 12.83, female 10, male 5, controls). Aqueous humor levels of selenium were measured by Flow-Injection-Inductively-Coupled-Plasma-DRC-Mass-Spectrometry (ICP-DRC-MS). RESULTS: Maximum likelihood estimation of the least squares means (LS-means) and the relative 95% confidence limits of selenium aqueous humor levels were 6.90 ± 1.03 μg/L (control), 6.74 ± 1.14 μg/L (POAG) and 8.25 ± 1.18 μg/L (PEXG). The data were modeled using a generalized linear model (GLM) analysis, where selenium was set as dependent variable. The model was corrected for group differences in age and gender. The data show no differences among all the calculated differences between the least square means (LS means), taking in consideration the simultaneous 95% confidence limit and the multiple comparison tests with Tukey-Cramer adjustment. The evaluation of the model disclosed that POAG and PEXG patients had no significantly different aqueous humor selenium concentrations compared to controls and to each other. However, the quantile regression analysis of selenium aqueous humor levels showed differences in quantiles for open-angle glaucoma patients considering age and gender. CONCLUSION: As no significant difference in aqueous humor concentration of selenium was detected between open-angle glaucoma and controls, however, quantile analysis showed differences in quantiles levels for different age ranges in open-angle glaucoma patients, the trace element selenium seemed to be linked to glaucoma disease, yet not in a major role.
EVALuna2:34757

Association of the retinal vasculature, intrathecal immunity, and disability in multiple sclerosis - Noll, Christina; Hiltensperger, Michael; Aly, Lilian; Wicklein, Rebecca; Afzali, Ali Maisam; Mardin, Christian; Gasperi, Christiane; Berthele, Achim; Hemmer, Bernhard; Korn, Thomas; Knier, Benjamin (Frontiers in Immunology, 2022)
Background: Optical coherence tomography angiography (OCT-A) is a novel technique allowing non-invasive assessment of the retinal vasculature. During relapsing remitting multiple sclerosis (RRMS), retinal vessel loss occurs in eyes suffering from acute optic neuritis and recent data suggest that retinal vessel loss might also be evident in non-affected eyes. We investigated whether alterations of the retinal vasculature are linked to the intrathecal immunity and whether they allow prognostication of the future disease course. Material and methods: This study includes two different patient cohorts recruited at a tertiary German academic multiple sclerosis center between 2018 and 2020 and a cohort of 40 healthy controls. A total of 90 patients with RRMS undergoing lumbar puncture and OCT-A analysis were enrolled into a cross-sectional cohort study to search for associations between the retinal vasculature and the intrathecal immune compartment. We recruited another 86 RRMS patients into a prospective observational cohort study who underwent clinical examination, OCT-A and cerebral magnetic resonance imaging at baseline and during annual follow-up visits to clarify whether alterations of the retinal vessels are linked to RRMS disease activity. Eyes with a history of optic neuritis were excluded from the analysis. Results: Rarefication of the superficial vascular complex occured during RRMS and was linked to higher frequencies of activated B cells and higher levels of the pro-inflammatory cytokines interferon-γ, tumor necrosis factor α and interleukin-17 in the cerebrospinal fluid. During a median follow-up of 23 (interquartile range 14 - 25) months, vessel loss within the superficial (hazard ratio [HR] 1.6 for a 1%-point decrease in vessel density, p=0.01) and deep vascular complex (HR 1.6 for a 1%-point decrease, p=0.05) was associated with future disability worsening. Discussion: Optic neuritis independent rarefication of the retinal vasculature might be linked to neuroinflammatory processes during RRMS and might predict a worse disease course. Thus, OCT-A might be a novel biomarker to monitor disease activity and predict future disability.
CRIS-Team Scopus Importer:2022-12-09
Keywords: cerebrospinal fluid; disability; multiple sclerosis; Optical coherence tomography; optical coherence tomography angiography

Asymmetry of Peripapillary Retinal Blood Vessel Position and Thickness in Healthy Right and Left Eyes - Quach, Jack; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian; Scheuerle, Alexander Friedrich; Burgoyne, Claude F.; Chauhan, Balwantray C.; Vianna, Jayme R. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2020)
CRIS-Team WoS Importer:2020-09-11

Basic research in ophthalmology in Germany and its international context - Schlötzer-Schrehardt, Ursula; Cursiefen, C. (Ophthalmologe, 2017)
Experimental basic research provides the foundations for the elucidation of pathophysiological mechanisms of diseases and the development of novel diagnostic and therapeutic strategies for ophthalmological diseases. The objective of this contribution is to provide an overview of the international interconnection of basic research in ophthalmology in Germany.The international context of ophthalmological research conducted in Germany is presented by means of personal experiences and data published by the German Ophthalmological Society (DOG), the German Research Foundation (DFG) and the European Union (EU). Due to the lack of organized databases this article lays no claim to completeness.Basic research in ophthalmology in Germany is mainly conducted in university eye departments and is mainly related to the etiology, pathophysiology and therapy development for various ophthalmic diseases. It is primarily funded by the DFG, the Federal Ministry of Education and Research (BMBF) and the EU plays an increasingly important role. Thus, ophthalmological research is integrated into numerous European research networks and beyond that into many international interconnections and relationships.In Germany, both clinical and basic research in ophthalmology is integrated into many international networks and is only functionally viable in an international context; however, given the increasing impact of ophthalmological research in Asian countries, future strategies require a continued focus on career development, research infrastructure, working environment and international cooperation.
EVALuna2:21348

Bilateral circumscribed posterior keratoconus: visualization by ultrasound biomicroscopy and slit-scanning topography analysis - Rejdak, Robert; Nowomiejska, Katarzyna; Haszcz, Dariusz; Jünemann, Anselm (Journal of Ophthalmology, 2012)
This paper documents a rare nonprogressive developmental disorder-bilateral circumscribed posterior keratoconus-in a 60-year-old man referred for a cataract surgery. For the first time ultrasound biomicroscopy was used to visualise the local anterior bulging of the posterior corneal surface with concomitant thinning of the stroma. The amount of localized posterior depression, corneal thickness and the refractive power of both the posterior and anterior corneal curvature were measured using slit-scanning topography analysis (Orbscan).
EVALuna2:21081

Biomechanical and morphological differences between the sclera canal ring and a peripheral sclera ring in the porcine eye - Terai, Naim; Schlötzer-Schrehardt, Ursula; Spoerl, Eberhard; Hornykewycz, Karin; Haentzschel, Janek; Haustein, Michael; Pillunat, Lutz E. (Ophthalmic Research, 2012)
To investigate a possible association between the biomechanical load and unload behaviour and the elastin content of the sclera canal ring (SCR) and a superiorly localized sclera ring (SPS) in the porcine eye.Two sclera rings were trephined from each of 40 porcine eyes, one containing the SCR and the other an SPS. The load and the unload curves were measured in the extension range of 0-2.0 mm by a biomaterial tester. Hysteresis was determined from the area enclosed by the loading and unloading curve. Histochemical staining with resorcin-fuchsin and morphometric analysis of paraffin-embedded sections of both rings were performed to detect the area occupied by elastin fibres.At 1 mm extension, the mean load of the SCR was 0.89 ± 0.22 N and that of the SPS 1.13 ± 0.19 N, which was not significantly different between both rings (p > 0.05). Mean hysteresis in the SCR was 1.55 ± 0.30 N × mm and 1.90 ± 0.18 N × mm in the SPS, which was significantly different between both rings (p = 0.01). Mean sclera thickness was 986 ?m in the SCR (range: 900-1,060 ?m) and 971 ?m in the SPS (range: 800-1,200 ?m) without a statistically significant difference between both sclera rings (p = 0.78). The area occupied by elastin fibres was 15.5 ± 3.4% in the SCR and 4.5 ± 1.5% in the SPS, which was significantly different between both rings (p = 0.0001).Hysteresis in the SCR was significantly lower than in the SPS, indicating a higher elasticity of the SCR in the porcine eye. This effect could be explained by a higher content of elastin in the surrounding ring of the peripapillary optic nerve head providing reversible contraction in cases of intra-ocular pressure variations.
EVALuna2:21047

Cell Homogeneity Indispensable for Regenerative Medicine by Cultured Human Corneal Endothelial Cells - Hamuro, Junji; Toda, Munetoyo; Asada, Kazuko; Hiraga, Asako; Schlötzer-Schrehardt, Ursula; Montoya, Monty; Sotozono, Chie; Ueno, Morio; Kinoshita, Shigeru (Investigative Ophthalmology & Visual Science, 2016)
To identify the subpopulation (SP) among heterogeneous cultured human corneal endothelial cells (cHCECs) devoid of cell-state transition applicable for cell-based therapy.Subpopulation presence in cHCECs was confirmed via surface CD-marker expression level by flow cytometry. CD markers effective for distinguishing distinct SPs were selected by analyzing those on established cHCECs with a small cell area and high cell density. Contrasting features among three typical cHCEC SPs was confirmed by PCR array for extracellular matrix (ECM). Combined analysis of CD markers was performed to identify the SP (effector cells) applicable for therapy. ZO-1 and Na+/K+ ATPase, CD200, and HLA expression were compared among heterogeneous SPs.Flow cytometry analysis identified the effector cell expressing CD166+CD105-CD44- +/-CD26-CD24-, but CD200-, and the presence of other SPs with CD166+ CD105-CD44+++ (CD26 and CD24, either + or -) was confirmed. PCR array revealed three distinct ECM expression profiles. Some SPs expressed ZO-1 and Na+/K+ ATPase at comparable levels with effector cells, while only one SP expressed CD200, but not on effector cells. Human leukocyte antigen expression was most reduced in the effector SP. The proportion of effector cells (E-ratio) inversely paralleled donor age and decreased during prolonged culture passages. The presence of Rho-associated protein kinase (ROCK) inhibitor increased the E-ratio in cHCECs. The average area of effector cells was approximately 200 220 ?m2, and the density of cHCECs exceeded 2500 cells/mm2.A specified cultured effector cell population sharing the surface phenotypes with mature HCECs in corneal tissues may serve as an alternative to donor corneas for the treatment of corneal endothelial dysfunction.
EVALuna2:21305

Characterization of the mucocutaneous junction of the human eyelid margin and meibomian glands with different biomarkers - Tektas, Ozan Yüksel; Yadav, Ajay; Garreis, Fabian; Schlötzer-Schrehardt, Ursula; Schicht, Martin; Hampel, Ulrike; Bräuer, Lars; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2012)
To investigate the morphology of the human eyelid margin and the presence of different cytokeratins, mucins and stem cell markers within the skin epithelium, mucocutaneous junction (MCJ) and palpebral conjunctiva.Eyelids of body donors were investigated histologically and ultrastructurally as well as by immunohistochemical methods using antibodies to cytokeratins 1, 4, 7, 8, 10, 13, 14, 15, and 19; mucins MUC1, MUC4, and MUC5AC and potential stem cell markers K15, BCRP/ABCG2, integrin ?1, and N-cadherin.The expression pattern of cytokeratins, mucins and stem cell markers varied across the different epithelia of the human eyelid. Within the MCJ, CK7, 15 and 19 were absent, whereas the epithelium reacted positive to antibodies to CK1, 4, 8, 10, 13 and 14. Reactivity was also observed for MUC1 and MUC4, but not for MUC5AC. No reactivity was determined for K15, BCRP/ABCG2 and integrin ?1 in the area of the MCJ epithelium but a strong reactivity was present for N-cadherin.The present immunohistochemical findings lead to a better characterization of the MCJ. Additionally, the knowledge of distribution of biomarkers like cytokeratins, mucins and stem cells can be useful in the investigation of MCJ disturbances which occur in several disorders of the meibomian glands and the lid epithelium in the course of dry eye syndrome and especially meibomian gland dysfunction.
EVALuna2:4382

Chicken GRIFIN: binding partners, developmental course of localization and activation of its lens-specific gene expression by L-Maf/Pax6 - Caballero, Gabriel Garcia; Schmidt, Sebastian; Schnoelzer, Martina; Schlötzer-Schrehardt, Ursula; Knospe, Clemens; Ludwig, Anna-Kristin; Manning, Joachim C.; Muschler, Paul; Kaltner, Herbert; Kopitz, Juergen; Gabius, Hans-Joachim (Cell and Tissue Research, 2019)
Tissue lectins appear to be involved in a broad range of physiological processes, as reflected for the members of the family of galectins by referring to them as adhesion/growth-regulatory effectors. In order to clarify the significance of galectin presence, key challenges are to define their binding partners and the profile of localization. Having identified the chicken galectin-related interfiber protein (C-GRIFIN) as lens-specific protein present in the main body of adult lens, we here report its interaction with lens proteins in ligand blotting. The assumption for pairing with -, - and -crystallins was ascertained by mass spectrometric detection of their presence in eluted fractions obtained by affinity chromatography. Biochemical and immunohistochemical monitoring revealed protein presence from about 3-day-old embryos onwards, mostly in the cytoplasm of elongated posterior cells, later in secondary lens fiber cells. On the level of gene expression, its promoter was activated by transcription factor L-Maf alone and together with Pax6 like a crystallin gene, substantiating C-GRIFIN's status as lens-specific galectin. Using this combined strategy for counterreceptor and expression profiling by bio- and histochemical methods including light, electron and fluorescence microscopy, respective monitoring in lens development can now be taken to the level of the complete galectin family.
CRIS-Team WoS Importer:2019-03-20

Chicken lens development: complete signature of expression of galectins during embryogenesis and evidence for their complex formation with α-, β-, δ-, and τ-crystallins, N-CAM, and N-cadherin obtained by affinity chromatography - García Caballero, Gabriel; Schmidt, Sebastian; Manning, Joachim C.; Michalak, Malwina; Schlötzer-Schrehardt, Ursula; Ludwig, Anna Kristin; Kaltner, Herbert; Sinowatz, Fred; Schnölzer, Martina; Kopitz, Jürgen; Gabius, Hans Joachim (Cell and Tissue Research, 2019)
The emerging multifunctionality of galectins by specific protein-glycan/protein interactions explains the interest to determine their expression during embryogenesis. Complete network analysis of all seven chicken galectins (CGs) is presented in the course of differentiation of eye lens that originates from a single type of progenitor cell. It answers the questions on levels of expression and individual patterns of distribution. A qualitative difference occurs in the CG-1A/B paralogue pair, underscoring conspicuous divergence. Considering different cell phenotypes, lens fiber and also epithelial cells can both express the same CG, with developmental upregulation for CG-3 and CG-8. Except for expression of the lens-specific CG (C-GRIFIN), no other CG appeared to be controlled by the transcription factors L-Maf and Pax6. Studying presence and nature of binding partners for CGs, we tested labeled galectins in histochemistry and in ligand blotting. Mass spectrometric (glyco)protein identification after affinity chromatography prominently yielded four types of crystallins, N-CAM, and, in the cases of CG-3 and CG-8, N-cadherin. Should such pairing be functional in situ, it may be involved in tightly packing intracellular lens proteins and forming membrane contact as well as in gaining plasticity and stability of adhesion processes. The expression of CGs throughout embryogenesis is postulated to give meaning to spatiotemporal alterations in the local glycome.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Cadherin; Crystallin; Lectin; Lens

Clonal analysis of limbal epithelial stem cell populations - Schlötzer-Schrehardt, Ursula (Methods in Molecular Biology, 2013)
While convincing data clearly suggest the presence of stem cells in the basal limbal epithelium in vivo, testing the proliferation, self-renewal, and differentiation capacity of stem cells relies on the development of methodologies that allow for their isolation and extensive propagation in vitro. Clonal analysis involving differentiation between short-lived transient cell clones and long-lived stem cell clones is an invaluable technique to identify stem cells in vitro, and allows cells to be expanded over multiple passages. This chapter describes a protocol for the isolation, expansion, and clonal analysis of limbal epithelial stem cells. The cultivation method described may be essential for long-term restoration of the damaged ocular surface in patients with limbal stem cell deficiency.
EVALuna2:21129

Complement regulation at necrotic cell lesions is impaired by the age-related macular degeneration-associated factor-H His402 risk variant - Lauer, Nadine; Mihlan, Michael; Hartmann, Andrea; Schlötzer-Schrehardt, Ursula; Keilhauer, Claudia; Scholl, Hendrik P. N.; Issa, Peter Charbel; Holz, Frank; Weber, Bernhard H. F.; Skerka, Christine; Zipfel, Peter F. (Journal of Immunology, 2011)
Age-related macular degeneration is a leading form of blindness in Western countries and is associated with a common SNP (rs 1061170/Y402H) in the Factor H gene, which encodes the two complement inhibitors Factor H and FHL1. However, the functional consequences of this Tyr(402) His exchange in domain 7 are not precisely defined. In this study, we show that the Tyr(402) His sequence variation affects Factor H surface recruitment by monomeric C-reactive protein (mCRP) to specific patches on the surface of necrotic retinal pigment epithelial cells. Enhanced attachment of the protective Tyr(402) variants of both Factor H and FHL1 by mCRP results in more efficient complement control and further provides an anti-inflammatory environment. In addition, we demonstrate that mCRP is generated on the surface of necrotic retinal pigment epithelial cells and that this newly formed mCRP colocalizes with the cell damage marker annexin V. Bound to the cell surface, Factor H-mCRP complexes allow complement inactivation and reduce the release of the proinflammatory cytokine TNF-?. This mCRP-mediated complement inhibitory and anti-inflammatory activity at necrotic membrane lesions is affected by residue 402 of Factor H and defines a new role for mCRP, for Factor H, and also for the mCRP-Factor H complex. The increased protective capacity of the Tyr(402) Factor H variant allows better and more efficient clearance and removal of cellular debris and reduces inflammation and pathology.
EVALuna2:21046

Consensus statement on indications for anti-angiogenic therapy in the management of corneal diseases associated with neovascularisation: outcome of an expert roundtable - Cursiefen, Claus; Colin, Joseph; Dana, Reza; Diaz-Llopis, Manuel; Faraj, Lana A.; Garcia-Delpech, Salvador; Geerling, Gerd; Price, Francis W.; Remeijer, Lies; Rouse, Barry T.; Seitz, Berthold; Udaondo, Patricia; et al. (British Journal of Ophthalmology, 2012)
The cornea is the clear window at the front of the eye and is the eye's main refractive medium. Its transparency is essential for vision. Corneal neovascularisation is a common clinical problem with serious consequences for vision; it can compromise corneal transparency and plays a major role in corneal graft rejection by breaching corneal immune privilege. In this review, we formulate a consensus on the unmet medical needs in the management of corneal neovascularisation and outline a framework for the clinical research that is needed to identify suitable agents to meet these needs.
EVALuna2:21219

Corneal graft alterations after Descemet stripping: implications for split cornea transplantation - Heindl, Ludwig M.; Riss, Stephan; Adler, Werner; Steven, Philipp; Hos, Deniz; Cursiefen, Claus (JAMA Ophthalmology, 2013)
EVALuna2:5415

Depletion of annexin A5, annexin A6, and collagen X causes no gross changes in matrix vesicle-mediated mineralization, but lack of collagen X affects hematopoiesis and the Th1/Th2 response - Grskovic, Ivan; Kutsch, Anna; Frie, Christian; Groma, Gergely; Stermann, Jacek; Schlötzer-Schrehardt, Ursula; Niehoff, Anja; Moss, Stephen E.; Rosenbaum, Sabrina; Poeschl, Ernst; Chmielewski, Markus; Rappl, Gunter; et al. (Journal of Bone and Mineral Research, 2012)
Numerous biochemical studies have pointed to an essential role of annexin A5 (AnxA5), annexin A6 (AnxA6), and collagen X in matrix vesicle-mediated biomineralization during endochondral ossification and in osteoarthritis. By binding to the extracellular matrix protein collagen X and matrix vesicles, annexins were proposed to anchor matrix vesicles in the extracellular space of hypertrophic chondrocytes to initiate the calcification of cartilage. However, mineralization appears to be normal in mice lacking AnxA5 and AnxA6, whereas collagen X-deficient mice show only subtle alterations in the growth plate organization. We hypothesized that the simultaneous lack of AnxA5, AnxA6, and collagen X in vivo induces more pronounced changes in the growth plate development and the initiation of mineralization. In this study, we generated and analyzed mice deficient for AnxA5, AnxA6, and collagen X. Surprisingly, mice were viable, fertile, and showed no obvious abnormalities. Assessment of growth plate development indicated that the hypertrophic zone was expanded in Col10a1(-/-) and AnxA5(-/-) AnxA6(-/-) Col10a1(-/-) newborns, whereas endochondral ossification and mineralization were not affected in 13-day- and 1-month-old mutants. In peripheral quantitative computed tomography, no changes in the degree of biomineralization were found in femora of 1-month- and 1-year-old mutants even though the diaphyseal circumference was reduced in Col10a1(-/-) and AnxA5(-/-) AnxA6(-/-) Col10a1(-/-) mice. The percentage of naive immature IgM(+) /IgM(+) B cells and peripheral T-helper cells were increased in Col10a1(-/-) and AnxA5(-/-) AnxA6(-/-) Col10a1(-/-) mutants, and activated splenic T cells isolated from Col10a1(-/-) mice secreted elevated levels of IL-4 and GM-CSF. Hence, collagen X is needed for hematopoiesis during endochondral ossification and for the immune response, but the interaction of annexin A5, annexin A6, and collagen X is not essential for physiological calcification of growth plate cartilage. Therefore, annexins and collagen X may rather fulfill functions in growth plate cartilage not directly linked to the mineralization process. © 2012 American Society for Bone and Mineral Research.
EVALuna2:21096

Diagnosis and therapy of pseudoexfoliation glaucoma - Jünemann, Anselm (Ophthalmologe, 2012)
Pseudoexfoliation (PEX) glaucoma is the most frequent and most important type of secondary glaucoma, accounting for approximately 25% of open angle glaucoma worldwide and currently representing the most common identifiable cause of glaucoma overall. Due to high intraocular pressure levels, marked diurnal pressure fluctuations and spikes, and rapid optic nerve damage and visual field loss, PEX glaucoma represents a relatively severe and progressive type of glaucoma. Therefore, hard and fast lowering of intraocular pressure is necessary. Fixed combinations in medical therapy and early glaucoma surgery are recommended. When considering a surgical procedure (e.g. selective laser trabeculoplasty, bleb-dependent or bleb-independent surgery) the timing of cataract surgery plays a major role. Pathogenesis, clinical characteristics and therapeutic aspects of PEX glaucoma are described in the following article.
EVALuna2:21092

Erratum to: Induction of initial steps of angiogenic differentiation and maturation of endothelial cells by pericytes in vitro and the role of collagen IV - Zhou, Zhigang; Pausch, Friederike; Schlötzer-Schrehardt, Ursula; Brachvogel, Bent; Poeschl, Ernst (Histochemistry and Cell Biology, 2016)
EVALuna2:21306

ER stress and basement membrane defects combine to cause glomerular and tubular renal disease resulting from Col4a1 mutations in mice - Jones, Frances E.; Bailey, Matthew A.; Murray, Lydia S.; Lu, Yinhui; Mcneilly, Sarah; Schlötzer-Schrehardt, Ursula; Lennon, Rachel; Sado, Yoshikazu; Brownstein, David G.; Mullins, John J.; Kadler, Karl E.; Van Agtmael, Tom (Disease Models & Mechanisms, 2016)
Collagen IV is a major component of basement membranes, and mutations in COL4A1, which encodes collagen IV alpha chain 1, cause a multisystemic disease encompassing cerebrovascular, eye and kidney defects. However, COL4A1 renal disease remains poorly characterized and its pathomolecular mechanisms are unknown. We show that Col4a1 mutations in mice cause hypotension and renal disease, including proteinuria and defects in Bowman's capsule and the glomerular basement membrane, indicating a role for Col4a1 in glomerular filtration. Impaired sodium reabsorption in the loop of Henle and distal nephron despite elevated aldosterone levels indicates that tubular defects contribute to the hypotension, highlighting a novel role for the basement membrane in vascular homeostasis by modulation of the tubular response to aldosterone. Col4a1 mutations also cause diabetes insipidus, whereby the tubular defects lead to polyuria associated with medullary atrophy and a subsequent reduction in the ability to upregulate aquaporin 2 and concentrate urine. Moreover, haematuria, haemorrhage and vascular basement membrane defects confirm an important vascular component. Interestingly, although structural and compositional basement membrane defects occurred in the glomerulus and Bowman's capsule, no tubular basement membrane defects were detected. By contrast, medullary atrophy was associated with chronic ER stress, providing evidence for cell-type-dependent molecular mechanisms of Col4a1 mutations. These data show that both basement membrane defects and ER stress contribute to Col4a1 renal disease, which has important implications for the development of treatment strategies for collagenopathies.
EVALuna2:21307

Generation of Reversible Immortalized Cell Lines to Model Pseudoexfoliation Syndrome - Luna, Coralia; Challa, Pratap; Schlötzer-Schrehardt, Ursula; Gonzalez, Pedro (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-10-29

Gene Signature-Based Development of ELISA Assays for Reproducible Qualification of Cultured Human Corneal Endothelial Cells - Ueno, Morio; Asada, Kazuko; Toda, Munetoyo; Schlötzer-Schrehardt, Ursula; Nagata, Kazue; Montoya, Monty; Sotozono, Chie; Kinoshita, Shigeru; Hamuro, Junji (Investigative Ophthalmology & Visual Science, 2016)
To develop a method to qualify the function of cultured human corneal endothelial cells (cHCECs) applicable for clinical settings.The diversified gene and microRNA (miRNA) signatures in HCECs from a variety of tissue donors were confirmed by three-dimensional (3D) gene human miRNA profiling. These were compared with those of more than 20 cHCECs distinct in their cell morphology or culture lots. Candidate genes were selected after quantitative (q)RT-PCR validation, and gene products were assayed by ELISA. After three additional screening steps, final candidate cytokines for qualification were selected.Gene and miRNA signatures among distinct cHCEC lots were greatly diversified compared with those among fresh tissues from different age donors. By comparing more than 20 lots of cultures, 32 candidate genes were assigned to be seemingly linked to distinct cHCEC morphologic features. The validation of candidate genes by qRT-PCR revealed the genes, either upregulated or downregulated, corresponding to morphologic variances in cHCECs (e.g., epithelial-mesenchymal transition or cell senescence). Further adding the ELISA results by Bio-Plex Human Cytokine 27-Plex Panel, 11 candidate cytokines suitable to qualify cHCEC function were selected. In consideration of the presence of these cytokines in the anterior chamber, IL-8, tissue inhibitors of metalloproteinases 1 (TIMP-1), monocyte chemotactic protein-1 (MCP-1), and platelet-derived growth factor-BB (PDGF-BB) were ultimately selected and applied in practice for the qualification of cHCECs actually used in our clinical cell-injection studies.The specified cytokines properly discriminating the functional features of cHCECs indicates a correlation between profiling signatures and cell morphology.
EVALuna2:21285

Genetics and genomics of pseudoexfoliation syndrome/glaucoma - Schlötzer-Schrehardt, Ursula (Middle East African Journal of Ophthalmology, 2011)
Pseudoexfoliation (PEX) syndrome, one of the most common causes of glaucoma, represents a complex, multifactorial, late-onset disease of worldwide significance. The etiopathogenesis involves both genetic and non-genetic factors. The PEX-specific tissue alterations are caused by a generalized fibrotic matrix process, which has been characterized as a stress-induced elastosis associated with the excessive production and abnormal cross-linking of elastic microfibrils into fibrillar PEX aggregates. The identification of lysyl oxidase-like 1 (LOXL1) as a major genetic risk factor for PEX syndrome and PEX glaucoma further supports a role of elastogenesis and elastosis in the pathophysiology of PEX, as LOXL1 is a pivotal cross-linking enzyme in elastic fiber formation and stabilization. The available data suggest that LOXL1 is markedly dysregulated depending on the stage of the fibrotic process. While transient upregulation of LOXL1 during the early stages of PEX fibrogenesis participates in the formation and aggregation of abnormal PEX fiber deposits, the decreased expression of LOXL1 during the advanced stages of the disease may affect elastin metabolism and promote elastotic processes, e.g. in the lamina cribrosa, predisposing to glaucoma development. However, in view of the low penetrance of the PEX-associated risk variants of LOXL1, other genetic and/or environmental factors must contribute to the risk of developing the PEX phenotype. Some evidence exists for the contribution of additional genes with relatively small effects, e.g. clusterin (CLU), contactin-associated protein-like 2 (CNTNAP2), apolipoprotein E (APOE), glutathione S-transferases (GSTs), and tumor necrosis factor-alpha (TNFA), in certain study populations. Several environmental conditions associated with PEX, such as oxidative stress as well as pro-fibrotic cytokines and growth factors, can regulate expression of LOXL1 and elastic proteins in vitro and may therefore act as co-modulating external factors. Ultimately, both detection and functional characterization of yet unidentified genetic and non-genetic factors may lead to the development of more precise screening tools for the risk of PEX glaucoma.
EVALuna2:21023

Histoacryl-Kleber zur Akutversorgung von Hornhautperforationen bei nekrotisierender herpetischer Keratitis - El Halabi, M.; Seitz, B.; Quintin, A.; Suffo, S.; Flockerzi, F.; Schlötzer-Schrehardt, Ursula; Daas, L. (Ophthalmologe, 2020)
CRIS-Team Scopus Importer:2020-12-25

HIV Nef, paxillin, and Pak1/2 regulate activation and secretion of TACE/ADAM10 proteases - Lee, Jung-Hyun; Wittki, Sebastian; Braeu, Tanja; Dreyer, Florian; Kraetzel, Kirsten; Dindorf, Jochen; Johnston, Ian C. D.; Gross, Stefanie; Kremmer, Elisabeth; Zeidler, Reinhard; Schlötzer-Schrehardt, Ursula; Lichtenheld, Mathias; et al. (Molecular Cell, 2013)
The HIV Nef protein recruits the polycomb protein Eed and mimics an integrin receptor signal for reasons that are not entirely clear. Here we demonstrate that Nef and Eed complex with the integrin effector paxillin to recruit and activate TNF? converting enzyme (TACE alias ADAM 17) and its close relative ADAM10. The activated proteases cleaved proTNF? and were shuttled into extracellular vesicles (EVs). Peripheral blood mononuclear cells that ingested these EVs released TNF?. Analyzing the mechanism, we found that Pak2, an established host cell effector of Nef, phosphorylated paxillin on Ser272/274 to induce TACE-paxillin association and shuttling into EVs via lipid rafts. Conversely, Pak1 phosphorylated paxillin on Ser258, which inhibited TACE association and lipid raft transfer. Interestingly, melanoma cells used an identical mechanism to shuttle predominantly ADAM10 into EVs. We conclude that HIV-1 and cancer cells exploit a paxillin/integrin-controlled mechanism to release TACE/ADAM10-containing vesicles, ensuring better proliferation/growth conditions in their microenvironment.
EVALuna2:12854

Induction of initial steps of angiogenic differentiation and maturation of endothelial cells by pericytes in vitro and the role of collagen IV - Zhou, Zhigang; Pausch, Friederike; Schlötzer-Schrehardt, Ursula; Brachvogel, Bent; Poeschl, Ernst (Histochemistry and Cell Biology, 2016)
Activation of endothelial cells and recruitment of mural cells define critical steps during the formation of stable vascular elements. Both events are reflected by cocultures of endothelial cells and isolated murine pericyte-like cells and define a versatile platform for the analysis of distinct steps during the angiogenic process in vitro. Isolated pericyte-like cells promote the survival of endothelial cells, induce the assembly of endothelial cells as well as establish direct contacts with forming endothelial alignments. More importantly, they also induce characteristic steps of maturation including the assembly of stable cell-cell junctions, deposition of basement membrane-like matrices and local formation of a central lumen. The presence of pericyte-like cells induces the secretion of extracellular matrices enriched in collagen IV by endothelial cells, which improves endothelial tube formation and provides the adhesive substrate for mural cell recruitment. Collagen-binding integrins contribute differentially to the process, with ?1?1 involved in the adhesion of pericyte-like cells to collagen IV and ?2?1 mainly involved in endothelial cord formation. These data indicate that pericyte-like cells are essential for the survival of endothelial cells, the efficient formation of endothelial alignments as well as initial steps of maturation of capillary-like structures.
EVALuna2:21323

Influence of mode of delivery on pre-existing eye diseases - Jünemann, Anselm; Sterk, N.; Rejdak, R. (Ophthalmologe, 2012)
Many ophthalmologists and obstetricians recommend either an assisted vaginal delivery with forceps or vacuum extraction, or a Caesarean section in cases of pre-existing eye diseases, such as myopia, retinal detachment, glaucoma or diabetic retinopathy. This is mainly based on the increase of intraocular pressure during the final stage of labor. These recommendations, however, are not evidence-based. None of the published trials have reported any retinal changes after vaginal delivery. This report provides information on the influence of physiological changes on eye diseases during the final stage of delivery. In general eye disease is not an indication for an instrumental or operative delivery provided regular eye examinations (once each trimester) have been performed.
EVALuna2:21064

Integrin: Basement membrane adhesion by corneal epithelial and endothelial cells - McKay, Tina B.; Schlötzer-Schrehardt, Ursula; Pal-Ghosh, Sonali; Stepp, Mary Ann (Experimental Eye Research, 2020)
Integrins mediate adhesion of cells to substrates and maintain tissue integrity by facilitating mechanotransduction between cells, the extracellular matrix, and gene expression in the nucleus. Changes in integrin expression in corneal epithelial cells and corneal endothelial cells impacts their adhesion to the epithelial basement membrane (EpBM) and Descemet's membrane, respectively. Integrins also play roles in assembly of basement membranes by both activating TGFβ1 and other growth factors. Over the past two decades, this knowledge has been translated into methods to grow corneal epithelial and endothelial cells in vitro for transplantation in the clinic thereby transforming clinical practice and quality of life for patients. Current knowledge on the expression and function of the integrins that mediate adhesion to the basement membrane expressed by corneal epithelial and endothelial cells in health and disease is summarized. This is the first review to discuss similarities and differences in the integrins expressed by both cell types.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Corneal endothelial cells; Corneal epithelial cells; Descemet's membrane; Epithelial basement membrane; Integrins

Isolation and enrichment of melanocytes from human corneal limbus using CD117 (c-Kit) as selection marker - Polisetti, Naresh; Schlötzer-Schrehardt, Ursula; Reinhard, Thomas; Schlunck, Günther (Scientific Reports, 2020)
Limbal melanocytes (LM) are located in the basal epithelial layer of the corneoscleral limbus and interact with adjacent limbal epithelial progenitor cells. The exploration of their biological role in the maintenance of the limbal stem cell niche has been limited by the difficulty of LM isolation and cultivation. Here, we report on a facile protocol for the efficient isolation and enrichment of pure populations of human LMs by fluorescence-activated cell sorting (FACS) using antibodies raised against the cell surface marker CD117 (c-Kit). The enriched LMs retain self-renewal capacity and sustained melanin production, and are suitable to study the potential of LMs in stem cell-based corneal tissue engineering.
CRIS-Team Scopus Importer:2020-10-23

Mechanisms, clinical profile and role of prostaglandin and prostamide analogues in antiglaucomatous therapy - Yu, A.; Welge-Lüssen, Ulrich-Christoph (Klinische Monatsblätter für Augenheilkunde, 2013)
Prostaglandin and prostamide analogues belong to a new substance group which came into the market in the 1990s. They have revolutionised antiglaucomatous therapy by their once-daily dosing regimen and fewer side effects. Today, prostaglandin and prostamide analogues are approved as first-line therapy for patients with primary open-angle glaucoma and ocular hypertension. They lower the intraocular pressure primarily by increasing the uveoscleral outflow. Recent investigations have shown that they also improve the trabecular outflow facility and thus the conventional outflow pathways. Prostaglandin and prostamide analogues are highly efficient in lowering the intraocular pressure, for which they are superior to other antiglaucomatous substance groups. In particular, they appear to have a good control of 24-hour intraocular pressure fluctuations by primarily improving the outflow pathways. Furthermore, they have less systemic side effects than ?-blockers. However, their use is often associated with higher costs. In case of undesirable events, they mostly present with ocular symptoms. Based on their good clinical profile, prostaglandin and prostamide analogues play an important role in the primary and additive therapy for glaucoma.
EVALuna2:21128

Mitochondrial respiratory chain function promotes extracellular matrix integrity in cartilage - Bubb, Kristina; Holzer, Tatjana; Nolte, Janica L.; Krüger, Marcus; Wilson, Richard; Schlötzer-Schrehardt, Ursula; Brinckmann, Jürgen; Altmüller, Janine; Aszodi, Attila; Fleischhauer, Lutz; Clausen-Schaumann, Hauke; Probst, Kristina; et al. (Journal of Biological Chemistry, 2021)
Energy metabolism and extracellular matrix (ECM) function together orchestrate and maintain tissue organization, but crosstalk between these processes is poorly understood. Here, we used single-cell RNA-Seq (scRNA-Seq) analysis to uncover the importance of the mitochondrial respiratory chain for ECM homeostasis in mature cartilage. This tissue produces large amounts of a specialized ECM to promote skeletal growth during development and maintain mobility throughout life. A combined approach of high-resolution scRNA-Seq, mass spectrometry/matrisome analysis, and atomic force microscopy was applied to mutant mice with cartilage-specific inactivation of respiratory chain function. This genetic inhibition in cartilage results in the expansion of a central area of 1-month-old mouse femur head cartilage, showing disorganized chondrocytes and increased deposition of ECM material. scRNA-Seq analysis identified a cell cluster–specific decrease in mitochondrial DNA–encoded respiratory chain genes and a unique regulation of ECM-related genes in nonarticular chondrocytes. These changes were associated with alterations in ECM composition, a shift in collagen/noncollagen protein content, and an increase of collagen crosslinking and ECM stiffness. These results demonstrate that mitochondrial respiratory chain dysfunction is a key factor that can promote ECM integrity and mechanostability in cartilage and presumably also in many other tissues.
CRIS-Team Scopus Importer:2021-10-22

New pathogenetic insights into pseudoexfoliation syndrome/glaucoma : Therapeutically relevant? - Schlötzer-Schrehardt, Ursula (Ophthalmologe, 2012)
Pseudoexfoliation (PEX) syndrome is a genetically determined, generalized disease of the extracellular matrix leading to the progressive deposition of an abnormal fibrillar material in various intraocular and extraocular tissues including the trabecular meshwork. It thus represents the most common identifiable cause of open-angle glaucoma and a leading cause of blindness worldwide. The PEX-specific fibrotic matrix process, a stress-induced elastosis, is characterized by an excessive production and abnormal cross-linking of elastic microfibrils into fibrillar PEX aggregates. Co-modulating factors triggering this fibrotic process include elevated concentrations of fibrogenic growth factors, such as TGF-?1, reduced activity of proteolytic enzymes, subtle inflammatory processes and various external stress factors, such as oxidative stress. Genetic studies identified a highly significant association between several polymorphisms in the LOXL1 (lysyl oxidase-like 1) gene with both PEX syndrome and PEX glaucoma. As these LOXL1 risk variants were found to occur in almost 100% of PEX patients throughout all geographical populations worldwide, LOXL1 appears to represent a principal risk factor for manifestation of the PEX phenotype. LOXL1 is a pivotal cross-linking enzyme in extracellular matrix metabolism and seems to be specifically required for elastic fiber formation and stabilization. The available data suggest that LOXL1 enzyme function and expression are dysregulated in PEX tissues and thereby play a central role in glaucoma development. On the one hand, increased expression of LOXL1 and elastic fiber components contributes to the formation of abnormally cross-linked PEX aggregates in the outflow pathways leading to increased outflow resistance and intraocular pressure. On the other hand, reduced expression and inadequate tissue levels of LOXL1 may lead to degenerative tissue alterations, particularly in the lamina cribrosa adversely affecting the biomechanical properties of this critical tissue. This PEX-specific elastinopathy of the lamina cribrosa rendering PEX eyes more vulnerable to pressure-induced optic nerve damage may constitute an independent risk factor for glaucoma development. The findings may have direct consequences for the clinical management of PEX patients underlining the need for an exact diagnosis, a strict IOP-reducing therapy and a close and regular follow-up.
EVALuna2:21099

OCT Diagnostics in Patients with Glaucoma: Tips & Tricks - Mardin, Christian (Augenheilkunde up2date, 2020)
CRIS-Team WoS Importer:2020-02-25

OCT-Diagnostik beim Glaukom: Tipps & Tricks - Mardin, Christian (Klinische Monatsblätter für Augenheilkunde, 2020)
High-resolution optical coherence tomography (OCT) with spectral-domain or swept-source techniques has become a mainstay in glaucoma and progression diagnosis. Imaging and morphometry of ganglion cell (GCL) and retinal nerve fiber (RNF) layer thickness and Bruch's membrane based minimum neuroretinal rim width (BMO-MRW) measurement allow the detection of pathologic changes. Graphic display of these measurements facilitate a comparison with normative data. False positive (red disease) and false negative (green disease) results represent pitfalls in OCT diagnosis. Pathologies of the posterior pole either caused by glaucoma or non-glaucoma associated changes of optic disc and retina play an important role. Epiretinal gliosis, age related macular degeneration and cystoid retinal changes cause measuring artefacts. A careful inspection of OCT B-scans is mandatory to detect these changes. Highly myopic eyes, underrepresented in normative databases cause changes resembling glaucoma and challenge the OCT glaucoma diagnosis. Neurological diseases present an important differential diagnosis when atrophy of neuroretinal tissue and ganglion cells occur. The location of the atrophy and the relationship of GCL, RNF and BMO-MRW changes may help in differential diagnosis. Sensory tests and imaging of the brain are mandatory in these cases. Drusen and disc edema cause thickening of BMO-MRW and may be followed by loss of RNF and GCL. Again a close observation of OCT B-scans and fundus may help to find the correct diagnosis. Good image quality, knowledge of OCT pathologies and technique of OCT imaging may help to avoid pitfalls in OCT glaucoma diagnosis.
CRIS-Team Scopus Importer:2020-05-22
Keywords: BMO-MRW; differential diagnosis; glaucoma; OCT; RNF

Ocular changes in nephropathic cystinosis: The course of the gold-dust - Flockerzi, Elias; Daas, Loay; Schlötzer-Schrehardt, Ursula; Zimpfer, Annette; Bohle, Rainer; Seitz, Berthold (International Ophthalmology, 2019)
PurposeCystinosis is an autosomal recessive inherited lysosomal storage disease with an incidence of 1:100.000 up to 1:200.000 caused by a gene mutation of a lysosomal transport protein resulting in deposition of cystine in lysosomes in all cells and tissues. In the cornea, crystalline, gold-dust deposition of cystine leads to visual impairment, recurrent erosions, photophobia, epiphora and blepharospasmus. Standard therapy is topical and systemic application of cysteamine which may resolve the accumulated cystine crystals.Patient and methodsThis is a case report of a thirty-one-year-old patient who already underwent renal transplantation because of nephropathic cystinosis. Visual impairment by cystine crystal deposition was aggravated by a central avascular pannus formation in his right eye. Penetrating keratoplasty was performed in intention to improve the patient's visual acuity and life quality.ResultsAfter penetrating keratoplasty in the right eye, there was only a slight visual improvement. OCT scans of the macula revealed intraretinal cystine crystals and a cystoid macular edema, which was treated with a bevacizumab injection. Transmission electron microscopy of the excised cornea revealed spiky intracorneal inclusions and confocal in vivo microscopy of the left eye allowed detailed visualization of the cystine crystal deposition.ConclusionsThere is a variability of ocular manifestations of nephropathic cystinosis. Ophthalmologists have a central role in the early diagnosis of cystinosis as mostly the first manifestation are cystine crystals in the cornea. Penetrating keratoplasty may be one of the therapeutical options. Nevertheless, the patient has to be informed about the limited prognosis because of the persisting underlying disease.
CRIS-Team WoS Importer:2019-06-18

Peripapillary Scleral Bowing Increases with Age and Is Inversely Associated with Peripapillary Choroidal Thickness in Healthy Eyes - Wang, Ya Xing; Yang, Hongli; Luo, Haomin; Hong, Seung Woo; Gardiner, Stuart K.; Jeoung, Jin Wook; Hardin, Christy; Sharpe, Glen P.; Nouri-Mahdavi, Kouros; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; et al. (American Journal of Ophthalmology, 2020)
Purpose: To use optical coherence tomography (OCT) to 3-dimensionally characterize the optic nerve head (ONH) in peripapillary scleral bowing in non-highly myopic healthy eyes. Design: Cross-sectional, multicenter study. Methods: A total of 362 non-highly myopic (+6 diopters [D] > spherical equivalent > −6D) eyes of 362 healthy subjects from 20-90 years old underwent OCT ONH radial B-scan imaging. Bruch's membrane (BM), BM opening (BMO), anterior scleral canal opening (ASCO), and the peripapillary scleral surface were segmented. BMO and ASCO planes were fit, and their centroids, major axes, ovality, areas and offsets were determined. Peripapillary scleral bowing was characterized by 2 parameters: peripapillary scleral slope (ppSS) of 3 anterior peripapillary scleral segments (0-300, 300-700, and 700-1,000 μm from the ASCO centroid); and ASCO depth relative to a peripapillary scleral reference plane (ASCOD-ppScleral). Peripapillary choroidal thickness (ppCT) was calculated relative to the ASCO as the minimum distance between the anterior scleral surface and BM. Results: Both ppSS and ASCOD-ppScleral ranged from slightly inward through profoundly outward in direction. Both parameters increased with age and were independently associated with decreased ppCT. Conclusions: In non-highly myopic healthy eyes, outward peripapillary scleral bowing achieved substantial levels, was markedly increased with age, and was independently associated with decreased peripapillary choroidal thickness. These findings provide a normative foundation for characterizing this anatomy in cases of high myopia and glaucoma and in eyes with optic disc tilt, torsion, and peripapillary atrophy.
CRIS-Team Scopus Importer:2020-06-23

PEX syndrome : Clinical diagnosis and systemic manifestations - Scharfenberg, E.; Schlötzer-Schrehardt, Ursula (Ophthalmologe, 2012)
As a result of demographic changes pseudoexfoliation (PEX) syndrome, an age-related systemic disorder of the extracellular matrix, will become an increasingly important issue in clinical practice. Apart from its well-known association with cataract and glaucoma, PEX syndrome predisposes to a broad spectrum of spontaneous and surgical ocular complications due to characteristic alterations of all anterior segment tissues. In view of the high risk of glaucoma development and potential complications during cataract surgery, an accurate and early diagnosis of PEX syndrome is of considerable clinical relevance. Since the characteristic central PEX deposits are lacking in up to 50 % of patients, a reliable diagnosis requires pupillary dilation. Early stages of the disease may be recognized on the basis of subtle alterations of the lens surface in addition to poor pupillary dilation and pigment-related signs including pigment dispersion and peripupillary atrophy. Any asymmetric clinical signs, e.g., regarding pupil width, pigmentation, cataract and intraocular pressure, should alert the ophthalmologist to the potential presence of PEX syndrome. Although the description of PEX syndrome as a systemic disorder of the extracellular matrix associated with the deposition of PEX material in the skin, blood vessel walls and various organ systems dates back to the early 1990s, a causal relationship between the abnormal material deposits and systemic diseases has not yet been clearly established. A growing number of smaller studies have found suggestive evidence for associations between PEX syndrome and cardiovascular/cerebrovascular diseases. The current evidence, however, is ambiguous and requires further investigation through multicenter or population-based, prospective, randomized clinical studies.
EVALuna2:21100

Pseudoexfoliation syndrome and glaucoma: from genes to disease mechanisms - Schlötzer-Schrehardt, Ursula; Khor, Chiea Chuen (Current Opinion in Ophthalmology, 2021)
Purpose of review The genetic basis of pseudoexfoliation (PEX) syndrome, the most common identifiable cause of open-angle glaucoma, is steadily being elucidated. This review summarizes the recent advances on genetic risk factors for PEX syndrome/glaucoma and their potential functional implications in PEX pathophysiology. Recent findings As of today, seven loci associated with the risk of PEX surpassing genome-wide significance have been identified by well-powered genome-wide association studies and sequencing efforts. LOXL1 (lysyl oxidase-like 1) represents the major genetic effect locus, although the biological role of common risk variants and their reversed effect in different ethnicities remain an unresolved problem. Rare protein-coding variants at LOXL1 and a single noncoding variant downstream of LOXL1 showed no allele effect reversal and suggested potential roles for elastin homeostasis and vitamin A metabolism in PEX pathogenesis. Other PEX-associated genetic variants provided biological insights into additional disease processes and pathways, including ubiquitin-proteasome function, calcium signaling, and lipid biosynthesis. Gene-environment interactions, epigenetic alterations, and integration of multiomics data have further contributed to our knowledge of the complex etiology underlying PEX syndrome and glaucoma. PEX-associated genes are beginning to reveal relevant biological pathways and processes involved in disease development. To understand the functional consequences and molecular mechanisms of these loci and to translate them into novel therapeutic approaches are the major challenges for the future.
CRIS-Team WoS Importer:2021-02-26

Pseudoexfoliation syndrome/glaucoma : Causes, consequences and management - Schlötzer-Schrehardt, Ursula; Naumann, Gottfried (Ophthalmologe, 2012)
EVALuna2:21098

Pseudoexfoliation syndrome: the puzzle continues - Schlötzer-Schrehardt, Ursula (Journal of Ophthalmic & Vision Research, 2012)
EVALuna2:21143

Relative Mikro- und Makropapillen – eine Herausforderung in der Glaukomdiagnostik mit der optischen Kohärenztomographie? - Mardin, Christian (Ophthalmologe, 2021)
Optical coherence tomography provides high-resolution imaging and measurement of glaucoma-relevant structures of the posterior pole. Minimal rim width, retinal nerve fiber layer, and ganglion cell layer thickness are parameters that enhance interpretation of micro- and macrodiscs in relation to a normative database. They are a valuable supplement to ophthalmoscopy and sensory testing in glaucoma diagnostics.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Ocular hypertension; Open-angle glaucoma; Ophthalmoscopy; Optic disc; Optic nerve diseases

Special topic "inflammations of the eye in inflammatory systemic diseases" - Heiligenhaus, A.; Cursiefen, Claus (Klinische Monatsblätter für Augenheilkunde, 2011)
EVALuna2:21054

TGF-β2- and H2O2-Induced Biological Changes in Optic Nerve Head Astrocytes Are Reduced by the Antioxidant Alpha-Lipoic Acid - Yu, Alice L.; Moriniere, Jerome; Welge-Lüssen, Ulrich-Christoph (Ophthalmic Research, 2012)
Background/Aims: The goal of the present study was to determine whether transforming growth factor-?(2) (TGF-?(2))- and oxidative stress-induced cellular changes in cultured human optic nerve head (ONH) astrocytes could be reduced by pretreatment with the antioxidant ?-lipoic acid (LA). Methods: Cultured ONH astrocytes were treated with 1.0 ng/ml TGF-?(2) for 24 h or 200 µM hydrogen peroxide (H(2)O(2)) for 1 h. Lipid peroxidation was measured by a decrease in cis-parinaric acid fluorescence. Additionally, cells were pretreated with different concentrations of LA before TGF-?(2) or H(2)O(2) exposure. Expressions of the heat shock protein (Hsp) ?B-crystallin and Hsp27, the extracellular matrix (ECM) component fibronectin and the ECM-modulating protein connective tissue growth factor (CTGF) were examined with immunohistochemistry and real-time PCR analysis. Results: Both TGF-?(2) and H(2)O(2) increased lipid peroxidation. Treatment of astrocytes with TGF-?(2) and H(2)O(2) upregulated the expression of ?B-crystallin, Hsp27, fibronectin and CTGF. Pretreatment with different concentrations of LA reduced the TGF-?(2)- and H(2)O(2)-stimulated gene expressions. Conclusion: We showed that TGF-?(2)- and H(2)O(2)-stimulated gene expressions could be prevented by pretreatment with the antioxidant LA in cultured human ONH astrocytes. Therefore, it is tempting to speculate that the use of antioxidants could have protective effects in glaucomatous optic neuropathy.
EVALuna2:21103

The Different Binding Properties of Cultured Human Corneal Endothelial Cell Subpopulations to Descemet's Membrane Components - Toda, Munetoyo; Ueno, Morio; Yamada, Jun; Hiraga, Asako; Tanaka, Hiroshi; Schlötzer-Schrehardt, Ursula; Sotozono, Chie; Kinoshita, Shigeru; Hamuro, Junji (Investigative Ophthalmology & Visual Science, 2016)
To clarify the adherent properties of cultured human corneal endothelial cell (cHCEC) subpopulations (SPs).Each SP was prepared by controlling the culture conditions or by using magnetic cell separation, and then confirmed by staining with several cell-surface markers. Binding abilities of HCEC SPs were examined by adding the cells to culture plates immobilized with collagens, laminins, or proteoglycans, and then centrifuging the plates. Adhered cells were then evaluated by phase-contrast microscopy.The cHCECs were bound to laminin-511, laminin-411, and Type-IV collagen in a concentration-dependent manner, yet weakly bound to Perlecan, Agrin, and TSP-1. Comparison of the influence of cell-suspension vehicles on cHCEC attachment showed that cells suspended in Opti-MEM-I or Opeguard-MA were bound to laminin, yet no binding was observed in cells suspended in BSS-Plus. Next, we compared the adherent properties of HCEC SPs. Both the fully differentiated, mature cHCEC SP and the epithelial-to-mesenchymal-transitioned (EMT)-phenotype SP were found to attach to laminin- or collagen-coated plates. Interestingly, the binding properties to laminins differed among those SPs. Although the level of cells adhered to the laminin-411-coated plate was the same among the cHCEC SPs, the fully differentiated, mature cHCEC SP was significantly more tightly bound to laminin-511 than was the EMT-phenotype SP.The findings of this study suggest that the binding ability of cHCECs to major Descemet's membrane components is distinct among cHCEC SPs, and that Opti-MEM-I and Opeguard-MA are useful cell-suspension vehicles for cell-injection therapy.
EVALuna2:21304

Transcorneal freezing and topical Rho-kinase inhibitor treatment in Fuchs endothelial corneal dystrophy - Menzel-Severing, Johannes; Schrader, Stefan; Schlötzer-Schrehardt, Ursula; Geerling, Gerd (Eye, 2021)
CRIS-Team Scopus Importer:2021-11-19

Transgenic lysyl oxidase homolog 1 overexpression in the mouse eye results in the formation and release of protein aggregates - Zadravec, Patrick; Braunger, Barbara M.; Melzer, Benjamin; Kroeber, Markus; Boesl, Michael R.; Jaegle, Herbert; Schlötzer-Schrehardt, Ursula; Tamm, Ernst R. (Experimental Eye Research, 2019)
Sequence variants in LOXL1 coding for the secreted enzyme lysyl oxidase homolog 1 (LOXL1) associate with pseudoexfoliation (PEX) syndrome, a condition that is characterized by the deposition of extracellular fibrillar PEX material in the anterior eye and other parts of the body. Since the specific role of LOXL1 in the pathogenesis of PEX is unclear, and an increase in its expression was reported for early stages of PEX syndrome, we generated and studied transgenic mice with ocular overexpression of its mouse ortholog Loxl1. The chicken beta B1-crystallin promoter was used to overexpress Loxl1 in the lenses of beta B1-crystallin-Loxll transgenic mice. Transgenic lenses contained high levels of the protein LOXL1 and its mRNA, which were both not detectable in lenses of wildtype littermates. In wildtype mice, immunoreactivity for LOXL1 was mainly seen extracellularly in region of the ciliary zonules. beta B1-crystallin-Loxl1 littermates showed an additional diffuse immunostaining in lens fibers and capsule, and in the inner limiting membrane and retina indicating secretion of soluble LOXL1 from transgenic lenses. In addition, lens fibers of transgenic animals contained multiple distinct spots of very intense LOXL1 immunoreactivity. By transmission electron microscopy, those spots correlated with electron-dense round or oval bodies of 20-50 nm in diameter which were localized in the rough endoplasmic reticulum and not seen in wildtype lenses. Immunogold electron microscopy confirmed that the electron-dense bodies contained LOXL1 indicating aggregation of insoluble LOXL1. Similar structures were seen in the extracellular lens capsule suggesting their secretion from lens fibers. Otherwise, no changes were seen between the eyes of beta B1-crystallin-Loxl1 mice and their wildtype littermates, neither by light microscopy and funduscopy of whole eyes, nor by scanning and quantitative transmission electron microscopy of ciliary epithelium and zonules. At one month of age, intraocular pressure was significantly higher in transgenic mice than in wildtype littermates. No differences in IOP were seen though at 2-5 months of age. We conclude that LOXL1 has a strong tendency to aggregate in the rER when expressed in vivo at high amounts. A similar scenario, involving intracellular aggregation of LOXL1 and secretion of LOXL1 aggregates into the extracellular space, may be involved in the early pathogenetic events in eyes of PEX patients.
CRIS-Team WoS Importer:2019-03-06

Transient expression of Wnt5a elicits ocular features of pseudoexfoliation syndrome in mice - Yuan, Yong; Schlötzer-Schrehardt, Ursula; Ritch, Robert; Call, Mindy; Chu, Fred B.; Dong, Fei; Rice, Taylor; Zhang, Jianhua; Kao, Winston W. -Y. (PLoS ONE, 2019)
Purpose
CRIS-Team WoS Importer:2019-03-20

Treatment of dry eye disease - Jacobi, Christina (ACTA OPHTHALMOLOGICA, 2019)
CRIS-Team WoS Importer:2020-08-07

Ultrastructural findings in graft failure after Descemet membrane endothelial keratoplasty (DMEK) and new triple procedure - Schmidt, Isabell; Schlötzer-Schrehardt, Ursula; Langenbucher, Achim; Eppig, Timo; Hager, Tobias; Zimpfer, Annette; Seitz, Berthold (Medicine, 2019)
To investigate factors that influence graft failure after Descemet membrane endothelial keratoplasty (DMEK) based on transmission electron microscopy results.Retrospective observational case series.This single center study included 16 eyes of 16 patients with penetrating keratoplasty (n = 14) or repeat DMEK (n = 2) following graft failure after DMEK. The main outcome measures were ultrastructural changes in the explanted graft on transmission electron microscopy, best-corrected visual acuity, and central corneal thickness.The mean preoperative and postoperative best-corrected visual acuity was 1.01 ± 0.54 logMAR and 0.56 ± 0.37 logMAR. The mean central corneal preoperative and postoperative thickness was 667 ± 187 μm and 511 ± 42 μm. Visual acuity and central corneal thickness improved significantly (P = .001/P = .003) after repeat surgery. Electron microscopy showed that 3 of 14 corneas showed upside down transplantation, and 3 corneas had pigmented cells or pigment granules at the Descemet-stroma interface. Further, 9 of 16 specimens showed a posterior collagenous layer deposited onto the Descemet membrane (average thickness 5.1 ± 6.2 μm; ranged 0.65-20 μm); this did not correlate significantly with the time between the original and repeat keratoplasty. Of 16 original grafts, 7 showed ultrastructural anomalies of the Descemet membrane, but one excised cornea showed no Descemet membrane pathologies.The majority of eyes with graft failure after DMEK showed ultrastructural changes in the Descemet membrane. It is crucial to assess donor tissue quality and to conduct graft marking before surgery to avoid immediate or delayed graft failure after DMEK. Nevertheless, repeat keratoplasty provided significant improvement in central corneal thickness and visual acuity.
CRIS-Team Scopus Importer:2019-06-04

Wenn Tränenersatzmittel nicht mehr ausreichen: die Bedeutung von Entzündungsprozessen beim Trockenen Auge. Praktische Aspekte einer antientzündlichen Therapie des Trockenen Auges - Pleyer, Uwe; Geerling, Gerd; Schrader, Stefan; Jacobi, Christina; Kimmich, Friedemann; Messmer, Elisabeth (Klinische Monatsblätter für Augenheilkunde, 2020)
Dry eye disease (DED) is a heterogenous disease of the ocular surface. Multiple pathogenetic factors are responsible for the disease process, but DED is generally linked to an increase in the osmolarity of the tear film and to inflammation of the ocular surface. The significance of inflammatory processes in DED is highlighted in the most recent definition of dry eye in the Dry Eye Workshop (DEWS). It is therefore critically important for the management of dry eye disease to understand the pathomechanisms and therapeutic options for the treatment of inflammatory processes. This review summarizes our current knowledge on Inflammation associated with DED and provides practical recommendations for the diagnosis and monitoring of the disease, as well as the use of currently available therapeutic options to counteract inflammation in DED.
CRIS-Team Scopus Importer:2020-06-02
Keywords: ciclosporine A; corticosteroids; dry eye; inflammation

WT1-dependent sulfatase expression maintains the normal glomerular filtration barrier - Schumacher, Valerie A.; Schlötzer-Schrehardt, Ursula; Karumanchi, S. Ananth; Shi, Xiaofeng; Zaia, Joseph; Jeruschke, Stefanie; Zhang, Dongsheng; Pavenstaedt, Hermann; Drenckhan, Astrid; Amann, Kerstin Ute; Ng, Carrie; Hartwig, Sunny; et al. (Journal of the American Society of Nephrology, 2011)
Paracrine signaling between podocytes and glomerular endothelial cells through vascular endothelial growth factor A (VEGFA) maintains a functional glomerular filtration barrier. Heparan sulfate proteoglycans (HSPGs), located on the cell surface or in the extracellular matrix, bind signaling molecules such as VEGFA and affect their local concentrations, but whether modulation of these moieties promotes normal crosstalk between podocytes and endothelial cells is unknown. Here, we found that the transcription factor Wilms' Tumor 1 (WT1) modulates VEGFA and FGF2 signaling by increasing the expression of the 6-O-endosulfatases Sulf1 and Sulf2, which remodel the heparan sulfate 6-O-sulfation pattern in the extracellular matrix. Mice deficient in both Sulf1 and Sulf2 developed age-dependent proteinuria as a result of ultrastructural abnormalities in podocytes and endothelial cells, a phenotype similar to that observed in children with WT1 mutations and in Wt1(+/-) mice. These kidney defects associated with a decreased distribution of VEGFA in the glomerular basement membrane and on endothelial cells. Collectively, these data suggest that WT1-dependent sulfatase expression plays a critical role in maintaining the glomerular filtration barrier by modulating the bioavailability of growth factors, thereby promoting normal crosstalk between podocytes and endothelial cell
EVALuna2:21045

Zoledronate-induced panuveitis - Bergua, A.; Hohberger, B. (Ophthalmologe, 2017)
Zoledronate-induced (Aclasta®) uveitis is a rare iatrogen-induced inflammation of ocular structures, which can result in substantial morphological and functional limitations. This case report describes the clinical course of a female patient with zoledronate-induced panuveitis. Additionally, the diagnostic procedure, therapy and follow-up are presented.
EVALuna2:21354